Calcite growth in Cissus quadrangularis plant extract, a traditional Indian bone-healing aid - Sanyal, A.; Ahmad, Absar; Sastry, M. (Current Science, 2005)
Cissus quadrangularis, a plant that has been customarily used in the Indian subcontinent to hasten the process of healing in bone fractures, has been studied and exploited to synthesize calcite crystals. The plant extract serves as a rich source of calcium ions, which when reacted with CO2, leads to the formation of calcite crystals of highly irregular morphology indicating that bioorganic molecules present in the extract modulate the crystal morphology.
Keywords: bone fracture; calcite crystals; Cissus quadrangularis; traditional healing

Carbohydrate-based approach for the total synthesis of 1,3-polyol/alpha-pyrone antifungal natural products - Ramana, Chepuri V.; Srinivas, B.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Organic Chemistry, 2005)
An elimination and stereoselective hydrogenation of alpha-D-glucoheptonic-gamma-lactone derivative has been applied to prepare a differentially protected anti,anti-1,3,5-triol system, the utility of which has been extended for the total synthesis of anti-fungal 1,3-polyol/alpha-pyrone natural products.

Carbohydrate-based approach for the total synthesis of strictifolione - Ramana, C. V.; Raghupathi, N.; Gurjar, M. K.; Chorghade, Mukund S. (Tetrahedron Letters, 2005)
A chiral pool approach starting with D-glucose, using the Yamaguchi protocol and a Z-selective HWE reaction followed by lactonization, has been applied to execute the total synthesis of strictifolione. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: D-Glucose; double elimination; Horner-Wadsworth-Emmons reaction; lactonization; strictifolione; Yamaguchi protocol

Carbon-free dry reforming of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Mamman, Ajit Singh; Joshi, Upendra A. (Catalysis Letters, 2005)
CoNdOx (Co/Nd = 1) is a highly promising catalyst for the carbon-free CO2 reforming of methane. Influence of the Co/Nd ratio on the catalyst performance in the CO2 reforming and also on the crystalline phases and reduction by temperature programmed reduction (TPR) of the CoNdOx catalyst has also been investigated. The CoNdOx (CoNd = 1.0) catalyst consisted of mainly NdCoO3 perovskite- type mixed metal oxide and it showed not only a high resistance to carbon formation at different process conditions ( viz. temperature = 750 - 900 degrees C and gas hourly space velocity (GHSV) = 10000 - 50000 cm(3) g(-1) h(-1)) but also high activity and selectivity in the CO2 reforming process. The high resistance to carbon formation for this catalyst is attributed mostly to strong metal (Co degrees) - support (Nd2O3) interactions.
Keywords: CO2 reforming of methane to syngas; CoNdOx catalyst; NdCoO3 perovskite; resistance to carbon formation in CO2 reforming

Carbonylation of alkynes, alkenes and alcohols using metal complex catalysts - Sarkar, B. R.; Chaudhari, Raghunath V. (Catalysis Surveys from Asia, 2005)
Carbonylation of olefins, alcohols and halides using homogeneous as well as heterogeneous catalysts has been discussed. Highlights of contributions on the activity, selectivity and stability of catalysts for carbonylation reactions are discussed. Kinetics and mechanism including characterization of the intermediate catalytic species has also been reviewed. The performance of anchored Pd complexes on mesoporous supports (MCM-41 and MCM-48), water soluble Pd complexes and supported Pd catalysts in carbonylation of aryl alcohols and olefins has been discussed in the context of catalyst-product separation. Some aspects of kinetic modelling and reaction engineering of these multiphase catalytic reactions have also been reviewed.
Keywords: Carbonylation; catalysis; Heterogenization; homogeneous; Palladium

Cataloguing Indian biota - Response - Chavan, V.; Watve, A. V.; Rane, N. S.; Krishnan, S. (Current Science, 2005)

Catalytic transesterification of beta-ketoesters with zeolite H-FER under solvent free conditions - Chavan, Subhash P.; Pasupathy, K.; Shengule, S.; Shinde, V.; Anand, R. (Arkivoc, 2005)
Zeolite H-FER catalyzes the transesterification of beta-ketoesters with variety of alcohols under solvent-less condition in excellent yields. The catalyst can be reused without any loss of activity.
Keywords: ferrierite; transesterification; zeolite

Catalyzing Henry reactions in chloroaluminate ionic liquids - Kumar, Anil; Pawar, Sanjay S. (Journal of Molecular Catalysis A - Chemical, 2005)
Henry reactions can be accelerated in chloroaluminate room temperature ionic liquids. The choloroaluminates with higher compositions of organic species of the chloroaluminates prove to be more efficient rate promoters than the ones with lower organic species in catalyzing Henry reactions. involving both aliphatic and aromatic carbonyl compounds. The ionic liquids can be recycled five times to offer good yields. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chloroaluminates; Henry reactions; ionic liquids; Recycling

Characterization of barium titanate: BaTiO3 (BT) ceramics prepared from sol-gel derived BT powders - Deshpande, S. B.; Godbole, P. D.; Khollam, Y. B.; Potdar, H. S. (Journal of Electroceramics, 2005)
Sol-gel synthesis was attempted at room temperature by adding drop wise a clear solution (made by reacting BaCO3 with glacial acetic acid) to an equi-molar solution of titanium tetrabutoxide in isopropanol (IPA) and acetic acid. The gelation occurred within 30 minutes. The as-dried gel was calcined at 750 degrees C/6 h in air to obtain carbon free BaTiO3 powders. The resulting BT powders were further pressed into pellets and sintered at 1280 degrees C/4 h in air to get dense ceramics (density similar to 94%). XRD and SEM techniques were used for phase and microstructure analysis respectively. The room temperature relative permittivity (e) of 1280 increased to 7200 (at Curie temperature of 127 degrees C) at 1 kHz frequency. The dissipation factor (tan delta) similar to 1.6% was observed in these samples. Also, the ferroelectric properties such as spontaneous polarization (Ps similar to 13 mu C/cm(2)), coercive field (E-c similar to 4.0 kV/cm) and dielectric strength (similar to 34 kV/cm) are estimated for these samples. These performance parameters are compared with the available standard data from the literature.
Keywords: barium titanate; ferroelectricity; Microstructure; relative permittivity; sol-gel processing

Characterization of gas-liquid flows in rectangular bubble columns using conductivity probes - Buwa, Vivek V.; Ranade, Vivek V. (Chemical Engineering Communications, 2005)
Unsteady gas-liquid flows in bubble columns are comprised of various flow processes occurring with varying length and time scales and govern mixing and transport processes. In the present work, we have characterized dynamic and time-averaged properties of gas-liquid flows in rectangular bubble columns using conductivity probes. The development of a single-tip conductivity probe, data processing methodology, and photographic validation procedure is discussed in detail. The effect of superficial gas velocity and aerated liquid height-to-width ( H/W) ratio on voidage fluctuations and time-averaged gas holdup was investigated. The experimental data presented here can help in understanding the dynamics of various flow processes and validating computational fluid dynamics based models.
Keywords: Bubble column; gas holdup; gas-liquid flows; voidage fluctuations

Characterization of gas-liquid flows in stirred vessels using pressure and torque fluctuations - Khopkar, A. R.; Panaskar, S. S.; Pandit, A. B.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2005)
Gas-liquid flows in a stirred vessel exhibit different flow regimes and demonstrate complex interaction of transport processes with varying spatio-temporal scales. The knowledge of key space and time scales of fluid dynamics is important for designing and enhancing the performance of gas-liquid stirred reactor. The present study uses simple, robust, and nonintrusive experimental techniques (torque and pressure sensors) to characterize the fluid dynamics in a gas-liquid stirred vessel. Time series obtained from the pressure and torque sensors were analyzed to develop criteria for flow regime identification. Further analyses of torque and pressure time series were done to extract valuable information of different time scales of fluid dynamics. The detailed analysis of torque and wall pressure fluctuations provided not only an insight into the fluid dynamics but also a possible opportunity to on-line monitoring of gas-liquid flows in stirred vessel.

Characterization of nanocrystalline anatase titania: an in situ HTXRD study - Jagtap, Neelam; Bhagwat, Mahesh; Awati, Preeti; Ramaswamy, Veda (Thermochimica Acta, 2005)
Nanocrystalline titania was synthesized by the hydrolysis of titanium iso-propoxide using ultrasonication. The powder XRD patterns of the sample were recorded in static air and vacuum using a Philips X-pert Pro diffractometer equipped with a high-temperature attachment (HTK16) from room temperature (298 K) to 1173 K and were analyzed by the Rietveld refinement technique. The anatase to rutile phase transformation was observed at 1173 K for the data collected in static air. Only 3% of anatase titania transformed to rutile when the experiments were carried out at H 73 K in vacuum. The phase transformation from anatase to rutile is accompanied by a continuous increase in the crystallite size of the anatase phase from 9 nm at room temperature to 28 nm at 873 K and then to 50 nm at 1173 K in air while the process of crystallite growth was suppressed in vacuum. A linear increase in the unit cell parameters `a' and `c', and thus, an overall linear increase in the unit cell volume was observed as a function of temperature in static air as well as vacuum. The lattice and volume thermal expansion coefficients (TEC), alpha(a), alpha(c), and alpha(v) at 873 K are 8.57 x 10(-6), 8.71 x 10(-6) and 25.91 x 10(-6) K-1 in air and 18.01 x 10(-6), 14.95 x 10(-6) and 51.13 x 10(-6) K-1 in vacuum, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Anatase; HTXRD; Rietveld refinement; rutile; thermal expansion coefficient; titania

Characterization of two midgut proteinases of helicoverpa armigera and their interaction with proteinase inhibitors - Telang, M. A.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Journal of Insect Physiology, 2005)
Two serine proteinases from the midgut of Helicoverpa armigera have been partially purified and characterized. One proteinase, HGP-1, was capable of hydrolyzing a synthetic substrate of elastase and was inhibited by elastatinal. The second proteinase, HGP-2, was inhibited by a trypsin inhibitor. Molecular weights of HGP-1 and HGP-2 were approximately 26.0 and 29.0 kDa, respectively. Both the proteinases exhibited alkaline pH optima in the range of 10-11. Furthermore, interaction of HGP-1 and HGP-2 with proteinase inhibitors (PIs) from host and non-host plants was studied. HGP-1 was not only insensitive to a PI from chickpea (host) but was also able to degrade it. The same PI from chickpea was able to inhibit over 50% activity of HGP-2. On the contrary, PIs from potato (non-host) showed strong inhibition of both, HGP-1 and HGP-2 and also demonstrated protection of chickpea seed proteins from digestion by both the HGPs. These results could provide important clues in designing strategies for sustainable use of plant PIs in developing insect-tolerant transgenic plants. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: elastase; Helicoverpa armigera gut proteinases; insect-resistant plants; plant proteinase inhibitors

Chelation controlled regiospecific O-substitution of myo-inositol orthoesters: convenient access to orthogonally protected myo-inositol derivatives - Devaraj, Subramanian; Shashidhar, M. S.; Dixit, Shailesh S. (Tetrahedron, 2005)
A general method for the completely regioselective protection of the three secondary hydroxyl groups of orthoester derivatives of myo-mositol, utilizing the subtle differences in reactivity exhibited by its alkali metal alkoxides due to differences in their ability to form chelates, is described. This method provides convenient access to orthogonally protected myo-inositol derivatives. A comparison of the methylation of racemic 4-0-trityl-myo-inositol 1,3,5-orthoformate in the presence of sodium or lithium ions showed that stabilization of the C4-alkoxide by chelation with lithium overrides steric hindrance offered by the C6-axial substituent in deciding the regioselectivity during the nucleophilic O-substitution. (C) 2004 Elsevier Ltd. All rights reserved.

Chiral 2-C-methylene glycosides and carbohydrate-derived pyrano[2,3-b][1]benzopyrans: synthesis via InCl3 catalyzed stereoselective ferrier rearrangement of 2-C-acetoxymethyl glycal derivatives - Ghosh, R.; Chakraborty, A.; Maiti, D. K.; Puranik, Vedavati G. (Tetrahedron Letters, 2005)
2-C-Acetoxymethyl glycal derivatives react with aliphatic alcohols in the presence of InCl3 (30 mol %) to furnish the corresponding 2-C-methylene glycosides in excellent yields and with exclusive alpha-selectivity except for the methyl 2-C-methylene glycosides, which are formed in similar to 2:1 anomeric ratio in favour of the alpha-anomer. The reaction of 2-C-acetoxyglycals with phenols, however, produces the corresponding chiral carbohydrate-derived pyranobenzopyran derivatives via initial Ferrier rearrangement followed by tandem cyclization in excellent yields and moderate to high stereoselectivities in favour of the corresponding 10a-R-pyrano[2,3-b][1]benzopyran derivatives. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 2-C-methylene glycoside; InCl3; pyranobenzopyran; Stereoselective

Cloning, preparation and preliminary crystallographic studies of penicillin V acylase autoproteolytic processing mutants - Chandra, P. M.; Brannigan, James A.; Prabhune, Asmita; Pundle, A.; Turkenburg, J. P.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Cloning, purification, crystallization and preliminary structural studies of penicillin V acylase from Bacillus subtilis - Rathinaswamy, P.; Pundle, A. V.; Prabhune, Asmita; SivaRaman, H.; Brannigan, James A.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology Communications, 2005)
{Penicillin acylase proteins are amidohydrolase enzymes that cleave penicillins at the amide bond connecting the side chain to their beta-lactam nucleus. An unannotated protein from Bacillus subtilis has been expressed in Escherichia coli, purified and confirmed to possess penicillin V acylase activity. The protein was crystallized using the hanging-drop vapour-diffusion method from a solution containing 4 M sodium formate in 100 mM Tris-HCl buffer pH 8.2. Diffraction data were collected under cryogenic conditions to a spacing of 2.5 A. The crystals belonged to the orthorhombic space group C222(1), with unit-cell parameters a = 111.0

CO2 activation and synthesis of cyclic carbonates and alkyl/aryl carbamates over adenine-modified Ti-SBA-15 solid catalysts - Srivastava, R; Srinivas, D; Ratnasamy, P (Journal of Catalysis, 2005)
Cyclic carbonates were synthesized by the cycloaddition Of CO2 to epoxides (epichlorohydrin, propene oxide, and styrene oxide), and carbamates were synthesized by reaction of alkyl or aryl amines, CO2, and n-butyl bromide. Solvents and cocatalysts/promoters, like N,N-dimethylaminopyridine (DMAP) and quaternary ammonium salts, which are usually essential with conventional catalyst systems, could be avoided with the use of adenine-modi lied Ti-SBA-15 catalysts. The catalysts were reused in several recycle experiments. The structural and textural properties of the catalysts were determined by X-ray diffraction (XRD), transmission electron microscopy (TEM), N-2 adsorption, and Fourier transform infrared (FTIR) and diffuse reflectance ultraviolet-visible (UV-vis DRS) techniques. Acid-base properties of the solid catalysts were investigated by temperature-programmed desorption (TPD) of NH3 and CO2 and DRIFTIR spectroscopy of adsorbed pyridine and CO2 techniques. The studies reveal that the Ti4+ ions increase catalytic activity by enhancing the adsorption of the epoxide and alkyl or aryl amine substrates. CO2 molecules are activated at the basic nitrogen groups of adenine. Increasing the surface concentrations of either CO2 (by anchoring basic molecules like adenine or increasing the partial pressure of CO2) or epoxides and alkyl or aryl amines (by increasing the concentration of Lewis acidic Ti4+ ions) enhances the catalytic activity. CO2 molecules activated at the covalently anchored adenine sites react with epoxide/amines adsorbed on the silica surface to form carbonates/carbamates. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: activation of CO2; CO2 fixation; DRIFTIR spectroscopy of adsorbed pyridine and CO2; organo-functionalized mesoporous silica; phosgene-free synthesis; synthesis of carbamates; synthesis of cyclic carbonates; temperature-programmed desorption of NH3 and CO2 titanosilicates; Ti-SBA-15

Cobalt and magnesium ferrite nanoparticles: preparation using liquid foams as templates and their magnetic characteristics - Bala, Tanushree; Sankar, C. R.; Baidakova, Marina; Osipov, V.; Enoki, Toshiaki; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Langmuir, 2005)
An easy and convenient method for the synthesis of cobalt and magnesium ferrite nanoparticles is demonstrated using liquid foams as templates. The foam is formed from an aqueous mixture of an anionic surfactant and the desired metal ions, where the metal ions are electrostatically entrapped by the surfactant at the thin borders between the foam bubbles and their junctions. The hydrolysis is carried out using alkali resulting in the formation of desired nanoparticles, with the foam playing the role of a template. However, in the formation of ferrites with the formula MFe2O4, where the metal ion and iron possess oxidation states of +2 and +3, respectively, forming a foam from a 1:2 mixture of the desired ionic solutions would lead to a foam composition at variance with the original solution mixture because of greater electrostatic binding of ions possessing a greater charge with the surfactant. In our procedure, we circumvent this problem by preparing the foam from a 1:2 mixture of M2+ and Fe2+ ions and then utilizing the in situ conversion of Fe2+ to Fe3+ under basic conditions inside the foam matrix to get the desired composition of the metal ions with the required oxidation states. The fact that we could prepare both CoFe2O4 and MgFe2O4 particles shows the vast scope of this method for making even multicomponent oxides. The magnetic nanoparticles thus obtained exhibit a good crystalline nature and are characterized by superparamagnetic properties. The magnetic features observed for CoFe2O4 and MgFe2O4 nanoparticles are well in accordance with the expected behaviors, with CoFe2O4 particles showing higher blocking temperatures and larger coercivities. These features can easily be explained by the contribution of Co2+ sites to the magnetocrystalline anisotropy and the absence of the same from the Mg2+ ions.

Comment on ``Prediction of viscosity of mixed electrolyte solutions based on the Eyring's absolute rate theory and the equations of Patwardhan and Kumar by Y.-F. Hu'' (Chemical Engineering Science 2003,59,2457-2464) - Kumar, Anil (Chemical Engineering Science, 2005)

Comparison of the pervaporation separation of a water-acetonitrile mixture with zeolite-filled sodium alginate and poly(vinyl alcohol)-polyaniline semi-interpenetrating polymer network membranes - Naidu, B. V. K.; Bhat, S. D.; Sairam, M.; Wali, A. C.; Sawant, D. P.; Halligudi, Shivaraj B.; Mallikarjuna, N. N.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The pervaporation (PV) separation performance of ZSM-5- and Na-Y-type zeolite-filled sodium alginate (NaAlg) membranes were compared with those of pure NaAlg and semi-interpenetrating polymer network (semi-IPN) membranes of poly(vinyl alcohol) (PVA) with polyaniline (PANI) for the dehydration of acetonitrile. The PV separation characteristics of the zeolite-filled membranes showed a dependence on the nature of the zeolites. The variation of the acidity function of the ZSM-5 zeolite had an influence on the flux and selectivity of the membranes when compared to unfilled membranes. The crosslinked membranes were characterized by differential scanning calorimetry, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Increasing the PANI content of the semi-IPN network increased the separation selectivity. Among the NaAlg membranes, the plain NaAlg membrane showed the highest selectivity of 414 at 30 mass % water in the feed mixture, whereas the Na-Y- and ZSM-5 (40)-filled NaAlg membranes exhibited much lower values of selectivity, that is, 7.3 and 4.3, respectively for 30 mass % water in the feed. When the flux and selectivity data of ZSM-5 (250)-filled NaAlg membranes were compared with that of Na-Y- or ZSM-5 (40)-filled NaAlg membranes, a noticeable increase in the selectivity for the ZSM-5 (250)filled NaAlg membrane was observed, but a somewhat comparable flux was observed compared to the plain NaAlg membrane. For the first time, PANI was polymerized with PVA to yield a semi-IPN. The total flux and water flux increased systematically, whereas the selectivity decreased greatly from 251.87 to 5.95 with increasing amounts of water in the feed. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; interpenetrating network (IPN); zeolites

Computational study of a single-phase flow in packed beds of spheres - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
Packed-bed reactors are widely used in petrochemical, fine chemical, and pharmaceutical industries. Detailed knowledge of interstitial flow in the void space of such packed-bed reactors is essential for understanding the heat and mass transfer characteristics. In this paper, fluid flow through the array of spheres was studied using the unit-cell approach, in which different periodically repeating arrangements of particles such as simple cubical, 1-D rhombohedral, 3-D rhombohedral, and face-centered cubical geometries were considered. Single-phase flow through these geometries was simulated using computational fluid dynamics (CFD). The model was first validated by comparing predicted results with published experimental and computational results. The validated model was further used to study the effect of particle arrangement/orientation on velocity distribution and heat transfer characteristics. The simulated results were also used to understand and to quantify, relative contributions of surface drag and form drag in overall resistance to the flow through packed-bed reactors. The model and the results presented here would be useful in elucidating the role of microscopic flow structure on mixing and other transport processes occurring in packed-bed reactors. (C) 2005 American Institute of Chemical Engineers.
Keywords: CFD; drag; heat transfer; packed bed; packing arrangement

Concise account of recent S(N)2 ` grignard coupling reactions in organic synthesis - Kar, Anirban; N. P. Argade (Synthesis-Stuttgart, 2005)
Over the past few decades studies oil controlling the chemo-, regio- and stereoselectivities of allylic Substitution reactions have been well documented in the literature and the S(N)2' Grignard coupling reaction has emerged as a very powerful tool ill selective carbon-carbon bond formation. This review focuses on all the recent synthetic developments in this special class of reactions. 1 Introduction 2 S(N)2' Grignard Coupling Reactions with Allylic Substrates 2.1 Allyl Halides 2.2 Allyl Acetates 2.3 Allyl Carbonates 2.4 Allyl Carbamates 2.5 Allyl Ethers 2.6 Allyl Silyl Ethers 2.7 Allyl Epoxides 2.8 Allyl Aziridines 2.9 Allyl Oxazolidinones 2.10 Allyl Thioethers 2.11 Allyl Benzotriazoles 2.12 Oxabicyclic Alkenes 2.13 Azabicyclic Alkenes 2.14 Oxa-azabicyclic Alkenes 3 S(N)2' Grignard Coupling Reactions with Propargyl Substrates 3.1 Propargyl Acetates 3.2 Propargyl Silyl Ethers 3.3 Propargyl Epoxides 3.4 Propargyl Aziridines 3.5 Propargyl Dithioacetals 3.6 Propargyl Thioethers 4 S(N)2' Grignard Coupling Reactions with Bromoallenes 5 S(N)2' Grignard Coupling Reactions in Natural/Unnatural Product Synthesis 6 Conclusions.
Keywords: allylic substrates; bromoallenes; chiral/achiral S(N)2 ` Grignard coupling reactions; Natural products; propargyl Substrates

Concomitant dimorphs of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates with different halogen bonding contacts: first order crystal-to-crystal thermal phase transition of kinetic form to the thermodynamic form - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S.; Sanki, A. K. (Chemical Communications, 2005)
Crystallization of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates from ethyl acetate-petroleum ether solution produced concomitant dimorphs that have different halogen bonding contacts; the kinetic form with C-(BrO)-O-...-C contacts upon heating to 185 degrees C, converts completely to the thermodynamic form with C-(BrOLC)-O-... contacts via crystal-to-crystal first order phase transition.

Conformationally constrained PNA analogues: structural evolution toward DNA/RNA binding selectivity - Kumar, VA; Ganesh, Krishna N. (Accounts of Chemical Research, 2005)
Since its discovery 12 years ago, aminoethylglycyl peptide nucleic acid (aeg-PNA) has emerged as one of the successful DNA mimics for potential therapeutic and diagnostic applications. An important requisite for in vivo applications that has received inadequate attention is engineering PNA analogues for able discrimination between DNA and RNA as binding targets. Our approach toward this aim is based on structural preorganization of the backbone to hybridization-competent conformations to impart binding selectivity. This strategy has allowed us to design locked PNAs to achieve specific hybridization with DNA or RNA with aims to increase the binding strength without losing the binding specificity. This Account presents results of our rationale in design of different conformationally constrained PNA analogues, their synthesis, and evaluation of hybridization specificities.

Controlled growth of silicon nanocrystallites in silicon oxide matrix using 150 MeV Ag ion irradiation - Chaudhari, P. S.; Bhave, T. M.; Pasricha, R.; Singh, F.; Kanjilal, D.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2005)
We report the synthesis of silicon nanocrystals grown in silicon oxide matrix by swift heavy ion irradiation. Thin films of silicon oxide (SiO(x)) are irradiated with 150 MeV silver ions at fluence varying from 5 x 10(11) to 1 x 10(13) ions/cm(2). The variation in the properties of silicon nanocrystals embedded in silicon oxide with varying fluence is studied. The energy of the photoluminescence peak corresponding to the silicon nanocrystals is found to be red shifted with increasing fluence. The trends in the broadening of the X-ray diffraction peak with decreasing fluence supports the controlled growth of silicon nanocrystals in silicon oxide matrix. The crystallite size of nanoclusters of silicon is seen to increase with increasing fluence. The results are discussed in view of the structural transformation, in SiO(x) matrix, caused by swift heavy ion irradiation. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: oxide matrix; silicon nanocrystallites; swift heavy ion irradiation

Controlling the optical properties of lemongrass extract synthesized gold nanotriangles and potential application in infrared-absorbing optical coatings - Shankar, S. S.; Rai, A.; Ahmad, Absar; Sastry, M. (Chemistry of Materials, 2005)
Anisotropic metal nanoparticles have distinct optical behavior when compared with their spherical counterparts. In this report, we demonstrate a simple method involving the reduction of aqueous gold ions by the extract of the lemongrass plant leading to the formation of gold nanotriangles with interesting absorption in the near-infrared (NIR) region of the electromagnetic spectrum. We show that, by simple variation of the experimental conditions, it is possible to vary the size of the gold nanotriangles and, thus, to tune the absorbance of flat gold nanoparticles in the NIR region. The NIR absorption of the gold nanotriangles is expected to be of application in hyperthermia of cancer cells and in IR-absorbing optical coatings. We show that the lemongrass extract synthesized gold nanotriangles can be easily cast in the form of films on glass substrates and that these films are highly efficient in absorbing IR radiation for potential architectural applications.

Convenient synthesis of 5-methylene-4-substituted-2(5H)-furanones - Mahajan, Vishal A.; Shinde, Popat D.; Borate, Hanumant B.; Wakharkar, Radhika D. (Tetrahedron Letters, 2005)
A synthesis of novel 4-(substituted)benzyl-5-methylene-2(5H)-furanones involving Stobbe condensation of substituted aldehydes with ethyl levulinate followed by treatment with acetic anhydride in the presence of sodium acetate, has been developed. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: 5-methylene-2(5H)-furanones; acetic anhydride; arylaldehydes; ethyl levulinate; sodium acetate

Convenient synthesis of the enantiomerically pure beta-blocker (S)-betaxolol using hydrolytic kinetic resolution - Joshi, Ramesh A.; Garud, Dinesh R.; Muthukrishnan, Murugan; Joshi, Rohini R.; Gurjar, M. K. (Tetrahedron-Asymmetry, 2005)
Enantiopure (S)-betaxolol was prepared in an extremely simple and practical way using hydrolytic kinetic resolution of a terminal epoxide by Jacobsen's catalyst. High enantiomeric purity (99% ee) has been achieved and the method is amenable to industrial scale-up. (c) 2005 Elsevier Ltd. All rights reserved.

Conversion of fly ash - an environmentally detrimental waste to zeolite beta (BEA) for commercial catalytic applications - Kasture, M. W.; Bokade, Vijay V.; Joshi, P. N. (Journal of the American Ceramic Society, 2005)
Zeolite beta (BEA) was synthesized hydrothermally using fly ash as a combined source of alumina and silica. The overall crystallization period required to obtain pure crystalline BEA zeolite was found to be slightly longer when fly ash was used. The physicochemical properties of BEA phases obtained using fly ash (FLBEA) and conventional source materials (CONBEA) were compared. The H/FLBEA catalyst has exhibited excellent catalytic performance in commercially important benzene isopropylation process. These results have demonstrated that converting fly ash into BEA zeolite not only alleviates the disposal problem but also turns an otherwise waste material into a marketable commodity.

Copper- and ligand-free sonogashira reaction catalyzed by Pd(0) nanoparticles at ambient conditions under ultrasound irradiation - Gholap, Atul R.; Venkatesan, K.; Pasricha, R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Organic Chemistry, 2005)
The Sonogashira reaction proceeds at ambient temperature (30 degrees C) in acetone or room-temperature ionic liquid, 1,3-di-n-butylimidazolium tetrafluoroborate ([bbim]BF4), as solvent under ultrasound irradiation to give enhanced reaction rates, excellent chemoselectivity, and high yields in the absence of a copper cocatalyst and a phosphine ligand. TEM analysis showed the formation of stable, crystalline, and polydispersed Pd(0) nanoparticles as catalyst for the reaction.

Copper(II) ion-exchanged montmorillonite as catalyst for the direct addition of N-H bond to CC triple bond - Joseph, Trissa; Shanbhag, G. V.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
An efficient synthesis of phenyl-(1-phenylethylidene)amine using copper-exchanged montmorillonite clay (Cu K-10) is demonstrated. The catalyst was characterized using UV-vis, XRD, BET surface area measurements, pyridine adsorption etc. The XRD and surface area measurement show that the structural characteristics of the support montmorillonite K-10 (K-10) are preserved after Cu exchange. The hydroamination of phenyl acetylene with aniline was carried out in toluene under reflux condition in N-2 atmosphere at 393 K. The reaction is highly regio-selective for only Markovnikoff's addition of an-tine to CC multiple bond and proceeded smoothly to completion. The reaction conditions were optimized to obtain complete conversion with respect to phenyl acetylene. Reaction data showed that the activity of the catalyst in hydroamination reaction is greater at higher reaction temperatures and nonpolar solvents and NZ pressure promotes the reaction drastically. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: alkyne; Aniline; Catalyst; hydroamination; K-10 montmorillonite clay; phenyl acetylene

Co-precipitation method for the preparation of ferroelectric CaBi4Ti4O15 - Gaikwad, S. P.; Dhage, S. R.; Ravi, V. (Journal of Materials Science-Materials in Electronics, 2005)
A simple co-precipitation technique has been successfully applied for the preparation of pure single phase CaBi4Ti4O15 (CBT) powders. Ammonium oxalate and ammonium hydroxide were used to precipitate Ca2+, Bi3+ and Ti4+ cations simultaneously. No pyrochlore phase was found while heating powder at 600&DEG; C and pure CBT phase was found to be formed by X-ray diffraction. Particle size and morphology was studied by transmission electron microscopy (TEM). The room temperature dielectric constant at 1 kHz is 400. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2005 Springer Science + Business Media, Inc.

Co-precipitation method for the preparation of fine ferroelectric BaBi2M2O9 - Gaikwad, S. P.; Potdar, HS; Samuel, V; Ravi, V (Ceramics International, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure fine powders of single phase BaBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was formed while heating powder at 800 degrees C and pure BaBi2Nb2O9 phase was found to be formed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders chemical preparation

Co-precipitation method for the preparation of nanocrystalline ferroelectric SrBi2Nb2O9 ceramics - Gaikwad, S. P.; Dhage, S. R.; Potdar, H. S.; Samuel, V.; Ravi, V. (Journal of Electroceramics, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase SrBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Sr2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was found while heating powder at 850 C and pure SrBi2Nb2O9 (SBN) phase was formed as revealed by the X-ray diffraction (XRD) studies. Particle size and morphology was studied by transmission electron microscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic materials; ferroelectricity; Oxides

Coprecipitation technique to prepare BaNb2O6 - Natarajan, N; Samuel, V; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and niobium ions as barium oxalate and niobium hydroxide under basic conditions. This precursor on calcination at 750degreesC yielded BaNb2O6 ceramics. This is a much lower temperature as compared to that prepared by traditional solid-state method (1000degreesC), as reported for the formation of BaNb2O6. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ammonia; Ceramics; Electron microscopy; niobium oxide; Oxides

Coprecipitation technique to prepare SrNb2O6 - Ravi, V (Materials Characterization, 2005)
A mixture of ammonium oxalate and ammonium hydroxide was used to co-precipitate strontium and niobium ions as strontium oxalate and niobium hydroxide under basic conditions. This precursor yielded SrNb2O6 ceramics on calcining at 650 degrees C. This is a much lower temperature compared to preparation of SrNb2O6 by the traditional solid state method (900 degrees C). Transmission electron microscopy (TEM) revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 550. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectric; Oxides; X-ray methods

Coprecipitation technique to prepare ZnM2O6 powders - Deshpande, V. V.; Patil, M. M.; Navale, S. C.; Ravi, V. (Bulletin of Materials Science, 2005)
A simple coprecipitation technique was successfully applied for the preparation of pure ultrafine single phase, ZnNb2O6 (ZN). Ammonium hydroxide was used to precipitate Zn2+ and Nb5+ cations as hydroxides simultaneously. This precursor on heating at 750 degrees, produced ZN powders. For comparison, ZN powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM).
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction

Correlated complex independent particle potential for calculating electronic resonances - Sajeev, Y; Santra, R; Pal, S (Journal of Chemical Physics, 2005)
We have formulated and applied an analytic continuation method for the recently formulated correlated independent particle potential [A. Beste and R. J. Bartlett J. Chem. Phys. 120, 8395 (2004)] derived from Fock space multireference coupled cluster theory. The technique developed is an advanced ab initio tool for calculating the properties of resonances in the low-energy electron-molecule collision problem. The proposed method quantitatively describes elastic electron-molecule scattering below the first electronically inelastic threshold. A complex absorbing potential is utilized to define the analytic continuation for the potential. A separate treatment of electron correlation and relaxation effects for the projectile-target system and the analytic continuation using the complex absorbing potential is possible, when an approximated form of the correlated complex independent particle potential is used. The method, which is referred to as complex absorbing potential-based correlated independent particle (CAP-CIP), is tested by application to the well-known (2)Pi(g) shape resonance of e-N-2 and the B-2(2g) shape resonance of e-C2H4 (ethylene) with highly satisfactory results. (c) 2005 American Institute of Physics.

Corrosion protective poly(o-toluldine) coatings on copper - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Corrosion Science, 2005)
This study examines the use of poly(o-toulidine) (POT) coatings for corrosion protection of copper (Cu) in an aqueous solution of 3% NaCl. The POT coatings were synthesized on Cu substrates under cyclic voltammetric conditions from an aqueous solution of sodium oxalate. The resulting, POT coatings were uniform, shiny and strongly adherent to the Cu substrates. These coatings were characterized by cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The ability of POT to serve as a corrosion protective coating for Cu was examined by potentiodynamic polarization measurements and CV. The results of this study clearly reveal that the POT acts as corrosion protective coating on Cu and reduces the corrosion rate of Cu almost by a factor of 40. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Crystallization and preliminary x-ray characterization of a lectin from Cicer arietinum (chickpea) - Katre, Uma V.; Gaikwad, S. M.; Bhagyawant, S. S.; Deshpande, U. D.; Khan, Mohammad Islam; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Crystallization of polymers from stressed melts - Kumaraswamy, Guruswamy (Journal of Macromolecular Science-Polymer Reviews, 2005)
In the last decade, there have been several investigations into the route by which a polymer melt that has been subjected to flow transforms into a crystalline state. Crystallization of polymers from flowing or stressed melts is a technologically important problem since most thermoplastics are subjected to intense flow fields during normal processing operations. The renewed interest in this problem is due to the availability of new experimental tools that, coupled with advances in modeling and simulations, are beginning to yield insights into the molecular characteristics that control the crystallization pathways adopted by a stressed polymer melt. Recent evidence conclusively implicates the high molecular weight tail in promoting crystallization on shearing. It appears that the formation of oriented nuclei in polydisperse melts is controlled by chain orientation of a small fraction of high molecular weight chains in a melt. Thus, it is the theological criteria for ``critical'' chain orientation that govern flow-induced acceleration and orientation in polymer crystallization. This review summarizes the literature on the effect of shearing on polymer crystallization, and focuses on recent advances in understanding the role of molecular parameters that couple polymer crystallization to flow and melt orientation.
Keywords: flow; polymer crystallization; processing; shear

Cure characteristics and dielectric properties of magnetic composites containing strontium ferrite - Soloman, M. A.; Kurian, P.; Anantharaman, Maliemadom R.; Joy, Pattayil Alias (Journal of Elastomers and Plastics, 2005)
Hexagonal strontium ferrite (SrFe12O19) powders were synthesized by the conventional ceramic techniques. They were then characterized by the X-ray diffraction method and incorporated in the natural rubber matrix according to a specific recipe for various loadings of ferrite to produce rubber ferrite composites (RFCs). The processability of these compounds was determined by evaluating the cure characteristics namely, scorch time, cure time, minimum and maximum torque. The evaluation of the dielectric properties of ceramic strontium ferrite (SrF), natural rubber gum vulcanizate, and RFCs were done with the help of a Hewlett Packard (HP) impedance analyzer. The magnetic properties of these composites were studied using a Vibrating Sample Magnetometer (VSM). The effect of carbon black on the processability, and the magnetic and dielectric properties were also studied by the incorporation of carbon black into these composites. It has been found that the addition of these ferrites and carbon black does not affect the processability of these composites, whereas the physical properties are found to be modified. From the magnetic and dielectric measurements it has been found that flexible magnets having appropriate dielectric strength can be prepared by the incorporation of appropriate amount of SrF and carbon black in the natural rubber matrix.
Keywords: hexagonal ferrites; Magnetic materials; permanent magnets; rubber ferrite composites (RFCs); strontium ferrite

CFD simulation of gas-liquid stirred vessel: VC, S33, and L33 flow regimes - Khopkar, A. R.; Ranade, V. V. (AICHE Journal, 2006)
A comprehensive computational model based on the Eulerian-Eulerian approach was developed to simulate gas-liquid flows in a stirred vessel. A separate submodel was developed to quantitatively understand the influence of turbulence and presence of neighboring bubbles on drag acting on bubbles. This submodel was used to identify an appropriate correlation for estimating the interphase drag force. The standard k-epsilon turbulence model was used to simulate turbulent gas-liquid flows in a stirred vessel. A computational snapshot approach was used to simulate motion of the standard Rushton turbine in a fully baffled vessel. The computational model was mapped onto FLUENT4.5, a commercial CFD solver. The model predictions were compared with the previously published experimental data of Bombac and co-workers. The model was used to simulate three distinct flow regimes in gas-liquid stirred vessels: vortex clinging (VC), alternating small cavities (S33), and alternating large cavities (L33). The predicted results show reasonably good agreement with the experimental data for all three regimes. The computational model and results discussed in this work would be useful for understanding and simulating gas holdup distribution and flow regimes in stirred vessels. (c) 2006 American Institute of Chemical Engineers.
Keywords: computational fluid dynamics (CFD); Flow regimes; gas holdup distribution; Rushton turbine; stirred vessel

CFD simulation of mixing in tall gas-liquid stirred vessel: role of local flow patterns - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Chemical Engineering Science, 2006)
In this work, we have used the computational fluid dynamics (CFD)-based models to investigate the gas-liquid flows generated by three down-pumping pitched blade turbines. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence [Khopkar and Ranade, 2005. CFD simulation of gas-liquid flow in a stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal, accepted for publication] were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). The computational model has successfully captured the flow regimes as observed during experiments. The particle trajectory simulations were then carried out to examine the influence of the different flow regimes on the circulation time distribution. The model predictions were verified by comparing the predicted results with the experimental data of [Shewale and Pandit, 2006. Studies in multiple impeller agitated gas-liquid contactors. Chemical Engineering Science 61, 489-504]. The computational model and results discussed in this study would be useful for explaining the implications local flow patterns on the mixing process and extending the applications of CFD models for Simulating large multiphase stirred reactors. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CFD; Flow regimes; mixing; pitched blade turbine; stirred vessel

CFD simulation of shortstopping runaway reactions in vessels agitated with impellers and jets - Dakshinamoorthy, D.; Khopkar, A. R.; Louvar, J. F.; Ranade, V. V. (Journal of Loss Prevention in the Process Industries, 2006)
Runaway reactions are continuing to be a problem in the chemical industry. A recent study showed that 26% of our major chemical plant accidents are due to runaways. The consequences of runaway reactions are usually mitigated with (a) reliefs and containment systems or (b) shortstopping (reaction inhibition). This study covers the concept of shortstopping. One of the major reasons for runaways is power failure. In the advent of a power failure, mixing an inhibiting agent with the reactor contents is challenging. However, jets or impellers driven by a small generator can be used for mixing. This study compares shortstopping results in vessels agitated with jets and impellers using computational fluid dynamics (CFD). A commercial CFD code, Fluent is used. For shortstopping systems relying on jet mixing, angle and diameter of jet nozzle and jet velocity are the key design/operating parameters. For the systems with impellers, type, size and RPM of impeller are the key parameters. In this work, mixing with a jet mixer is first investigated for three nozzle diameters and two angles of injection. The best jet mixer configuration on the basis of mixing time is used for shortstopping studies. The simulated shortstopping results with the jet mixer are then compared with those obtained with impeller (Rushton and pitched blade turbine) stirred vessels. Our results identify the conditions for effective shortstopping; i.e., agitation requirements, locations for adding the inhibitor, and the quantity of inhibitor. The distribution of excess inhibitor is shown to be an important and essential design criterion for effective shortstopping when using impeller stirred vessels. The comparative study with a single jet shows that jet mixer is ineffective when used for shortstopping. Efforts such as adding excess inhibitor and inhibition with higher reaction rates at the same power, proved to be ineffective when using jet mixer compared to the results with impellers. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; impeller stirred vessels; jet mixer; runaway reaction; shortstopping

Characterization of Cd1-xZnxSe thin films deposited at low temperature by chemical route - Hankare, P. P.; Chate, P. A.; Asabe, M. R.; Delekar, S. D.; Mulla, Imtiaz S.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2006)
Optoelectronic technologically important pseudo-binary Cd1-xZnxSe thin films with a variable composition ( 0 < x < 1) has been developed by chemical bath deposition method. The objective to study growth kinetics, physical, microscopic, compositional, optical, electrical and structural changes. Cd1-xZnxSe have been deposited on non-conducting glass substrate in tartarate bath containing Cd+2 and Zn+2 ions with sodium selenosulphate with an aqueous alkaline medium at 278 K. The quality and the thickness of the films are depends upon deposition temperature, deposition time and pH, etc. X-ray diffraction (XRD), atomic absorption spectroscopy, optical absorption, scanning electron microscopy and thermoelectric technique characterized the films. The XRD study indicates the polycrystalline nature in single cubic phase over whole range of composition. Analysis of absorption spectra gave direct type band gap, the magnitude of which increases non-linearly as zinc content in the film is increased and dc electrical conductivity at room temperature was found to decreases from 10(-7) to 10(-8) (Omega cm)(-1). All the films show n-type conductivity. The promising features observed are the formation of continuous solid solutions in a single cubic phase.

Characterization of nanosized NiZn ferrite powders synthesized by an autocombustion method - Deka, Sasanka; Joy, Pattayil Alias (Materials Chemistry and Physics, 2006)
Nanocrystalline Ni0.5Zn0.5Fe2O4 with average particle size of similar to 9 nm has been synthesized by an autocombustion method and characterized by powder XRD, TEM and room temperature magnetic measurements. High room temperature magnetization comparable to that of the bulk material is obtained for the nanosized powders annealed at 800 degrees C, with a maximum particle size of similar to 54 nm. The results show that optimum properties can be achieved for NiZn ferrite powders synthesized by the present autocombustion method and processed at relatively lower temperatures. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Magnetic materials; magnetic properties; Oxides

Characterization of polydimethylsiloxane rubber upon photochemical, thermal, salt-fog ageings and exposure to acid vapours - Delor-Jestin, Florence; Tomer, N. S.; Singh, R. P.; Lacoste, Jacques (E-Polymers, 2006)
The changes in the chemical structure and the physical properties of a filled crosslinked polydimethylsiloxane rubber were monitored as a function of various ageing factors. The variables included photochemical, thermal, salt-fog ageings and exposure to acid vapours. Unaged and aged samples were studied by IR spectroscopy, hardness measurements, Differential Scanning Calorimetry (DSC) and thermogravimetric analysis (TGA) coupled with IR spectroscopy. No significant oxidation was detected after all ageings, except for nitric acid treatment. The presence of aluminium trihydrate was clearly identified as responsible for the observed chemical changes. Then an important vulnerability of this filled silicone rubber towards the cross-linking reactions provoked by usual ageings was also detected. The DSC-thermoporosimetry measurements of the mesh size distribution gave a comparison of cross-linking densities for each ageing. The complementary analysis with TGA-IR allowed us to differenciate the thermal stability of the formulation after various ageings and to acquire new knowledge about thermal decomposition.

Chemical methods to synthesize FeTiO3 powders - Mona, J.; Kale, Sangeeta N.; Gaikwad, A. B.; Murugan, A. Vadivel; Ravi, V. (Materials Letters, 2006)
Three different techniques were used to synthesize FeTiO3 powders. The first method is simple coprecipitation of both Fe and Ti ions under basic conditions using standard ammonia solution from aqueous ferric nitrate and titanium oxy chloride. This precipitate on heating at 400 degrees C produces ilmenite phase. The second method is to digest hydroxide precipitates at 100 degrees C to form FeTiO3 phase. The third technique is to make use of citrate process to form FeTiO3 powders. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by Transmission Electron Microscopy (TEM). (c) 2005 Elsevier B.V. All tights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray methods

Chemistry of recently isolated naturally occurring quinazolinone alkaloids - Mhaske, Santosh B.; N. P. Argade (Tetrahedron, 2006)
The present review portrays a concise account of the isolation, bioactivity, and synthesis of bioactive quinazolinone-based natural products for the period 1983-2005 and the recent developments in the area of complex quinazolinone natural products with a special emphasis on new synthetic routes and strategies. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1983-2005; bioactivity; concise account; isolation; natural quinazolinones; synthesis

Chemo-, regio- and stereo-selective aerial oxidation of limonene to the endo-1,2-epoxide over Mn(Salen)-sulfonated SBA-15 - Saikia, Lakshi; Srinivas, D.; Ratnasamy, Paul (Applied Catalysis A-General, 2006)
Mn(Salen) complexes immobilized on sulfonic acid-functionalized SBA-15 molecular sieves (SBA-15-pr-SO3-Mn(Salen)) catalyze the Mukaiyama-type oxidation of R-(+)-limonene selectively to the 1,2-epoxide with molecular oxygen at 298 K (Salen = N,N-ethylenebis(salicylidenaminato)). The endo-diastereomer is formed with a diasteromeric excess of 39.8%. This catalyst exhibited higher catalytic activity than ``neat'' Mn(Salen) complexes directly supported on SBA-15 or zeolite-Y. A change in the oxidation state of Mn from +3 in the ``neat'' complex to +2 when immobilized on the sulfonated surface is a probable cause for the observed enhancement of catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: aerial oxidation of limonene; catalysis by Mn(Salen) complexes; chemo-; immobilized Mn Schiff base complexes; Mesoporous molecular sieves; Mukaiyama-type oxidation; regio- and stereo-selective epoxidation; sulfonic acid-functionalized SBA-15

Chemoselective anti-Markovnikov hydroamination of alpha,beta-ethylenic compounds with amines using montmorillonite clay - Joseph, Trissa; Shanbhag, G. V.; Sawant, D. P.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A-Chemical, 2006)
The catalytic activity of montmorillonite clays as a catalyst for the hydroamination of alpha,beta-ethylenic compounds with amines was tested. Aniline and substituted amines reacted with alpha,beta-ethylenic compounds in the presence of catalytic amount of commercially available clay to afford exclusively anti-Markovnikov adduct in excellent yields. Aniline reacted with ethyl acrylate to yield only anti-Markovnikov adduct N-[2-(ethoxycarbonyl)ethyl] aniline (mono-addition product). No Markovnikov adduct (N-[1-(ethoxycarbonyl)ethyl]aniline and double addition product N,N-bis[2-(ethoxycarbonyl)ethyl]aniline were formed under selected reaction conditions. For a better exploitation of the catalytic activity in terms of increased activity and improved selectivity for the mono-addition product, the reaction parameters were optimized in terms of temperature, solvent, reactant mole ratio. Under optimized reaction conditions, montmorillonite clay K-10 showed a superior catalytic performance in the hydroamination of ethyl acrylate with aniline with a conversion of aniline to mono-addition product (almost 100% chemoselectivity) with a high rate constant 0.3414 min(-1) compared to the reported protocols. The dependence of conversion of aniline over different types of montmorillonite clays (K-10, K-20, K-30, Al-Pillared clay and untreated clay) has also been discussed. The activities of clay for the hydroamination of different aromatic and aliphatic amines have also been investigated. Under harsh reaction conditions (increased temperature and long reaction time) small amounts of di-addition products were observed. The kinetics data has been interpreted using the initial rate approach model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alpha; amines; anti-Markovnikov addition product; beta-ethylenic compounds; chemo-selective; hydroamination; K-10 montmorillonite clay

Chemoselective dithioacetalization of aldehydes using silica sulfuric acid as a reusable catalyst - Pore, D. M.; Desai, Uday V.; Mane, R. B.; Wadgaonkar, P. P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Silica sulfuric acid has been found to be an efficient and reusable catalyst for chemoselective dithioacetalization of aldehydes over ketones, in excellent yields.
Keywords: Chemoselective; dithioacetalization; silica sulfuric acid

Claisen rearrangement of allyl phenyl ether over zeolites beta, mordenite and Y - Wagholikar, S. G.; Mayadevi, S.; Jacob, Nalini E.; Sivasanker, S. (Microporous and Mesoporous Materials, 2006)
The Claisen rearrangement of allyl phenyl ether (APE) to o-allylphenol was investigated over zeolites beta (BEA), mordenite (MOR) and Y (FAU) with different Si/Al ratios. Over the zeolite catalysts, the allylphenol cyclized to produce 2,3-dihydro-2-methyl benzofuran. Larger catalyst loading, higher reaction temperatures and longer run duration favored the formation of the ring compound. Conversion was small over MOR and FAU although they possessed higher acidity (as measured by the temperature programmed desorption of ammonia) compared to BEA. Studies using BEA revealed that the nature of the solvent influenced the reaction rate. The order of reactivity in the solvents was, benzene > EDC (1,2-dichloroethane) > toluene > TCE (1, 1,2,2-tetrachloroethane) >> ACN (acetonitrile). The intermediate allylphenol reacted with the aromatic solvents to produce byproducts when benzene and toluene were used as solvents. A kinetic analysis assuming first order series and parallel reactions is presented. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: allyl phenyl ether; allylphenol; Benzofuran; Claisen rearrangement; zeolites

Clay-mediated selective hydrolysis of 5 `-O-acetyl-2 `,3 `-isopropylidene/cyclohexylidene nucleosides - Gurjar, Mukund K.; Mondal, Dhananjoy; Ravindranadh, S. V.; Chorghade, Mukund S. (Synthetic Communications, 2006)
A generalized procedure for the selective hydrolysis of 5'O-acetyl-2',3'-isopropylidene/cyclohexylidene nucleosides with a solid catalyst, Montmorillonite K-10 in refluxing methanol, to furnish 5'-O-acetyl-nucleosides is described.
Keywords: 5-O-acetylnucleosides; isopropylidene-nucleoside hydrolysis; montmorillonite K 10

CO2 reforming of methane combined with steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal-oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C. (Applied Energy, 2006)
CO2 reforming with simultaneous steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst (prereduced by H-2) at different process conditions has been investigated. In the simultaneous CO2 and steam reforming, the conversion of methane and H2O and also the H-2/CO product ratio are strongly influenced by the CO2/H2O feed-ratio. In the simultaneous CO2 reforming and partial oxidation of methane, the conversion of methane and CO2, H-2 selectivity and the net heat of reaction are strongly influenced by the process parameters (viz. temperature, space velocity and relative concentration of O-2 in the feed). In both cases, no carbon deposition on the catalyst was observed. The reduced NdCoO3 perovskite-type mixed-oxide catalyst (Co dispersed on Nd2O3) is a highly promising catalyst for carbon-free CO2 reforming combined with steam reforming or partial oxidation of methane to syngas. (c) 2005 Published by Elsevier Ltd.
Keywords: Co/Nd2O3 catalyst; methane; NdCoO3 perovskite-type mixed metal-oxide catalyst; Oxy-CO2 reforming of methane; simultaneous CO2 and steam reforming of methane

CO2 reforming of methane to syngas over CoOx/MgO supported on low surface area macroporous catalyst carrier: Influence of Co loading and process conditions - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Industrial & Engineering Chemistry Research, 2006)
The effect of Co loading (5-30 wt %) and process parameters ( reduction pretreatment, reaction temperature, and space velocity) have been investigated over CoOx/MgO(5%)/SA-5205 catalyst for the CO2 methane reforming process. The Co loading had a profound effect on the methane conversion and the hydrogen selectivity ( initial and time-on-stream activity) for the unreduced catalysts. While negligible methane conversion was observed for the 5 and 10 wt % Co loading catalyst, methane conversions > 95% were obtained over the high Co loading ( 20 and 30 wt %) catalysts; hydrogen selectivity followed the same trend as methane conversion. The Co loading level had a relatively smaller influence in the case of the reduced catalysts. While the 5 wt % Co catalyst showed low methane conversion activity (< 30%), the 10 wt % Co catalyst showed methane conversion levels comparable to those of the high Co loading catalysts. The high Co loading catalysts showed an excellent time-on-stream performance for the CO2 methane reforming reaction. X-ray diffraction and temperature-programmed reduction experiments indicate that the interesting activity behavior exhibited by the catalysts is related to the different phases ( and their reducibility) present in the catalysts at different Co loadings. The hydrogen selectivity was found to decrease with decreasing reaction temperature and increasing space velocity due to the increased simultaneous occurrence of the reverse water-gas shift reaction along with the CO2 reforming reaction.

Cobalt-containing hexagonal mesoporous molecular sieves (Co-HMS): Synthesis, characterization and catalytic activity in the oxidation reaction of ethylbenzene - Bhoware, Shrikant S.; Shylesh, S.; Kamble, K. R.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2006)
Cobalt-containing hexagonal mesoporous materials (Co-HMS and Co/HMS) with different cobalt content were synthesized for the first time by direct hydrothermal and post-synthesis (grafting) method. The materials were characterized in detail by X-ray diffraction, BET surface area, N-2 sorption isotherms, SEM, TEM, UV-vis and XPS techniques. Powder X-ray diffraction pattern, N2 adsorption-desorption analysis and TEM analysis show the presence of hexagonal mesoporous structure, having Type W isotherms and reveals the typical wormhole-like morphology. Spectroscopic techniques like UV-vis and XPS reveal cobalt in +2 oxidation state and tetrahedrally coordinated. Liquid phase oxidation of ethylbenzene using TBHP (70 wt%) as an oxidant shows that the catalysts are highly active, under solvent free conditions as well as under lower cobalt concentrations. Leaching studies performed by hot filtration experiments show that the cobalt catalysts prepared by hydrothermal methods are stable, while the grafted catalysts show the leaching of cobalt under the reaction conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Co-HMS; ethylbenzene; HMS; hydrothermal; Oxidation

Co-catalyzed reductive cyclization of azido and cyano substituted alpha,beta-unsaturated esters with NaBH4: enantioselective synthesis of (R)-baclofen and (R)-rolipram - Paraskar, A. S.; Sudalai, A. (Tetrahedron, 2006)
Sodium borohydride in combination with a catalytic amount of CoCl, has been found to be an excellent catalytic system in reductive cyclizations of suitably substituted azido and cyano groups of alpha,beta-unsaturated esters to afford gamma and delta-lactams in high yields. The process has been demonstrated for the enantioselective synthesis of (R)-baclofen, (R)-rolipram, and (R)-4-fluorophenylpiperidinone, a key intermediate for (-)-paroxetine. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Asymmetric synthesis; cobalt chloride; gamma and delta-lactams; reduction; sodium borohydride

COLL 613-Studies on the vapor-phase photo-oxidation of methanol over nano-size titania clusters dispersed in MCM-41 mesoporous silica - Kumar, Dharmesh; Bhattacharyya, Kaustav; Tripathi, Arvind; Varma, Salil; Gupta, Narendra M. (Abstracts of Papers of the American Chemical Society, 2006)

Collapse transition in random copolymer solutions - Dasmahapatra, Ashok Kumar; Kumaraswamy, Guruswamy; Nanavati, Hemant (Macromolecules, 2006)
We present dynamic Monte Carlo lattice simulations of the coil to globule collapse of single chains of a copolymer comprising monomer units, m and c, wherein there is a net attractive interaction between c-units. As the copolymer is cooled, the solvent quality becomes poorer, and the size of the chain decreases, driven by the net m-m and c-c attractions. The strong c-c attraction increases the overall solvophobicity of the chain relative to a homopolymer and, therefore, copolymers collapse more abruptly and at a higher effective temperature relative to homopolymers. We compare copolymers with homopolymers by rescaling collapse data to the same theta values to account for the effect of overall solvophobicity. This comparison shows that the behavior of copolymers and the corresponding homopolymers is identical as the chain size reduces from high temperatures to the theta value. Beyond theta, copolymers with c-content < similar to 50% collapse more abruptly than either homopolymer, after accounting for the difference in overall solvophobicity. Collapse of copolymers containing higher c-content is dominated entirely by the c-c attractions, and these chains behave qualitatively like homopolymers with a higher effective solvophobicity. Analysis of the chain structure during collapse provides a structural reason for the qualitative change in copolymer collapse at low c-content. When such copolymers are cooled below theta, the c-units rapidly aggregate to form an isotropic, compact core surrounded by an anisotropic solvated shell of m-units. The shell densifies as the copolymer is further cooled, but remains anisotropic for the finite chain sizes investigated.

Comment on ``Photoelectron spectroscopic investigation of nitrogen-doped titania nanoparticles'' - Gopinath, Chinnakonda S. (Journal of Physical Chemistry B, 2006)

Comparative assessment of downstream processing options for lactic acid - Joglekar, H. G.; Rahman, Imran; Babu, Suresh; Kulkarni, B. D.; Joshi, Ajit (Separation and Purification Technology, 2006)
The possibility of manufacturing a biodegradable polymer from lactic acid has led to extensive research in recovery of lactic acid produced by fermentation, by different downstream processing routes. This paper assesses the suitability of different downstream processing options such as reactive extraction, adsorption, electrodialysis, esterification and reactive distillation. It compares the costs of different process routes. The assessment indicates that the conventional precipitation of calcium lactate, followed by acidification, esterification and hydrolysis will be the most economical route although it generates large quantity of gypsum sludge. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; electrodialysis; Esterification; Lactic acid; Reactive distillation; reactive extraction

Comparative study of conductive polypyrrole and polyaniline coatings on electro-active papers - Kim, Jachwan; Deshpande, S. D.; Yun, Sungryul; Li, Qubo (Polymer Journal, 2006)
{A comparative study is performed on the conductive polymer-coated electro-active paper (EAPap) actuators by aiming at improving the overall performance of the actuators. Conductive Polymer coated Electro-active Paper [
Keywords: conifer; glufosinate; particle bombardment; Pinus roxburghii; stable transformation

Comparison of flow structures in spacer-filled flat and annular channels - Ranade, Vivek V.; Kumar, Anil (Desalination, 2006)
Spacers are designed to create directional changes in the flow through membrane modules. Such secondary flow structures reduce concentration polarization and membrane fouling. Obviously, type of the spacer used in membrane modules strongly influences the resulting flow and therefore performance of the module. In this work, we have modeled detailed fluid dynamics of spacer filled channels by using the `unit cell' approach. The validated computational fluid dynamics (CFD) model was used to evaluate performance of certain spacer shapes and compare the resulting fluid dynamics in flat and curved channels. The simulations show that fluid flow behavior in a spacer-filled flat and a spiral channel was not significantly different. This means that pressure drops and mass transfer coefficients measured in flat channels may provide adequate guidelines, which would also be valid for spiral-wound modules. The results presented in this work will have significant implications for identifying improved spacers with higher propensities to reduce fouling in membrane modules.
Keywords: annular channel; CFD; flat channel; membrane spacers

Computational fluid dynamics simulation of the solid suspension in a stirred slurry reactor - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2006)
A comprehensive computational fluid dynamics CFD model was developed in the present study to gain insight into the solid suspension in a stirred slurry reactor. The preliminary simulations highlighted the need for the correct modeling of the interphase drag force. A two-dimensional model problem was then developed using CFD to understand the influence of free stream turbulence on the particle drag coefficient. The proposed correlation was then incorporated in a two-fluid model (Euler-Euler) along with the standard k-epsilon turbulence model with mixture properties to simulate the turbulent solid-liquid flow in a stirred reactor. A multiple reference frame approach was used to simulate the impeller rotation in a fully baffled reactor. A computational model was mapped on to a commercial CFD solver FLUENT6.2 (of Fluent Inc., USA). The model predictions were compared with the published experimental data of Yamazaki et al. [Powder Technol. 1986, 48, 205] and Godfrey and Zhu [AIChE Symp. Ser. 1994, 299, 181]. The predicted results show reasonably good agreement with the experimental data. The computational model and results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.

Concise asymmetric route to the antibiotic macrolides patulolide A and pyrenophorin - Rao, K. Srinivasa; Reddy, D. Srinivasa; Mukkanti, K.; Pal, Manojit; Iqbal, Javed (Tetrahedron Letters, 2006)
In this letter, we describe an enantiospecific route to patulolide A and pyrenophorin through the synthesis of known protected seco acid precursors starting from commercially available (S)-ethyl lactate. (c) 2006 Elsevier Ltd. All rights reserved.

Conducting polymer based hybrid nano-composites for enhanced corrosion protective coatings - Patil, R. C.; Radhakrishnan, S. (Progress in Organic Coatings, 2006)
Hybrid composite coatings containing zinc oxide (ZnO) and polyaniline (PANI) as nano-additives dispersions were prepared with poly(vinyl acetate) (PVAc) as the major matrix. The steel plates dip-coated with these formulations were tested for corrosion protection by immersion in saline water over long periods. The Tafel plots for the determination of open circuit potential (OCP) and corrosion current (I-corr) were recorded. The coatings containing both ZnO and PANI showed improved corrosion resistance as compared to the single component coating. The I-corr values of PVAc-ZnO-PANI are found to be two-order magnitude lower than that of PVAc and PVAc-ZnO coatings. The results are explained on the basis of enhancement in barrier properties due to nano-particulate additives in PVAc-ZnO-PANI film together with the redox behaviour of PANI and protective oxide layer formation near the substrate. (C) 2006 Elsevier B.V All rights reserved.
Keywords: Coatings; corrosion; nano-additives; polyaniline; ZnO

Conformation and microenvironment of the active site of a low molecular weight 1,4-beta-D-glucan glucanohydrolase from an alkalothermophilic thermomonospora sp.: involvement of lysine and cysteine residues - Jagtap, Sharmili; Rao, Mala (Biochemical and Biophysical Research Communications, 2006)
Conformation and microenvironment at the active site of 1,4-beta-D-glucan glucanohydrolase was probed with fluorescent chemo-affinity labeling using o-phthalaldehyde. OPTA has been known to form a fluorescent isoindole derivative by cross-linking the proximal thiol and amino groups of cysteine and lysine. Modification of lysine of the enzyme by TNBS and of cysteine residue by PHMB abolished the ability of the enzyme to form an isoindole derivative with OPTA. Kinetic analysis of the TNBS and PHMB-modified enzyme suggested the presence of essential lysine and cysteine residues, respectively, at the active site of the enzyme. The substrate protection of the enzyme with carboxymethylcellulose (CMC) confirmed the involvement of lysine and cysteine residues in the active site of the enzyme. Multiple sequence alignment of peptides obtained by tryptic digestion of the enzyme showed cysteine is one of the conserved amino acids corroborating the chemical modification studies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 1; 4-beta-D-glucan glucanohydrolase; active site microenvironment; Cysteine; lysine; OPTA; PHMB; Thermomonospora sp.; TNBS

Conjugate addition of a silyl ketene acetal to alpha,beta-unsaturated lactones - Gnaneshwar, Rudhramyna; Sivaram, S (Synthetic Communications, 2006)
{Conjugate addition of a silyl ketene acetal [
Keywords: acetals; deprotection; MoO3/SiO2; protection

Constrained variational response to Fock-space multi-reference coupled-cluster theory: Some pilot applications - Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Molecular Structure-Theochem, 2006)
Fock space (FS) multi-reference (MR) coupled-cluster (CC) has been established to be state-of-the-art method for energies of open-shell radicals, ionized, electron attached states and excited states. Due to the multi-root nature of the method, the linear response of MRCC, however, is non-trivial. Constrained variation approach (CVA) makes it plausible to calculate response of the MRCC method efficiently. However, the approach is used for only one root of the problem at a time. In the present article, we make first implementation of the approach and present test results of dipole moments of small radicals. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: constrained variation; coupled-cluster; Dipole moment; Multi-reference; response

Construction of conductive multilayer films of biogenic triangular gold nanoparticles and their application in chemical vapour sensing - Singh, Amit; Chaudhary, Minakshi V.; Sastry, Murali (Nanotechnology, 2006)
Metal nanoparticles are interesting building blocks for realizing films for a number of applications that include bio- and chemical sensing. To date, spherical metal nanoparticles have been used to generate functional electrical coatings. In this paper we demonstrate the synthesis of electrically conductive coatings using biologically prepared gold nanotriangles as the building blocks. The gold nanotriangles are prepared by the reduction of aqueous chloroaurate ions using an extract of the lemongrass plant (Cymbopogon flexuosus) which are thereafter assembled onto a variety of substrates by simple solution casting. The conductivity of the film shows a drastic fall upon mild heat treatment, leading to the formation of electrically conductive thin films of nanoparticles. We have also investigated the possibility of using the gold nanotriangle films in vapour sensing. A large fall in film resistance is observed upon exposure to polar molecules such as methanol, while little change occurs upon exposure to weakly polar molecules such as chloroform.

Construction of enantiopure pyrrolidine ring system via asymmetric [3+2]-cycloaddition of azomethine ylides - Pandey, Ganesh; Banerjee, Prabal; Gadre, Smita R. (Chemical Reviews, 2006)

Contrasting solid-state structures of trithiocyanuric acid and cyanuric acid - Guo, F.; Cheung, E. Y.; Harris, Kenneth D. M.; Pedireddi, V. R. (Crystal Growth & Design, 2006)
Although trithiocyanuric acid (TTCA) has been investigated widely as an agent in the formation of molecular cocrystals, the crystal structure of pure TTCA has never been determined. Attempts to grow crystals of pure TTCA by crystallization from solution invariably lead to the formation of solvate cocrystals, and desolvation of these materials leads to polycrystalline powder samples. In this paper, we report the structure determination of pure TTCA directly from powder X-ray diffraction data, using the direct-space genetic algorithm technique for structure solution followed by Rietveld refinement. The structure presents interesting contrasts to that of the oxygen analogue, cyanuric acid, and alludes to the possibility that both compounds might be capable of exhibiting polymorphism.

Control of molecular structure in the generation of highly luminescent liquid crystalline perylenebisimide derivatives: synthesis, liquid crystalline and photophysical properties - Jancy, B.; Asha, S. K. (Journal of Physical Chemistry B, 2006)
We report here, for the first time, the role of the molecular design on the liquid crystalline and solid-state photoluminescent properties of soluble and thermally stable liquid crystalline perylenebisimide derivatives. A new series of perylenebisimides were designed and developed for this purpose by adopting the stoichiometry-control approach, and amine-, hydroxyl-, ester-, and amide-functionalized molecules were synthesized. Various types of spacers with different lengths (C2 to C12), types (linear, cyclohexyl, and tricyclodecane), and end-capped by phenyl or tridodecyloxy gallic units were introduced in the perylenebisimide core. The molecules were completely characterized by NMR, FT-IR, SEC, and MALDI-TOF mass techniques. Thermal analysis revealed that the perylenebisimide derivatives were thermotropic liquid crystalline, and threadlike nematic phases were observed under a polarizing light microscope. The spacer length and the rigidity of the spacers play a major role in the liquid crystalline properties of the materials. In phenyl systems, the C6 chain with ester- and the C12 chain with amide-end-capped molecules showed a nematic phase, whereas the C6 chain with an amide end cap and their cyclic and tricyclic counterparts did not show any LC property. The introduction of a tridodecyloxy gallic unit induced the LC property in C12 and the cyclohexyl system; however, it failed to do so in the tricyclodecane molecule. The absorption properties of the molecules were almost unchanged by the structural variation; however, the emission quantum yield in solution and photoluminescent (PL) intensity in the solid state were significantly different. Though the gallic unit induced liquid crystallinity in the perylenebisimide core, the quantum yield and PL intensity are 4−5 times less compared to those of the simple phenyl-capped liquid crystalline system. Among the various types of spacers, the tricyclodecane induced strong molecular aggregates via π-stacking, which in turn increased the rigidity of the entire perylenebisimide core, resulting in the absence of liquid crystallinity and low luminescence compared to their linear and cyclohexyl analogues. The molecular aggregates were very stable even at very dilute concentration and also at high temperatures. The aggregates disappeared immediately upon addition of trifluoroacetic acid, thus confirming the strong hydrogen bonding in the aggregated states. In a nutshell, the present report demonstrates the importance of molecular design for introducing liquid crystalline phases in perylenebisimides and also the development of novel highly luminescent n-type π-conjugated material for application in optoelectronics.

Control of stereoselectivity in 4-tert-butylphenol hydrogenation over a carbon-supported rhodium catalyst by carbon dioxide solvent - Hiyoshi, Norihito; Mine, Eiichi; Rode, Chandrashekhar V.; Sato, Osamu; Ebina, Takeo; Shirai, Masayuki (Chemistry Letters, 2006)
cis-4-tert-Butylcyclohexanol was obtained with a high cis ratio (cis/(cis + trans) = 0.9) in the hydrogenation of 4-tert-butylphenol over a carbon-supported rhodium catalyst along with hydrochloric acid in supercritical carbon dioxide solvent.

Convenient chemoenzymatic synthesis of (1S,7aS)-1-hydroxy-5-oxo-4-(2 `-carboxyethyl)-7a-methyltetrahydro-indane - a key intermediate of steroids - Kalkote, Uttam R.; Purude, A. N.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Molecular Catalysis B-Enzymatic, 2006)
A porcine pancreatic lipase mediated enzymatic hydrolysis of (+/-)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydroindane (5b) furnished (1S,7aS)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (9) and (1R,7aR)-1-hydroxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (8) with > 99% e.e. which on further chemical hydrolysis gave 1 and ent-1, key intermediates of steroids. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemoenzymatic method; Enzymatic hydrolysis; steroids; terpenoids

Convergent approach toward the synthesis of the stereoisomers of C-6 homologues of 1-deoxynojirimycin and their analogues: evaluation as specific glycosidase inhibitors - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M. (Journal of Organic Chemistry, 2006)
A new and stereoselective strategy is developed to synthesize an appropriate template 9 to obtain C-6 homologues of 1-deoxyazasugars such as 1-deoxy-D-galactohomonojirimycin ( 5), 1-deoxy-4-hydroxymethyl-D-glucohomonojirimycin (6), and their enantiomers. The template 9 is also used to obtain neutral nonbasic pseudo-glyconolactam (8), C-4 amino, and methyl analogues of 1-deoxy- homonojirimycin as new analogues of 1- deoxyhomoazasugars. Compound 5 is found to be a potent and specific inhibitor to alpha-galactosidase (K-i = 1.7 mu M). Similarly compounds 6 (K-i = 28 mu M), ent-5 (K-i = 129 mu M), and ent-6 K-i = 12 mu M) exhibited specific inhibition of beta-glucosidase.

Copper-, ligand- and solvent-free synthesis of ynones by coupling acid chlorides with terminal alkynes - Palimkar, Sanjay S.; Kumar, P. Harish; Jogdand, Nivrutti R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron Letters, 2006)
A general and efficient copper-, ligand- and solvent-free synthesis of ynones by coupling of a wide range of acid chlorides with terminal alkynes catalyzed by palladium(II) acetate at room temperature is reported. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ligandless; neat; ynones

Co-precipitation technique for the preparation of ferroelectric BaBi2Ta2O9 - Dhage, S. R.; Pasricha, R.; Murugan, A. Vadivel; Ravi, V. (Materials Chemistry and Physics, 2006)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase BaBi2Ta2O9 (BBT). Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Ta5+ cations simultaneously. No pyrochlore phase was found while heating powder at 800 degrees C and pure BaBi2Ta2O9 phase was found to be formed by X-ray diffraction. Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 350. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Coprecipitation technique to prepare LiTaO3 powders - Navale, SC; Gaikwad, A. B.; Ravi, V (Materials Letters, 2006)
A simple coprecipitation technique had been successfully applied for the preparation of pure ultrafine single phase LiTaO3 (LT). An aqueous mixture of ammonium carbonate and ammonium hydroxide was used to precipitate Li+ and Ta5+ cations as carbonate and hydroxide respectively. This precursor oil heating at 750 degrees C produces LT powders. For comparison, LT powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction

Coprecipitation technique to prepare NaNbO3 and NaTaO3 - Samuel, V; Gaikwad, A. B.; Ravi, V (Bulletin of Materials Science, 2006)
A simple coprecipitation technique has been used successfully for the preparation of pure, ultrafine, single phases of NaNbO3 (NN) and NaTaO3 (NT). An alcoholic solution of ammonium carbonate and ammonium hydroxide was used to precipitate Na+ and Nb5+ (or Ta5+) cations under basic conditions as carbonate and hydroxide, respectively. On heating at 700 degrees C, these precursors produce respective products. For comparison, both NN and NT powders were also prepared by the traditional solid state method. The phase purity and lattice parameters were studied by powder X-ray diffraction (XRD). The particle size and morphology were studied by scanning electron microscopy (SEM).
Keywords: Ceramics; Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods

Coprecipitation technique to prepare Sr0.5Ba0.5Nb2O6 - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Bulletin of Materials Science, 2006)
An aqueous mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and strontium ions as oxalates and niobium ions as hydroxide under basic conditions. This precursor on calcining at 750 degrees C yielded Sr0.5Ba0.5Nb2O6 phase. This is a much lower temperature than that prepared by traditional solid state method (1000 degrees C) as reported for the formation of Sr0.5Ba0.5Nb2O6 (SBN). Transmission electron microscopic (TEM) investigations revealed that the average particle size was 80 nm for the calcined powders. The room temperature dielectric constant at I kHz was found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides; X-ray diffraction

Crystalline phases in nylon-11: studies using HTWAXS and HTFTIR - Nair, S. S.; Ramesh, C.; Tashiro, K. (Macromolecules, 2006)
Nylon-11 was crystallized into different crystalline phases by appropriate methods. The chance in the structure during heating was monitored in situ by wide-angle X-ray scattering (WAXS). The alpha phase obtained by precipitating nylon-11 in 1,4-butanediol started transforming into the pseudohexagonal phase on heating, but the transformation was not fully completed before melting. The melt crystallized sample at 175 degrees C gave the pseudohexagonal phase, which transformed into the alpha' phase on cooling to room temperature at about 100 degrees C. The d spacing of the 00 1 reflection also showed a change at the transition temperature. The melt-quenched sample showed the pseudohexagonal phase, which did not change during heating, but on cooling transformed into alpha' phase. The gamma phase was obtained by casting nylon-11 in trifluoroacetic acid (TFA), and it changed into the pscudohexagonal phase at about 110 degrees C on heating. The d spacing of the 001 reflection depended on the way in which it was obtained. The studies have shown that nylon-11 is one of the few nylons that exhibit an extensive degree of polymorphism. High-temperature Fourier transform infrared spectroscopy (HTFTIR) studies revealed, apart from the conformational differences between various phases of nylon-11, some information on the formation of the gamma phase.

Crystallisation in polymer nanocomposites - Jog, Jyoti Prakash (Materials Science and Technology, 2006)
Polymer nanocomposites are of interest as they exhibit extraordinary properties compared with the base polymer. The second phase dispersed in the polymer matrix can be carbon nanotubes, semi-conducting inorganic nanoparticles or layer silicates such as clay. Crystallisation in these materials is also of great interest. Polymers exhibit structures at various scales (e.g. lamella, unit cell and spherulites) and the presence of a second phase has a profound effect on crystallisation. General trends observed include acceleration/retardation of crystallisation, changes in spherulite morphology and, in a few cases, changes in the crystal structure. All these observations relate to the presence of a micrometre scale second phase. However, when the dimensions of the second phase are close to the chain dimensions, the effects on crystallisation become particularly interesting. An attempt is made in the present review to address the effect of a nanoscale second phase on aspects such as isothermal and non-isothermal crystallisation, spherulite growth, phase transformation and polymorphism.
Keywords: clay; crystallisation; Nanocomposites; polymer matrix composites

Crystallization and phase transformation kinetics of poly(1-butene)/MWCNT nanocomposites - Wanjale, Santosh D.; Jog, Jyoti Prakash (Polymer, 2006)
Poly(1-butene)/MWCNT nanocomposites were prepared by simple melt processing technique. Crystallization, crystal-to-crystal phase transformation and spherulitic morphology were studied using differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and optical microscopy (OM). The non-isothermal crystallization exhibited higher values of Z, derived from Avrami theory and lower values of F(T) obtained from Avrami-Ozawa analysis, while the isothermal crystallization revealed a significant increase in crystallization temperatures and lower crystallization half times compared to pristine PB. The observed changes in the crystallization kinetics were ascribed to the enhanced nucleation of PB in the presence of MWCNT. The nucleating activity calculated from the non-isothermal crystallization data revealed that the MWCNTs provide an active surface for the nucleation of PB. The optical micrographs exhibited significantly smaller crystallites with disordered morphology for the nanocomposites compared to the well defined spherulitic morphology for pristine PB. The rate of phase transformation from kinetically favored tetragonal to thermodynamically stable hexagonal form was noticeably enhanced as evidenced by the reduction in the half time for phase transformation from 58 h to 25 h for PB reinforced with 7% MWCNT. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: MWCNT; Phase transformation; poly(1-butene)

Crystallization and preliminary X-ray characterization of a thermostable low-molecular-weight 1,4-beta-D-glucan glucohydrolase from an alkalothermophilic thermomonospora sp. - Manikandan, K.; Jagtap, Sharmili; Rao, M.; Ramakumar, S. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2006)
{Cellulases catalyze the hydrolysis of beta-1,4-glycosidic linkages within cellulose, the most abundant organic polymer on earth. The cellulase (TSC; EC 3.2.1.4) from an alkalothermophilic Thermomonospora sp. has a low molecular weight of 14.2 kDa. It is optimally active at 323 K and stable over the wide pH range of 5 - 9. Moreover, it has bifunctional activity against cellulose and xylan polymers. In this study, TSC was purified from the native source and crystallized by the hanging-drop vapour-diffusion method. The crystals belong to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 49.9

Cu(I)-catalyzed cycloaddition of constrained azido-alkynes: access to 12- to 17-membered monomeric triazolophanes incorporating furanoside rings - Ray, A.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mukhopadhyay, R.; Bhattacharjya, A. (Tetrahedron Letters, 2006)
A strained monomeric 12-membered triazolophane was formed by the Cu(I)-catalyzed intramolecular cycloaddition of an azide to an alkyne having a constrained tether incorporating ail aromatic ring and a furanoside ring. Similar cycloadditions of azido-alkynes having ester, furanoside and peptidic tethers led to the formation of monomeric triazolophanes of higher ring sizes. (c) 2006 Elsevier Ltd. All rights reserved.

Cu(OTf)(2) or Et3N-catalyzed three-component condensation of aldehydes, amines and cyanides: a high yielding synthesis of alpha-aminonitriles - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
Copper(II) triflate or Et3N have been found to catalyze, under ambient conditions, the addition of a cyanide anion, such as trimethylsilyl cyanide or acetone cyanohydrin, onto in situ generated imines, furnishing alpha-aminonitriles in excellent yields. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; aminonitriles; multicomponent reactions; organocatalyst; Strecker reaction

Cyanuric chloride: Trichloro-1,3,5-triazine - Haval, Kishan P. (Synlett, 2006)

Cyclitol based metal complexing agents. preference for the extraction of lithium by myo-inositol based crown-4-ethers depends on the relative orientation of crown ether oxygen atoms - Dixit, Shailesh S.; Shashidhar, M. S.; Devaraj, Subramanian (Tetrahedron, 2006)
myo-Inositol derived crown-4-ethers in which two of the oxygen atoms in the crown ether moiety have different relative orientations were prepared. Metal picrate binding studies revealed that the crown ether having 1,3-diaxial orientation shows the highest selectivity for binding to lithium although the crown ether having 1,2-diequatorial orientation exhibited the highest binding constant for lithium picrate. These results suggest that relative binding affinity of metal ions to crown ethers can be tuned by varying the relative orientation of crown ether oxygen atoms. The relevance of these results to the previously observed regioselectivity during the O-substitution of myo-inositol orthoesters is discussed. (c) 2606 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; lithium; metal complex

Carbohydrate based approach towards the synthesis of aspercyclide C - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A formal total synthesis of aspercyclide C (3) is described in which D-ribose is employed as a chiral pool material. The key step is a ring closing metathesis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: chiron approach; D-ribose; Mukaiyama reagent; ring closing metathesis (RCM); Ullmann coupling

Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

CdS quantum dots: enzyme mediated in vitro synthesis, characterization and conjugation with plant lectins - Ansary, Abu Ayoobul; Kumar, S. Anil; Krishnasastry, M. V.; Abyaneh, Majid Kazemian; Kulkarni, Sulabha K.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Biomedical Nanotechnology, 2007)
This paper presents the in vitro synthesis of CdS quantum dot nanoparticles using sulphite reductase and capping peptide in the presence of a co-factor alpha-NADPH, their characterization and conjugation with plant lectins, Jacalin and Chick pea lectin. Incubation of sulphite reductase with aqueous CdCl2, Na2SO3, and capping peptide in the presence of a-NADPH, which acts as a co-factor, resulted in the formation of CdS nanoparticles of dimensions 5-20 nm. These CdS nanoparticles were conjugated with plant lectins by EDAC mediated coupling. These observations are of significance, as it will help in the development of eco-friendly process for the formation of CdS nanoparticles and their application as fluorescent biolabels. Moreover the above studies will also help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: bio-label; CdS quantum dots; conjugation; Enzyme; in vitro synthesis; Nanoparticles

Ce-Al-MCM-41: an efficient catalyst for Mukaiyama-Michael reaction - Kalita, Pranjal; Kumar, Rajiv (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
The activity of cerium containing Al-MCM-41 mesoporous materials has been studied for carbon-carbon bond formation reaction like Mukaiyama-Michael reaction under mild liquid phase conditions. The catalysts were synthesized by hydrothermal method at 383 K for 24-36 h in Teflon-lined autoclave and characterized thoroughly by XRD, UV-VIS, TEM, EPR, XPS, (27)Al NMR, NH(3)-TPD, pyridine-IR and AAS in order to obtain well-ordered M41S type materials. The Mukiayama-Michael reactions between silyl enol ether and alpha,beta-unsaturated ketones give Michael product in very good yields (100% selectivity). The catalysts were reusable.

Central core of uprolides D and E: a survey of some ring closing metathesis approaches - Ramana, C. V.; Salian, Sumanth R.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A preliminary study dealing with the feasibility of ring closing metathesis and ene-yne ring closing metathesis to construct the central bicyclic cores of uprolides D and E was investigated. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cembranolides; ene-yne metathesis; Ring closing metathesis; Sharpless asymmetric epoxidation; uprolides D and E

Cephalexin-mediated synthesis of quasi-spherical and anisotropic gold nanoparticles and their in situ capping by the antibiotic - Jagannathan, Ramya; Poddar, Pankaj; Prabhune, Asmita (Journal of Physical Chemistry C, 2007)
Here we report, for the first time, synthesis of gold nanostructures in aqueous medium by reducing gold ions using cephalexin, a potent broad-spectrum antibiotic, where the morphology of the gold nanoparticles is found to be dependent on the concentration of chloroauric acid. The characterization techniques indicate that particle surfaces are coated with the robust layer of the antibiotic making them stable for a long time. Thus, cephalexin acts as both the reducing and the capping agent. NMR and XPS analysis indicate that the sulfur moiety is responsible for the reduction and binding process.

Characterization and catalytic activity of cobalt containing MCM-41 prepared by direct hydrothermal, grafting and immobilization methods - Bhoware, Shrikant S.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
{Cobalt containing hexagonal mesoporous molecular sieves (MCM-41) were prepared by different methods viz., direct hydrothermal synthesis, grafting and immobilization. The calcined material was characterized by various spectroscopic tools such as powder X-ray diffraction (XRD), N-2 adsorption-desorption isotherms, Fourier transformed infra-red (Fr-IR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), diffuse reflectance UV-vis and X-ray photoelectron spectroscopy (XPS). The XRD patterns show the highly intense (100) reflection peak in the range 2-3 degrees (2 theta angle), characteristic of mesoporous material. Higher order reflection peaks suggest highly ordered mesoporous structure. N2 adsorption-desorption isotherms are of type IV according to IUPAC classification and the steep rise in the isotherms in the narrow range 3.5-4.5 of relative pressure (P/P-0) is due to the condensation of N-2 gas molecules in the pores (characteristic of mesoporous structure). In FT-IR increase in the intensity of band at 960 cm(-1) with the increase of the cobalt content in Co-MCM-41 samples indicate the incorporation of cobalt ions in the framework of MCM-41. SEM and TEM reveal spherical morphology for the cobalt substituted MCM-41. UV-vis spectra demonstrate the characteristic features of framework and extraframework cobalt in MCM-41. Cobalt is in +2 oxidation state as evidenced from UV-vis and XPS. The catalysts were tested for the side chain oxidation of ethylbenzene using 70 wt.% tert-butyl hydrogen peroxide as an oxidant with and without the use of solvent. Solvents have effect in the catalytic activity and selectivity. In the absence of solvent, substituted cobalt [
Keywords: 2-butanol; cyclohexanone; Mesoporous molecular sieves; MPV reduction

Characterization of nano-sized CdS-Ag2S core-shell nanoparticles using XPS technique - Hota, G.; Idage, Susheela B.; Khilar, Kartic C. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2007)
This paper reports the use of X-ray photoelectron spectroscopy (XPS) method for the characterization of surface composition of core and shell nanoparticles. The core and shell nanoparticles were synthesized using sodium bis(2-ethylhexyl) sulfosuccinate (AOT)/n-heptane/water microemulsion technique. The post-core and partial microemulsion methods have shown promise for core and shell formation and enhanced stability and sphericity of the semiconductor nanoparticles. In addition to above technique, the core-shell nanoparticles have also been characterized using SEM-elemental detection X-ray analysis (EDAX) and results are discussed. The XPS studies of US, Ag2S, and CdS-Ag2S nanoparticles prepared by post-core/partial microemulsion methods were carried out and results are compared with physical mixing of US and Ag2S nanoparticles. The Ag/Cd atomic ratio is found to be 5 and 10 as determined by XPS methods for nanoparticles prepared by using post-core and partial microemulsion methods, respectively. These results show the formation of core and shell nanoparticles. (c) 2006 Elsevier B.V. All rights reserved.

Characterization of the proteins of bacterial strain isolated from contaminated site involved in heavy metal resistance - a proteomic approach - Bar, Chinmayee; Patil, Rajendra; Doshi, Jignesh; Kulkarni, Mahesh J.; Gade, Wasudeo N. (Journal of Biotechnology, 2007)
The present study describes response of a bacterial strain isolated from a polluted river to heavy metal toxicity. The bacterium was identified to be Klebsiella pneumoniae by biochemical tests using API 20E strips and 16S ribotyping. The isolate was studied for its tolerance to two heavy metals, i.e., cobalt (Co2+) and lead (Pb2+) by growing it in citrate mineral medium (CMM). Proteomic approach involving two-dimensional polyacrylamide gel electrophoresis (2D PAGE) and mass spectrometry (MS) was used to identify the differentially expressed proteins under heavy metal stress. Two of the differentially expressed proteins were identified to be L-isoaspartate protein carboxymethyltransferase type II and DNA gyrase A. To our knowledge, this is for the first time that K pneumoniae has been reported to be present in metal contaminated site and L-isoaspartate protein carboxymethyltransferase type II protein to be over expressed under heavy metal stress. The role of these proteins in metal tolerance is discussed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2D PAGE; heavy metal toxicity; Mass spectrometry

Chemical, thermal and pH-induced equilibrium unfolding studies of fusarium solani lectin - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The effect of urea, guanidine thiocyanate, temperature and pH was studied on the conformational stability of Fusarium solani lectin. Equilibrium unfolding with chemical denaturants showed that the lectin was least stable at pH 12 and maximally stable at pH 8.0 near its pI ( 8.7). Guanidine thiocyanate ( the concentration of denaturant at which the protein is half folded, D-1/2 = 0.49 M at pH 12) was found to be an eight times stronger denaturant than urea (D-1/2 = 3.88 M at pH 12). The unfolding curves obtained with fluorescence and CD measurements showed good agreement indicating a monophasic nature of unfolding and excluded the possibility of formation of any stable intermediate. The effect of pH on the lectin was found to be unusual as at acidic pH, the lectin showed a flexible tertiary structure with pronounced secondary structure, and retained its hemagglutinating activity. On the other hand, the lectin did not show any loss of conformation or activity upto 70 degrees C for 15 min. Moreover, thermal denaturation did not result in the aggregation or precipitation of the protein even at high temperatures. Thermal denaturation was also carried out in the presence of a low concentration of guanidine thiocyanate. Change in the enthalpy of transition (Delta H-m) varied linearly with transition temperature (T-m), which indicated that the heat capacity (Delta C-p =3.95 kJ (.) mol(-1) (.) K-1) of the lectin remained constant during the unfolding.
Keywords: Denaturation; Fusarium solani; guanidine; Lectin; thermal; Unfolding

Chemoselective alkane oxidations by reactive superoxovanadium(V) species in vanadosilicate molecular sieves - Srinivas, D.; Ratnasamy, P. (From ZEOLITES to Porous Mof Materials: The 40th Anniversary of International ZEOLITE Conference, Proceedings of The 15th International ZEOLITE Conference, 2007)
Unlike their titanium analogs, vanadosilicate molecular sieves catalyze the oxidation of the terminal (primary) C-H bonds in paraffins. This dissimilarity is attributed to differences in the type of reactive superoxo species generated on contact with oxidant. The latter were identified and characterized by in situ EPR and DRUV-vis spectroscopic techniques. By a suitable choice of silicate structure (VS-1 or V-MCM-41), solvent and oxidant (H(2)O(2), tert.-butyl hydroperoxide or H(2)+O2()), the V-O bond covalency and mode of O-O bond cleavage in the oxo-species and thereby, the chemoselectivity in the oxidation of the terminal carbon atoms in paraffins could be controlled.

Cholesterol-linked beta-cyclodextrin - a thermotropic liquid-crystalline derivative - Shaikh, Vasi Ahmed Ebrahim; Lonikar, Shrikant Vitthal; Dhoble, Deepa Arun; Pawar, G. M. (Bulletin of the Chemical Society of Japan, 2007)
Liquid-crystalline derivative of ss-cyclodextrin (BCD) was prepared by covalent linking of monocholesteryl succinate (ChMS) with ss-cyclodextrin. To the best of our knowledge, this was first ever attempt so far of its kind, in which BCD has been converted into its liquid-crystalline derivative through covalent linkage of a mesogen. The degree of substitution (DS) obtained was approximate to 2.00. The product was characterized by various techniques, such as FT-IR, NMR, DSC, hot-stage-coupled optical polarizing microscopy (OPM), microanalysis and chemical methods. Cholesterol-linked ss-cyclodextrin (CDCh) derivative was found to exhibit thermotropic liquid-crystalline behavior. The product exhibited birefringence during first heating above 130 degrees C, and it became isotropic at about 180 degrees C, whereas the parent compound BCD decomposed without melting above 250 degrees C. A comparison of CDCh derivative to similar liquid-crystalline polysaccharide derivatives is presented.

Chromium-containing small pore mesoporous silicas: synthesis, characterization and catalytic behavior in the liquid phase oxidation of cyclohexane - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Applied Catalysis A-General, 2007)
Organic-inorganic hybrid mesoporous silica materials containing chromium and various organo trialkoxysilanes (chloropropyl, vinyl, methyl) were prepared by the co-condensation method, in the presence of cetyl trimethyl ammonium surfactants. The hybrid material, containing chromium, retains one X-ray diffractogram (XRD) peak up to a molar ratio of 1: 1 between tetra ethyl orthosilicate (TEOS) and organosilane in the synthesis gel. Small pore mesoporous chromium-silica samples can be prepared from the large pore hybrid mesoporous chromium samples by calcination. By this method, the pore size of the material can be tailored into the supermicroporous region, without changing the chain length of the surfactant used in the assembly process, as judged from the XRD and N-2 sorption isotherms. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups, such that the chloro propyl and vinyl pendant mesoporous material show more pore size shrinkage than the smaller methyl pendant units. Because of the tailorable pore size and with better textural characteristics, the chromium samples show better catalytic activity in the aerial oxidation reaction of cyclohexane than the conventional chromium-containing mesoporous material, like Cr-MCM-41, under a solvent free system. Among the porous chromium catalysts, the samples prepared using chloro propyl silane show higher cyclohexane conversion and cyclohexanone selectivity and behave as a true heterogeneous catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chromium; Cyclohexane; Oxidation; small pore silicas

CO2 reforming of methane to syngas over highly active and stable supported CoOx (accompanied with MgO, ZrO2 or CeO2) catalysts - Mondal, Kartick C.; Choudhary, Vasant R.; Joshi, Upendra A. (Applied Catalysis A-General, 2007)
{Catalytically inactive CoOx-MgO (calcined at 900 degrees C) becomes highly active and selective in the CO2 reforming of methane to syngas when it is deposited on a commercial low surface-area macro-porous silica-alumina support (SA-5205) or when CoOx is deposited on the support precoated with MgO. Both the supported CoOx and MgO containing catalysts (CoOx -MgO/SA-5205 and CoOx/MgO/SA-5205) show high methane conversion (> 98%) activity and H-2 selectivity (> 94%) and also high stability against carbon deposition [
Keywords: arylboronic acids; diarylmethylidenefluorene; dibromomethylidenefluorene; Pd-mediated coupling; Suzuki reaction

Cobalt-salen intercalated montmorillonite catalyst for air oxidation of p-cresol under mild conditions - Rode, Chandrashekhar V.; Kshirsagar, Vikas S.; Nadgeri, Jayprakash M.; Patil, Kashinath R. (Industrial & Engineering Chemistry Research, 2007)
Air oxidation of p-cresol under very mild conditions (338 K and ambient pressure) was carried out in a semibatch reactor over a solid catalyst developed by intercalating cobalt-salen into the montmorillonite clay. The intercalation of cobalt - salen was done by a simple protocol, and the characterization of the intercalated catalyst was done by XPS, FTIR, and XRD techniques. A total selectivity >= 90% to the oxidation products could be achieved with this solid catalyst by eliminating the undesired coupling side products in air oxidation of p-cresol under ambient pressure conditions. Effect of various process parameters on the conversion and selectivity pattern were also studied, and it was found that the selectivity ratio of aldehyde to alcohol could be varied by suitably changing the reaction conditions. This heterogeneous catalyst was found to give a 5-fold higher turnover number than the homogeneous cobalt - salen complex.

Comparative catalytic activity of Mn(Salen) complexes grafted on SBA-15 functionalized with amine, thiol and sulfonic acid groups for selective aerial oxidation of limonene - Salkia, Lakshi; Srinivas, Darbha; Ratnasamy, Paul (Microporous and Mesoporous Materials, 2007)
SBA-15 molecular sieves were functionalized with propylamine, propylthiol and propylsulfonic acid groups. Mn(Salen)Cl complexes were grafted on these organo-functionalized SBA-15. The support and the type of organo-functional group influenced the electronic structure (oxidation state and redox behavior) and chemo selectivity of the Mn-complexes in the oxidation of limonene. The Mn ions were reduced from +3 to +2, the extent of this reduction on different supports decreasing in the order: SBA- 15-pr-SH > SBA- 15-prSO(3)H > SBA-15-pr-NH2- Mn(Salen)Cl supported on propylthiol-functionalized SBA-15 yielded the 1,2-limonene epoxide with 100% chemo- and regioselectivity. Higher electron density at the site of Mn ions and the consequent lower redox potential of the Mn-complexes on immobilization are the probable causes for their efficient and selective catalytic activity. Solvents, additives (N-MeIm) and co-reagents (iso-butyraldehyde), which facilitated formation of Mn2+ ions, enhance the catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction and the extent of this with different catalysts decreased in the order: SBA-l5-pr-NH2-Mn(Salen)Cl > SBA- 15-pr-SO3H-Mn(Salen)Cl > SBA- 15-pr-SH-Mn(Salen)Cl. (C) 2007 Elsevier Inc. All rights reserved

Complex carbohydrate specificity of lectin from fruiting body of ganoderma lucidum. a surface plasmon resonance study - Thakur, Atul; Pal, Lakhan; Ahmad, Absar; Khan, Mohammad Islam (IUBMB Life, 2007)
The thermodynamics and kinetics of binding of glycans and glycoproteins to Ganoderma lucidum lectin was studied using surface plasmon resonance. The lectin showed highest affinity for asialo triantennary N glycan (Ka = 3.52 x 10(5)) among the glycans tested. There was a several fold increase in affinity for glycoproteins compared to their corresponding glycans and coincident increase in contribution from enthalpy (Delta H), suggesting the involvement of hydrogen bonding in the interaction as well as involvement of protein-protein interactions. Increased affinity also showed increase in unfavorable negative binding entropy (Delta S) which was compensated with higher enthalpy. The glycoproteins showed faster association rates (k(1)) and the activation energy (E-1(double dagger)) in the association process was much lower for the glycoproteins than glycans, resulting in their faster associations. These observations elaborate the role of protein matrix in lectin-glycoconjugate interaction.
Keywords: ganoderma lucidum; glycans; Lectin; SPR

Concise synthesis of beta-blockers (S)-metoprolol and (S)-betaxolol using hydrolytic kinetic resolution - Muthukrishnan, Murugan; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A. (Tetrahedron, 2007)
Enantiopure (S)-metoprolol and (S)-betaxolol were prepared in an extremely simple and practical way using Jacobsen's hydrolytic kinetic resolution of terminal epoxides in isopropanol. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: beta-blockers; betaxolol; Hydrolytic kinetic resolution; metoprolol

Concise synthesis of (-)-deoxoprosopinine - Pandey, Satyendra Kumar; Kumar, Pradeep (Synlett, 2007)
A simple and highly efficient approach to (-)-deoxoprosopinine from racemic epoxide as a starting material is described employing a Jacobsen's hydrolytic kinetic resolution (HKR) and Sharpless asymmetric dihydroxylation (AD) as key steps.
Keywords: hydroboration-oxidation; Jacobsen's HKR; Piperidine alkaloids; sharpless AD; Total synthesis

Conductance switching in an organic material: from bulk to monolayer - Rath, Arup Kumar; Pal, Amlan J. (Langmuir, 2007)
Fluorescein sodium, which does not exhibit electrical bistability in thin films, can be switched to a high conducting state by the introduction of carbon nanotubes as channels for carrier transport. Thin films based on fluorescein sodium/carbon nanotubes display memory switching phenomenon among a low conducting state and several high conducting states. Read-only and random-access memory applications between the states resulted in multilevel memory in these systems. Results in thin films and in a monolayer (deposited via layer-by-layer assembly) show that instead of different molecular conformers, multilevel conducting states arise from the different density of high conducting fluorescein molecules.

Confinement of nano CdS in designated glass: a novel functionality of quantum dot-glass nanosystems in solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Apte, Sanjay K.; Sonawane, Ravindra S.; Naik, Sonali D.; Patil, Kashinath R. (Journal of Materials Chemistry, 2007)
The present work is the investigation of our novel approach to designing quantum dot-glass nanosystems by confining nano CdS in designated glass and the first employment of such a quantum dot system in solar hydrogen production. The CdS quantum dots were grown in a special glass matrix, which involved a sequence of steps. The obtained glass was of uniformly bright yellow in color and the bulk glass was pulverized to a fine powder of micron size particles. The glass powder was characterized structurally and morphologically. X-Ray diffraction and electron diffraction patterns reveal a hexagonal crystallite system for the CdS quantum dots. Field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, X-ray fluorescence spectroscopy and chemical leaching with HCl studies demonstrate that the 2.5 nm size CdS quantum dots distribute homogeneously in a monodispersed form in the glass domain and on the surface with a ``partially embedded exposure'' configuration. This disposition imparts an excellent photostability against photocorrosion and also a facile catalytic function. Therefore, even a very small amount of CdS quantum dots (0.005 g per gram of glass powder) is able to photodecompose H2S under visible light (lambda >= 420 nm) both in alkaline and pure aqueous media and produce solar hydrogen with markedly high quantum yields of 17.5 and 11.4%, respectively at 470 nm. Salient features like reusability after simple washing, corrosionless-stability and remarkable catalytic activity of this quantum dot-glass nanosystem are brought forth by our novel catalyst design and are much acclaimed in large scale solar H-2 production.

Constrained variational response to fock-space multi-reference coupled-cluster theory: formulation for excited-state electronic structure calculations and some pilot applications - Manohar, Prashant Uday; Pal, Sourav (Computational Methods in Science and Engineering Vol 1: Theory and Computation: Old Problems and New Challenges, 2007)
Fock-space (FS) multi-reference (MR) coupled-cluster (CC) method has emerged as compact tool to account for electronic structure of open-shell systems and molecules in low-lying excited states. Development of linear response (LR) has been one of the challenging problems in FSMRCC due to multiple-root nature of effective Hamiltonian. The recently developed constrained variational approach (CVA) has opened up a promising tool for efficient evaluation of analytic response properties. In this article, we present formulation of the method for excited state calculations. We discuss the decoupling of equations as a result of spin-adaptation and present some preliminary results for analytical dipole moments and polarizabilities of some molecules in low-lying triplet excited states.
Keywords: CVA; Dipole moment; excited states; FSMRCC; polarizability

Controlled aggregation of gold nanoparticle networks induced by alkali metal ions - Tamang, Sudarsan; Hotha, Srinivas; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
Gold nanoparticle networks were obtained by linking them with cysteine modified triethyleneglycols. The oligo-ether linker molecule initially having a linear structure probably adopts a crown ether type structure upon complexation with alkali metal ions that leads to a controlled aggregation of the network. The extent of aggregation depends on the degree of conformational change in the molecule upon complexation with the metal ion, which in turn is governed by the metal ion radius leading to a dependence of red shift of the surface plasmon resonance on the metal ion radius. Since this network is present in the organic solvent they also act as phase transferring agent for the alkali metal ions from aqueous to organic media.
Keywords: Aggregation; Alkali Metal Ions; Au Nanoparticles; Crown Ether; Surface Plasmon Resonance

Controlled covalent functionalization of multiwalled carbon nanotubes using [4+2] cycloaddition of benzocyclobutenes - Sakellariou, Georgios; Ji, Haining; Mays, Jimmy W.; Hadjichristidis, Nikos; Baskaran, Durairaj (Chemistry of Materials, 2007)

Controlled synthesis of low-molecular-weight polyethylene waxes by titanium-biphenolate-ethylaluminum sesquichloride based catalyst systems - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Applied Polymer Science, 2007)
Soluble complexes of titanium(IV) bearing sterically hindered biphenols, such as biphenol, 1,1'-methylene di-2-naphthol, 2,2'-methylene bis(4-chlorophenol), 2,2'-methylene bis(6-tert-butyl-4-ethyl phenol), and 2,2' ethylidene bis(4,6-di-tert-butyl phenol), were prepared and characterized. These catalyst precursors, formulated as [Ti((OO)-O-boolean AND)X-2], were active in the polymerization of ethylene at high temperatures in combination with ethylaluminum sesquichloride as a cocatalyst. The ultra-low-molecular-weight polyethylenes (PEs) were linear and crystalline and displayed narrow polydispersities. The catalytic polymerization leading to PE waxes in this reaction exhibited unique properties that have potential applications in surface coatings and adhesive formulations. (c) 2007 Wiley Periodicals, Inc.
Keywords: Catalysts; polyethylene (PE); synthesis; Ziegler-Natta polymerization

Convenient chromatography-free access to enantio-pure 6,6’-di-tert-butyl-1,1’- binaphthalene-2,2’-diol- its 3,3’-dibromo, di-tert-butyl and phosphorus derivatives: utility in asymmetric synthesis - Balaraman, Ekambaram; Swamy, K. C. Kumara (Tetrahedron-Asymmetry, 2007)
A simple chromatography-free high-yielding synthesis of the hexane-soluble enantiopure 6,6′-di-tert-butyl-1,1′-binaphthalene-2,2′-diol 3 (6,6′-di-tert-butyl BINOL) using Friedel–Crafts reaction on 1,1′-binaphthalene-2,2′-diol 1 (BINOL) is described. The enantiomeric purity was fully maintained in the reaction. Compound 3 has been used as an entry point for the convenient chromatography-free synthesis of 3,3′,6,6′-tetra-tert-butyl BINOL 4 and 3,3′-dibromo-6,6′-di-tert-butyl BINOL 5. A straightforward route to enantiopure bisphosphites [(6,6′-R2C20H10O2)P]2[O2C20H10-6,6′-R2] [R = H 15, t-Bu 16] by simply reacting phosphorochloridite (6,6′-R2C20H10O2)PCl [R = H 20, t-Bu 6] with metallic sodium is highlighted. The identity of 15 and 16 as their selenium-oxidized products 17 and 18 (at phosphorus center) is confirmed by X-ray crystallography (17 in the enantiopure form and 18 as racemate). Various enantiopure phosphoramidites of the modified BINOL have been synthesized. It is established that even when the phosphoramidites derived from the unsusbstituted BINOL 1 fail to give an appreciable optical induction in the asymmetric reduction of acetophenone/phenacyl chloride, those derived from 3 do induce moderate chiral induction (up to 30% ee in the case for acetophenone and 43% ee in the case of phenacyl chloride), thus leaving scope for further improvement in ee for related reactions.

Convenient formal synthesis of (+/-)-paroxetine - Chavan, Subhash P.; Khobragade, Dushant A.; Pathak, Ashok B.; Kalkote, Uttam R. (Synthetic Communications, 2007)
A formal total synthesis of antidepressant (+/-)-paroxetine employing a solvent-free Heck reaction is disclosed.
Keywords: antidepressants; carbamate; electrophile; Heck reaction; piperidines

Copolyesters based on poly(butylene terephthalate)s containing cyclohexyl and cyclopentyl ring: Effect of molecular structure on thermal and crystallization behavior - Sandhya, T. E.; Ramesh, C.; Sivaram, S. (Macromolecules, 2007)
In an effort to understand the role of molecular structure on the thermal properties of polyesters and copolyesters, the following polyesters were synthesized: poly(1,4-cyclohexane dimethylene terephthalate) (PCT), poly(butylene-1,4-cyclohexane dicarboxylate) (PBCD), poly (1,3-cyclopentane dimethylene terephthalate) (PCPDT), and poly(butylene-1,3-cyclopentane dicarboxylate) (PBCP). PCT and PCPDT are semicrystalline polymers with crystallization and melting temperatures higher than poly(butylene terephthalate) (PBT). However, PBCD and PBCP have lower glass transition temperature than PBT. From these homopolymers a series of poly(butylene-co-1,4-cyclohexane dimethylene terephthalate) (P(BT-co-CT )), poly(butylene terephthalate-co-1,4cyclohexane dicarboxylate) (P(BT-co-BCD)), poly(butylene-co-1,3-cyclopentylene dimethylene) (P(BT-co-CPDT)), and poly(butylene terephthalate-co-1,3-cyclopentane dicarboyxlate) (P(BT-co-PBCP)) random copolyesters were synthesized for the first time, and their cocrystallization behavior was investigated using differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WAXD). The copolymers were found to be statistically random and crystallized in all compositions. The P(BT-co-CT) and (P(BT-co-CPDT) copolyesters exhibited typical eutectic behavior in melting and crystallization, which indicated isodimorphic cocrystallization behavior. On the other hand, in the case of P(BT-co-BCD) and P(BT-co-PBCP) copolymers, the melting and crystallization temperatures showed linear dependency with composition, indicating isomorphic-like crystallization behavior.

Copper phthalocyanine films deposited by liquid-liquid interface recrystallization technique (LLIRCT) - Patil, K. R.; Sathaye, S. D.; Hawaldar, Ranjit R.; Sathe, B. R.; Mandale, A. B.; Mitra, A. (Journal of Colloid and Interface Science, 2007)
The simple recrystallization process is innovatively used to obtain the nanoparticles of copper phthalocyanine by a simple method. Liquid-liquid interface recrystallization technique (LLIRCT) has been employed successfully to produce small sized copper phthalocyanine nanoparticles with diameter between 3-5 nm. The TEM-SAED studies revealed the formation of 3-5 nm sized with beta-phase dominated mixture of alpha and beta copper phthalocyanine nanoparticles. The XRD, SEM, and the UV-vis studies were further carried out to confirm the formation of copper phthalocyanine thin films. The cyclic voltametry (CV) studies conclude that redox reaction is totally reversible one electron transfer process. The process is attributed to Cu(II)/Cu(I) redox reaction. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: Copper phthalocyanine; cyclic voltametry; nanoparticulate films

Copper(II) ion exchanged A1SBA-15: a versatile catalyst for intermolecular hydroamination of terminal alkynes with aromatic amines - Shanbhag, Ganapati V.; Joseph, Trissa; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
The hydroarnination reaction offers a very attractive route for the synthesis of alkylated amines and their derivatives with no byproduct formation. AISBA-15 was synthesized by isomorphous substitution of aluminum into the framework of SBA-15, which induces the Bronsted acid sites, and these were exchanged with metal ions such as Cu2+, Zn2+, and Pd2+. The catalysts were characterized by XRD, N-2-sOrption, SEM, TEM, acidity measurements by FT-IR pyridine adsorption, H-2-TPR, (27)AI MAS NMR, and Si-29 MAS NMR. Hydroamination of phenylacetylene (PhAc) with 2,4-xylidine has been used as a test reaction, which gave N-(1-phenylethylidene)-2,4-dimethylaniline with no byproduct formation. CuAlSBA-15 and CuAIMCM-41 showed around three times greater activity in hydroamination of PhAc compared with Cu-clay and Cu-beta, due to the moderate Lewis acidity of Cu2+ present in mesoporous supports. The performance of the CuAlSBA-15 was also determined with different alkynes and amines to evaluate the catalyst's general applicability in hydroamination reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: A1SBA-15; addition; alkyne; Amine; Copper catalyst; heterogeneous; hydroamination; ion exchange; Mesoporous

Co-precipitation technique to prepare BaTa2O6 - Navale, S. C.; Samuel, Violet; Gaikwad, A. B.; Ravi, V. (Ceramics International, 2007)
A mixture of ammonium oxalate and ammonium hydroxide was used to co-precipitate barium and tantalum ions as barium oxalate and tantalum hydroxide under basic conditions. On calcination at 750 degrees C, this precursor yielded BaTa2O6 (BT) ceramics. This is much lower temperature as compared to that prepared by traditional solid-state method (1000 degrees C) as reported for the formation of BaTa206. Transmission electron microscope (TEM) investigations revealed that the average particle size is 70 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 100. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: barium tantalate; Ceramics; Electron microscopy; Oxides; X-ray diffraction

Coprecipitation technique to prepare CoTa2O6 and CoNb2O6 - Mulla, Imtiaz S.; Natarajan, N.; Gaikwad, A. B.; Samuel, V.; Guptha, U. N.; Ravi, V. (Materials Letter, 2007)
An aqueous solution of sodium hydroxide was used to coprecipitate cobalt and tantalum (or niobium) ions from their precursors as hydroxides under basic conditions. This precipitate yielded CoTa2O6 (CT) or CoNb2O6 (CN) ceramics on calcining at 700 degrees C, i.e. at a temperature much lower than 900 degrees C, reported for the formation of these powders prepared by the traditional solid state method. The X-ray diffraction (XRD) studies were employed to investigate phase contents and lattice parameters. The morphology of the synthesized powders was investigated by transmission electron microscopy (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; Oxides; X-ray methods

Coprecipitation technique to prepare NiNb2O6 - Samuel, V.; Gaikwad, A. B.; Jadhav, A. D.; Natarajan, N.; Ravi, V. (Materials Letter, 2007)
A mixture of ammonium carbonate and ammonium hydroxide was used to coprecipitate nickel and niobium ions as nickel carbonate and niobium hydroxide under basic conditions. This precursor yielded NiNb2O6 (NN) ceramics on calcining at 700 degrees C (at a temperature lower than 800 degrees C which is necessary for the formation of NiNb2O6 when prepared by the traditional solid state method). The average particle size and morphology of these powders were investigated by transmission electron microscope (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods

Correlation between mobility enhancement and conformational change in polyaniline and its derivatives: polaron lattice formation - Harima, Yutaka; Ogawa, Fumiyuki; Patil, Rahul; Jiang, Xiaoqing (Electrochimica Acta, 2007)
Conformational changes in polyaniline, poly(methyl aniline), and poly(methoxyaniline) are studied in perchloric acid and acetonitrile by means of an in situ reflection technique with oxidation level as a parameter. Stretching of polymer chains leading to enhancement of specular reflection at the polymer-coated electrodes is found to be well correlated with the increase in carrier mobility. The concomitant change in mobility and chain conformation observed with the polyaniline family is explained in terms of the formation of polaron lattice at increased oxidation levels. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Conformation; polyaniline; reflection; scattering : mobility

Corrosion protection aspects of electrochemically synthesized poly(o-anisidine-co-o-toluidine) coatings on copper - Pawar, Pritee; Gaikwad, A. B.; Patil, P. P. (Electrochimica Acta, 2007)
The poly(o-anisidine-co-o-toluidine) coatings were synthesized on copper substrates by electrochemical copolymerization of o-anisidine with o-toluidine using sodium salicylate as supporting electrolyte. These coatings were characterized by cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR) and scanning electron microscopy (SEM). The formation of the copolymer with the mixture of monomers in the aqueous sodium salicylate solution was ascertained by a critical comparison of the results obtained with the polymerization of the individual monomers, o-anisidine and o-toluidine, respectively. The corrosion protection aspects of poly(o-anisidine-co-o-toluidine) coatings to copper was investigated in aqueous 3% NaCl solution by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The results of the potentiodynamic polarization measurements and EIS studies showed that the poly(o-anisidine-co-o-toluidine) coatings provided the effective corrosion protection to copper than that of respective homopolymers. The corrosion rate is observed to depend on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: copolymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-anisidine-co-o-toluidine)

Cross- and axial-peak intensities in 2D-SLF experiments based on cross-polarization - the role of the initial density matrix - Das, Bibhuti B.; Ajithkumar, Thalasseril G.; Sinha, Neeraj; Opella, Stanley J.; Ramanathan, K. V. (Journal of Magnetic Resonance, 2007)
Simulations and experiments on simple oriented systems have been used to estimate the relative ratio of cross-peak to axial-peak intensities in 2D-SLF experiments based on dipolar oscillations during cross-polarization (CP). The density matrix prior to dipolar evolution is considered and for an isolated spin pair, it is shown that direct calculations of the ratios match well with simulations and experimental results. Along with the standard CP pulse sequence, two other pulse sequences namely CP with polarization inversion (PI-CP) and another novel variation of the standard CP experiment (EXE-CP) reported recently have been considered. Inclusion of homonuclear dipolar coupling has been observed to increase the axial-peak intensities. In combination with Lee-Goldburg (LG) decoupling, experiments on an oriented liquid crystalline sample have been carried out and the performance of the pulse schemes have been compared. The applicability of the new pulse sequence for different samples and different nuclei is discussed. Such studies are expected to lead to a better understanding of the experiments and to the design of useful pulse sequences. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: cross polarization; oriented molecules; PISEMA; SLF

Cross-linking assessment after accelerated ageing of ethylene propylene diene monomer rubber - Tomer, N. S.; Delor-Jestin, Florence; Singh, R. P.; Lacoste, Jacques (Polymer Degradation and Stability, 2007)
The ageing of filled and cross-linked ethylene propylene diene elastomer (EPDM) has been studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C, thermal ageing at 100 degrees C and in nitric acid vapours for different time intervals. Hardness measurements were performed. DSC-thermoporosimetry was used to estimate the mesh size distribution and cross-linking densities for each ageing. The development of functional groups was monitored by ATR spectroscopy. An increase in oxidation with exposure time after the different types of ageing was observed. The thermal stability of EPDM was assessed by TGA and evolved volatile gases were identified using FTIR spectroscopy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ageing; EPDM; Oxidation; thermal analysis; thermoporosimetry

Cu(OTf)(2) catalyzed high yield synthesis of hantzsch 1,4-dihydropyridines - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2007)
Copper(II) triflate catalyzes efficiently the three-component condensation of aldehydes, beta-ketoesters and ammonium acetate in acetonitrile at 25 degrees C to afford the corresponding Hantzsch 1,4-dihydropyridines in high yields.
Keywords: 4-dihydropyridines; anti-hypertensive drug; calcium channel blockers; cardiovascular diseases; Hantzsch 1; three-component condensation

Cyclic voltammetry, electrochemical impedance and ex situ X-ray diffraction studies of electrochemical insertion and deinsertion of lithium ion into nanostructured organic-inorganic poly(3,4-ethylenedioxythiophene) based hybrids - Murugan, A. Vadivel; Reddy, M. V.; Campet, Guy; Vijayamohanan, K. (Journal of Electroanalytical Chemistry, 2007)
In this work, we discuss the electrochemical insertion and deinsertion of lithium into poly(3,4-ethylenedioxythiophene) PEDOT-V(2)O(5) nanohybrids by using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and powder ex situ X-ray diffraction (XRD) studies with special emphasis on their application potential as cathode materials for rechargeable Lithium batteries. The interlayer spacing of crystalline V(2)O(5) expands from 0.43 to 1.41 nm by the intercalation of PEDOT nanoribbons prepared by a microwave irradiation method. Cyclic voltammetry studies of PEDOT-V(2)O(5) hybrid at a slow scan rate of 0.058 mVs(-1) between 2.0-4.3 V vs. Li/ Li(+), demonstrates that structural transitions Of V(2)O(5) are suppressed and more facile intercalation features appear in terms of well-defined reversible cathodic and anodic peaks when compared to that at higher scan rate. Electrochemical Impedance studies of PEDOT-V(2)O(5) hybrid as cathode at ambient temperature with lithium metal foil as both counter and reference electrodes in 1 M LiPF(6) in a mixture of ethylene and diethylcarbonate (50:50 by volume) between the range 2.0-4.3 V reveals the usefulness of these materials. The observed capacity fading during cycling in terms of surface passivation and structural transformations is also investigated by CV, EIS and XRD analysis. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ex situ XRD studies; high capacity lithium batteries; impedance studies; nanostructured hybrid materials

Calculation of vibrational energy of molecule using coupled cluster linear response theory in bosonic representation: convergence studies - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Physics, 2008)
Vibrational excited state energies have been calculated using vibrational coupled cluster linear response theory (CCLRT). The method has been implemented on formaldehyde and water molecule. Convergence studies have been shown with varying the cluster operator from S(4) to S(6) as well as the excitation operator from four bosons to six bosons. A good agreement with full configuration interaction results has been observed with S(6) truncation at coupled-cluster method level and six bosonic excitations at CCLRT level. (C) 2008 American Institute of Physics.

Capsaicin: preclinical and clinical studies - Qureshi, Absar A.; Qureshi, Azfar A.; Omer, Shaista; Sanghai, Dhirendra B.; Setty, S. R.; Bhajipale, N. S. (Plant Archives, 2008)
Drugs obtained from plant sources occupy important position in different pharmacopoeias. Many of the life saving drugs in the present day allopathic system are obtained from plant origin only. Extensive scientific research on capsaicin, a natural compound, pungent principle, present in the fruits of plant Capsicum anum, has been performed. In preclinical studies capsaicin shows lipid lowering by stimulating its metabolism, gastroprotection against aspirin and ethanol induced ulcers. Capsaicin in rodents shows anticancer activity against NKK induced lung and liver cancer. It also exhibits antidiabetic, antimicrobial, anti-inflammatory and antioxidant properties in rodents. In clinical studies Capsaicin shows gastroprotection in healthy volunteers. In double blind studies capsaicin proved to be useful in skin disorders against prutitic psoriasis and prurigo nodularis with randomized double blind studies. It also exhibits good analgesic activity against post-therapeutic neuralgia, osteo-arthritis, rheumatoid arthritis and diabetic neuropathy. Capsaicin is fairly safe with oral dose 0.5-1.0 mg/kg.
Keywords: capsaicin; Capsicum anum; clinical studies; preclinical

Carbohydrate templates for the synthesis of prototype renin inhibitors - Mohapatra, Debendra K.; Sahoo, Gokarneswar; Sankar, Kuppusamy; Gurjar, Mukund K. (Tetrahedron-Asymmetry, 2008)
A concise synthesis of a prototype renin inhibitor and its 7-epimer has been accomplished starting from readily available D-glucose. (C) 2008 Elsevier Ltd. All rights reserved.

Carbohydrate-based approach for the total synthesis of aculeatin D and 6-epi-aculeatin D - Ramana, C. V.; Srinivas, Burgula (Journal of Organic Chemistry, 2008)
A concise approach for the total synthesis of aculeatin D and 6-epi-aculeatin D employing differentially protected anti,anti-1,3,5-triol alkyne prepared from alpha-D-glucoheptonic-gamma-lactone derivative is documented. Phenol protecting group manipulation for selective O-debenzylation during the hydrogenation of the diyne intermediate and one-pot phenolic oxidation with concomitant spiroketalization highlight the accomplished total synthesis.

Carbon nano horn and bovine serum albumin hierarchical composite: towards bio-friendly superhydrophobic protein film surfaces - Jadhav, Anil D.; Ogale, Satishchandra B.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2008)
Highly hydrophilic glass substrates when coated with films of carbon nano horns dispersed in the ubiquitous protein bovine serum albumin display hydrophobic characteristics. Incidentally both the materials used to create the final hydrophobic surface are known to be highly bio-compatible. The features observed are accredited to the replication of the micro and nanoscale hierarchical structures of carbon nano horns in the final film composite.

Carbon-nitrogen bond-forming reactions of dialkyl azodicarboxylate: a promising synthetic strategy - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C.; Pattoorpadi, Beneesh Babu (Chemistry an Asian Journal, 2008)
Azodicarboxylates have found applications in electrophilic amination reactions and in pericyclic reactions. The nucleophilic trigger in Mitsunobu reactions, that is, the zwitterion formed from triphenylphosphine and dialkyl azodicarboxylate, has been utilized recently in various heterocyclic constructions. This Focus Review summarizes the potential utility of azodicarboxylates in various carbon–nitrogen bond-forming reactions.
Keywords: amination reactions; azodicarboxylates; C[BOND]N bond formation; heterocycles; Huisgen zwitterion

Catalyst-free efficient synthesis of 2-aminothiazoles in water at ambient temperature - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Tetrahedron, 2008)
A highly efficient and facile method has been described for the synthesis of substituted 2-aminothiazoles in water without any added catalyst or co-organic solvent. The reaction was carried out at ambient temperature and the products were obtained in excellent isolated yields. The developed protocol is successfully applied for the preparation of an anti-inflammatory drug, fanetizole. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 2-aminothiazoles; ambient temperature; environment-friendly synthesis; Water

Catalytic hydrogenation of 2-butyne-1,4-diol: activity, selectivity and kinetics studies - Rode, Chandrashekhar V. (Journal of the Japan Petroleum Institute, 2008)
The reaction pathway for hydrogenation of 2-butyne-1,4-diol involves parallel and consecutive isomerization as well as hydrogenation reactions forming other side products along with cis-2-butene-1,4-diol and butane-1,4-diol. Hence, achieving the highest selectivity to butene- and/or butanediol is critical from industrial point of view. Hydrogenation of butynediol is also of fundamental significance, due to its adsorption characteristics leading to the formation of active species and their role in determining the product distribution. Studies on designing various catalyst systems including colloidal as well supported palladium nanoparticles for the hydrogenation of butynediol, role of additives, catalyst pretreatment, kinetic studies carried out in our group has been presented in this review. Interestingly, almost complete selectivity to the intermediate olefinic diol was achieved with 1% Pd/CaCO3-NH3 catalyst system. This could be due to the competitive adsorption of ammonia on the palladium surface along with the substrate 2-butyne-1,4-diol. Studies on catalyst pretreatment and kinetics using palladium catalyst have also been presented here. Nanostructure palladium both colloidal as well as supported catalysts showed a very high catalytic activity (10-40 times more) in the hydrogenation 2-butyne-1,4-diol to cis-2-butene-1,4-diol compared with the corresponding conventional Pd catalysts. For platinum based catalysts, formation of side products was completely eliminated in the hydrogenation of butyne diol. The increase in the basic strength of alkali metal doped Pt catalysts measured by CO2-TPD, led to the increase in electron density of Pt hence, faster desorption and higher selectivity to butenediol. In the case of continuous hydrogenation, the selectivity pattern was completely different from that found in the case of batch slurry reactor and by varying the contact time, the selectivity to both butene- and butanediols could be varied over a wide range of conditions.
Keywords: 2-butene-1; 2-butyne-1; 4-diol; alkali metal doping; catalyst pretreatment; nano palladium catalyst; Selective hydrogenation

Cationic polymerization of epoxides using novel xanthenyl phosphonium salts as thermo-latent initiator - Gupta, Mukesh Kumar; Singh, Raj Pal (Polymer Bulletin, 2008)
The present article describes the effect of steric and electronic factors on the efficiency of initiators based on novel xanthenyl phosphonium salts for cationic polymerization of epoxide monomers. 2-substituted (I(H), I(Cl), I(Me), and I(OMe)) xanthenyl phosphonium hexafluoroantimonate were synthesized and characterized by NMR ((1)H, (13)C and (31)P) and IR spectroscopy. The order of initiator activity in polymerization of glycidyl phenyl ether (GPE), was found as I(H)> I(Cl)> I(Me)> I(OMe). To understand the effect of steric factor, the polymerization of cyclohexene oxide (CHO) was performed and the order of activity was found as I(Cl)> I(H)> I(Me) > I(OMe). All the initiators were found to be latent at ambient temperature and initiates polymerization on thermal initiation. The order of initiator activity was influenced by electronic and steric factors in the system. The thermal stability of these salts was measured by Thermo gravimetric analysis (TGA). The solubility of the initiators in various organic solvents and epoxy monomers is also discussed.

Cellular polyamines influence maturation and germination of somatic embryos from pro-embryonal masses of two grapevine cultivars - Nookapaju, A.; Barreto, M. S.; Agrawal, Dinesh C. (Vitis, 2008)
Somatic embryos of grapevine multiply repeatedly and often fail to mature and germinate due to factors like dormancy and embryo teratology. The present investigation was carried out to improve the maturation and germination of somatic embryos from pro-embryonal masses (PEM) of 2A-Clone and `Crimson Seedless', two seedless grapevine cultivars. Also, the aim was to study a correlation between cellular and residual polyamine (PA) levels in PEM and culture media. The efficiency of maturation and germination of embryos from PEM varied significantly between the two cultivars and depended on incubation period and type of PAs in the medium. HPLC analysis showed that higher levels of cellular putrescine in PEM had correlation with maturation and germination percentages in both cultivars. The levels of three PAs depleted in the media rapidly indicating its uptake by PEM. Of the three PAs, putrescine (PUT) was the most effective and resulted in 100.0 or 92.0 % maturation at 14 d or 30 d in 2A-Clone or `Crimson Seedless', respectively. The maximum germination of somatic embryos was recorded with PUT at 14 d or 21 d in 2A-Clone or `Crimson Seedless', respectively.
Keywords: germination; Grapevine; maturation; polyamines; `2A-Clone'; `Crimson Seedless'

Cellulose conversion under heterogeneous catalysis - Dhepe, Paresh Laxmikant; Fukuoka, Atsushi (ChemSusChem, 2008)
In view of current problems such as global warming, high oil prices, food crisis, stricter environmental laws, and other geopolitical scenarios surrounding the use of fossil feedstocks and edible resources, the efficient conversion of cellulose, a non-food biomass, into energy, fuels, and chemicals has received much attention. The application of heterogeneous catalysis could allow researchers to develop environmentally benign processes that lead to selective formation of value-added products from cellulose under relatively mild conditions. This Minireview gives insight into the importance of biomass utilization, the current status of cellulose conversion, and further transformation of the primary products obtained
Keywords: Biomass; cellulose; heterogeneous catalysis; supported catalysts

Cellulose supported layered double hydroxides for the adsorption of fluoride from aqueous solution - Mandal, Sujata; Mayadevi, S. (Chemosphere, 2008)
Cellulose supported layered double hydroxides (CSLDHs) were synthesized and tested for adsorption of fluoride in aqueous medium. Three samples of cellulose supported LDHs were synthesized by varying the LDH loading on cellulose. The raw cellulose, unsupported LDH and cellulose supported LDHs were characterized by XRD, SEM and BET surface area. Batch adsorption as well as fixed-bed column experiments were performed for determining the fluoride adsorption characteristics of CSLDHs. The fluoride adsorption properties of CSLDHs were found to be superior to that of reported adsorbents, including activated alumina and carbon nanotubes. Defluoridation capacity of the CSLDHs was 2-4 times higher than that of unsupported LDH. The cellulose supported LDH, CSLDH-50, having an LDH loading of 27% showed maximum fluoride uptake capacity (5.29 mg g(-1) of CSLDH, 25.18 mg g(-1) of LDH) in fixed-bed column study. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; cellulose; Fluoride; Layered double hydroxide

CFD modeling of rotary cement kilns - Mujumdar, Kaustubh S.; Ranade, Vivek V. (Asia-Pacific Journal of Chemical Engineering, 2008)
Rotary cement kilns are widely used to convert calcineous raw meal into cement clinker, and are key components in the cement industry. In this article, we report a comprehensive computational fluid dynamics (CFD)-based model to capture key transport processes in rotary cement kilns. Separate but coupled computational models were developed for the bed and the freeboard regions of the rotary kiln. The complex swirling airflow produced by kiln burners, coal combustion, gas-phase combustion of volatile matter and radiative heat transfer in the freeboard region were modeled. The clinkerization reactions in the bed region were modeled assuming solids as pseudo fluids. Coating formation in cement kilns (for both bed and freeboard regions) was considered. Appropriate source and sink terms were developed to model transfer of CO(2) from the bed to the freeboard region due to calcination reaction in the bed region. The developed bed and freeboard models were coupled by mass and energy communication through common interface. These coupled computational models were able to quite satisfactorily predict the available data from industrial kilns and previously published results. The computational models were also able to capture the intricacies of the burning zones of rotary cement kilns for changing burner-operational parameters like axial to swirl ratio and oxygen enrichment. The developed approach, computational models and simulation results will not only help in developing better understanding of cement kilns but also provide quantitative information about influence of burner design and other design parameters on kiln performance. (C) 2008 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: burner; CFD; coal combustion; rotary cement kiln

CFD simulation of gas-liquid flows in a reactor stirred by dual rushton turbines - Kasat, Gopal R.; Pandit, Aniruddha B.; Ranade, V. V. (International Journal of Chemical Reactor Engineering, 2008)
In the present work, we have simulated gas-liquid flows in a tall stirred reactor equipped with dual Rushton turbines. A two fluid model along with the standard k-epsilon turbulence model and modified drag coefficient, (proposed by Khopkar & Ranade, 2006) accounting for the effect of bulk turbulence, was used to simulate the dispersed gas-liquid flow in a stirred reactor. The multiple reference frames (MRF) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc. USA). The model was used to simulate three distinct flow regimes in a gas-liquid stirred reactor: L33-VC (lower impeller-upper impeller), S33-VC and VC-VC. The model predictions were compared with the published experimental data of Bombac & Zun (2000). The predicted results show good agreement with the experimental data for all the three flow regimes. The computational model presented in this work would be useful for simulating different flow regimes in a gas-liquid stirred vessel.
Keywords: computational fluid dynamics; dual Rushton turbine; Flow regimes; gas hold-up distribution; stirred reactor

CFD simulation of liquid-phase mixing in solid-liquid stirred reactor - Kasat, Gopal R.; Khopkar, A. R.; Ranade, V. V.; Pandita, A. B. (Chemical Engineering Science, 2008)
A comprehensive CFD model was developed to gain an insight into solid suspension and its implications on the liquid-phase mixing process in a solid-liquid stirred reactor. The turbulent solid-liquid flow in a stirred reactor was simulated using a two-fluid model with the standard k-epsilon. turbulence model with mixture properties. The multiple reference frames (MRFs) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model with necessary sub-models was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc., USA). The predicted solid concentration distribution was compared with the experimental data of Yamazaki et al. [ 1986. Concentration profiles of solids suspended in a stirred tank. Powder Technology 48, 205-216]. The computational model was then further extended to simulate and understand the implications of the suspension quality on liquid-phase mixing process. The computational model and the predicted results discussed here will be useful for understanding the liquid-phase mixing process in stirred slurry reactors in various stages of solid suspension. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: CFD; mixing; solid suspension; stirred reactor

C-glycosides of dodecanoic acid: new capping/reducing agents for glyconanoparticle synthesis - Ramana, C. V.; Durugkar, Kulbhushan A.; Puranik, Vedavati G.; Narute, Sachin B.; Bhagavatula L. V. Prasad (Tetrahedron Letters, 2008)
A concise synthesis of 12-C-glycosylated dodecanoic acids employing an olefin cross-metathesis reaction is developed. Examination of these acids as capping agents for the synthesis of metal nanoparticles reveals that they do not cap the Co-metal nanoparticles synthesized in aqueous phase, but that two of them can reduce and cap the Ag nanoparticles in water without any aggregation. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: C-Glycosides; Cross metathesis; glyconanoparticles; Grubbs' catalyst; silver nanoparticles

Changes in dynamics of SRE-RNA on binding to the VTS1p-SAM domain studied by C-13 NMR relaxation - Oberstrass, Florian C.; Allain, Frederic H. T.; Ravindranathan, Sapna (Journal of the American Chemical Society, 2008)
RNA recognition by proteins is often accompanied by significant changes in RNA dynamics in addition to conformational changes. However, there are very few studies which characterize the changes in molecular motions in RNA on protein binding. We present a quantitative C-13 NMR relaxation study of the changes in RNA dynamics in the pico-nanosecond time scale and micro-millisecond time scale resulting from interaction of the stem-loop SRE-RNA with the VTS1p-SAM domain. C-13 relaxation rates of the protonated carbons of the nucleotide base and anomeric carbons have been analyzed by employing the model-free formalism, for a fully C-13/N-15-labeled sample of the SRE-RNA in the free and protein-bound forms. In the free RNA, the nature of molecular motions are found to be distinctly different in the stem and the loop region. On binding to the protein, the nature of motions becomes more homogeneous throughout the RNA, with many residues showing increased flexibility at the aromatic carbon sites, while the anomeric carbon sites become more rigid. Surprisingly, we also observe indications of a slow collective motion of the RNA in the binding pocket of the protein. The observation of increased motions on binding is interesting in the context of growing evidence that binding does not always lead to motional restrictions and the resulting entropy gain could favor the free energy of association.

Characterization of MoSe2 thin film deposited at room temperature from solution phase - Hankare, P. P.; Patil, A. A.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Manikshete, A. H.; Mulla, Imtiaz S. (Journal of Crystal Growth, 2008)
A simple, low-temperature method has been developed to synthesis molybdenum diselenide semiconductor thin films, based on the chemical reaction of conlplexed ammonium molybdate, hydrazine hydrate and sodium Selenosulphate in aqueous alkaline medium. The deposition parameter of the MoSe2 thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption and electrical measurements. The deposited film was found to be polycrystalline in hexagonal form. The direct band gap `E-g' for the film was found to be 1.43eV and electrical conductivity in the order of 10(-2)(Omega cm)(-1) with n-type conduction mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from solution; Inorganic compound; Polycrystalline deposition; Semiconducting materials; X-ray diffraction

Characterization of smallest active monomeric penicillin V acylase from new source: a yeast, rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Prabhune, Asmita; Suresh, C. G.; Pundle, Archana (Process Biochemistry, 2008)
An intracellular monomeric penicillin V acylase (PVA) of 36,000 Da exhibiting pI of 4.19, purified from newly identified yeast source, Rhodotorula aurantiaca (NCIM 3425). The enzyme was purified by hydrophobic interaction chromatography. The enzyme showed optimal activity at 45 degrees C and retained 80% activity after incubation at 45 degrees C and pH 5.5 for I h. The enzyme showed maximum activity at pH 5.5 and was very stable between pH 5.5-6.5 with optimum stability at pH 6.0. It exhibited 50% of its original activity after 30 min incubation at 60 degrees C. Enzyme hydrolyzed substrates with benzyl side chain but preferred penicillin V as primary substrate. N-terminally located serine supports the fact that it belongs to Ntn (N-terminal nucleophile)-hydrolase superfamily. The initial ten amino acid residues of R. aurantiaca PVA were identical to the initial sequence of NADH dehydrogenase (EC 1.6.99.3): however the enzyme lacks dehydrogenase activity. EGTA, EDTA, hexane and ethyl acetate stabilized the activity where as small chain alcohols inhibited it. 1,4-Dioxane, THF (tetrahydrofurane), phenol and benzyl alcohol severely inhibited enzyme activity while BME and DTT increased it. Tween 80 and Tween 20 highly enhanced the activity where as SIDS and Triton X-100 inhibited it. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Intracellular enzyme; N-terminal sequencing; Penicillin V acylase; Purification; Rhodotorula aurantiaca; Substrate specificity

Chemical inhomogeneity and mixed-state ferromagnetism in diluted magnetic semiconductor Co : TiO2 - Ogale, Satishchandra B.; Kundaliya, Darshan; Mehraeen, Shareghe; Fu, Lian-feng; Zhang, Shixiong; Lussier, Alexandre; Dvorak, Joe; Browning, Nigel D.; Idzerda, Yves; Venkatesan, Thirumalai (Chemistry of Materials, 2008)
Diluted magnetic semiconductors (DMS) are among the most intensely investigated materials in recent times in view of their great application potential. Yet, they are also the most controversial because of the possibility of extrinsic effects attributable to dopant solubility and clustering, point defects, incorporation of unintentional impurities, etc. This has highlighted the central role of materials chemistry in rendering a specific microstate and property response. In this work, we provide a combined window of high-resolution scanning transmission electron microscopy and electron energy-loss spectrometry, X-ray absorption (XAS)/X-ray magnetic circular dichroism (XMCD), and magnetization measurements on epitaxial rutile CoxTi1-xO2 (x = 0-0.06) system (the first discovered oxide-DMS, which continues to be controversial) grown at low temperature (400 degrees C) under different ambient atmospheres. The study brings out a mixed-state scenario of ferromagnetism involving intrinsic DMS (uniform dopant distribution at low dopant concentration) and coupled cluster magnetism, involving cobalt associations within the matrix at higher concentrations. We also show that by matrix valence control during growth, it is possible to realize a uniform embedded cluster state and the related coupled cluster magnetism.

Chemoselective synthesis of beta-amino acid derivatives by hydroamination of activated olefins using AISBA-15 catalyst prepared by post-synthetic treatment - Shanbhag, Ganapati V.; Kumbar, S. M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
beta-Amino acid derivatives have a wide variety of applications viz. in the synthesis of peptide analogues, precursor for amino alcohols, optically active amino acids, lactums and diamines. Chemoselective anti-Markovnikov hydroamination reaction of activated olefins was effectively used to synthesize beta-amino acid derivatives using AlSBA-15 and AlMCM-41 catalysts. These catalysts with different Si/Al ratios were synthesized by isomorphous substitution of aluminium into the framework of SBA-15, which induces the Bronsted and Lewis acid sites. The structural integrity of the catalysts was established by characterizing with XRD, N-2-sorption, TEM, NH3-TPD Al-27 MAS NMR and Si-29 MAS NMR techniques. Hydroamination of ethyl acrylate with aniline was used as a test reaction, which gave N-[2-(ethoxycarbonyl)ethyl] aniline with high selectivity. The performance of AlSBA-15 catalyst was also determined with different acrylates and amines to know the general applicability of the catalyst in hydroamination reactions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acrylate; activated olefin; addition; AlMCM-41; AlSBA-15; Amine; beta-amino acid; Catalyst; hydroamination; Mesoporous

Chimeric (alpha-amino acid plus nucleoside-beta-amino acid)(n) peptide oligomers show sequence specific DNA/RNA recognition - Gogoi, Khirud; Kumar, Vaijayanti A. (Chemical Communications, 2008)
An alpha/beta-peptide backbone oligonucleotide comprising natural alpha-amino acids alternating with a beta-amino acid component derived from thymidine sequence specifically recognizes and binds to deoxy- and ribo-oligoadenylates in triplex mode.

Chiral Mn(III) salen complex immobilized onto ionic liquid modified mesoporous silica for oxidative kinetic resolution of secondary alcohols - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Tetrahedron Letters, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a chiral Mn(III) salen complex onto ionic liquid modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high enantioselectivity and activity in the oxidative kinetic resolution of secondary alcohols, and could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mesoporous silica SBA-15; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Co : CdS diluted magnetic semiconductor nanoparticles: radiation synthesis, dopant-defect complex formation, and unexpected magnetism - Bogle, Kashinath A.; Ghosh, Saurabh; Dhole, Sanjay D.; Bhoraskar, Vasant N.; Fu, Lian-feng; Chi, Miao-Fang; Browning, Nigel D.; Kundaliya, Darshan; Das, Gour P.; Ogale, Satishchandra B. (Chemistry of Materials, 2008)
Incorporating a dopant into a nanoparticle is a nontrivial proposition in view of the size dependent surface versus bulk energy considerations and the intrinsic proximity of the surface to the interior, which facilitates migration to the surface. If realized and controlled, however, it can open up new avenues to novel nanomaterials. Some previous studies have shown the dopability of nanosystems but only with specific surface functionalization. Here, we demonstrate the successful dopant incorporation via a new route of pulsed high energy electron induced synthesis. We choose a system Co:CdS (dilutely cobalt doped cadmium sulfide) in view of the well-known application-worthy properties of CdS and the potential possibility of its conversion to a diluted magnetic semiconductor of interest to spintronics. By using various techniques, we show that matrix incorporation and uniform distribution of cobalt are realized in US nanocrystals without the need for additional chemical or physical manipulation. Optical and photoluminescence properties also support dopant incorporation. Interestingly, although magnetism is realized, it is weak, and it decreases at higher cobalt concentration. First principle density functional calculations are performed to understand this counterintuitive behavior. These calculations suggest that the introduction of parent cation or anion vacancies lead to magnetic moment reduction, albeit marginally. However, with some Co impurity fraction in the octahedral interstitial site inside the wurtzite cage, the magnetic moment drops down drastically. This study reveals that defect states may have an interesting role in dopant stabilization in nanosystems, with interesting system dependent consequences for the properties.

Co-catalyzed mild and chemoselective reduction of phenyl esters with NaBH(4): a practical synthesis of (R)-tolterodine - Jagdale, Arun R.; Sudalai, Arumugam (Tetrahedron Letters, 2008)
CoCl(2) catalyzes effectively the chemoselective reduction of phenyl carboxylic esters to the corresponding saturated alcohols in high yields using NaBH(4) at ambient conditions. By employing this methodology, the synthesis of (R)-tolterodine, a muscarinic receptor antagonist, has been achieved in high yield and optical purity. (C) 2008 Elsevier Ltd. All rights reserved.

COLL 41-studies in biosurfactants: sophorolipids - Momin, Shamim A.; Prabhune, Asmita; Sonchal, Bhushan P.; Shah, Sachin; Kothekar, Shrinivas C. (235th American-Chemical-Society National Meeting, 2008)
Keywords: Biosurfactants; Candida bombicola ATCC 22214; Fermentation Process; sophorolipids

Comparative biochemical and structural characterizations of fungal polygalacturonases - Niture, Suryakant K. (Biologia, 2008)
Endo- and exo-polygalacturonases produced by various fungi are involved in the degradation of pectic substances. They have found a wide range of applications in the food and textile industries. Several phyto-pathogenic fungi secrete polygalacturonases and they act as virulence factors during plant pathogenesis. The comparison of biochemical properties of different fungal polygalacturonases, their mechanism of actions, structural aspects and interactions with inhibitors/proteins could be used as a possible strategy for the fungal-crop disease management. This review focuses on fungal polygalacturonases, including their regulation, comparative biochemical and structural characterizations and their interactions with inhibitors.
Keywords: pectate lyase; plant pathogenesis; polygalacturonase; polygalacturonase-inhibiting proteins

Comparative study of structural, acidic and hydrophilic properties of Sn-BEA with Ti-BEA using periodic density functional theory - Shetty, Sharan; Kulkarni, Bhakti S.; Kanhere, Dilip G.; Goursot, Annick; Pal, Sourav (Journal of Physical Chemistry B, 2008)
Periodic density functional theory has been employed to characterize the differences in the structural, Lewis acidic and hydrophilic properties of Sn-BEA and Ti-BEA. We show that the incorporation of Sri increases the Lewis acidity of BEA compared to the incorporation of Ti. Hence, the present work gives insight into the role of Sn in increasing the efficiency of the oxidation reactions. The results also justify that the percentage of Sri substituted in BEA is less than Ti. The structural analysis shows that the first coordination shell of Sri is larger than that of Ti. However, the second coordination of both sites remains the same. The water adsorption properties of these substituted zeolites are quantified. Moreover, we explain the higher Lewis acidity of Sn than the Ti site on the basis of the Fukui functions and charge population analysis.

Comparative study of the shape-dependent electrocatalytic activity of platinum multipods, discs, and hexagons: applications for fuel cells - Subhramannia, Mahima; Ramalyan, Kannan; Pillal, Vijayamohanan K. (Langmuir, 2008)
We here demonstrate a remarkable potential-dependent morphological evolution of platinum mesostructures in the form of multipods, discs, and hexagons using a porous anodic alumina membrane (PAAM). These structures prepared potentiostatically at -0.7, -0.5 and -0.3 V, respectively, reveal unique shape-dependent electrocatalytic activity toward both formic acid and ethanol oxidation reactions. A comparison of the electrooxidation kinetics of these structures illustrates that hexagons show better performance toward formic acid oxidation whereas, for ethanol oxidation, multipods show significantly enhanced activity. Interestingly, the enhancement factor (R) for these mesostructures with respect to that of commercial platinized carbon toward formic acid oxidation ranges up to 2000% for hexagons whereas for multipods and disc they are about 700% and 300%, respectively. Similarly, for ethanol oxidation, the calculated value of R varies up to 600% for multipods while for disc and hexagons these values are 500% and 200%, respectively. These shape-dependent electrocatalytic activity of Pt mesostructures have been further correlated with XRD results. Thus, the present results demonstrate the importance of precise control of morphology by an electric field and their potential benefits especially for fuel cell applications since designing a better electrocatalyst for many fuel cell reactions continues to be an important challenge.

Comparison of Metarhizium isolates for biocontrol of helicoverpa armigera (Lepidoptera : Noctuidae) in chickpea - Kulkarni, Shuklangi A.; Ghormade, Vandana; Kulkarni, Girish; Kapoor, Manisha; Chavan, Santosh B.; Rajendran, Armugam; Patil, Sanjay K.; Shouche, Yogesh; Deshpande, Mukund V. (Biocontrol Science and Technology, 2008)
Metarhizium isolates from soil (53) and insect hosts (10) were evaluated for extracellular production of cuticle degrading enzyme (CDE) activities such as chitinase, chitin deacetylase (CDA), chitosanase, protease and lipase. Regression analysis demonstrated the relation of CDE activities with Helicoverpa armigera mortality. On basis of this relation, ten isolates were selected for further evaluation. Subsequently, based on LT(50) of the 10 isolates towards H. armigera, five isolates were selected. Out of these five isolates, three were selected on the basis of higher conidia production (60-75 g/kg rice), faster sedimentation time (ST(50)) (2.3-2.65 h in 0.1% (w/v) Tween 80) and lower LC(50) (1.4- 5.7 x 10(3) conidia/mL) against H. armigera. Finally, three Metarhizium isolates were selected for the molecular fingerprinting using ITS sequencing and RAPD patterning. All three isolates, M34412, M34311 and M81123, showed comparable RAPD patterns with a 935G primer. These were further evaluated for their field performance against H. armigera in a chickpea crop. The percent efficacies with the three Metarhizium isolates were from 65 to 72%, which was comparable to the chemical insecticide, endosulfan (74%).
Keywords: appressorium formation; chitin deacetylase; chitinase; chitosanase; Helicoverpa armigera; Lipase; Metarhizium anisopliae; Protease

Complexation of heavy metals by crosslinked chitin and its deacetylated derivatives - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2008)
Chitin was crosslinked using diisocyanatohexane (HDI), trimellitic anhydride (TMA), and dibromodecane (DBD), then deacetylated in strong aqueous alkali. This led to a product with amine functional groups on the exposed surface of the crosslinked chitin, which could be utilized for complexation with heavy metals. Thus, a key feature of the crosslinked derivatives prepared was that only the hydroxy Groups were utilized in the crosslinking reaction, and the acetylamino groups of chitin were hydrolyzed only after the crosslinking was accomplished. This ensured that all amino groups of the chitosans so produced would be available for metal complexation, and not partially used up in crosslinking. This proposed advantage was proved by the similar binding observed for heavy metals like Hg (348-372 mg/g), Cu (91-119 mg/g), Zn (71-92 mg/g), Mn (3-10 mg/g), Cd (121-160 mg/g), and Pb (32-86 mg/g) using these crosslinked polymers, whereas the control polymer (uncrosslinked chitosan powder) had complexation values for Hg (348-361 mg/g), Cu (100-106 mg/g), Zn (81-92 mg/g), Mn (4-7 mg/g), Cd (135 mg/g), and Pb (25-59 mg/g). Additionally, in a case where chitosan was crosslinked with HDI. the amino groups were consumed in the crosslinking reaction, and the metal complexation capacity has found to be decreased for Cu (91-109 mg/g), Cd (133 mg/g), and Zn (71-77 mg/g), while remaining nearly the same for Hg (362 mg/g). The literature value for Cu complexation is 59.67 mg/g for chitosan crosslinked with glutaraldehyde. The crosslinked derivatives have the added advantage of insolubility even in low pH aqueous media, making their repeated re-use possible. Further, these crosslinked derivatives could be used in powder form, and the additional step of preparing beads was found to be not necessary for ease of separation of the crosslinked powder by filtration. The binding capacity of various crosslinked chitin and deacetylated derivatives for Cu, Cd, Hg, Zn, Mn. and Pb was in the region of 100, 140, 360 88, 5, and 60 mg/g (rounded off values) of polymer, respectively, very close to the values obtained for uncrosslinked chitosan. The metal binding for crosslinked chitosan was slightly lower than that of crosslinked chitin and deacetylated derivatives, due to use of some amino groups in crosslinking. For Cu ions, the Langmuir equation was found to be the best fit for HDI crosslinked deacetylated chitin and TMA crosslinked deacetylated chitin. The morphological studies conducted using WAXRD are in close agreement with the metal complexation data, showing complete loss of original chitosan peaks for the heavily complexed derivatives, and minor changes for the weakly complexed metals. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; deacetylated chitin; metal complexation; Morphology

Composites of polypropylene with layered Mg-silsesquioxanes show an unusual combination of properties - Kumaraswamy, Guruswamy; Deshmukh, Yogesh S.; Agrawal, Vikrant V.; Nisal, Anuya (Industrial & Engineering Chemistry Research, 2008)
We report the synthesis of vinyl modified magnesium silsesqiuoxanes (''vinyl clay''), and the formation of their composites with isotactic polypropylene (iPP) by melt compounding. Vinyl clay is a layered compound with a layer thickness of approximately 1 nm. Vinyl clay does not exfoliate in iPP; rather, it disperses to form a network that exhibits a characteristic low frequency solid-like plateau in the elastic modulus in dynamic melt theological measurements. Strangely, vinyl clay also plasticizes iPP-there is a decrease in the high frequency complex viscosity. The decrease in the complex viscosity is higher at higher frequencies, suggesting the influence of slip at the iPP-vinyl clay interface. The combination of the low frequency elastic plateau and plasticization makes the vinyl clay composite significantly more shear thinning than the matrix iPP. In the solid state, vinyl clay-iPP composites exhibit increased tensile modulus (showing approximate to 50% increase for a 5% loading), but surprisingly, no corresponding decrease in the elongation at break. Thus, while microstructural characterization indicates that only a small fraction, if any, of the vinyl clay is exfoliafed, the enhancement in mechanical properties is similar to that observed for iPP-exfoliated montmonillonite nanocomposites. Our compounding protocol is unable to effectively disperse the clay in the iPP at clay loadings greater than about 7.5%. Therefore, the low frequency plateau in the melt elastic modulus and the solid tensile modulus increase with clay loading until 7.5% but exhibit a nonmonotonic decrease at higher clay loadings.

Concise synthesis of protected (2S,4R)-4-hydroxyornithine - Pandey, Satyendra Kumar; Pandey, Menaka; Kumar, Pradeep (Tetrahedron Letters, 2008)
A short synthesis of the nonproteinogenic amino acid, (2S,4R)-4-hydroxyornithine is described. Starting from racemic benzyl glycidol, the scaffold of the target compound was constructed in high enantio- and diastereoselectivity using Jacobsen's hydrolytic kinetic resolution (HKR) and regioselective opening of an epoxide as key steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Epoxide; Grignard reaction; hydroxyornithine; Jacobsen's HKR; Natural product

Conformational preferences of hypermodified nucleoside lysidine (k(2)C) occurring at wobble position in anticodon loop of tRNA(IIe) - Sonawane, Kailas D.; Tewari, Ravindra (Nucleosides Nucleotides & Nucleic Acids, 2008)
Conformational preferences of hypermodified nucleoside, 4-amino-2-(N(6)-lysino)-1-(beta-D-ribofuranosyl) pyrimidinium (Lysidine or 2-lysyl cytidine), usually designated as k(2)C, have been investigated theoretically by the quantum chemical perturbative configuration interaction with localized orbitals (PCILO) method. The zwitterionic, non-zwitterionic, neutral, and tautomeric forms have been studied. Automated geometry optimization using molecular mechanics force field (MMFF), semi-empirical quantum chemical PM3, and ab initio molecular orbital Hartree-Fock SCF quantum mechanical calculations have also been made to compare the salient features. The predicted most stable conformations of zwitterionic, non-zwitterionic, neutral, and tautomeric form are such that in each of these molecules the orientation of lysidine moiety (R) is trans to the N(1) of cytidine. The preferred base orientation is anti (chi = 3 degrees) and the lysine substituent folds back toward the ribose ring. This results in hydrogen bonding between the carboxyl oxygen O(12a) of lysine moiety and the 2'-hydroxyl group of ribose sugar. In all these four forms of lysidine O(12a)...H-C(9) and O(12b)...H-N(11) interactions provide stability to respective stable conformers. Watson-Crick base pairing of lysidine with A is feasible only with the tautomeric form of usual anti oriented lysidine. This can help in recognition of AUA codon besides in avoiding misrecognition of AUG.
Keywords: hypermodified; k(2)C; lysidine; stable conformers

Continuous flow nitration of salicylic acid - Kulkarni, Amol A.; Nivangune, Nayana T.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2008)
Continuous flow nitration of salicylic acid using HNO3/AcOH was studied in the SS316 tubular microreactor. At specific reaction conditions, complete conversion of the reactant was achieved in less than 7 min. It yielded only mononitro derivatives with a higher selectivity of 5-nitrosalicylic acid. Presence of the lower amount of acetic acid in the reaction mixture was seen to be detrimental, leading to precipitation of the desired product (5-nitrosalicylic acid). Reaction at higher temperatures yielded byproducts. The continuous mode operation using the system comprising the microdevices was demonstrated for 2 h with consistent composition at the outlet.

Controlled synthesis of ZnO from nanospheres to micro-rods and its gas sensing studies - Navale, Shalaka C.; Gosavi, S. W.; Mulla, Imtiaz S. (Talanta, 2008)
1D ZnO rods are synthesized using less explored hydrazine method. Here we find, besides being combustible hydrazine can also be used as a structure-directing agent. The ratio of zinc nitrate (ZN) to hydrazine is found to control the morphology of ZnO. At lower concentration of ZN as compared with hydrazine the morphology of ZnO is found to be spherical. As we increase the hydrazine content the morphology changes from spherical (diameter similar to 100 nm) to the elongated structures including shapes like Y, T as well dumbbell (diameter similar to 40 nm and length similar to 150 nm). Interestingly for more than 50% of hydrazine ZnO micro-rods are formed. Such rods are of diameter similar to 120 mn having length of about 1 mu m for ZN to hydrazine ratio of 1:9, isolated as well as bundle of rods are seen in scanning electron microscopy (SEM). The X-ray diffraction (XRD) reveals the phase formation with average particle size of 37 nm as calculated using Scherrer's formula. The high-resolution transmission electron microscopy (HRTEM) is also done to confirm the d-spacing in ZnO. Gas sensing study for these samples shows high efficiency and selectivity towards LPG at all operating temperatures. Photoluminescence (PL) study for these samples is performed at room temperature to find potential application as photoelectric material. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrazine; LPG sensor; Nanostructures; photoluminescence; ZnO

Convenient access to 1, 3,4-trisubstituted pyrazoles carrying 5-nitrothiophene moiety via 1,3-dipolar cycloaddition of sydnones with acetylenic ketones and their antimicrobial evaluation - Rai, N. Satheesha; Kalluraya, Balakrishna; Lingappa, B.; Shenoy, Shaliny; Puranik, Vedavati G. (European Journal of Medicinal Chemistry, 2008)
Novel 1-aryl-3-(5-nitro-2-thienyl)-4-aroyl-pyrazoles 7 have been synthesized by the 1,3-dipolar cycloaddition of 3-arylsydnones 3 with 1-aryl-3-(5-nitro-2-thienyl)-2-propyn- 1-ones 6. The newly synthesized compounds were well characterized by elemental analysis, IR, (1)H NMR and mass spectral studies. They were also screened for their antibacterial and antifungal activities against a variety of microorganisms and the results of such studies have been discussed in this article. (c) 2007 Elsevier Masson SAS. All fights reserved.
Keywords: 1; 3-dipolar cycloaddition; 5-nitrothiophene; acetylenic ketone; Antibacterial; antifungal; Pyrazole; sydnone

Convenient synthesis of 1-acetyl-2,2-dimethyl-3-arylcyclopropanes - Muthusubramanian, Lakshmi; Mitra, Raiat B. (Organic Preparations and Procedures International, 2008)

Copolyester nanocomposites based on carbon nanotubes: reinforcement effect of carbon nanotubes on viscoelastic and dielectric properties of nanocomposites - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Polymer International, 2008)
Nanocomposites based on an amorphous copolyester, poly(ethylene glycol-co-cyclohexane-1,4-dimethanol terephthalate) and carbon nanotubes were fabricated using a simple melt processing technique. The reinforcement effect of carbon nanotubes in the copolyester was investigated experimentally using different approaches based on dynamic mechanical analysis, theology and dielectric analysis. The nanocomposites show a mechanical reinforcement effect with significant increase in the stiffness especially in the rubbery regime with increasing nanotube content. An increase in T-g and a decrease in damping are seen, which are derived from the presence of a percolating superstructure of the filler. Rheological experiments show an increase in storage modulus up to four orders of magnitude. Viscolelastic characterization shows that the percolation threshold is at 3 wt% of nanotubes. Dielectric relaxation spectroscopy confirms the presence of this percolating structure. We conclude that the responses of both rheological and electrical properties are different, although both are related to the formation of a percolating network superstructure of the filler. (c) 2007 Society of Chemical Industry.
Keywords: Carbon nanotubes; dielectric analysis; nanocomposites.; reinforcement; viscoelastic properties

Co-precipitation method for preparation of Bi3TiNbO9 powders - Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Patil, S. D.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure, ultrafine, single phase Bi3TiNbO9 (BTN). An aqueous ammonium hydroxide solution was used to simultaneously precipitate Bi3+, Ti4+ and Nb5+, cations as hydroxides under basic conditions (pH similar to 9). No pyrochlore phase was found while heating powder at 500 degrees C and pure BTN phase was found to be formed by X-ray diffraction (XRD). For comparison, BTN samples were also synthesized by the traditional solid state method. The sequence of phase formation in both cases were investigated by XRD studies. (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; Oxides; XRD

Co-precipitation technique to prepare BiNbO4 powders - Radha, R.; Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique was successfully used for the preparation of pure ultrafine single phase BiNbO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. For comparison, BN powders were also prepared by the traditional solid-state method. It is observed that the co-precipitation technique produces BiNbO4 on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the solid-state method. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). (C) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Co-precipitation technique to prepare BiTaO4 powders - Muthurajan, H.; Gupta, U. N.; Rituraj, B.; Rao, N. Koteswara; Pradhan, Sivaram; Radha, R.; Ravi, V. (Materials Letters, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure ultrafine single phase BiTaO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. This precursor, on heating at 600 degrees C, produced product phase. This is the lowest temperature for the formation of BiTaO4 phase so far reported in the literature. For comparison BiTaO4 powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: BiTaO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Crystal-to-crystal transformation amongst dimorphs of racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates that achieves halogen bonding contacts - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2008)
{Racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (1) and chloro (2)) produced two polymorphs each, thin needle type crystals (Form I) were obtained from methanol, whereas larger rectangular crystals (Form II) were produced from ethyl acetate. Both forms could be produced concomitantly on crystallization (of 1 or 2) from ethyl acetate-light petroleum ether mixture; the yield of Form II crystal was always much more compared to Form I crystals. Although, a one-dimensional isostucturality linking molecules via O-H center dot center dot center dot O hydrogen bonding is seen in both forms, the difference arises in linking these chains. In larger Form II crystals (of 1 and 2), the adhesions are via halogen bonding (C-X center dot center dot center dot O=C

Cu-Ce mixed oxides supported on Al-pillared clay: effect of method of preparation on catalytic activity in the preferential oxidation of carbon monoxide - Ramaswamy, Veda; Malwadkar, Sachin S.; Chilukuri, Satyanarayana V. (Applied Catalysis B-Environmental, 2008)
The possibility of using Al-pillared montmorillonite (Al-PILC) clay as a high-surface-area support for CuO-CeO2-based catalysts has been investigated. The preparation of the samples was done by three different methods, viz., amorphous citrate route (ACR), deposition precipitation (DP) and wet impregnation method (WIM). Samples with different CuO-CeO2 loadings (10-50 wt.%) were prepared by each of the three methods. The catalytic activity of these samples was investigated for the preferential oxidation (PROX) of carbon monoxide (CO) in excess of H-2. The samples prepared by DP and WIM methods show better activity than the samples prepared by ACR method. At low Cu content, the samples prepared by DP method have a slight edge over samples prepared by WIM method. The DP-30 sample shows a very high CO conversion of 96.1% at 423 K. A higher dispersion of CuO-CeO2 on pillared montmorillonite clay and better reducibility of copper oxide species may be responsible for the good activity of these samples even at lower reaction temperatures. A higher O-2/CO ratio increased the CO conversion but led to a reduction in oxidation selectivity. No methanation of CO or CO2 was observed at the reaction temperature. These CuO-CeO2/Al-PILC samples could be considered as comparable in performance with supported noble metal catalysts for the preferential oxidation of CO in excess hydrogen. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Alumina-pillared clay; Clay-supported CuO-CeO2; CuO-CeO2; PROX of CO

Cu(OTf)(2) catalyzed Biginelli type condensation of aldehydes, beta-keto esters and carbamates: synthesis of 3,4-dihydro[1,3]oxazin-2-ones - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2008)
Cu(OTf)(2) catalyzes effectively a new multicomponent reaction comprising aldehydes, beta-ketoester and methy carbamate in acetonitrile to afford substituted 3,4-dihydro[1,3]oxazin-2-ones in 60-82% yields. These compounds have been found to show inhibition activity against HL-60 cancer cell.
Keywords: aldehydes; Catalysts; Copper; Multicomponent reaction

Cyanuryl peptide nucleic acid: synthesis and DNA complexation properties - Vysabhattar, Raman; Ganesh, Krishna N. (Tetrahedron Letters, 2008)
The synthesis of cyanuryl PNA monomer (CyaPNA) 6 was achieved by direct N-monoalkylation of cyanuric acid with N-(2-Boc-aminoethyl)-N'-(bromoacetyl)glycyl ethyl ester 4. Compound 6 was incorporated as a T-mimic into PNA oligomers and biophysical studies on their triplexes/duplex complexes with complementary DNA oligomers indicated unusual stabilization of PNA:DNA hybrids when the cyanuryl unit was located in the middle of the PNA oligomer. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: cyanuryl PNA; PNA

CARB 36-Novel and structurally biased backbone modifications of nucleic acids - Kumar, Vaijayanti A. (Abstracts of Papers of the American Chemical Society, 2009)

Carbon nanofiber with selectively decorated pt both on inner and outer walls as an efficient electrocatalyst for fuel cell applications - Balan, Beena K.; Unni, SreeKuttan M.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2009)
A novel electrocatalyst, with excellent Pi dispersion oil the inner and outer wall of a carbon nanofiber (CNF) was prepared by a modified polyol process in which both surface tension and polarity characteristics of the medium were properly adjusted to favor solution entry into the tubular region by capillary filling and homogeneous wetting of the inner wall surface by the solvents. The pristine CNF, which possesses an inherently active inner wall surface and inactive outer Wall surface, led to selective Pt deposition along the inner wall, whereas activation of the outer wall with chemical functionalization resulted in excellent dispersion of Pt along both inner and outer walls. Structural and morphological characterizations using high resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) revealed that when Pt could be dispersed along the inner as well as the Outer walls of CNF, the Pt particle size decreased to almost half as compared to the one With Pt decoration only along a single wall of the Substrate material. Further, electrochemical studies using cyclic voltammetry (CV) and rotating disk electrode (RDE) measurements revealed enhanced methanol oxidation and oxygen reduction properties, respectively. The electrochemical active area obtained for the catalyst with both inner and outer wall Pt decoration wits nearly two times higher than that corresponding to the one with only inner wall Pt decoration. Similarly, the rate constant for the oxygen reduction reaction displayed by this sample was four times higher in comparison with the sample prepared by Utilizing only one wall for Pt decoration.

Carboxylic-functionalized water soluble pi-conjugated polymer: highly selective and efficient chemosensor for mercury(II) ions - Balamurugan, A.; Reddy, M. L. P.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
Here, we report a new carboxylic-functionalized water soluble pi-conjugated polymer for selective detection of highly toxic Hg(2+) in neutral pH condition. carboxylic-functionalized thiophene containing oligophenylenevinylene was synthesized and polymerized under oxidative route to obtain water soluble polymer. Free carboxylic groups present in the pi-conjugated materials provide opportunity to use pH as external stimuli for studying secondary interaction such as hydrogen bonding and aromatic pi-stacking of the chromophores. The pH changes strongly influence on the molecular interactions in the monomer, whereas the long chain polymer was less disturbed. The polymer showed high selectivity for detecting Hg(2+) ions compared with any other transition metal ions in water. The detection efficiency of the polymer was found almost 40 times higher than that of its monomeric unit. Stern-Volmer constant for the Hg(2+) ion sensing was determined through concentration dependent studies as 6.4 x 10(5) M(-1). The carboxylic-functionalized polymer showed reversibility in the metal-ion detecting capabilities which was further investigated by NaCl complexation with Hg(2+) complex. Both funneling of excitation energy to the Hg(2+) center and also excitation energy migration through chain pi-conjugated backbone were correlated to the superior sensing characteristics of the polymer compared to its monomeric counterpart. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 5144-5157, 2009
Keywords: conjugated polymer; pH sensitive; photophysical studies; sensing; synthesis; water soluble

Catalytic activity of cobalt containing MCM-41 and HMS in liquid phase oxidation of diphenylmethane - Bhoware, Shrikant S.; Kamble, K. R.; Singh, A. P. (Catalysis Letters, 2009)
Cobalt containing MCM-41 and HMS were synthesized by direct hydrothermal (DHT) and post synthesis methods (grafting and immobilization). The catalytic activity of these materials was investigated in the liquid phase oxidation of diphenylmethane at 80 A degrees C with TBHP (70 wt%) as oxidant. Comparative study of cobalt containing MCM-41 and HMS was carried out to reveal the catalytic performance of framework, extraframework and immobilized cobalt species. The role of the solvent in the performance of catalyst was examined with different polar and non polar solvents. Oxidation of diphenylmethane in solvent free media (under similar reaction conditions) shows formation of hydroxy derivatives of benzophenone in addition to main product (benzophenone). Hundred percent selectivity to benzophenone was obtained when the reaction was carried out in solvent.
Keywords: diphenylmethane; HMS; Immobilization; MCM-41; XRD

Catalytic aerobic oxidation of cyclohexane and ethyl benzene over chromium-containing mesoporous organosilicas - Singh, A. P.; Torita, N.; Shylesh, S.; Iwasa, N.; Arai, M. (Catalysis Letters, 2009)
Chromium-containing ethane-bridged hybrid periodic mesoporous organosilicas (Cr-PMO) were synthesized using 1,2-bis(triethoxysilyl) ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts as surfactants by two different synthesis routes. PXRD and N(2) adsorption-desorption analysis shows that the original structure of the materials is maintained after chromium substitution while spectroscopic study proves the incorporation of chromium in the frame wall positions and show the existence of Cr(2)O(3) species in the mixed silica source (BTEE-TEOS) synthesized chromium samples. The catalytic activity of the newly developed chromium samples was evaluated in the liquid phase oxidation of cyclohexane and ethylbenzene using air as an oxidant. Further, the Cr-PMO samples exhibited better cyclohexane conversion and cyclohexanone selectivity than the conventional Cr-MCM-41 and other metal-containing MCM-41 samples. The exceptional activity of the new chromium-containing molecular sieves is attributed to the hydrophobicity of the materials and to the complementary structural features that facilitates the accessibility of substrate to the active framework chromium sites.
Keywords: Cr-MCM-41; Cyclohexane; Ethyl benzene; Organosilicas; Oxidation

Catalytic meerwein-ponndorf-verley reductions over mesoporous silica supports: rational design of hydrophobic mesoporous silica for enhanced stability of aluminum doped mesoporous catalysts - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Samuel, Prinson R.; Srilakshmi, Ch; Singh, A. R. (Journal of Molecular Catalysis A-Chemical, 2009)
A series of aluminum isopropoxide-grafted mesoporous organosilica having ethane (-CH(2)-CH(2)-) and ethene (-CH=CH-) groups in the frame wall positions (ethane-silica, ethene-silica) as well as mesoporous silicas (MCM-41, MCM-48. SBA-15) through siloxide linkages were fabricated. The samples were used as catalysts in the Meerwein-Ponndorf-Verley reduction of ketones and aldehydes of different nature and size using secondary alcohols as the hydrogen transfer agents. Aluminum isopropoxide supported mesoporous silica samples show higher catalytic conversion and among them, the one-dimensionally channel oriented Si-MCM-41 supported aluminum isopropoxide shows better results than the three-dimensional Si-MCM-48 and the large pore Si-SBA-15. Compared to aluminum isopropoxide-grafted mesoporous silica samples, aluminum alkoxide-grafted organosilica samples shows better catalytic activity even in the presence of 10% of water and the better stability is attributed to the presence of integrated hydrophobic organic groups in the frame wall positions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Aluminum isopropoxide; Mesoporous silica; Organosilica; reduction

Catalytic synthesis of chalcone and flavanone using Zn-Al hydrotalcite adhere ionic liquid - Kunde, Lalita B.; Gade, Swapna M.; Kalyani, Vishwanath S.; Gupte, Sunil P. (Catalysis Communications, 2009)
The Claisen-Schmidt condensation of 2'-hydroxy acetophenone and benzaldehyde to chalcone and flavanone show that calcined Zn-Al (6) hydrotalcite is active for this synthesis. Coating of ionic liquid `1-(tri-ethoxy-silyl-propyl)-3-methyl-imidazolium chloride' on Zn-Al hydrotalcites was accomplished employing incipient wetness process and on NaY, NaX, MK-5 and silica gel employing co-condensation methodology. Impregnated IL on calcined Zn-Al (6) catalysts were characterized by XRD, SEM, BET, (13)C and (27)Al NMR analysis and the activity of these catalysts were investigated for chalcone and flavanone synthesis. (27)Al CP MAS NMR technique was used to show that interaction of IL with hydrotalcite modifies the acid-base sites and is responsible for enhancement of catalyst activity. Several aromatic aldehydes were screened to assess the general applicability of the system. (c) 2009 Published by Elsevier B.V.
Keywords: (27)Al CP MAS NMR; chalcone; Claisen-Schmidt condensation; Flavanone; Ionic liquid; Zn-Al hydrotalcite

Cell proliferation and controlled drug release studies of nanohybrids based on chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Acta Biomaterialia, 2009)
The present paper reveals the potential uses of novel hybrids of chitosan-g-lactic acid and sodium montmorillonite (MMT) in controlled drug delivery and tissue engineering applications. The drug-loaded novel nanohybrid films and porous scaffolds have been prepared by solvent casting and freeze-drying of the grafted polymer solution, respectively. Sodium Ibuprofen was loaded into nanohybrids of chitosan-g-lactic acid/sodium montmorillonite (CS-g-LA/MMT). Grafting of lactic acid and the drug loading were characterized by Fourier transform infrared spectroscopy. Formation of intercalated nanocomposites was confirmed by X-ray diffraction. Mechanical properties measurements have shown improvement in modulus and strength with expense of elongation by MMT reinforcement. The nanohybrids were found to be stable regardless of pH of the medium. The cell proliferation profile also shows that prepared nanohybrids are biocompatible. MMT reinforcement was found to control the drug (Ibuprofen) release rate in phosphate buffer saline solution (pH 7.4). MMT clay is therefore a viable additive for formulating sustained drug delivery systems based on lactic acid grafted chitosan. (C) 2008 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Chitosan; clay; Controlled release; drug delivery systems; Nanocomposites

Cellulases from penicillium janthinellum mutants: solid-state production and their stability in ionic liquids - Adsul, Mukund G.; Terwadkar, Asawari P.; Varma, Anjanikumar; Gokhale, Digambar V. (Bioresources, 2009)
The cellulase production by P. janthinellum mutants on lignocellulosic material such as cellulose or steam exploded bagasse (SEB) in combination with wheat bran was studied in solid state fermentation (SSF). One of the mutants, EU2D21, produced the highest levels of endoglucanase (3710 IU g(-1) carbon source) and beta-glucosidase (155 IU g(-1) carbon source). Ionic liquids are so-called green solvents that have become attractive for biocatalysis. Stability of mutant cellulases was tested in 10-50% of the ionic liquid 1-butyl-3-methylimidazolium chloride ([bmim]Cl). FPA and CMCase were significantly stable in 10% ionic liquid after 5h. beta-glucosidase showed 85% of its original activity after 5 h incubation in 30% ionic liquid and retained 55% of its activity after 24 h. This enzyme preparation hydrolyzed ionic-liquid-treated SEB completely in 15 h in the presence of 20% ionic liquid. These studies revealed that there is no need of regenerating cellulose after ionic liquid treatment, since cellulase of mutant strain was found to be significantly stable in the ionic liquid.
Keywords: Cellulase stability; Ionic liquid; Mutant cellulase; Solid state fermentation

CFD Simulation of bubble columns: modeling of nonuniform gas distribution at sparger - Rampure, M. R.; Mahajani, S. M.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2009)
Most laboratory bubble columns are equipped with sieve plate spargers. The sieve plate spargers are known to lead to nonuniform gas distribution. It is important to account for such nonuniform gas distribution at the sparger in the computational model before experimental data collected from such columns are used to fit the model parameters. In this article, such an attempt is made. A detailed, 3D CFD model was developed to simulate unsteady gas-liquid flows in bubble Columns with sieve plate spargers. The sensitivity of the nonuniformity of gas distribution at the sparger with sparger resistance was examined. The model predictions were compared with the experimental data. The developed model and presented results will be useful for Simulating industrial bubble columns.

C-H center dot center dot center dot N hydrogen bonds mediated solid state structures of 2,2 `-bis (4-pyridylsulfanylmethyl)-1,1 `-biphenyl and 9-(4-pyridylsulfanyl)phenanthrene - Upadhye, Ketaki; PrakashaReddy, J.; Pedireddi, V. R. (Journal of Molecular Structure, 2009)
Solid state structure elucidation of sulfanyl ligands, 2,2'-bis(4-pyridylsulfany[methyl)-1,1'-biphenyl, L(1) and 9-(4-pyridylsulfanyl)plienanthrene, L(2) are reported. In the structures L(1) and L(2), the molecules are self-assembled through C-H center dot center dot center dot N hydrogen bonds, yielding ensembles of cyclic and helical networks. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonds; noncovalent interactions; Supramolecular assemblies

Challenges associated with metal chelation therapy in alzheimer's disease - Hegde, Muralidhar L.; Bharathi, P.; Suram, Anitha; Venugopal, Chitra; Jagannathan, Ramya; Poddar, Pankaj; Srinivas, Pullabhatla; Sambamurti, Kumar; Rao, Kosagisharaf Jagannatha; Scancar, Janez; Messori, Luigi; Zecca, Luigi; et al. (Journal of Alzheimers Disease, 2009)
A close association between brain metal dishomeostasis and the onset and/or progression of Alzheimer's disease ( AD) has been clearly established in a number of studies, although the underlying biochemical mechanisms remain obscure. This observation renders chelation therapy an attractive pharmacological option for the treatment of this disease. However, a number of requirements must be fulfilled in order to adapt chelation therapy to AD so that the term ``metal targeted strategies'' seems now more appropriate. Indeed, brain metal redistribution rather than brain metal scavenging and removal is the major goal of this type of intervention. The most recent developments in metal targeted strategies for AD will be discussed using, as useful examples, clioquinol, curcumin, and epigallocatechin, and the future perspectives will also be outlined.
Keywords: Alzheimer's disease; clioquinol; cuprizone; metal dishomeostasis; metal ions; nanomedicine; Parkinson's disease; polyphenols

On the change in bacterial size and magnetosome features for magnetospirillum magnetotacticum (MS-1) under high concentrations of zinc and nickel - Kundu, S.; Kale, A. A.; Banpurkar, Arun G.; Kulkarni, G. R.; Ogale, S. B. (Biomaterials, 2009)
The characteristic size, shape and specific alignment of magnetite crystals synthesized by magnetotactic bacteria is a highly coordinated process with precise control over magnetosome vesicle formation, uptake and transport of Fe, and magnetite biomineralization. Magnetosome membranes along with some specific membrane proteins regulate crystal nucleation and morphology of magnetite. Several previous works have indicated that the morphology of mature magnetite crystals is largely unaffected by environmental conditions, though some recent studies have shown the possibility of manipulation of the biomineralization process. In this study we have examined the effects of high concentrations of Zinc and Nickel on the growth of Magnetospirillum magnetotacticum (MS-1) and the corresponding magnetosome formation. Using various characterizations it is shown that the growth of the bacterial cells, as well as the size, shape and magnetosome chain alignment is significantly influenced in the presence of high concentrations of Zn or Ni. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biomineralization; magnetite; Magnetosome; Magnetospirillum magnetotacticum; Nickel; zinc

Changes in volatile composition during fruit development and ripening of `Alphonso' mango - Pandit, Sagar S.; Kulkarni, Ram S.; Chidley, Hemangi G.; Giri, Ashok P.; Pujari, Keshav H.; Koellner, Tobias G.; Degenhardt, Joerg; Gershenzon, Jonathan; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2009)
BACKGROUND: Volatile blends of five developing and five ripening stages of mango (Mangifera indica L. cv. Alphonso) were investigated along with those of flowers and leaves. Raw and ripe fruits of cv. Sabia were also used for comparison. RESULTS: A total of 55 volatiles belonging to various chemical classes such as aldehydes, alcohols, mono- and sesquiterpene hydrocarbons, lactones and furanones were identified. In all Alphonso tissues monoterpenes quantitatively dominated, with 57-99% contribution; in particular, (Z)-ocimene was found in the highest amount. Ripeness was characterized by the de novo appearance of lactones and furanones in the blend of monoterpenes. Sabja was distinguished by the abundance of monoterpene hydrocarbons in the raw fruit, and that of sesquiterpene hydrocarbons and their derivatives in the ripe stage. CONCLUSION: Various stages of the Alphonso fruit during transition from flower to ripe fruit are characterized by unique volatile signatures that are distinguished from each other by the qualitative and quantitative appearance of different volatile compounds. Thus volatiles can be highly informative markers while studying the development and ripening of mango. (C) 2009 Society of Chemical Industry
Keywords: Deogad; Gas chromatography; Mangifera indica; mango products; ripening indicator; Sabja

Characterization of clay intercalated cobalt-salen catalysts for the oxidation of p-cresol - Kshirsagar, V. S.; Garade, Ajit C.; Mane, R. B.; Patil, K. R.; Yamaguchi, A.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2009)
The intercalation of cobalt-salen complexes into the interlamelar spaces of montmorillonite clay was investigated by various characterization studies. The ``neat'' cobalt-salen complex showed a weight loss at 368 degrees C while the weight loss for the corresponding intercalated complex was observed at much higher temperature of 492 degrees C due to decomposition of the complex. The thermal stabilization observed was due to the host-guest interaction of clay and metal complex and thus confirmed the intercalation. The XANES spectrum of Co(salen)-mont sample revealed the change of symmetry from the tetrahedral in plane to the octahedral structure having an axial bonding of oxygen to the cobalt, indicating that cobalt atoms in Co(salen)-mont were coordinated axially with the lattice oxygen of montmorillonite. Both XANES and EXAFS results indicated that cobalt atoms in Co(salen)-mont form two additional Co-O bonds with a bond length of 0.199 nm by the intercalation while retaining the Co-salen structure. Co-salen intercalated into the montmorillonite clay showed the highest activity for the air oxidation of p-cresol, giving 88% selectivity to the oxidation products. Effects of NaOH concentration and various solvents on the conversion and selectivity patterns also have been studied. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cobalt-oxygen bond; Cobalt-salen; Extended X-ray absorption fine structure; Intercalation; Lattice oxygen; Montmorillonite; X-ray absorption near edge structure

Characterization of the smallest dimeric bile salt hydrolase from a thermophile brevibacillus sp. - Sridevi, N.; Srivastava, Sameer; Khan, Bashir Mohammad; Prabhune, Asmita Ashutosh (Extremophiles, 2009)
A thermophilic microorganism producing bile salt hydrolase was isolated from hot water springs, Pali, Maharashtra, India. This microorganism was identified as Brevibacillus sp. by 16S rDNA sequencing. Bile salt hydrolase (BSH) was purified to homogeneity from this thermophilic source using Q-sepharose chromatography and its enzymatic properties were characterized. The subunit molecular mass of the purified enzyme was estimated to be 28 kDa by SDS-PAGE and, 28.2 kDa by MALDI-TOF analysis. The native molecular mass was estimated to be 56 kDa by gel filtration chromatography, indicating the protein to be a homodimer. The pH and temperature optimum for the enzyme catalysis were 9.0 and 60A degrees C, respectively. Even though BSH from Brevibacillus sp. hydrolyzed all of the six major human bile salts, the enzyme preferred glycine conjugated substrates with apparent K (M) and k (cat) values of 3.08 mu M and 6.32 x 10(2) s(-1), respectively, for glycodeoxycholic acid. The NH2-terminal sequence of the purified enzyme was determined and it did not show any homology with other bacterial bile salt hydrolases. To our knowledge, this is the first report describing the purification of BSH to homogeneity from a thermophilic source.
Keywords: Bile salt hydrolase; Brevibacillus sp.; Dimeric intracellular enzyme; Purification; Thermophile

Chemical bath deposition of CdS quantum dots on vertically aligned ZnO nanorods for quantum dots-sensitized solar cells - Lee, Wonjoo; Min, Sun Ki; Dhas, Vivek V.; Ogale, Satishchandra B.; Han, Sung-Hwan (Electrochemistry Communications, 2009)
Formation of US quantum dots (Q dots) on the vertically aligned ZnO nanorods electrode was carried out by chemical bath deposition. The diameter and thickness of ZnO nanorods are similar to 100-150 nm and similar to 1.6 mu m, respectively, and CdS Q dots on ZnO nanorods have a diameter of smaller than 15 nm. In application of the Q dots-sensitized solar cells, composite film exhibited a power conversion efficiency of 0.54% under air mass 1.5 condition (80 mW/cm(2)), and incident-photon-to-current conversion efficiency showed 18.6%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical bath deposition; Photosensitization; quantum dots; solar cells; Wet-chemical process

Chlorophyll-based photocatalysts and their evaluations for methyl orange photoreduction - Joshi, Meenal M.; Kamble, Sanjay R.; Labhsetwar, Nitin K.; Parwate, D. V.; Rayalu, Sadhana S. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Immobilization of chlorophyll on different functionalized mesoporous materials has been attempted. The replacement of butanediol with monoethanol amine has resulted in increase in chlorophyll loading by a factor of two. The maximum immobilization of chlorophyll was on MCM-41 functionalized with monoethanolamine MCM-41/MEA/Chl) as compared to other mesoporous materials. This material has been characterized using XRD, UV-vis diffuse reflectance spectroscopy, scanning electron microscopy (SEM-EDX) and fluorescence spectroscopy. The photocatalytic reduction of methyl orange (MO)was studied using MCM-41/MEA/Chl as photocatalyst under the visible light. The photocatalytic reduction of MO was 0.396 mg/g of MCM-41/MEA/Chl photocatalyst as compared to 0.508 mg/g of TiO(2) for that of Degussa P-25 photocatalyst. The effect of various operating parameters like catalyst loading, initial concentration and intensity of light has also been studied. Photocatalytic property of chlorophyll-based photocatalytic material indicates that chlorophyll acts as a reaction center, which absorbs visible light and generates electron, which is transferred to different electron acceptors reducing MO into derivative of hydrazine. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Chlorophyll-based photocatalyst; Mesoporous material; Methyl orange; Photoreduction

Chromate reduction by PVA-alginate immobilized streptomyces griseus in a bioreactor - Poopal, Ashwini C.; Laxman, Ryali Seeta (Biotechnology Letters, 2009)
Microbial reduction of toxic Cr(6+) to the less toxic Cr(3+) is potentially a useful bioremediation process. Among the matrices tested for whole cell immobilization of an efficient chromate-reducing Streptomyces griseus strain, PVA-alginate was the most effective and was used for reduction of Cr(VI) in a bioreactor. Cr(6+) reduction efficiency decreased as Cr(6+) was increased from 2 to 12 mg l(-1) but increased with an increase in biomass concentration. However, increasing the flow rate from 2 to 8 ml h(-1) did not significantly affect Cr(6+) reduction. The reduction was faster in simulated effluent than in synthetic medium and complete removal of 8 mg Cr(6+) l(-1) from effluent and synthetic medium occurred in 2 and 12 h, respectively. Our results indicate that immobilized S. griseus cells could be applied for the large-scale bioremediation of chromate-containing effluents and wastewaters.
Keywords: Bioremediation; Chromate reduction; Immobilized cells; Polyvinyl alcohol-alginate; Streptomyces griseus

Class II alpha-mannosidase from aspergillus fischeri: energetics of catalysis and inhibition - Shashidhara, K. S.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2009)
Energetics of the catalysis of Class II alpha-mannosidase (E.C.3.2.1.24) from Aspergillus fischeri was studied. The enzyme showed K(cat)/K(m) for Man (alpha 1-3) Man, Man (alpha 1-2) Man and Man (alpha 1-6) Man as 7488, 5376 and 3690 M(-1) min(-1), respectively. The activation energy, Ea was 15.14, 47.43 and 71.21 kJ/mol for a1-3, alpha 1-2 and alpha 1-6 linked mannobioses, respectively, reflecting the energy barrier in the hydrolysis of latter two substrates. The enzyme showed K(cat)/K(m) as 3.56 x 10(5) and 4.61 x 10(5) M(-1) min(-1) and E(a) as 38.7 and 8.92 kJ/mol, towards pNP alpha Man and 4-MeUmb alpha Man, respectively. Binding of Swainsonine to the enzyme is stronger than that of 1-deoxymannojirimycin. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Mannosidase; Energy of activation; kinetics; Swainsonine

Click chemistry based rapid one-pot synthesis and evaluation for protease inhibition of new tetracyclic triazole fused benzodiazepine derivatives - Mohapatra, Debendra K.; Maity, Pradip K.; Shabab, M.; Khan, Mohammad Islam (Bioorganic & Medicinal Chemistry Letters, 2009)
We describe herein a one-pot synthesis of novel tetracyclic scaffolds that incorporate a fusion of a proline, 1,2,3-triazole ring with [1,4]-benzodiazepin-8(4H)-one ring systems following click chemistry. The expected peptide bond formation followed by in situ 1,3-dipolar cycloaddition in absence of any catalyst led to the formation of new triazole fused benzodiazepine derivatives. (C) 2009 Published by Elsevier Ltd.

Click synthesis of isomeric compounds for assessing the efficiency of the bifurcated Br center dot center dot center dot NO2 synthon - Ramana, C. V.; Chatterjee, Soumitra; Durugkar, Kulbhushan A.; Gonnade, Rajesh G. (Crystengcomm, 2009)
We report herein the extention of the azide-alkyne ``click reaction'' to crystal engineering and synthesize a collection of isomeric compounds with modular positioning of Br and NO2 on a tricyclic template and crystal structural analyses of the derived isomers. It is quite remarkable to notice that none of the isomers displayed the bifurcated three-center NO2 center dot center dot center dot Br supramolecular synthon in their crystal structures

Clickable SBA-15 mesoporous materials: synthesis, characterization and their reaction with alkynes - Malvi, Bharmana; Sarkar, Bibhas R.; Pati, Debasis; Mathew, Renny; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam (Journal of Materials Chemistry, 2009)
SBA-15 mesoporous silica has been functionalized with azidopropyl groups through both one-pot co-condensation and post-synthetic grafting. For both these methodologies, azidopropyltriethoxysilane was used to introduce the azidopropyl groups. The azidopropyl modified SBA-15 material synthesized by one-pot co-condensation had hexagonal crystallographic order, pore diameters up of 50 angstrom, and the content of azidopropyl groups was found to be 1.3 mmol g(-1). The presence of the azidopropyl group was confirmed by multinuclear ((13)C, (29)Si) solid state NMR and IR spectroscopy. Both these materials underwent very efficient Cu(I)-catalyzed azide alkyne ``click'' reaction (CuAAC) with a variety of alkynes. Nearly 85% of the azide present in the SBA-15 material was converted to the corresponding triazole when propargyl alcohol was used as the substrate. This methodology was also used to incorporate mannose into SBA-15. Incubation of this mannose labeled SBA-15 with fluorescein labeled Concanavalin-A led to the formation of a fluorescent silica-protein hybrid material. The ease of synthesis for the azide labeled SBA-15 material together with its ability to undergo very efficient chemoselective CuAAC in water would make it a very attractive platform for the development of covalently anchored catalysts, enzymes and sensors.

CNS Depressant activity of ethanol extract of sterculia guttata seeds in mice - Katade, S. R.; Misar, Ashwini V.; Mujumdar, Arvind M.; Phalgune, U. D.; Wakharkar, R. D.; Deshpande, N. R. (Indian Journal of Pharmaceutical Sciences, 2009)
Shade dried, powdered seeds of Sterculia guttata were extracted using a Soxhlet extractor with ethanol. Ethanol was removed under reduced pressure and dried to obtained crude extract. This extract was evaluated for its effect on behavioral changes, exploratory activity and barbiturate-sleeping time, using appropriate standard methods in mice. The extract exhibited dose-dependent CNS depressant activity.
Keywords: Barbitone sodium; CNS depressant activity; pentobarbitone sodium; Sterculia guttata Roxb.; Swiss albino mice

CO sensor based on polypyrrole functionalized with iron porphyrin - Paul, Santhosh; Amalraj, Francis; Radhakrishnan, S. (Synthetic Metals, 2009)
Polypyrrole (PPy) was chemically functionalized with 5,10,15,20-tetraphenyl-21H,23H-porphyrin iron(III) chloride (FeTPPCl) with special interest on noxious carbon monoxide (CO) gas in ppm level. Controlled functionalization of PPy was achieved with incorporation of various concentrations of porphyrin. The resulted semiconducting material was well characterized by different techniques such as UV-vis spectroscopy, FTIR, GFAAS, XRD, and EDAX. The functionalized polypyrrole material on interdigitated electrode was experienced an immediate increase in resistance when exposed to carbon monoxide gas at very low concentration. The CO gas interacted very fast with the FeTPPCl functionalized PPy at room temperature (RT) and then slowly saturated. The response of these materials was not unidirectional, but reverses to the original resistance level when CO was removed from the test chamber. The highest response factor (Delta R/R(0) x 100) and lowest response time (t(50)) obtained are 12 and 169s, respectively. An optimum level of doping (1 mol% of FeTPPCl) was established for the highest sensitivity and the detection level is as low as 100ppm. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; Fe(III) porphyrin; polypyrrole

Cobalt(II) chloride hexahydrate-diisopropylamine catalyzed mild and chemoselective reduction of carboxylic esters with sodium borohydride - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Synthesis-Stuttgart, 2009)
The cobalt-catalyzed reduction of unsaturated alpha-cyano carboxylic esters using sodium borohydride (NaBH(4)) leads to the corresponding saturated cyano alcohols in high yields. In particular, the new catalytic system cobalt(II) chloride-diisopropylamine in combination with NaBH(4) showed excellent activity in the chemoselective reduction of a variety of carboxylic esters to their corresponding alcohols in good to excellent yields under mild conditions.
Keywords: Alcohols; amines; catalysis; Esters; reductions

Column liquid chromatography-ultraviolet and column liquid chromatography/mass spectrometry evaluation of stress degradation behavior of escitalopram oxalate - Dhaneshwar, Sunil R.; Mahadik, Mahadeo V.; Kulkarni, Mahesh J. (Journal of AOAC international, 2009)
{The objective of this work was to study the degradation behavior of escitalopram oxalate under different International Conference on Harmonization (ICH)-recommended stress conditions by column liquid chromatography (LC)-UV and LC/mass spectrometry (LC/MS) and to establish a validated stability-indicating LC assay method. Escitalopram oxalate was subjected to stress conditions of hydrolysis, oxidation, photolysis, and thermal decomposition. Extensive degradation was found to occur in alkaline medium. Mild degradation was observed in acidic and oxidative conditions. Escitalopram oxalate was stable to neutral, photolytic, and thermal stress. Successful separation of the drug from degradation products formed under stress conditions was achieved on a PerfectSil-100 ODS-3 column [C(18) (5 mu m, 25 cm x 4.6 mm id)] using methanol-0.01 M acetate buffer pH 3.8 adjusted with acetic acid (45 + 55) as the mobile phase. The flow rate was 1 mL/min, and the detection wavelength was 239 nm. The method was validated according to ICH guidelines. Major degradation products formed in hydrolysis and oxidative conditions were isolated, and structural elucidation of degradation products was done by LC/MS and infrared spectrometry studies. The major hydrolysis degradation product was confirmed as 1-(3-dimethylaminopropyl)-1-(4-fluoro-phenyl)-1,3dihydroisobenzofuran-5- carboxylic acid, and the major oxidative degradation product was confirmed as 1-{[3-dimethylamino(oxide)-propyl]-1(4-flurophenyl)}-1,3-dihydro-iso benzofuran-5-carbonitrile.

Combinatorial library of primaryalkylammonium dicarboxylate gelators: a supramolecular synthon approach - Sahoo, Pathik; Adarsh, N. N.; Chacko, George E.; Raghavan, Srinivasa R.; Puranik, Vedavati G.; Dastidar, Parthasarathi (Langmuir, 2009)
Following the supramolecular synthon approach, a combinatorial library comprising 35 organic salts derived from 7 dicarboxylic acids (malonic, succinic-, adipic, L-tartaric-, maleic-, phthalic-, and isophthalicacid) and 5 primaryalkyl amines Me-(CH2)(n)-NH2 (n = 11 - 15) was prepared and scanned for gelation. About 66% of the salts in the combinatorial library were found to show moderate to good gelling ability in various polar and nonpolar solvents including commercial fuels such as petrol. The majority of the salts having a rigid, unsaturated anionic backbone (maleate, phthalate, and isophthalate) did not show gelation; only the corresponding hexadecylammonium salts showed gelation. Some of the representative gels were characterized by rheology, small-angle neutron scattering (SANS), optical microscopy (OM), and scanning electron microscopy (SEM). Single-crystal structures of two gelator and two nongelator salts were also discussed in the context of supramolecular synthon and structure-property correlation.

Combustion synthesis of triangular and multifunctional ZnO1-xNx (x <= 0.15) materials - Mapa, Maitri; Gopinath, Chinnakonda S. (Chemistry of Materials, 2009)
The preparation and characterization of multifunctional ZnO1-xNx (x <= 0.15) via a simple solution combustion method is reported. ZnO1-xNx exhibits visible light absorption, thermal stability, nanometer-/ micrometer-sized triangular particles, and catalytic properties. X-ray diffraction studies of ZnO1-xNx, demonstrate that the lattice oxygen in ZnO is replaced by nitrogen without any major change in the wurtzite structure; however, charge compensation occurs, because of interstitial Zn atoms, as well as oxygen vacancies. Microscopic studies reveal the dominance of nanometer- and micrometer-sized triangles of ZnO1-xNx. UV-visible and Raman spectra indicate a midgap state, derived from N 2p states, and direct Zn-N interaction, respectively. Secondary ion mass spectrometry studies show the presence of N and ZnN species in the bulk and support the direct Zn-N interaction. Electron paramagnetic resonance (EPR) studies indicate the presence of a small amount of defects. Photocatalytic decomposition of rhodamine B, and anisole acylation at room temperature, highlights the effectiveness of ZnO1-xNx to catalysis applications. The aforementioned multifunctional characteristics suggest that ZnO1-xNx might be used in place of conventional ZnO for better control and that it might be explored for further applications in catalysis and optoelectronics.

Comparative studies of two araceous lectins by steady state and time-resolved fluorescence and CD spectroscopy - Dharker, Poorva N.; Gaikwad, Sushama M.; Suresh, C. G.; Dhuna, Vikram; Khan, Mohammad Islam; Singh, Jatinder; Kamboj, Sukhdev Singh (Journal of Fluorescence, 2009)
Transitions in the tryptophan microenvironment and secondary structure of two monocot lectins from Sauromatum guttatum and Arisaema tortuosum under different denaturing conditions were studied by steady state and time resolved fluorescence and CD spectroscopy. The lectins exist as tetramers with a single tryptophan residue estimated per monomer, present in a polar environment. Quenching with ionic quenchers showed predominantly electropositive environment for tryptophan residues. Acrylamide had maximum quenching effect. A decrease in KI quenching due to lectin denaturation indicated redistribution of charges as a result of possible conformational change. The two values for lifetimes of tryptophanyl population (1.2-1.4 and 6.3-6.4 ns) reduced substantially on quenching or denaturation. Similarly, both the lectins showed a drastic loss of secondary structure in 5 M Gdn-HCl or 6 M Urea or at pH 2.0 and below. For the first time araceous lectins, like legume lectins are shown to bind adenine. The presence of a compact structure at alkaline pH 10.0-12.0 was observed in CD spectra.
Keywords: Araceae lectins; Denaturation; fluorescence; Lifetime spectroscopy; Secondary structure

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia

Comparing ultraviolet and chemical reduction techniques for enhancing photocatalytic activity of silver oxide/silver deposited nanocrystalline anatase titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K.; Warrier, K. G. K. (Journal of Physical Chemistry C, 2009)
Silver oxide/silver have been deposited, with varying silver concentration (0.01-10 mol %), on the surface of sol-gel derived nanocrystal line anatase titania using two different techniques, namely the ultraviolet reduction and chemical reduction (using stannous ions). The pure and silver oxide/silver-deposited nanocrystalline anatase titania have been characterized for their morphology, average nanocrystal lite size, specific surface area, phases involved, surface chemistry, band gap, and photoluminescence using various analytical techniques, such as scanning electron microscopy, transmission electron microscopy, Brunauer, Emmett, and Teller surface-area measurement, X-ray diffraction, X-ray photoelectron spectroscopy, ultraviolet-visible spectrophotometry, and spectrofluorometry, respectively. The photocatalytic activity of pure and silver oxide/silver-deposited nanocrystalline anatase titania has been measured by monitoring the degradation of methylene blue dye in an aqueous solution under ultraviolet-radiation exposure. Within the investigated Ag-concentration range, the maximum photocatalytic activity has been observed for 0.1 and 10 mol % Ag for the chemical-reduction (using stannous ions) and ultraviolet-reduction methods with the corresponding apparent first-order reaction-rate constant (k(app)) values of 0.228 and 0.151 min(-1), which are 3.5 and 2.3 times larger than that of pure nanocrystalline anatase fitania (0.065 min(-1)). The chemical-reduction method (using stannous ions), hence, appears to be more effective than the ultraviolet-reduction method for enhancing the photocatalytic activity of nanocrystalline anatase titania. Various factors such as the surface concentration of superoxide ions, oxygen-ion vacancies, and stannous ions as well as the amount of silver oxide/silver and tin oxide are observed to control the surface-adsorption of methylene blue and photoinduced electron/hole lifetime and, hence, variation in the photocatalytic activity as a function of silver concentration.

Comparison of feature selection and classification combinations for cancer classification using microarray data - Vijayan, V.; Bulsara, B.; Gadgil, Chetan J.; Gadgil, Mugdha (International Journal of Bioinformatics Research and Applications, 2009)

Complex permeability studies of Ni-Co-Zn ferrites synthesized by an oxalate precursor method - Ghodake, J. S.; Kambale, R. C.; Kulkarni, S. D.; Sawant, S. R.; Suryavanshi, S. S. (Smart Materials & Structures, 2009)
Nanocrystalline Co-substituted Ni-Zn ferrites have been synthesized by employing a co-precipitation technique using oxalate precursors. The co-precipitated oxalates were decomposed in air at 650 degrees C for 1 h and the powder was sintered at 1000 degrees C. The phase formation of the sintered ferrite was confirmed by x-ray diffraction studies. The lattice parameter a (angstrom) increases with the addition of Co(2+) which is attributed to the large ionic size of Co(2+) (0.78 angstrom), which replaces Ni(2+) (0.74 angstrom). The crystallite size has been estimated by the Debye-Scherrer formula using the full width at half-maximum (FWHM) of the line broadening of the (311) reflection and it is found to be in the range of 25-28 nm. Also, with increasing cobalt content the magnetocrystalline anisotropy constant (K(1)) and magnetostriction constant (lambda(s)) increase, and the grain size decreases, hence the value of initial permeability mu(i) decreases. The saturation magnetization M(s) and magnetic moment (n(B)) do not show any significant variation for all compositions varying with the cobalt content.

Composites of plasma treated poly(etherimide) films with gold nanoparticles and lysine through layer by layer assembly: a ``friendly-rough'' surface for cell adhesion and proliferation for tissue engineering applications - D'Britto, Virginia; Tiwari, S.; Purohit, V.; Wadgaonkar, P. P.; Bhoraskar, S. V.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2009)
A composite film fabricated by plasma treated poly(etherimide) with subsequent deposition of gold nanoparticles and lysine using layer by layer assembly has been demonstrated to be good for cell attachment and proliferation making it an attractive strategy for tissue engineering applications. As compared to the other methods the decrease in contact angle obtained here does not depend much on the plasma treatment thus affecting the polymer structure minimally. A combination of surface roughness provided by the gold nanoparticles and the presence of amine groups of lysine is hypothesized to be the reason for the features observed.

Computational study of electronic structure, thermodynamics and kinetics of hydrogen desorption from Al- and Si-doped alpha-, gamma-, and beta-MgH2 - Kelkar, Tuhina; Pal, Sourav (Journal of Materials Chemistry, 2009)
First principles calculations of pure and Al-and Si-doped alpha-, gamma-, and beta-MgH2 were performed to investigate the influence of Al and Si as impurities and the presence of high pressure phases on the properties of hydrogen sorption of magnesium hydride. The ab initio plane wave pseudopotential method based on density functional theory within the generalized gradient approximation was used in the present study. The total energies of the considered systems were calculated as a function of cell volume to obtain material properties such as bulk modulus K-0, equilibrium cell volume V-0 and minimum energy E-0(V-0). From the density of states (DOS) analysis, it was shown that doping MgH2 with Al and Si caused a reduction in the band gaps of each of the three phases. The diminished band gaps made the Mg-H bond more susceptible to dissociation. The destabilization of the hydrides was reflected in the decreased heats of formation of the doped hydrides, with the following Delta H-f order: Si < Al and beta < gamma < alpha. A 30.5% reduction in the activation energy barrier E-act for H-2 desorption was calculated for the Al-doped alpha-MgH2(001) surface and a 15.5% decrease in E-act of the Si-doped gamma-MgH2(001) surface was deduced, while doping with Al and Si increased the activation energy barrier for the beta-MgH2 (001) surface drastically.

Concise enantioselective synthesis of 1-[(S)-3-(dimethylamino)-3,4 dihydro-6,7-dimethoxyquinolin-1(2H)-yl]propan-1-one, (S)-903 - Jagdale, Arun R.; Reddy, R. Santhosh; Sudalai, Arurnugam (Tetrahedron-Asymmetry, 2009)
A concise enantioselective synthesis of (S)-903, an inotropic agent, is described in nine linear steps and 95% ee based on asymmetric dihydroxylation of cinnamate ester and Co-catalyzed Multifunctional reduction of several functional groups leading to the construction of core tetrahydroquinolin-3-ol, as the key steps. (C) 2009 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of (+)-decarestrictine L via proline-catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination - Rawat, Varun; Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A short enantioselective synthesis of (+)-decarestrictine L, a cholesterol biosynthesis inhibitor metabolite, is described using a D-proline catalyzed sequential alpha-aminooxylation and a Horner-Wadsworth-Emmons olefination. (C) 2009 Elsevier Lid All rights reserved

Concise enantioselective synthesis of (+)-febrifugine - Emmanuvel, Lourdusamy; Kamble, Dayanand A.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A short enantioselective synthesis of (+)-febrifugine, a potent antimalarial alkaloid, has been described based on the regioselective asymmetric dihydroxylation of a 1,4-dienic ester as the key step. The strategy also involves chemoselective [3,3]-sigmatropic rearrangement of 1,5-hexadiene-3-ol and intramolecular lactamization of azidolactone for the construction of piperidine core. (C) 2008 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of (+)-lentiginosine - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A high yielding enantioselective synthesis of the indolizidine alkaloid, (+)-lentiginosine, has been described based on asymmetric oza-Cope rearrangement and the L-proline catalyzed alpha-aminooxylation of aldehydes. The strategy also makes use of ring-closing metathesis for the construction of piperidine core. (C) 2009 Elsevier Ltd. All rights reserved.

Concurrent In-situ formation of Ag/Ag2S nanoparticles in polymer matrix by facile polymer-inorganic solid state reaction - Waghmare, Sujata; Shinde, Manish; Gholap, Ramkrishna S.; Rao, N. Koteswara; Hawaldar, Ranjit R.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Journal of Nano Research, 2009)
We herein report the feasibility of polymer-inorganic solid-state reaction route for simultaneous in situ generation of Ag & Ag2S nanostructures in polymer network wherein an engineering thermoplastic, polyphenylene sulphide (PPS), itself acts as a chalcogen source as well as a stabilizing matrix for the resultant nanoproducts. Typical solid-state reaction was accomplished by simply heating the physical admixture of the two reactants i.e. AgNO3 and PPS by varying molar ratios mainly 1:1, 1:5, 1:15, 1:20, at the crystalline melting temperature (285 degrees C) of PPS. The synthesized nanoparticles were characterized by various physico-chemical techniques like X-ray Diffractometry, Scanning Electron Microscopy equipped with EDAX, Transmission Electron Microscopy and UV-Visible spectroscopy. The prima facie observations suggest the effective formation and subsequent entrapment of mainly nanocrystalline metallic silver (fcc) in PPS matrix for all the molar ratios chosen for the reaction. Additionally, simultaneous occurrence of nanocrystalline Ag2S (monoclinic phase) is also noticed in case of heated admixture of AgNO3: PPS with equimolar ratio. The TEM analysis reveals nanoscale polydispersity (5nm to 70nm) and prevalence of mainly spherical morphological features in all the cases with occasional indications of triangular and hexagonal morphological features depending upon the reaction molar ratio.
Keywords: Ag; Ag2S; Nanoparticles; Polymer inorganic solid -state reaction; Thermoplastic polymer matrix

Conducting polyaniline-nano-TiO2 composites for smart corrosion resistant coatings - Radhakrishnan, S.; Siju, C. R.; Mahanta, Debajyoti; Patil, Satish; Madras, Giridhar (Electrochimica Acta, 2009)
Coatings prepared from polyaniline-nano-TiO2 particles synthesized by in situ polymerization were found to exhibit excellent corrosion resistance much superior to polyaniline (PANI) in aggressive environments. The corrosion Studies were carried out on steel plates coated with these formulations containing 10 wt% polyaniline prepared with different concentrations of nano-TiO2. The electrochemical impedance spectroscopy was studied at periodic intervals during exposure to hot saline (65 degrees C) conditions for prolonged durations over a period of 90 h. The open circuit potential (OCP) was found to shift with time from -0.38 V SCE to more anodic side (-0.2 V SCE) much above that of bare steel (-0.5 VSCE). The presence of nano-TiO2 was found to be vital in the prevention of corrosion and the shift of OCP to anodic side. From these data, one could envisage more than 100 times improvement in the corrosion resistance especially for polyaniline prepared with 4.18 wt% nano-TiO2. The exceptional improvement of performance of these coatings has been associated with the increase in barrier to diffusion, prevention of charge transport by the nanosize TiO2, redox properties of polyaniline as well as very large surface area available for the liberation of dopant due to nano-size additive. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Anticorrosion; Coating; conducting polymer; Nano-composite; Titanium dioxide

Conformational characterization of human eukaryotic initiation factor 2 alpha: a single tryptophan protein - Sreejith, R. K.; Yadav, Viveka Nand; Varshney, Nishant K.; Berwal, Sunil K.; Suresh, C. G.; Gaikwad, Sushama M.; Pal, Jayanta K. (Biochemical and Biophysical Research Communications, 2009)
The alpha-subunit of the human eukaryotic initiation factor 2 (heIF2 alpha), a GTP binding protein, plays a major role in the initiation of protein synthesis. During various cytoplasmic stresses, eIF2 alpha gets phosphorylated by eIF2 alpha-specific kinases resulting in inhibition of protein synthesis. The cloned and over expressed heIF2 alpha, a protein with a single tryptophan (trp) residue was examined for its conformational characteristics using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The steady-state fluorescence spectrum, fluorescence lifetimes (tau(1) = 1.13 ns and tau(2) = 4.74 ns) and solute quenching studies revealed the presence of trp conformers in hydrophobic and differential polar environment at any given time. Estimation of the alpha-helix and beta-sheet content showed: (i) more compact structure at pH 2.0, (ii) distorted alpha-helix and rearranged beta-sheet in presence of 4 M guanidine hydrochloride and (iii) retention of more than 50% ordered structure at 95 degrees C. Hydrophobic dye binding to the protein with loosened tertiary structure was observed at pH 2.0 indicating the existence of a molten globule-like structure. These observations indicate the inherent structural stability of the protein under various denaturing conditions. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Circular dichroism; heIF2 alpha; K562 cells; Molten globule; Steady-state and time-resolved fluorescence

Consequence of hazards on some petroleum storage tanks and model for off-site emergency plan - Biswajit, Ruj; Chattaraj, Pratim Kumar; Rehman, I; Ray, B. C. (Disaster Advances, 2009)
Explosions, fire and the release of toxic gase cause deaths and injuries to workers and the public, resulting in the evacuation of communities and adversely affecting the environment as a whole. The primary objective of the off-site emergency plan for a hazardous installation is the prevention of accidents. The prevention of accidents involving hazardous substances is the concern of everyone. The poolfire from a petroleum storage tank leads to fatal consequences. This paper highlights some salient features of the emergency scenario from four petroleum storage tanks situated in Budge Budge area, 24 Pgs(S), West Bengal, which ultimately lead to poolfire with enormous heat wave all around and their consequence analysis, affected areas, rescue and evacuation plans, communication and public information systems, roles and responsibilities of the district emergency authority, police, fire and medical authorities.
Keywords: MAH industries; Off-site emergency plan; Petroleum storage tank; Poolfire; radial distance

Continuous flow nitration of benzaldehyde - Kulkarni, Amol A.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2009)
The nitration of benzaldebyde can be carried out in a safe manner in continuous mode using a microreactor system. Choice of a micromixer was seen to affect the performance of this two-phase reaction significantly The reaction time could he brought down to 2 min by increasing the reaction temperature and thereby taking advantage of higher heat transfer area. The simple T-micromixer is seen to be inefficient for two-phase reactions. Further scope of process intensification is also discussed.

Continuous hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-Methylphenol) in a fixed bed reactor - Garade, Ajit C.; Hengne, Amol M.; Deshpande, Tushar N.; Shaligram, Sayali V.; Shirai, Masayuki; Rode, Chandrashekhar V. (Journal of Chemical Engineering of Japan, 2009)
{Catalytic activity of various solid acid catalysts is evaluated for the continuous hydroxyalkylation of p-cresol to [

Control of molecular aggregation in symmetrically substituted pi-conjugated bulky poly(p-phenylenevinylene)s and their copolymers - Resmi, R.; Amrutha, S. R.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
A new series of symmetrically substituted bulky PPV-copolymers based on poly(bis-2,5-(2-ethylhexyloxy)-1,4-phenylenevinylene) (BEH-PPV) bearing tricyclodecane (TCD) pendants were synthesized to study the effect of chain aggregation in the pi-conjugated polymer backbone. The composition of the copolymers was varied up to 100 mol % and the structures of the copolymer were confirmed by NMR and FTIR. The molecular weights of the copolymers were obtained as M(w) = 11,500-1,78,800 depending on the TCD-incorporation in BEH-PPV. The origin of the pi-aggregation was investigated using mixture of solvents (polar or nonpolar) or temperature as external stimuli. Absorption, photoluminescence, and time-resolved fluorescence decay techniques were employed as tools to trace molecular aggregation in solution and solid state. The TCD-substituted bulky copolymers showed almost twice the enhancement in photoluminescence compared with that of BEH-PPV Solvent-induced aggregation studies of copolymers revealed the existence of strong molecular aggregation in BEH-PPV compared with that of bulky copolymers. Variable temperature studies further evidence for the reversibility of molecular aggregation on beating/cooling cycles and showed isosbetic points with respect to free and aggregated polymer chains. Time-resolved fluorescent studies confirmed the existence of free and aggregated pi-conjugated species with a life time of 0.1 to 1.0 ns. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2631-2646, 2009
Keywords: conjugated polymers; fluorescence; poly(p-phenylenevinylene); solution properties; Structure-property relationship

Convenient synthesis of enantiomerically pure (R)-mexiletine using hydrolytic kinetic resolution method - Sasikumar, Murugesan; Nikalje, Milind D.; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2009)
Enantiopure (R)-mexiletine was prepared in a simple and practical way using hydrolytic kinetic resolution method of terminal epoxide by Jacobsen catalyst. High enantiomeric purity (98% ee) was achieved and the method is well amenable to industrial scale-up. (C) 2009 Elsevier Ltd. All rights reserved.

Copper (I) complexes of a thioether-functionalized short-bite aminobis(phosphonite) - Punji, Benudhar; Mague, Joel T.; Mobin, Shaikh M.; Balakrishna, Maravanji S. (Polyhedron, 2009)
Copper(I) complexes of short-bite aminobis(phosphonite), PhN{P(–OC10H6(μ-S)C10H6O–)}2 (1) have been synthesized. Reactions of 1 with an excess of CuX (X = Cl, Br, and I) afforded the ligand-bridged binuclear complexes, [PhN(PR-κP)2{Cu(μ-X)(MeCN)}2] (2, X = Cl; 3, X = Br; 4, X = I; R = –OC10H6(μ-S)C10H6O–), whereas treatment with 0.5 equiv. of [Cu(MeCN)4]PF6 produces the mononuclear bischelated cationic complex, [{PhN(PR-κP)2}2Cu](PF6) (5). Single crystal X-ray structures of complexes 3 and 4 are reported. Complex 3 shows strong π–π stacking interactions between the naphthyl moieties, whereas complex 4 shows ligand-supported Cu⋯Cu metallophilic interactions.

Copper-based catalysts for water gas shift reaction: influence of support on their catalytic activity - Pradhan, S.; Reddy, A. Satyanarayana; Devi, R. N.; Chilukuri, Satyanarayana V. (Catalysis Today, 2009)
Three copper containing catalysts supported on ceria and mixed oxides of ceria with zirconia and titania were prepared by co-precipitation method and their catalytic activity was tested for water gas shift (WGS) reaction. High surface area (>100m(2)/g) mixed oxides were obtained following the present method of preparation. The catalysts were characterized by XRD, H(2)-temperature programmed reduction (TPR), UV-vis and XPS. Catalytic activity was evaluated for water gas shift reaction in the 200-400 degrees C temperature range, The gas hourly space velocity was varied from 5000 to 25,000h(-1) for better evaluation and comparison of their performance. The effect of CO(2) in the feed gas mixture on the WGS activity of these catalysts was also studied. Among the three catalysts studied, CuO-CeO(2)-ZrO(2) mixed oxide shows better activity, implying the influence of support. Characterization of the catalysts after WGS reaction was also carried out in order to investigate structure-property correlation. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: ceria; Ceria-titania; Ceria-zirconia; Co-precipitation; Copper; Water gas shift

Copper-catalyzed synthesis of 2-unsubstituted, n-substituted benzimidazoles - Hirano, Keiichi; Biju, Akkattu T.; Glorius, Frank (Journal of Organic Chemistry, 2009)
An efficient copper-catalyzed intramolecular arylation of formamidines forming 2-unsubstituted benzimidazoles in excellent yields is reported. Sixteen examples bearing sterically demanding substituents on nitrogen like Mes, 2,6-diisopropylphenyl, or 2-tert-butylphenyl and tolerating various functional groups demonstrate the utility of this method.

Correlations of thermodynamic properties of aqueous amino acid-electrolyte mixtures - Saritha, C.; Satpute, Dilip B.; Badarayani, Rohini; Kumar, Anil (Journal of Solution Chemistry, 2009)
Suitable equations have been proposed to correlate thermodynamic properties, like mean ion activity coefficients, volumes and compressibilities, of amino acids in electrolyte solutions. An amino acid-electrolyte-water interaction parameter is extracted from the regression of the amino acid property values in aqueous electrolyte solution that is then transferred to an expression to correlate the properties of the electrolyte in mixtures. The single interaction parameter can successfully correlate the published data on mean ion activity coefficients, apparent molar volumes and compressibilities of amino acids as well as of electrolytes in their aqueous mixtures. The equations are tested against the large number of experimental data sets available in the literature.
Keywords: Amino acids; Electrolytes; Pitzer equation; Thermodynamic properties

Cu(I)-promoted one-pot `SNAr-click reaction' of fluoronitrobenzenes - Durugkar, Kulbhushan A.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2009)
A one-pot two-step sequence involving a nucleophilic aromatic substitution (SNAF) of activated fluorobenzenes with azide nucleophile and in situ Huisgen cycloaddition of the resulting aryl azides with alkynes has been developed for a rapid access to 1,4-substituted triazoles. Control experiments revealed that both the steps are catalyzed by Cu(I) and also the course of reaction as SNAr followed by [3+2]-cycloaddition. (C) 2009 Elsevier Ltd. All rights reserved.

Cultivar relationships in mango based on fruit volatile profiles - Pandit, Sagar S.; Chidley, Hemangi G.; Kulkarni, Ram S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2009)
Aroma volatiles of mango (Mangifera indica L.) determine consumer acceptability and influence selection, whilst breeding. To assess their variety, composition and possible impact on cultivar relationships, volatile blends of 22 Indian and five non-Indian cultivars were investigated using solvent extraction and gas chromatography. Totally 84 volatiles belonging to various chemical classes were detected. Based on the Cumulative Occurrence of members of these classes, cultivars were grouped as monoterpene or sesquiterpene dominant. a-Pinene, beta-myrcene and beta-caryophyllene were found in all 27 cultivars. For ordination, common compounds with high (relative) concentration provided quantitative characters, whereas the rare and lesser ones provided qualitative (binary) characters; non-Indian cultivars separated from Indian ones but displayed close relations within their groups. In conclusion, mango flavour is dominated qualitatively as well as quantitatively by terpene hydrocarbons; ancient selection of mango cultivars is hinted to be driven by different aroma characters in different parts of the world. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Flavour; GC-MS; Mangifera indica; Multivariate analysis; Ordination

Cu(OTf)(2)-catalyzed alpha-halogenation of ketones with 1,3-dichloro-5,5 `-dimethylhydantoin and N-bromosuccinimide - Jagdale, Arun R.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2009)
Copper(II) triflate catalyses efficiently the alpha-halogentation of aryl or alkyl ketones with 1,3-dichloro-5,5'-dimethyl-hydantoin and N-bromosaccinimde to give the corresponding alpha,alpha-dichloroketones and alpha-bromoketones in high yield with excellent product selectivity.
Keywords: Bromination; Catalyst; chlorination; copper (II); Ketone; Lewis acid

Calculation of dipole transition matrix elements and expectation values by vibrational coupled cluster method - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Theory and Computation, 2010)
An effective operator approach based on the coupled cluster method is described and applied to calculate vibrational expectation values and absolute transition matrix elements. Coupled cluster linear response theory (CCLRT) is used to calculate excited states. The convergence pattern of these properties with the rank of the excitation operator is studied. The method is applied to a water molecule. Arponen-type double similarity transformation in extended coupled cluster (ECCM) framework is also used to generate an effective operator, and the convergence pattern of these properties is compared to the normal coupled cluster (NCCM) approach. It is found that the coupled cluster method provides an accurate description of these quantities for low lying vibrational excited states. The ECCM provides a significant improvement for the calculation of the transition matrix elements.

Carbon dissolution and segregation in Pd(110) - Bowker, Michael; Counsell, Jonathan; El-Abiary, Kareem; Gilbert, Lee; Morgan, Chris; Nagarajan, Sankaranarayanan; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2010)
The bulk-surface diffusion of carbon in Pd(110) has been investigated using Molecular beams to examine the clean-off of carbon with gas-phase oxygen. The dominant product of the reaction above 600 K is CO CO, is only produced at much lower temperatures where the lifetime of adsorbed CO is significant. The segregation from the bulk Only Occurs at a measurable rate at >750 K, while loss of carbon into the bulk call occur at much lower temperatures. The reaction of carbon at high temperatures shows two regimes: (i) a non steady-state evolution of CO due to the clean-off of surface carbon already present on the surface, followed by (ii) a near steady-state reaction due to the continuous diffusion of carbon to the surface.

Catalytic asymmetric transfer hydrogenation of ketones using [Ru(p-cymene)Cl-2](2) with chiral amino alcohol ligands - Deshpande, Sudhindra H.; Kelkar, Ashutosh A.; Gonnade, Rajesh G.; Shingote, Savita K.; Chaudhari, Raghunath V. (Catalysis Letters, 2010)
Catalytic asymmetric transfer hydrogenation of aromatic alkyl ketones has been investigated using [Ru(p-cymene)Cl-2](2) and new derivatives of beta-amino alcohols synthesized from (S)-(-)-lactic acid and mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%). Asymmetric transfer hydrogenation of ketones has been investigated using [Ru(p-cymene)Cl-2](2) and beta-amino alcohols synthesized from (S)-(-)-lactic acid and Mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%).
Keywords: Amino alcohol ligand; Asymmetric transfer hydrogenation; Ketones; Ru catalyst

CDASE-A reliable scheme to explain the reactivity sequence between Diels-Alder pairs - Saha, Soumen; Roy, Ram Kinkar; Pal, Sourav (Physical Chemistry Chemical Physics, 2010)
The reliability of the Comprehensive Decomposition Analysis of Stabilization Energy (CDASE) scheme, proposed recently (Phys. Chem. Chem. Phys., 2009, 11, 8306), has been demonstrated in the present study. Reactivity sequence among more than 100 pairs, taking part in Diels-Alder (DA) reaction, is successfully generated by this scheme. The diene series consisted mainly of cis-1,3-butadiene and different substituted butadienes whereas dienophiles are mainly ethylene and its different substitutions. Both the positive energy component (i.e., the energy parameter defined as `internal assistance') and the negative energy component could generate the expected reactivity trend among the chosen DA pairs, which is also supported by the global electrophilicities of dienes and dienophiles and the corresponding charge-transfer values (Delta N). The numerical values of these components are capable of predicting even the `normal electron demand' (NED) and `inverse electron demand' (IED) nature of the corresponding DA reaction. The method is also capable of reproducing the lower reactivity of acetylene as dienophile when compared to that of ethylene. The reason for the success of CDASE-scheme in explaining intermolecular reactivity sequence is also analysed.

Chemical shielding of closed-shell molecules using extended coupled-cluster theory - Ravichandran, Lalitha; Joshi, Sayali; Vaval, Nayana (International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, 2010)
In this paper we report calculation of the nuclear magnetic shielding constant using extended coupled cluster response approach. We present the results for the HF, BH, CO and N(2) molecules. These results show importance of correlation corrections for the shielding constant.

Chemoselective coupling reactions of 5,7-dimethoxyphthalide with the remotely functionalized alkyl iodides: facile racemic synthesis of helicobacter pylori antibiotics - Singh, Mandeep; N. P. Argade (Journal of Organic Chemistry, 2010)
Highly chemoselective coupling reactions of 5,7-dimethoxyphthalide carbanion with the remotely functionalized long chain alkyl iodides have been demonstrated to accomplish the concise and efficient synthesis of Helicobacter pylori antibiotics, the CJ-molecules, and sporotricale methyl ether.

Chemoselective hydrogenation of cinnamaldehyde over Pd/CeO2-ZrO2 catalysts - Bhogeswararao, Seemala; Srinivas, D. (Catalysis Letters, 2010)
Selective hydrogenation of cinnamaldehyde over Pd (2 wt%) supported on CeO2, ZrO2 and CeO2-ZrO2 catalysts is reported for the first time. In general, the olefinic (C=C) group of cinnamaldehyde is preferentially hydrogenated compared to the carbonyl (C=O) group. This selectivity preference could, however, be altered or reversed by adding alkali additives to the catalyst. The influence of additive on the structure and redox properties of the active sites and correlation of that with selective hydrogenation activity is investigated.
Keywords: alpha; beta-Unsaturated aldehyde; Ceria-zirconia; Cinnamaldehyde; Hydrogenation; palladium catalyst

Chronic inflammatory responses to microgel-based implant coatings - Bridges, Amanda W.; Whitmire, Rachel E.; Singh, Neetu; Templeman, Kellie L.; Babensee, Julia E.; Lyon, L. Andrew; Garcia, Andres J. (Journal of Biomedical Materials Research, 2010)

Citrate-capped quantum dots of CdSe for the selective photometric detection of silver ions in aqueous solutions - Ingole, Pravin P.; Rajiv M. Abhyankar; Bhagavatula L. V. Prasad; Haram, Santosh K. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A simple strategy for the synthesis of water soluble, luminescent, citrate-capped CdSe quantum dots (Q-CdSe) and their applications to selective detection of silver ions are described. The steady state photoluminescence (PL) spectra show single, narrow emission band at ca. 554 nm without any contribution from the trap states. The effect of various ions including physiologically important metal ions (viz. K(+), Ca(2+), Fe(3+), Zn(2+), Mg(2+), Mn(2+), Cu(2+), Ag(+), Pb(2+) and Cd(2+)), on the PL intensity of citrate-capped Q-CdSe has been studied. Among these, selective luminescence quenching with Ag(+) ion was found to be predominant. Under the optimum conditions, the response was linear between 1.7 and 18 mu M. The quenching constant K(SV) was found to be ca. 3.4 x 10(5) M(-1). The mechanism of photoluminescence quenching of Q-CdSe by metal ions (Ag(+)) is also discussed. Based on these studies, the potential use of Q-CdSe as a luminescent probe for the selective detection of silver ion has been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag(+) ions; Luminescence quenching; Luminescent probe; Q-CdSe; Tri-sodium citrate

Clicking molecular hooks on silica nanoparticles to immobilize catalytically important metal complexes: the case of gold catalyst immobilization - Ganai, Anal Kumar; Bhardwaj, Rima; Hotha, Srinivas; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
Gold mediated reactions have emerged as one of the best choices for affecting a variety of chemical transformations with a wide range of functional group tolerance. Application of such transformations to industrial processes necessitates immobilization of the Au ions into a matrix for easy separation of the catalyst after reaction. We report the synthesis and characterization of silica nanoparticles in which Au(III) has been immobilized through a 1,2,3-triazole linkage using an alkynalated picolinic acid exploiting ``click chemistry''. The Au( III) immobilized silica nanoparticle has been thoroughly characterized using FT-IR, C-13 CP MAS NMR and XPS. The utility of these particles as an easily separable catalyst for the Hashmi phenol synthesis is also reported.

Cobalt nanoparticles doped emaraldine salt of polyaniline: a promising room temperature magnetic semiconductor - Hatamie, Shadie; Kulkarni, M. V.; Kulkarni, S. D.; Ningthoujam, R. S.; Vatsa, R. K.; Kale, Sangeeta N. (Journal of Magnetism and Magnetic Materials, 2010)
Incorporation of magnetic nanoparticles in polymers with organic functional groups working as semiconducting substrate is of immense interest in the field of dilute magnetic semiconductors (DMS) and spintronics. In this article we report on synthesis and evaluation of dilutely doped (0-10 wt%) cobalt nanoparticles in emaraldine salt (ES) of polyaniline in the presence of dodecyl benzene sulfonic acid (DBSA) and p-toluene sulfonic acid (p-TSA) using a sonochemical-assisted-reduction approach as a possible DMS candidate. The X-ray diffraction pattern and high resolution transmission electron microscopy (HRTEM) image show the ES to be polycrystalline, in which 10 nm sized Co nanoparticles get embedded in its FCC structural form. From Fourier transform infrared (FT-IR) and UV-visible (UV-vis) spectroscopy studies, it is predicted that cobalt particles get electrostatically bound to the specific SO(3)(-) ion sites of ES, thereby modifying torsional degrees of freedom of the system. The applied field dependent magnetization study shows that the sample exhibits hysteresis loop with a minimal doping of 3 wt% of Co nanoparticles and increases with the amount of Co nanoparticles in ES due to dipolar interaction. The electron transport data show that with increase in Co wt% there is a gradual shift from ohmic to non-ohmic response to the sample bias, accompanied by opening of electrical hysteresis and an increased resistance. The non-linear response of higher doped systems has been attributed to the combination of direct and Fowler-Nordheim tunneling phenomena in these systems. Persistence of optical and transport properties of the polymer, with an introduction of magnetic moment in the system, envisages the system to be a fine magnetic semiconductor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cobalt nanoparticles; Magnetic semiconductor; polyaniline

Co(III)(salen)-catalyzed HKR of two stereocentered alkoxy- and azido epoxides: a concise enantioselective synthesis of (S,S)-reboxetine and (+)-epi-cytoxazone - Reddy, R. Santhosh; Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Chavan, Vilas B.; Sudalai, Arumugam (Chemical Communications, 2010)
The HKR of racemic syn- or anti- alkoxy- and azido epoxides catalyzed by Co(salen) complex affords a practical access to a series of enantioenriched syn- or anti- alkoxy- and azido epoxides and the corresponding 1,2-diols. This strategy has been successfully employed in the concise, enantioselective synthesis of bioactive molecules such as (S, S)-reboxetine and (+)-epi-cytoxazone.

Colossal thermoelectric power in Gd-Sr manganites - Sagar, S.; Ganesan, V.; Joy, Pattayil Alias; Thomas, Senoy; Liebig, A.; Albrecht, M.; Anantharaman, Maliemadom R. (EPL, 2010)
Manganites belonging to the series Gd(1-x)Sr(x)MnO(3) (x=0.3, 0.4 and 0.5) were prepared by wet solid-state reaction and their thermoelectric power was evaluated. Thermoelectric power measurements revealed a peak value at similar to 40 K. All the samples exhibited a colossal thermopower at similar to 40K and in that Gd(0.5)Sr(0.5)MnO(3) exhibited a maximum value of similar to 35 V/K, which is the largest reported for these class of materials at this temperature. Temperature-dependent magnetisation measurements showed that the samples exhibit a phase transition from paramagnetic to spin-glass-like state at these temperatures. Plausible mechanisms responsible for the observed colossal thermoelectric power in Gd-Sr manganites are discussed. Copyright (C) EPLA, 2010

Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium

Comparison of the auxiliary density perturbation theory and the noniterative approximation to the coupled perturbed kohn-sham method: case study of the polarizabilities of disubstituted azoarene molecules - Shedge, Sapana V.; Carmona-Espindola, Javier; Pal, Sourav; Koster, Andreas M. (Journal of Physical Chemistry A, 2010)
We present a theoretical study of the polarizabilities of free and disubstituted azoarenes employing auxiliary density perturbation theory (ADPT) and the noniterative approximation to the coupled perturbed Kohn-Sham (NIA-CPKS) method. Both methods are noniterative but use different approaches to obtain the perturbed density matrix. NIA-CPKS is different froth the conventional CPKS approach in that the perturbed Kohn-Sham matrix is obtained numerically, thereby yielding a single-step solution to CPKS. ADPT is an alternative approach to the analytical CPKS method in the framework of the auxiliary density functional theory. It is shown that the polarizabilities obtained using these two methods are in good agreement with each other. Comparisons are made for disubstituted azoarenes, which give support to the push-pull mechanism. Both methods reproduce the same trend for polarizabilities because of the substitution pattern of the azoarene moiety. Our results are consistent with the standard organic chemistry ``activating/deactivating'' sequence. We present the polarizabilities of the above molecules calculated with three different exchange-correlation functionals and two different auxiliary function sets. The computational advantages of both methods are also discussed.

Concise synthesis of (2S,3S,4S)-2-(Hydroxymethyl)pyrrolidine-3,4-diol (LAB1) - Upadhyay, Puspesh K.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
The synthesis of (2S,3S,4S)-2-(hydroxymethyl)pyrrolidine-3,4-diol (LAB1) from Garner's aldehyde is described using the Sharpless asymmetric dihydroxylation as the key step.
Keywords: alkaloid; azasugars; diastereoselectivity; Garner's aldehyde; pyrrolidine; Wittig reaction

Conformational and functional transitions in class II alpha-mannosidase from aspergillus fischeri - Shashidhara, K. S.; Gaikwad, Sushama M. (Journal of Fluorescence, 2010)
The conformational transitions in an oligomeric and high molecular weight class II alpha-mannosidase from Aspergillus fischeri were examined using fluorescence and CD spectroscopy under chemical, thermal and acid denaturing conditions. The enzyme lost the activity first and then the overall folded conformation and secondary structure. The midpoint values of GdnHCl mediated changes measured by inactivation; fluorescence and negative ellipticity were 0.48 M, 1.5 M and 1.9 M, respectively. The protein almost completely unfolded in 4.0 M GdnHCl but not at 90 A degrees C. The inactivation and unfolding were irreversible. At pH 2.0, the protein exhibited molten-globule like intermediate with rearranged secondary and tertiary structures and exposed hydrophobic amino acids on the surface. This species showed increased accessibility of Trp to the quenchers and got denatured with GdnHCl in a different manner. The insoluble aggregates of a thermally denatured protein could be detected only in the presence of 0.25-0.75 M GdnHCl.
Keywords: Aggregation; alpha-Mannosidase; ANS binding; Circular dichroism; fluorescence; GdnHCl; Hydrobicity; Thermal denaturation

Conformational polymorphism in racemic 2,4-Di-o-Benzoyl-6-o-Tosyl myo-Inositol 1,3,5-Orthoacetate - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Journal of Structural Chemistry, 2010)
The title compound, C(29)H(26)O(10)S, yields two conformational polymorphs concomitantly from dichloromethane-methanol mixture; the major polymorph grows as plates (Form I, monoclinic, P2(1)/n) and the minor polymorph grows as needles (Form II, triclinic, P-1). The two forms differ mainly in orientation of the tosyl group. In Form I, sulfonyl oxygen of the tosyl group makes intermolecular C -HaEuro broken vertical bar O interactions, whereas the same group in Form II is involved in an intramolecular short dipolar S=OaEuro broken vertical bar C=O (sulfonyl-carbonyl) contact. The molecular organization and the influence of various weak non-covalent interactions that stabilize these conformers in the crystal lattices are discussed.
Keywords: Conformation; crystal structure; dipolar interactions; Inositol; non-covalent interactions; polymorphism; sulfonyl-carbonyl contact

Continuous flow synthesis of functionalized silver nanoparticles using bifunctional biosurfactants - Kumar, D. V. Ravi; Kasture, Manasi; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Green Chemistry, 2010)
Silver nanoparticles were synthesized by continuous flow methods using biosurfactants, namely, oleic acid sophorolipid (OASL) and stearic acid sophorolipid (SASL). Both the sophorolipids can act as reducing and capping agents. The effect of temperature on the completion of nanoparticle formation and the particle growth dynamics (size) were studied in batch mode. While the completion of the reaction using oleic acid sophorolipid needed 20 min, only 5 min were required with the stearic acid sophorolipid as capping and reducing agent. Hence all the continuous flow experiments were carried out using the stearic acid sophorolipid. The continuous flow synthesis of silver nanoparticles was carried out in a stainless steel helical coil and also in a spiral polymeric minichannel reactor. The DLS results show that higher flow rate leads to the formation of bigger and polydisperse particles because of incomplete reactions. Higher residence time allowed the completion of reaction leading to spherical, small and monodisperse particles.

Continuous phenol biodegradation in a simple packed bed bioreactor of calcium alginate-immobilized Candida tropicalis (NCIM 3556) - Varma, R. J.; Gaikwad, B. G. (World Journal of Microbiology & Biotechnology, 2010)
Phenol biodegradation in a continuous system of immobilized Candida tropicalis NCIM 3556 was studied. The bioreactor was simple, it had a feed inlet from the bottom and the effluent outlet from top, no supplementary oxygen was supplied, the reactor was operated continuously for 116 days. Initially the column was run continuously with a feed concentration of 2 g l(-1) for 42 days whence a degradation of > 97% was achieved. The feed concentration was then increased to 3 g l(-1), for which a similar to 80% biodegradation was sustained for 90 days after which there was a steady decrease in the performance. When the phenol degradation was reduced to similar to 50% in 116 days, the reactor was stopped. The efficiency of free cells recycled every 24 h and immobilized cells were compared; it was estimated that repeated reuse of free cells in batch mode gave an overall efficiency of 0.102 g phenol degradation g(-1) cell wet weight in 12 days. In contrast, the immobilized system of the same biomass had a longer working lifetime of similar to 4 months indicating an efficiency of 3.72 g phenol g(-1) cell wet wt.
Keywords: Biodegradation; Ca alginate; Candida tropicalis; Immobilization; phenol

Contrasting thermosolvatochromic trends in pyridinium-, pyrrolidinium-, and phosphonium-based ionic liquids - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry B, 2010)
Thermosolvatochromism has been studied in three series of ionic liquids, pyridinium-based 1-butylpyridinium, 1-hexylpyridinium, and 1-octylpyridinium with bis(trifluoromethylsulfonyl)imide [NTf2] and tetrafluoroborate [BF4] anions, pyrrolidinium-based ionic liquids 1-methyl-1-butylpyrrolidium, 1-methyl-1-hexylpyrrolidium, 1-methyl-1-octylpyrrolidium with bis(trifluoromethylsulfonyl) imide anion and phosphonium-based ionic liquids tetrabutylphosphonium with alanate and valinate anions. The effect of increase in alkyl chain length and temperature on normalized polarity E-T(N), Kanilet-Taft parameters, hydrogen bond donor ability (alpha), hydrogen bond acceptor ability (beta), and polarizability (pi*) was investigated in the temperature range of 298-353 K. Interestingly, the polarity decreases with temperature in the case of pyridinium- and pyrrolidinium-based ionic liquids, and it increases with temperature in the case of phosphonium-based ionic liquids.

Convenient approach to the synthesis of different types of schiff's bases and their metal complexes - Pradhan, Kiran; Selvaraj, Kaliaperumal; Nanda, Ashis K. (Chemistry Letters, 2010)
Various metal complexes derived from different Schiff bases are conveniently prepared using solvent-free condensation reactions in one-pot synthesis, resulting in significantly enhanced yields Initial calorimetric studies, and/or TGA of reaction mixtures, led to better optimization of reaction conditions The ligands like mines, hydrazones, semicarbazones, and nitrones are also synthesized by this method, thus this process is general and expedient

Copolymerzation of L,L-lactide with epsilon-caprolactone by using novel zinc L-proline organometallic catalyst - Pandey, Asutosh K. (E-Polymers, 2010)
Copolyesters based on L, L-lactide (LA) and e-caprolactone (CL) with different LA: epsilon-CL ratios were synthesized by ring opening polymerization using zinc (L-proline) as a catalyst. Ring opening polymerization results in random P(L, L-lactide-epsilon-caprolactone) copolymers of molecular weights between 9,800 to 30,000 and block copolymer up to 51,800 Da. H-1 NMR spectroscopy analysis was used for calculation of monomer incorporation in the copolymer. FT-IR spectra were used to differentiate between random and block copolymer using carbonyl region splitting. C-13 quantitative NMR spectroscopy analysis coupled with information from TGA and DSC allowed determination of the polymer structure. Copolymers (CP-1, CP-2 and CP-3) prepared by ROP are random copolymer (h > 1), while CP-4 prepared by ROP (sequential addition of epsilon-caprolactone and L, L-lactide) has a multi block character (h < 1). The LA number-average sequence length (L-LA) decreased from 14 to 5 for LA-CL 80:20 to 50:50 copolymers prepared by ROP. The copolymer (CP-4) prepared by sequential addition showed the number-average sequence length (L-LA) to be 83.0.

Copper-catalyzed intramolecular N-arylation of quinazolinones: facile convergent approach to (-)-circumdatins H and J - Kshirsagar, Umesh A.; N. P. Argade (Organic Letters, 2010)
A copper-catalyzed intramolecular N-arylation of a quinazolinone nucleus that furnished the central benzodiazepine core unit has been demonstrated to accomplish an efficient convergent total synthesis of (-)-circumdatins H and J.

Coupling growth-factor engineering with nanotechnology for therapeutic angiogenesis - Roy, Rituparna Sinha; Soni, Shivani; Harfouche, Rania; Vasudevan, Pooja R.; Holmes, Oliver; de Jonge, Hugo; Rowe, Arthur; Paraskar, Abhimanyu; Hentschel, Dirk M.; Chirgadze, Dimitri; Blundell, Tom L.; Gherardi, Ermanno; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Therapeutic angiogenesis is an emerging paradigm for the management of ischemic pathologies. Proangiogenic Therapy is limited, however, by the current inability to deliver angiogenic factors in a sustained manner at the site of pathology. In this study, we investigated a unique nonglycosylated active fragment of hepatocyte growth factor/scatter factor, 1K1, which acts as a potent angiogenic agent in vitro and in a zebrafish embryo and a murine matrigel implant model. Furthermore, we demonstrate that nanoformulating 1K1 for sustained release temporally alters downstream signaling through the mitogen activated protein kinase pathway, and amplifies the angiogenic outcome. Merging protein engineering and nanotechnology offers exciting possibilities for the treatment of ischemic disease, and furthermore allows the selective targeting of downstream signaling pathways, which translates into discrete phenotypes.
Keywords: cardiovascular disease; HGF/SF; ischemic disease; nanoparticle; protein engineering

Covalently immobilized triphenylphosphine rhodium complex: synthesis, characterization, and application in catalytic olefin hydrogenation - Wang, Lei; Jia, Mingjun; Shylesh, Sankaranarayanapillai; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Singh, Anand Pal; Thiel, Werner R. (Chemcatchem, 2010)
A trimethoxysilane functionalized triphenylphosphine was coordinated to rhodium(I) and the resulting rhodium complex was covalently bound to a mesoporous SBA-15 support. The catalytic activity of this hybrid material was studied for the hydrogenation of 2-cyclohexen-1-one and compared with the corresponding homogeneous catalyst. According to the (31)P-MAS NMR data, the catalytically active species was stable against oxidation; no structural change could be detected after exposing it to air for more than two months. Transmission electron microscopy (TEM) measurements on the used catalyst confirmed that the rhodium species was also stable against reduction to the metal because the formation of rhodium nanoparticles during the catalysis could be excluded. The kinetic curves of the recycled system confirmed that this hybrid catalyst shows excellent activity, selectivity, stability, and reusability, and is truly heterogeneous in the hydrogenation reaction.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; mesoporous materials; Rhodium

Critical role of particle size and interfacial properties in the visible light induced splitting of water over the nanocrystallites of supported cadmium sulphide - Deshpande, Aparna; Gupta, Narendra M. (International Journal of Hydrogen Energy, 2010)
CdS crystallites of varying size (1 to 5.0 nm) were successfully deposited on the surfaces of polyester and activated charcoal. The size and the texture of these crystallites depended on CdS loading and also on the substrate morphology. These highly dispersed photocatalysts displayed a pyramidal trend in activity for visible light induced splitting of water molecules, similar to that reported for the heterogeneous catalytic reactions over supported noble metals. Thus, the CdS particles of similar to 2.5 nm size gave rise to maximum rate of H(2) evolution as compared to the particles of either smaller or of larger size. The particles of <1.5 nm diameter were of poor crystallinity and displayed a significant Q-size effect on the absorption edge. Our study provides direct evidence for the structure sensitivity of photocatalytic dissociation of water over supported semiconductor nanocrystallites, where the particle size and the interfacial microstructural defects played a vital role. (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: CdS nanocrystallites; Interfacial defects; Photocatalysis; Structural sensitivity; water splitting

Crystal structure, NMR and theoretical investigations on 2-(o-hydroxy-anilino)-1,4-napthoquinone - Feizi, Nourollah; Pinjari, Rahul V.; Gejji, Shridhar P.; Sayyed, Fareed B.; Gonnade, Rajesh G.; Rane, Sandhya Y. (Journal of Molecular Structure, 2010)
Crystal structure, (1)H NMR and cyclic voltammetric investigations of 2-(o-hydroxy-anilino)-1,4-napthoquinone (HAN), resulting from coupling of aminophenol with 2-hydroxy-1,4-napthoquinone, have been carried out. X-ray structure reveals that the HAN ligand crystallizes in orthorhombic space group Pca2(1) with Z = 4. forming a chain via inter-molecular O2 center dot center dot center dot H1A-O1 and C15-H15 center dot center dot center dot O3 interactions. Both (1)H NMR and cyclic voltammetry experiments suggest the titled ligand is associated and exists as dinner in d(6)-DMSO while the monomer has been predicted in CDCl(3) solution. Density functional calculations can be utilized to gauge the strength of hydrogen-bonded interactions from the (1)H chemical shifts in the NMR spectra. Self-consistent reaction field (SCRF) calculations further support the inferences drawn from cyclic voltammetry experiments. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: (1)H NMR; cyclic voltammetry; Density functional; hydrogen bonding; Napthoquinone

Crystallization and preliminary X-ray diffraction analysis of various enzyme-substrate complexes of isopropylmalate dehydrogenase from thermus thermophilus - Merli, Angelo; Manikandan, Karuppasamy; Graczer, Eva; Schuldt, Linda; Singh, Rajesh Kumar; Zavodszky, Peter; Vas, Maria; Weiss, Manfred S. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2010)
The Thermus thermophilus 3-isopropylmalate dehydrogenase (Tt-IPMDH) enzyme catalyses the penultimate step of the leucine-biosynthesis pathway. It converts (2R,3S)-3-isopropylmalate to (2S)-2-isopropyl-3-oxosuccinate in the presence of divalent Mg(2+) or Mn(2+) and with the help of NAD(+). In order to elucidate the detailed structural and functional mode of the enzymatic reaction, crystals of Tt-IPMDH were grown in the presence of various combinations of substrate and/or cofactors. Here, the crystallization, data collection and preliminary crystallographic analyses of six such complexes are reported.

Crystal-to-crystal thermal phase transition amongst dimorphs of hexa-O-p-toluoyl-myo-inositol conserving two-dimensional isostructurality - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystengcomm, 2010)
Triclinic (P-1) crystals of hexa-O-p-toluoyl-myo-inositol obtained from common organic solvents exhibited single crystal-to-single crystal irreversible phase transition centered at similar to 250 degrees C. The transformation of these crystals to monoclinic P2(1)/n form was revealed using DSC and X-ray diffraction studies. The latter crystals could also be produced by melt crystallization. Crystal structure analysis revealed that the molecules in both forms are linked via bifurcated C-H center dot center dot center dot O interactions to make almost identical centrosymmetric dimers. The neighbouring dimers are bridged via C-H center dot center dot center dot O and aromatic pi center dot center dot center dot pi stacking interactions to create two-dimensional isostructural assemblies. The difference in the two crystal forms arises from linking of the centrosymmetric dimers along the third dimension; the dimers are centrosymmetrically bridged in the triclinic form, while they have n-glide relationship in the monoclinic form. Comparison of the dimorph structures further revealed that they are actually an excellent case of morphotropism since dimorphs are related by non crystallographic rotation and translation of their basic motif (centrosymmetric dimers) that transforms the triclinic (P-1) phase to a monoclinic (P2(1)/n) phase.

Cu:Al Nano catalyst for selective hydrogenolysis of glycerol to 1,2-propanediol - Mane, Rasika B.; Hengne, Amol M.; Ghalwadkar, Ajay A.; Vijayanand, Subramanian; Mohite, Pravin H.; Potdar, Hari S.; Rode, Chandrashekhar V. (Catalysis Letters, 2010)
Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H(2) pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu(+) species in the activated Cu: Al nano catalyst. Although Cu(+) is catalytically inactive in glycerol hydrogenolysis reaction, the presence of Cu(+) helps to stabilize the particle size in a narrow range of 7-11 nm by inhibiting the sintering of copper particles under reaction conditions.
Keywords: 1; 2-Propanediol; Cu:Al nano catalyst; Glycerol; Selective hydrogenolysis

[Cu]-Catalyzed S(N)AR reactions: direct amination of electron deficient aryl halides with sodium azide and the synthesis of arylthioethers under Cu(II)-ascorbate redox system - Goriya, Yogesh; Ramana, C. V. (Tetrahedron, 2010)
A one pot [Cu]-promoted SNAr reaction of electron-deficient halobenzenes with sodium azide and the reduction of the intermediate aryl azides under the same Cu(II) ascorbate redox conditions leading to anilines has been documented. Control experiments revealed that both ascorbate and proline play important role in the reaction path way. Further, the use of this catalytic Cu(II) ascorbate redox system has been explored for the synthesis of arylthioethers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Anilines; Azide reduction; Cu(II)-ascorbate redox system; SNAr reaction; Thioether

Cytotoxic activity of 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda against human cancer cells - Shriram, Varsha; Kumar, Vinay; Kishor, P. B. Kavi; Suryawanshi, Sharad B.; Upadhyay, Ankur K.; Bhat, Manoj K. (Journal of Ethnopharmacology, 2010)
Ethnopharmacological relevance: Eulophia nuda L. (Orchidaceae) is a medicinally important terrestrial orchid used for the treatment of tumours and various health problems by the local healers throughout the Western Ghats region in Maharashtra (India). Aim of the study: To isolate the active molecule from Eulophia nuda and to study its cytotoxic potential against human cancer cells. Materials and methods: The crude methanolic extract of Eulophia nuda tubers was fractionated by stepwise gradient of the solvents chloroform-methanol to isolate the pure compound. Isolated pure compound was assessed for its cytotoxic potential against human breast cancer cell lines, MCF-7 and MDA-MB-231 using MTT assay. Structure elucidation of the isolated active compound was carried out by extensive spectroscopic analysis including (1)H NMR, (13)C NMR, NOESY, COSY, LC-MS and IR. Results: The isolated active molecule was identified as phenanthrene derivative 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol. This compound showed good antiproliferative activity against human breast cancer cell lines MCF-7 (91%) and MDA-MB-231 (85%) at 1000 mu g/ml concentration. Conclusion: 9,10-Dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda tubers showed good growth suppressive effect against human cancer cell lines MCF-7 and MDA-MB-231 making it a potential biomolecule against human cancer. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Cytotoxic activity; Eulophia nuda; Phenanthrene derivatives

Cytotoxic and genotoxic assessment of glycolipid-reduced and -capped gold and silver nanoparticles - Singh, Sanjay; D'Britto, Virginia; Prabhune, Asmita; Ramana, C. V.; Dhawan, Alok; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
A systematic cytotoxic and genotoxic evaluation of glycolipid-conjugated silver and gold nanoparticles is carried out. These glycolipid nanoparticle conjugates are obtained by exploiting the reductive capability of a class of glycolipids called sophorolipids that play the role of capping agent as well. Further, when tested for their cytotoxicity and genotoxicity on HepG2 cells, these nanoparticles are found to be cytocompatible up to 100 mu M metal concentrations. Of the two metallic systems investigated, gold nanoparticles are found to be more cytocompatible than the same concentrations of silver nanoparticles. Similarly, it is also demonstrated that at 100 mu M, silver nanoparticles cause more DNA damage compared to gold nanoparticles of similar concentrations.

Carbon nanotube-modified sodium dodecyl sulfate-polyacrylamide gel electrophoresis for molecular weight determination of proteins - Parthasarathy, Meera; Debgupta, Joyashish; Kakade, Bhalchandra A.; Ansary, Abu Ayoobul; Khan, Mohammad Islam; Pillai, Vijayamohanan K. (Analytical Biochemistry, 2011)
The effect of incorporating carbon nanotubes (CNTs) in the gel matrix on the electrophoretic mobility of proteins based on their molecular weight differences was investigated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). More specifically, a reduction in standard deviation in the molecular weight calibration plots by 55% in the case of multiwalled carbon nanotubes (MWCNTs) and by 34% in the case of single-walled carbon nanotubes (SWCNTs) compared with that of pristine polyacrylamide gels was achieved after incorporating an insignificant amount of functionalized CNTs into the gel matrix. A mechanism based on a more uniform pore size distribution in CNT modified polyacrylamide gel matrix is proposed. Furthermore, the impact of SWCNTs and MWCNTs on the mobility of proteins in different molecular weight regimes at a given acrylamide concentration offers a tunable gel matrix in terms of the selection of molecular weight ranges of proteins. The robustness and excellent reproducibility of the CNT-PAGE protocol are expected to have a significant impact on the molecular weight determination of newly isolated proteins. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Carbon nanotubes; Gel electrophoresis; Molecular weight determination; Polyacrylamide; Protein separation

Catalytic dehydroaromatization of n-alkanes by pincer-ligated iridium complexes - Ahuja, Ritu; Punji, Benudhar; Findlater, Michael; Supplee, Carolyn; Schinski, William; Brookhart, Maurice; Goldman, Alan S. (Nature Chemistry, 2011)
Aromatic hydrocarbons are among the most important building blocks in the chemical industry. Benzene, toluene and xylenes are obtained from the high temperature thermolysis of alkanes. Higher alkylaromatics are generally derived from arene–olefin coupling, which gives branched products—that is, secondary alkyl arenes—with olefins higher than ethylene. The dehydrogenation of acyclic alkanes to give alkylaromatics can be achieved using heterogeneous catalysts at high temperatures, but with low yields and low selectivity. We present here the first catalytic conversion of n-alkanes to alkylaromatics using homogeneous or molecular catalysts—specifically ‘pincer’-ligated iridium complexes—and olefinic hydrogen acceptors. For example, the reaction of n-octane affords up to 86% yield of aromatic product, primarily o-xylene and secondarily ethylbenzene. In the case of n-decane and n-dodecane, the resulting alkylarenes are exclusively unbranched (that is, n-alkyl-substituted), with selectivity for the corresponding o-(n-alkyl)toluene.

Ceria-zirconia mixed oxides as thermal resistant catalysts for the decomposition of nitrous oxide at high temperature - Esteves, P.; Wu, Y.; Dujardin, Christophe; Dongare, Mohan K.; Granger, P. (Catalysis Today, 2011)
This present study deals with the development of thermally stable catalysts for the decomposition of nitrous oxide. There is actually a growing interest to minimise the emissions of nitrous oxide (N(2)O) as side-product from nitric acid plants due to a global warming potential of approximately 300 times higher than that of CO(2). Different strategies have already been implemented at industrial scale but they are still suffering from significant drawbacks essentially associated to a poor selectivity and sometimes a short lifetime in particular when the catalytic process is inserted downstream the ammonia burner. In those critical conditions, with high residual temperature of similar to 900 degrees C, significant surface and bulk reconstructions take place and then lead to drastic losses of specific surface area and related catalytic performances in the decomposition of N(2)O to N(2). Previous investigations performed in our laboratory revealed the potentiality of zirconia particularly after yttria incorporation [Appl. Catal. B 62 (2005) 236]. Novel developments of more stable ceria-zirconia based catalysts are reported in this study. Further stabilisation and enhancement in activity have been discussed on the basis of oxygen mobility related to structural properties. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceria-zirconia based catalysts; Greenhouse gas; N(2)O catalytic decomposition; Nitric acid plant; Nitrous oxide

CFD simulation of stirred tanks: comparison of turbulence models (Part II: axial flow impellers, multiple impellers and multiphase dispersions) - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
In the first part of the review, published literature regarding the CFD modelling of single-phase turbulent flow in stirred tank reactors with radial flow impellers was critically analysed. A brief overview of different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model and large eddy simulation) as well as impeller baffle interaction models has been presented in the previous part. This part is concerned with the review of literature regarding CFD simulation of axial flow impellers. Comprehensive simulations have been carried out using various turbulence models and the model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. The strengths and weaknesses of various turbulence models for axial flow impellers is presented. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-e model as well as Reynolds stress model. Literature efforts on multiple impeller systems and multiphase systems have been discussed in a separate section. Based on these results, suggestions have been made for the future work in this area.
Keywords: axial flow impellers; CFD; impeller models; stirred vessel; turbulence models

CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
A critical review of the published literature regarding the computational fluid dynamics (CFD) modelling of single-phase turbulent flow in stirred tank reactors is presented. In this part of review, CFD simulations of radial flow impellers (mainly disc turbine (DT)) in a fully baffled vessel operating in a turbulent regime have been presented. Simulated results obtained with different impeller modelling approaches (impeller boundary condition, multiple reference frame, computational snap shot and the sliding mesh approaches) and different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model (RSM) and large eddy simulation) have been compared with the in-house laser Doppler anemometry (LDA) experimental data. In addition, recently proposed modifications to the standard k-epsilon models were also evaluated. The model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. A discussion is presented to highlight strengths and weaknesses of currently used CFD models. A preliminary analysis of sensitivity of modelling assumptions in the k-epsilon models and RSM has been carried out using LES database. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-epsilon model as well as RSM. The volume integral of predicted energy dissipation rate is compared with the energy input rate. Based on these results, suggestions have been made for the future work in this area.
Keywords: CFD; impeller models; k-epsilon models; LES; radial flow impellers; RSM; stirred vessel

Characterisation of copolymer, poly (hydroxybutyrate-co-hydroxyvalerate) (PHB-co-PHV) produced by halomonas campisalis (MCM B-1027), its biodegradability and potential application - Kulkarni, Snehal O.; Kanekar, Pradnya P.; Jog, Jyoti Prakash; Patil, Prashant A.; Nilegaonkar, Smita S.; Sarnaik, Seema S.; Kshirsagar, Pranav R. (Bioresource Technology, 2011)
Characterisation of polyhydroxyalkanoate (PHA) film produced by haloalkalitolerant Halomonas campisalis (MCM B-1027) in 14 L SS fermenter revealed it to have composition of monomer units, HB:HV as 96:4 as analysed by (1)H NMR indicating the PHA as a co-polymer of PHB-co-PHV, molecular weight by gel permeation chromatography as 2.08 x 10(6), melting temperature 166.51 degrees C, tensile strength 18.8 MPa; two relaxations namely beta transition corresponding to the glass rubber transition and alpha transition corresponding to crystalline relaxation by Dynamic Mechanical Thermal analysis and only one relaxation corresponding to MWS interfacial polarisation with activation energy of 129 kJ/mol by broadband dielectric spectroscopy. Optical microscopic studies showed typical Maltese-cross pattern of spherulites. The PHA film was found to be biodegradable by standard ASTM method as well as by soil burial method. The leak proof polymer bags prepared from the film could be used as a packaging material. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymer; Copolymer PHB-co-PHV; Dielectric relaxation spectroscopy; Dynamic mechanical analysis; Halomonas

Characterization of surface acid sites in tin-silicalite-1 (Sn-MFI) molecular sieve by X-ray photoelectron spectroscopy - Niphadkar, P. S.; Patil, K. R.; Joshi, P. N. (Microporous and Mesoporous Materials, 2011)
The nature, strength and density of surface acid sites in Sn-MFI molecular sieves with different Sn-content were characterized by N 1s high resolution photoelectron peak of chemisorbed pyridine in combination with pyridine-IR and TPAD. Two peaks emerged at 399.5 +/- 0.2 and 401.5 +/- 0.2 eV by deconvoluting composite N is peak were assigned to chemisorbed pyridine on weak and relatively strong Lewis acid sites, respectively. The relative percentage of strong Lewis acid sites was found to increase with the decrease of framework Sn content. A close agreement was observed between the ratios of weak Lewis acid sites to strong Lewis acid sites obtained from XPS and TPAD. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Lewis acidity; Pyridine chemisorption; SiO2/SnO2 molar ratio; Sn-MFI; XPS

Chemoenzymatic total synthesis of potent HIV RNase H inhibitor (-)-1,3,4,5-tetragalloylapiitol - Batwal, Ramesh U.; Patel, Ramesh M.; N. P. Argade (Tetrahedron-Asymmetry, 2011)
Starting from racemic dimethyl 2-acetoxy-3-methylenesuccinate, the chemoenzymatic facile total synthesis of (-)-1,3,4,5-tetragalloylapiitol has been demonstrated via an efficient lipase catalyzed resolution followed by a DIBAL reduction-double gallyolation, osmium tetroxide dihydroxylation-double gallyolation, and reductive global O-benzyl deprotection pathway. (C) 2010 Elsevier Ltd. All rights reserved.

Chlorate ion mediated rutile to anatase reverse phase transformation in the TiO2 nanosystem - Bhosale, Reshma; Hyam, Rajeshkumar S.; Dhanya, P.; Ogale, Satishchandra B. (Dalton Transactions, 2011)
Rutile TiO2 nanoneedles (8 nm x 100 nm) synthesized at room temperature by anodization in perchloric acid (pH < 1) are shown to undergo an interesting reverse phase transformation to anatase nanoparticles (8 nm) at 300 degrees C only if the chlorate ions are maintained in the ambient medium. When chlorate ions are removed by multiple washing, the rutile phase and the needle morphology are maintained. The mechanism of formation of the ion-stabilized solid and its thermal evolution is discussed.

Chromatographic separations of zinc, iron and copper metal ions through cellulose poroussolid fiber supported solid membrane in mixedsolvent systems - Gaikwad, Abaji G. (Chemical Engineering Communications, 2011)
An interesting aspect of chromatographic separation of zinc, iron, and copper metal ions through a cellulose porous solid fiber supported solid membrane from source solution to receiving phase has been explored in mixed solvent systems. The cellulose porous solid fiber supported solid membrane was prepared by chemically immobilizing tartaric acid. The experimental variables explored were concentration of copper, zinc, and iron metal ions, hydrochloric acid, composition of mixed solvents, and stirring speed. The efficiency of a cellulose porous solid fiber supported solid membrane system has been evaluated for the separation of metal ions. The pre-concentration of metal ions was carried out from the dilute solutions. The two-channel chromatographic cellulose porous solid fiber supported solid membrane system has been investigated for the transport of metal ions from the source solution to receiving phase. The capillary action phenomenon in the cellulose micro fibers plays a significant and active role in the transport of ions through the cellulose porous solid fiber supported solid membrane in mixed solvents.
Keywords: and iron ions: Single- and double-channel membrane system; Cellulose porous solid fiber supported solid membrane; Copper; zinc

Classification of Indian power coals using K-means clustering and self organizing map neural network - Pandit, Yogesh P.; Badhe, Yogesh P.; Sharma, B. K.; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Fuel, 2011)
The present study reports results of the classification of Indian coals used in thermal power stations across India. For classifying these power coals a classical unsupervised clustering technique, namely ``K-Means Clustering'' and an artificial intelligence (AI) based nonlinear clustering formalism known as ``Self-Organizing Map (SOM)'' have been used for the first time. To conduct the said classification, five coal descriptor variables namely moisture, ash, volatile matter, carbon and gross calorific value (GCV) have been used. The classification results thereof indicate that Indian power coals from different geographical origins can be classified optimally into seven classes. It has also been found that the K-means and SOM based classification results exhibit similarity in close to 75% coal samples. Further, K-means and SOM based seven coal categories have been compared with as many grades of a commonly employed Useful Heat Value (UHV) based Indian non-coking coal grading system. Here, it was observed that a number of UHV-based grades exhibit similarity with the categories identified by the K-means and SOM methods. The classification of Indian power coals as provided here can be gainfully used in selecting application-specific coals as also in their grading and pricing. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Coal classification; Indian power coals; K-means clustering; Self-Organizing Map

Click chemistry: 1,2,3-triazoles as pharmacophores - Agalave, Sandip G.; Maujan, Suleman R.; Pore, Vandana S. (Chemistry-an Asian Journal, 2011)
The copper(I)-catalyzed 1,2,3-triazole-forming reaction between azides and terminal alkynes has become the gold standard of `click chemistry' due to its reliability, specificity, and biocompatibility. Applications of click chemistry are increasingly found in all aspects of drug discovery; they range from lead finding through combinatorial chemistry and target-templated in vitro chemistry, to proteomics and DNA research by using bioconjugation reactions. The triazole products are more than just passive linkers; they readily associate with biological targets, through hydrogen-bonding and dipole interactions. The present review will focus mainly on the recent literature for applications of this reaction in the field of medicinal chemistry, in particular on use of the 1,2,3-triazole moiety as pharmacophore.
Keywords: Click chemistry; Copper; Cycloaddition; pharmacophores; triazoles

Combined strategy for the dispersion/dissolution of single walled carbon nanotubes and cellulose in water - Adsul, Mukund G.; Rey, Diego A.; Gokhale, Digambar V. (Journal of Materials Chemistry, 2011)
Co-dispersion of native cellulose and single walled carbon nanotubes in water is demonstrated. The pH of the water should be between 6 and 10 for better dispersion. Raman spectra confirm debundling of nanotubes in water and FTIR spectra reveal that the co-solubility is likely caused through disruption of intramolecular hydrogen bonds in the cellulose by hydroxyl groups present on nanotubes surface and the creation of intermolecular hydrogen bonds between cellulose and carbon nanotubes. This is a very simple method for co-dispersion/dissolution of nanotubes and cellulose in water without covalent modifications and expands the repertoire of nanotube modification strategies that are amenable to biological applications.

Combustion synthesis to incorporate nitrogen in ZnO and TiO2 and their applications in solar energy harvesting - Chinnakonda, Gopinath S. (241st National Meeting and Exposition of the American-Chemical-Society (ACS), 2011)

Comparative and chemical proteomic approaches reveal gatifloxacin deregulates enzymes involved in glucose metabolism - Suresh, Kesavan K.; Bhosale, Santosh D.; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J. (Journal of Toxicological Sciences, 2011)
Gatifloxacin has been associated with increased risks of hypoglycemic and hyperglycemic side effects. In order to understand the molecular mechanism of gatifloxacin induced deregulation of glucose metabolism, a Combination of comparative and chemical proteomic approaches were employed using yeast as a model system. Differential protein expression studies using two dimensional electrophoresis and mass spectrometry reveal that gatifloxacin deregulates the expression of key enzymes involved in glucose metabolism. Furthermore, affinity chromatography and LC-MSE analysis led to identification of enolase, as one of the key gatifloxacin binding proteins. Fluorescence spectrometric studies confirmed that the gatifloxacin indeed binds to enolase. Role of enolase in regulation of gatifloxacin induced dysglycemic effect is discussed.
Keywords: antibiotics; Differential protein expression; Fluoroquinolone; Glycolysis; Yeast

Comparative behavior of CdS and CdSe quantum dots in poly (3-hexylthiophene) based nanocomposites (vol 41, pg 198, 2006) - Sonar, Prashant; Sreenivasan, K. P.; Maddanimath, Trupti; Vijayamohanan, K. (Materials Research Bulletin, 2011)

Comparative genomics of the pathogenic ciliate Ichthyophthirius multifiliis, its free-living relatives and a host species provide insights into adoption of a parasitic lifestyle and prospects for disease control - Coyne, Robert S.; Hannick, Linda; Shanmugam, Dhanasekaran; Hostetler, Jessica B.; Brami, Daniel; Joardar, Vinita S.; Johnson, Justin; Radune, Diana; Singh, Irtisha; Badger, Jonathan H.; Kumar, Ujjwal; Saier, Milton; et al. (Genome Biology, 2011)
Background: Ichthyophthirius multifiliis, commonly known as Ich, is a highly pathogenic ciliate responsible for 'white spot', a disease causing significant economic losses to the global aquaculture industry. Options for disease control are extremely limited, and Ich's obligate parasitic lifestyle makes experimental studies challenging. Unlike most well-studied protozoan parasites, Ich belongs to a phylum composed primarily of free-living members. Indeed, it is closely related to the model organism Tetrahymena thermophila. Genomic studies represent a promising strategy to reduce the impact of this disease and to understand the evolutionary transition to parasitism. Results: We report the sequencing, assembly and annotation of the Ich macronuclear genome. Compared with its free-living relative T. thermophila, the Ich genome is reduced approximately two-fold in length and gene density and three-fold in gene content. We analyzed in detail several gene classes with diverse functions in behavior, cellular function and host immunogenicity, including protein kinases, membrane transporters, proteases, surface antigens and cytoskeletal components and regulators. We also mapped by orthology Ich's metabolic pathways in comparison with other ciliates and a potential host organism, the zebrafish Danio rerio. Conclusions: Knowledge of the complete protein-coding and metabolic potential of Ich opens avenues for rational testing of therapeutic drugs that target functions essential to this parasite but not to its fish hosts. Also, a catalog of surface protein-encoding genes will facilitate development of more effective vaccines. The potential to use T. thermophila as a surrogate model offers promise toward controlling 'white spot' disease and understanding the adaptation to a parasitic lifestyle.

Comparative production of cellulases by mutants of penicillium janthinellum NCIM 1171 and its application in hydrolysis of avicel and cellulose - Singhvi, M. S.; Adsul, Mukund G.; Gokhale, D. V. (Bioresource Technology, 2011)
Mutants of Penicillium janthinellum NCIM 1171 were evaluated for cellulase production using both submerged fermentation (SmF) and solid state fermentation (SSF). Mutant EU2D-21 gave highest yields of cellulases in both SmF and SSF. Hydrolysis of Avicel and cellulose were compared using SmF and SSF derived enzyme preparations obtained from EU2D-21. Surprisingly, the use of SSF derived preparation gave less hydrolysis compared to SmF derived enzymes. This may be due to inactivation of beta-glucosidase at 50 degrees C in SSF derived enzyme preparations. SmF derived enzyme preparations contained both thermostable and thermosensitive beta-glucosidases where as SSF derived enzyme preparations contained predominantly thermosensitive beta-glucosidase. This is the first report on less thermostability of SSF derived p-glucosidase which is the main reason for getting less hydrolysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: beta-Glucosidase thermostability; Mutant EU2D-21; Solid state fermentation; Submerged fermentation

Comparative study of porphyrin derivatives in monolayers at the air-water interface and in langmuir-blodgett films - Ghosh, Amrita; Mahato, Prasenjit; Choudhury, Sipra; Das, Amitava (Thin Solid Films, 2011)
The orientation and aggregation of various porphyrin derivatives at the air–water interface and in Langmuir–Blodgett films were investigated. Monolayer properties of these molecules, where long alkyl chain(s) were covalently bound through different functionality of varying hydrophilicity were studied by measuring surface pressure area isotherms. Such derivatives, where ether functionality (functionalities) was (were) used for linking long alkyl chain(s), did not form uniform monolayer; instead they were found to form multilayer clusters or aggregates on the water surface. On the other hand, porphyrin derivative functionalized at the four peripheral phenyl rings with eight hexadecyl ether chains formed stable spherical vesicles when deposited on mica. Tetra N-alkyl pyridinium porphyrins with long alkyl chain were found to form various phases on the water surface. Evidence of transition from horizontal orientation to vertical orientation of porphyrin rings of porphyrin molecules having C14 chains was observed. This type of transition was lost with the porphyrin molecule with a relatively smaller chain (C8).

Comparison of racemic epi-inosose and (-)-epi-inosose - Krishnaswamy, Shobhana; Patil, Madhuri T.; Shashidhar, Mysore S. (ACTA Crystallographica Section C-Crystal Structure Communications, 2011)
The conversion of myo-inositol to epi-inositol can be achieved by the hydride reduction of an intermediate epi-inosose derived from myo-inositol. (-)-epi-Inosose, (I), crystallized in the monoclinic space group P2(1), with two independent molecules in the asymmetric unit [Hosomi et al. (2000). Acta Cryst. C56, e584-e585]. On the other hand, (2RS,3SR,5SR,6SR)epi-inosose, C6H10O6, (II), crystallized in the orthorhombic space group Pca2(1). Interestingly, the conformation of the molecules in the two structures is nearly the same, the only difference being the orientation of the C-3 and C-4 hydroxy H atoms. As a result, the molecular organization achieved mainly through strong O-H center dot center dot center dot O hydrogen bonding in the racemic and homochiral lattices is similar. The compound also follows Wallach's rule, in that the racemic crystals are denser than the optically active form.

Competitive binding of Ba2+and Sr2+ to 18-crown-6 in a receptor with a 1-methoxyanthraquinone analogue as the other binding site - Banerjee, Tanmay; Suresh, Moorthy; Ghosh, Hirendra N.; Das, Amitava (Europian Journal of Inorganic Chemistry, 2011)
Owing to their immense biological significance, development of sensors for the selective detection of alkaline earth metal ions has attracted vast research interest. In this article we have reported the synthesis, characterisation and ion binding studies of a new RuII-polypyridyl-crown-anthraquinone complex (5). Studies confirm selective binding of BaII, SrII and CaII ions, with Kmath image > Kmath image >> Kmath image, over all other metal ions, to the crown ether moiety and not to the methoxy anthraquinone component, the latter being the second binding site available and known for its affinity towards alkaline earth metal ions from one of our previous reports.

Competitive wetting of acetonitrile and dichloromethane in comparison to that of water on functionalized carbon nanotube surfaces - Debgupta, Joyashish; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Differential wetting of pristine and ozonized carbon nanotubes has been studied using solvents like acetonitrile and dichloromethane in comparison to the well-known wetting behavior of water. Based on their unique structural and physical properties, functionalized CNT substrates have been used due to the fact that independent variation in molecular as well as electronic properties could be controlled by understanding the wetting of these liquids on carbon nanotubes (CNTs), both pristine as well as ozone treated. The sensitivity of the wetting behavior with respect to molecular interactions has been investigated using contact angle measurements while Raman and XPS studies unravel the differential wetting behavior. Charge-transfer between adsorbed molecules and CNTs has been identified to play a crucial role in determining the interfacial energies of these two liquids, especially in the case of acetonitrile. Ozone treatment has been observed to affect the surface properties of pristine CNTs along with a concomitant change in the wetting dynamics.

Composition-structure-property (Zn2+ and Ca2+ ion release) evaluation of Si-Na-Ca-Zn-Ce glasses: potential components for nerve guidance conduits - Zhang, X. F.; Kehoe, S.; Adhi, S. K.; Ajithkumar, Thalasseril G.; Moane, S.; O'Shea, H.; Boyd, D. (Materials Science & Engineering C-Materials for Biological Applications, 2011)
Bioactive glasses have demonstrated tailored therapeutic ion release, primarily with respect to the augmentation of hard tissues. However, controlled degradation and release of therapeutic ions from biomaterials may also play an important role in soft tissue regeneration such as repair of peripheral nerve discontinuities. In this study, three silica based glasses (0.5SiO(2)-0.2CaO-0.13ZnO-XNa2O-(0.17-X) CeO2) where, (0.04 < X < 0.14) were synthesised and characterised. The local environment of the Si-29 isotope was probed for each glass using Si-29 MAS-NMR, whilst the thermal characteristics of each glass were examined using DTA. Following these analyses, ion release profiles for Ca2+ and Zn2+ were evaluated; an equivalent specific surface area of 1 m(2) of each glass powder was incubated (37 degrees C) in 10 ml of citric acid buffer and TRIS-HCl buffer solution (pH 3.0 and pH 7.4 respectively) for incubation periods of up to 30 days. The Zn2+ concentration of each filtrate was analysed using flame Atomic Absorption Spectroscopy (Varian AA240FS Fast Sequential AAS) and the Ca2+ concentration of each filtrate was determined using Inductively Coupled Plasma-Mass Spectrometer (Varian 820 ICP-MS). Results obtained from the Si-29 MAS-NMR spectra indicated Q(2) structures pervading the network. An analytical model was proposed to analyse the ion release profiles for each glass, and indicated heterogeneous dissolution of glass networks. The ion release data demonstrates that ion release in the range (19.26-3130 ppm) for Ca2+ and in the range (5.97-4904 ppm) for Zn2+ occurred. Release of such elements, at appropriate levels, from peripheral nerve guidance conduits may be advantageous with respect to the repair of peripheral nerve discontinuities. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Dissolution; Modelling

Computer vision based chemical information extraction from digital images and streaming videos - Karthikeyan, Muthukumarasamy (242nd National Meeting of the American-Chemical-Society (ACS), 2011)

Concise enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol via Co-catalyzed HKR of anti-(2SR, 3RS)-3-methoxy-3-phenyl-1, 2-epoxypropane - Kiran, I. N. Chaithanya; Reddy, R. Santhosh; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2011)
A short, enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol, cytotoxic styryllactones, has been achieved in high optical purities (99% ee). The strategy employs Co-catalyzed HKR of racemic anti-(2SR, 3RS)-3-methoxy-3-phenyl-1,2-epoxypropane and Lewis acid-mediated diastereoselective allylation of aldehyde as chiral inducing key reactions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Allylation; diastereoselectivity; Hydrolytic kinetic resolution; Racemic anti-epoxide; Styryllactones

Concurrent display of both alpha- and beta-turns in a model peptide - Srinivas, Deekonda; Vijayadas, Kuruppanthara N.; Gonnade, Rajesh G.; Phalgune, Usha D.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This article describes a model peptide that concurrently displays both alpha- and beta-turns, as demonstrated by structural investigations using single crystal X-ray crystallography and solution-state NMR studies. The motif reported herein has the potential for the design of novel conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Conformational transitions in ariesaema curvatum lectin: characterization of an acid induced active molten globule - Sharma, Urvashi; Gaikwad, Sushama M.; Suresh, C. G.; Dhuna, Vikram; Singh, Jatinder; Kamboj, Sukhdev Singh (Journal of Fluorescence, 2011)
Biophysical characterization of a lectin from Ariesaema curvatum (ACL) was carried out using steady state as well as time resolved fluorescence and CD spectroscopy under various denaturing conditions. An intermediate with altered tryptophan microenvironment was detected in the phase diagram, which exibited pronounced secondary structure and hemagglutinating activity in presence of 0.25 M Gdn-HCl. An acid induced molten- globule like structure possessing activity and higher thermostability was detected. Transition to the molten globule state was reversible in nature. The lectin retained hemagglutinating activity even after incubation at 95 A degrees C. Both chemical and thermal unfolding of the lectin were found to consist of multistate processes. Fluorescence quenching of ACL was strong with acrylamide and KI. The single tryptophan was found to be surrounded by high density of the positively charged amino acid residues as shown by a ten fold higher K(sv) for KI compared to that for CsCl. The average lifetime of tryptophan fluorescence increased from 1.24 ns in the native state to 1.72 ns in the denatured state.
Keywords: Araceae; Fluorescence lifetime; Hemagglutinin; Molten globule; Secondary structure; Thermostability; Unfolding

Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Construction of the 5,10b-phenanthridine skeleton using [3+2]-cycloaddition of a non-stabilized azomethine ylide: total synthesis of (+/-)-maritidine and (+/-)-crinine alkaloids - Pandey, Ganesh; Gupta, Nishant R.; Gadre, Smita R. (European Journal of Organic Chemistry, 2011)
Vicinal quaternary and tertiary stereocenters of the 5,10b-phenanthridine skeleton 1 are constructed simultaneously in one step by the [3+2]-cycloaddition of non-stabilized azomethine ylide 9, generated by sequential double desilylation of 10 utilizing silver(I) fluoride as a one-electron oxidant. The regioas well as stereochemical origin of this cycloaddition reaction is explained through a favorable transition state 9''. The strategy is successfully applied for the total synthesis of the biologically active alkaloids (+/-)-maritidine (1a), (+/-)-crinine (1b), and their analogues (1d, 1e, and 1f).
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Natural products; Ylides

Control of competing hydrogenation of phenylhydroxylamine to aniline in a single-step hydrogenation of nitrobenzene to p-aminophenol - Nadgeri, Jayprakash M.; Biradar, Narayan S.; Patil, Priyanka B.; Jadkar, Sachin T.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2011)
Two steps involving catalytic hydrogenation of nitrobenzene to phenylhydroxylamine (PHA) in acid medium and its rearrangement to p-aminophenol (PAP) were studied separately in a batch reactor, using a well-characterized 3% Pt/C catalyst. The first step of hydrogenation of nitrobenzene to PHA could be carried out at 303 K and a H(2) pressure of 0.69 MPa with complete conversion of nitrobenzene, while the achieved selectivity to PHA was higher than 90% with some formation of aniline, even at lower temperature. The second step of PHA rearrangement to PAP could be achieved under a hydrogen atmosphere at elevated temperature of 353 K to give a maximum selectivity to PAP of 74%.

Controlling stoichiometry in low temperature synthesis of La0.7Sr0.3MnO3 nanoparticles - Azarifar, Ali; Yadav, P. A.; Chawla, A. K.; Jog, Jyoti Prakash; Patil, S. I.; Chandra, Ramesh; Ogale, S. B. (Advanced Science Letters, 2011)
Nanoparticles of complex oxides (<20 nm) are desirable for several applications in view of the diverse range of physical properties of such oxides. However the simultaneous presence of multiple cation precursors makes the corresponding chemical synthesis non-trivial with possible intermediate evolution of secondary phases. Such phases could react at high temperatures to form the desired stoichiometry, but this process is diffusion limited and can lead to larger particles. In this work we examine the role of three different reaction and growth controlling additives, namely dextran, citric acid and hexamine, on the synthesis of the well known colossal magneto-resistive (CMR) manganite La0.7Sr0.3MnO3. We demonstrate that phase evolutions differ significantly in the three cases, and the physical properties of the products also differ dramatically. Only dextran is shown to yield the desired phase with faceted nanoparticles at as low a temperature as 600 degrees C. A high saturation moment of similar to 47 emu/gm is realized at 10 K with a good square hysteresis loop. In 650 degrees C annealed sample, room temperature magnetization of similar to 15 emu/gm was obtained, which brings the nanoparticles in the applicability domain.
Keywords: Citric acid; Complex Oxide; Dextran; Hexamine; hydrothermal

Convenient and efficient protocol for the synthesis of acylals catalyzed by bronsted acidic ionic liquids under ultrasonic irradiation - Borikar, Sanjay P.; Daniel, Thomas (Ultrasonics Sonochemistry, 2011)
The synthesis of acylals (1,1-diacetates) via the reactions of aldehydes with acetic anhydride was carried Out in 85-97% yields at room temperature under ultrasound irradiation catalyzed by the Bronsted acidic ionic liquid [bmpy]HSO(4). This method provides several advantages, such as solvent-free conditions, operational simplicity, higher yields, and reduced environmental consequences. The ionic liquid was recovered and reused. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 1-Butyl-3-methylpyridinium hydrogen sulfate; 1-Diacetates; Acylals; Ionic liquid; Solvent-free; Ultrasonic irradiation

Convenient formal synthesis of (2S,3S)-3-hydroxy pipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Dumare, Nilesh B.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2011)
A convenient synthesis of (2S,3S)-3-hydroxy pipecolic acid starting from inexpensive and easily available L-(+)-tartaric acid has been described. (C) 2011 Elsevier Ltd. All rights reserved.

Correction to what drives the redox properties of model green fluorescence protein chromophores? - Solntsev, Kyril M.; Ghosh, Debashree; Amador, Adrian; Josowicz, Mira; Krylov, Anna I. (Journal of Physical Chemistry Letters, 2011)
We report the first experimental determination of the oxidation potentials E-ox(0). (relative to the standard hydrogen electrode, SHE) of model green fluorescent protein (GFP) chromophores. Para-, meta, and ortho-hydroxy (4-hydroxybenzylidene-2,3-dimethylimidazolinone, HBDI) and methoxy (MeOBDI) derivatives were studied. E-ox(0) of the three isomers in acetonitrile are -1.31, -1.52, and -1.39 V, respectively. Electronic structure calculations reproduce the observed differences between the isomers and reveal that E-ox(0) follows the ionization energies (IEs), that is, p-MeOBDI has the lowest IE (6.96 eV in the gas phase) due to resonance stabilization of its cation, whereas the resonance is detuned in m-MeOBDL resulting in more-negative E-ox(0). The observed meta and ortho effects in E-ox(0) are similar to the trends in pK(a). The effect of increased solvent polarity on absolute.E-ox(0) (and especially on para-meta-ortho differences) was found to be small. The redox properties of GFP chromophores are driven by their structure and can be correlated with IEs, which can be exploited in predicting the properties of other fluorescent protein chromophores.

Correlation of architecture with excimer emission in 100% pyrene-labeled self-assembled polymers - Kaushlendra, K.; Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2011)
Pyrene was incorporated as pendant unit to side-chain urethane methacrylate polymers having a short ethyleneoxy or a long polyethyleneoxy spacer segment. The short-spacer pyrene urethane methacrylate was also incorporated either as block or random copolymer (1:9) along with polystyrene. The excimer emission was observed to be different for different polymers with the random copolymer exhibiting the lowest efficiency. But, the total quantum yield was highest (phi = 0.58) for random copolymer due to the high emission coefficient of monomer compared to that of excimer. The polymer dynamics were compared by steady state emission and fluorescence decay in THF or THF/water (9:1) solvent mixture and films. The solid state decay profile showed decay without a rise time indicating presence of ground state aggregates. In THF/water (9:1), the decay profile at the excimer emission (500 nm) showed a rise time indicating dynamic excimers. The evolution of excimeric emission centred similar to 430 or similar to 480 nm as a function of temperature was also studied in THF/water (9:1). The I(E)/I(M) ratio for the lambda(343) nm excitation exhibited steady increase with temperature with the block copolymer PS-b-PIHP exhibiting the highest ratio and highest rate of increase; whereas, the random copolymer PS-r-PIHP had the lowest I(E)/I(M) ratios. (C) 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 49: 1678-1690, 2011
Keywords: I(E)/I(M) ratio; Morphology; pyrene; Self-assembly; structure-property relations; time-resolved and variable temperature fluorescence

Cosolvent-directed diels-alder reaction in ionic liquids - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry A, 2011)
The rate constants of a bimolecular Diels-Alder reaction in binary mixtures of ionic liquids prepared in molecular solvents were analyzed to investigate the effect of viscosity of the medium and solvent effect. In this connection, we have carried out the Diels-Alder reaction of anthracene 9-carbinol with N-ethyl maleimide in binary mixtures of pyridinium-based ionic liquids, 1-butyl-pyridinium tetrafluoroborate, 1-buty1-3-pyridinium tetrafluoroborate, and 1-butyl-4-methyl pyridinium tetrafluoroborate in water, methanol, and chloroform at 298.15 K. The rates of reaction decreased, caused by gradually increasing the volume fraction of ionic liquids in solvents for all three ionic liquids. The kinetic results demonstrate a successful application of the pairwise interaction model built upon the concept of enforced hydrophobic hydration. A temperature-dependent study of kinetics of the Diels-Alder reaction was carried out in the binary mixtures of ionic liquids in water and was explained by the entropy-enthalpy compensation effect based upon activation parameters. Kinetics of the Diels-Alder reaction in highly aqueous medium was noted to be entropically driven.

Crucial role of ocean-atmosphere coupling on the Indian monsoon anomalous response during dipole events - Krishnan, R.; Sundaram, Suchithra; Swapna, P.; Kumar, Vinay; Ayantika, D. C.; Mujumdar, M. (Climate Dynamics, 2011)
This paper examines an issue concerning the simulation of anomalously wet Indian summer monsoons like 1994 which co-occurred with strong positive Indian Ocean Dipole (IOD) conditions in the tropical Indian Ocean. Contrary to observations it has been noticed that standalone atmospheric general circulation models (AGCM) forced with observed SST boundary condition, consistently depicted a decrease of the summer monsoon rainfall during 1994 over the Indian region. Given the ocean-atmosphere coupling during IOD events, we have examined whether the failure of standalone AGCM simulations in capturing wet Indian monsoons like 1994 can be remedied by including a simple form of coupling that allows the monsoon circulation to dynamically interact with the IOD anomalies. With this view, we have performed a suite of simulations by coupling an AGCM to a slab-ocean model with spatially varying mixed-layer-depth (MLD) specified from observations for the 1994 IOD; as well as four other cases (1983, 1997, 2006, 2007). The specification of spatially varying MLD from observations allows us to constrain the model to observed IOD conditions. It is seen that the inclusion of coupling significantly improves the large-scale circulation response by strengthening the monsoon cross-equatorial flow; leading to precipitation enhancement over the subcontinent and rainfall decrease over south-eastern tropical Indian Ocean-in a manner broadly consistent with observations. A plausible physical mechanism is suggested to explain the monsoonal response in the coupled frame-work. These results warrant the need for improved monsoon simulations with fully coupled models to be able to better capture the observed monsoon interannual variability.
Keywords: Anomalous wet Indian monsoons; Indian ocean dipole; Numerical simulation; Ocean-atmosphere coupling

Cyclodiphosph(III)azane chemistry – ylides from the reaction of [(RNH)P-N(t-Bu)]2 [R = t-Bu, i-Pr] with dimethyl maleate and chiral ansa-type derivatives from reaction of [ClP-N(t-Bu)]2 with a substituted BINOL - Swamy, K.C. Kumara; Gangadhararao, G.; Srinivas, Venu; Kumar, N. N. Bhuvan; Balaraman, Ekambaram; Chakravarty, Manab (Inorganica Chimica Acta, 2011)
Use of a simple inorganic ring system with the cyclodiphosph(III)azane skeleton [e.g. [(RNH)P-N(t-Bu)]2 [R = t-Bu (7), i-Pr (8)] to probe some of the intermediates proposed in phosphine mediated organic reactions is highlighted. Thus the reaction of 7–8 with the allenylphosphine oxide Ph2P(O)C(Ph)double bond; length as m-dashCdouble bond; length as m-dashCH2 (9) affords the phosphinimines [(RNH)P(μ-N-t-Bu)2P(double bond; length as m-dashN-R)-C(double bond; length as m-dashCH2)CH(Ph)-P(O)Ph2] [R = t-Bu (10), i-Pr (11)], while a similar reaction of 7–8 with dimethyl maleate (or dimethyl fumarate) affords the ylides [(RNH)P(μ-N-t-Bu)2P(NH-R)double bond; length as m-dashC(CO2Me)-CH2(CO2Me) [R = t-Bu (18), i-Pr (19)]. The implication of such reactions on phosphine mediated organic transformations including Morita–Baylis–Hillman reaction is mentioned. In a rather rare type of situation, an unusually long phosphoryl (Pdouble bond; length as m-dashO) bond [1.538 (5) Å] as revealed the X-ray structure of {(R)-6,6′-(t-Bu)2-1,1′-(C10H5)2-2,2′-O2-}{P(O)(N-t-Bu)2-P(Se)} (27) is rationalized by means of crystallographic disorder in packing after comparing the data with that in the literature and {1,1′-(C10H6)2-2,2′-O2}{P(Se)(N-t-Bu)2-P(Se)} (29). X-ray structures of the new compounds 10–11, 18–19, 27 and 29 are discussed. Compound 10 crystallizes in the chiral space group Pca2(1) with (S)-chirality at the carbon center [–C(double bond; length as m-dashCH2)CH(Ph)-P] suggesting a case of spontaneous resolution through crystallization.

Cyclopropyl methyl bromide-mediated gem-diallylation: total synthesis of (+/-)-alpha-cuparenone - Shivakumar, I.; Salunke, Ganesh B.; Kumar, Suneel (Synthetic Communications, 2011)
[image omitted] The total synthesis of (+/-)–cuparenone, an aromatic sesquiterpene, has been described using the radical mediated gem-diallylation of substituted cyclopropyl methylbromide followed by ring-closing metathesis approach.
Keywords: Aromatic sesquiterpene; gem-diallylation; Ring-closing metathesis

Cytotoxicity of sophorolipid-gellan gum-gold nanoparticle conjugates and their doxorubicin loaded derivatives towards human glioma and human glioma stem cell lines - Dhar, Sheetal; Reddy, E. Maheswara; Prabhune, Asmita; Pokharkar, Varsha; Shiras, Anjali; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Biocompatible gold nanoparticles were synthesized by using a naturally occurring gum-Gellan Gum-as a capping and reducing agent. These were further conjugated with sophorolipids which again were accessed through a biochemical transformation of a fatty acid. The cellular uptake of sophorolipid-conjugated gellan gum reduced gold nanoparticles and their cytotoxicity on human glioma cell line LN-229 and human glioma stem cell line HNGC-2 were investigated. Quite surprisingly even the simple sophorolipid-conjugated gellan gum reduced/capped gold nanoparticles showed greater efficacy in killing the glioma cell lines and, gratifyingly, the glioma stem cell lines also. The cytotoxic effects became more prominent once the anti cancer drug doxorubicin hydrochloride was also conjugated to these gold nanoparticles.

Calcined, rare earth modified hydrotalcite as a solid, reusable catalyst for dimethyl carbonate synthesis - Unnikrishnan, P.; Srinivas, D. (Industrial & Engineering Chemistry Research, 2012)
An eco-friendly building block and fuel additive dimethyl-carbonate (DMC)-was synthesized through a benign route by transesterification of propylene carbonate (PC) with methanol. The catalytic activity of a series of calcined, rare earth elements (La3+, Ce3+, Pr3+, Sm3+, and Y3+; 2-10 mol %) incorporated Mg-Al hydrotalcites (HT) was evaluated for this reaction. Among several, the La (8 mol %) modified HT showed the highest activity (PC conversion = 65.4 mol % and DMC selectivity = 88 mol % at 150 degrees C and in 2 h). Basicity of the catalyst played an important role on the transesterification activity. The influence of reaction parameters and calcination temperature on the catalytic activity of HT was investigated. The La modified HT catalyst was heterogeneous and could be reused with little loss of activity.

Carbohydrate based total synthesis of xestodecalactone B and C: revision of the absolute configuration - Pal, Rita; Rahaman, Hasibur; Gurjar, Mukund K. (Current Organic Chemistry, 2012)
A convergent chiral pool approach for the total synthesis of xestodecalactones B and C was demonstrated in which intramolecular acylation reaction constituted the key step. Synthetic and spectroscopic studies reported herein, suggested that the previously assigned structures of xestodecalactone B and C be interchanged.
Keywords: Chiral pool; Hydroboration; Intramolecular acylation; Pinnick oxidation; Revision of absolute configuration; Xestodecalactone B and C

Carbohydrate-based synthesis of the C13-C22 fragment of amphidinolide X - Gurjar, Mukund K.; Yellol, Gorakh S.; Mohapatra, Debendra K. (European Journal of Organic Chemistry, 2012)
A facile carbohydrate-based route was developed for the synthesis of the tetrahydrofuran (C13C22) fragment of amphidinolide X. Starting from L-sorbose, the key reactions followed include the stereoselective synthesis of a quaternary center at C1, BartonMcCombie deoxygenation at C2, Mitsunobu inversion at C3, and chain elongation by a Wittig reaction at C5.
Keywords: Cytotoxicity; Macrolides; Mitsunobu inversion; Natural products; Wittig reactions

Carbohydrate-derived conformationally restricted bicyclic dipeptides as potential hetero foldamer building blocks - Ramesh, Veera V. E.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Tetrahedron-Asymmetry, 2012)
Starting from carbohydrate precursors, hetero foldamer building blocks featuring diverse amino acid side chains and stereochemistry have been accessed via a multi-step synthetic protocol. These conformationally restricted bicyclic dipeptide building blocks are characterized by a constrained beta-lactam ring fused with a pyrrolidine ring carrying a hydroxyethylamine isostere (HEA) on the backbone. These building blocks offer the possibility of developing foldamers with interesting structural architectures, conspicuously different from those classically observed. Furthermore, such hetero-building blocks have the potential to augment the conformational space available for foldamer design with diverse backbone conformations and structural architectures. (C) 2012 Elsevier Ltd. All rights reserved.

Carbon dioxide capture by metal organic frameworks - Saha, Subhadeep; Chandra, Suman; Garai, Bikash; Banerjee, Rahul (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
The design and synthesis of functionalized metal organic framework materials (MOFs) for reversible physisorption of CO2 is discussed. This strategy of CO2 adsorption in MOFs requires less energy for regeneration than materials relying on chemisorption. As a result the MOFs have received considerable attention as sorbent materials for strategic gases such as CO2 and H,. In this review, we have discussed different MOFs and hybrid materials containing MOFs which can adsorb CO2 at room temperature. In order to achieve high adsorption capacity, fast CO2 adsorption-desorption and low energy requirement for regeneration are necessary. Several avenues for increasing the CO2 adsorption capacity of such materials, for instance, introduction of open metal sites and the use of ligand molecules with specific functionalities (like -OH or -NH2) have been described. It has been observed that CO2 loading capacity of MOFs increases with functionalization. Herein, we have discussed how N-containing and fluorinated MOFs are designed to achieve higher CO2 loading than their non-functionalized counterparts. Nanocarbons (e.g. carbon nanotubes, carbon nanofibres, etc.) are porous materials and a blend of these porous materials with porous MOFs or porous carbon derived from MOFs may act as a better adsorbate than even the pure materials. Enhancement of CO2 loading by nanocarbon-MOF hybrid material is also discussed.
Keywords: Carbon dioxide adsorbents; Carbon dioxide capture; hybrid materials; Metal organic frameworks; Nanocarbons; Porous nanocarbons

Carbon dioxide capture using amine functionalized silica gel - Sakpal, Tushar; Kumar, Asheesh; Kamble, Sanjay; Kumar, Rajnish (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Commercially available silica gel is chemically modified for carbon dioxide capture. Calcinated silica gel of certain particle size functionalized with amine using two different methods, wet impregnation and grafting via silane chemistry has been employed as a porous media. The prepared material is characterized by Fourier transform infrared, scanning electron microscopy, energy dispersive analysis of X-rays, thermogravimetry and N-2 physisorption techniques. Gas uptake measurements have been carried out to ascertain the CO2 capture capacity of the amine functionalized material. The experiments have been carried out at moderate pressure and temperature range to ascertain its potential for easy scale up.
Keywords: Amine functionalized silica gel; Carbon dioxide capture; grafting; Poly(ethyleneimine); Silane chemistry; Wet impregnation

Carbon dioxide reforming of methane over ruthenium substituted strontium titanate perovskite catalysts - Gurav, Hanmant R.; Bobade, Richa; Das, Vineetha Lakshmi; Chilukuri, Satyanarayana V. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Strontium titanate (SrTiO3) doped with varying amounts of ruthenium (7.9, 15.6 and 31 wt%) have been prepared by the citrate gel synthesis method. Structural and textural characterizations reveal that at lower concentrations, a major part of Ru is incorporated in the lattice of SiTiO3. The content of surface Ru (outside lattice) increases with increasing amounts of the doped Ru. The surface Ru reduced at lower temperatures compared to Ru incorporated into the lattice. The reduction of the lattice substituted Ru occurs only at temperatures above the collapse of the perovskite structure. The catalyst sample with 7.9 wt% of Ru shows good conversions in the dry reforming of methane with CO2. The conversion of CO2 is in excess compared to methane under the studied reaction conditions. As a result, H-2/CO ratio of the product gases which should have been equivalent to unity is lower than the stoichiometric value. This ratio is particularly low when lower reaction temperatures (873-973 K) were used. Similar was the case when high space velocities were used. Low methane conversion and reverse water gas shift reaction are the causes for the low H-2/CO ratios.
Keywords: Carbon dioxide reforming; Catalysts; Citrate gel method; Doped catalysts; Dry reforming; Methane reforming; Perovskites; Reverse water gas shift; Ruthenium doped catalysts; Strontium titanate; Syngas

Carbon nanoscrolls by pyrolysis of a polymer - Yadav, Prasad; Warule, Sambhaji; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2012)
3D network of carbon nanoscrolls was synthesized starting from pyrolysis of poly(acrylic acid-co-maleic acid) sodium salt. It is a catalyst-free process where pyrolysis of polymer leads to formation of carbon form and sodium carbonate. Upon water soaking of pyrolysis product, the carbon form undergoes self-assembly to form carbon nanoscrolls. The interlayer distance between the walls of carbon nanoscroll was found to be 0.34 nm and the carbon nanoscrolls exhibited a surface area of 188 m(2)/g as measured by the BET method. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon nanoscrolls; Polymer; Pyrolysis; supercapacitor

Ce-Ni mixed oxide as efficient catalyst for H-2 production and nanofibrous carbon material from ethanol in the presence of water - Fang, Wenhao; Pirez, Cyril; Capron, Mickael; Paul, Sebastien; Raja, Thirumalaiswamy; Dhepe, Paresh Laxmikant; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (RSC Advances, 2012)
Hydrogen production from ethanol steam reforming (H2O/C2H5OH = 3) was studied over Ce-Ni based catalysts issued from different preparation methods (co-precipitation (CP), impregnation (IMP) and incipient wetness impregnation (IWI)). Catalysts prepared by the CP method exhibit higher activity and much better stability compared to the other two types of catalysts. The Ni1CeOY-CP catalyst is able to completely convert ethanol at 450 degrees C to H-2, CO2 and CH4 (almost no CO is observed), with a H-2 yield of 3 moles of hydrogen produced per mole of ethanol converted. A very high H-2 yield of 4.6 mol mol(EtOH)(-1) is achieved over the Ni1CeOY-CP mixed oxide at 650 degrees C. Correlations between the preparation method, catalytic activity and stability, and type of carbon deposition are discussed. The CP method forms very active small sized NiO (15 nm) and CeO2 (4 nm) nanoparticles, leading to the formation of a lower amount of carbon deposition in the form of nanofibrous carbon materials, the size of which depends on the Ni related nanoparticles. For CP catalysts, the graphitic filaments obtained correspond to carbon nanofibers (CNFs) and carbon nanotubes (CNTs) with a much smaller and homogenous size compared to the filamentous carbon formed over the catalysts issued from the other preparation methods, in relation to the active particles size. The catalytic stability is attributed to the type of carbon formed.

Challenges and opportunities in biofuels production - Srinivas, Darbha; Satyarthi, Jitendra Kumar (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Biofuels are attractive alternative to petroleum diesel. They are renewable, non-toxic, biodegradable, carbon neutral and lead to reduced tailpipe emissions. This article presents the current state-of-art processes of their production and discusses the opportunities and future challenges in this area of research.
Keywords: Biodiesel; biofuels; Deoxygenation; Hydrotreatment; Renewable fuels; Solid catalysts; Transesterification (fatty acid glycerides); Vegetable oils/fats

Characterization of a new bacillus cereus ATUAVP1846 strain producing penicillin V acylase, and optimization of fermentation parameters - Sunder, Avinash Vellore; Kumar, Atul; Naik, Neha; Pundle, Archana V. (Annals of Microbiology, 2012)
Penicillin acylases are involved chiefly in the industrial production of semisynthetic penicillins, which remain the most widely used group of antibiotics. We have isolated a new bacterial strain ATUAVP1846 that produces penicillin V acylase (PVA). Phylogenetic analysis using 16S rRNA sequencing showed 99.37% homology with Bacillus cereus. Maximum PVA production was observed with B. cereus ATUAVP1846 at 30A degrees C, pH 7 after 24 h fermentation time under submerged conditions. Highest enzyme productivity was achieved using sucrose as carbon source, and tryptone and ammonium hydrogen phosphate as nitrogen sources. Minimal medium containing 0.4% glucose and 0.3% ammonium hydrogen phosphate was found to be optimal for maximum PVA production from B. cereus ATUAVP1846. The crude enzyme from B. cereus ATUAVP1846 was partially purified using ammonium sulfate fractionation and showed highest enzymatic activity in the hydrolysis of penicillin V at 40A degrees C and pH 6. The crude enzyme preparation also showed unique substrate specificity, preferring ampicillin and cephalexin over penicillin V.
Keywords: 16S rRNA; Bacillus cereus; isolation; Ntn hydrolase; Optimization; Penicillin acylase

Characterization of biocompatible NiCo2O4 nanoparticles for applications in hyperthermia and drug delivery - Kale, Sangeeta N.; Jadhav, Anil D.; Verma, Seema; Koppikar, Soumya J.; Kaul-Ghanekar, Ruchika; Dhole, Sanjay D.; Ogale, Satishchandra B. (Nanomedicine-Nanotechnology Biology and Medicine, 2012)
Monodispersed, superparamagnetic nickel cobaltite (NCO) nanoparticles were functionalized using mercaptopropionic acid (MPA). MPA conjugates with NCO forming a metal-carboxylate linkage, with the MPA-MPA interaction occurring via formation of disulfide bonds, leaving another carboxyl end free for additional conjugation. The cytotoxicity studies on NCO-MPA show cell viability of similar to 100% up to a dosage of 40 mu g/mL on SiHa, MCF7, and B16F10 cell lines, and on mouse primary fibroblasts. Time-dependent cell viability studies done for a duration of 72 hours showed the cell lines' viability up to 80% for dosages as high as 80 mu g/mL. Negligible leaching (<5 ppm) of ionic Co or Ni was noted into the delivery medium. Upon subjecting the NCO-MPA dispersion (0.1 mg/mL) to radiofrequency absorption, the nanoparticles were heated to 75 degrees C within 2 minutes, suggesting its promise as a magnetic hyperthermia agent. Furthermore, the amino acid lysine and the drug cephalexin were successfully adducted to the NCO system, suggesting its potential for drug delivery. From the Clinical Editor: NCO-MPA nanopartciles were found to be promising magnetic hyperthermia agents, suggesting potential future clinical applications. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Cytotoxicity; drug delivery; Magnetic hyperthermia; Magnetic nanoparticles

Characterization of smallest active monomeric lipase from novel rhizopus strain: application in transesterification - Kantak, Jayshree B.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2012)
An extracellular lipase-producing fungus was isolated from oil-rich soil. This fungus belongs to the genus Rhizopus and clades with Rhizopus oryzae. Lipase was purified to homogeneity from this novel fungal source using ammonium sulphate precipitation followed by Q-Sepharose chromatography. The extracellular lipase was purified 8.6-fold, and enzymatic properties were studied. The molecular mass of the purified enzyme was estimated to be 17 kD by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and 16.25 kD by matrix-assisted laser desorption ionization/time-of-flight analysis. The native molecular mass was estimated to be 17.5 kD by gel filtration, indicating the protein to be monomer. The optimum pH and temperature for the enzyme catalysis were 7.0 A degrees C and 40 A degrees C, respectively. Enzyme was stable in pH range 6.0-7.0 and retains 95-100% activity when incubated at 50 A degrees C for 1 h. The pI of the purified lipase was 4.2. Enzyme was stable in the organic solvents such as ethanol, hexane and methanol for 2 h. Purified enzyme was used for transesterification of oleic acid in the presence of ethanol for production of oleic acid ethyl ester with a conversion efficiency of 66% after 24 h at 30 A degrees C.
Keywords: Lipase; Low molecular weight; Purification; Rhizopus; transesterification

Charge transport in functionalized multi-wall carbon nanotube-Nafion composite - Sangeeth, C. S. Suchand; Kannan, Ramaiyan; Pillai, Vijayamohanan K.; Menon, Reghu (Journal of Applied Physics, 2012)
The charge transport in sulfonated multi-wall carbon nanotube (sMWNT)-Nafion composite is reported. The scanning electron microscope images of the composite, at 1 and 10 wt % of sMWNT, show that the nanotubes are well dispersed in polymer matrix, with conductivity values of 0.005 and 3.2 S/cm, respectively; and the percolation threshold is nearly 0.42 wt. %. The exponent (similar to 0.25) of the temperature dependence of conductivity in both samples indicates Mott's variable range hopping (VRH) transport. The conductance in 1 wt. % sample increases by three orders of magnitude at high electric-fields, consistent with VRH model. The negative magnetoresistance in 10 wt. % sample is attributed to the forward interference scattering mechanism in VRH transport. The ac conductance in 1 wt. % sample is expressed by sigma(omega) proportional to omega(s), and the temperature dependence of s follows the correlated barrier hopping model. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4749264]

Chemical deposition of CuInSe2 thin films by photoelectrochemical applications - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2012)
Copper indium diselenide films have been synthesized by chemical bath deposition method. The configuration of fabricated cell is n-CuInSe2|NaOH (1 M) + S (1 M) + Na2S (1 M)|C-(graphite). The photoelectrochemical cell characterization of the films is carried out by studying current-voltage characteristics in dark, capacitance-voltage in dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that CuInSe2 thin films are n-type conductivity. The junction ideality factor is found to be 3.81. The flat band potential is found to be 0.763 V. The barrier height value is found to be 0.232 eV. The study of power output characteristic shows open circuit voltage, short circuit current, fill factor and efficiency are found to be 310 mV, 20 mu A, 42.12% and 0.82%, respectively. Photoresponse shows lighted ideality factor which is 2.92. Spectral response shows the maximum current observed at 650 nm. (C) 2011 Published by Elsevier B.V.
Keywords: Chemical bath deposition; Flat band potential; Photo response; Power output; Spectral response

ChIP-Seq data analysis: identification of protein-DNA binding sites with SISSRs peak-finder - Narlikar, Leelavati; Jothi, Raja (Methods in molecular biology, 2012)
Protein-DNA interactions play key roles in determining gene-expression programs during cellular development and differentiation. Chromatin immunoprecipitation (ChIP) is the most widely used assay for probing such interactions. With recent advances in sequencing technology, ChIP-Seq, an approach that combines ChIP and next-generation parallel sequencing is fast becoming the method of choice for mapping protein-DNA interactions on a genome-wide scale. Here, we briefly review the ChIP-Seq approach for mapping protein-DNA interactions and describe the use of the SISSRs peak-finder, a software tool for precise identification of protein-DNA binding sites from sequencing data generated using ChIP-Seq.

Chiral crystals from an achiral molecule: 4,6-di-O-benzyl-1,3-O-benzylidene-2-O-(4-methoxybenzyl)-myo-5-inosose - Gurale, Bharat P.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2012)
The title achiral compound, C35H34O7, crystallizes in the chiral monoclinic space group P21. The molecules are densely packed to form a helical assembly along the crystallographic twofold screw axis via CH...O and CH...p interactions. Interestingly, the unit-translated helical chains are loosely connected via a rather uncommon edge-to-edge PhH...HPh short contact (H...H = 2.33 angstrom).

Cholesterol modulates the structure, binding modes, and energetics of caveolin-membrane interactions - Sengupta, Durba (Journal of Physical Chemistry B, 2012)
Caveolin-1 (cav-1) is an important membrane protein that plays a vital role in cellular signaling and trafficking by organizing membrane domains. The peptide interacts with cholesterol-rich membranes and induces large morphological changes in them, forming microdomains such as caveolae. Here, we use coarse-grain molecular dynamics simulations to study the interaction of cav-1 peptides with several model bilayer systems mimicking biological scenarios, such as cholesterol-rich domains, cholesterol-depleted domains, and unsaturated lipid domains. We show that cholesterol modulates the depth as well as orientation of cav-1 binding to membranes. Furthermore, the presence of cholesterol stabilizes more open conformations of cav-1, and we speculate that the binding modes and open conformations could be responsible for inducing morphological changes in the bilayer. We also calculated the partitioning free energy to different bilayers and show that binding to cholesterol-rich bilayers is more favorable than cholesterol-depleted bilayers and the binding to unsaturated bilayers is the least favorable. Binding to cholesterol-rich bilayers also changes the pressure profile of the bilayer to which it is bound and thereby affects the local spontaneous curvature. Our results highlight molecular details of protein-lipid interplay and provide new insights into the effects of cav-1 in tuning the morphology of cholesterol-rich membranes.

Cholesterol-tethered platinum II-based supramolecular nanoparticle increases antitumor efficacy and reduces nephrotoxicity - Sengupta, Poulomi; Basu, Sudipta; Soni, Shivani; Pandey, Ambarish; Roy, Bhaskar; Oh, Michael S.; Chin, Kenneth T.; Paraskar, Abhimanyu S.; Sarangi, Sasmit; Connor, Yamicia; Sabbisetti, Venkata S.; Kopparam, Jawahar; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Nanoscale drug delivery vehicles have been harnessed extensively as carriers for cancer chemotherapeutics. However, traditional pharmaceutical approaches for nanoformulation have been a challenge with molecules that exhibit incompatible physicochemical properties, such as platinum-based chemotherapeutics. Here we propose a paradigm based on rational design of active molecules that facilitate supramolecular assembly in the nanoscale dimension. Using cisplatin as a template, we describe the synthesis of a unique platinum (II) tethered to a cholesterol backbone via a unique monocarboxylato and O -> Pt coordination environment that facilitates nanoparticle assembly with a fixed ratio of phosphatidylcholine and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine- N-[amino (polyethylene glycol)-2000]. The nanoparticles formed exhibit lower IC50 values compared with carboplatin or cisplatin in vitro, and are active in cisplatin-resistant conditions. Additionally, the nanoparticles exhibit significantly enhanced in vivo antitumor efficacy in murine 4T1 breast cancer and in K-Ras(LSL/+/)Pten(fl/fl) ovarian cancer models with decreased systemic- and nephro-toxicity. Our results indicate that integrating rational drug design and supramolecular nanochemistry can emerge as a powerful strategy for drug development. Furthermore, given that platinum-based chemotherapeutics form the frontline therapy for a broad range of cancers, the increased efficacy and toxicity profile indicate the constructed nanostructure could translate into a nextgeneration platinum-based agent in the clinics.
Keywords: chemotherapy; nanomedicine

Clare: cracking the language of regulatory elements - Taher, Leila; Narlikar, Leelavati; Ovcharenko, Ivan (Bioinformatics, 2012)
CLARE is a computational method designed to reveal sequence encryption of tissue- specific regulatory elements. Starting with a set of regulatory elements known to be active in a particular tissue/process, it learns the sequence code of the input set and builds a predictive model from features specific to those elements. The resulting model can then be applied to user-supplied genomic regions to identify novel candidate regulatory elements. CLARE's model also provides a detailed analysis of transcription factors that most likely bind to the elements, making it an invaluable tool for understanding mechanisms of tissue- specific gene regulation.

Cloning, characterization and impact of up- and down-regulating subabul cinnamyl alcohol dehydrogenase (CAD) gene on plant growth and lignin profiles in transgenic tobacco - Sirisha, V. L.; Prashant, S.; Kumar, D. Ranadheer; Pramod, S.; Jalaja, N.; Kumari, P. Hima; Rao, P. Maheshwari; Rao, S. Nageswara; Mishra, Preeti; Karumanchi, S. Rao; Khan, Bashir Mohammad; Kishor, P. B. Kavi (Plant Growth Regulation, 2012)
Both cDNA including 5'UTR and 3'UTR and genomic clones of cinnamyl alcohol dehydrogenase (CAD) were isolated and characterized from a pulp-yielding leguminous tree Leucaena leucocephala (LlCAD1). The deduced amino acid sequence shared high identity with orthologous sequences of Acacia mangium x Acacia auriculiformis (83%), Medicago sativa (83%), Nicotiana tabaccum (83%) and Aralia cordata (81%). Full length cDNA contained 78 bases of 5'UTR and 283 bases of 3'UTR, while the genomic clone contained 5 exons and 4 introns. Western blot analysis revealed elevated expression of LlCAD1 in seedling roots and shoots compared to leaves. Sense and antisense CAD tobacco transgenics showed increased and reduced CAD activity accompanied by a change in monomeric lignin composition. Histochemical staining of lignin in down-regulated plants suggested an increase in aldehyde units and a decrease in S/G ratio. Down-regulation of CAD resulted in accumulation of syringic, ferulic, p-coumaric and sinapic acids compared to untransformed controls. These observations were validated by anatomical studies of down-regulated transgenic stems which showed thin walled, elongated phloem and xylem fibres, accompanied by a reduction in the density of vessel elements and amount of secondary xylem when compared to untransformed plants. Furthermore, Klason lignin analysis of CAD antisense transgenics showed 7-32% reduced lignin and normal phenotype as compared to untransformed plants. Such a reduction was not noticed in up-regulated transgenics. These results demonstrate a unique opportunity to explore the significant role that down-regulation of CAD gene plays in reducing lignin content thereby offering potential benefits to the pulp and paper industry.
Keywords: Cinnamyl alcohol dehydrogenase; Lignin down-regulation; Subabul (Leucaena leucocephala); Tobacco

CN-assisted oxidative cyclization of cyano cinnamates and styrene derivatives: a facile entry to 3-substituted chiral phthalides - Reddy, R. Santhosh; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2012)
The asymmetric dihydroxylation (AD) of o-cyano cinnamates and styrene derivatives leads to efficient construction of chiral phthalide frameworks in high optical purities. This unique reaction is characterized by unusual synergism between CN and osmate groups resulting in rate enhancement of the AD process. The method is amply demonstrated by the synthesis and the structural/stereochemical assignment of the natural products.

Comparative genomics of the apicomplexan parasites toxoplasma gondii and neospora caninum: coccidia differing in host range and transmission strategy - Reid, Adam James; Vermont, Sarah J.; Cotton, James A.; Harris, David; Hill-Cawthorne, Grant A.; Koenen-Waisman, Stephanie; Latham, Sophia M.; Mourier, Tobias; Norton, Rebecca; Quail, Michael A.; Sanders, Mandy; Shanmugam, Dhanasekaran; et al. (Plos Pathogens, 2012)
Toxoplasma gondii is a zoonotic protozoan parasite which infects nearly one third of the human population and is found in an extraordinary range of vertebrate hosts. Its epidemiology depends heavily on horizontal transmission, especially between rodents and its definitive host, the cat. Neospora caninum is a recently discovered close relative of Toxoplasma, whose definitive host is the dog. Both species are tissue-dwelling Coccidia and members of the phylum Apicomplexa; they share many common features, but Neospora neither infects humans nor shares the same wide host range as Toxoplasma, rather it shows a striking preference for highly efficient vertical transmission in cattle. These species therefore provide a remarkable opportunity to investigate mechanisms of host restriction, transmission strategies, virulence and zoonotic potential. We sequenced the genome of N. caninum and transcriptomes of the invasive stage of both species, undertaking an extensive comparative genomics and transcriptomics analysis. We estimate that these organisms diverged from their common ancestor around 28 million years ago and find that both genomes and gene expression are remarkably conserved. However, in N. caninum we identified an unexpected expansion of surface antigen gene families and the divergence of secreted virulence factors, including rhoptry kinases. Specifically we show that the rhoptry kinase ROP18 is pseudogenised in N. caninum and that, as a possible consequence, Neospora is unable to phosphorylate host immunity-related GTPases, as Toxoplasma does. This defense strategy is thought to be key to virulence in Toxoplasma. We conclude that the ecological niches occupied by these species are influenced by a relatively small number of gene products which operate at the host-parasite interface and that the dominance of vertical transmission in N. caninum may be associated with the evolution of reduced virulence in this species.

Comparing the interactions of DNA, polyamide (PNA) and polycarbamate nucleic acid (PCNA) oligomers with graphene oxide (GO) - Kotikam, Venubabu; Fernandes, Moneesha; Kumar, Vaijayanti Anil (Physical Chemistry Chemical Physics, 2012)
The fluorescently labelled short octameric oligothymine sequences of DNA, PNA and PCNA were used in fluorescence quenching studies in conjunction with dispersed graphene oxide. The measurable restoration of their fluorescence by complementary oligodeoxyadenylate was compared. This is the first study aimed at replacing the natural DNA probes with synthetic DNA mimics that show excellent properties in terms of formation of very strong duplexes with cDNA in addition to their stability towards proteases and nucleases.

Competition between gelation and crystallisation of a peculiar multicomponent liquid system based on ammonium salts - Kapoor, Iti; Schoen, Eva-Maria; Bachl, Jurgen; Kuehbeck, Dennis; Cativiela, Carlos; Saha, Subhadeep; Banerjee, Rahul; Roelens, Stefano; Juan Marrero-Tellado, Jose; Diaz, David Diaz (Soft Matter, 2012)
An exemplar competition between gelation and crystallisation phenomena was examined with an unusual synergistic multicomponent (organo) gelator solution (MGS), which consists of a well-defined methanolic solution of (1R, 2R)-1,2-diaminocyclohexane L-tartrate containing 2.4 equiv. of concentrated hydrochloric acid. The optimal composition of the MGS was determined through meticulous solubility, gelation and structural studies, which support a transient gelation mechanism based on the kinetic self-assembly of the tartrate salt driven by hydrogen-bonding interactions, involving ammonium nitrogen donors and hydroxyl oxygen acceptors, and electrostatic interactions. The hydrochloric acid is involved in the solubilisation of the salt through an ionic dissociation-exchange process, which ends up with the formation-precipitation of (1R, 2R)-1,2-diaminocyclohexane dihydrochloride. As a consequence, an irreversible destruction of the gel takes place, which indicates the metastable nature of this phase that cannot be accessed from the thermodynamically equilibrated state. Gelation of a variety of oxygenated and nitrogenated solvents with moderate polarity occurred efficiently using extremely low MGS concentrations at low temperatures, and the gel phase was confirmed by dynamic rheological measurements. Several features make the described MGS unique: (1) it is a multicomponent solution where each component and its stoichiometry play a key role in the reproducible formation and stabilization of the gels; (2) it is formed by simple, small, and commercially available chiral building blocks (dissolved in a well-defined solvent system), which are easily amenable for further modifications; (3) the gelation phenomenon takes place efficiently at low temperature upon warming up the isotropic solution, conversely to the typical gel preparation protocol; and (4) the formed organogels are not thermoreversible despite the non-covalent interactions that characterize the 3D-network.

Computational fluid dynamics modelling of solid suspension in stirred tanks - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Current Science, 2012)
Solid suspension and mixing are crucial in many important processes, including multiphase catalytic reactions, crystallization, precipitation, etc. In recent years, various efforts have been made to numerically simulate solid-liquid flows in stirred vessels using computational fluid dynamics (CFD). In this article, we present a brief account of our group's efforts at developing and using CFD models for simulating solid suspension in stirred tanks. Computational models were developed and evaluated by comparing model predictions with our data as well as published experimental data. A variety of experimental techniques ranging from torque and wall pressure fluctuations to ultrasound velocity profiler were used. Efforts were made to develop appropriate sub-models for capturing influence of the prevailing turbulence and solid volume fraction on effective inter-phase coupling terms. A hysteresis in variation of the height of the cloud of suspended solid with impeller rotational speed was observed. The hysteresis, besides having applications in realizing better suspension at lower effective power consumption, also offers an attractive evaluation test for CFD models. A new way to carry out dynamic settling of solid cloud by sudden impeller stoppage has been developed. The approach, models and results presented here will be useful for extending applications of CFD models for simulating industrial stirred slurry reactors as well as further research in the field.
Keywords: computational fluid dynamics; hysteresis; solid suspension; stirred tanks

Computational investigation of the role of the iridium dihydrogen pincer complex in the formation of the cyclic pentamer (NH2BH2)(5) - Ghatak, Kamalika; Vanka, Kumar (Computational and Theoretical Chemistry, 2012)
Computational studies with density functional theory (DFT) and MP2 have been done to investigate the interaction between the iridium dihydrogen pincer complex: (POCOP)IrH2 (where POCOP = eta(3)-1,3(OPt-Bu-2)(2)C6H3) and NH2BH2, the immediate product of ammonia borane (NH3BH3) dehydrogenation. A mechanism has been proposed for an oligomerisation process at the metal centre that involves competition between (i) insertion of an NH2BH2 molecule into the (NH2BH2)(n) chain and (ii) termination of the chain leading to the formation of the cyclic (NH2BH2)(n) oligomer. The calculated Delta G values show that the competition favours insertion over termination for the cases n = 1 to n = 4 but favours termination for n = 5. The computational studies therefore indicate that the cyclic pentamer (NH2BH2)(5) would be formed during NH3BH3 dehydrogenation by the (POCOP)IrH2 catalyst, agreeing with experimental findings. The mechanistic understanding gained has implications for the facile regeneration of ammonia borane. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ammonia borane; Hydrogen storage; Iridium pincer ligand catalyst; Mechanistic studies; Oligomerisation cycle

Concise synthesis of (+)-deoxoprosophylline via Co(III)(salen)-catalyzed two stereocentered HKR of racemic azido epoxides - Devalankar, Dattatray A.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
An efficient synthesis of (+)-deoxoprosophylline has been achieved in high optical purity (99% ee) from readily available cis-2-butene-1,4-diol. The strategy employs Co-catalyzed Hydrolytic Kinetic Resolution (HKR) of two stereocentered racemic azido epoxides and diastereoselective intramolecular reductive cyclization as key reactions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Azido epoxide; Hydrolytic kinetic resolution; Piperidine; Wittig olefination

Conducting polyanilline based paints on hot dip galvanized low carbon steel for corrosion protection - Deshpande, P.; Vagge, S.; Jagtap, Sharmili; Khiarnar, R.; Kelkar, Sarika A.; More, Minal (Bulgarian Chemical Communications, 2012)
Conducting polyaniline based paints have been applied on hot dip galvanized low carbon steel samples. The corrosion protection performance of these paint coatings was evaluated by using Tafel plots and impedance spectroscopy. It was found that the paint coatings offered significant corrosion protection to hot dip galvanized low carbon steel in aqueous 3.5 wt % NaCl solution.
Keywords: Conducting polyaniline based paints; corrosion prevention; hot dip galvanized low carbon steel

Confinement of zinc oxide nanoparticles in ordered mesoporous silica MCM-41 - Lihitkar, P. B.; Violet, Samuel; Shirolkar, Mandar; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Materials Chemistry and Physics, 2012)
Mesoporous silica (MS) and zinc loaded MS composites have been synthesized and characterized using high resolution transmission electron microscopy, X-ray diffraction, UV-visible spectroscopy, photoluminescence spectroscopy, N-2 adsorption-desorption isotherms, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Thermal treatment of the zinc loaded MS composite lead to the formation of ZnO-MS composite. The well ordered uniform pore structure of MS (pore size similar to 3.4 nm) is found to remain stable even after 30% Zn loading albeit decrease in the pore size 1.2 nm indicates the formation of ZnO inside the pores. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Defect; Energy spectroscopy for chemical analysis (ESCA); Mesoporous; Photoluminescence spectroscopy; Surface properties

Conformational modulation of Ant-Pro oligomers using chirality alteration of proline residues - Kale, Sangram S.; Kotmale, Amol S.; Dutta, Achintya Kumar; Pal, Sourav; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2012)
Structural modulation of Ant-Pro (anthranilic acid-proline) oligomers has been carried out by chirality alteration of the proline residues. The results suggest that the chirality altered oligomers show well-defined helical conformation featuring nine-membered hydrogen bonding interactions - without compromising conformational rigidity.

Conformational transitions of the catalytic domain of heme-regulated eukaryotic initiation factor 2 alpha kinase, a key translational regulatory molecule - Sreejith, R. K.; Suresh, C. G.; Bhosale, Siddharth H.; Bhavnani, Varsha; Kumar, Avinash; Gaikwad, Sushama M.; Pal, Jayanta K. (Journal of Fluorescence, 2012)
In mammalian cells, the heme-regulated inhibitor (HRI) plays a critical role in the regulation of protein synthesis at the initiation step through phosphorylation of a-subunit of the eukaryotic initiation factor 2 (eIF2). In this study we have cloned and performed biophysical characterization of the kinase catalytic domain (KD) of rabbit HRI. The KD described here comprises kinase 1, the kinase insertion domain (KI) and kinase 2. We report here the existence of an active and stable monomer of HRI (KD). The HRI (KD) containing three tryptophan residues was examined for its conformational transitions occurring under various denaturing conditions using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The parameter A and phase diagram analysis revealed multi-state unfolding and existence of three stable intermediates during guanidine hydrochloride (Gdn-HCl) induced unfolding of HRI (KD). The protein treated with 6 M Gdn-HCl showed collisional and static mechanism of acrylamide quenching and the constants (K-sv=3.08 M-1 and K-s=5.62 M-1) were resolved using time resolved fluorescence titration. Based on pH, guanidine hydrochloride and temperature mediated transitions, HRI (KD) appears to exemplify a rigid molten globule-like intermediate with compact secondary structure, altered tertiary structure and exposed hydrophobic patches at pH 3.0. The results indicate the inherent structural stability of HRI (KD), a member of the class of stress response proteins.
Keywords: Circular dichroism (CD); eIF2 alpha kinase; Heme-regulated inhibitor; Molten globule; Steady-state and time-resolved fluorescence

Constrained variational approach for energy derivatives in Intermediate hamiltonian fock-space coupled-cluster theory - Ghosh, Aryya; Gupta, Jitendra; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
Fock-space multi-reference coupled cluster theory is an efficient method for electronic structure of nearly degenerate cases. However, it suffers from the intruder state problem for large model space. The intermediate Hamiltonian formulation eliminates intruder state problem and helps in the convergence of equations. In this paper we have implemented intermediate Hamiltonian approach in Fock-space coupled cluster method for the response properties. We test our method for the dipole moments of doublet radicals. We report dipole moments of CN, SF and NS radicals. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Constrained variational approach; Fock-space multi-reference coupled cluster; Intermediate Hamiltonian theory; Response approach

Continuous dehydration and hydrogenolysis of glycerol over non-chromium copper catalyst: laboratory-scale process studies - Mane, Rasika B.; Rode, Chandrashekhar V. (Organic Process Research & Development, 2012)
A non-chromium Cu:Al catalyst was developed for glycerol dehydration under N-2 atmosphere to acetol and hydrogenolysis to 1,2-propanediol (1,2-PDO). Among the various copper-based catalysts screened in this work, Cu:Al-1 catalyst showed the highest activity and acetol selectivity in water medium, whereas transfer hydrogenation in 2-propanol as the reaction medium led to the formation of 1,2-PDO (10-38%). The same catalyst was also found to catalyze the direct hydrogenolysis of glycerol to 1,2-PDO. Time on stream activity (TOS) of our Cu:Al-1 catalyst for both continuous dehydration and hydrogenolysis of glycerol was found to be 400 h with an average glycerol conversion of 90% and 65%, respectively. Maximum acetol selectivity was 55% while 1,2-PDO selectivity was 91% in dehydration and hydrogenolysis reactions separately. Effects of various reaction conditions on conversion, selectivity, and global rates of the two processes were also investigated.

Control of porosity by using isoreticular zeolitic imidazolate frameworks (IRZIFs) as a template for porous carbon synthesis - Pachfule, Pradip; Biswal, Bishnu P.; Banerjee, Rahul (Chemistry-A European Journal, 2012)
Herein, by using isoreticular zeolitic imidazolate frameworks (IRZIFs) as a template, we report the synthesis, morphology, and gas adsorption properties of porous carbon synthesized by a nanocasting method at 1000 degrees C, in which furfuryl alcohol (FA) was used as a carbon source. By using IRZIFs with variable porosity as templates, we could achieve control over the carbon porosity and H-2 and CO2 uptake. The resultant microporous carbon C-70, synthesized by using ZIF-70 as the template, is the most porous (Brunauer-Emmett-Teller (BET) surface area 1510 m(2)g(-1)). Carbon C-68, synthesized by using ZIF-68, has moderate porosity (BET surface area 1311 m(2)g(-1)), and C-69, synthesized by using ZIF-69, has the lowest porosity in this series (BET surface area 1171 m(2)g(-1)). The porous carbons C-70, C-68, and C-69, which have graphitic texture, have promising H2 uptake capacities of 2.37, 2.15, and 1.96 wt%, respectively, at 77 K and 1 atm. Additionally, C-70, C-68, and C-69 show CO2 uptake capacities of 5.45, 4.98, and 4.54 mmolg(-1), respectively, at 273 K and 1 atm. The gas uptake trends shown by C-70, C-68, and C-69 clearly indicate the dependence of carbon porosity on the host template. Moreover, the as-synthesized carbons C-70, C-68, and C-69 show variable conductivity.
Keywords: Carbon; Hydrogen storage; metal-organic frameworks; microporous materials; zinc

Controlled release of nutrients to mammalian cells cultured in shake flasks - Hegde, Swati; Pant, Tejal; Pradhan, Ketaki; Badiger, Manohar V.; Gadgil, Mugdha (Biotechnology Progress, 2012)
Though cell culture-based protein production processes are rarely carried out under batch mode of operation, cell line and initial process development operations are usually carried out in batch mode due to simplicity of operation in widely used scale down platforms like shake flasks. Nutrient feeding, if performed, is achieved by bolus addition of concentrated feed solution at different intervals, which leads to large transient increases in nutrient concentrations. One negative consequence is increased waste metabolite production. We have developed a hydrogel-based nutrient delivery system for continuous feeding of nutrients in scale down models like shake flasks without the need for manual feed additions or any additional infrastructure. Continuous delivery also enables maintaining nutrient concentrations at low levels, if desired. The authors demonstrate the use of these systems for continuous feeding of glucose and protein hydrolysate to a suspension Chinese Hamster Ovary (CHO) culture in a shake flask. Glucose feeding achieved using the glucose-loaded hydrogel resulted in a 23% higher integral viable cell density and an 89% lower lactate concentration at the end of the culture when compared with a bolus-feed of glucose. (c) 2011 American Institute of Chemical Engineers Biotechnol. Prog., 2012

Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.

Conversion of cellulose to polyols over promoted nickel catalysts - Shrotri, Abhijit; Tanksale, Akshat; Beltramini, Jorge Norberto; Gurav, Hanmant; Chilukuri, Satyanarayana V. (Catalysis Science & Technology, 2012)
Sorbitol is one of the key platform chemicals that can be applied to several industrial applications, including bio-fuels and hydrogen production. Presently there is no commercial heterogeneous catalytic process to produce sorbitol from cellulose due to the low yield and high cost of noble metals required for the conversion. In this paper we describe an aqueous phase hydrolysis-hydrogenation process to convert cellulose to sorbitol using a cheap Ni based catalyst. Monometallic Ni catalysts showed little activity for the reaction, but with the addition of a small amount of Pt to the Ni catalyst (Ni : Pt = 22 : 1 atom ratio), the activity was greatly enhanced. Results showed that the bimetallic Ni-Pt catalysts supported on mesoporous alumina gave a hexitol (sorbitol + mannitol) yield of 32.4% compared to only 5% with a Ni catalyst. Moreover, Ni-Pt supported on a mesoporous beta zeolite support provided even higher yield of 36.6%. These results were obtained after only 6 hours of run at 200 degrees C and 50 bar H-2 pressure (at room temperature). The presence of a small amount of Pt promotes the protonation of water and hydrogen molecules, which spill over to Ni sites creating in situ acid sites to catalyse hydrolysis of cellulose.

Converting ab initio energies to enthalpies of formation of free radicals. I. new atom equivalents for alkyl radicals - Bhattacharya, Arijit (Aiche Journal, 2012)
A simple method is presented to convert ab initio computed total energies to the standard enthalpy of formation (Delta H-f(o)) of a large number of saturated alkyl radicals (especially those that are relatively highly branched), for which experimental data are scarcely available. For this purpose a new set of radical atom-equivalents (AEQ) and their unique combinations were defined and the energy values of the latter assigned. The theory level and the basis set requirement for the quantum chemistry calculation of the molecular energy were found to be moderate. The Delta H-f(o) predictions appear to be quite accurate with reference to limited available experimental data and are better than values calculated by the group-additivity and the difference methods. The strategy provides an inexpensive way of harnessing the power of computational chemistry and combining it with the organization and insight from the group-additivity method sans any empirical corrections. (C) 2011 American Institute of Chemical Engineers AIChE J, 58: 600-609, 2012
Keywords: atom-equivalents; computational chemistry; enthalpy of formation; free radicals; goup additivity method

Copper modified waste fly ash as a promising catalyst for glycerol hydrogenolysis - Rode, C. V.; Mane, R. B.; Potdar, A. S.; Patil, P. B.; Niphadkar, P. S.; Joshi, P. N. (Catalysis Today, 2012)
Several catalyst formulations using waste fly ash along with Cu were prepared and characterised by XRD, BET and TEM. These catalysts were also evaluated for the first time for hydrogenolysis of glycerol to 1,2 propanediol (1,2-PDO) in a batch reactor under 52 bar H-2 pressure in the temperature range of 473-513 K conditions. The fly ash pretreated by alkali using the fusion method and impregnated with Cu showed higher activity and stability for glycerol hydrogenolysis. Due to pretreatment with alkali at high temperature, transformation of alpha-quartz to the tridymite phase of SiO2 occurred. More importantly, use of alkali either during the pretreatment or the Cu loading step resulted in a high dispersion on the surface which was responsible for higher glycerol conversion and 1,2-PDO selectivity. The effects of temperature, Cu loading and solvent on glycerol conversion and product selectivities were also studied in this work. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propanediol; Alkali fusion; Cu loading; Fly ash; Glycerol hydrogenolysis

Correlation between coordinated water content and proton conductivity in Ca-BTC-based metal-organic frameworks - Mallick, Arijit; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2012)
Proton conductivity of five Ca-based MOFs which depends on the amount of water molecules coordinated to the Ca-centres has been reported. These MOFs show high temperature proton conductivity due to the strong hydrogen bonding between the lattice and coordinated water molecules.

Covalently anchored ruthenium-phosphine complex on mesoporous organosilica: catalytic applications in hydrogenation reactions - Sisodiya, Sheetal; Lazar, Anish; Shylesh, Sankaranarayanapillai; Wang, Lei; Thiel, Werner R.; Singh, Anand Pal (Catalysis Communications, 2012)
New heterogeneous catalysts for alkene hydrogenation reactions were prepared by the immobilization of trimethoxysilane functionalized triphenylphosphine eta(6)-p-cymene ruthenium complex on mesoporous organosilica (PMO-Ru). Characterization techniques confirmed the structural integrity of the organosilica material and proved the successful anchoring of ruthenium complex. Catalytic activity and stability of PMO-Ru sample investigated in the hydrogenation of various olefins showed higher activity than a neat and MCM-41 supported ruthenium catalyst. High catalytic activity and stability of organosilica supported ruthenium catalyst are attributed to the hydrophobic environments and to the unique structural features imparted from the presence of organic groups in the framewall positions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Heterogenization; Hydrogenation; Organosilica; ruthenium; Triphenyl phosphine

Critical review of membrane bioreactor models - Part 2: Hydrodynamic and integrated models - Naessens, W.; Maere, T.; Ratkovich, N.; Vedantam, S.; Nopens, I. (Bioresource Technology, 2012)
Membrane bioreactor technology exists for a couple of decades, but has not yet overwhelmed the market due to some serious drawbacks of which operational cost due to fouling is the major contributor. Knowledge buildup and optimisation for such complex systems can heavily benefit from mathematical modelling. In this paper, the vast literature on hydrodynamic and integrated MBR modelling is critically reviewed. Hydrodynamic models are used at different scales and focus mainly on fouling and only little on system design/optimisation. Integrated models also focus on fouling although the ones including costs are leaning towards optimisation. Trends are discussed, knowledge gaps identified and interesting routes for further research suggested. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: CFD; Costs; hydrodynamics; Integrated model; Modelling

Crystal structure of (2S, 4R)-2-benzyl 1-tert-butyl 4-(tosyloxy)pyrrolidine-1,2-dicarboxylate, C24H29NO7S - Ghosh, Munmun; Mallick, Arijit; Diaz, David Diaz (Zeitschrift Fur Kristallographie-New Crystal Structures, 2012)
{C24H29NO7S, triclinic, P1 (no. 1)

Crystallization and X-ray structure analysis of a thermostable penicillin G acylase from alcaligenes faecalis - Varshney, Nishant Kumar; Kumar, R. Suresh; Ignatova, Zoya; Prabhune, Asmita; Pundle, Archana; Dodson, Eleanor J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2012)
{The enzyme penicillin G acylase (EC 3.5.1.11) catalyzes amide-bond cleavage in benzylpenicillin (penicillin G) to yield 6-aminopenicillanic acid, an intermediate chemical used in the production of semisynthetic penicillins. A thermostable penicillin G acylase from Alcaligenes faecalis (AfPGA) has been crystallized using the hanging-drop vapour-diffusion method in two different space groups: C2221, with unit-cell parameters a = 72.9
Keywords: calcium binding; disulfide bridges; Ntn hydrolases; orthorhombic form; tetragonal form; Thermostability

Cu-II-exchanged montmorillonite K10 clay-catalyzed direct carboxylation of terminal alkynes with carbon dioxide - Aher, Ravindra D.; Gade, Madhuri H.; Reddy, R. Santhosh; Sudalai, Arumugam (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
A new, simple and straight-forward protocol for direct carboxylation of terminal alkynes has been developed using Cu-II-montmorillonite K10 clay as a heterogeneous catalyst and CO2 as the C1 carbon feedstock. Also coupling of terminal alkynes with CO2 (1 atm) in the presence of alkyl halides has been achieved under the same reaction conditions, thereby providing access to a variety of functionalized alkyl-2-alkynoates in high yields.
Keywords: Alkyl esters; Alkyne C-H activation; Carbon dioxide activation; Carboxylation; Catalysts; Montmorillonite clays

CuO nanoparticles supported on silica: a simple, efficient, and recyclable catalyst for hydroacylation reactions of aldehydes with azodicarboxylate - Inamdar, Suleman M.; More, Vinod K.; Mandal, Sisir K. (Chemistry Letters, 2012)
We describe a green and efficient procedure for the hydroacylation of aldehydes with diisopropyl azodicarboxylate, using CuO nanoparticles supported on silica (CuO-np/SiO2) as a catalyst, in good to excellent yields. A wide range of aldehydes, including aromatic and aliphatic compounds, were considered. The catalyst is found to be truly heterogeneous in the reaction mixture and can be reused without loss of catalytic activity.

Cu-ZrO2 nanocomposite catalyst for selective hydrogenation of levulinic acid and its ester to gamma-valerolactone - Hengne, Amol M.; Rode, Chandrashekhar V. (Green Chemistry, 2012)
Several copper based catalysts were prepared, characterized and evaluated for the hydrogenation of levulinic acid and its methyl ester. Among these, nanocomposites of Cu-ZrO2 and Cu-Al2O3 quantitatively catalyzed the hydrogenation of levulinic acid and its methyl ester to give 90-100% selectivity to gamma-valerolactone in methanol and water respectively. Both the Cu-ZrO2 and Cu-Al2O3 nanocomposites were prepared by the co-precipitation method using mixed precursors under controlled conditions. XRD results showed that the main active phase of the reduced Cu-ZrO2 catalyst was metallic copper and particle size was found to be of 10-14 nm by HRTEM. The active metal leaching was at a maximum for the Cu-Al2O3 catalyst in a water medium due to the formation of a copper-carboxylate complex that was blue in colour. Surprisingly, copper leaching was completely suppressed in the case of the Cu-ZrO2 catalyst in methanol in spite of the substrate loading was increased from 5 to 20% w/w. The excellent recyclability of the Cu-ZrO2 catalyst with complete LA conversion and > 90% GVL selectivity makes it a sustainable process having a commercial potential.

CVD synthesis of highly graphitized single-walled carbon nanotubes using nitrogen-pretreated Fe-Mo/MgO catalyst - Patil, Gaurav; Sarode, Chetan; Patil, Rahul; Gokhale, Suresh (Chemistry Letters, 2012)
Single-walled carbon nanotubes (SWNTs) with highly graphitized structure were synthesized by thermal chemical vapor deposition using an improved nitrogen-pretreated Fe-Mo/MgO catalyst. The effects of nitrogen pretreatment of Fe-Mo/MgO on the structure and properties of SWNTs were studied by TEM, Raman spectroscopy, and TGA. The investigations revealed that the nitrogen pretreatment of the catalyst promoted the growth of SWNTs. It also enhanced the structural features and thermal properties of SWNTs.

C-3 `-endo-puckered pyrrolidine containing PNA has favorable geometry for RNA binding: novel ethano locked PNA (ethano-PNA) - Banerjee, Anjan; Kumar, Vaijayanti A. (Bioorganic & Medicinal Chemistry, 2013)
A novel peptide nucleic acid (PNA) analogue is designed with a constraint in the aminoethyl segment of the aegPNA backbone so that the dihedral angle beta is restricted within 60-80 degrees, compatible to form PNA:RNA duplexes. The designed monomer is further functionalized with positively charged amino-/guanidino-groups. The appropriately protected monomers were synthesized and incorporated into aegPNA oligomers at predetermined positions and their binding abilities with cDNA and RNA were investigated. A single incorporation of the modified PNA monomer into a 12-mer PNA sequence resulted in stronger binding with complementary RNA over cDNA. No significant changes in the CD signatures of the derived duplexes of modified PNA with complementary RNA were observed. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Antisense therapeutics; Conformationally constrained PNA; Diagnostics; Peptide nucleic acid (PNA)

Can molecular cages be effective at small molecule activation? a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Inorganic Chemistry, 2013)
Several approaches have been investigated in recent years in the area of small molecule activation. The current work introduces a new concept in this field: that of molecular cages, containing only main group elements, serving to activate small molecules. Full quantum mechanical calculations employing DFT/SCS-MP2 methods indicate that recently synthesized Ga-N cage compounds would be excellent candidates for mediating in important reactions such as the catalysis of ammonia borane dehydrogenation. The current work therefore opens up exciting new possibilities in small molecule activation research.

CAP/EOM-CCSD method for the study of potential curves of resonant states - Ghosh, Aryya; Karne, Anagha S.; Pal, Sourav; Vaval, Nayana (Physical Chemistry Chemical Physics, 2013)
The equation-of-motion coupled-cluster (EOM-CC) method along with the complex absorbing potential (CAP) is used for the study of resonance in e(-)-N-2 and e(-)-CO. Resonance position and width are studied as a function of bond length. We report the potential curves (PC) of the resonance states.

Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrids for improved supercapacitor performance - Balan, Beena K.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (RSC Advances, 2013)
Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrid electrode material which integrates dual wall decoration and interfacial area tuning for supercapacitor applications has been devised based on a simple approach. This is achieved by decorating RuO2 nanoparticles of size ca. 2-3 nm along the inner and outer walls of a hollow carbon nanofiber (CNF) support (F-20RuO(2)). In the next step, a proton conducting polymer, phosphoric acid doped polybenzimidazole (PBI-BuI), interface is created along the inner and outer surfaces of this material. A 103% increase in the specific capacitance is obtained for RuO2-PBI hybrid material as compared to that of F-20RuO(2) at the optimum level of the polymer wrapping. Apart from the high specific capacitance, the RuO2-PBI hybrid materials exhibit enhanced rate capability and excellent electrochemical stability of 98% retention in the capacitance. Such a remarkably high activity can be primarily attributed to the efficient dispersion of active sites achieved by properly utilizing inner and outer surfaces of CNF. Apart from this, the facile routes for ion transport created as a result of PBI incorporation coupled with excellent interfacial contact between the RuO2 and the electrolyte resulting in the improved utilization of the active material also contribute to the improved activity. In addition to this, the synergistic effects of pseudocapacitive contribution from both the PBI-BuI and RuO2 also contribute to the redefined performance characteristics.

Carboxamide versus sulfonamide in peptide backbone folding: a case study with a hetero foldamer - Ramesh, Veera V. E.; Kale, Sangram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic Letters, 2013)
Strikingly dissimilar hydrogen-bonding patterns have been observed for two sets of closely similar hetero foldamers containing carboxamide and sulfonamides at regular intervals. Although both foldamers maintain conformational ordering, the hydrogen-bonding pattern and backbone helical handedness differ diametrically.

Carrier free co-immobilization of alpha amylase, glucoamylase and pullulanase as combined cross-linked enzyme aggregates (combi-CLEAs): a tri-enzyme biocatalyst with one pot starch hydrolytic activity - Talekar, Sachin; Pandharbale, Amol; Ladole, Mayur; Nadar, Shamraja; Mulla, Mosin; Japhalekar, Kshitija; Pattankude, Kishori; Arage, Devika (Bioresource Technology, 2013)
A tri-enzyme biocatalyst ``combi-CLEAs'' with starch hydrolytic activity was prepared from commercially available alpha amylase, glucoamylase and pullulanase preparations by aggregating enzymes with ammonium sulphate followed by cross-linking formed aggregates for 4.5 h with 40 mM glutaraldehyde. The effects of precipitant type and cross-linking were studied and the biocatalyst was characterized. Scanning electron microscopy analysis showed that tri-enzyme biocatalyst was of spherical structure. For one pot starch hydrolytic activity, shift in optimum pH from 6 to 7 and temperature from 65 to 75 degrees C were observed after co-immobilization of enzymes. After one pot starch hydrolysis reaction in batch mode, 100%, 60% and 40% conversions were obtained with combi-CLEAs, separate CLEAs mixture and free enzyme mixture, respectively. Co-immobilization also enhanced the thermal stability of enzymes. Finally, the catalytic activity of enzymes in combi-CLEAs during one pot starch hydrolysis was well maintained up to five cycles without performance changes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Alpha amylase; Combined cross-linked enzyme aggregates (combi-CLEAs); Glucoamylase; One pot starch hydrolysis; Pullulanase

Catalytic activity of ZIF-8 in the synthesis of styrene carbonate from CO2 and styrene oxide - Zhu, Minqi; Srinivas, Darbha; Bhogeswararao, Seemala; Ratnasamy, Paul; Carreon, Moises A. (Catalysis Communications, 2013)
The catalytic activity of ZIF-8 in the synthesis of styrene carbonate from carbon dioxide and styrene oxide is presented. ZIF-8 crystals displayed catalytic activity even at temperatures as low as 50 degrees C, with styrene carbonate yields as high as similar to 54% at 100 degrees C. In contrast to many prior-art catalysts, solvents or co-catalysts were not required. Pyridine and ammonia were used as probe molecules to estimate the type and density of acid sites in fresh and reused ZIF-8 catalysts. DRIFT spectroscopy of adsorbed pyridine revealed the presence of both Bronsted (B) and Lewis (L) acid sites. The B-sites have nearly vanished in the case of recycled ZIF-8 catalysts. The simultaneous presence of both the acid sites and the nitrogen basic moieties from the imidazole linker in ZIF-8 promoted the adsorption of the CO2 on the solid surface and its further conversion to the cyclic carbonate. The ZIF-8 catalysts could be recycled and reused without significant loss in catalytic activity. Published by Elsevier B.V.
Keywords: CO2 conversion; cyclic carbonates; Styrene carbonate; Zeolitic imidazolate frameworks; ZIF-8

Catalytic and DFT study of selective ethylene oligomerization by nickel(II) oxime-based complexes - Tayade, Kamlesh N.; Mane, Manoj V.; Sen, Suman; Murthy, C. N.; Tembe, Gopal L.; Pillai, S. Muthukumaru; Vanka, Kumar; Mukherjee, Soumen (Journal of Molecular Catalysis A-Chemical, 2013)
The reactivity of nickel(II) thiophenealdoxime complex (3) toward oligomerization of ethylene in the presence of an alkylaluminum co-catalyst has been studied. The complex was found to be a selective ethylene dimerization catalyst in the presence of co-catalysts such as methylalumoxane (MAO) and diethylaluminum chloride (DEAC). With DEAC, the productivity was considerably higher than with MAO. Under optimum conditions the productivity reaches 388 kg/mol catalyst/h/bar with DEAC whereas for MAO this value was 119 kg/mol catalyst/h/bar. Complex 3 displays good ethylene conversions of up to a maximum of 90% with exceptionally high alpha-selectivity for 1-butene (>99.5%) amongst C-4 products. Computational studies using density functional theory (DFT) were also carried out to ascertain the decomposition pathway for 3 as well as that for Ni(II) complex of the pyridine ketoxime ligand 2. The results suggest that loss of one of the two bidentate oxime ligands attached to the metal center through reaction with DEAC is likely for both 2 and 3. Further, calculations indicate that the subsequent decomposition step was significantly more probable for 3 than for 2 thus explaining why the pyridine ketoxime ligand bound nickel complex 2 was experimentally found to be more stable than the thiophene aldoxime bound nickel complex 3. Calculations also show that the proton of the -OH group (oxime) plays a major role in the stability of the molecules. This was confirmed experimentally by synthesizing the Ni(II) dichloro complex of Pyridine-2-carbaldehyde O-methyloxime 5 and reacting it with ethylene under similar conditions. 5 was found to be highly active even at low co-catalyst concentrations. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Butene-1; Ethylene dimerization; Ni(II) complex; Thiophene aldoxime

Catalytic dehydration of lactic acid to acrylic acid using calcium hydroxyapatite catalysts - Ghantani, Vidhya C.; Lomate, Samadhan T.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Green Chemistry, 2013)
A series of calcium hydroxyapatite (HAP) catalysts were synthesised with a Ca/P ratio ranging from 1.3 to 1.89 by a co-precipitation method that involved changing the pH of the calcium and phosphorous precursors. The physicochemical characterization by XRD, SEM, BET surface area and CO2 and NH3-TPD techniques confirmed the hydroxyapatite formation. These HAP catalysts were used for the vapour phase dehydration of lactic acid to acrylic acid. The HAP catalyst with a Ca/P ratio of 1.3 was found to be the most efficient catalyst among the synthesised series, which gave 100% conversion of lactic acid and 60% selectivity towards acrylic acid at 375 degrees C when a 50% (w/w) aqueous solution of lactic acid was used. The higher selectivity towards acrylic acid has been correlated to the increased acidity and reduced basicity of the HAP catalyst with a Ca/P ratio of 1.3 compared to the other HAP catalysts. The catalyst was found to be very stable and no deactivation was observed even after 300 h of reaction time. In situ FTIR studies were performed for understanding the mechanistic aspects and showed the formation of calcium lactate as an intermediate species during the dehydration of lactic acid to acrylic acid.

Catalytic signal amplification using [Fe-III(biuret-amide)]-mesoporous silica nanoparticles: visual cyanide detection - Panda, Chakadola; Dhar, Basab B.; Malvi, Bharmana; Bhattacharjee, Yudhajit; Sen Gupta, Sayam (Chemical Communications, 2013)
Catalytic signal amplification was used for the colorimetric detection of CN- in aqueous media by using the enzyme catalase in tandem with mesoporous silica nanoparticle based synthetic HRP enzyme mimic Fe-MSNs. Signal amplification up to a maximum of eight fold was observed for the reporter ``oxidized TMB'' with respect to the added CN- ion.

Catalytic transformation of alcohols to carboxylic acid salts and H2 using water as the oxygen atom source - Balaraman, Ekambaram; Khaskin, Eugene; Leitus, Gregory; Milstein, David (Nature Chemistry, 2013)
The oxidation of alcohols to carboxylic acids is an important industrial reaction used in the synthesis of bulk and fine chemicals. Most current processes are performed by making use of either stoichiometric amounts of toxic oxidizing agents or the use of pressurized dioxygen. Here, we describe an alternative dehydrogenative pathway effected by water and base with the concomitant generation of hydrogen gas. A homogeneous ruthenium complex catalyses the transformation of primary alcohols to carboxylic acid salts at low catalyst loadings (0.2 mol%) in basic aqueous solution. A consequence of this finding could be a safer and cleaner process for the synthesis of carboxylic acids and their derivatives at both laboratory and industrial scales.

Catalytic upgrading of renewable levulinic acid to ethyl levulinate biodiesel using dodecatungstophosphoric acid supported on desilicated H-ZSM-5 as catalyst - Nandiwale, Kakasaheb Y.; Sonar, Shilpa K.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Patil, Vilas S.; Bokade, Vijay V. (Applied Catalysis A-General, 2013)
Levulinic acid (LA) is considered as a renewable platform chemical and can be used for the synthesis of variety of important fuels and chemicals. In particular, its esterification with ethanol produces ethyl levulinate (EL) would be green process, as it can be used as diesel miscible biofuel (DMB), preventing global warming by decreasing atmospheric CO2. This study explores the use of modified H-ZSM-5 by desilication viz.; DH-ZSM-5 and dodecatungstophosphoric acid (DTPA) loaded on DH-ZSM-5 for esterification of LA with ethanol aiming to EL. Different degree of desilication of H-ZSM-5 was performed by using aq. NaOH (0.2-1.5 M) at 338 K for 30 min and then DTPA was loaded on these desilicated H-ZSM-5 (DH-ZSM-5) support. H-ZSM-5, DH-ZSM-5 and DTPA on these DH-ZSM-5 samples were characterized by powder x-ray diffraction (XRD), N-2 adsorption-desorption, pyridine chemisorbed IR spectroscopy, Temperature Programmed Ammonia Desorption (TPAD). The increase in conversion of levulinic acid was observed from 28% to 94% with increase of DTPA loading from 0% to 15%. The increased LA conversion may be due to increase in total acidity from 43.14% to 84.31%. The use of DH-ZSM-5 as support for deposition of DTPA may be reported for the first time. The present work also extended to optimize process parameters such as DTPA loading on DH-ZSM-5, catalyst to LA ratio, LA to ethanol molar ratio, speed of agitation, particle size reaction temperature and catalyst reusability. Kinetic study based on pseudo-homogeneous (P-H) model is also presented. The experimental results follow second order kinetics. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: desilicated H-ZSM-5; DTPA on desilicated H-ZSM-5; Esterification; ethyl levulinate; levulinic acid

C-C Bond formation catalyzed by natural gelatin and collagen proteins - Kuehbeck, Dennis; Dhar, Basab Bijayi; Schoen, Eva-Maria; Cativiela, Carlos; Gotor-Fernandez, Vicente; Diaz, David Diaz (Beilstein Journal of Organic Chemistry, 2013)
The activity of gelatin and collagen proteins towards C-C bond formation via Henry (nitroaldol) reaction between aldehydes and nitroalkanes is demonstrated for the first time. Among other variables, protein source, physical state and chemical modification influence product yield and kinetics, affording the nitroaldol products in both aqueous and organic media under mild conditions. Significantly, the scale-up of the process between 4-nitrobenzaldehyde and nitromethane is successfully achieved at 1 g scale and in good yield. A comparative kinetic study with other biocatalysts shows an increase of the first-order rate constant in the order chitosan < gelatin < bovine serum albumin (BSA) < collagen. The results of this study indicate that simple edible gelatin can promote C-C bond forming reactions under physiological conditions, which may have important implications from a metabolic perspective.
Keywords: biocatalysis; carbon-carbon bond formation; gelatin; Henry reaction; protein

Characterisation and determination of in vitro antioxidant potential of betalains from talinum triangulare (Jacq.) willd. - Swarna, J.; Lokeswari, T. S.; Smita, M.; Ravindhran, R. (Food Chemistry, 2013)
Talinum triangulare (Jacq.) Willd is an erect, succulent, perennial herb belonging to the family Portulacaceae. Under extreme environmental conditions, the plant produces betalain pigments which get accumulated in the stem region. Hence, in the present study, the betaxanthin and betacyanin patterns from different samples of T. triangulare have been investigated by applying high-performance liquid chromatography photo-diode array detection (HPLC-PDA) coupled with positive ion electro-spray mass spectrometry. Two betacyanins and two betaxanthins were identified in aqueous methanolic extract of flower, stem and leaf. Betanin, isobetanin, immonium conjugates of betalamic acid with dopamine and tyrosine were elucidated. The total betalain content was estimated by photometric analysis. In vitro antioxidant activity for the betalain extract determined by various methods revealed potent scavenging ability. The current work may possibly be considered beneficial in utilisation of the plant T. triangulare as a natural colourant in food and beverage industries. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Antioxidant; Betalains; HPLC-MS; Portulacaceae; Waterleaf

Characterization of a chemostable serine alkaline protease from Periplaneta americana - Sanatan, Prashant T.; Lomate, Purushottam R.; Giri, Ashok P.; Hivrale, Vandana K. (BMC Biochemistry, 2013)
Background: Proteases are important enzymes involved in numerous essential physiological processes and hold a strong potential for industrial applications. The proteolytic activity of insects' gut is endowed by many isoforms with diverse properties and specificities. Thus, insect proteases can act as a tool in industrial processes. Results: In the present study, purification and properties of a serine alkaline protease from Periplaneta americana and its potential application as an additive in various bio-formulations are reported. The enzyme was purified near to homogeneity by using acetone precipitation and Sephadex G-100 gel filtration chromatography. Enzyme activity was increased up to 4.2 fold after gel filtration chromatography. The purified enzyme appeared as single protein-band with a molecular mass of similar to 27.8 kDa in SDS-PAGE. The optimum pH and temperature for the proteolytic activity for purified protein were found around pH 8.0 and 60 degrees C respectively. Complete inhibition of the purified enzyme by phenylmethylsulfonyl fluoride confirmed that the protease was of serine-type. The purified enzyme revealed high stability and compatibility towards detergents, oxidizing, reducing, and bleaching agents. In addition, enzyme also showed stability towards organic solvents and commercial detergents. Conclusion: Several important properties of a serine protease from P. Americana were revealed. Moreover, insects can serve as excellent and alternative source of industrially important proteases with unique properties, which can be utilized as additives in detergents, stain removers and other bio-formulations. Properties of the P. americana protease accounted in the present investigation can be exploited further in various industrial processes. As an industrial prospective, identification of enzymes with varying essential properties from different insect species might be good approach and bioresource.
Keywords: Chemostability; Industrial catalyst; Insect proteases; Periplaneta americana; Serine alkaline protease

Characterization of conformation and interaction of gene delivery vector polyethylenimine with phospholipid bilayer at different protonation state - Choudhury, Chandan Kumar; Kumar, Abhinaw; Roy, Sudip (Biomacromolecules, 2013)
Polyethylenimine (PEI) is a pH sensitive polymer possessing stretched and coiled conformation at low and high pH, respectively. It is an efficient gene delivery agent. Thus, the interaction of PEI with the biomembrane is very crucial to understand the gene delivery mechanism. In this report, we have investigated the structural properties of PEI and bilayer due to the interaction of PEI with lipid molecules. PEI has coil structure at high pH while at low pH it is elongated. The neutral PEI chain predominately settles itself at the bilayer water interface. We do not find any disruption or pore formation on the bilayer due to interaction of neutral PEI chain. PEI at low pH gets elongated due to electrostatic interaction between charges of the protonated sites. This protonated PEI chain interacts with bilayer membrane, which leads to formation of water/ion channel through the membrane. We have analyzed the structure of the channel and water dynamics along the channel.

Characterization of the structures and dynamics of phosphoric acid doped benzimidazole mixtures: a molecular dynamics study - More, Minal; Pahari, Swagata; Roy, Sudip; Venkatnathan, Arun (Journal of Molecular Modeling, 2013)
Benzimidazole-based polymer membranes like poly(2,5-benzimidazole) (ABPBI) doped with phosphoric acid (PA) are electrolytes that exhibit high proton conductivity in fuel cells at elevated temperatures. The benzimidazole (BI) moiety is an important constituent of these membranes, so the present work was performed in order to achieve a molecular understanding of the BI-PA interactions in the presence of varying levels of the PA dopant, using classical molecular dynamics (MD) simulations. The various hydrogen-bonding interactions, as characterized based on structural properties and hydrogen-bond lifetime calculations, show that both BI and PA molecules exhibit dual proton-acceptor/donor functionality. An examination of diffusion coefficients showed that the diffusion of BI decreases with increasing PA uptake, whereas the diffusion of PA slightly increases. The hydrogen-bond lifetime calculations pointed to the existence of competitive hydrogen bonding between various sites in BI and PA.
Keywords: Diffusion coefficient; Hydrogen bond; molecular dynamics; Radial distribution functions

Characterization of three novel isoprenyl diphosphate synthases from the terpenoid rich mango fruit - Kulkarni, Ram; Pandit, Sagar; Chidley, Hemangi G.; Nagel, Raimund; Schmidt, Axel; Gershenzon, Jonathan; Pujari, Keshav; Giri, Ashok P.; Gupta, Vidya (Plant Physiology and Biochemistry, 2013)
Mango (cv. Alphonso) is popular due to its highly attractive, terpenoid-rich flavor. Although Alphonso is clonally propagated, its fruit-flavor composition varies when plants are grown in different geo-climatic zones. Isoprenyl diphosphate synthases catalyze important branch-point reactions in terpenoid biosynthesis, providing precursors for common terpenoids such as volatile terpenes, sterols and carotenoids. Two geranyl diphosphate synthases and a farnesyl diphosphate synthase were isolated from Alphonso fruits, cloned for recombinant expression and found to produce the respective products. Although, one of the geranyl diphosphate synthases showed high sequence similarity to the geranylgeranyl diphosphate synthases, it did not exhibit geranylgeranyl diphosphate synthesizing activity. When modeled, this geranyl diphosphate synthase and farnesyl diphosphate synthase structures were found to be homologous with the reference structures, having all the catalytic side chains appropriately oriented. The optimum temperature for both the geranyl diphosphate synthases was 40 degrees C and that for farnesyl diphosphate synthase was 25 degrees C. This finding correlated well with the dominance of monoterpenes in comparison to sesquiterpenes in the fruits of Alphonso mango in which the mesocarp temperature is higher during ripening than development. The absence of activity of these enzymes with the divalent metal ion other than Mg2+ indicated their adaptation to the Mg2+ rich mesocarp. The typical expression pattern of these genes through the ripening stages of fruits from different cultivation localities depicting the highest transcript levels of these genes in the stage preceding the maximum terpene accumulation indicated the involvement of these genes in the biosynthesis of volatile terpenes. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Alphonso; Flavor variation; Fruit; Isoprenyl diphosphate synthase; Mangifera indica; Terpene volatiles

Charge storage and electron transport properties of gold nanoparticles decorating a urethane-methacrylate comb polymer network - Patil, Sumati; Datar, Suwarna; Rekha, N.; Asha, S. K.; Dharmadhikari, C. V. (Nanoscale, 2013)
We propose enhanced charge storage capacity of nanoparticles based polymer films. A flat band voltage window varying from 5-7 V is obtained leading to a trapped charge density of the order of 10(13) cm(-2). These results vary for two distinct morphologies obtained due to decoration of a urethane-methacrylate comb polymer (UMCP) network by gold nanoparticles (AuNPs). Films have been further investigated for morphology, optical, charge storage, and electron transport properties using techniques like scanning electron microscopy (SEM), atomic force microscopy (AFM), absorption spectroscopy (UV-Vis), scanning tunneling microscopy/spectroscopy (STM/STS) and capacitance versus voltage (C-V) measurements. SEM and AFM confirm either the deposition of AuNPs inside the UMCP network or the formation of ring like structures depending on the deposition sequence. STS measurements performed on both films are compared with bare UMCP and AuNPs films. Current versus voltage (I-V) characteristics so obtained are discussed in the light of electron transport mechanisms in such materials.

Chemical looping reforming of ethanol for syngas generation: a theoretical investigation - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Bharadwaj, K. V. (International Journal of Energy Research, 2013)
Chemical looping reforming (CLR) is a novel technology that can be used for reforming of cheaply available abundant biofuel like ethanol for the production of hydrogen/syngas for fuel cells. A systematic thermodynamic study for the CLR process using selected oxygen carriers was done to analyze the products and energy requirements of the CLR process in the temperature range of 5001200 degrees C at 1bar pressure for ethanol. The results showed favorable conditions for syngas manufacture from this process. Fe2O3 was found to be the best performing oxygen carrier followed by calcium and sodium sulfates, while Mn oxides were the least preferred oxygen carriers for CLR of ethanol process. The optimum process temperature was found to be 1000 degrees C. The actual CLR-ethanol process shows exothermicity against the theoretical endothermic partial oxidation of ethanol. The results obtained in this theoretical study can pave the way for experimental programs for syngas generation for SOFC-type fuel cells. Similar studies can be undertaken for other fuels for fuel processor development by CLR process. Copyright (c) 2012 John Wiley & Sons, Ltd.
Keywords: chemical looping reforming; ethanol to syngas; Fuel Processor; Gibbs minimization; oxygen carriers

Chemical modification of ethyl cellulose-based highly porous membrane for the purification of immunoglobulin G - Adikane, H. V.; Iyer, G. J. (Applied Biochemistry and Biotechnology, 2013)
The chemical modification of developed ethyl cellulose-based membrane was carried out to make it suitable for bioseparation. The different reagents were used for the modification of membrane to couple protein A (PA) to study the purification of immunoglobulin G (IgG) from blood. The chemical modification was carried out using relatively simple and mild reaction conditions. The attenuated total reflectance Fourier transform infrared analysis of chemically modified membrane showed new peak at 1,596.06 and 1,716.49 cm(-1). The scanning electron microscopy of PA-coupled membrane, which was used for IgG purification showed open pores and 950 +/- 21.5 LMH (L m(-2) h(-1)) operational flux at 0.5-bar out pressure. The flux of unmodified membrane was 1,746 +/- 18.5 LMH at 0.5-bar out pressure. The equilibrium adsorption concentration (318.5 +/- 5.9 mu g cm(-2)) was obtained at 3 h. The adsorption character of PA-coupled membrane was consistent with the Langmuir adsorption model and the non-specific binding was 67.08 +/- 1.3 mu g cm(-2). The sodium dodecyl sulfate polyacrylamide gel electrophoresis analysis showed similar purification pattern for purified IgG from human serum and commercial preparation of IgG. All the results have suggested a high potential of PA-coupled ethyl cellulose-based membrane for large-scale purification of IgG.
Keywords: Affinity bioseparation; Ethyl cellulose; Glutaraldehyde; Immunoglobulin G; Polyethylenimine; Protein A

Chemically conjugated sophorolipids on CdTe QDs: a biocompatible photoluminescence nanocomposite for theranostic applications - Singh, Pooja; Joshi, Kasturi; Guin, Debanjan; Prabhune, Asmita (RSC Advances, 2013)
Functional nontoxic cadmium telluride (CdTe) quantum dots (QDs) have been synthesized using a natural functional glycolipid belonging to the family of sophorolipids (SL) as a surface-modifying agent. These SLs with open acidic form are highly suitable for QDs stabilization, are readily obtained by a fermentation process of the yeast Candida bombicola (polymorph Starmerella bombicola) in large amounts. In this work chemically stable, water soluble, and photoluminescent CdTe QDs were successfully conjugated to sophorolipids via a cross-linking reaction. The formation of SLs conjugated CdTe QDs was confirmed using different analytical techniques X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), Electron Diffraction (ED), Atomic Force Microscopy (AFM), Dynamic Light Scattering (DLS), and Photoluminescence (PL). It was shown that after being conjugated with SL the SL-CdTe QDs becomes biocompatible, still maintaining its water solubility and photoluminescence properties. The final SL coated photoluminescent CdTe QDs represent interesting biocompatible materials potentially useful for biomedical applications.

Chemically stable multilayered covalent organic nanosheets from covalent organic frameworks via mechanical delamination - Chandra, Suman; Kandambeth, Sharath; Biswal, Bishnu P.; Lukose, Binit; Kunjir, Shrikant M.; Chaudhary, Minakshi V.; BabaRao, Ravichandar; Heine, Thomas; Banerjee, Rahul (Journal of the American Chemical Society, 2013)
A series of five thermally and chemically stable functionalized covalent organic frameworks (COFs), namely, TpPa-NO2, TpPa-F-4, TpBD-(NO2)(2), TpBD-Me-2, and TpBD-(OMe)(2) were synthesized by employing the solvothermal aldehyde-amine Schiff base condensation reaction. In order to complete the series, previously reported TpPa-1, TpPa-2, and TpBD have also been synthesized, and altogether, eight COFs were fully characterized through powder X-ray diffraction (PXRD), Fourier transform IR (FT-IR) spectroscopy, C-13 solid-state NMR spectroscopy, and thermogravimetric analysis. These COFs are crystalline, permanently porous, and stable in boiling water, acid (9 N HCl), and base (3 N NaOH). The. synthesized COFs (all eight) were successfully delaminated using a simple, safe, and environmentally friendly mechanical grinding route to transform into covalent organic nanosheets (CONs) and were well characterized via transmission electron microscopy and atomic force microscopy. Further PXRD and FT-IR analyses confirm that these CONs retain their structural integrity throughout the delamination process and also remain stable in aqueous, acidic, and basic media like the parent COFs. These exfoliated CONs have graphene-like layered morphology (delaminated layers), unlike the COFs from which they were synthesized.

Chemistry in India: unlocking the potential - Arunan, Elangannan; Brakaspathy, Ramasamy; Desiraju, Gautam R.; Sivaram, Swaminathan (Angewandte Chemie-International Edition, 2013)

Chiral (VO)-O-IV-Sal-Indanol complex over modified SBA-15: an efficient, reusable enantioselective catalyst for asymmetric sulfoxidation reaction - Lazar, Anish; Sharma, Priti; Singh, A. P. (Microporous and Mesoporous Materials, 2013)
A reusable, mesoporous, heterogeneous vanadium complex, (VO)-O-IV-Sal-Ind-SBA-15 has been synthesized first time from (1R,2S)-(+)-Cis-1-amino-2-indanol for enantioselective sulfoxidation reaction. The physico-chemical properties of the functionalized catalyst were analyzed by a series of characterization techniques like XRD, N-2 sorption measurement isotherm, TEM, FT-IR, XPS, EPR, DRS UV-Visible, ICP-OES and solid & liquid state C-13, Si-29 and V-51 NMR spectroscopy. Powder X-ray diffraction patterns, TEM and N-2 physisorption analysis confirmed the retention of mesoporous structure after various modifications. Solid-state NMR (C-13 CP-MAS NMR, Si-29 MAS NMR) and FT-IR analysis certified the integrity of organo-catalyst residing inside the pore channels of the mesoporous support. Further, XPS, EPR, V-51 NMR and DRS UV-Visible analyses help to find out the oxidation state and coordination environment of vanadium in (VO)-O-IV-Sal-Ind-SBA-15. Catalytic evaluation in asymmetric sulfoxidation reaction of sulfides indicated that VOIV-Sal-Ind-SBA-15 exhibited higher catalytic activity, stability, reusability and comparable enantioselectivity than SBA-15, PrNH2-SBA-15, neat (VO)-O-IV-Sal-Indanol complex and without catalyst. The effect of different catalysts, temperature, solvents and substrates on sulfoxidation reaction were examined in order to optimize the conversion and enantioselectivity of thioanisoles to sulfoxides. Crown Copyright (C) 2012 Published by Elsevier Inc. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric sulfoxidation; Heterogeneous vanadium complex; Mesoporous; Thioanisole

Chitin synthase inhibitors as antifungal agents - Chaudhary, Preeti M.; Tupe, Santosh G.; Deshpande, Mukund V. (Mini-Reviews in Medicinal Chemistry, 2013)
Increased risk of fungal diseases in immunocompromised patients, emerging fungal pathogens, limited repertoire of antifungal drugs and resistance development against the drugs demands for development of new and effective antifungal agents. With greater knowledge of fungal metabolism efforts are being made to inhibit specific enzymes involved in different biochemical pathways for the development of antifungal drugs. Chitin synthase is one such promising target as it is absent in plants and mammals. Nikkomycin Z, a chitin synthase inhibitor is under clinical development. Chitin synthesis in fungi, chitin synthase as a target for antifungal agent development, different chitin synthase inhibitors isolated from natural sources, randomly synthesized and modified from nikkomycin and polyoxin are discussed in this review.
Keywords: Antifungal agents; Chitin synthase; Chitin synthase inhibitors; Nikkomycin; Peptidyl nucleoside antibiotics; Polyoxin

Chitinolytic enzymes: an appraisal as a product of commercial potential - Chavan, S. B.; Deshpande, Mukund V. (Biotechnology Progress, 2013)
Chitin, its deacetylated form, chitosan and chitinolytic enzymes viz. endo-chitinase, N-acetylglucosaminidase, chitosanase, chitin deacetylase (CDA) are gaining importance for their biotechnological applications. Presently, chitin degrading enzymes constitute high-cost low-volume products in human health care and associated research. Indeed chitinases and CDA-chitosanase complex possesss tremendous potential in agriculture to control plant pathogenic fungi and insects. The success in exploring chitinases especially for agriculture, i.e. as a high-volume low-cost product, depends on the availability of highly active preparations with a reasonable cost. Therefore, a reconsideration in terms of understanding the roles of chitinolytic enzymes in applications, e.g. host-pathogen interaction for biocontrol, different mechanisms of chitin degradation, and identification of new enzymes with varying specificities, may make them more useful in a variety of commercial processes in the near future. The possible issues and challenges encountered in the translation of proof of concept into a commercial product will be appraised in this review. (c) 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:833-846, 2013
Keywords: chitin deacetylase; chitinase; chitosanase; high-cost low-volume product; high-volume low-cost product

Cinnamate 4-hydroxylase (C4H) genes from leucaena leucocephala: a pulp yielding leguminous tree - Kumar, Santosh; Omer, Sumita; Patel, Krunal; Khan, Bashir Mohammad (Molecular Biology Reports, 2013)
Leucaena leucocephala is a leguminous tree species accounting for one-fourth of raw material supplied to paper and pulp industry in India. Cinnamate 4-Hydroxylase (C4H, EC 1.14.13.11) is the second gene of phenylpropanoid pathway and a member of cytochrome P450 family. There is currently intense interest to alter or modify lignin content of L. leucocephala. Three highly similar C4H alleles of LlC4H1 gene were isolated and characterized. The alleles shared more than 98 % sequence identity at amino acid level to each other. Binding of partial promoter of another C4H gene LlC4H2, to varying amounts of crude nuclear proteins isolated from leaf and stem tissues of L. leucocephala formed two loose and one strong complex, respectively, suggesting that the abundance of proteins that bind with the partial C4H promoter is higher in stem tissue than in leaf tissue. Quantitative Real Time PCR study suggested that among tissues of same age, root tissues had highest level of C4H transcripts. Maximum transcript level was observed in 30 day old root tissue. Among the tissues investigated, C4H activity was highest in 60 day old root tissues. Tissue specific quantitative comparison of lignin from developing seedling stage to 1 year old tree stage indicated that Klason lignin increased in tissues with age.
Keywords: Cinnamate 4-Hydroxylase (C4H); Leucaena leucocephala; lignin; Phenylpropanoid

Cinnamic acid derivatives via heck reaction in an aqueous-biphasic catalytic system with easy catalyst-product separation - Jagtap, Sangeeta Vijay; Deshpande, R. M. (Asian Journal of Chemistry, 2013)
A true biphasic [aqueous-organic] system for the coupling of water soluble sodium acrylate with different aryl halides for the synthesis of cinnamic acid derivatives has been developed, employing palladium catalysts that is soluble in organic phase. Amongst them, palladacycle was found to be stable in presence of water and could be recycled for four times with no loss in the activity. Such a system facilitates easy recycle of catalyst and also the removal of the salts from the catalyst phase, ensuring high activity with respect to cumulative turn over number (TON) and turn over frequency (TOF). The reaction was facilitated by organic as well as inorganic bases. The efficiency of the catalyst, role of organic/inorganic bases on the activity is reported.
Keywords: Biphasic catalysis; Heck reaction; Palladacycle; Separation

Clay entrapped Cu(OH)(x) as an efficient heterogeneous catalyst for ipso-hydroxylation of arylboronic acids - Dar, Bashir Ahmad; Bhatti, Prince; Singh, A. P.; Lazar, Anish; Sharma, Parduman R.; Sharma, Meena; Singh, Baldev (Applied Catalysis A-General, 2013)
A remarkably active, selective and stable montmorilonite-KSF entrapped Cu(OH)(x) catalyst, has been prepared for the ipso-hydroxylation of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst shows excellent reusability without leaching and any significant loss in catalytic activity. The catalyst was characterized using, XRD, SEM, TPR, IR, XPS and BET surface area measurement techniques. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: clay; Copper; heterogeneous catalysis; Phenols; Water chemistry

Cleavable and removable polymer thermosets for organic field effect transistor packaging - Arulkashmir, Arulraj; Bhosale, Manik E.; Krishnamoorthy, Kothandam (RSC Advances, 2013)
Recent years have witnessed tremendous progress in the design and synthesis of electroactive materials for the fabrication of organic electronic devices. However, very little research effort has been devoted to developing organic packaging materials, which are crucial for the efficient functioning of the devices. Polymer thermosets (PTs) are extensively used for the packaging of microelectronic and optoelectronic devices. Although PTs are effective in providing mechanical stability and environmental protection to devices, the removal of PTs without destroying the underlying surface is cumbersome. Facile removal of PTs is essential to reuse the expensive substrates. Herein, we report the preparation of a thermoset using an aliphatic disulfide containing cross-linker, cystamine. By varying the cross-linker concentration, the mechanical property of the thermoset was varied from ductile to brittle. The ductile thermoset was coated on metal, semiconductor and flexible substrates. The thermosets were then cleaved using a biomolecule in neutral pH. We have demonstrated that the cleavage and removal of thermosets don't affect the surface properties of the underlying substrates. Furthermore, the thermosets were coated on top of organic field effect transistors to provide environmental protection. The thermoset coated devices showed a charge carrier mobility of 5.3 x 10(-3) cm(2) V-1 s(-1). Then, the thermoset was cleaved and removed, and the substrate was reused for the fabrication of organic field effect transistors with unchanged device efficiencies.

Cloning and sequence analysis of three variants of the gene encoding alkaline xylanase C from the alkaliphilic bacillus sp (NCL 87-6-10) - Sharma, Poonam; Rele, Meenakshi V.; Kumar, Lalitha Sunil (Biochemical Genetics, 2013)
Alkaline xylanase C from the alkaliphilic Bacillus sp. (NCL 87-6-10) has a low molecular weight and alkaline pI and is cellulase-free, properties compatible with its use in the prebleaching of pulp. We report here the cloning and sequence analysis of three variants of the gene encoding xylanase C; xyl C1, xyl C2, and xyl C3. In phylogenetic analysis, the three xylanase C variants clustered into a single group along with other reported alkaline xylanases. Residues contributing to the alkaline pH were present in all three variants. DNA and protein sequence comparison of these variants with other reported alkaline xylanases revealed silent mutations, some of which are due to codon preference in the respective organisms. The recombinant Xyl C1 that was successfully expressed in E. coli BL21 (DE3) had properties similar to the native enzyme.
Keywords: Alkaline xylanase C; Alkaliphilic Bacillus sp (NCL 87-6-10); Cloning; E. coli BL21 (DE3) expression; Sequence analysis

Cloning, overexpression, crystallization and preliminary X-ray crystallographic analysis of a slow-processing mutant of penicillin G acylase from Kluyvera citrophila - Varshney, Nishant Kumar; Ramasamy, Sureshkumar; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2013)
{Kluyvera citrophila penicillin G acylase (KcPGA) has recently attracted increased attention relative to the well studied and commonly used Escherichia coli PGA (EcPGA) because KcPGA is more resilient to harsh conditions and is easier to immobilize for the industrial hydrolysis of natural penicillins to generate the 6-aminopenicillin (6-APA) nucleus, which is the starting material for semi-synthetic antibiotic production. Like other penicillin acylases, KcPGA is synthesized as a single-chain inactive pro-PGA, which upon autocatalytic processing becomes an active heterodimer of alpha and beta chains. Here, the cloning of the pac gene encoding KcPGA and the preparation of a slow-processing mutant precursor are reported. The purification, crystallization and preliminary X-ray analysis of crystals of this precursor protein are described. The protein crystallized in two different space groups, P1, with unit-cell parameters a = 54.0

CN? specific turn-on phosphorescent probe with probable application for enzymatic assay and as an imaging reagent - Reddy, Upendar G.; Das, Priyadip; Saha, Sukdeb; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2013)
A new “turn-on” luminescence probe for imaging the uptake of 0.2 ppm inorganic CN− in live HeLa cells as well as for probing the CN− generation through an enzymatic process in a virtual aqueous medium at appropriate pH.

Cobalt-catalyzed C–H bond functionalizations with aryl and alkyl chlorides - Punji, Benudhar; Song, Weifeng; Shevchenko, Grigory A.; Ackermann, Lutz (Chemistry - A European Journal, 2013)
Inexpensive cobalt catalysts derived from N-heterocylic carbenes (NHC) allowed efficient catalytic C[BOND]H bond arylations on heteroaryl-substituted arenes with widely available aryl chlorides, which set the stage for the preparation of sterically hindered tri-ortho-substituted biaryls. Likewise, challenging direct alkylations with β-hydrogen-containing primary and even secondary alkyl chlorides proceeded on pyridyl- and pyrimidyl-substituted arenes and heteroarenes. The cobalt-catalyzed C[BOND]H bond functionalizations occurred efficiently at ambient reaction temperature with excellent levels of site-selectivities and ample scope. Mechanistic studies highlighted that electron-deficient aryl chlorides reacted preferentially, while the arenes kinetic C[BOND]H bond acidity was found to largely govern their reactivity.

Combinatorial approach of statistical optimization and mutagenesis for improved production of acidic phytase by Aspergillus niger NCIM 563 under submerged fermentation condition - Bhavsar, Kavita P.; Gujar, P.; Shah, P.; Kumar, V. Ravi; Khire, Jayant Malhar (Applied Microbiology and Biotechnology, 2013)
Combination of statistical optimization and mutagenesis to isolate hypersecretory strains is studied to maximize phytase production from Aspergillus niger NCIM 563 under submerged fermentation. The overall results obtained show a remarkable 5.98-fold improvement in phytase production rates when compared to that using basal medium. Optimization of culture conditions from parent strain is studied first by the Plackett-Burman technique to evaluate the effects of 11 variables for phytase production. The results showed that glucose, MgSO4, KCl, incubation period, and MnSO4 are the most significant variables affecting enzyme production. Further optimization in these variables, using a central composite design technique, resulted in 3.74-fold increase in the yield of phytase production to 254,500 U/l when compared with the activity observed with basal media (68,000 U/l) in shake flask. Our experiments show that the phytase from A. niger NCIM 563 exhibits desirable activity in simulated gastric fluid conditions with low pH and also improved thermostability when compared to commercial phytase. The improved yield demonstrates the potential applicability of phytase enzyme as a source of phytase supplement for phosphorus nutrition and environmental protection in animal feed industry. Physical and chemical mutagenesis experiments were carried out in parallel to isolate hypersecretory mutants that could possibly further enhance the enzyme production. Using optimized media conditions of the parent strain, our results show that mutant strain A. niger NCIM 1359 increased the phytase activity by another 1.6-fold to 407,200 U/l.
Keywords: Animal feed; Aspergillus niger; Mutagenesis; Phytase; Statistical optimization

Commercializing technologies from universities and research institutes in India: some insights from the US experience - Nandagopal, Magesh (Current Science, 2013)
Translating research done in universities and research institutes to products and services in the market takes considerable and sustained effort. Dedicated technology transfer offices (TTOs) and supporting systems are required to achieve this. Starting from attracting the right people, devising flexible models to work with varioius commercial partners (like large and small companies, startups), bringing in external funding to further the technology goals, TTOs can perform a crucial role in commercializing academic technologies. Various strategies followed by TTOs in the US universities are analysed and suggestions to improve the technology transfer process in the Indian context are presented.
Keywords: Commercializing technologies; research institutes; technology transfer offices; universities

Comparison of methods for identifying periodically varying genes - Vijayan, V.; Deshpande, P.; Gadgil, Chetan J.; Gadgil, Mugdha (International Journal of Bioinformatics Research and Applications, 2013)

Compensatory proteolytic responses to dietary proteinase inhibitors from Albizia lebbeck seeds in the helicoverpa armigera larvae - Hivrale, Vandana K.; Lomate, Purushottam R.; Basaiyye, Shriniwas S.; Kalve, Neeta D. (Arthropod-Plant Interactions, 2013)
Plant proteinase inhibitors (PIs) have been shown to reduce the growth rates in larvae of numerous insect species. On the other hand, insects can also regulate their proteinases against plant PIs. In the present study, we report the compensatory activities of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) gut proteinases against the PIs of Albizia lebbeck seeds. Total of ten proteinase inhibitor bands were detected in the seed extract of A. lebbeck. Bioassays were conducted by feeding H. armigera larvae on diet containing partially purified PIs from A. lebbeck seeds. Results show that larval growth and survival was significantly reduced by A. lebbeck PIs. We found that higher activity H. armigera gut proteinase (HGP) isoforms observed in the midgut of control larvae were inhibited in the midgut of larvae fed on test diet. Some HGP isoforms were induced in the larvae fed on PI containing test diet; however, these isoforms showed lower activity in the larvae fed on control diet. Aminopeptidase activities were significantly increased in the midgut of larvae fed on test diet. A population of susceptible and resistant enzymes was observed in the midgut of H. armigera, when fed on diet containing PIs from A. lebbeck seeds. Our initial observations indicate that H. armigera can regulate its digestive proteinase activity against non-host plant PIs, too. It is important to study the exact biochemical and molecular mechanisms underlying this phenomenon in order to develop PI-based insect control strategies.
Keywords: Albizia lebbeck; Helicoverpa armigera; Midgut proteinases; Proteinase inhibitors; regulation

Competition between adsorption and intrinsic collapse of full-length a beta 1-42 on the surface of a single-walled carbon nanotube: insights from molecular dynamics simulations - Sengupta, Neelanjana (Biophysical Journal, 2013)

Complementation of intramolecular interactions for structural-functional stability of plant serine proteinase inhibitors - Joshi, Rakesh S.; Mishra, Manasi; Suresh, C. G.; Gupta, Vidya S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2013)
Background: Plant protease inhibitors (PIs) constitute a diverse group of proteins capable of inhibiting proteases. Among Pls, serine Pls (SPIs) display stability and conformational restrictions of the reactive site loop by virtue of their compact size, and by the presence of disulfide bonds, hydrogen bonds, and other weak interactions. Scope of review: The significance of various intramolecular interactions contributing to protein folding mechanism and their role in overall stability and activity of SPIs is discussed here. Furthermore, we have reviewed the effect of variation or manipulation of these interactions on the activity/stability of SPIs. Major conclusions: The selective gain or loss of disulfide bond(s) in SPIs can be associated with their functional differentiation, which is likely to be compensated by non-covalent interactions (hydrogen bonding or electrostatic interactions). Thus, these intramolecular interactions are collectively responsible for the functional activity of SPIs, through the maintenance of scaffold framework, conformational rigidity and shape complementarities of reactive site loop. General significance: Structural insight of these interactions will provide an in-depth understanding of kinetic and thermodynamic parameters involved in the folding and stability mechanisms of SPIs. These features can be explored for engineering canonical SPIs for optimizing their overall stability and functionality for various applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Disulfide bond; hydrogen bonding; Intramolecular weak interaction; Protease; Reactive site loop; Serine proteinase inhibitor

Comprehensive study on mutual interplay of multiple V-shaped ligands on the helical nature of a series of coordination polymers and their properties - Goswami, Arijit; Bala, Sukhen; Pachfule, Pradip; Mondal, Raju (Crystal Growth & Design, 2013)
{V-shaped ligands are commonly used for helical coordination polymer synthesis. However, employment of multiple V-shaped ligands does not always lead to a helical network. The mutual interplay of two V-shaped ligands, which is neither easily predictable nor well documented, plays a major role directing the self-assembly of the resultant network. We report here the construction of a series of novel coordination polymers {[Ni(OBA)(H2MDP)(H2O)]center dot(DMF)(3)}(n) (1),{[Ni(FBA)(H2MDP)]center dot(H2O)(3)center dot(DMF)\

Concise synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate - Ramalingam, S.; Bhise, Ankushkumar D.; Show, Krishanu; Kumar, Pradeep (Arkivoc, 2013)
An efficient synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate 1, a common intermediate for various polyhydroxylated piperidines is reported in six steps with 32% overall yield starting from Garner's aldehyde. The key steps include the diastereoselective nucleophilic addition and intramolecular cyclization. (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate is a common precursor for the synthesis of 1-deoxy-L-mannojirimycin, 1-deoxy-L-idonojirimycin, L-fagomycin and related analogues.
Keywords: cyclization; Garner's aldehyde; nucleophilic addition; polyhydroxy piperidines

Contact potential induced enhancement of magnetization in polyaniline coated nanomagnetic iron oxides by plasma polymerization - Sethulakshmi, N.; Sooraj, V.; Sajeev, U. S.; Nair, Swapna S.; Narayanan, T. N.; Joy, Lija K.; Joy, Pattayil Alias; Ajayan, Pulickel M.; Anantharaman, Maliemadom R. (Applied Physics Letters, 2013)
The present work derives motivation from the so called surface/interfacial magnetism in core shell structures and commercial samples of Fe3O4 and gamma Fe2O3 with sizes ranging from 20 to 30 nm were coated with polyaniline using plasma polymerization and studied. The High Resolution Transmission Electron Microscopy images indicate a core shell structure after polyaniline coating and exhibited an increase in saturation magnetization by 2 emu/g. For confirmation, plasma polymerization was performed on maghemite nanoparticles which also exhibited an increase in saturation magnetization. This enhanced magnetization is rather surprising and the reason is found to be an interfacial phenomenon resulting from a contact potential. (C) 2013 AIP Publishing LLC.

Continuous flow multipoint dosing approach for selectivity engineering in sulfoxidation - Kulkarni, A. A.; Nivangune, N. T.; Joshi, Rohini R.; Joshi, Ramesh A. (Organic Process Research & Development, 2013)
A continuous synthesis approach with multipoint dosing of one of the reagents is demonstrated for the synthesis of sulfoxide compounds such as proton pump inhibitors. Use of multipoint dosing of the oxidizing agent helped to minimize the possibility of over-oxidation leading to sulfone. Different oxidizing agents were used, and the effect of various parameters (viz. mole ratio of sulfide to oxidizing agent, temperature, residence time, concentration of oxidizing agent, etc.) on the yield of the desired sulfoxide compound was studied. Single-point and multipoint dosing approaches of the oxidizing agent were used for the most promising set of parameters. The performance was compared in terms of conversion of sulfide and the selectivity of the desired sulfoxide. Numbering up approach was used to produce the sulfoxide in a relatively large quantity at laboratory scale with complete conversion and over 99% selectivity for the sulfoxide.

Controlled synthesis of a catalytically active hybrid metal-oxide incorporated zeolitic imidazolate framework (MOZIF) - Dey, Chandan; Banerjee, Rahul (Chemical Communications, 2013)
A rare hybrid Metal-Oxide incorporated Zeolitic Imidazolate Framework, MOZIF-1, containing tetrahedral Zn(II) and Mo(VI) centres has been synthesized. MOZIF-1 can degrade methyl orange and orange II dyes under visible light. Na-3[PMo12O40] is the source of Mo(VI) in MOZIF-1.

Controlled synthesis of aligned Bi2S3 nanowires, sharp apex nanowires and nanobelts with its morphology dependent field emission investigations - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Pandiraj, S.; Khare, Ruchita T.; More, Mahendra A. (Crystengcomm, 2013)
Well-aligned ultra-long Bi2S3 nanowire arrays with three kinds of apex morphology - abruptly sharpened apex, thin belt and flat - have been systematically fabricated on tungsten (W) foil by a facile hydrothermal method. The structural and morphological studies reveal formation of distinct tip morphologies, possessing high aspect ratio, single crystalline nature and growth along the orthorhombic [001] axis. A plausible growth mechanism has been proposed on the basis of observed experimental results. The field emission properties of Bi2S3 nanowires and sharp apex Bi2S3 nanowires are investigated. From the field emission studies, the values of the turn-on field, required to draw emission current density of similar to 0.1 mu A cm(-2), are observed to be similar to 2.01 and 1.21 V mu m(-1) for nanowires and sharp apex nanowires, respectively. Furthermore, ultra-long Bi2S3 nanowires are also grown on the W microtip (brush-like) from which very high emission current density similar to 11 mA cm(-2) has been drawn. These results are helpful for the design, fabrication and optimization of integrated field emitters using 1D nanostructures as cold cathode material.

Copolymerization of aleuritic acid with l-lactic acid and study the aggregation behavior in different solvents - Pandey, Asutosh K.; Garnaik, Baijayantimala (International Journal of Research in Pharmacy and Chemistry, 2013)
In this present work, we highlight the copolymerization of L-lactic acid (L-LA with protected aleuritic acid in presence of Lewis acid catalyst using dehyropolycondensation method. The resulted copolymers are pliable, soft, waxy or even viscous liquid copolymers influenced by the aleuritic acid content. The purpose of this study is to investigate the physical properties. In addition, deprotected copolymers focus micelle-like aggregates in various organic solvents and mixed organic solvent at various proportions.

Copolymerization of ethylene with unsaturated alcohols and methylmethacrylate using a silylated alpha-diimine nickel catalyst: molecular modeling and photodegradation studies - Matos, Ines; Fernandes, Susete N.; Liu, Hua-Rong; Tevtia, Amit K.; Singh, R. P.; Manda, Lemos; Lemos, Francisco; Marques, Maria M. (Journal of Applied Polymer Science, 2013)
In this article, the experimental results obtained in the copolymerization of ethylene with polar monomers using a silylated -diimine nickel catalyst are described and compared with those obtained with a non-silylate similar one. The results show that the introduction of a siliyl group in the para-position of the imine moiety turns the catalyst less sensitive toward polar functionalities. However, the reactivity observed in copolymerization reactions was found to be reduced both the global polymerization and incorporation rates. Molecular modeling calculation allowed us to understand both the preferred insertion mode and the intermediate product structures for E/MMA copolymerization. Photodegradation studies showed that the presence of polar groups in the copolymers increases their rate of oxidation and turn them more easily degradable. The stabilization performed by Tinuvin 770 showed that for long-exposure times, it is not very effective regardless it is only mixed or grafted to the copolymer. (c) 2012 Wiley Periodicals, Inc.
Keywords: ageing; copolymers; Degradation; grafting

Correlation between the variation in observed melting temperatures and structural motifs of the global minima of gallium clusters: an ab initio study - Susan, Anju; Kibey, Aniruddha; Kaware, Vaibhav; Joshi, Kavita (Journal of Chemical Physics, 2013)
We have investigated the correlation between the variation in the melting temperature and the growth pattern of small positively charged gallium clusters. Significant shift in the melting temperatures was observed for a change of only few atoms in the size of the cluster. Clusters with size between 31-42 atoms melt between 500-600 K whereas those with 46-48 atoms melt around 800 K. Density functional theory based first principles simulations have been carried out on Ga-n(+) clusters with n = 31, ... , 48. At least 150 geometry optimizations have been performed towards the search for the global minima for each size resulting in about 3000 geometry optimizations. For gallium clusters in this size range, the emergence of spherical structures as the ground state leads to higher melting temperature. The well-separated core and surface shells in these clusters delay isomerization, which results in the enhanced stability of these clusters at elevated temperatures. The observed variation in the melting temperature of these clusters therefore has a structural origin. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4772470]

Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Critical roles of key domains in complete adsorption of a beta peptide on single-walled carbon nanotubes: insights with point mutations and MD simulations - Jana, Asis K.; Jose, Jaya C.; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2013)
Owing to the influence of nanomaterials on biomacromolecular behavior, their potential applications are rapidly gaining attention. Based on atomistic molecular dynamics simulation studies we have recently reported that the full-length A beta peptide, whose self-assembly is associated with Alzheimer's disease, adsorbs rapidly on single-walled carbon nanotubes, thereby losing its natural propensity to collapse. Here, we investigate the mechanistic overlap between the peptide's compactification and its adsorption, while decoupling the roles of hydrophobicity and aromaticity via point mutations. The collapse mechanism is correlated with interactions between the central hydrophobic core (HP1) and the peptide's C-terminal domain, which are almost exactly compensated by interactions arising from the nanotube after complete adsorption. Adsorption is initiated by HP1 and consolidated by strong interactions arising from the N-terminal domain. Altering the hydrophobicity, but not the aromatic character, of the central residue in HP1 decreases the collapse probability. On the other hand, the adsorption propensity is dramatically reduced when either the hydrophobicity or the aromatic character in HP1 is compromised. The hydrophobicity of HP1 is responsible for dewetting transitions that facilitate its initial interactions with the nanotube, which then lead to very favorable interactions with the nanotube.

Crystal structure and fluorescence analysis of alkaline thermostable xylanase from bacillus sp (NCL 87-6-10) - Satyanarayana, L.; Gaikwad, Sushama M.; Balkrishnan, H.; Suresh, C. G. (Protein and Peptide Letters, 2013)
Structural information deduced from the new crystal form of xylanase from Bacillus sp (NCL 87-6-10) (ATBXYL-C) helped us to identify the active site and interpret the stability of the enzyme. The analysis of the tetragonal crystal structure of ATBXYL-C with a bound and cleaved xylotriose revealed the two glutamic acid residues in the structure that could act as nucleophile (Glu94) and base (Glu184) in the enzyme activity and also the tryptophan residues interacting with the substrate. The cleavage of xylotriose in the crystal showed xylobiose to be the major product. Intrinsic fluorescence of the enzyme showed the presence of tryptophans in partially exposed to the solvent at the active site and surface tryptophans in electropositive environment. The titration experiments with xylobiose and xylotriose revealed slightly enhanced preference for longer chain X3 compared with X2. The crystal structure also account for some of the factors, such as increased number of ionic interactions and additional interactions at the N-terminus, which contributed to increased alkalophilicity and thermostability of the enzyme.
Keywords: active site residues; Alkaline thermophile Bacillus xylanase (ATBXYL-C); fluorescence studies; three-dimensional structure

Crystalline xylitol production by a novel yeast, pichia caribbica (HQ222812), and its application for quorum sensing inhibition in gram-negative marker strain chromobacterium violaceum CV026 - Mukherji, Ruchira; Joshi-Navare, Kasturi; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2013)
Xylitol, a sugar alcohol, is fast gaining ground over other artificial sugar substitutes owing to its advantageous properties. Xylitol is a safer alternative for diabetics because of insulin-independent metabolism. It has beneficial properties suitable to form an important part of odontological formulations. Conventional commercial production of xylitol involves harsh chemical method operating at high temperature and pressure. Thus, microbial production of xylitol is preferred over chemical method, and yeasts have been extensively exploited for this purpose. In the present manuscript, quantitative production of xylitol from d-xylose with the yield of 0.852 gm/gm and volumetric productivity of 1.83 gm/l/h in crystalline form, using novel yeast Pichia caribbica is reported. Also, a mild, safe procedure for product extraction is described. The ability of xylitol to act as a quorum sensing antagonist in gram-negative marker strain Chromobacterium violaceum CV026 has been demonstrated for the first time.
Keywords: Crystallization; CV026; Pichia caribbica; Quorum sensing antagonist; xylitol

Crystallisation of ferrous sulphate heptahydrate: experiments and modelling - Shaikh, Latif; Pandit, Aniruddha; Ranade, Vivek (Canadian Journal of Chemical Engineering, 2013)
Crystallisation is an industrially important unit operation for purifying and separating chemical mixtures. A generic crystallisation modelling framework has been implemented in the general process modelling system (gPROMS) software (of PSE, UK). This framework can be used to model the batch cooling crystallisation of ferrous sulphate heptahydrate (FSH). The parameter estimation and sensitivity of the predicted results with various numerical parameters was studied for batch crystalliser. An Excel front-end to the gPROMS model was developed to facilitate the interactive use of the model. (c) 2011 Canadian Society for Chemical Engineering
Keywords: batch crystallisation; ferrous sulphate heptahydrate; gPROMS; MSExcel-linking; parameter estimation

Crystallization: key thermodynamic, kinetic and hydrodynamic aspects - Vedantam, Sreepriya; Ranade, Vivek V. (Sadhana-Academy Proceedings in Engineering Sciences, 2013)
Crystallization is extensively used in different industrial applications, including the production of a wide range of materials such as fertilizers, detergents, food and pharmaceutical products, as well as in the mineral processing industries and treatment of waste effluents. In spite of the wide-spread use of crystallization, a clear understanding of the thermodynamic, kinetic and hydrodynamic aspects of the design methodologies are not yet well established. More often than not crystallization is still considered an art especially in fine-chemicals, pharmaceuticals and life-sciences sector. It is essential to understand and relate key thermodynamic, kinetic and hydrodynamic aspects to crystallizer performance, not just in terms of yield but also in terms of product quality (characterized by particle size distribution, morphology, polymorphism and the amount of strain as well as the uptake of solvent or impurities in the crystal lattice). This paper attempts to do that by critically reviewing published experimental and modelling studies on establishing and enhancing state-of-the-art thermodynamic, kinetic and hydrodynamic aspects of crystallization. Efforts are made to discuss and raise points for emerging modelling tools needed for a flexible design and operation of crystallizers and crystallization processes that are needed to meet the ever increasing demand on precise product specifications. Focus is on bringing out the trends which can be used as perspectives for future studies in this field.
Keywords: CFD; Crystallization; growth; Nucleation; polymorphism; supersaturation

Crystallization kinetics of Sn-MFI molecular sieve formation by dry gel cross mark conversion method - Niphadkar, P. S.; Tangale, N. P.; Joshi, P. N.; Awate, S. V. (Microporous and Mesoporous Materials, 2013)
The conversion of amorphous stannosilicate dry gel into crystalline molecular sieve with MFI structure (Sn-MFI) was achieved by dry gel conversion (DGC) method at 413, 443 and 473 K. For comparison purpose, Sn-MFI molecular sieve with similar SiO2/SnO2 mole ratio was also obtained by hydrothermal crystallization route. Crystallization curves were established by conducting time dependant studies on progressive crystallization processes for both the systems. The values of activation energy of nucleation (E-n), activation energy of crystallization (E-c), and their pre-exponential factors (InA(n), InA(c) respectively) were calculated from Arrhenius plots. Compared to the hydrothermal method, shorter induction period was observed when DGC method was employed. Both the E-n (49.70 kJ/mol) and E-c (52.82 kJ/mol) for DGC method were found to be lower than that of the E-n (55.70 kJ/mop and E-c (60.23 kJ/mol) for hydrothermal method. The kinetics parameters viz. K and q were derived from kinetic expressions and DGC method showed higher value of K and lower value of q compared to hydrothermal crystallization method at identical temperature. Various DGC method parameters such as water content at the bottom of autoclave and SiO2/SnO2 mole ratio have shown the influence on the kinetics of crystallization of Sn-MFI. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Crystallization; DGC; kinetics; Nucleation; Sn-MFI

CuCN-Mediated cascade cyclization of 4-(2-bromophenyl)-2-butenoates: a high-yield synthesis of substituted naphthalene amino esters - Reddy, R. Santhosh; Prasad, Pragati K.; Ahuja, Brij Bhushan; Sudalai, Arumugam (Journal of Organic Chemistry, 2013)
A new method of CuCN-mediated one-pot cyclization of 4-(2-bromophenyl)-2-butenoates leading to efficient synthesis of substituted naphthalene amino esters including phenanthrene aromatic structural units is described. Deuterium labeling studies establish that this one-pot cascade cyclization proceeds through isomerization of olefin, intramolecular C-C bond cyclization, and aromatization as the key intermediates, all occurring in a single step.

Cyanate ester resins containing pentadecyl-substituted cyclohexyl moiety: synthesis, curing and structure-property relationship - Kulkarni, Arun D.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2013)
Cyanate ester (CE) monomers containing pentadecyl-substituted cyclohexyl moieties such as 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane and 1,1-bis(4-cyanatophenyl) cyclohexane were synthesized and characterized by Fourier transform infrared, proton-nuclear magnetic resonance (H-1-NMR) and carbon-nuclear magnetic resonance (C-13-NMR) spectroscopies as well as differential scanning calorimetry (DSC). Both 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane and 1,1-bis(4-cyanatophenyl) cyclohexane exhibited better processability coupled with lower melting points, lower cure onset with broad cure exotherm than the commercially available CE monomer, namely, 2,2-bis(4-cyanatophenyl) propane. Glass transition temperatures of cured 2,2-bis(4-cyanatophenyl) propane, 1,1-bis(4-cyanatophenyl) cyclohexane and 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane were observed to be 288 degrees C, 302 degrees C and 160 degrees C, respectively. Cured 1,1-bis(4-cyanatophenyl) cyclohexane displayed higher storage modulus (1.59 x 10(9) Pa) than 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane (1.07 x 10(9) Pa) and 2,2-bis(4-cyanatophenyl) propane (1.39 x 10(9) Pa). The order of thermal stability of cured polycyanurates was found to be 2,2-bis(4-cyanatophenyl) propane > 1,1-bis(4-cyanatophenyl) cyclohexane > 1,1-bis(4-cyanato phenyl) 3-pentadecylcyclohexane. The moisture absorption of cured resins derived from 1,1-bis(4-cyanatophenyl) 3-pentadecyl cyclohexane and 1,1-bis(4-cynatophenyl) cyclohexane was found to be lower than that of 2,2-bis(4-cynatophenyl) propane implying the role of pentadecyl substituent and/or cyclohexyl moiety in imparting hydrophobicity to the polycyanurates.
Keywords: (pentadecyl substituted) cyclohexyl; curing; cyanate ester resin; thermosets

Calcium oxide supported gold nanoparticles as catalysts for the selective epoxidation of styrene by t-butyl hydroperoxide - Dumbre, Deepa K.; Choudhary, Vasant R.; Patil, Nilesh S.; Uphade, Balu S.; Bhargava, Suresh Kumar (Journal of Colloid and Interface Science, 2014)
Gold nanoparticles are deposited on basic CaO supports as catalysts for the selective conversion of styrene into styrene oxide. Synthetic methods, gold loading and calcination temperatures are varied to permit an understanding of their influence on gold nanoparticle size, the presence of cationic gold species and the nature of interaction between the gold nanoparticles and the CaO support. Based on these studies, optimal conditions are designed to make the Au/CaO catalyst efficient for the selective epoxidation of styrene. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/CaO; Epoxidation of styrene; gold nanoparticles; Homogenous deposition precipitation method; Styrene oxide

Calorimetric elucidation of ionic interactions in room temperature ionic liquid solutions - Rai, Gitanjali; Kumar, Anil (Clean Technologies and Environmental Policy, 2014)
Knowledge of thermal properties of room temperature ionic liquid (RTIL) solutions is essential in chemical process designing in addition to their application in understanding ionic interactions at molecular level. RTILs are considered to be substitutes for volatile organic compounds. While some experimental thermal data on these systems are available in a random manner, the modeling efforts to correlate enthalpy-concentration profiles of RTIL solutions are very scanty. In this review, an effort has been made to compare and discuss the experimental data of these RTIL solutions available in the literature. The readers are also made aware of the disappointing situation regarding the availability of any type of correlative models for the enthalpy-concentration data of the RTIL systems. An accurate knowledge of activity coefficients at infinite dilutions, Iyen (i) (a) acquired from thermal data will serve as inputs for the newer less polluting process designing and thus open opportunity for a cleaner environment.
Keywords: Calorimeters; Correlative models; Excess partial molar enthalpy; Room temperature ionic liquids

Can silylenes rival transition metal systems in bond-strengthening pi-back donation? a computational investigation - Pal, Amrita; Vanka, Kumar (Chemical Communications, 2014)
Full quantum chemical calculations with density functional theory (DFT) show that bond-strengthening back-donation to a pi-diborene, recently discovered for transition metal systems (Braunschweig and co-workers, Nat. Chem., 2013, 5, 115-121), would be just as favored for Main Group silylene complexes. This result not only shows the range and applicability of the bond-strengthening back-bonding interaction, but also showcases the capacity of silylene complexes to do new chemistry, such as the cooperative activation of carbon monoxide and carbon dioxide.

Capturing a novel metastable polymorph of the anticancer drug gefitinib - Thorat, Shridhar H.; Patwadkar, Manjusha V.; Gonnade, Rajesh G.; Vaidhyanathan, R. (CrystEngComm, 2014)
Gefitinib, a life-extending anticancer drug, exhibits solvent-mediated conformational polymorphism to yield stable (form I) and novel metastable (form II) polymorphs. Crystal structure analysis revealed 3D isostructurality in the molecular organization of the polymorphs, and the metastable polymorph undergoes a crystal-to-crystal thermal phase transition to the stable polymorph.

Cationic charged helical glycopolypeptide using ring opening polymerization of 6-deoxy-6-azido-glyco-N-carboxyanhydride - Shaikh, Ashif Y.; Das, Soumen; Pati, Debasis; Dhaware, Vinita; Sen Gupta, Sayam; Hotha, Srinivas (Biomacromolecules, 2014)
Glycopolypeptides with a defined secondary structure are of significance in understanding biological phenomena. Synthetic glycopolypeptides, or polypeptides featuring pendant carbohydrate moieties, have been of particular interest in the field of tissue engineering and drug delivery. In this work, we have synthesized charged water-soluble glycopolypeptides that adopt a helical conformation in water. This was carried out by the synthesis of a glyco-N-carboxyanhydride (glyco-NCA) containing an azide group at the sixth position of the carbohydrate ring. Subsequently, the NCA was polymerized to obtain azide-containing glycopolypeptides having good control over molecular weight and polydispersity index (PDI) in high yields. We were also able to control the incorporation of the azide group by synthesizing random co-glycopolypeptide containing 6-deoxy-6-azido and regular 6-OAc functionalized glucose. This azide functionality allows for the easy attachment of a bioactive group, which could potentially enhance the biological activity of the glycopolypeptide. We were able to obtain water-soluble charged glycopolypeptides by both reducing the azide groups into amines and using CuAAC with propargylamine. These charged glycopolypeptides were shown to have a helical conformation in water. Preliminary studies showed that these charged glycopolypeptides showed good biocompatibility and were efficiently taken up by HepG2 cells.

CdS nanowires: ultra-long growth and enhanced field emission properties - Chavan, Padmakar G.; Kashid, Ranjit V.; Badhade, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Vaccum, 2014)
Here, we report the synthesis of ultra-long CdS nanowires with aspect ratio similar to 8 x 10(4) by simple route of thermal evaporation technique. A change in the vertical arrangement of quartz boats leads in to the synthesis of ultra-long CdS nanovvires via high degree of condensation. This technique is seen to be cost effective and easy. The growth of the nanowires is found to be increased very rapidly from few micrometers to few millimeters. The possible reason for the growth of the ultra-long CdS nanowires is discussed in detail. The turn-on field defined for the current density of similar to 0.1 mu A/cm(2) has been found to be similar to 1.4, 1.45, 1 and 0.17 V/mu m for specimen A, B, C and D (specimens A-D, synthesized by variation in synthesis parameters) respectively. The turn-on field of the specimen D (similar to 0.17 V/mu m) is found to be quite superior than the value reported for other CdS nanoforms which is very remarkable. Simple way of bulk fabrication leads to the low turn-on value which indicates a possible use of the present emitter in the micro/nanoelectronics devices. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Current stability; field emission; synthesis

Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs): a new heterogeneous and recyclable catalyst for the one pot synthesis of 1,4-disubstituted-1,2,3-triazoles in water - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (RSC Advances, 2014)
Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs) have been demonstrated for the first time as an efficient heterogeneous catalyst in the click synthesis of 1,4-disubstituted 1,2,3-triazoles by a one-pot three component reaction between aralkyl/alkyl bromides, alkynes and sodium azide in water. The catalyst has been characterized by XRD, HRTEM, SEM, ICP-AES, EDS as well as IR spectroscopy. It was found to be reusable for five consecutive runs without significant loss of activity.

CH3NH3PbI(3-x)(BF4)(x): molecular ion substituted hybrid perovskite - Nagane, Satyawan; Bansode, Umesh P.; Game, Onkar S.; Chhatre, Shraddha; Ogale, Satishchandra (Chemical Communications, 2014)
A molecular ion (BF4-) substituted hybrid perovskite CH3NH3PbI(3-x)(BF4)(x) is synthesized. The substituted perovskite shows significant enhancement in electrical conductivity at low frequencies and improved photoresponse under AM1.5 illumination as compared to the perovskite (CH3NH3PbI3).

Characteristics of HRV patterns for different yoga postures - Pitale, Rahul; Tajane, Kapil; Phadke, Leena; Joshi, Aniruddha; Umale, Jayant (2014 Annual IEEE India Conference (INDICON), 2014)
Human heart rate fluctuates in a complex and non-stationary manner, due to continuous influences from autonomic nervous system and other factors (harmones, temp, etc) on the sinoatrial node (S.A) (Pacemaker of the heart). ANS dysfunction is known to be associated with various cardiovascular and lifestyle diseases. The importance of traditional ancient Indian practice like Yoga has increased significantly due to the observed beneficial effects of it in various lifestyle diseases. Preliminary studies have shown that yoga may have its beneficial effect by influencing autonomic nervous system. Heart rate variability (HRV) is a most promising predictive and prognostic marker of autonomic (ANS) activity. HRV is analyzed by time and frequency domain parameters (Fast Fourier Transform). Being linear parameters these are not able to extract full information regarding the non linear behavior of heart rate fluctuations. In this paper, we propose to analyze HRV by using linear as well as non-linear methods during different yogaasanas. These mathematical models will be useful to understand the underlying physiological mechanisms during different yogasanas.
Keywords: ECG; HRV; Poincare plot; Recurrence plot; Yogasanas

Characterization, non-isothermal decomposition kinetics and photocatalytic water splitting of green chemically synthesized polyoxoanions of molybdenum containing phosphorus as hetero atom - D'Cruz, Bessy; Samuel, Jadu; George, Leena (Thermochimica Acta, 2014)
In here, the green synthesis and thermal characterization of a novel polyoxoanions of molybdenum containing phosphorus as hetero atom are reported. The composition and morphology of the nanorods were established by fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermogravimetric analysis (TGA) and inductively coupled plasma atomic emission spectroscopic (ICP-AES) techniques. Thermal properties of the nanoparticles were investigated by non-isothermal analysis under nitrogen atmosphere. The values activation energy of each stage of thermal decomposition for all heating rates was calculated by Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunnose (KAS) methods. Invariant kinetic parameter (IKP) method and master plot methodmere also used to evaluate the kinetic parameters and mechanism for the thermal decomposition of cetylpyridinium phosphomolybdate (CPM). Photocatalytic water oxidation mechanism using CPM catalyst in the presence of platinum (Pt) co-catalyst enhances the H-2 evolution and was found to be 1.514 mmol/g/h. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Keggin structure; Master plot method; Polyoxometalate; Water oxidation

Chemically delaminated free standing covalent organic nanosheets (CONs) - Khayum, Abdul M.; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; porous polymers; ultra thin nano sheets

Chemically doped perylene diimide lamellae based field effect transistor with low operating voltage and high charge carrier mobility - Arulkashmir, Arulraj; Jain, Bhanprakash; John, Jino C.; Roy, Kanak; Krishnamoorthy, Kothandam (Chemical Communications, 2014)
Chemical doping of an electron transporter results in the formation of a radical anion containing semiconductor which showed high electron mobility (13 cm(2) V-1 s(-1)) at low operating voltage (1 V).

Chemically stable urea based COF for size selective heterogeneous catalysis - Basu, Arghya; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: chemical stability; Covalent organic framework; heterogeneous catalysis

ChemInfoCloud: opensource based cloud compatible chemical textmining tools for harvesting largescale medical literature - Karthikeyan, Muthukumarasamy (248th National Meeting of the American-Chemical-Society (ACS), 2014)

Chemistry of materials celebrates the 80th birthday of one of the premier "chemists of materials" - Prasad, Bhagavatula L. V; Buriak, Jillian M. (Chemistry of Materials, 2014)

Chemoinformatics approach for the design and screening of focused virtual libraries - Karthikeyan, Muthukumarasamy; Vyas, Renu (Practical Chemoinformatics, 2014)
It is challenging to handle a large volume of molecular data without appropriate tools. Here, we describe the need and the approaches for the development of focussed virtual libraries to design efficient molecules and optimize them for lead generation. The experimental chemists and biologists are more interested in properties of chemicals and their response to biological system in both beneficial and adverse effects context rather than just their structures. In this chapter, the focus is to relate newly designed chemical structures to their predicted activity, property or toxicity. Property prediction tools save time, money and lives of experimental animals. They come in handy while taking informed decisions especially in certain cases involving pharmacodynamic studies of drug molecules in humans where there are inevitable ethical and safety concerns. Property prediction is an important component in virtual screening which is at the heart of drug design and the most important step where chemoinformatics plays a major role. The other fields where structure–activity relation-based principles hold good for virtual screening are agrochemicals and environmental science, specifically the toxicity and biodegradability prediction of pollutant molecules. In this chapter, we will show how to design software tools to handle generation of focussed virtual libraries from a given set of molecules with common features, fragments or bioactivity spectrum.

Chemoselective deprotection of N-allylic amines using DDQ - Kumar, Pradeep; Cherian, Shijo K.; Jain, Ruchi; Show, Krishanu (Tetrahedron Letters, 2014)
A highly chemoselective and simple method for the deprotection of N-allylic amines using DDQ has been developed. The use of DDQ in dichloromethane-water provides a mild and efficient one-step deallylation of a wide variety of orthogonally protected tertiary amine derivatives. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chemoselective deprotection; DDQ; N-Allylic amines; Orthogonally protected tertiary amines

Chickpea Kunitz Inhibitor: a mechanistic basis for trypsin inhibition - Bendre, Ameya Dipak; Ramasamy, Sureshkumar; Suresh, C. G. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Chickpea; Kunitz Inhibitor; Protease

Chiral poly(L-lactic acid) driven helical self-assembly of oligo(p-phenylenevinylene) - Nisha, S. Kumari; Asha, S. K. (Journal of Materials Chemistry C, 2014)
The synthesis and self-assembly of a series of copolyesters incorporating varying mol ratios of an achiral oligo(p-phenylenevinylene) (OPV) into the backbone of a chiral poly(L-lactic acid) (PLLA) via high temperature solution blending is reported. The polymers were characterized by H-1 NMR spectroscopy and size exclusion chromatography (SEC) and their bulk properties were investigated by differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WXRD). The DSC and WXRD analyses confirmed the crystallinity and pi-pi stacking of the OPV units in the PLLA-OPV copolyester. Absorption, emission and lifetime-decay studies showed that the OPV chromophore was highly aggregated in the solid state. The solid powder samples of the copolyesters exhibited an intense, red shifted aggregate emission beyond 470 nm. Circular dichroism (CD) spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM) studies revealed that the PLLA-OPV copolyester formed a self-assembled architecture, in which the helical organization of the achiral OPV segments was dictated by the chiral PLLA segments. The observed CD signal and AFM image accounted for the right-handed helical self-assembly of the OPV chromophore in the solid state. These results confirmed the effect of the chiral PLLA segment on tuning the OPV chromophore packing and supramolecular chirality in molecular aggregates. The methodology illustrated here provides opportunities for the design of a new class of hierarchical, self-assembled architectures, based on organic pi-conjugated materials and the manipulation of their optical properties.

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2014)
The efficient and practical formal syntheses of both enantiomers of cis 3-hydroxypipecolic acid were accomplished from cis aziridine-2-carboxylate as the common synthetic precursor. The key steps involved are stereo and regioselective aziridine ring opening, reductive cyclization and selective N-debenzylation over O-debenzylation reactions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxypipecolic acid; Aziridine ring opening; Aziridine-2-carboxylate; Piperidine alkaloids; Selective debenzylation

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing

Cholesterol depletion by methyl-beta-cyclodextrin augments tamoxifen induced cell death by enhancing its uptake in melanoma - Mohammad, Naoshad; Malvi, Parmanand; Meena, Avtar Singh; Singh, Shivendra Vikram; Chaube, Balkrishna; Vannuruswamy, Garikapati; Kulkarni, Mahesh J.; Bhat, Manoj Kumar (Molecular Cancer, 2014)
Background: Despite modern advances in treatment, skin cancer is still one of the most common causes of death in the western countries. Chemotherapy plays an important role in melanoma management. Tamoxifen has been used either alone or in-combination with other chemotherapeutic agents to treat melanoma. However, response rate of tamoxifen as a single agent has been comparatively low. In the present study, we investigated whether treatment with methyl-beta-cyclodextrin (MCD), a cholesterol depleting agent, increases the efficacy of tamoxifen in melanoma cells. Methods: This was a two-part study that incorporated in vitro effects of tamoxifen and MCD combination by analyzing cell survival, apoptosis and cell cycle analysis and in vivo antitumor efficacy on tumor isografts in C57BL/6J mice. Results: MCD potentiated tamoxifen induced anticancer effects by causing cell cycle arrest and induction of apoptosis. Sensitization to tamoxifen was associated with down regulation of antiapoptotic protein Bcl-2, up-regulation of proapoptotic protein Bax, reduced caveolin-1 (Cav-1) and decreased pAkt/pERK levels. Co-administration of tamoxifen and MCD caused significant reduction in tumor volume and tumor weight in mice due to enhancement of drug uptake in the tumor. Supplementation with cholesterol abrogated combined effect of tamoxifen and MCD. Conclusion: Our results emphasize a potential synergistic effect of tamoxifen with MCD, and therefore, may provide a unique therapeutic window for improvement in melanoma treatment.
Keywords: Caveolin-1; Cholesterol; Methyl beta-cyclodextrin; Tamoxifen

Cholesterol modulates the dimer interface of the beta(2)-adrenergic receptor via cholesterol occupancy sites - Prasanna, Xavier; Chattopadhyay, Amitabha; Sengupta, Durba (Biophysical Journal, 2014)
The beta(2)-adrenergic receptor is an important member of the G-protein-coupled receptor (GPCR) superfamily, whose stability and function are modulated by membrane cholesterol. The recent high-resolution crystal structure of the beta(2)-adrenergic receptor revealed the presence of possible cholesterol-binding sites in the receptor. However, the functional relevance of cholesterol binding to the receptor remains unexplored. We used MARTINI coarse-grained molecular-dynamics simulations to explore dimerization of the beta(2)-adrenergic receptor in lipid bilayers containing cholesterol. A novel (to our knowledge) aspect of our results is that receptor dimerization is modulated by membrane cholesterol. We show that cholesterol binds to transmembrane helix IV, and cholesterol occupancy at this site restricts its involvement at the dimer interface. With increasing cholesterol concentration, an increased presence of transmembrane helices I and II, but a reduced presence of transmembrane helix IV, is observed at the dimer interface. To our knowledge, this study is one of the first to explore the correlation between cholesterol occupancy and GPCR organization. Our results indicate that dimer plasticity is relevant not just as an organizational principle but also as a subtle regulatory principle for GPCR function. We believe these results constitute an important step toward designing better drugs for GPCR dimer targets.

Clay encapsulated Cu(OH)(x) promoted homocoupling of arylboronic acids: an efficient and eco-friendly protocol - Dar, Bashir Ahmad; Singh, Snehil; Pandey, Nalini; Singh, A. P.; Sharma, Priti; Lazar, Anish; Sharma, Meena; Vishwakarma, Ram A.; Singh, Baldev (Applied Catalysis A-General, 2014)
Cu(OH)(x) has been encapsulated over montmorillonite-KSF by simple ologomeric deposition strategy. The resulting catalyst has been employed for selective homocoupling of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst is easy to recover and shows excellent reusability without losing its activity. Techniques like XRD, SEM, TPR, IR, BET surface area measurement and XPS were used to characterize the catalyst. The present method promises for the simple and clean homocoupling of arylboronic acids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biaryls; clay; Copper; Heterogenous catalyst; Homocoupling

Clay-supported copper nitrate (Claycop): a mild reagent for the selective nitration of aromatic olefins - Begari, Eeshwaraiah; Singh, Chandani; Nookaraju, U.; Kumar, Pradeep (Synlett, 2014)
A straightforward and highly selective method has been developed for the nitration of a wide variety of aromatic and aliphatic olefins by using a clay-supported copper nitrate (Claycop) and a catalytic amount of (2,2,6,6-tetramethylpiperidin-1-yl)oxyl, an inexpensive and mild reagent system. High conversions and exclusive E-selectivity, together with the environmentally benign nature of the Claycop reagent, make this a green method and an attractive alternative to established methods.
Keywords: alkenes; nitrations

Cocrystals/salts of Furosemide : Interesting case of colour cocrystal polymorphism - Sangtani, Ekta; Jha, Kunal; Munshi, Parthapratim; Gonnade, Rajesh (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Color cocrystal polymorphism; Sandwich assembly; Stacking interactions

Co(III)(salen)-catalyzed phenolic kinetic resolution of two stereocentered benzyloxy and azido epoxides: its application in the synthesis of ICI-118,551, an anti-hypertensive agent - Karabal, Pratibha U.; Kamble, Dayanand A.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2014)
The salen Co(III)-catalyzed phenolic kinetic resolution of racemic anti- or syn-azido and benzyloxy epoxides provides a practical route to a range of enantioenriched anti-or syn-1-aryloxy-3-azido or benzyloxy-2-alcohols in excellent yields and ees. The synthetic potential of this protocol is illustrated with an enantioselective synthesis of ICI-118,551, a beta-blocker, in a highly optically pure form (99% ee).

Co-immobilized glucose oxidase and beta-galactosidase on bovine serum albumin coated allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer as a biosensor for lactose determination in milk - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Fadnavis, Nitin W.; Addepally, Uma; Daniels, Siona; Ponrathnam, Surendra (Enzyme and Microbial Technology, 2014)
Bovine serum albumin (BSA) was adsorbed on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) at pH 8.0 (16% w/w). The amino, thiol and carboxylic acid functional groups available on protein coated surface were utilized for covalent immobilization of glucose oxidase and beta-galactosidase, both independently, and in a step-wise manner on the same matrix, with no more than 10% loss of enzyme activity during immobilization. Glutaraldehyde cross-linking after immobilization provided stable enzyme preparations. The pH-optima of the immobilized enzymes were similar to those for free enzyme but their thermal stability was vastly improved. The co-immobilized enzyme support was used as a biosensor for determination of lactose in milk with excellent reproducibility and reusability. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: beta-Galactosidase; Bovine serum albumin; Glucose oxidase; Immobilization; Lactose assay

Combined gasification of lignite coal: thermodynamic and application study - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Chavan, Rank N. (Journal of the Taiwan Institute of Chemical Engineers, 2014)
Combined gasification (a combination of steam gasification and CO2 gasification) without air is an important process for research in coal gasification to reduce the steam generation energy in the gasification system and also to enhance the slow CO2 gasification reaction. A thermodynamic study involving the effect of temperature, pressure and feed CO2 and steam ratios in gasification of lignite coal was studied in this paper. The product generation trends of syngas and methane with carbon (in coal) conversion were studied in detail. The carbon (in lignite coal) was converted completely at a lower temperature than pure carbon in the combined gasification. Some applications of the gasifier product gas were also studied. Combined gasification offers great advantages to produce syngas of exact ratio in one step for use in petrochemical manufacture and fuel cell systems. The complete carbon (in coal) conversion occurred beyond the thermoneutral gasification temperature in the study. The combined gasification process was a useful way for CO2 utilization reducing the net CO2 emission to the atmosphere. (C) 2013 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: CO2 utilization; Coal gasification; Coal to syngas; Combined gasification; Thermodynamic study

Comparative study on the dye sensitized solar cell performance of solution processed ZnO - Jana, Arpita; Das, Partha Pratim; Agarkar, Shruti A.; Devi, P. Sujatha (Solar Energy, 2014)
We have monitored the performance of the dye-sensitized solar cells (DSSC) using solution processed ZnO having different shapes and aspect ratios. The aspect ratio and surface area of the ZnO structures have been regulated by carefully controlling the precursor concentration and reaction conditions. The shape of the synthesized structures has been varied from larger rods to smaller rods to hexagonal prisms. The synthesized hexagonal prism shaped ZnO with an aspect ratio of around one exhibited the highest surface area of 42 m(2)/g. The ZnO rods with higher aspect ratios of 5 and 16 exhibited lower surface areas of 22 and 2 m(2)/g, respectively. The dye sensitized solar cells constructed using the as-prepared ZnO structures and N719 dye molecules, exhibited efficiencies that varied as a function of surface area of the samples, with ZnO hexagonal prism exhibiting a maximum efficiency of around 1.38 +/- 0.01%. The results indicated a direct correlation between the surface area of the ZnO structures and the energy conversion efficiency. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: DSSC; Photoanode; surface area; ZnO

Comparison of polymer induced and solvent induced trypsin denaturation: the role of hydrophobicity - Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Addepally, Uma; Daniels, Siona; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2014)
Trypsin adsorption from aqueous buffer by various copolymers of allyl glycidyl ether-ethylene glycol dimethacrylate (AGE-EGDM) copolymer with varying crosslink density increases with increasing crosslink density and the effect slowly wears off after reaching a plateau at 50% crosslink density. The copolymer with 25% crosslink density was reacted with different amines with alkyl/aryl side chains to obtain a series of copolymers with 1,2-amino alcohol functional groups and varying hydrophobicity. Trypsin binding capacity again increases with hydrophobicity of the reacting amine and a good correlation between logP(octanol) of the amine and protein binding is observed. The bound trypsin is denatured to the extent of 90% in spite of the presence of hydrophilic hydroxyl and amino groups. The behavior was comparable to that in mixtures of aqueous buffer and water-miscible organic co-solvents where the solvent concentration required to deactivate 50% of the enzyme (C-50) is dependent on logP(octanol) of the co-solvent. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Denaturation; Hydrophobicity; Polymer; Trypsin

Comparison of sodium zirconium phosphate and calcium zirconium phosphate structures for the retention of fluoride - Dey, Ambarish; Das Gupta, Amit; Basu, Debrata; Ambashta, Ritu D.; Wattal, P. K.; Kumar, Sanjiv; Body, Monique; Rajamohanan, P. R. (Journal of Radioanalytical and Nuclear Chemistry, 2014)
Fluoride anion interaction has been explored for the first time to investigate how the structure of sodium zirconium phosphate (NZP) and calcium zirconium phosphate (CZP) can be altered in its presence. Different compositions were made by adding NaF and CaF2 in CZP and NZP matrices respectively. Fluoride interaction differs with NZP and CZP structure as suggested by F-NMR data. The addition of fluoride to the NZP or CZP structure enables to stabilize the structure at a low temperature of 600-700 A degrees C under microwave conditions.
Keywords: F-NMR; Fluoride characterization; Microwave; NZP; PIGE

Complex absorbing potential based coupled-cluster methods to metastable states - Pal, Sourav (248th National Meeting of the American-Chemical-Society (ACS), 2014)

Complex absorbing potential based equation-of-motion coupled cluster method for the potential energy curve of CO2- anion - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav; Bartlett, Rodney J. (Journal of Chemical Physics, 2014)
The equation-of-motion coupled cluster method employing the complex absorbing potential has been used to investigate the low energy electron scattering by CO2. We have studied the potential energy curve for the (2)Pi(u) resonance states of CO2- upon bending as well as symmetric and asymmetric stretching of the molecule. Specifically, we have stretched the C-O bond length from 1.1 angstrom to 1.5 angstrom and the bending angles are changed between 180 degrees and 132 degrees. Upon bending, the low energy (2)Pi(u) resonance state is split into two components, i.e., (2)A(1), B-2(1) due to the Renner-Teller effect, which behave differently as the molecule is bent. (c) 2014 AIP Publishing LLC.

Computational investigation on the catalytic activity of Rh-6 and Rh4Ru2 clusters towards methanol activation - Ghatak, Kamalika; Sengupta, Turbasu; Krishnamurty, Sailaja; Pal, Sourav (Theoretical Chemistry Accounts, 2014)
Catalysis of molecular activation of small molecules through scission of strong chemical bonds is one of the major challenges faced by chemists. More specifically, activation of the strong C-H and O-H bonds of various alcohols, especially methanol, is one of the various important intermediate steps of key organic reactions. Our present work explores a suitable metal cluster catalyst towards methanol dissociation. In particular, we have examined the effect of ruthenium doping (Rh:Ru = 2:1) on the catalytic activity of Rh-6 cluster towards methanol dissociation. Density functional theory-based calculations illustrate two competitive pathways for methanol dissociation, which are via O-H and C-H bond breaking. Both the pathways are found to be energetically favourable in the presence of bimetallic and mono-metallic clusters. Importantly, energy barrier for O-H bond dissociation reduces considerably in doped cluster as compared to pure Rh-6 cluster and is smaller than the values reported for a number of other small metallic clusters.
Keywords: Bimetallic Clusters; Density Functional Theory (DFT); Doping; Methanol Activation; Rhodium Clusters

Concise account of the chemistry of valuable alkyl(methyl)maleic anhydrides - Deore, Prashant S.; Haval, Kishan P.; Gadre, Smita R.; N. P. Argade (Synthesis-Stuttgart, 2014)
A large number of significant bioactive natural and synthetic alkyl(methyl)maleic anhydrides are known in the contemporary literature. A broad range of suitably functionalized substrates have been tailored to accomplish concise and efficient syntheses of an array of alkyl(methyl)maleic anhydrides employing a variety of elegant synthetic strategies. This review presents a brief literature account of the isolation and activity of these important target compounds with a special emphasis on their synthesis.
Keywords: alkyl(methyl)maleic anhydrides; bioactivity; dimethylmaleic anhydride; isolation; nucleophilic reactions; Total synthesis

Concise account of various approaches for stereoselective construction of the C-20(H) stereogenic center in steroid side chain - Shingate, Bapurao B.; Hazra, Braja G. (Chemical Reviews, 2014)

Concise enantioselective syntheses of (+)-L-733,060 and (2S,3S)-3-hydroxypipecolicw acid by cobalt(III)(salen)-catalyzed two-stereocenter hydrolytic kinetic resolution of racemic azido epoxides - Devalankar, Dattatray A.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Synlett, 2014)
An efficient synthesis of the 2,3-disubstituted piperidines (+)-L-733,060 and (2S,3S)-3-hydroxypipecolic acid (99% ee) in high optical purity from commercially available starting materials is described. The strategy involves a cobalt-catalyzed hydrolytic kinetic resolution of a racemic azido epoxide with two stereocenters and an intramolecular reductive cyclization as key reactions.
Keywords: azides; cyclizations; epoxides; piperidines; stereoselective synthesis; Wittig reactions

Concise synthetic approach toward tamiflu (oseltamivir phosphate): cis-aziridine as the key synthon and RCM - Chavan, S. P.; Chavan, P. N.; Khairnar, L. B. (RSC Advances, 2014)
A synthesis of oseltamivir (Tamiflu) was achieved starting from D-mannitol. A unique feature of the synthetic route is that an acyclic precursor was constructed, which was then cyclized in an intramolecular aldol reaction to form the Tamiflu skeleton. Throughout the synthesis, well-established, highly efficient reactions were employed, and no protection/deprotection sequence was needed.

Confined space synthesis of fully alloyed and sinter-resistant AuPd nanoparticles encapsulated in porous silica - Samanta, Anupam; Rajesh, Thattarathody; Devi, R. Nandini (Journal of Materials Chemistry A, 2014)
Facile synthesis of highly sinter-resistant silica encapsulated Au-Pd alloy nanocatalysts with average particle size stabilized at similar to 4.5 nm even after calcination at 750 degrees C temperature is reported. The synthesis was achieved by utilizing thiol protected ultra small clusters of Au and Pd as precursors for silica encapsulation. The presence of intimate mixtures of the clusters within silica encapsulation ensures the formation of fully alloyed nanoparticles at high temperatures, at the same time controlling further growth and sintering. At optimum alloy compositions, these catalysts showed high catalytic activity for CO oxidation displaying low light-off temperatures.

Conformational modulation of peptide secondary structures using beta-aminobenzenesulfonic acid - Kale, Sangram S.; Kunjir, Shrikant M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
This communication describes the influence of beta-aminobenzenesulfonic acid ((S)Ant) on the conformational preferences of hetero foldamers. The designed (Aib-(S)Ant-Aib)(n) and (Aib-(S)Ant-Pro)(n) oligomers display a well-defined folded conformation featuring intramolecular mixed hydrogen bonding (7/11) and intra-residual (6/5) H-bonding interactions, respectively.

Conformational transitions of cinnamoyl CoA reductase 1 from leucaena leucocephala - Sonawane, Prashant D.; Khan, Bashir Mohammad; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2014)
Conformational transitions of cinnamoyl CoA reductase, a key regulatory enzyme in lignin biosynthesis, from Leucaena leucocephala (L1-CCRH1) were studied using fluorescence and circular dichroism spectroscopy. The native protein possesses four trp residues exposed on the surface and 66% of helical structure, undergoes rapid structural transitions at and above 45 C and starts forming aggregates at 55 C. LI-CCRH1 was transformed into acid induced (pH 2.0) molten globule like structure, exhibiting altered secondary structure, diminished tertiary structure and exposed hydrophobic residues. The molten globule like structure was examined for the thermal and chemical stability. The altered secondary structure of Ll -CCRH1 at pH 2.0 was stable up to 90 C. Also, in presence of 0.25 M guanidine hydrochloride (GdnHCI), it got transformed into different structure which was stable in the vicinity of 2 M GdnHCI (as compared to drastic loss of native structure in 2 M GdnHC1) as seen in far UV-CD spectra. The structural transition of LI-CCRH1 at pH 2.0 followed another transition after readjusting the pH to 8.0, forming a structure with hardly any similarity to that of native protein. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aggregation Cinnamoyl CoA reductase; Conformation; Molten globule; Thermostability; Unfolding

Construction of highly crystalline ultraporous covalent organic frameworks in seconds - Karak, Suvendu; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COFs; Crystalline; Ultraporous

Contemporary avenues in catalytic P-H bond addition reaction: a case study of hydrophosphination - Koshti, Vijay; Gaikwad, Shahaji R.; Chikkali, Samir H. (Coordination Chemistry Reviews, 2014)
Remarkable advances and current state-of-the-art developments in catalytic hydrophosphination of alkenes and alkynes are reviewed. The challenges in constructing a C P bond with a special emphasis on metal catalysed (asymmetric) hydrophosphination are highlighted. Only those systems that unambiguously proceed via P H bond addition across a C-C/X (X = O, N, S) multiple bond have been covered in this overview. Reviewed examples support the assumption that either strongly chelating ligands or reaction products that act as ligands, enhance the rate of hydrophosphination. The asymmetric variant of this transformation allows installation of p-chiral [enantiomeric excess (ee) up to 82%] as well as C-chiral (ee up to 99%) centres. The limited spectroscopic, mechanistic data and OFT calculations point at two distinctly different mechanisms. In case of hydrophosphination, the metal undergoes oxidative addition and reductive elimination steps (in general), thus changing the oxidation state from M(0) to M(II) and back to M(0). Whereas in asymmetric hydrophosphination it is proposed that the oxidation state of the metal remains unaltered throughout the catalytic cycle. The examples described in this overview showcase the real power of catalytic hydrophosphination in constructing various phosphorus compounds, which may initiate a new era in organo-phosphorus chemistry. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Alkynes; Asymmetric hydrophosphination; Hydrophosphination; Metal catalyzed hydrophosphination; Olefins; P-H bond addition

Continuous flow nitration in miniaturized devices - Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2014)
This review highlights the state of the art in the field of continuous flow nitration with miniaturized devices. Although nitration has been one of the oldest and most important unit reactions, the advent of miniaturized devices has paved the way for new opportunities to reconsider the conventional approach for exothermic and selectivity sensitive nitration reactions. Four different approaches to flow nitration with microreactors are presented herein and discussed in view of their advantages, limitations and applicability of the information towards scale-up. Selected recent patents that disclose scale-up methodologies for continuous flow nitration are also briefly reviewed.
Keywords: continuous flow; flow chemistry; microreactors; nitration; nitric acid; Tubular reactor

Continuous-flow meerwein arylation - Bhaya, Vinay G.; Joshi, Ramesh A.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2014)
The continuous-flow Meerwein arylation is demonstrated for a set of few aryl donors (anilines and m-aminoacetophenone) and specific radical acceptors. Homogeneous catalyst (CuBr in HBr and CuCl in HCl) was used to facilitate the reaction. The effect of parameters, viz., temperature, catalyst concentration, residence time, and concentration of the radical acceptor on the yield of the arylated product, was studied. The yield of the aryl derivative obtained by continuous-flow syntheses was always better than the respective experiments in batch mode. Flow synthesis allows easy variation in these parameters and thus allows going close to the maximum possible yields in a system where the relative rates of different reactions create a complex situation. Temperature plays a crucial role by affecting the rates as well as by governing the system homogeneity. The nitrogen bubbles generated in the reaction helped to avoid any channel blockage.
Keywords: diazonium salt; flow chemistry; homogeneous catalyst; Meerwein arylation; micromixer; multistep synthesis

Controlled release of antimicrobial Cephalexin drug from silica microparticles - Rao, B. V. Bhaskara; Mukherji, Ruchira; Shitre, G.; Alam, F.; Prabhune, Asmita; Kale, Sangeeta N. (Materials Science & Engineering C-Materials for Biological Applications, 2014)
Release of antimicrobial drugs in a controlled fashion for extended duration of time has been investigated for long. Such controlled-drug-releasing materials show promising applications in medicinal bandages. Along with antimicrobial agents, one could also incorporate other therapeutic drugs, to make such bandages more versatile. In this context, silica micro particles were synthesized using direct reduction method, in which the synthesis was done in the presence of Cephalexin. Cephalexin was chosen as an antimicrobial candidate. The morphological characterization shows formation of monodispersed, silica microparticles of similar to 200 nm in size. The FTIR spectroscopy shows weak interaction of the drug molecule at its hydroxide (OH) site with oxygen ions on the silica surface. Upon conjugation, the UV-vis spectroscopy shows persistence of the Cephalexin signature, especially its R group, confirming its antimicrobial activity even after conjugation. Loading studies reveal 12% Cephalexin loading on silica. The antimicrobial studies were done on three micro-organisms, namely, Staphylococcus aureus, Bacillus subtilis and Escherichia coli. Using zone-of-inhibition studies, it was found that E. coli, did not respond to the delivery of Cephalexin either directly or via microparticles. However, for both S. aureus and B. subtilis, the particles showed controlled release of Cephalexin for the duration of 48 h and continued maintenance and even increase in the zone of inhibition. This work demonstrates an effective protocol to prepare antimicrobial patches for controlled drug delivery. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial; Medicinal bandage; Silica microparticles; sustained drug release

Controlling the cell adhesion property of silk films by graft polymerization - Dhyani, Vartika; Singh, Neetu (ACS Applied Materials & Interfaces, 2014)
We report here a graft polymerization method to improve the cell adhesion property of Bombyx mori silk fibroin films. B. mori silk has evolved as a promising material for tissue engineering because of its biocompatibility and biodegradability. However, silk's hydrophobic character makes cell adhesion and proliferation difficult. Also, the lack of sufficient reactive amino acid residues makes biofunctionalization via chemical modification challenging. Our study describes a simple method that provides increased chemical handles for tuning of the surface chemistry of regenerated silk films (SFs), thus allowing manipulation of their bioactivity. By grafting pAAc and pHEMA via plasma etching, we have increased carboxylic acid and hydroxyl groups on silk, respectively. These modifications allowed us to tune the hydrophilicity of SFs and provide functional groups for bioconjugation. Our strategy also allowed us to develop silk-based surface coatings, where spatial control over cell adhesion can be achieved. This control over cell adhesion in a particular region of the SFs is difficult to obtain via existing methods of modifying the silk fibroin instead of the SF surface. Thus, our strategy will be a valuable addition to the toolkit of biofunctionalization for enhancing SFs' tissue engineering applications.
Keywords: Bombyx mori; polymer grafting cell adhesion; silk films

Conversion of hemicellulose using acidic ionic liquids - Dhepe, Paresh Laxmikant; Matsagar, Babasaheb Mansub (WO2015111086 A1, 2014)
The present invention discloses one pot process for the conversion of hemicellulose into C5 sugars using ionic liquids in water media.

Copper(I) bromide-catalyzed carbonylative coupling of aryl halides with phenols, alcohols and amines using sodium cyanide as C-1 source: a synthesis of carboxylic acid derivatives - Prasad, Pragati K.; Sudalai, Arumugam (Advanced Synthesis & Catalysis, 2014)
A new ``carbon monoxide-free'' synthesis of carboxylate derivatives via carbonylative coupling of aryl bromides with phenols, alcohols, amines and acids in the presence of copper(I) bromide as catalyst and sodium cyanide in a stoichiometric amount has been developed. Its intramolecular version provides for the preparation of lactones (e.g., isochroman-1-ones and isobenzfuranones), imides, anhydrides and lactams in excellent yields (73-96%).
Keywords: anhydrides; C-1 building blocks; isochroman-1-ones; lactams; lactones

Correlation of the solid-state reactivities of racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate and its 4,4 `-bipyridine cocrystal with their crystal structures - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Structural Chemistry, 2014)
Racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate, C21H18O8, (1), shows a very efficient intermolecular benzoyl-group migration reaction in its crystals. However, the presence of 4,4 `-bipyridine molecules in its cocrystal, C21H18O8 center dot C10H8N2, (1)center dot BP, inhibits the intermolecular benzoyl-group transfer reaction. In (1), molecules are assembled around the crystallographic twofold screw axis (b axis) to form a helical self-assembly through conventional O-H center dot center dot center dot O hydrogen-bonding interactions. This helical association places the reactive C6-O-benzoyl group (electrophile, El) and the C4-hydroxy group (nucleophile, Nu) in proximity, with a preorganized El center dot center dot center dot Nu geometry favourable for the acyl transfer reaction. In the cocrystal (1)center dot BP, the dibenzoate and bipyridine molecules are arranged alternately through OH center dot center dot center dot N interactions. The presence of the bipyridine molecules perturbs the regular helical assembly of the dibenzoate molecules and thus restricts the solid-state reactivity. Hence, unlike the parent dibenzoate crystals, the cocrystals do not exhibit benzoyl-transfer reactions. This approach is useful for increasing the stability of small molecules in the crystalline state and could find application in the design of functional solids.
Keywords: acyl transfer; cocrystal; crystal structure; design of functional solids; helical assembly; hydrogen bonding; myo-inositol; solid-state reactions

Counter-ion dependent, longitudinal unzipping of multi-walled carbon nanotubes to highly conductive and transparent graphene nanoribbons - Shinde, Dhanraj B.; Majumder, Mainak; Pillai, Vijayamohanan K. (Scientific Reports, 2014)
Here we report for the first time, a simple hydrothermal approach for the bulk production of highly conductive and transparent graphene nanoribbons (GNRs) using several counter ions from K2SO4, KNO3, KOH and H2SO4 in aqueous media, where, selective intercalation followed by exfoliation gives highly conducting GNRs with over 80% yield. In these experiments, sulfate and nitrate ions act as a co-intercalant along with potassium ions resulting into exfoliation of multi-walled carbon nanotubes (MWCNTs) in an effective manner. The striking similarity of experimental results in KOH and H2SO4 that demonstrates partially damaged MWCNTs, implies that no individual K+, SO42- ion plays a key role in unwrapping of MWCNTs, rather this process is largely effective in the presence of both cations and anions working in a cooperative manner. The GNRs can be used for preparing conductive 16 k Omega sq(-1), transparent (82%) and flexible thin films using low cost fabrication method.

Coupled cluster methods for autoionisation resonances - Sajeev, Y.; Ghosh, A.; Vaval, N.; Pal, S. (International Reviews in Physical Chemistry, 2014)
The quantum chemical calculation of autoionisation resonances in many-electron systems is a highly challenging task due to the ionisation continuum involved. Recently, advances were reported where conventionally used ab initio codes can be employed to compute autoionisation resonances. This is made possible by the use of analytical continuation tools such as complex scaling and complex absorbing potential (CAP) in the electronic structure codes. We review the formulation and the use of complex scaling and CAP in coupled cluster methods for the electron correlated calculation of energy position and autoionisation decay rate of resonance states. The application of analytically continued coupled cluster method for the correlated calculation of interatomic or intermolecular Coulombic decay process is also discussed.
Keywords: autoionisation resonances; complex absorbing potential; complex scaling; equation-of-motion coupled cluster; Fock space multi-reference-coupled cluster; intermolecular Coulombic decay

Covalent organic framework thin-films for molecular separation - Dey, Kaushik; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Separation; Thin-films

Covalent organic framework-cadmium sulfide hybrid as a prototype photocatalyst for visible-light-driven hydrogen production - Thote, Jayshri; Aiyappa, Harshitha Barike; Deshpande, Aparna; Diaz, David Diaz; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry A-European Journal, 2014)
CdS nanoparticles were deposited on a highly stable, two-dimensional (2D) covalent organic framework (COF) matrix and the hybrid was tested for photocatalytic hydrogen production. The efficiency of CdS-COF hybrid was investigated by varying the COF content. On the introduction of just 1 wt% of COF, a dramatic tenfold increase in the overall photocatalytic activity of the hybrid was observed. Among the various hybrids synthesized, that with 10 wt% COF, named CdS-COF (90: 10), was found to exhibit a steep H2 production amounting to 3678 mmolh(-1) g(-1), which is significantly higher than that of bulk CdS particles (124 mmolh(-1)g(-1)). The presence of a p-conjugated backbone, high surface area, and occurrence of abundant 2D hetero-interface highlight the usage of COF as an effective support for stabilizing the generated photoelectrons, thereby resulting in an efficient and high photocatalytic activity.
Keywords: charge transfer; covalent organic frameworks; hybrid materials; hydrogen production; Photocatalysis

Covalently anchored 2,4,6-triallyloxy-1,3,5-triazine Pd(II) complex over a modified surface of SBA-15: catalytic application in hydrogenation reaction - Sharma, Priti; Singh, A. P. (RSC Advances, 2014)
Highly efficient and reusable SBA-15-TAT-Pd(II) has been synthesized by anchoring a 2,4,6-triallyloxy-1,3,5-triazine (TAT) complex over the organo-functionalized surface of SBA-15. The physiochemical properties of the organo-functionalized catalyst were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption measurement isotherm, TGA & DTA, solid state C-13, Si-29 NMR spectra, FT-IR, XPS, DRS UV-visible, SEM and TEM. XRD & N-2 sorption were analyzed to find out the textural properties of the synthesized catalyst and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The electronic environment and oxidation state of Pd in SBA-15-TAT-Pd(II) were monitored by XPS and DRS UV-visible techniques. The catalytic activity of the synthesized catalyst SBA-15-TAT-Pd(II) was screened for hydrogenation reactions and shows higher catalytic activity with good turnover numbers (TON) under optimized experimental conditions with maximum conversion (> 99%) and selectivity (100%). The anchored solid catalyst can be recycled efficiently and reused upto five times without major loss in reactivity.

Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction

Cross dimerization of amyloid-beta and alpha synuclein proteins in aqueous environment: a molecular dynamics simulations study - Jose, Jaya C.; Chatterjee, Prathit; Sengupta, Neelanjana (Plos One, 2014)
Self-assembly of the intrinsically unstructured proteins, amyloid beta (A beta) and alpha synclein (alpha Syn), are associated with Alzheimer's Disease, and Parkinson's and Lewy Body Diseases, respectively. Importantly, pathological overlaps between these neurodegenerative diseases, and the possibilities of interactions between A beta and alpha Syn in biological milieu emerge from several recent clinical reports and in vitro studies. Nevertheless, there are very few molecular level studies that have probed the nature of spontaneous interactions between these two sequentially dissimilar proteins and key characteristics of the resulting cross complexes. In this study, we have used atomistic molecular dynamics simulations to probe the possibility of cross dimerization between alpha Syn(1-95) and A beta(1-42), and thereby gain insights into their plausible early assembly pathways in aqueous environment. Our analyses indicate a strong probability of association between the two sequences, with inter-protein attractive electrostatic interactions playing dominant roles. Principal component analysis revealed significant heterogeneity in the strength and nature of the associations in the key interaction modes. In most, the interactions of repeating Lys residues, mainly in the imperfect repeats `KTKEGV' present in alpha Syn(1-95) were found to be essential for cross interactions and formation of inter-protein salt bridges. Additionally, a hydrophobicity driven interaction mode devoid of salt bridges, where the non-amyloid component (NAC) region of alpha Syn(1-95) came in contact with the hydrophobic core of A beta(1-42) was observed. The existence of such hetero complexes, and therefore hetero assembly pathways may lead to polymorphic aggregates with variations in pathological attributes. Our results provide a perspective on development of therapeutic strategies for preventing pathogenic interactions between these proteins.

Crystal engineering principles: fluoroquinolone salts - Dandela, Rambabu; Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: ciprofloxacin; Fluoroquinolone; norfloxacin

Crystal shape evolution using polyhedral population balance - Shaikh, Latif J.; Ranade, Vivek V.; Pandit, Aniruddha B. (Industrial & Engineering Chemistry Research, 2014)
Research on crystal morphology covers shape evolution of single crystal and evolution of the size and shape distribution of populations of crystals. The population balance models have been used for the single or multiple dimensions for predicting the evolution of crystal size distributions (CSDs). More often than not these models do not consider the change in solute concentration due to disappearance/appearance of the crystal faces and therefore compromise rigorous mass balance. The present work focuses on the methodology for the morphological evolution of crystal shape using a polyhedral population balance model. This methodology is based on the morphodrome which illustrates the shapes of crystals at various operating conditions. gPROMS software (PSE, UK) along with Microsoft Excel is used to devise the framework for predicting the crystal shape evolution. The developed approach and models can be implemented for various crystallization systems and will be useful for simulating crystal shape evolutions.

Crystal structure of AtGet3 Delta L, a chloroplast Get3 from Arabidopsis thaliana - Manu, M. S.; Ramasamy, Sureshkumar (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Arabidopsis thaliana; Get3; protein targeting

Crystalline metal-organic frameworks (MOFs): synthesis, structure and function - Dey, Chandan; Kundu, Tanay; Biswal, Bishnu P.; Mallick, Arijit; Banerjee, Rahul (Acta Crystallographica Section B-Structural Science, 2014)
Metal-organic frameworks (MOFs) are a class of hybrid network supramolecular solid materials comprised of organized organic linkers and metal cations. They can display enormously high surface areas with tunable pore size and functionality, and can be used as hosts for a range of guest molecules. Since their discovery, MOFs have experienced widespread exploration for their applications in gas storage, drug delivery and sensing. This article covers general and modern synthetic strategies to prepare MOFs, and discusses their structural diversity and properties with respect to application perspectives.

Crystalline porous materials for gas adsorption - Pal, Tapan Kumar; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; gas adsorption

Crystal-to-crystal thermal phase transformation of polymorphs of isomeric 2,3-naphthalene diol ditoluates: mechanism and implications for molecular crystal formation and melting - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2014)
Isomeric para- (1) and meta- (2) ditoluate derivatives of naphthalene 2,3-diol exhibited polymorphism producing three (Forms 1I, 1II, 1III) and two (Forms 2I, 2II) polymorphs each, respectively, depending on the solvent and conditions of crystallization. Crystal forms 1I, 1II, and 2I could be obtained repeatedly, whereas crystal forms 1III and 2II were obtained (separately) in one of the crystallization experiments, each. All the crystal forms were stable at ambient conditions, except for Form 2II, which disintegrated to a powder over 45 days. In contrast, the ortho-ditoluate (3) of naphthalene 2,3-diol did not exhibit polymorphism; it yielded fibrous chiral crystals from different solvents/conditions. Crystal structure analysis of all these polymorphs revealed dominance of energetically similar weak intermolecular interactions such as CH center dot center dot center dot O, CH center dot center dot center dot pi, pi center dot center dot center dot pi, and their interplay in molecular aggregation resulting in polymorphic modifications. Differential scanning calorimetry (DSC), hot stage microscopy, single crystal and powder X-ray diffraction measurements revealed crystal-to-crystal thermal transformation of Forms 1I and 1II crystals to Form 1III crystals and Form 2II crystals to Form 2I crystals. The transformation of Form 1I and Form 1II crystals to Form 1III crystals can be viewed as progressive destabilization of the crystal lattice during heating and converting to metastable phase, whereas the conversion of Form 2II to Form 2I crystals can be considered as reorganization of an unstable crystalline phase to a stable crystalline phase. Hence comparative studies of the structure of stable, metastable, or transient crystals and crystal-to-crystal transformations involving these forms could aid in unraveling the process of crystallization.

C@SiNW/TiO2 core-shell nanoarrays with sandwiched carbon passivation layer as high efficiency photoelectrode for water splitting - Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Shelke, Manjusha V. (Scientific Reports, 2014)
One-dimensional heterostructure nanoarrays are efficiently promising as high performance electrodes for photo electrochemical (PEC) water splitting applications, wherein it is highly desirable for the electrode to have a broad light absorption, efficient charge separation and redox properties as well as defect free surface with high area suitable for fast interfacial charge transfer. We present highly active and unique photoelectrode for solar H-2 production, consisting of silicon nanowires (SiNWs)/TiO2 core-shell structures. SiNWs are passivated to reduce defect sites and protected against oxidation in air or water by forming very thin carbon layer sandwiched between SiNW and TiO2 surfaces. This carbon layer decreases recombination rates and also enhances the interfacial charge transfer between the silicon and TiO2. A systematic investigation of the role of SiNW length and TiO2 thickness on photocurrent reveals enhanced photocurrent density up to 5.97 mA/cm(2) at 1.0 V vs. NHE by using C@SiNW/TiO2 nanoarrays with photo electrochemical efficiency of 1.17%.

Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.

Culturable bacterial phylogeny from a shallow water hydrothermal vent of espalamaca (Faial, Azores) reveals a variety of novel taxa - Rajasabapathy, Raju; Mohandass, Chellandi; Colaco, Ana; Dastager, Syed Gulam; Santos, Ricardo Serrao; Meena, Ram Murti (Current Science, 2014)
Phylogenetic diversity of the 16S rRNA gene associated with the domain bacteria was examined at the level of operational taxonomic units (OTUs) using the rarefaction analysis from a newly identified shallow water hydrothermal vent, Espalamaca in the Azorean Island Faial (Horta), North Atlantic Ocean. Diluted sea water nutrient agar amended with metals manganese, lead, iron and element sulphur, could help in retrieving highest OTUs (95) from the vent and 39 OTUs from nonvent. Molecular tools implemented on bacterial census indicated the occupancy of gamma-Proteobacteria by 55.78%, alpha-Proteobacteria by 21.05% and 12.63% of Bacteroidetes in the total population. Occurrence of novel species maximized with alpha-Proteobacteria (11/20) followed by Bacteroidetes (5/12) signified the necessity of studying these groups to strengthen the biodiversity database. Shannon index (H') and the Chao I richness estimator illustrated a strong bacterial community in the venting area. The current study confers many bacterial genera which were not reported earlier in any of the shallow water vents and adds 33 new taxa to the database.
Keywords: Bacterial phylogeny; metals; novel taxa; rarefaction analysis; shallow vent

Current research and future perspectives of phytase bioprocessing - Bhavsar, Kavita P.; Khire, Jayant Malhar (RSC Advances, 2014)
Phosphorus is one of nature's paradoxes as it is life's bottleneck for subsistence on earth but at same time is detrimental in surplus quantities in an aquatic environment. Phosphorus cannot be manufactured, though fortunately it can be recovered and reused. The only way to avert a supply crisis is to implement the ``3R's'' of sustainability, ``Reduce, Reuse and Recycle.'' Phytase is likely to play a critical role in the dephosphorylation of antinutritional and indigestible phytate, a phosphorus locking molecule, to digestible phosphorus, calcium and other mineral nutrients in the coming years. Hence, efforts are required to produce cost effective phytase with fast upstream and economic downstream processing because the current available process is expensive and time consuming. This review summarizes the present state of methods studied for phytase bioprocessing. Production, extraction and purification incur a large cost in product development. In addition, the process has several limitations such as dilute concentration of enzyme, extensive downstream procedures and treatment of generated effluents. However, these methods are currently employed due to lack of alternative methods. Thus, there is a clear need for an efficient, scalable and economical process for phytase production and bioseparation, and improvements are especially required with regard to yield, purity, and energy consumption. Perspectives for an improved bioprocess development for phytase are discussed based on our own experience and recent studies. It is argued that the optimization of production techniques, strain improvement and liquid-liquid extraction deserves more attention in the future.

CVD synthesis of graphene nanoplates on MgO support - Jugade, Ravin M.; Sharma, Shalini; Gokhale, Suresh (Materials Science-Poland, 2014)
Synthesis of graphene directly on MgO has been carried out and the structural properties of the obtained material have been investigated. Few-layered graphene was produced by simple thermal decomposition of methane over MgO powder at 950 A degrees C in a CVD reactor. The samples were purified by 10 N HNO3 treatment, and studied by TEM, Raman spectroscopy, EDAX and SEM. TEM clearly indicated the formation of graphene. EDAX showed that the purified sample contained only carbon and no traces of MgO. The characteristic Raman features of graphene were also seen as D-band at 1316 cm(-1), G-band at 1602 cm(-1), and a small 2D-band at 2700 cm(-1) in the Raman spectra. The strong D-band suggests that the graphene possess large number of boundary defects. The small 2D-band indicates the formation of few-layered graphene.
Keywords: graphene; magnesium oxide; nanographene

C. Siva Raman (1923-2014) - Deshpande, Mukund V. (Current Science, 2015)

c Squalene synthase gene from medicinal herb bacopa monniera: molecular characterization, differential expression, comparative modeling, and docking studies - Vishwakarma, Rishi K.; Patel, Krunal; Sonawane, Prashant; Kumari, Uma; Singh, Somesh; Ruby; Shakeel Abbassi; Agrawal, Dinesh C.; Tsay, Hsin-Sheng; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2015)
The widespread pharmaceutically important triterpenoid saponins are synthesized via isoprenoid pathway. The formation of squalene is the key regulatory point in triterpene biosynthesis, catalyzed by squalene synthase (SQS). The present study deals with the detailed characterization of SQS by molecular, biochemical, and computational means from Bacopa monniera, an immensely important medicinal plant rich in triterpenoid saponin, bacosides. A full-length SQS gene was isolated from B. monniera, characterized as B. monniera squalene synthase (BmSQS) (1242 bp) encoding 414 amino acids. Deduced amino acid sequence of BmSQS showed highly conserved consensus aspartate-rich motifs (DXXXD) and catalytic site residues. Phylogenetic analysis showed that BmSQS belongs to dicot group having closest relationship with Salvia miltiorrhiza. Semiquantitative and real-time PCR studies showed that the BmSQS messenger RNA (mRNA) expression level was higher in vegetative parts (roots) as compared to floral parts. Methyl jasmonate induces the BmSQS mRNA expression in all tissues tested, while salicylic acid, cold, and salt induce much higher expression in roots. Homology modeling and docking simulations of BmSQS showed the pivotal roles of Asp77, Asp81, Asp213, Asp217, and Tyr168 in catalysis.
Keywords: Abiotic stress; Bacopa monniera; Comparative modeling and docking; Differential expression; Isoprenoid pathway; Squalene synthase

Calcium phosphate nanocapsule crowned multiwalled carbon nanotubes for pH triggered intracellular anticancer drug release - Banerjee, Shashwat S.; Todkar, Kiran J.; Khutale, Ganesh V.; Chate, Govind P.; Biradar, Ankush V.; Gawande, Manoj B.; Zboril, Radek; Khandare, Jayant J. (Journal of Materials Chemistry B, 2015)
We report calcium phosphate (CaP) nanocapsule crowned multi-walled carbon nanotubes (CNT-GSH-G4-CaP) as a novel platform for intracellular delivery of an anticancer drug. As a proof-of-concept, CNT-GSH-G4-CaP demonstrates release of anticancer drug doxorubicin hydrochloride (DOX) within intracellular lysosomes from the interior cavity of CNT upon pH triggered CaP dissolution. Importantly, we found that the CNT with a CaP nanolid can efficiently prevent untimely drug release at physiological pH but promotes DOX release at increased acidic milieu as observed in subcellular compartments such as lysosomes (similar to 5.0). This ``zero premature release'' characteristic is of clinical significance in delivering cytotoxic drugs, by reducing systemic toxicity and thus beneficial for the effective anticancer treatment. We envision that this pH triggered CaP crowned CNT nanosystem would lead to a new generation of self-regulated platforms for intracellular delivery of a variety of anticancer drugs.

Calculation of P,T-odd interaction constant of PbF using Z-vector method in the relativistic coupled-cluster framework - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2015)
The effective electric field experienced by the unpaired electron in the ground state of PbF, which is a potential candidate in the search of electron electric dipole moment due to some special characteristics, is calculated using Z-vector method in the coupled cluster single-and double-excitation approximation with four component Dirac spinor. This is an important quantity to set the upper bound limit of the electron electric dipole moment. Further, we have calculated molecular dipole moment and parallel magnetic hyperfine structure constant (A(parallel to)) of Pb-207 in PbF to test the accuracy of the wavefunction obtained in the Z-vector method. The outcome of our calculations clearly suggests that the core electrons have significant contribution to the ``atom in compound'' properties. (C) 2015 AIP Publishing LLC.

Can enantiomer ligands produce structurally distinct homochiral MOFs? - Dubey, Mrigendra; Kumar, Ashish; Dhavale, Vishal M.; Kurungot, Sreekumar; Pandey, Daya Shankar (CrystEngComm, 2015)
Here, we report a self-assembled homochiral metal-organic framework [Cu-1.5(H2LL-leu)(Ac)H2O](n)center dot 3H(2)O (1) obtained from an L-leucine-derived ligand (H4L(L-leu)) and Cu(Ac)(2)center dot H2O in a 1 : 1 ratio. Coordination-induced conformational change in the ligand has been monitored by circular dichroism which has been further attested by synthesizing a D-leucine-containing enantiomer H4L D-leu and its Cu(II) complex [Cu-1.5(H2LD-leu)H2O](n)center dot 10H(2)O (2). Structure determination revealed entirely different structures for the homochiral MOFs (1 and 2) obtained from the L/D-leucine-derived enantiomer ligands under analogous reaction conditions. Further, structural dissimilarity in these MOFs has been judicially supported by proton conductance studies. MOF 1 shows higher proton (10(-5) S cm(-1)) conductance in comparison to 2 (10(-6) S cm(-1)) due to dissimilar alignment of the hydrogen-bonded water molecules in the hydrophilic pocket as well as crystal packing.

Can silicon substituted metal-free organic dyes achieve better efficiency compared to silicon free organic dyes? a computational study - Biswas, Abul Kalam; Das, Amitava; Ganguly, Bishwajit (Physical Chemistry Chemical Physics, 2015)
The power conversion efficiency of metal-free organic dyes in dye-sensitized solar cells (DSSCs) is now comparable to ruthenium-based polypyridyl and zinc-based porphyrin dyes. We have computationally investigated the structural, electronic and optical properties of a series of metal free organic dyes and their corresponding silicon substituted dyes. The DFT and TD-DFT calculations revealed that silicon substituted organic dyes have higher efficiency than the corresponding silicon free organic dyes. The computational results showed that the presence of silole units as a spacer group can significantly affect the performance of DSSCs compared to typically using thiophene as a spacer unit. These results corroborate the experimental observations reported in the literature. The time-dependent density functional theory (TDDFT) calculations performed at the CPCM-CAM-B3LYP/6-31+G* level of theory showed better agreement with the experimental absorption spectra of some reported metal free organic dyes having silole in the spacer group compared to other functionals and are employed in this study. Indoline donor based dye 5 showed a much shorter absorption spectrum (absorption peak at 425 nm) and smaller electron injection driving force (Delta G(injection) = -1.77 eV) than the corresponding dye 8 containing silicon substituted indoline as a donor and a silole group as a spacer unit. lambda(max) = 502 nm and Delta G(injection) = -1.82 eV calculated for dye 8 are much larger than the corresponding silicon free dye 5. The silicon based dye 8 helps in achieving a much lower DGregeneration value than 5, which can facilitate the faster electron injection rate from the dye to the semiconductor TiO2. Dye 8 should also have a higher V-oc value compared to other dyes (5-7) due to favourable interaction with the electrolyte (I-/I-3(-)). The higher planarity and better conjugation in dye 8 facilitate the transfer of electrons from the dye molecules to the semiconductor TiO2. The calculations performed with phenyl protecting groups near the silicon center of the dye molecule 8 to diminish the dimerization process showed very similar optical properties as obtained with the corresponding unprotected dye system. The designed julolidine and pyrrolo-indolizine donor based dyes also showed a similar trend as observed for indoline donor based dyes.

Can substituted allenes be highly efficient leaving groups in catalytic processes? a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Journal of Computational Chemistry, 2015)
There is considerable interest presently in the chemistry of allenes. The current computational investigation looks into the possibility of using allenes and their derivatives as leaving groups. As it is well known, leaving groups are significant in catalytic processes for generating the active site. A full quantum mechanical study using density functional theory shows that allenes and their derivatives can function as excellent leaving groups. Indeed, the calculations show that they can be several orders of magnitude more effective than existing ligands for this purpose. The modification of second generation Grubbs' catalysts with these ligands suggests that the allene ligand cases that would be most effective are those having electron withdrawing groups, especially those that have the potential for supramolecular interactions between the substituent groups in the free state. (c) 2015 Wiley Periodicals, Inc.
Keywords: allenes; carbones; Density functional theory; olefin metathesis; supramolecular interactions

Can we shift and/or broaden the catalysis regime towards ambient temperature? - Gopinath, Chinnakonda S.; Roy, Kanak; Nagarajan, Sankaranarayanan (ChemCatChem, 2015)
An attempt was made to shift the temperature regime of oxidation catalysis towards ambient temperatures by employing surface modification (SM) as a handle. Systematic SM of Pd(111) was performed by O-atom diffusion into the subsurfaces. Virgin and modified Pd(111) catalysts were evaluated for CO oxidation. Typical CO poisoning observed on virgin surfaces was partially lifted, and ambient CO oxidation was observed on the modified surfaces. CO oxidation was followed by the molecular beam method and near-ambient pressure (NAP) photoelectron spectroscopy under different pressure regimes. UV valence band spectral analysis of the SM and the CO+O-2 reaction on modified Pd(111) surfaces under NAP conditions demonstrated changes in the electronic structures of the surfaces with a change in surface potential by 0.35eV and directly probed CO2 formation under the reaction conditions. Supported metal catalysts may be subjected to SM and evaluated for a shift in the catalysis regime for many different reactions.
Keywords: heterogeneous catalysis; Oxidation; photoelectron spectroscopy; surface chemistry; surface modification

Carbon dioxide sequestration: influence of porous media on hydrate formation kinetics - Bhattacharjee, Gaurav; Kumar, Asheesh; Sakpal, Tushar; Kumar, Rajnish (ACS Sustainable Chemistry & Engineering, 2015)
In the present study, CO, sequestration by hydrate formation in porous sediments has been discussed. Two siliceous materials with high porosities, pumice and fire hardened red clay (FHRC), have been used as packing materials in a fixed bed setup to study hydrate formation kinetics. The results obtained using the aforementioned materials were compared with those obtained using silica sand and quartz. Carbon dioxide hydrate formation kinetics was studied at 3.0 MPa pressure and 274 K temperature. Two different types of experiments were conducted: (a) using a constant volume of water and (b) maintaining a constant bed height. These experiments were conducted using the different porous media individually as packing materials. It was observed that pumice as the porous medium showed better hydrate formation kinetics resulting in 46 mol % water to hydrate conversion in 5 h. Moreover, kinetics was enhanced with decrease in the bed height of pumice; this suggests that at field scale adaptation of CO, sequestration in geological formations, mass transfer limitations would be significant. The effects of particle size on hydrate formation kinetics were also investigated. It was observed that hydrate formation kinetics was enhanced with decrease in the particle size fraction.
Keywords: Bed height; Gas hydrate; gas uptake; Geological sequestration; Particle size

Carbon nanohorn-derived graphene nanotubes as a platinum-free fuel cell cathode - Unni, SreeKuttan M.; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Puthenpediakkal, Hasna; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Current low-temperature fuel cell research mainly focuses on the development of efficient nonprecious electrocatalysts for the reduction of dioxygen molecule due to the reasons like exorbitant cost and scarcity of the current state-of-the-art Pt-based catalysts. As a potential alternative to such costly electrocatalysts, we report here the preparation of an efficient graphene nanotube based oxygen reduction electrocatalyst which has been derived from single walled nanohorns, comprising a thin layer of graphene nanotubes and encapsulated iron oxide nanopartides (FeGNT). FeGNT shows a surface area of 750 m(2)/g, which is the highest ever reported among the metal encapsulated nanotubes. Moreover, the graphene protected iron oxide nanoparticles assist the system to attain efficient distribution of Fe-N-x and quaternary nitrogen based active reaction centers, which provides better activity and stability toward the oxygen reduction reaction (ORR) in acidic as well as alkaline conditions. Single cell performance of a proton exchange membrane fuel cell by using FeGNT as the cathode catalyst delivered a maximum power density of 200 mW cm(-2) with Nafion as the proton exchange membrane at 60 degrees C. The facile synthesis strategy with iron oxide encapsulated graphitic carbon morphology opens up a new horizon of hope toward developing Pt-free fuel cells and metal-air batteries along with its applicability in other energy conversion and storage devices.
Keywords: carbon nanohorns; carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction

Carbon-carbon bond forming reactions: application of covalently anchored 2,4,6-triallyloxy-1,3,5-triazine (TAT) Pd(II) complex over modified surface of SBA-15 to Heck, Suzuki, Sonogashira and Hiyama cross coupling reactions - Singh, Chandani; Jawade, Kiran; Sharma, Priti; Singh, Anand P.; Kumar, Pradeep (Catalysis Communications, 2015)
A highly active SBA-15-TAT-Pd(II) catalyst was synthesized from organofunctionalized SBA-15 and 2,4,6-triallyloxy-1,3,5-triazine. The catalyst was employed in carrying out Heck, ``copper-free'' Sonogashira, Suzuki and Hiyama cross coupling reactions. Under the optimized conditions the catalyst displays excellent catalytic activity in delivering the desired products in good to excellent yields. The catalytic system exhibited superior activity regarding the time taken for the completion of reaction, isolation, Pd loading (0.62 mmol%) and yields of products as compared to the earlier reported heterogeneous SBA-15 anchored Pd catalysts. The catalyst could be recycled and reused for five times without any appreciable loss of catalytic activity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heck; Hiyama; SBA-15-TAT-Pd(II) catalyst; Sonogashira; Suzuki

Carboxymethyl cellulose based multifunctional targeted drug delivery platform for pancreatic cancer: nanotheranostic potential and biocompatibility analysis - Joshi, Preeti Nigam; Wangnoo, Shishanka; Louis, Michelle (World Journal of Pharmaceutical Sciences, 2015)

Catalyst-dependent selectivity in the relay catalytic branching cascade - Bansode, Avinash H.; Shaikh, Aslam C.; Kavthe, Rahul D.; Thorat, Shridhar; Gonnade, Rajesh G.; Patil, Nitin T. (Chemistry-A European Journal, 2015)
The synthesis of small organic molecules as probes for discovering new therapeutic agents has been an important aspect of chemical biology. One of the best ways to access collections of small molecules is to use various techniques in diversity-oriented synthesis (DOS). Recently, a new form of DOS, namely relay catalytic branching cascades (RCBCs), has been introduced, wherein a common type of starting material reacts with several scaffold-building agents (SBAs) to obtain structurally diverse molecular scaffolds under the influence of catalysts. Herein, the RCBC reaction of a common type of substrate with SBAs is reported to give two different types of molecular scaffolds and their formation is essentially dependent on the type of catalyst used.
Keywords: alkynols; cascade synthesis; chemoselectivity; diversity-oriented synthesis; Homogeneous catalysis

Catalytic conversion of furfural to industrial chemicals over supported Pt and Pd catalysts - Bhogeswararao, Seemala; Srinivas, D. (Journal of Catalysis, 2015)
Several industrial chemicals were prepared by hydrogenation of furfural over gamma-Al2O3-supported Pt and Pd catalysts. These catalysts were active even at room temperature (25 degrees C). While the Pt catalysts were selective for C=O hydrogenation (yielding furfuryl alcohol), Pd facilitated ring hydrogenation (producing tetrahydrofurfuryl alcohol). At high temperature (240 degrees C), the Pd catalyst exhibited excellent decarbonylation activity forming furan with 85% yield. The catalyst was reusable even in the absence of external hydrogen. The presence of hydrogen led to ring-opened products. Furan was quantitatively converted at 25 degrees C to tetrahydrofuran. Acidity of the support made a marked influence on the activity and selectivity. Pt on SO4-ZrO2 favored hydrogenolysis yielding 2-methyl furan along with furan with >75 wt% selectivity. Particle size, metal dispersion, and solvent influenced catalytic activity. Differences in structure and mode of furfural adsorption were also the causes for variations in selectivity of these supported Pt and Pd catalysts. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Biomass to fuels and chemicals; Decarbonylation; furfural; Hydrogenation; Hydrogenolysis; Supported Pt and Pd catalysts

Catalytic upgrading of citric acid to environmental friendly tri-butyl citrate plasticizer over ultra stable phosphonated Y zeolite - Nandiwale, Kakasaheb Y.; Gogoi, Pranjal; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
The catalytic synthesis of non-toxic/eco-friendly tributyl citrate (TBC) plasticizer by esterification of renewable citric acid (CA) with butanol would be completely sustainable route. In this context, catalytic performance of parent ultra stable Y (USY) and phosphonated USY catalysts were investigated for TBC synthesis. Parent USY and phosphonated USY catalysts were characterized by powder X-ray diffraction (XRD), N-2 adsorption-desorption, NH3 temperature programmed desorption (TPD), pyridine-Fourier Transform Infrared Spectroscopy (FTIR), FTIR, SEM, ICP. The influence of various process parameters such as phosphorous (P) loading (0 to 4 wt/%), catalyst loading (5-25%), molar ratio of CA to n-butanol (1:4 to 1:12), reaction temperature (383-423 K) and reaction time (1-5 h) have been investigated over USY catalyst with aim to maximize CA conversion and TBC yield. Amongst the studied catalysts, the 2% (w/w) P/USY was found to be highly potential catalyst with complete CA conversion (100%) and 93% TBC yield. The present method of using 2% (w/w) P/USY catalyst for the synthesis of TBC would be environmentally benign in the context of bio-renewable synthetic route, high catalytic activity, non-toxic product, long term stability and reusability of catalyst (five catalytic cycles). (c) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved,
Keywords: Butanol; Citric acid; heterogeneous catalysis; Plasticizer; Tributyl citrate

Cathepsins of lepidopteran insects: aspects and prospects - Saikhedkar, Nidhi; Summanwar, Aarohi; Joshi, Rakesh S.; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2015)
Molecular understanding of lepidopteran physiology has revealed that proteases consist of one of the central regulatory/reacting system for insect growth and survival. Among the various proteases, cathepsins are the most crucial cellular proteases, which play vital roles during insect development. In the present review, we have discussed various aspects of the lepidopteran insect cathepsins, emphasizing their roles in processes like development, growth, metamorphosis, apoptosis and immunity. Cathepsins are categorized into different types on the basis of their sequence diversification, leading to variation in structure and catalytic function. Cathepsins exhibit tissue and stage specific expression pattern which is fine-tuned by a delicate balance of expression, compartmentalization, zymogen activation, inhibition by protein inhibitors and degradation. The indispensability of cathepsins as cellular proteases in the above mentioned processes proposes them as novel targets for designing effective and specific insect controlling strategies. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Apoptosis; Cathepsin; Cysteine/aspartate protease; Development; Lepidoptera; Pest control; Stress response

Cationic photopolymerization kinetics of neat coating formulations involving poly(propylene glycol) diglycidyl ether and glycerol diglycidyl ether - Harikrishna, Reghunathan (Journal of Thermal Analysis and Calorimetry, 2015)
Kinetic analysis of formulations based on poly(propylene glycol) diglycidyl ether and glycerol diglycidyl ether was carried out using photodifferential scanning calorimeter. The effects of formulation monomer ratios at different temperatures were studied as photocalorimetric optimization studies of formulation ratios involving diglycidyl ethers are less reported. The nature of cure was found to depend more on the in situ physical parameters rather than on the mechanism of the reaction. The variations in the observed kinetic parameters can be related to interplay of mobility of reactive species, distance of counter ion and the diffusional restrictions. The final conversion was found to increase with increase in poly(propylene glycol) diglycidyl ether content, while the thermal stability increased with an increase in glycerol diglycidyl ether content. Autocatalytic kinetic model was also evaluated, and the system underwent early gelation. The studies show that the intermediate formulations are promising compositions for surface-coating applications.
Keywords: Coatings; Diglycidyl ether; kinetics; PhotoDSC; Photopolymerization

Cations and dications of heavier group 14 elements in low oxidation states - Swamy, V. S. V. S. N.; Pal, Shiv; Khan, Shabana; Sen, Sakya S. (Dalton Transactions, 2015)
Cations and dications of heavier group 14 elements in their low oxidation state have received widespread attention in recent years. The journey started with the isolation of a series of cations of the composition [(C5Me5)E:](+) [E = Si-Pb], followed by the more recent isolation of a Ge(II) dication encapsulated within a cryptand, a carbodiphosphorane stabilized [GeCl](+) monocation with a two coordinate Ge atom, Si(II) cations and dications stabilized by N-heterocyclic carbenes (NHCs), which highlights the ongoing growth and interest in the chemistry of tetrel(II) cations. This is presumably because the central atom (E) in these compounds contains two or three unoccupied valence orbitals as well as holds a lone pair of electrons. Such an electronic description represents ambiphilicity, which is of great interest for catalysis. The successful synthesis of divalent group 14 cations requires new synthetic strategies based on the sterically demanding neutral or monoanionic ligands, utilization of counter anions, and solvents with low nucleophilicity in order to minimize the degree of interactions with the cations. An alternative approach for the realization of divalent cations of group 14 elements is their coordination to the transition metals. This synthetic approach was successfully applied for the isolation of a range of transition metal coordinated divalent cations of group 14 elements. Apart from arousing academic interest some of these cations have found application as activators in the Ziegler-Natta polymerization of alkenes.

Cell line development for biomanufacturing processes: recent advances and an outlook - Le, Huong; Vishwanathan, Nandita; Jacob, Nitya M.; Gadgil, Mugdha; Hu, Wei-Shou (Biotechnology Letters, 2015)
At the core of a biomanufacturing process for recombinant proteins is the production cell line. It influences the productivity and product quality. Its characteristics also dictate process development, as the process is optimized to complement the producing cell to achieve the target productivity and quality. Advances in the past decade, from vector design to cell line screening, have greatly expanded our capability to attain producing cell lines with certain desired traits. Increasing availability of genomic and transcriptomic resources for industrially important cell lines coupled with advances in genome editing technology have opened new avenues for cell line development. These developments are poised to help biosimilar manufacturing, which requires targeting pre-defined product quality attributes, e.g., glycoform, to match the innovator's range. This review summarizes recent advances and discusses future possibilities in this area.
Keywords: Biomanufacturing; Biosimilars; Cell line development; CHO cells genomics; Genome editing; Transcriptomics

Cell scale host-pathogen modeling: another branch in the evolution of constraint-based methods - Jamshidi, Neema; Raghunathan, Anu (Frontiers in Microbiology, 2015)
Constraint-based models have become popular methods for systems biology as they enable the integration of complex, disparate datasets in a biologically cohesive framework that also supports the description of biological processes in terms of basic physicochemical constraints and relationships. The scope, scale, and application of genome scale models have grown from single cell bacteria to multi cellular interaction modeling; host-pathogen modeling represents one of these examples at the current horizon of constraint-based methods. There are now a small number of examples of host-pathogen constraint-based models in the literature, however there has not yet been a definitive description of the methodology required for the functional integration of genome scale models in order to generate simulation capable host-pathogen models. Herein we outline a systematic procedure to produce functional host-pathogen models, highlighting steps which require debugging and iterative revisions in order to successfully build a functional model. The construction of such models will enable the exploration of host-pathogen interactions by leveraging the growing wealth of omic data in order to better understand mechanism of infection and identify novel therapeutic strategies.
Keywords: constraint-based model; flux balance analysis; host-pathogen; mathematical models; omics-technologies; optimization methods; salmonella typhimurium; tuberculosis

Characterization of 10-hydroxygeraniol dehydrogenase from catharanthus roseus reveals cascaded enzymatic activity in iridoid biosynthesis - Krithika, Ramakrishnan; Srivastava, Prabhakar Lal; Rani, Bajaj; Kolet, Swati P.; Chopade, Manojkumar; Soniya, Mantri; Thulasiram, Hirekodathakallu V. (Scientific Reports, 2015)
Catharanthus roseus [L.] is a major source of the monoterpene indole alkaloids (MIAs), which are of significant interest due to their therapeutic value. These molecules are formed through an intermediate, cis-trans-nepetalactol, a cyclized product of 10-oxogeranial. One of the key enzymes involved in the biosynthesis of MIAs is an NAD(P)(+) dependent oxidoreductase system, 10-hydroxygeraniol dehydrogenase (Cr10HGO), which catalyses the formation of 10-oxogeranial from 10-hydroxygeraniol via 10-oxogeraniol or 10-hydroxygeranial. This work describes the cloning and functional characterization of Cr10HGO from C. roseus and its role in the iridoid biosynthesis. Substrate specificity studies indicated that, Cr10HGO has good activity on substrates such as 10-hydroxygeraniol, 10-oxogeraniol or 10-hydroxygeranial over monohydroxy linear terpene derivatives. Further it was observed that incubation of 10-hydroxygeraniol with Cr10HGO and iridoid synthase (CrIDS) in the presence of NADP(+) yielded a major metabolite, which was characterized as (1R, 4aS, 7S, 7aR)-nepetalactol by comparing its retention time, mass fragmentation pattern, and co-injection studies with that of the synthesized compound. These results indicate that there is concerted activity of Cr10HGO with iridoid synthase in the formation of (1R, 4aS, 7S, 7aR)-nepetalactol, an important intermediate in iridoid biosynthesis.

Charge-switchable gold nanoparticles for enhanced enzymatic thermostability - Shankar, Shiv; Soni, Sarvesh K.; Daima, Hemant K.; Selvakannan, P. R.; Khire, Jayant Malhar; Bhargava, Suresh Kumar; Bansal, Vipul (Physical Chemistry Chemical Physics, 2015)
This study illustrates a facile strategy for efficient immobilization of enzymes on a metal nanoparticle surface. The strategy proposed here enables the enzymatic activity to be retained while increasing the enzyme thermostability. It is demonstrated that the use of a zwitterionic amino acid tyrosine as a reducing and capping agent to synthesise gold nanoparticles allows efficient immobilization of phytase enzyme through charge-switchable electrostatic interactions. The detailed kinetic and thermodynamic studies reveal that the proposed enzyme immobilization strategy improves the overall quality of phytase by reducing the activation energy required for substrate hydrolysis and broadening the temperature window in which immobilized enzyme is able to operate. The outcomes of this study indicate that the underlying zwitterionic nature of 20 natural amino acids along with significant variability in their isoelectric points and hydropathy indices as well the ability of some of the amino acids to reduce metal ions is likely to offer significant opportunities for tailoring nano-bio interfaces in a rational manner for a range of biological applications.

Chemical and biological metal nanoparticles as antimycobacterial agents: a comparative study - Singh, Richa; Nawale, Laxman U.; Arkile, Manisha A.; Shedbalkar, Utkarsha U.; Wadhwani, Sweety A.; Sarkar, Dhiman; Chopade, Balu Ananda (International Journal of Antimicrobial Agents, 2015)
Resistance among mycobacteria leading to multidrug-resistant and extensively drug-resistant tuberculosis is a major threat. However, nanotechnology has provided new insights in drug delivery and medicine development. This is the first comparative report to determine the activity of chemically and biologically synthesised silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) against mycobacteria. Screening data revealed the high mycobactericidal efficiency of AgNPs, with minimum inhibitory concentrations (MICs) of <3 mu g/mL, whereas no such activity was exhibited by AuNPs at concentrations up to 100 mu g/mL. Moreover, in vitro and ex vivo THP-1 infection model assays showed greater efficacy of chemical AgNPs compared with biogenic AgNPs to inhibit active and dormant stage mycobacterial growth. Up to 40% cytotoxicity against human cell lines was observed at a AgNP concentration of 10 x MIC (30 mu g/mL) after 48 h. AgNPs were shown to have more specificity towards mycobacteria than towards other Gram-negative and Gram-positive pathogenic bacteria. The selectivity index was found to be in the range of 11-23, indicating the potential of these nanoparticles for use in developing new therapeutics for tuberculosis. (C) 2015 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.
Keywords: Antibiotic resistance; Antimycobacterial agent; Cytotoxicity; Mycobacteria; Nanoparticles; tuberculosis

Chemical sensing in two dimensional porous covalent organic nanosheets - Das, Gobinda; Biswal, Bishnu P.; Kandambeth, Sharath; Venkatesh, V.; Kaur, Gagandeep; Addicoat, Matthew A.; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Chemical Science, 2015)
Two new imide-based crystalline, porous, and chemically stable covalent organic frameworks (COFs) (TpBDH and TfpBDH) have been successfully synthesized employing solvothermal crystallization route. Furthermore, thin layered covalent organic nanosheets (CONs) were derived from these bulk COFs by the simple liquid phase exfoliation method. These 2D CONs showcase increased luminescence intensity compared to their bulk counterparts (COFs). Notably, TfpBDH-CONs showcase good selectivity and prominent, direct visual detection towards different nitroaromatic analytes over TpBDH-CONs. Quite interestingly, TfpBDH-CONs exhibit a superior ``turn-on'' detection capability for 2,4,6-trinitrophenol (TNP) in the solid state, but conversely, they also show a ``turn-off'' detection in the dispersion state. These findings describe a new approach towards developing an efficient, promising fluorescence chemosensor material for both visual and spectroscopic detection of nitroaromatic compounds with very low [10(-5) (M)] analyte concentrations.

Chemical utilisation of CO2 a challenge for the sustainable world - Jagadeesan, Dinesh; Joshi, Bhaskar; Parameswaran, Prashant (Resonance, 2015)
We derive more than 80% of our energy and chemicals from fossil fuels such as oil, coal and natural gas. Depleting resources and environmental pollution are forcing us to look for alternative resources. Carbon dioxide (CO2), which is produced in large quantities, could be recycled to chemical feedstocks.

Chemically chargeable photo battery - Thimmappa, Ravikumar; Paswan, Bhuneshwar; Gaikwad, Pramod; Devendrachari, Mruthyunjayachari Chattanahalli; Kotresh, Harish Makri Nimbegondi; Mohan, Ramsundar Rani; Alias, Joy Pattayil; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry C, 2015)
Here we show a surrogate strategy for power production, wherein light is used to actuate a discharge Chemistry in the cathode of an aqueous rechargeable battery (ARB). The proposed photo battery consists of a titaninm nitride photoanode, promising. cathode:material iron(III) hexacyanoferrate(II) as the battery active species, and Na2S2O8 as the chemical charging agent The photo battery delivered negligible capacity in the dark and the capacity shot up to 77.8 mAh/g when artificially shined light, confirming that the battery chemistry is light driven. In the ambient light, the device retained 72% of its artificial light discharge capacity with a stable cycling for more than 100 cycles. Further, an unprecedented means for charging the battery rapidly is presented using Na2S2O8 and it revitalized the battery in 30 s without any external bias. This methodology of expending a photoanode extends to a battery that is free from dissolution of active materials, irreversible structural changes, spontaneous deinsertion reactions, and safety concerns commonly encountered in the state of the art anode materials in ARBs. Apart from bringing out a sustainable way for power production, this device opens up avenues for charging the battery in the likely events of electrical input unavailability, while solving the critcial issues of longer charging time and higher charging voltage.

Chemically grafted graphite nanosheets dispersed in poly(ethylene-glycol) by gamma-radiolysis for enhanced lubrication - Gupta, Bhavana; Panda, Kalpataru; Kumar, Niranjan; Melvin, Ambrose A.; Dash, Sitaram; Tyagi, Ashok Kumar (RSC Advances, 2015)
Graphite nanosheets (Gr-NS) dispersed in poly(ethylene-glycol) (PEG200) medium were subjected to various doses of gamma-irradiation. Hydroxyl functional groups present in PEG are chemically grafted through hydrogen bonding with hydroxyl, carbonyl and carboxylic groups of Gr-NS. The grafting process is driven by the generation of active radicals from solvent radiolysis. Chemical grafting was investigated using X-ray photoelectron spectroscopy (XPS) and Fourier transform infra-red (FTIR) spectroscopy. The results of spectroscopic studies revealed reduction in oxygen functionality of PEG-Gr-NS at higher doses of gamma-irradiation. The gamma-irradiation not only bridges the functionalities between PEG and PEG-Gr-NS but edge and basal plane defects in Gr-NS are further reduced as is evident from Raman analysis. The inter-planar sheet distance in Gr-NS is increased due to intercalated chemical grafting with PEG molecules. The chemical grafting between PEG and Gr-NS and reduction in defects enhance the tribological properties with a decrease of 26% and 32% for the friction coefficient and wear, respectively as compared to PEG alone. The lubrication mechanism is mediated through inter-planar weak forces when PEG is chemically grafted with Gr-NS. The electrostatic interaction of PEG with Gr-NS acts as a molecular bridge thus enhancing the sustainability of tribo-stress. Additionally, in the presence of functionalized PEG-Gr-NS tribo-contact conditions, evidence of deposited graphitic tribo-film was observed from micro-Raman spectroscopy inside the steel wear track. This film further enhanced lubrication mediated through low shear strength interlayer graphite sheets and therefore, antiwear properties were synergistically improved.

Chemically reduced organic small-molecule-based lithium battery with improved efficiency - Bhosale, Manik E.; Krishnamoorthy, Kothandam (Chemistry of Materials, 2015)
Organic lithium batteries are attractive because of the possibility of fabricating lightweight and flexible devices. However, the organic lithium batteries have a few drawbacks. The specific capacity is usually lower than the theoretical capacity, which further decreases upon cycling. Often, the specific capacity is very low compared to theoretical capacity while discharging the battery at moderate and high C rates. To circumvent this issue, we chemically reduced carboxylic acid functionality substituted perylene diimide (benzoic-PDI) with hydrazine. Indeed, we found that the rate of redox reaction as well as the conductivity of the benzoic-PDI increased upon chemical reduction. The battery comprising reduced benzoic-PDI exhibits 100% Coulombic efficiency and specific capacity while discharging at 20C. The battery also exhibits very high specific energy (213 Wh/kg) and specific power (8548 W/kg). The control experiments confirm our hypothesis of using chemical reduction to improve the performance of organic lithium battery.

Chemoenzymatic collective synthesis of optically active hydroxyl(methyl)tetrahydronaphthalene-based bioactive terpenoids - Batwal, Ramesh U.; N. P. Argade (Organic & Biomolecular Chemistry, 2015)
Starting from succinic anhydride and 2-methylanisole, a chemoenzymatic collective formal/total synthesis of several optically active tetrahydronaphthalene based bioactive natural products has been presented via advanced level common precursors; the natural product and antipode (-)/(+)-aristelegone B. Regioselective benzylic oxidations, stereoselective introduction of hydroxyl groups at the alpha-position of ketone moiety in syn-orientation, efficient enzymatic resolutions with high enantiomeric purity, stereoselective reductions, samarium iodide induced deoxygenations and tandem acylation-Wittig reactions without racemization and/or eliminative aromatization were the key features. An attempted diastereo-selective synthesis of (+/-)-vallapin has also been described.

Chemoinformatics approach for building molecular networks from marine organisms - Karthikeyan, Muthukumarasamy; Nimje, Deepika; Pahujani, Rakhi; Tyagi, Kushal; Bapat, Sanket; Vyas, Renu; Padmakumar, Krishna Pillai (Combinatorial Chemistry & High Throughput Screening, 2015)
Natural products obtained from marine sources are considered to be a rich and diverse source of potential drugs. In the present work we demonstrate the use of chemoinformatics approach for the design of new molecules inspired by molecules from marine organisms. Accordingly we have assimilated information from two major scientific domains namely chemoinformatics and biodiversity informatics to develop an interactive marine database named MIMMO (Medicinally Important Molecules from Marine Organisms). The database can be queried for species, molecules, scaffolds, drugs, diseases and associated cumulative biological activity spectrum along with links to the literature resources. Molecular informatics analysis of the molecules obtained from MIMMO was performed to study their chemical space. The distinct skeletal features of the biologically active compounds isolated from marine species were identified. Scaffold molecules and species networks were created to identify common scaffolds from marine source and drug space. An analysis of the entire molecular data revealed a unique list of around 2000 molecules from which ten most frequently occurring distinct scaffolds were obtained.
Keywords: Chemoinformatics; Drug design; marine; virtual library

ChemScreener: a distributed computing tool for scaffold based virtual screening - Karthikeyan, Muthukumarasamy; Pandit, Deepak; Vyas, Renu (Combinatorial Chemistry & High Throughput Screening, 2015)
In this work we present ChemScreener, a Java-based application to perform virtual library generation combined with virtual screening in a platform-independent distributed computing environment. ChemScreener comprises a scaffold identifier, a distinct scaffold extractor, an interactive virtual library generator as well as a virtual screening module for subsequently selecting putative bioactive molecules. The virtual libraries are annotated with chemophore-, pharmacophore- and toxicophore-based information for compound prioritization. The hits selected can then be further processed using QSAR, docking and other in silico approaches which can all be interfaced within the ChemScreener framework. As a sample application, in this work scaffold selectivity, diversity, connectivity and promiscuity towards six important therapeutic classes have been studied. In order to illustrate the computational power of the application, 55 scaffolds extracted from 161 anti-psychotic compounds were enumerated to produce a virtual library comprising 118 million compounds (17 GB) and annotated with chemophore, pharmacophore and toxicophore based features in a single step which would be non-trivial to perform with many standard software tools today on libraries of this size.
Keywords: Scaffold extraction; therapeutic category; virtual library generation; virtual screening

Chiral aziridine ring opening: facile synthesis of (R)-modletine and (R)-phenoxybenzamine hydrochloride - Viswanadh, N.; Velayudham, R.; Jambu, S.; Sasikumar, M.; Muthukrishnan, Murugan (Tetrahedron Letters, 2015)
A simple and efficient synthesis of chiral drugs (R)-mexiletine 1, an anti-arrhythmic drug and (R)-phenoxybenzamine hydrochloride 2, an anti-hypertensive drug has been described via controlled reductive ring opening of chiral aziridine as a key step. The target compounds 1 and 2 were obtained in overall yields of 34% and 10.5%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Aziridine; Mexiletine; Phenoxybenzamine

Chiral pool approach for the synthesis of functionalized amino acids: synthesis of antiepileptic drug (R)-lacosamide - Aratikatla, Eswar K.; Bhattacharya, Asish K. (Tetrahedron Letters, 2015)
An efficient total synthesis of (R)-lacosamide 1 has been achieved from N-Boc-N,O-isopropylidene-l-serinol 2 which could easily be obtained from natural l-serine. Our synthesis of 1 starting from 2 using chiral pool strategy resulted in 54% overall yield.

Chirality induction and chiron approaches to enantioselective total synthesis of alpha-lipoic acid - Chavan, Subhash P.; Pawar, Kailash P.; Praveen, Ch; Patil, Niteen B. (Tetrahedron, 2015)
An efficient, short and convenient asymmetric synthesis of (R)-(+)-lipoic acid in seven steps from chiral hydroxy aldehyde with 32.5% overall yield is described. Synthesis of S and R enantiomers of a-lipoic acid from cis-1,4-butene diol derived chiral lactone is reported with 34 % overall yield. The present synthesis involves use of simple reaction conditions making it a convenient synthesis. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool; Chirality induction; enantioselective; Lipoic acid; sharpless asymmetric dihydroxylation

Chromerid genomes reveal the evolutionary path from photosynthetic algae to obligate intracellular parasites - Woo, Yong H.; Ansari, Hifzur; Otto, Thomas D.; Klinger, Christen M.; Kolisko, Martin; Michalek, Jan; Saxena, Alka; Shanmugam, Dhanasekaran; Tayyrov, Annageldi; Veluchamy, Alaguraj; Ali, Shahjahan; Bernal, Axel; et al. (Elife, 2015)
The eukaryotic phylum Apicomplexa encompasses thousands of obligate intracellular parasites of humans and animals with immense socio-economic and health impacts. We sequenced nuclear genomes of Chromera velia and Vitrella brassicaformis, free-living non-parasitic photosynthetic algae closely related to apicomplexans. Proteins from key metabolic pathways and from the endomembrane trafficking systems associated with a free-living lifestyle have been progressively and non-randomly lost during adaptation to parasitism. The free-living ancestor contained a broad repertoire of genes many of which were repurposed for parasitic processes, such as extracellular proteins, components of a motility apparatus, and DNA-and RNA-binding protein families. Based on transcriptome analyses across 36 environmental conditions, Chromera orthologs of apicomplexan invasion-related motility genes were co-regulated with genes encoding the flagellar apparatus, supporting the functional contribution of flagella to the evolution of invasion machinery. This study provides insights into how obligate parasites with diverse life strategies arose from a once free-living phototrophic marine alga.

Citrate modified beta-cyclodextrin functionalised magnetite nanoparticles: a biocompatible platform for hydrophobic drug delivery - Jayaprabha, Kunnoth N.; Joy, Pattayil Alias (RSC Advances, 2015)
Water-dispersible magnetite nanoparticles functionalized with citric acid (CIT) modified beta-cyclodextrin (CD) are prepared and curcumin (CUR) is loaded inside the cavity of CD. The CUR loading capacity of CD-CIT functionalized magnetite nanoparticles is found to be much larger than that of CD alone as well as the CD-CIT conjugate. The release profile of curcumin is found to follow zero order kinetics at the physiological pH, and thus, can release CUR at a constant rate, after the initial burst release. Relaxivity studies using NMR showed that the functionalized nanoparticles are suitable for contrast enhancement in MRI. Thus, the water-dispersible, CIT modified beta-CD functionalized magnetite nanofluid is an efficient carrier for water insoluble curcumin, and can be used for magnetic drug targeting/delivery as well as for contrast enhancement in MRI due to the superparamagnetic magnetite core.

Citreicella manganoxidans sp nov., a novel manganese oxidizing bacterium isolated from a shallow water hydrothermal vent in Espalamaca (Azores) - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A Gram-stain negative, non-motile, non-spore forming, aerobic and rod or narrow lemon-shaped bacterial strain, VSW210(T), was isolated from surface seawater in a shallow water hydrothermal vent region in Espalamaca (Azores). Strain VSW210(T) was found to grow optimally at 30 A degrees C, at pH 7 and in the presence of 2-6 % (w/v) NaCl. A neighbour-joining phylogenetic tree based on 16S rRNA gene sequences revealed that strain VSW210(T) clusters with the type strain Citreicella marina CK-I3-6(T) (sequence similarity value of 99.6 %), but DNA-DNA hybridization showed DNA-DNA relatedness between the strain VSW210(T) and C. marina CK-I3-6(T) to be 55.8 +/- A 3.2 %. The DNA G+C content of strain VSW210(T) was determined to be 67.4 mol%. The cellular fatty acid profiles of strain VSW210(T) was found to contain C-18:1 omega 7c (80.1 %) and C-16:0 (9.2 %). The major polar lipids in strain VSW210(T) were identified as phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and an unidentified phospholipid. Strain VSW210(T) was found to be able to oxidize soluble Mn(II) to insoluble MnO2, which was confirmed with LBB staining. Differential phenotypic properties and genetic uniqueness revealed that this strain VSW210(T) is distinguishable from other species of the genus Citreicella. On the basis of the data presented, strain VSW210(T) is considered to represent a novel species of the genus Citreicella, for which the name Citreicella manganoxidans sp. nov. is proposed. The type strain is VSW210(T) (=KCTC 32497(T) = MCC 2286(T)).
Keywords: Azores; Citreicella manganoxidans sp nov; Hydrothermal vent; Polyphasic taxonomy; Seawater

Clerodane type diterpene as a novel antifungal agent from polyalthia longifolia var. pendula - Bhattacharya, Asish K.; Chand, Hemender R.; John, Jyothis; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2015)
Bioactivity-guided chemical examination of methanolic extract of leaves of Polyalthia longifolia var. pendula led to the isolation of the active constituent, a diterpene 1 which was identified as 16α-hydroxycleroda-3,13(14)Z-dien-15,16-olide on the basis of its spectral data. Among the tested strains, diterpene 1 was found to exhibit antifungal activities having MIC90 values of 50.3, 100.6 and 201.2 μM against Candida albicans NCIM3557, Cryptococcus neoformans NCIM3542 (human pathogens) and Neurospora crassa NCIM870 (saprophyte), respectively. Initial, structure–activity-relationship (SAR) data generated by synthesizing some derivatives revealed that the double bond between C3–C4 and the free hydroxyl group at C16 are crucial for the antifungal activity of the diterpene 1. The mode of action of 1 in C. albicans is due to compromised cell membrane permeability and also probably due to disruption of cell wall structures. The red blood cell haemolysis of all the compounds (1–4) did not show any significant haemolysis and was found to be less than 15% for all the compounds when tested at highest concentration, i.e. 1200 μM. Interestingly, all the tested compounds inhibited Y–H transition in dimorphic C. albicans NCIM3557 at much lower concentration than their MIC90 values. Determination of ROS generation by diterpene 1 using DCFH-DA and DHR123 (dihydrorhodamine) staining of C. albicans NCIM3557 indicated production of intracellular ROS as a mechanism of antifungal activity.
Keywords: Diterpene; Polyalthia longifolia; Isolation; Flash chromatography; Natural products; Antifungal activity

Cloning, expression and in silico studies of a serine protease from a marine actinomycete (Nocardiopsis sp NCIM 5124) - Rohamare, Sonali; Gaikwad, Sushama M.; Jones, Dafydd; Bhavnani, Varsha; Pal, Jayanta; Sharma, Ranu; Chatterjee, Prathit (Process Biochemistry, 2015)
A serine protease (N. protease), from Nocardiopsis sp., was cloned and expressed in Escherichia coli and investigated for its potential kinetic stability. Protein expression using two vectors, pET-22b (+) and pET-39b (+) was compared based on proper folding and soluble expression of the protein. pET-39b (+) was found to be a better vector for soluble expression of this protease containing disulfide bonds. In silico studies were also carried out for N. protease. Homology modeling suggested N. protease to be a member of PA clan of proteases. The phylogenetic analysis showed relatedness of N. protease to kinetically stable proteases. Molecular docking studies performed exhibited interaction of a peptide substrate with catalytic pocket of the enzyme. High temperature MD simulations were performed on N. protease to study its unfolding behavior and comparisons were made with alpha LP. A novel approach to study `cooperativity' of protein unfolding was undertaken, wherein `P' value analysis based on phi and psi values of the protein was performed. Data showed sharper P value transition for alpha LP when compared to N. protease thus indicating relatively less kinetic stability of N. protease. Present study holds significance as the non-streptomycete actinomycetes group is least explored and ensures industrially important enzymes with exceptional stabilities. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Actinomycetes; Cloning and expression; Kinetic stability; Protease; Thermal simulation

Co3O4 nanorods-efficient non-noble metal electrocatalyst for oxygen evolution at neutral pH - Ramsundar, Rani M.; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Joy, Pattayil Alias (Electrocatalysis, 2015)

Cobalt ferrite nanoparticles: a magnetically separable and reusable catalyst for Petasis-Borono-Mannich reaction - Kulkarni, Aparna M.; Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2015)
Magnetically separable cobalt ferrite nanoparticles (CoFe2O4, NPS) have been demonstrated for the first time as an efficient catalyst in Petasis-Borono-Mannich (PBM) reaction between salicylaldehydes, sec. amines and aryl boronic acids to furnish alkylaminophenols in high yields. Relatively shorter reaction times, easy purification of the products and reusability of the catalyst for five consecutive runs without appreciable loss in it's activity are the noteworthy features of the developed protocol.

Co-catalyzed two-stereocentered hydrolytic kinetic resolution: application to the synthesis of yashabushidiols A and B and the lactone unit of compactin and mevinolin - Gadakh, Sunita K.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A short and efficient enantioselective synthesis of yashabushidiols A and B and the beta-hydroxy-delta-lactone moiety of compactin and mevinolin with high enantiomeric purity (98% ee) is described starting from commercially available materials. The strategy mainly comprises of iodine-induced intramolecular electrophilic addition of a carbonate occurring in a highly diastereoselective fashion and the Co-catalyzed two-stereocentered hydrolytic kinetic resolution of a functionalized epoxide as the chiral inducing step. (C) 2014 Elsevier Ltd. All rights reserved.

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2015)
2,3-Dihydroxynaphthalene forms 2:1 cocrystals with its p-ditoluate and 1:1 cocrystals with its m-ditoluate but not with the o-ditoluate. In 2:1 cocrystals of the p-ditoluate, naphthalene diol molecules form a dimeric motif through OH...O hydrogen bonding interactions. The adjacent dimers sandwich the molecules of p-ditoluate through C-H...pi interactions. In 1:1 cocrystals of the m-ditoluate, naphthalene diol molecules generate a zigzag pattern through O-H...O hydrogen bonding interaction involving -OH of the diol and the C=O of the m-ditoluate. Intermolecular toluoyl group transfer reaction was more facile in cocrystals of the p-ditoluate as compared to cocrystals of the m-ditoluate. This difference in reactivity is consistent with the relative geometry of the electrophile (El, C-O) and the nucleophile (Nu, OH) in these cocrystals. A comparison of the cocrystallization behavior and structure of the two cocrystals with their constituents suggests that the position of the methyl group is crucial for cocrystal formation. A survey of the CSD revealed that the incidence of polymorphism and cocrystals formation decreases (number of hits) in the order para- > ortho- > meta- for disubstituted benzene derivatives. This suggests that compounds prone to exhibit polymorphism have more propensities to form cocrystals as compared to those that resist polymorphism. This information could be useful while selecting cocrystal formers and construction of supramolecular functional assemblies with desired properties.

Coherent fusion of water array and protonated amine in a metal-sulfate-based coordination polymer for proton conduction - Manna, Biplab; Anothumakkool, Bihag; Desai, Aamod V.; Samanta, Partha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2015)
A new function of metal-sulfate-based co-ordination polymer (CP) for proton,conduction Was investigated through rational integration of a continuous water array and protonated amine in the coordination space of the CP. The H-bonded arrays of watet molecules along with nitrogen-rich aromatic cation (protonated melamine) facilitate proton conduction in the compound under humid conditions. Although several reports of metal-oxalate/phosphate-based CPs showing proton conduction are known, this is the first designed synthesis of a metal sulfate-based CP bearing-Water arrays functioning as a solid-state proton conductor:

Colossal increase in negative magnetization, exchange bias and coercivity in samarium chromite due to a strong coupling between Sm3+-Cr3+ spins sublattices - Gupta, Preeti; Bhargava, Richa; Poddar, Pankaj (Journal of Physics D-Applied Physics, 2015)
We report giant temperature dependent negative magnetization (magnetization reversal) along with a large exchange bias and large coercivity in SmCrO3. The static magnetization measurements show the negative magnetization below similar to 192 K, due to competition between the external field, thermal activation energy and antiparallel Sm3+-Cr3+ spin interaction. At further lower temperatures, Sm3+ spins show an increased alignment due to the internal induced field of Cr3+ spins with minimum magnetization similar to - 0.037 emu g(-1). The temperature dependent exchange bias shows non-monotonic behavior. At 35 K, the exchange bias ceases to exist due to the orientation of Sm3+ moments with respect to canted Cr3+ moments. The crossover temperature decreases from similar to 191 K at 100 Oe to similar to 153 K at 250 Oe. The training effect further confirms the exchange bias in SmCrO3. The dynamic magnetization measurements exhibit anomalies around spin reorientation transition (T-SR similar to 34 K) and Neel transition (T-N similar to 192 K) which is consistent with static measurement and no frequency dependence was observed. The room temperature Raman spectra of SmCrO3 show peaks at similar to 364, similar to 375 and similar to 456 cm(-1) suggesting O-Cr-O bending modes within the octahedral.
Keywords: exchange bias; multiferroics etc; negative magnetization; samarium chromite; spin reorientation

Combined experimental and theoretical study of the structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 - Jana, Manoj K.; Singh, Anjali; Late, Dattatray J.; Rajamathi, Catherine R.; Biswas, Kanishka; Felser, Claudia; Waghmare, Umesh V.; Rao, C. N. R. (Journal of Physics-Condensed Matter, 2015)
The recent discovery of non-saturating giant positive magnetoresistance has aroused much interest in Td-WTe2. We have investigated structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 experimentally and theoretically. Spin-orbit coupling is found to govern the semi-metallic character of Td-WTe2 and its structural link with the metallic 1 T form provides an understanding of its structural stability. There is a metal-to-insulator switch-over in the electrical conductivity and a change in the sign of the Seebeck coefficient around 373 K. Lattice vibrations of Td-WTe2 have been analyzed using first-principles calculations. Out of the 33 possible zone-center Raman active modes, five distinct Raman bands are observed around 112, 118, 134, 165 and 212 cm(-1) in bulk Td-WTe2. Based on symmetry analysis and calculated Raman tensors, we assign the intense bands at 165 cm(-1) and 212 cm(-1) to the A(1)' and A(1)'' modes, respectively. Most of the Raman bands stiffen with decreasing thickness, and the ratio of the integrated intensities of the A(1)'' to A(1)' bands decreases in the few-layer sample, while all the bands soften in both the bulk and few-layer samples with increasing temperature.
Keywords: Raman spectroscopy; Td-structure; tungsten ditelluride

Compact polar moieties induce lipid-water systems to form discontinuous reverse micellar phase - Kumar, Manoj; Patil, Naganath G.; Choudhury, Chandan Kumar; Roy, Sudip; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Soft Matter, 2015)
The role of molecular interactions in governing lipid mesophase organization is of fundamental interest and has technological implications. Herein, we describe an unusual pathway for monoolein/water reorganization from a bicontinuous mesophase to a discontinuous reverse micellar assembly, directed by the inclusion of polar macromolecules. This pathway is very different from those reported earlier, wherein the Fd3m phase formed only upon addition of apolar oils. Experiments and molecular dynamics simulations indicate that hydrophilic ternary additives capable of inducing discontinuous phase formation must (i) interact strongly with the monoolein head group and (ii) have a compact molecular architecture. We present a detailed investigation that contrasts a monoolein-water system containing polyamidoamine (PAMAM) dendrons with one containing their linear analogs. The Fd3m phase forms only on the addition of PAMAM dendrons but not their linear analogs. Thus, the dendritic architecture of PAMAM plays an important role in determining lipid mesophase behavior. Both dendrons and their linear analogs interact strongly with monoolein through their amine groups. However, while linear polymers adsorb and spread on monoolein, dendrons form aggregates that interact with the lipid. Dendrons induce formation of an intermediate reverse hexagonal phase, which subsequently restructures into the Fd3m phase. Finally, we demonstrate that other additives with compact structures that are known to interact with monoolein, such as branched polyethylenimine and polyhedral silsesquioxane cages, also induce the formation of the Fd3m phase.

Comparison of codon usage bias across leishmania and trypanosomatids to understand mRNA secondary structure, relative protein abundance and pathway functions - Subramanian, Abhishek; Sarkar, Ram Rup (Genomics, 2015)
Understanding the variations in gene organization and its effect on the phenotype across different Leishmania species, and to study differential clinical manifestations of parasite within the host, we performed large scale analysis of codon usage patterns between Leishmania and other known Trypanosomatid species. We present; the causes and consequences of codon usage bias in Leishmania genomes with respect to mutational pressure, translational selection and amino acid composition bias. We establish GC bias at wobble position that governs codon usage bias across Leishmania species, rather than amino acid composition bias. We found that, within Leishmania, homogenous codon context coding for less frequent amino acid pairs and codons avoiding formation of folding structures in mRNA are essentially chosen. We predicted putative differences in global expression between genes belonging to specific pathways across Leishmania. This explains the role of evolution in shaping the otherwise conserved genome to demonstrate species-specific function-level differences for efficient survival. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Amino acid bias; Base composition; Codon usage bias; Leishmania; Mutation; Selection bias; Species specificity

Comparison of human cell signaling pathway databases-evolution, drawbacks and challenges - Chowdhury, Saikat; Sarkar, Ram Rup (Database-the Journal of Biological Databases and Curation, 2015)
Elucidating the complexities of cell signaling pathways is of immense importance to gain understanding about various biological phenomenon, such as dynamics of gene/protein expression regulation, cell fate determination, embryogenesis and disease progression. The successful completion of human genome project has also helped experimental and theoretical biologists to analyze various important pathways. To advance this study, during the past two decades, systematic collections of pathway data from experimental studies have been compiled and distributed freely by several databases, which also integrate various computational tools for further analysis. Despite significant advancements, there exist several drawbacks and challenges, such as pathway data heterogeneity, annotation, regular update and automated image reconstructions, which motivated us to perform a thorough review on popular and actively functioning 24 cell signaling databases. Based on two major characteristics, pathway information and technical details, freely accessible data from commercial and academic databases are examined to understand their evolution and enrichment. This review not only helps to identify some novel and useful features, which are not yet included in any of the databases but also highlights their current limitations and subsequently propose the reasonable solutions for future database development, which could be useful to the whole scientific community.

Comprehensive study on the effect of acid additives in 1(R),2(R)-Bis[(S)-prolinamido]cyclohexane catalyzed direct asymmetric aldol reactions in aqueous media - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
The catalytic efficacy of (1R,2R)-bis[(S)-prolinamido]cyclohexane 1, prepared from the readily available natural amino acid L-proline has been studied for the direct asymmetric aldol reaction of cyclohexanone with substituted benzaldehydes at room temperature in presence of various acid additives. A wide variety of acids e.g. aliphatic fatty acid, chiral acid, sulphonic acid, aromatic acid, etc. have been used as additive for the aldol reaction in aqueous media. A loading of 10 mol% of catalyst 1 is employed in this reaction, and good yields (up to 98% yield), diastereoselectivity (up to 96% de) and enantioselectivities (up to 87% ee) can be achieved in aqueous media within very short reaction time (1-4 hours).
Keywords: acid additives; aqueous media; Asymmetric synthesis; direct aldol reaction; organocatalysis

Computational strategies for understanding the nature of interaction in dioxin imprinted nanoporous trappers - Khan, Muntazir S.; Pal, Sourav; Krupadam, Reddithota J. (Journal of Molecular Recognition, 2015)
A new computational model capable of understanding the nature of interactions in signature complexes formed between the template(2,3,7,8-tetrachlorodibenzo-p dioxin (TCDD)) and the functional monomers (methacrylic acid (MAA)) using density functional theory (DFT) has been designed. The polymer precursors were optimized for geometries in polymerization media, computing the interaction energies between template molecules and functional monomers of transient pre-polymerized complexes (PPC), and structural and vibrational properties reference to theoretical infrared spectra were computed using DFT of B3LYP/6 311+G(d,p) hybrid functional method. Atom in molecule theory was used to analyze the hydrogen-bonding characteristics of PPC of MAA-TCDD. Considering the theoretical titrations conducted in a virtual solvent box, it was found that the 1:4 molar ratio was required to form the most stable PPC in a given solvent system. The electron density plots indicate strong hydrogen bonding as shown by the 2pz dominant highest occupied molecular orbital (HOMO) character that could be the preferable sites of binding for target molecule, TCDD. Considering HOMO approach, the active adsorption sites in molecularly imprinted polymer was modeled to get insight on molecular recognition property for targeted molecule, TCDD. The proposed computational protocol is simple, accurate, and novel to design the polymer and is useful to predict the properties of polymer systems than the conventional theoretical analysis of template-monomer interactions. Copyright (c) 2015 John Wiley & Sons, Ltd.
Keywords: carcinogenic pollutants; computer simulations; Density Functional Theory (DFT); intermolecular interactions; Molecularly Imprinted Polymers (MIP)

Computational study of metal free alcohol dehydrogenation employing frustrated lewis pairs - Mane, Manoj V.; Rizvi, Masood A.; Vanka, Kumar (Journal of Organic Chemistry, 2015)
The catalysis of acceptorless alcohol dehydrogenation (AAD) is an important area of research. Transition metal-based systems are known to be effective catalysts for this reaction, but developing metal free catalytic systems would lead to highly desirable cheaper and greener alternatives. With this in mind, this computational study investigates design strategies than can lead to metal free frustrated Lewis pairs (FLPs) that can be employed for AAD catalysis. A careful study of 36 different proposed FLP candidates reveals that several new FLPs can be designed from existing, experimentally synthesized FLPs that can rival or be even better than state-of-the-art transition metal-based systems in catalyzing the alcohol dehydrogenation process.

Concise enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid via proline catalyzed alpha-aminooxylation of aldehydes and Pd-catalyzed ether directed aza-Claisen rearrangements - Ahuja, Brij Bhushan; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
An efficient approach to (2S,3S)-3-hydroxypipecolic acid with an overall yield of 10.2% and 98% ee starting from 1,5-pentanediol has been developed. The key steps employed in the synthesis are the D-proline catalyzed sequential alpha-aminooxylation/Horner-Wadsworth-Emmons olefination of an aldehyde and the Pd-catalyzed MOM-ether directed aza-Claisen rearrangement of an allylic trichloroacetimidate. (C) 2014 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of marine macrolide-stagonolide E via organocatalysis - Dey, Soumen; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A short and efficient enantioselective synthesis of marine macrolide stagonolide E in high enantiomeric purity (98% ee and 8.5% overall yield) starting from commercially available raw materials has been achieved. The strategy involves proline catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination, highly stereoselective Ando's cis-olefination, and modified Yamaguchi macrolactonization as the key reaction steps. (C) 2015 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of naturally active (S)-3-hydroxypiperidine - Dey, Soumen; Karabal, Pratibha U.; Sudalai, Arumugam (Synthetic Communications, 2015)
A short and efficient enantioselective synthesis of natural product (S)-3-hydroxypiperidine has been achieved starting from commercially available raw materials employing two catalytic routes: (i) cocatalyzed hydrolytic kinetic resolution (HKR) of racemic methyl-3-(oxiran-2-yl)propanoate; (ii) proline-catalyzed -aminooxylation followed by Horner-Wardsworth-Emmons olefination in high enantiomeric purity (97% ee) and high overall yield (38%).
Keywords: Asymmetric synthesis; bioactivity; Enantioselectivity; Natural products; organocatalysis

Concise enantioselective synthesis of (R)-selegiline, (S)-benzphetamine and formal synthesis of (R)-sitagliptin via electrophilic azidation of chiral imide enolates - Dey, Soumen; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A concise and high yielding enantioselective synthesis of (R)-selegiline, an anti-Parkinson's drug, (S)-benzphetamine, an anti-obesity agent, and (S)-sitagliptin, an anti-diabetic drug has been described starting from commercially available starting materials employing Evans' electrophilic azidation of chiral imide enolates as a key chiral inducing step, which proceeds in a highly diastereoselective manner (>99%). (C) 2014 Elsevier Ltd. All rights reserved.

Concise synthesis of (+/-)-clopidogrel via carboxylation of benzylamine with CO2 - Venkataramasubramanian, V.; Sudalai, Arumugam (Synthetic Communications, 2015)
A concise and efficient synthesis of (+/-)-clopidogrel, an antithrombotic agent, is achieved by inserting CO2 at the benzylic position as the key reaction without using any toxic transition metals. The overall yield of the synthetic process is 38% and the salient features include operationally simple process chemistry and fewer steps.
Keywords: Antithrombatic agent; clopidogrel; CO2 insertion; Plavix

Conformational modulation of peptides using beta-amino benzenesulfonic acid ((S)Ant) - Priya, Gowri; Kotmale, Amol S.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication describes the utility of a conformationally restricted aromatic beta-amino acid (2-aminobenzenesulfonic acid, (S)Ant) inducing various folding interactions in short peptides. Sandwiching (S)Ant between diverse amino acid residues was shown to form robust folded architectures featuring a variety of H-bonded networks, suggesting its utility in inducing peptide folding.

Construction and structural diversity of Cd-MOFs with pyrazole based flexible ligands and positional isomer of naphthalenedisulfonate - Singh, Udai P.; Singh, Neetu; Chandra, Suman (Inorganic Chemistry Communications, 2015)
In the present communication, we have reported the construction of a series of Cd(II)-MOFs using conformationally flexible ligand (CFL); 3,3',5,5'-tetramethy1-4,4'-bipyrazolyl (H(2)BPz), flexible bent ligand (FBL); methylenebis-(3,5-dimethylpyrazole) (H(2)MBPz) and positional isomer of naphthalene disulfonic acid salt ligands (1,5-NDS, 2,6-NDS). By using these ligands, four new coordination polymers namely [Cd(H(2)MBPz)(2) center dot 1,5-NDSA](n) (NDS-MOF-1), [Cd(H(2)BPz)center dot 1,5-NDSA](n) (NDS-MOF-2), {[Cd(H(2)MBPz)(2)](2+)center dot 2,6-NDSA(2-)}(n), (NDS-MOF-3) and {[Cd(H(2)BPz)(2)](2+).2,6-NDSA(n)(2-}) (NDS-MOF-4) have been synthesized. The crystal structure analysis revealed that the employment of positional isomeric naphthalene disulfonic acid salts resulted in different architectures ranging from one dimensional chain to two dimensional grid network and further connected into a three dimensional supramolecular structure through intermolecular hydrogen bonds, pi center dot center dot center dot pi and C-H center dot center dot center dot pi interactions. In addition, the photophysical properties and thermal stability studies for all the NDS-M0F5 1-4 were also investigated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cadmium(II); Conformation; coordination polymers; Naphthalenedisulfonate; Photophysical properties; thermal stability

Construction of polynuclear lanthanide (Ln = Dy-III, Tb-III, and Nd-III) cage complexes using pyridine-pyrazole-based ligands: versatile molecular topologies and smm behavior - Bala, Sukhen; Sen Bishwas, Mousumi; Pramanik, Bhaskar; Khanra, Sumit; Fromrn, Katharina M.; Poddar, Pankaj; Mondal, Raju (Inorganic Chemistry, 2015)
Employment of two different pyridyl pyrazolyl-based ligands afforded three octanudear lanthanide(III) (Ln = Dy, Tb) cage compounds and one hexanudear neodymium(III) coordination cage, exhibiting versatile molecular architectures including a butterfly core. Relatively less common semirigid pyridyl pyrazolyl-based asymmetric ligand systems show an interesting trend of forming polynuclear lanthanide cage complexes with different coordination environments around the metal centers. It is noteworthy here that construction of lanthanide complex itself is a challenging task in a ligand system as soft N-donor rich as pyridyl pyrazol. We report herein some lanthanide complexes using ligand containing only one or two O-donors compare to five N-coordinating sites. The resultant multinuclear lanthanide complexes show interesting magnetic and spectroscopic features originating from different spatial arrangements of the metal ions. Alternating current (ac) susceptibility measurements of the two dysprosium complexes display frequency- and temperature-dependent out-of-phase signals in zero and 0.5 T direct current field, a typical characteristic feature of single-molecule magnet (SMM) behavior, indicating different energy reversal barriers due to different molecular topologies. Another aspect of this work is the occurrence of the not-so-common SMM behavior of the terbium complex, further confirmed by ac susceptibility measurement.

Continuous precipitation of calcium carbonate using sonochemical reactor - Shirsath, S. R.; Sonawane, S. H.; Saini, D. R.; Pandit, A. B. (Ultrasonics Sonochemistry, 2015)
The continuous production of calcium carbonate (CaCO3) by precipitation method at room temperature was carried out in a stirred reactor under ultrasonic environment and was compared with the conventional stirring method. The effect of various operating parameters such as Ca(OH)(2) slurry concentration, CO2 flow rate and Ca(OH)(2) slurry flow rate on the particle size of CaCO3 was investigated. The calcium carbonate particles were characterized by Fourier transform infrared (FTIR), wide angle X-ray diffraction (WXRD) and particle size. The morphology was studied by using scanning electron microscopic (SEM) images. The particle size obtained in the presence of ultrasonic environment was found to be smaller as compared to conventional stirring method. The particle size is found to be reduced with an increase in the concentrations of Ca(OH)(2) and increased with increasing CO2 flow rate for both the methods. The slurry flow rate had a major effect on the particle size and the particle size decreased with increased slurry flow rate. Only calcite phase of CaCO3 was predominantly present as confirmed by the characterization techniques for both the preparation methods. In most of the cases rhombohedral calcite particles were observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcite; Crystal growth; Morphology; Nucleation; Particle size; Ultrasound

Continuous-flow nitration of o-xylene: effect of nitrating agent and feasibility of tubular reactors for scale-up - Sharma, Y.; Joshi, Ramesh A.; Kulkarni, A. A. (Organic Process Research & Development, 2015)
Continuous-flow nitration of o-xylene has been studied with different nitrating agents over a wide range of conditions for different parameters such as temperature, residence time, and concentrations. A nitrating mixture comprising sulfuric acid and fuming nitric acid was seen to yield higher selectivity for the isomer 1,2-dimethyl-3-nitrobenzene over the isomer 1,2-dimethyl-4-nitrobenzene and also a non-negligible quantity of dinitro derivatives of o-xylene. With only fuming nitric acid as the nitrating agent, the reaction was selective for 1,2-dimethyl-4-nitrobenzene over 1,2-dimethyl-3-nitrobenzene. Impurities mainly come from nitration of mononitro derivatives, and this occurs more from nitration of the 3-nitro isomer because of its higher reactivity with nitric acid. An economic analysis of the continuous-flow reactor for the production of 1,2-dimethyl-4-nitrobenzene at 100 and 500 kg/h in a jacketed tubular reactor showed that numbering-up is a more economical approach for higher production capacity. A combination of large- and small-sized tubes depending upon the relative rates of heat generation during a reaction will achieve more profit and a shorter payback period than having the entire reactor made of a single tube size.

Controlled micellar disassembly of photo- and pH-cleavable linear-dendritic block copolymers - Kalva, Nagendra; Parekh, Nimisha; Ambade, Ashootosh V. (Polymer Chemistry, 2015)
A linear-dendritic block copolymer with both photo-and pH-cleavable linkages at the junction between the hydrophobic dendron and hydrophilic linear polymer was synthesised. The photocleavable o-nitrobenzyl group attached to alkyne was introduced at the focal point of polyester dendron and acid-degradable acetal linkage with terminal azide was introduced at one end of linear polyethylene glycol. The two segments were connected using click chemistry. The copolymer was found to self-assemble into micelle-like aggregates in dilute aqueous solution. Stimuli-responsive disassembly of the aggregates was studied by monitoring fluorescence emission of the encapsulated hydrophobic dye and dynamic light scattering (DLS). Products of acetal cleavage at acidic pH were analyzed by gel permeation chromatography and NMR spectroscopy. The photo and pH stimuli were applied separately as well as simultaneously to study the rate of dye release. The synergistic effect of the two stimuli on dye release was demonstrated and the non-cytotoxic nature of the polymer was shown using the MTT assay. Cell uptake of DOX-loaded micelles and photo-induced release of the drug resulting in significantly higher cytotoxicity than by free DOX was demonstrated using MDA-MB-231 cells.

Conversion of biomass into sugars - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant; Dmitry, Murzin; Olga, Simakova (Biomass sugars for non-fuel applications, 2015)

Conversion of concentrated sugar solutions into 5-hydroxymethyl furfural and furfural using Bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Munshi, Mudassir K.; Kelkar, Ashutosh A.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Catalytic amounts of recyclable Bronsted acidic ionic liquids (BAILs) yielded HMF (73%) and furfural (81%) with high selectivity from highly concentrated solutions of D-fructose (40 wt%) and D-xylose (3 wt%), respectively. With a 6 wt% D-xylose solution, 73% yield was observed. An activity-property correlation of BAIL is established.

Conversion of dried aspergillus candidus mycelia grown on waste whey to biodiesel by in situ acid transesterification - Kakkad, Hardik; Khot, Mahesh; Smita S. Zinjarde; RaviKumar, Ameeta; Kumar, V. Ravi; Kulkarni, B. D. (Bioresource Technology, 2015)
This study reports optimization of the transesterification reaction step on dried biomass of an oleaginous fungus Aspergillus candidus grown on agro-dairy waste, whey. Acid catalyzed transesterification was performed and variables affecting esterification, viz., catalyst methanol and chloroform concentrations, temperature, time, and biomass were investigated. Statistical optimization of the transesterification reaction using Plackett-Burman Design showed biomass to be the predominant factor with a 12.5-fold increase in total FAME from 25.6 to 320 mg. Studies indicate that the transesterification efficiency in terms of conversion is favored by employing lower biomass loadings. A. candidus exhibited FAME profiles containing desirable saturated (30.2%), monounsaturated (31.5%) and polyunsaturated methyl esters (38.3%). The predicted and experimentally determined biodiesel properties (density, kinematic viscosity, iodine value, cetane number, TAN, water content, total and free glycerol) were in accordance with international (ASTM D6751, EN 14214) and national (IS 15607) standards. (C) 2015 Published by Elsevier Ltd.
Keywords: Aspergillus candidus; Biodiesel; In situ acid transesterification; Plackett-Burman Design; Whey

Core-shell nanoparticles: synthesis and applications in catalysis and electrocatalysis - Gawande, Manoj B.; Goswami, Anandarup; Asefa, Tewodros; Guo, Huizhang; Biradar, Ankush V.; Peng, Dong-Liang; Zboril, Radek; Varma, Rajender S. (Chemical Society Reviews, 2015)
Core-shell nanoparticles (CSNs) are a class of nanostructured materials that have recently received increased attention owing to their interesting properties and broad range of applications in catalysis, biology, materials chemistry and sensors. By rationally tuning the cores as well as the shells of such materials, a range of core-shell nanoparticles can be produced with tailorable properties that can play important roles in various catalytic processes and offer sustainable solutions to current energy problems. Various synthetic methods for preparing different classes of CSNs, including the Stober method, solvothermal method, one-pot synthetic method involving surfactants, etc., are briefly mentioned here. The roles of various classes of CSNs are exemplified for both catalytic and electrocatalytic applications, including oxidation, reduction, coupling reactions, etc.

Correlations between structure, microstructure, density and dielectric properties of the lead-free ferroelectrics Bi0.5(Na,K)0.5TiO3 - Anjali, K.; Ajithkumar, Thalasseril G.; Joy, Pattayil Alias (Journal of Advanced Dieletrics, 2015)

CoSe2 supported on nitrogen-doped carbon nanohorns as a methanol-tolerant cathode for air-breathing microlaminar flow fuel cells - Unni, SreeKuttan M.; Mora-Hernandez, Juan M.; Kurungot, Sreekumar; Alonso-Vante, Nicolas (Chemelectrochem, 2015)
The synthesis of CoSe2 nanoparticles supported on nitrogendoped carbon nanohorns (CoSe2/NCNH) and the influence of the interaction of the metal centre with the NCNH on the oxygen reduction reaction (ORR) are reported. CoSe2/NCNH shows a 50 mV lower onset overpotential and a 150 mV positive shift in the half-wave potential compared to CoSe2 supported on carbon and carbon nanohorns. This suggests that the intrinsic activity and the density of active reaction centres of CoSe2 are modified by NCNHs. An air-breathing direct meth-anol microlaminar flow fuel cell (mLFFC) is constructed using CoSe2/NCNH as a methanol-tolerant cathode catalyst. A maximum power density of 10.05 mWcm(-2) and a maximum current density of 124.20 mAcm(-2) are achieved with CoSe2/NCNH compared to the non-doped catalyst, CoSe2/C and Pt/C with 5m methanol as the fuel. The improved activity of CoSe2/ NCNH is attributed to the peculiar morphology and the nitrogen doping of the carbon nanohorns. This catalyst could be a suitable alternative to Pt.
Keywords: carbon nanohorns; chalcogenides; fuel cells; oxygen reduction reaction; platinum

Cosolvent effects on solute-solvent hydrogen-bond dynamics: ultrafast 2D IR investigations - Kashid, Somnath M.; Jin, Geun Young; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry B, 2015)
Cosolvents strongly influence the solute-solvent interactions of biomolecules in aqueous environments and have profound effects on the stability and activity of several proteins and enzymes. Experimental studies have previously reported on the hydrogen-bond dynamics of water molecules in the presence of a cosolvent, but understanding the effects from a solute's perspective could provide greater insight into protein stability. Because carbonyl groups are abundant in biomolecules, the current study used 2D IR spectroscopy and molecular dynamics simulations to compare the hydrogen-bond dynamics of the solute's carbonyl group in aqueous solution, with and without the presence of DMSO as a cosolvent. 2D IR spectroscopy was used to quantitatively estimate the time scales of the hydrogen-bond dynamics of the carbonyl group in neat water and 1:1 DMSO/water solution. The 2D IR results show spectral signatures of a chemical exchange process: The presence of the cosolvent was found to lower the hydrogen-bond exchange rate by a factor of 5. The measured exchange rates were 7.50 X 10(11) and 1.48 X 10(11) s(-1) in neat water and 1:1 DMSO/water, respectively. Molecular dynamics simulations predict a significantly shorter carbonyl hydrogen-bond lifetime in neat water than in 1:1 DMSO/water and provide molecular insights into the exchange mechanism. The binding of the cosolvent to the solute was found to be accompanied by the release of hydrogen-bonded water molecules to the bulk. The widely different hydrogen-bond lifetimes and exchange rates with and without DMSO indicate a significant change in the ultrafast hydrogen-bond dynamics in the presence of a cosolvent, which, in turn, might play an important role in the stability and activity of biomolecules.

CRE for magic(modular, agile, intensified & continuous) processes - Ranade, Vivek V.; Sharma, Mrityunjay K.; Kulkarni, Amol A. (Chemical Engineering Journal, 2015)
Fine and specialty chemical industry caters to several key applications required for maintaining and enhancing quality of life. Most of these fine and specialty chemicals are still manufactured in stirred tank reactors operated in batch or semi-batch modes. A paradigm shift is necessary to transform these into new age, efficient and continuous processes and plants. In this paper, recent attempts of our group on developing MAGIC (modular, agile, intensified and continuous) devices, processes and plants for fine and specialty chemicals industry are discussed. The focus is on key chemical reaction engineering aspects of developing MAGIC processes. An attempt is made to evolve guidelines for designing MAGIC devices and reactors. The discussion will be useful to researchers as well as to industry practitioners. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Agile; Continuous; CRE; Intensified; Modular

Cross over from 3D variable range hopping to the 2D weak localization conduction mechanism in disordered carbon with the extent of graphitization - Raj, Kovummal Govind; Joy, Pattayil Alias (Physical Chemistry Chemical Physics, 2015)
The changes in the electrical transport properties and mechanism of conduction in disordered carbon, with the extent of graphitization, are studied and discussed. With heat treatment induced graphitic ordering, the electrical properties are considerably modified, inducing a crossover from strong localization to weak localization behavior. Accordingly, the conduction mechanism is modified from the 3-dimensional variable range hopping (3D VRH) model to the 2-dimensional weak localization (2D WL) model. Results show that carrier-carrier and carrier-phonon interactions play major roles in developing the weak localization behavior with the extent of graphitization.

Crystal structure of a plant albumin from cicer arietinum (chickpea) possessing hemopexin fold and hemagglutination activity - Sharma, Urvashi; Katre, Uma V.; Suresh, C. G. (Planta, 2015)
Crystal structure of a reported PA2 albumin from Cicer arietinum shows that it belongs to hemopexin fold family, has four beta-propeller motifs and possesses hemagglutination activity, making it different from known legume lectins. A plant albumin (PA2) from Cicer arietinum, presumably a lectin (CAL) owing to its hemagglutination activity which is inhibited by complex sugars as well as glycoproteins such as fetuin, desialylated fetuin and fibrinogen. The three-dimensional structure of this homodimeric protein has been determined using X-ray crystallography at 2.2 in two crystal forms: orthorhombic (P2(1)2(1)2) and trigonal (P3). The structure determined using molecular replacement method and refined in orthorhombic crystal form reached R-factors R (free) 22.6 % and R (work) 18.2 % and in trigonal form had 22.3 and 17.9 % in the resolution range of 20.0-2.2 and 35.3-2.2 , respectively. Interestingly, unlike the known legume lectin fold, the structure of this homodimeric hemagglutinin belonged to hemopexin fold that consisted of four-bladed beta-propeller architecture. Each subunit has a central cavity forming a channel, inside of which is lined with hydrophobic residues. The channel also bears binding sites for ligands such as calcium, sodium and chloride ions, iodine atom in the case of iodine derivative and water molecules. However, none of these ligands seem important for the sugar recognition. No monosaccharide sugar specificity could be detected using hemagglutination inhibition. Chemical modification studies identified a potential sugar-binding site per subunit molecule. Comparison of C-alpha atom positions in subunit structures showed that the deviations between the two crystal forms were more with respect to blades I and IV. Differences also existed between subunits in two forms in terms of type and site of ligand binding.
Keywords: Beta-propeller fold; Chemical modification; Chickpea lectin; Complex sugars; PA2 albumin; Sugar binding

Crystal structures of the pyrazinamide-p-aminobenzoic acid (1/1) cocrystal and the transamidation reaction product 4-(pyrazine-2-carboxamido)-benzoic acid in the molten state - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2015)
The synthesis of pharmaceutical cocrystals is a strategy to enhance the performance of active pharmaceutical ingredients (APIs) without affecting their therapeutic efficiency. The 1: 1 pharmaceutical cocrystal of the antituberculosis drug pyrazinamide (PZA) and the cocrystal former p-aminobenzoic acid (p-ABA), C7H7NO2- C5H5N3O, (1), was synthesized successfully and characterized by relevant solid-state characterization methods. The cocrystal crystallizes in the monoclinic space group P21/n containing one molecule of each component. Both molecules associate via intermolecular O-H center dot center dot center dot O and NH center dot center dot center dot O hydrogen bonds [O center dot center dot center dot O = 2.6102 (15)angstrom and O-H center dot center dot center dot O = 168.3 (19)degrees; N center dot center dot center dot O = 2.9259 (18) angstrom and N-H center dot center dot center dot O = 167.7 (16)degrees] to generate a dimeric acidamide synthon. Neighbouring dimers are linked centrosymmetrically through N-H center dot center dot center dot O interactions [N center dot center dot center dot O = 3.1201 (18) angstrom and N-H center dot center dot center dot O = 136.9 (14)degrees] to form a tetrameric assembly supplemented by C-H center dot center dot center dot N interactions [C center dot center dot center dot N = 3.5277 (19) angstrom and C-H center dot center dot center dot N = 147 degrees]. Linking of these tetrameric assemblies through N-H center dot center dot center dot O [N center dot center dot center dot O = 3.3026 (19) angstrom and N-H center dot center dot center dot O = 143.1 (17)degrees], NH center dot center dot center dot N [N center dot center dot center dot N = 3.221 (2) angstrom and N-H center dot center dot center dot N = 177.9 (17)degrees] and C-H center dot center dot center dot O [C center dot center dot center dot O = 3.5354 (18) angstrom and C-H center dot center dot center dot O = 152 degrees] interactions creates the twodimensional packing. Recrystallization of the cocrystals from the molten state revealed the formation of 4-(pyrazine-2-carboxamido) benzoic acid, C12H9N3O3, (2), through a transamidation reaction between PZA and p-ABA. Carboxamide (2) crystallizes in the triclinic space group P1 with one molecule in the asymmetric unit. Molecules of (2) form a centrosymmetric dimeric homosynthon through an acid-acid O-H center dot center dot center dot O hydrogen bond [O center dot center dot center dot O = 2.666 (3) angstrom and O-H center dot center dot center dot O = 178 (4) degrees]. Neighbouring assemblies are connected centrosymmetrically via a C-H center dot center dot center dot N interaction [C center dot center dot center dot N = 3.365 (3) angstrom and C-H center dot center dot center dot N = 142 degrees] engaging the pyrazine groups to generate a linear chain. Adjacent chains are connected loosely via C-H center dot center dot center dot O interactions [C center dot center dot center dot O = 3.212 (3) angstrom and CH center dot center dot center dot O = 149 degrees] to generate a two-dimensional sheet structure. Closely associated two-dimensional sheets in both compounds are stacked via aromatic pi-stacking interactions engaging the pyrazine and benzene rings to create a threedimensional multi-stack structure.
Keywords: acid-amide hetero-synthon; active pharmaceutical ingredient (API); cocrystal; crystal structure; hydrogen bonding; molten-state reaction; powder diffraction; transamidation reaction

Cu-catalyzed debrominative cyanation of gem-dibromoolefins: a facile access to alpha,beta-unsaturated nitriles - Ahuja, Brij Bhushan; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2015)
An efficient catalytic route for the synthesis of alpha,beta-unsaturated nitriles from easily accessible gem-dibromoolefins has been developed. The method utilized inexpensive reagents such as Cu2O as a catalyst, L-proline as a ligand and NaCN as a cyanide source to afford alpha,beta-unsaturated nitriles in high yields (62-86%). A deuterium exchange study has shown that one of the bromide atoms of gem-dibromoolefins exchanges with cyanide while the other with a deuterium atom.

Cu-Pt nanocage with 3-D electrocatalytic surface as an efficient oxygen reduction electrocatalyst for a primary Zn-air battery - Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Catalysis, 2015)
Cu-Pt nanocage (CuPt-NC) intermetallic structures have been prepared by an in situ galvanic displacement reaction. The structures are found to be well organized within the framework demarcated with distinguishing arms, having clear edges and corners with a size of similar to 20 nm. The unique nanocage structure possessing large specific surface area and better structural integrity helps to achieve improved electrochemical oxygen reduction reaction activity and stability in alkaline solution in comparison to the commercially available 20 wt % Pt/C. CuPt-NC shows 50 mV positive onset potential shift with significantly higher limiting current in comparison to Pt/C. Interestingly, CuPt-NC has shown 2.9- and 2.5-fold improved mass activity and specific activity, respectively, for ORR at 0.9 V vs RHE in comparison to Pt/C. Moreover, the stability of CuPt-NC has been tested by an accelerated durability test under alkaline conditions. CuPt-NC has been subsequently utilized as the air electrode in a primary Zn-air battery and is found to possess 1.30- and 1.34-fold improved power density and current density at 1 V, respectively, in comparison to the state-of-the-art Pt/C catalyst. In addition, CuPt-NC has shown several hours of constant discharge stability at 20 mA cm(-2) with a specific capacity of 560 mAh gZn(-1) and energy density of 728 Wh kgZn(-1) in the primary Zn-air battery system.
Keywords: 3-D electrocatalytic surface; Cu-Pt nanocage; electrocatalyst; galvanic displacement; oxygen reduction reaction; solvothermal method; Zn-air battery

Cyclic cationic peptides containing sugar amino acids selectively distinguishes and inhibits maturation of pre-mirnas of the same family - Nahar, Smita; Bose, Debojit; Pal, Sudip; Chakraborty, Tushar Kanti; Maiti, Souvik (Nucleic Acid Therapeutics, 2015)
The discovery of microRNAs (miRNAs) has added a new dimension to the gene regulatory networks, making aberrantly expressed miRNAs as therapeutically important targets. Small molecules that can selectively target and modulate miRNA levels can thus serve as lead structures. Cationic cyclic peptides containing sugar amino acids represent a new class of small molecules that can target miRNA selectively. Upon treatment of these small molecules in breast cancer cell line, we profiled 96 therapeutically important miRNAs associated with cancer and observed that these peptides can selectively target paralogous miRNAs of the same seed family. This selective inhibition is of prime significance in cases when miRNAs of the same family have tissue-specific expression and perform different functions. During these conditions, targeting an entire miRNA family could lead to undesired adverse effects. The selective targeting is attributable to the difference in the three-dimensional structures of precursor miRNAs. Hence, the core structure of these peptides can be used as a scaffold for designing more potent inhibitors of miRNA maturation and hence function.

Cytostatic ruthenium(II)-platinum(II) bis(terpyridyl) anticancer complex that blocks entry into sphase by up-regulating p27(KIP1) - Ramu, Vadde; Gill, Martin R.; Jarman, Paul J.; Turton, David; Thomas, Jim A.; Das, Amitava; Smythe, Carl (Chemistry-A European Journal, 2015)
Cytostatic agents that interfere with specific cellular components to prevent cancer cell growth offer an attractive alternative, or complement, to traditional cytotoxic chemotherapy. Here, we describe the synthesis and characterization of a new binuclear Ru-II-Pt-II complex [Ru(tpy)(tpypma)Pt(Cl)(DMSO)](3+) (tpy=2,2:6,2-terpyridine and tpypma=4-([2,2:6,2-terpyridine]-4-yl)-N-(pyridin-2-ylmethyl)aniline), VR54, which employs the extended terpyridine tpypma ligand to link the two metal centres. In cell-free conditions, VR54 binds DNA by non-intercalative reversible mechanisms (K-b=1.3x10(5)M(-1)) and does not irreversibly bind guanosine. Cellular studies reveal that VR54 suppresses proliferation of A2780 ovarian cancer cells with no cross-resistance in the A2780CIS cisplatin-resistant cell line. Through the preparation of mononuclear Ru-II and Pt-II structural derivatives it was determined that both metal centres are required for this anti-proliferative activity. In stark contrast to cisplatin, VR54 neither activates the DNA-damage response network nor induces significant levels of cell death. Instead, VR54 is cytostatic and inhibits cell proliferation by up-regulating the cyclin-dependent kinase inhibitor p27(KIP1) and inhibiting retinoblastoma protein phosphorylation, which blocks entry into Sphase and results in G1 cell cycle arrest. Thus, VR54 inhibits cancer cell growth by a gain of function at the G1 restriction point. This is the first metal-coordination compound to demonstrate such activity.
Keywords: antitumor agents; cytostatic; p27KIP1; platinum drugs; ruthenium terpyridine

Calculation of hyperfine structure constants of small molecules using Z-vector method in the relativistic coupled-cluster framework - Sasmal, Sudip; Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Sciences, 2016)
The Z-vector method in the relativistic coupled-cluster framework is employed to calculate the parallel and perpendicular components of the magnetic hyperfine structure constant of a few small alkaline earth hydrides (BeH, MgH, and CaH) and fluorides (MgF and CaF). We have compared our Z-vector results with the values calculated by the extended coupled-cluster (ECC) method reported in Phys. Rev. A 91 022512 (2015). All these results are compared with the available experimental values. The Z-vector results are found to be in better agreement with the experimental values than those of the ECC values.

Can a diels-alder reaction accelerate in a supersaturated solvent at room temperature? - Nagare, Amit S.; Manna, Arpan; Kumar, Anil (New Journal of Chemistry, 2016)
A new supersaturated solvent is proposed to accelerate the Diels–Alder reaction between cyclopentadiene and methyl acrylate by several times. The proposed supersaturated solvent consists of various carbohydrates, organic acid and organic ketone in water, beyond their solubility limits in water, at room temperature. The results demonstrate that the presence of excess –OH groups from the carbohydrates plays a pivotal role leading to the increased reactivity and selectivity of the Diels–Alder reaction. The role of hydrogen bond accelerators and polarity of the solvent have been analyzed through a comparative study of the same reaction in similar green solvents. Collision-controlled reaction theory has been invoked to understand the role of encounter complexes to accelerate such a reaction at the molecular level in such highly viscous supersaturated solvent. No detrimental effects from the high viscosity of the new solvent medium on the reaction kinetics was been noted.

Can main group systems act as superior catalysts for dihydrogen generation reactions? A computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Dalton Transactions, 2016)
The protolytic cleavage of the O-H bond in water and alcohols is a very important reaction, and an important method for producing dihydrogen. Full quantum chemical studies with density functional theory (DFT) reveal that germanium based complexes, such as HCCMeArB(2)GeH (Ar = 2,6-(Pr2C6H3)-Pr-i), with the assistance of silicon based compounds such as SiF3H, can perform significantly better than the existing state-of-the-art post-transition metal based systems for catalyzing dihydrogen generation from water and alcohols through the protolysis reaction.

Capsicum annuum proteinase inhibitor ingestion negatively impacts the growth of sorghum pest Chilo partellus and promotes differential protease expression - Jadhav, A. R.; War, A. R.; Nikam, A. N.; Adhav, A. S.; Gupta, V. S.; Sharma, H. C.; Giri, A. P.; Tamhane, V.A. (Biochemistry and Biophysics Reports, 2016)
Background Chilo partellus is an important insect pest infesting sorghum and maize. The larvae internalize in the stem, rendering difficulties in pest management. We investigated the effects of Capsicum annuum proteinase inhibitors (CanPIs) on C. partellus larvae by in-vitro and in-vivo experiments. Methods Recombinant CanPI-7 (with four-Inhibitory Repeat Domains, IRDs), -22 (two-IRDs) and insect proteinase activities were estimated by proteinase assays, dot blot assays and in gel activity assays. Feeding bioassays of lab reared C. partellus with CanPI-7 and -22 were performed. C. partellus proteinase gene expression was done by RT-PCR. In-silico structure prediction of proteinases and CanPI IRDs was carried out, their validation and molecular docking was done for estimating the interaction strength. Results Larval proteinases of C. partellus showed higher activity at alkaline pH and expressed few proteinase isoforms. Both CanPIs showed strong inhibition of C. partellus larval proteinases. Feeding bioassays of C. partellus with CanPIs revealed a dose dependent retardation of larval growth, reduction of pupal mass and fecundity, while larval and pupal periods increased significantly. Ingestion of CanPIs resulted in differential up-regulation of C. partellus proteinase isoforms, which were sensitive to CanPI-7 but were insensitive to CanPI-22. In-silico interaction studies indicated the strong interaction of IRD-9 (of CanPI-22) with Chilo proteinases tested. Conclusions Of the two PIs tested, CanPI-7 prevents induction of inhibitor insensitive proteinases in C. partellus so it can be explored for developing C. partellus tolerance in sorghum. General significance Ingestion of CanPIs, effectively retards C. partellus growth; while differentially regulating the proteinases.

Carbonylations and hydroformylations for fine chemicals - Kelkar, A. A. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Carbonylation reactions (hydroformylation and carbonylation) constitute one of the most powerful tools for C. C bond formation in organic synthesis and represent an outstanding example of the application of homogeneous catalysis on an industrial scale. Carbonylation reactions have the potential to provide clean, atom-efficient routes for the synthesis of molecules with carboxylic acid, aldehyde and amide functional groups. However, catalyst product separation is a major problem for the application of homogeneous catalysts on an industrial scale. The manufacture of ibuprofen, one of the important antiinflammatory drugs involving palladium-catalyzed carbonylation, was the path-breaking technology in pharmaceutical chemistry. A significant amount of work is being carried out on the development of selective catalysts for specialty chemical synthesis. This chapter presents recent advances in the development of new catalysts for carbonylation reactions. Various strategies developed for the heterogenization of catalysts are also presented, with an emphasis on specialty chemicals.

Cascade synthesis of 2-cyanoacrylamides through deacetalization and/or knoevenagelcondensation followed by selective monohydration of acetals and aldehydes over solid acidferrites - Kamble, Sumit B.; Rode, Chandrashekhar V. (Chemcatchem, 2016)
A new protocol of cascade synthesis for biologically active 2-cyanoacrylamides (1) was developed. The reaction proceeds over a novel magnetically retrievable solid-acid composite of iron oxide, poly(vinylpyrrolidone) and phosphotungstic acid (Fe3O4/PVP-PWA) in AcOH-H2O medium under reflux conditions. This transformation is facilitated through single-site Bronsted acid catalyzed cascade reactions involving deacetalization and/or Knoevenagel condensation followed by selective monohydration of nitriles starting from acetals (5) and aldehydes (2) with malononitrile (3). A series of aldehydes, dimethyl and diethyl acetals, along with some heterocyclic aldehydes were successfully transformed to 2-cyanoacrylamides with >95% yields. TEM images confirmed the coating of the PVP over nanosized Fe3O4. Stereoselective monohydration of 2-benzylidenemalononitriles (4) to E isomers was demonstrated by NOESY experiments. The catalyst could be efficiently recycled seven times on employment of both acetals and aldehydes as substrates, as a result of its magnetic nature.

Catalysis and catalytic processes - Ranade, V. V.; Joshi, S. S. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Catalytic reactions are ubiquitous in chemical and allied industries. A homogeneous or heterogeneous catalyst that provides an alternative route of reaction with lower activation energy and better control of selectivity can make a substantial impact on process viability and economics. In this chapter, the basics of catalysis and catalytic processes are introduced. Some aspects of reaction and reactor engineering required to realize catalytic processes in practice are also discussed. In addition, the organization of the book is outlined.

Catalysis for fine and specialty chemicals - Joshi, S. S.; Bhatnagar, A.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
The fine and specialty chemical industry is extremely diverse, encompassing pharmaceuticals, dyestuffs, food additives, agrochemicals, polymer additives, flavors and fragrances, various chemical intermediates, etc. Fine and specialty chemicals have been around for more than 100 years and they are produced with the aim of either being used as is or in the form of additives/formulations. These organic chemicals are generally manufactured in batch or semibatch processes. Most of these generally involve multistep processes and often generate significant by-products/effluents per kg of useful products. Catalysis can be effectively used to reduce such waste generation and to minimize consumption of raw materials. In this chapter, we present various applications of homogeneous, as well as heterogeneous catalysis and catalytic processes, which are particularly relevant to fine and specialty chemicals

Catalyst deactivation and regeneration - Satyanarayana, C. V.; Srikant, D.; Gurav, H. R. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Catalysis plays a vital role in the manufacture of fuels, industrial chemicals, fine chemicals, and specialty chemicals. A catalyst is not only expected to be highly active, it should be stable for long hours on stream and should be recyclable, if required. However, in reality, all the catalysts have finite life. Hence, a most important goal of any catalyst development is to get a catalyst that is highly active for long periods without needing any regeneration. This chapter addresses various causes of catalyst deactivation with reference to different catalyst systems. It discusses various forms coke (carbon) forms on catalysts and the side reactions that drive their formation. The role of support on carbon formation as well as how carbon can be limited using bimetallic catalysts is discussed. Various mechanisms responsible for sintering of metals have been discussed while suggesting means to suppress the same. This chapter also discusses loss of catalyst activity due to strong chemisorption of impurities or byproducts. Typical poisons to different catalysts are listed. The effect of various poisons and how they can influence the course of a catalytic reaction are described. A catalyst may also lose its activity due to mechanical failures such as (i) crushing of catalyst pellets or granules, (ii) breakup of catalyst pellets followed by its attrition, and (iii) erosion of catalyst particles or monolith wash coats. Various solutions to prevent or delay catalyst deactivation as well as various catalyst regeneration methods are summarized.

Catalytic activity of bare and porous palladium nanostructures in the reduction of 4-nitrophenol - Kalekar, Ajit M.; Sharma, Kiran Kumar K.; Luwang, Meitram Niraj; Sharma, Geeta K. (RSC Advances, 2016)
The catalytic activity of bare and porous palladium nanostructures viz. palladium nanoballs (PdNBs) and palladium urchins (Pdurc) synthesized in surfactant based liquid crystalline mesophase have been investigated in the reduction of 4-nitrophenol. The loading of PdNBs and Pdurc nanocatalyst in the reaction are optimized to 1.57 x 10(-4) mol% and 1.57 x 10(-3) mol% respectively. The surface area normalized rate constant obtained at 303 K for PdNBs (0.74 +/- 0.03) s(-1) m(-2) L and Pdurc (0.41 +/- 0.05) s(-1) m(-2) L is the highest, considering the low palladium loading used in the reaction. The specific surface area determined for the PdNBs and Pdurc are 153 m(2) g(-1) and 27 m(2) g(-1) respectively. The high surface area of PdNBs nanostructure is consistent with the highest catalytic activity. The palladium nanostructure catalyzed reaction lacks induction time (t(0)), indicating the influence of porosity in the Langmuir-Hinshelwood mechanism. Besides, PdNBs and Pdurc exhibited thermal stability and structural integrity with good conversion of the substrate (>97%) even up to five consecutive reactions. The mechanistic insight of the bare and porous palladium nanostructures presented in this study is significant for the development of stable and efficient palladium metal based nanocatalyst.

Catalytic decarboxylation of non-edible oils over three-dimensional, mesoporous silica-supported Pd - Raut, Ravindra; Banakar, Vikram V.; Darbha, Srinivas (Journal of Molecular Catalysis A-Chemical, 2016)
Deoxygenation of fatty acids (oleic and stearic acids) and non-edible oil (jatropha oil) over Pd(1-5 wt%) supported on two structurally different, three-dimensional, mesoporous silica (SBA-12 and SBA-16) catalysts was investigated. Pd/SBA-16 (cubic mesoporous structure with space group Im (3) over barm) showed higher catalytic activity than Pd/SBA-12 (hexagonal mesoporous structure with space group p6(3)/mmc). The influence of reaction parameters like temperature, H-2 pressure and Pd content as well as the nature of the feedstock on catalytic activity and product selectivity was studied. A temperature of above 320 degrees C, reaction time of 5 h and Pd content (on silica surface) of 3 wt% enabled complete conversion of the fatty compounds into diesel-range hydrocarbons. Deoxygenation proceeded through hydrodeoxygenation and decarboxylation mechanisms when a saturated (stearic) acid was used as a feed while it advanced mainly through decarboxylation route when an unsaturated (oleic) acid was employed. Higher surface hydrophobicity and smaller size particles of Pd are the possible causes for the superior catalytic activity of Pd/SBA-16. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Biofuel; Deoxygenation; Diesel-range hydrocarbons; Mesoporous silica; Supported palladium; Vegetable oil

Catalytic reaction engineering - Gunjal, P. R.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
hemical reaction engineering has contributed remarkably in bringing laboratory-developed chemistry into commercial practice. Reaction engineering is useful for analysis of reactions, identifying rate-limiting steps, determining overall rates, selection of reactor configuration and design and scale-up of reactors. Reaction engineering also provides useful insights into catalytic cycles and provides clues for improving catalyst systems. It essentially includes all the activities necessary to evolve best possible hardware and operating protocol for the reactor to carry out the desired transformation of raw materials (or reactants) into value-added products. This chapter provides an overview of reaction engineering aspects of catalytic processes.

Catecholase and phenoxazinone synthase activities of a ferromagnetically coupled tetranuclear Cu(II) complex - Mitra, Merry; Kundu, Tanay; Kaur, Gurpreet; Sharma, Gyaneswar; Choudhury, Angshuman Roy; Singh, Yogesh; Ghosh, Rajarshi (RSC Advances, 2016)
A crystallographically characterized tetranuclear Cu(II) complex [Cu-4(II)(L)(4)] (1) [H2L = N-(2-hydroxyethyl)-3-methoxysalicylaldimine] is found to show overall ferromagnetic exchange coupling. Complex (1) mimics the catalytic activity of the plant enzyme catechol oxidase by oxidising 3,5-di-tert-butylcatechol to its corresponding quinone in methanol and dichloromethane medium in the presence of aerial oxygen. The reaction follows Michaelis-Menten enzymatic reaction kinetics with turnover numbers (K-cat) 6.99 x 10(3) and 1.85 x 10(3) h(-1) in methanol and dichloromethane, respectively. 1 is also phenoxazinone synthase active in methanol medium with a turnover number of 1.21 x 10(5) h(-1).

CeCl3 center dot 7H(2)O-NaI promoted regioselective sulfenylation of indoles with sulfonylhydrazides - Nookaraju, U.; Begari, Eeshwaraiah; Yetra, Ravikiran Reddy; Kumar, Pradeep (Chemistryselect, 2016)
A simple and highly efficient method has been developed for the regioselective sulfenylation of a wide variety of indoles with alkyl and aryl sulfonylhydrazides as a sulphur source and CeCl3 center dot 7H(2)O-Nal as an inexpensive and readily available reagent system. This method involves the breaking of sulfur-oxygen and sulfur-nitrogen bonds and making of carbon-sulfur bond. The method provides high yields of the products with enhanced regioselectivity. We studied the reactivity of various electron rich and electron deficient indoles towards the sulfe-nylation reaction. The indoles containing electron donating group reacts fast towards the sulfenylation reaction as compared to the indoles containing electron withdrawing groups. More over functional groups like alkoxy, aryloxy, bromo, nitro, cyano, ester, were well tolerated under the established reaction conditions. We also proposed a plausible mechanism for this transformation. The experimental simplicity and environmentally benign nature of the reagent system makes this method an attractive alternative to established methods.

Cells and organs on chip - revolutionary platform for biomedicine - Joshi, Preeti Nigam (Lab-on-a-chip fabrication and application, 2016)

Cetyl alcohol and oleic acid sophorolipids exhibit anticancer activity - Dubey, P.; Raina, P.; Prabhune, A.; Kaul-Ghanekar, R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Sophorolipids (SLs) are glycolipid biosurfactants that have been shown to have anticancer activity. We investigated the anti-cancer activity of cetyl alcohol sophorolipids (CAS) and oleic acid sophorolipids (OAS) in breast cancer (MCF-7, MDA-MB-231), cervical cancer (SiHa, HeLa) and non-cancerous (HaCaT and RAW264.7) cell lines. Methods: For cell viability assay, MCF-7, MDA-MB-231, SiHa, HeLa, HaCaT and RAW264.7 cell lines were treated with different concentrations (0-160 μg/ml) of OAS and CAS for 24h. The cell viability was determined by MTT dye uptake method. Cell proliferation assay was determined by using trypan blue dye exclusion method. Results: Our preliminary data shows that compared to OAS, CAS exhibited more significant reduction in the viability of MCF-7, MDA-MB-231 and SiHa. However, compared to CAS, OAS induced more decrease in viability in HeLa cells. Interestingly, both the types of SLs did not affect the viability of non-cancerous cells. Moreover, CAS, when used as a coating material, induced proliferation in macrophage cell line, RAW264.7. Conclusion: The present study provides an important clue towards the anti-cancer potential of OAS and CAS derived from Candida bombicola. Interestingly, the ability of CAS to promote the proliferation of non-cancerous cells suggests its future application as a scaffold for enhancing the adhesion and proliferation of normal cells.

C-H activation of methane to formaldehyde on Ce1-xZrxO2 thin films: a step to bridge the material gap - Dubey, Anjani; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (ChemCatChem, 2016)
Ce1−xZrxO2 (CZ) thin films were prepared by a combination of sol–gel and spin-coating methods and were evaluated for the C−H activation of methane by using a molecular beam set-up with the aim to bridge the material gap. The C−H activation of methane begins at 950 K, and a Ce-rich CZ composition displays a high selectivity (4–12 %) to the partially oxidised product, formaldehyde. A 10–12 % selectivity towards HCHO with 1.6 % methane conversion was observed with methane-rich CH4/O2 reactant compositions at 1050 K. Short contact times, prevalent under molecular beam conditions, could be a possible reason for HCHO formation. Although combustion products were observed instantly upon shining the mixture of reactants on CZ surfaces, up to 20 s delay was observed before formaldehyde generation, which indicates that the oxygen vacancy migration contributes to the rate-determining step and the diffusion-controlled nature of the reaction. A burst in HCHO generation at the point of molecular beam opening, after beam-closed conditions, suggests that the diffusion of oxygen vacancies to the surface is the reason for HCHO formation. Kinetics results also indicate the necessity of reduction sites for HCHO generation.

C-H activation of methane to syngas on MnxCe1-x-yZryO2 - a molecular beam study - Dubey, Anjani; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (Chemcatchem, 2016)
Mn-doped ceria zirconia thin films (MnxCe1-x-yZryO2, MCZ) were employed as flat model catalyst surfaces for CH4 activation. MCZ films exhibit characteristics of single crystal and powder materials, such as smooth surfaces and porosity. From molecular-beam studies, it has been identified that the oxygen storage capacity increases with Mn content. Mutually exclusive observation of H2O or a mixture of products (CO2+ CO + H-2) occurs, when the reactants was allowed to react directly on MCZ, underscoring their formation or prevention (and consumption), respectively. The results suggest that there is competition and cooperation among different elementary reactions under complementary conditions. From a significant partial oxidation of CH4 through C-H activation, it is found that formation of syngas begins at 700 K and the reaction rate increases with increasing temperature. Kinetic evidences indicate that the reaction proceeds through a combustion-reformation pathway.

CH3NH3Pb(BF4)(3) and (C4H9NH3)2Pb(BF4)(4) family of 3D and 2D perovskites without and with iodide and bromide ions substitution - Nagane, Satyawan; Ogale, Satishchandra B. (Journal of Physical Chemistry Letters, 2016)
We report the synthesis of fully molecular ion (BF4 )-based organicinorganic hybrid perovskite CH3NH3Pb(BF4)(3), which is a wide band gap semiconductor, and the same can be easily tuned toward the visible by the incorporation of bromide or iodide ions in the crystal framework simply by changing lead precursors. We have also successfully transformed the distorted 3D molecular-ion-induced perovskite to 2D (C4H9NH3)(2)Pb(BF4)(4), (C4H9NH3)(2)PbBr(4x)(BF4)(x), and (C4H9NH3)(2)PbI(4x)(BF4)(x) perovskites that exhibit the optical absorption over the UV to visible region. The thin films of molecular-ion-containing 2D perovskites with Br and I anions show blue and green luminescence, respectively, under UV illumination.

Characteristics of precipitation pattern in the Arabian Peninsula and its variability associated with ENSO - Babu, C. A.; Jayakrishnan, P. R.; Varikoden, Hamza (Arabian Journal of Geosciences, 2016)
A detailed analysis of the precipitation pattern of the Arabian Peninsula and its temporal and spatial variability were investigated in connection with ENSO. Also, the variability of precipitable water and circulation characteristics was examined for a better understanding. The study was carried out utilizing TRMM rainfall, NOAA OLR, precipitable water, wind, and humidity data sets. It is evident that Northern Arabian Peninsula receives high amount of rainfall mainly during winter and early summer (November to April) in connection with the passage of mid tropospheric westerly troughs and Mediterranean low-pressure systems. But the precipitation pattern over the Southern Arabian Peninsula reveals that it is mainly during summer (May to October) due to the Arabian Sea branch of monsoon and moisture laden cross equatorial LLJ flow. Further, analysis was carried out to assess the influence of ENSO on the precipitation pattern. Thorough analysis was carried out on the circulation pattern using velocity potential in the lower troposphere to understand the features of variability on Hadley/Walker circulation in relation with organized convection. El Nino and La Nina have profound influence on the rainfall pattern in a different manner in the Northern and Southern Arabian Peninsula. Large-scale circulation pattern as derived from velocity potential indicates that shifting of the rising/sinking limb of Hadley/Walker circulation associated with the ENSO causes variability in precipitation.
Keywords: Arid region; Circulation; El Nino and La Nina; Precipitation pattern

Characterization and valorization of biomass ashes - Trivedi, Nikhilesh S.; Mandavgane, Sachin A.; Mehetre, Sayaji; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2016)
In India, farming is the primary source of income for many families. Following each harvest, a huge amount of biomass is generated. These are generally discarded as "agrowaste," but recent reports have indicated several beneficial uses for these biomasses and their ashes. However, before the utilization of biomass ashes (BMAs), their chemical and physical properties need to be investigated (characterized) so as to utilize their potential benefit to the fullest. In this paper, eight different biomass ashes (soybean plant ash, mustard plant ash, maize ash, groundnut plant ash, cotton plant ash, wheat plant ash, pigeon peas ash, and groundnut shell ash) were characterized, and their chemical properties are discussed. Surface chemical composition analysis, proximate analysis, and ultimate analysis were performed on all BMA samples, and properties such as porosity, particle density, bulk density, point of zero charge, BET surface area, water-absorption capacity, and bulk parameters such as surface pH and surface charges were determined. BMAs were characterized by SEM and FTIR. The surface areas of biomass ashes vary from 1.9 to 46 m(2)/g, and point of zero charge for all BMAs exceed 9.8, which confirmed the alkaline nature of these samples. Based on the chemical composition, BMAs are categorized into four types (S, C, K, and CK), and their utilization is proposed based on the type. BMAs find applications in agriculture and construction industries; glass, rubber, and zeolite manufacturing; and in adsorption (as a source of silica/zeolites). The paper also discusses the research challenges and opportunities in utilization of BMAs.

Characterization of roseomonas and nocardioides spp. for arsenic transformation - Bagade, Aditi V.; Bachate, Sachin P.; Dholakia, Bhushan B.; Giri, Ashok P.; Kodam, Kisan M. (Journal of Hazardous Materials, 2016)
The metalloid arsenic predominantly exists in the arsenite [As(III)] and arsenate [As(V)]. These two forms are respectively oxidized and reduced by microbial redox processes. This study was designed to bioprospect arsenic tolerating bacteria from Lonar lake and to characterize their arsenic redoxing ability. Screening of sixty-nine bacterial species isolated from Lonar lake led to identification of three arsenic oxidizing and seven arsenic-reducing species. Arsenite oxidizing isolate Roseomonas sp. L-159a being closely related to Roseomonas cervicalis ATCC 49957 oxidized 2 mM As(III) in 60 h. Gene expression of large and small subunits of arsenite oxidase respectively showed 15- and 17-fold higher expression. Another isolate Nocardioides sp. L-37a formed a clade with Nocardioides ghangwensis JC2055, exhibited normal growth with different carbon sources and pH ranges. It reduced 2 mM As(V) in 36 h and showed constitutive expression of arsenate reductase which increased over 4-fold upon As(V) exposure. Genetic markers related to arsenic transformation were identified and characterized from the two isolates. Moderate resistance against the arsenicals was exhibited by the two isolates in the range of 1-5 mM for As(III) and 1-200 mM for As(V). Altogether we provide multiple evidences to indicate that Roseomonas sp. and Nocardioides sp. exhibited arsenic transformation ability. (C) 2016 Elsevier B.V. All rights reserved.

Characterization of two coleopteran alpha-amylases and molecular insights into their differential inhibition by synthetic alpha-amylase inhibitor, acarbose - Channale, Sonal M.; Bhide, Amey J.; Yadav, Yashpal; Kashyap, Garima; Pawar, Pankaj K.; Maheshwari, V. L.; Ramasamy, Sureshkumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2016)
Post-harvest insect infestation of stored grains makes them unfit for human consumption and leads to severe economic loss. Here, we report functional and structural characterization of two coleopteran alpha-amylases viz. Callosobruchus chinensis alpha-amylase (CcAmy) and Tribolium castaneum alpha-amylase (TcAmy) along with their interactions with proteinaceous and non-proteinaceous alpha-amylase inhibitors. Secondary structural alignment of CcAmy and TcAmy with other coleopteran alpha-amylases revealed conserved motifs, active sites, di-sulfide bonds and two point mutations at spatially conserved substrate or inhibitor binding sites. Homology modeling and molecular docking showed structural differences between these two enzymes. Both the enzymes had similar optimum pH values but differed in their optimum temperature. Overall, pattern of enzyme stabilities were similar under various temperature and pH conditions. Further, CcAmy and TcAmy differed in their substrate affinity and catalytic efficiency towards starch and amylopectin. HPLC analysis detected common amylolytic products like maltose and maltotriose while glucose and malto-tetrose were unique in CcAmy and TcAmy catalyzed reactions respectively. At very low concentrations, wheat alpha-amylase inhibitor was found to be superior over the acarbose as far as complete inhibition of amylolytic activities of CcAmy and TcAmy was concerned. Mechanism underlying differential amylolytic reaction inhibition by acarbose was discussed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acarbose; alpha-amylase; alpha-amylase inhibitor; Callosobruchus chinensis; Coleoptera; Tribolium castaneum

Characterizing flow and solid suspension in optimax crystallization workstation - Sardeshpande, M.; Pandit, A.; Vedantam, S.; Ranade, V. V. (North American Mixing Forum 2016 - Core Programming Area at the 2016 AIChE Annual Meeting, 2016)

Characterizing fruit and vegetable peels as bioadsorbents - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Current Science, 2016)
Fruit and vegetable peel (FVP) wastes are a commonly generated organic waste from both households and food-processing industries. However, FVPs are low-cost lignocellulosic materials that have some potential for reutilization. For its particular reutilization, the characterization of FVP is essential. In this regard, the present study provides a detailed physico-chemical characterization of commonly used FVPs such as pomegranate, pineapple, watermelon, garlic, green pea and pigeon pea. The materials were characterized by SEM, FTIR and TGA/DTG. Various properties of these materials, such as porosity, particle density, bulk density, surface charges, point of zero charge, surface pH, water absorption capacity and BET surface area were determined. The BET surface area of FVP was found in the range 1.0-1.4 m(2)/g. Water absorption capacity was highest for watermelon peel (11.5 ml/g), while it was lowest for pigeon pea peel (5.5 ml/g). Point of zero charge and surface pH of all FVPs were in the acidic range 3-6. The surface of FVP was irregular and rough with some pores. Thermal analysis showed that FVPs are thermally stable below 150 degrees C. The results of this study provide an understanding of the properties of FVPs and suggest that the materials can be used as a low-cost adsorbent.
Keywords: Bioadsorbent; fruit and vegetable peels; organic waste; physico-chemical characterization

Characterizing the nanoclay induced constrained amorphous region in model segmented polyurethane-urea/clay nanocomposites and its implications on gas barrier properties - Rath, Sangram K.; Sudarshan, Kathi; Bhavsar, Rupesh S.; Kharul, Ulhas K.; Pujari, Pradeep K.; Patri, Manoranjan; Khakhar, Devang V. (Physical Chemistry Chemical Physics, 2016)
There has been an increasing recognition of the fact that purely geometric factors associated with clay platelet dispersion in a polymer matrix cannot adequately explain the barrier properties of polymer/clay nanocomposites. The objective of the present work is to understand the nanoclay induced structural changes in a polyurethane-urea matrix and clay dispersion at different length scales using segment-specific characterization techniques and implications of the same in gas barrier properties using He, N-2 and CO2 as probe molecules. Wide angle X-ray diffraction (WAXD) and positron annihilation life time spectroscopy (PALS) studies revealed nanoclay induced alterations in the chain packing of the amorphous soft segments of the polyurethane matrix at a molecular scale of a few Angstroms. The hard segment organization and the phase morphology of the nanocomposites, spanning length scales of several nanometers, were investigated by small angle X-ray scattering (SAXS), scanning electron microscopy (SEM) and atomic force microscopy (AFM). Furthermore, the presence of a constrained amorphous region surrounding the nanoclay was confirmed from AFM, WAXD and PALS results. Several pertinent structural variables from the gas transport point of view were deduced from these characterization techniques to understand the effect of the barrier properties in tandem with the clay dispersion morphology.

Charge delocalization in the cascade band structure CdS/CdSe and CdS/CdTe core-shell sensitized with Re(I)-polypyridyl complex - Maity, Partha; Debnath, Tushar; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry C, 2016)
Charge-carrier dynamics of CdS quantum dot (QD) and CdS/CdSe type-I and CdS/CdTe type-II core shell nanocrystals (NCs) sensitized with a Re(I)-polypyridyl complex have been carried with special emphasis on studies on carrier delocalization and the role of Re-complex as a hole acceptor and sensitizer molecule. Our investigation confirmed photoexcited hole transfer from CdS and CdS/CdSe to the Re-complex, while no hole transfer was observed in the CdS/CdTe Re-complex system. This was rationalized by the evaluation of the relative energy levels, which revealed that such hole migration was not energetically favorable due to low-lying highest occupied molecular orbital (HOMO) of the Re-complex as compared with the valence band (VB) of CdTe shell; however, luminescence quenching from upper excited states of Re-complex was observed in the presence of all three QD and core shell systems, which has been attributed to electron injection from hot state (energetically higher than the LUMO state) of the Re-complex to the conduction band (CB) of the QDs. Transient absorption (lambda(pump) = 400 nm, lambda(probe) = 450-750 nm) spectra recorded for Re complex-sensitized CdS and CdS/CdSe composite in the femtosecond time domain revealed a broad transient absorption band in the 580-750 nm region with a peak around 595 nm, and this was attributed to the cation radical formation for Re-complex, either by capturing photoexcited hole from the NCs or by injecting electron to the CB of the NCs. As anticipated, no such spectrum was observed for the CdS/CdTe Re-complex composite system after 400 nm excitation. Electron injection from photoexcited Re-complex to CdS QD and CdS/CdSe core shell was found to be <100 fs, while the hole transfer from photoexcited CdS QD and CdS/CdSe core shell to Re-complex took place within the time scale of 900 fs and 2.5 ps, respectively.

ChemEngine: harvesting 3D chemical structures of supplementary data from PDF files - Karthikeyan, Muthukumarasamy; Vyas, Renu (Journal of Cheminformatics, 2016)
Digital access to chemical journals resulted in a vast array of molecular information that is now available in the supplementary material files in PDF format. However, extracting this molecular information, generally from a PDF document format is a daunting task. Here we present an approach to harvest 3D molecular data from the supporting information of scientific research articles that are normally available from publisher's resources. In order to demonstrate the feasibility of extracting truly computable molecules from PDF file formats in a fast and efficient manner, we have developed a Java based application, namely ChemEngine. This program recognizes textual patterns from the supplementary data and generates standard molecular structure data (bond matrix, atomic coordinates) that can be subjected to a multitude of computational processes automatically. The methodology has been demonstrated via several case studies on different formats of coordinates data stored in supplementary information files, wherein ChemEngine selectively harvested the atomic coordinates and interpreted them as molecules with high accuracy. The reusability of extracted molecular coordinate data was demonstrated by computing Single Point Energies that were in close agreement with the original computed data provided with the articles. It is envisaged that the methodology will enable large scale conversion of molecular information from supplementary files available in the PDF format into a collection of ready-to-compute molecular data to create an automated workflow for advanced computational processes.

Chemically delaminated free-standing ultrathin covalent organic nanosheets - Khayum, M. Abdul; Kandambeth, Sharath; Mitra, Shouvik; Nair, Sanoop B.; Das, Anuja; Nagane, Samadhan S.; Mukherjee, Rabibrata; Banerjee, Rahul (Angewandte Chemie-International Edition, 2016)
Covalent organic nanosheets (CONs) are a new class of porous thin two-dimensional (2D) nanostructures that can be easily designed and functionalized and could be useful for separation applications. Poor dispersion, layer restacking, and difficult postsynthetic modifications are the major hurdles that need to be overcome to fabricate scalable CON thin films. Herein, we present a unique approach for the chemical exfoliation of an anthracene-based covalent organic framework (COF) to N-hexylmaleimide-functionalized CONs, to yield centimeter-sized free-standing thin films through layer-by-layer CON assembly at the air-water interface. The thinlayer fabrication technique presented here is simple, scalable, and does not require any surfactants or stabilizing agents.

Chemically stable covalent organic framework (COF)-polybenzimidazole hybrid membranes: enhanced gas separation through pore modulation - Biswal, Bishnu P.; Chaudhari, Harshal D.; Banerjee, Rahul; Kharul, Ulhas K. (Chemistry-A European Journal, 2016)
Highly flexible, TpPa-1@PBI-BuI and TpBD@PBI-BuI hybrid membranes based on chemically stable covalent organic frameworks (COFs) could be obtained with the polymer. The loading obtained was substantially higher (50%) than generally observed with MOFs. These hybrid membranes show an exciting enhancement in permeability (about sevenfold) with appreciable separation factors for CO2/N-2 and CO2/CH4. Further, we found that with COF pore modulation, the gas permeability can be systematically enhanced.
Keywords: covalent organic frameworks; Gas separation; membranes; microporous materials; pore modulation

Chemoenzymatic access to (+)-artabotriol and its application in collective synthesis of (+)-grandiamide D, (-)-tulipalin B, (+)-spirathundiol, and (+)-artabotriolcaffeate - Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2016)
Starting from dimethyl (+/-)-2-hydroxy-3-methylenesuccinnate chemoenzymatic collective formal/total synthesis of enantiomerically pure bioactive natural products has been described via the advanced level common precursor (+)-artabotriol. An efficient enzymatic resolution with high enantiomeric purity, selective diester to diol reduction, and requisite dehydrative coupling reactions without any racemization are the significant topographies.
Keywords: (+)-artabotriol; collective synthesis; coupling reactions; dimethyl (+/-)-2-hydroxy-3-methylenesuccinate; Enzymatic resolution; Natural products; reduction

Chitosan-based lead ion-imprinted interpenetrating polymer network by simultaneous polymerization for selective extraction of lead(ii) - Hande, Pankaj E.; Kamble, Sanjay; Samui, Asit B.; Kulkarni, Prashant S. (Industrial & Engineering Chemistry Research, 2016)
In this study, we report the synthesis of a Pb(II) ion-imprinted interpenetrating polymer network (II-IPN) by simultaneous polymerization for selective extraction of Pb(II) from printed-circuit-board (PCB) recycling unit wastewater. Initially, a polymer network was synthesized by polymerization of methacrylic acid (monomer) and ethylene glycol dimethacrylate (cross-linker) and a second polymer network by chitosan (complexing monomer) and tetraethyl orthosilicate (cross-linker). The chemical structure and morphology of the II-IPN were analyzed using Fourier transform infrared, field-emission scanning electron microscopy, atomic force microscopy, and transmission electron microscopy. The interaction of the functionality in the II-IPN with Pb(II) through chelation was studied by X-ray photoelectron spectroscopy analysis. The maximum adsorption capacities for II-IPN and nonimprinted interpenetrating polymer network were 37.5 and 10.3 mg g(-1), respectively. The largest selectivity coefficient for Pb(II) in the presence of W(VI) was 161.58. The developed Pb(II) II-IPN was successfully employed for selective extraction of Pb(II) from PCB recycling unit wastewater.

Cholesterol-dependent conformational plasticity in GPCR dimers - Prasanna, Xavier; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
The organization and function of the serotonin1A receptor, an important member of the GPCR family, have been shown to be cholesterol-dependent, although the molecular mechanism is not clear. We performed a comprehensive structural and dynamic analysis of dimerization of the serotonin1A receptor by coarse-grain molecular dynamics simulations totaling 3.6 ms to explore the molecular details of its cholesterol-dependent association. A major finding is that the plasticity and flexibility of the receptor dimers increase with increased cholesterol concentration. In particular, a dimer interface formed by transmembrane helices I-I was found to be sensitive to cholesterol. The modulation of dimer interface appears to arise from a combination of direct cholesterol occupancy and indirect membrane effects. Interestingly, the presence of cholesterol at the dimer interface is correlated with increased dimer plasticity and flexibility. These results represent an important step in characterizing the molecular interactions in GPCR organization with potential relevance to therapeutic interventions.

Chord length distribution to particle size distribution - Pandit, Ajinkya V.; Ranade, Vivek V. (AICHE Journal, 2016)
A simple model is presented to extract the particle size distribution (PSD) from the chord length distribution measured using a focused beam reflectance measurement probe. The model can be implemented using simple spread sheeting tools and does not require the description of additional parameters as opposed to previous models. The model was validated for two systems consisting of spherical ceramic beads by comparing model predicted PSD against the PSD obtained through image analysis (IA). Then, the model was evaluated by considering various systems consisting of irregularly shaped particles (sand/zinc dust/plasma alumina). Model predictions accurately predicted the mean but over-predicted the variance of the PSD in comparison with the PSD obtained from IA. However, overall, a reasonable agreement was observed. Finally, the model was shown to be accurate in predicting PSD in comparison with the measured PSD for systems of practical relevance such as for paracetamol and p-aminophenol crystals. (c) 2016 American Institute of Chemical Engineers AIChE J, 62: 4215-4228, 2016

Chromium free high temperature water-gas shift catalyst for the production of hydrogen from waste derived synthesis gas - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Jang, Won-Jun; Shim, Jae-Oh; Jeon, Kyung-Won; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Applied Catalysis A-General, 2016)
A comparative study between monometallic (Me-CeO2, Me =Zn, Cu, Fe and Co) and Ni-doped bimetallic (Me-Ni-CeO2) catalysts has been performed in the high temperature water-gas shift (HT-WGS) reaction using waste derived synthesis gas. Experimental results revealed that Me-Ni-CeO2 exhibited higher catalytic performance than simple Me-CeO2 catalysts. Within the Me-Ni-CeO2 series, Co-Ni-CeO2 exhibited excellent and stable catalytic performance (CO conversion > 90%) at a very high GHSV of 143,000 h(-1). The existence of high" concentration of Ce3+ ions and oxygen vacancies on the catalyst surface were responsible for the increased WGS activity of Co-Ni-CeO2. In addition, Co-Ni-CeO2 maintains a stable performance for 50 h. However, commercial Fe2O3-Cr2O3 catalyst showed a steep decline from their initial CO conversion values 15-10% within 5 h. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeO2; Co-Ni-CeO2; Lattice strain; oxygen vacancies; Water-gas shift

Classification and study of near-surface region of active material for gas detection using x-ray photoelectron spectroscopy - More, Pravin S.; Late, Dattatray J.; Kondawar, Subhash B. (Advanced Materials Letters, 2016)
We report investigations on resistive material SnO2: Cu (9 wt. %) evaluated and optimized for the application of gas sensor. SnO2: Cu has been thoroughly characterized by using X-ray photoelectron spectroscopy (XPS). The deconvolution of XPS spectra confirms the existing surface reactive species in the form of states of the metal orbital and the presence of multiple pathways for the detection of CO vis-à-vis sintering temperature effect. Enhanced CO pickup at the sintering temperature of 650 0C (wide range and low sensitivity) and 750 0C (short range and high sensitivity) has been observed. The CO sensing and XPS data correlates well along with the nonconventional use of variation in average XPS background intensity of general scan seems to be related to optimized sensitivity conditions of various gases. Copyright © 2016 VBRI Press.

"Click" polymerization: a convenient strategy to prepare designer fullerene materials - Krishnamurthy, Munusamy; Krishnamoorthy, Kothandam; Arulkashmir, Arulraj; Raghavendra, V.; Murali, Adhigan; Jaisankar, Sellamuthu N.; Murugan, P.; Gurusamy-Thangavelu, Senthil A.; Nasar, A. Sultan; Mandal, Asit Baran; Samanta, Debasis (Materials & Design, 2016)
"Click" polymeric assemblies of fullerenes, thiophenes and aryl compounds were prepared for the first time to study their spectroscopic/chemical/electronic characteristics and possible applications in photovoltaic cells. The GPC and NMR spectroscopic data confirmed a moderate to high degree of polymerization while microscopic pictures showed well-defined arrangements of fullerenes. The FTIR studies indicated that the product is free from starting azide materials, whereas thermogravimetric analysis data suggested a good stability. Band gap of the material was determined using UV-Vis spectroscopy, cyclic voltammetric techniques and compared with computational investigation. The fullerene copolymer was fabricated as acceptor material in a bulk heterojunction photovoltaic cell. (C) 2016 Elsevier Ltd. All rights reserved.

CO oxidation on large high-index faceted Pd nanostructures - Sreedhala, S.; Sudheeshkumar, V.; Vinod, C. P. (Journal of Catalysis, 2016)
The structure sensitivity of CO oxidation has been investigated on oxide-supported palladium nanoparticles of different morphologies. The reactivity of concave nanocubes and nanoflowers that expose {3 1 0} and {3 1 1} high-index facets showed a lower onset temperature for CO oxidation than Pd nanospheres of size around 6 nm. These concave nanocubes and nanoflowers were also found to catalyze the CO oxidation reaction more efficiently than simple cubes and spheres of similar size that exposed low-index facets. The enhanced activity of these nanoparticles compared with other morphologies are attributed to the presence of sites of under-coordination on the exposed high-index facets. The larger nanoparticles were also found to be more stable in the reaction environment. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: CO oxidation; High-index facets; Pd nanoparticles; structure sensitivity

CO2 Laser direct written MOF-based metal-decorated and heteroatom-doped porous graphene for flexible all-solid-state microsupercapacitor with extremely high cycling stability - Basu, Aniruddha; Roy, Kingshuk; Sharma, Neha; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Rane, Sunit; Rode, Chandrashekhar V.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2016)
Over the past decade, flexible and wearable microelectronic devices and systems have gained significant importance. Because portable power source is an essential need of such wearable devices, currently there is considerable research emphasis on the development of planar interdigitated micro energy-torage devices by employing diverse precursor materials to obtain functional materials (functional carbon, oxides, etc.) with the desirable set of properties. Herein we report for the first time the use of metal organic framework (MOF) and zeolitic imidazolate framework (ZIF-67) for high-wavelength photothermal laser direct writing of metal-decorated, heteroatom-doped, porous few-layer graphene electrodes for microsupercapacitor application. We argue that the specific attributes of MOF as a precursor and the high-wavelength laser writing approach (which creates extremely high localized and transient temperature (>2500 degrees C) due to strong absorption by lattice vibrations) are together responsible for the peculiar interesting properties of the carbon material thus synthesized, thereby rendering extremely high cycling stability to the corresponding microsupercapacitor device. Our device exhibits near 100% retention after 200 000 cycles as well as stability under 150 degrees bending.

Cobalt ferrite bearing nitrogen-doped reduced graphene oxide layers spatially separated with microporous carbon as efficient oxygen reduction electrocatalyst - Kashyap, V.; Singh, S. K.; Kurungot, S. (ACS Applied Materials and Interfaces, 2016)
The present work discloses how high-quality dispersion of fine particles of cobalt ferrite (CF) could be attained on nitrogen-doped reduced graphene oxide (CF/N-rGO) and how this material in association with a microporous carbon phase could deliver significantly enhanced activity toward electrochemical oxygen reduction reaction (ORR). Our study indicates that the microporous carbon phase plays a critical role in spatially separating the layers of CF/N-rGO and in creating a favorable atmosphere to ensure the seamless distribution of the reactants to the active sites located on CF/N-rGO. In terms of the ORR current density, the heat-treated hybrid catalyst at 150 °C (CF/N-rGO-150) is found to be clearly outperforming (7.4 ± 0.5 mA/cm 2 ) the state-of-the-art 20 wt % Pt-supported carbon catalyst (PtC) (5.4 ± 0.5 mA/cm 2 ). The mass activity and stability of CF-N-rGO-150 are distinctly superior to PtC even after 5000 electrochemical cycles. As a realistic system level exploration of the catalyst, testing of a primary zinc-air battery could be demonstrated using CF/N-rGO-150 as the cathode catalyst. The battery is giving a galvanostatic discharge time of 15 h at a discharge current density of 20 mA/cm 2 and a specific capacity of ∼630 mAh g -1 in 6 M KOH by using a Zn foil as the anode. Distinctly, the battery performance of this system is found to be superior to that of PtC in less concentrated KOH solution as the electrolyte.

Cobalt-catalyzed bis-alkynylation of amides via double C–H bond activation - Landge, Vinod Gokulkrishna; Jaiswal, Garima; Balaraman, Ekambaram (Organic Letters, 2016)
The first example of cobalt-catalyzed selective bis-alkynylation of amides via double C–H bond activation with the directing assistance of a removable bidentate auxiliary is reported. The developed alkynylation strategy is simple, efficient, and tolerant of various functional groups including ether, amine, halides, and heterocyclic motifs. The reaction can be scaled up under mild conditions.

Cobalt-modified covalent organic framework as a robust wateroxidation electrocatalyst - Aiyappa, Harshitha Barike; Thote, Jayshri; Shinde, Digambar Balaji; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry of Materials, 2016)
The development of stable, efficient oxygen evolution reaction (OER) catalyst capable of oxidizing water is one of the premier challenges in the conversion of solar energy to electrical energy, because of its poor kinetics. Herein, a bipyridine-containing covalent organic framework (TpBpy) is utilized as an OER catalyst by way of engineering active Co(II) ions into its porous framework. The as-obtained Co-TpBpy retains a highly accessible surface area (450 m(2)/g) with exceptional stability, even after 1000 cycles and 24 h of OER activity in phosphate buffer under neutral pH conditions with an overpotential of 400 mV at a current density of 1 mA/cm(2). The unusual catalytic stability of Co-TpBpy arises from the synergetic effect of the inherent porosity and presence of coordinating units in the COF skeleton.

Colloidal assembly by ice templating - Kumaraswamy, Guruswamy; Biswas, Bipul; Choudhury, Chandan Kumar (Faraday Discussions, 2016)
We investigate ice templating of aqueous dispersions of polymer coated colloids and crosslinkers, at particle concentrations far below that required to form percolated monoliths. Freezing the aqueous dispersions forces the particles into close proximity to form clusters, that are held together as the polymer chains coating the particles are crosslinked. We observe that, with an increase in the particle concentration from about 106 to 108 particles per ml, there is a transition from isolated single particles to increasingly larger clusters. In this concentration range, most of the colloidal clusters formed are linear or sheet like particle aggregates. Remarkably, the cluster size distribution for clusters smaller than about 30 particles, as well as the size distribution of linear clusters, is only weakly dependent on the dispersion concentration in the range that we investigate. We demonstrate that the main features of cluster formation are captured by kinetic simulations that do not consider hydrodynamics or instabilities at the growing ice front due to particle concentration gradients. Thus, clustering of colloidal particles by ice templating dilute dispersions appears to be governed only by particle exclusion by the growing ice crystals that leads to their accumulation at ice crystal boundaries.

Comparative evaluation of packed-bed performance of biomass ashes as adsorbents for removal of diuron from aqueous solution - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Desalination and Water Treatment, 2016)
The packed-bed performance of biomass ashes (BMA), namely rice husk ash (RHA) and bagasse fly ash (BFA), was investigated for adsorptive removal of diuron (herbicide) under dynamic conditions. The effects of influent concentration (10-30mg/L), flow rate (1-3mL/min), and bed height (3-11cm) were studied at 30 degrees C and results were analyzed using various packed-bed models. The saturation time and capacity of the BFA bed were found to be approximately 1.5 and 1.6 times higher due to higher BET surface area than that of RHA bed. However, the bed utilization of RHA was higher because of smaller mass transfer zone. At a constant influent concentration (20mg/L) and flow rate (1mL/min), the maximum volume of diuron treated was 1,325 and 1,685mL using RHA (bed height 10cm) and BFA (bed height 11cm), respectively. Among the packed-bed models applied, the BDST model revealed the inconsistent MTZ and complex mechanism involving more than one rate-controlling step for the adsorption of diuron on both ashes. The kinetics in the initial part of the breakthrough curve was governed by external mass transfer according to the Bohart-Adams and Wolborska models. Better agreements between experimental and predicted values of bed capacities for each ash and the higher bed capacity of BFA than RHA were demonstrated by the Thomas model. The Yoon-Nelson model was found to be superior for BFA rather than for RHA to estimate 50% saturation time. However, the deactivation kinetic model, previously discovered and applied only for gas-solid adsorption, was found to be the best for the diuron-BMA (liquid-solid) adsorption system in this study.

Comparative functional characterization of eugenol synthase from four different ocimum species: implications on eugenol accumulation - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Singh, Priyanka A.; Joshi, Rakesh S.; Mulani, Fayaj A.; Dholakia, Bhushan B.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2016)
Isoprenoids and phenylpropanoids are the major secondary metabolite constituents in Ocimum genus. Though enzymes from phenylpropanoid pathway have been characterized from few plants, limited information exists on how they modulate levels of secondary metabolites. Here, we performed phenylpropanoid profiling in different tissues from five Ocimum species, which revealed significant variations in secondary metabolites including eugenol, eugenol methyl ether, estragole and methyl cinnamate levels. Expression analysis of eugenol synthase (EGS) gene showed higher transcript levels especially in young leaves and inflorescence; and were positively correlated with eugenol contents. Additionally, transcript levels of coniferyl alcohol acyl transferase, a key enzyme diverting pool of substrate to phenylpropanoids, were in accordance with their abundance in respective species. In particular, eugenol methyl transferase expression positively correlated with higher levels of eugenol methyl ether in Ocimum tenuiflorum. Further, EGSs were functionally characterized from four Ocimum species varying in their eugenol contents. Kinetic and expression analyses indicated, higher enzyme turnover and transcripts levels, in species accumulating more eugenol. Moreover, biochemical and bioinformatics studies demonstrated that coniferyl acetate was the preferred substrate over coumaryl acetate when used, individually or together, in the enzyme assay. Overall, this study revealed the preliminary evidence for varied accumulation of eugenol and its abundance over chavicol in these Ocimum species. Current findings could potentially provide novel insights for metabolic modulations in medicinal and aromatic plants. (C) 2016 Elsevier B.V. All rights reserved.

Comparative investigation of the ionicity of aprotic and protic ionic liquids in molecular solvents by using conductometry and NMR spectroscopy - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Chemphyschem, 2016)
Electrical conductivity (sigma), viscosity (), and self-diffusion coefficient (D) measurements of binary mixtures of aprotic and protic imidazolium-based ionic liquids with water, dimethyl sulfoxide, and ethylene glycol were measured from 293.15 to 323.15K. The temperature dependence study reveals typical Arrhenius behavior. The ionicities of aprotic ionic liquids were observed to be higher than those of protic ionic liquids in these solvents. The aprotic ionic liquid, 1-butyl-3-methylimidazolium tetrafluoroborate, [bmIm][BF4], displays 100% ionicity in both water and ethylene glycol. The protic ionic liquids in both water and ethylene glycol are classed as good ionic candidates, whereas in DMSO they are classed as having a poor ionic nature. The solvation dynamics of the ionic species of the ionic liquids are illustrated on the basis of the (HNMR)-H-1 chemical shifts of the ionic liquids. The self-diffusion coefficients D of the cation and anion of [HmIm][CH3COO] in D2O and in [D-6]DMSO are determined by using H-1 nuclei with pulsed field gradient spin-echo NMR spectroscopy.
Keywords: conducting materials; Electrochemistry; electrostatic interactions; Ion pairs; ionic liquids

Comparative study of dG affinity vs. DNA methylation modulating properties of side chain derivatives of procainamide: insight into its DNA hypomethylating effect - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Debgupta, Joyashish; Sangtani, E.; Narwade, S.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Deobagkar, D. D. (RSC Advances, 2016)
Procainamide derivatives have been synthesized to investigate the role of side chains in modulating the DNA methylation level in cancer cells and gain insight into its mechanism of action. The synthesized derivatives comprised of flexible (dimethyl), constrained (pyrrolidine, piperidine, morpholine) and planar aromatic (pyridine, phenyl) side chain motifs. The affinity of procainamide and its derivatives towards the deoxyguanosine (dG) base in neutral form has been assessed by performing Differential Pulse Voltammetry (DPV) under physiological conditions. Further, molecular docking with hemimethylated CpG rich DNA acquired from an active mDNMT-1-DNA (PDB ID-4DA4) crystal structure, reveals their preferential non-covalent interaction with dG nucleobase in the intercalation cavity of the minor groove. Differential affinity of the derivatives to dG base in neutral and bound forms (DNA) is correlated with their DNA methylation modulating properties at sub-lethal concentrations. Among all the derivatives, a compound with an aromatic phenyl side chain (1) has shown a highest binding affinity for dG nucleobase in neutral form as well as for partially denatured CpG rich DNA which is attributed to the formation of p/p stacking interaction in addition to N-H/O hydrogen bonding with the pyrimidine ring of dG base. It also shows the highest cytotoxicity and global hypomethylation at a sub-lethal level in the MCF-7 cancer cell line compared to other derivatives and procainamide. A docking study has also illustrated the plausible structural basis of DNA methylation modulating a property of procainamide. Strong association of procainamide with dG bases of partially denatured CpG rich DNA via H-bonding and other non-covalent interactions may alter the active topology of DNA required by the DNA-binding regulatory proteins (e. g. DNMT-1) which is validated by a DNMT-1 inhibition assay. This systematic investigation leads to a new potent alternative to procainamide being found and gives a plausible insight into the DNA hypomethylating effect of procainamide.

Complete metagenome sequencing based bacterial diversity and functional insights from basaltic hot spring of Unkeshwar, Maharashtra, India - Mehetre, Gajanan T.; Paranjpe, Aditi S.; Dastager, Syed Gulam; Dharne, Mahesh S. (Genomics Data, 2016)
Unkeshwar hot springs are located at geographical South East Deccan Continental basalt of India. Here, we report the microbial community analysis of this hot spring using whole metagenome shotgun sequencing approach. The analysis revealed a total of 848,096 reads with 212.87Mbps with 50.87% G+C content. Metagenomic sequences were deposited in SRA database with accession number (SUB1242219). Community analysis revealed 99.98% sequences belonging to bacteria and 0.01% to archaea and 0.01% to Viruses. The data obtained revealed 41 phyla including bacteria and Archaea and including 719 different species. In taxonomic analysis, the dominant phyla were found as, Actinobacteria (56%), Verrucomicrobia (24%), Bacteriodes (13%), Deinococcus-Thermus (3%) and firmicutes (2%) and Viruses (2%). Furthermore, functional annotation using pathway information revealed dynamic potential of hot spring community in terms of metabolism, environmental information processing, cellular processes and other important aspects. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of each contig sequence by assigning KEGG Orthology (KO) numbers revealed contig sequences that were assigned to metabolism, organismal system, Environmental Information Processing, cellular processes and human diseases with some unclassified sequences. The Unkeshwar hot springs offer rich phylogenetic diversity and metabolic potential for biotechnological applications.

Complexation key to a pH locked redox reaction - Rizvi, Masood Ahmad; Dangat, Yuvraj B.; Shams, Tahir; Khan, Khaliquz Zaman (Journal of Chemical Education, 2016)
An unfavorable pH can block a feasible electron transfer for a pH dependent redox reaction. In this experiment, a series of potentiometric titrations demonstrate the sequential loss in feasibility of iron(II) dichromate redox reaction over a pH range of 0-4. The pH at which this reaction failed to occur was termed as a pH locked reaction. The comparative ability of 10 selected iron binding ligands with varied propensity for the redox potential modification of Fe(III)/Fe(II) redox couple to restore/unlock the pH locked redox reaction is shown using potentiometric titrations. The spectrophotometric speciation analysis of Fe(III) Tiron complexation with pH was carried out to explain the differing ability of EDTA and Tiron to unlock the reaction under different pH Conditions. The experiment illustrates how environmental, biological redox reactions avoid severe laboratory conditions to occur and can be explored in the design of novel redox systems for natural attenuation of environmental toxins to their non- or lesser-toxic forms. The experiment also demonstrates prudent laboratory practice for safe waste disposal.
Keywords: Analytical Chemistry; Aqueous Solution Chemistry; Coordination Compounds; Oxidation/Reduction; pH; Physical Chemistry; Potentiometry; Second-Year Undergraduate; Thermodynamics; Titration/Volumetric Analysis; Upper-Division Undergraduate

Composition dependence of the glass forming ability in binary mixtures: the role of demixing entropy - Nandi, Ujjwal Kumar; Banerjee, Atreyee; Chakrabarty, Suman; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2016)
We present a comparative study of the glass forming ability of binary systems with varying composition, where the systems have similar global crystalline structure (CsCl+fcc). Biased Monte Carlo simulations using umbrella sampling technique show that the free energy cost to create a CsCl nucleus increases as the composition of the smaller particles is decreased. We find that systems with comparatively lower free energy cost to form CsCl nucleus exhibit more pronounced pre-crystalline demixing near the liquid/crystal interface. The structural frustration between the CsCl and fcc crystal demands this demixing. We show that closer to the equimolar mixture, the entropic penalty for demixing is lower and a glass forming system may crystallize when seeded with a nucleus. This entropic penalty as a function of composition shows a non-monotonic behaviour with a maximum at a composition similar to the well known Kob-Anderson (KA) model. Although the KA model shows the maximum entropic penalty and thus maximum frustration against CsCl formation, it also shows a strong tendency towards crystallization into fcc lattice of the larger ``A'' particles which can be explained from the study of the energetics. Thus for systems closer to the equimolar mixture although it is the requirement of demixing which provides their stability against crystallization, for KA model it is not demixing but slow dynamics and the presence of the ``B'' particles make it a good glass former. The locally favoured structure around ``B'' particles is quite similar to the CsCl structure and the incompatibility of CsCl and fcc hinders the fcc structure growth in the KA model. Although the glass forming binary systems studied here are quite similar, differing only in composition, we find that their glass forming ability cannot be attributed to a single phenomenon. Published by AIP Publishing.

Compounds with low-valent p-block elements for small molecule activation and catalysis - Yadav, Sandeep; Saha, Sumana; Sen, Sakya S. (Chemcatchem, 2016)
The past decade has witnessed staggering progress in the chemistry of compounds with low-valent main-group elements. Although these discoveries are mostly fundamental by nature, these compounds show promising reactivity towards small molecule activation. The reactivity of these compounds stems from the modest HOMO-LUMO energy gap; a characteristic known for the transition metals. The journey began in 2005 with the facile activation of dihydrogen by an alkyne analog of germanium [ArGeGeAr; Ar=2,6-Trip(2)-C6H3 (Trip=2,4,6-iPr(3)-C6H2)]. Subsequently, tremendous progress has been achieved in understanding and elucidating the potential of these compounds to activate small molecules as well as to use them in a variety of stoichiometric and catalytic transformations. In this review, we focus on developments in the activation of H-2, NH3, CO, and CO2 by compounds with multiply bound or open shell main-group elements. Emphasis will be given to their catalytic activity.
Keywords: activation; carbenes; main-group elements; silylenes; small molecules

Concentration-dependent apparent partition coefficients of ionic liquids possessing ethyl-and bi-sulphate anions - Jain, Preeti; Kumar, Anil (Physical Chemistry Chemical Physics, 2016)
This study deals with the concentration dependent apparent partition coefficients log P of the ethyl and bisulfate-based ionic liquids. It is observed that the bisulfate-based ionic liquids show different behaviour with respect to concentration as compared to ethyl sulphate-based ionic liquids. It is significant and useful analysis for the further implementation of alkyl sulfate based ionic liquids as solvents in extraction processes. The log P values of the ethyl sulphate-based ionic liquids were noted to vary linearly with the concentration of the ionic liquid, whereas a flip-flop trend with the concentration for the log P values of the bisulphate-based ionic liquids was observed due to the difference in hydrogen bond accepting basicity and possibility of aggregate formation of these anions. The pi-pi interactions between the imidazolium and pyridinium rings were seen to affect the log P values. The alkyl chain length of anions was also observed to influence the log P values. The hydrophobicity of ionic liquid changes with the alkyl chain in the anion in the order; [HSO4](-) < [EtSO4](-) < [BuSO4](-).

Concise enantioselective synthesis of (+)-L-733,060 and (+)-T-2328 via sequential proline catalysis - Lalwani, Komal G.; Sudalai, Arumugam (Synlett, 2016)
A new, sequential proline-catalyzed approach to the synthesis of (+)-L-733,060 and (+)-T-2328 in high optical purity (93% ee) is described starting from phenyl N-Boc imine. The strategy involves proline-catalyzed Mannich reaction of an arylimine with acetaldehyde followed by -aminoxylation/Wittig olefination in a sequential fashion as the key steps.
Keywords: Aminoxylation; imine; Mannich reaction; olefination; sequential

Concise enantioselective synthesis of (+)-sertraline and (-)-CP-52002 using proline catalysis - Kalshetti, Rupali G.; Venkataramasubramanian, V.; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (+)-sertraline and its C-4 epimer (-)-CP-52002 with an overall yield of 30%, respectively, as its hydrochloride has been described. The key steps are the proline catalyzed Mannich reaction of acetaldehyde and acid catalyzed intramolecular Friedel-Crafts' alkylation reaction of olefin proceeding with high optical purities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Indatraline; Mannich reaction; Proline catalysis; Sertraline; Tametraline

Conformational dynamics of GPCR dimers is dependent on membrane cholesterol - Sengupta, Durba; Prasanna, Xavier; Chattopadhyay, Amitabha (Biophysical Journal, 2016)

Conformational energy landscape of the ritonavir molecule - Chakraborty, Debayan; Sengupta, Neelanjana; Wales, David J. (Journal of Physical Chemistry B, 2016)
Conformational polymorphism of ritonavir, a well-known pharmaceutical drug, is intricately linked to its efficacy in the treatment of acquired immunodeficiency syndrome (AIDS). Polymorphic transition from the crystalline form I to form II leads to the loss of bioactivity. The constituent ritonavir molecules adopt a trans configuration about the carbamate torsion angle in the form I crystal, and a cis configuration in the form II crystal. Investigating the energetics and mechanistic features of conformational transitions at the single molecule level is a key step toward decoding the complex features of the solid state polymorphism. In this work, we employ the energy landscape framework to investigate the conformational transitions of an isolated ritonavir molecule. The landscape is explored using discrete path sampling (DPS) and visualized in terms of disconnectivity graphs. We identify two distinct funnels corresponding to the two molecular forms that are identified by crystallography. The two regions can be reliably distinguished using the carbamate torsion angle, and the corresponding interconversion rates are predicted to follow Arrhenius behavior. The results provide mechanistic insight into pathways for cis <-> trans interconversion at the molecular level and may also help in elucidating the polymorphic transitions in the crystal state.

Conformational features of the Aβ42 peptide monomer and its interaction with the surrounding solvent - Khatua, Prabir; Jose, Jaya C.; Sengupta, Neelanjana; Bandyopadhyay, Sanjoy (Physical Chemistry Chemical Physics, 2016)

Conjugated porous polymers as precursors for electrocatalysts and storage electrode materials - Bhosale, Manik E.; Illathvalappil, Rajith; Kurungot, Sreekumar; Krishnamoorthy, Kothandam (Chemical Communications, 2016)
Conjugated porous polymers were used as precursors to prepare nitrogen and sulphur doped carbon atoms, which were then used for oxygen reduction and energy storage.

Constructing covalent organic frameworks in water via dynamic covalent bonding - Thote, Jayshri; Aiyappa, Harshitha Barike; Kumar, Raya Rahul; Kandambeth, Sharath; Biswal, Bishnu P.; Shinde, Digambar Balaji; Roy, Neha Chaki; Banerjee, Rahul (Iucrj, 2016)
The formation of keto-enamine based crystalline, porous polymers in water is investigated for the first time. Facile access to the Schiff base reaction in water has been exploited to synthesize stable porous structures using the principles of Dynamic Covalent Chemistry (DCC). Most credibly, the water-based Covalent Organic Frameworks (COFs) possess chemical as well as physical properties such as crystallinity, surface area and porosity, which is comparable to their solvothermal counterparts. The formation of COFs in water is further investigated by understanding the nature of the monomers formed using hydroxy and non-hydroxy analogues of the aldehyde. This synthetic route paves a new way to synthesize COFs using a viable, greener route by utilization of the DCC principles in conjunction with the keto-enol tautomerism to synthesize useful, stable and porous COFs in water.

Continuous flow doebner–miller reaction and isolation using continuous stirred tank reactors - Yadav, Maruti B.; Kulkarni, Sourabh; Joshi, Ramesh A.; Kulkarni, Amol A. (Organic Process Research & Development, 2016)
Continuous flow Doebner–Miller synthesis of different quinaldines from respective anilines is demonstrated using sulfuric acid as a homogeneous catalyst. The extent of reaction was monitored for various parameters, namely, temperature, residence time, mole ratio of sulfuric acid to substrate, mole ratio of crotonaldehyde to substrate, and so forth. Continuous stirred reactors in series were used as a preferred configuration for this rection that generates byproduct in the form of sticky solid material. The approach has been extended for six different anilines, and the results are compared with batch reactions. Continuous stirred reactors in series with distributed dosing of crotonaldehyde facilitated a continuous flow reaction with lower byproduct formation, increased yields, and continuous workup and is a scalable approach.

Contriving a catalytically active structure from an inert conformation: a density functionalinvestigation of Al, Hf, and Ge doping of Au-20 tetrahedral clusters - Manzoor, Dar; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2016)
The transformation of an inert structure into a catalytically active conformation has immense potential from a structural engineering point of view. In the present work, we explored methods of achieving such a transformation through a density-functional-based study. Au-20 is known be one of the most stable and catalytically inert gold clusters, with a well-known tetrahedral structure. We demonstrate the transformation of the inert Au-20 conformation into a highly active catalytic cluster through selective doping with Hf and Ge atoms. Depending on the dopant, the inert tetrahedral Au-20 cluster evolves into either an endohedral or a hollow-cage-like conformation. The structural changes are manifested in the catalytic properties as well, with the result that the transformed doped cages exhibit extremely low activation barriers for the environmentally important CO oxidation reaction as compared to reported inert Au-20 cluster. The activation barriers for CO oxidation are particularly low (<0.12 eV) when germanium is directly involved in the CO oxidation. Thus, the current work highlights the importance of engineering structural properties of metal nanoclusters with the help of heteroatom dopants for future applications in efficient catalysis.

Controllable synthesis of SnO2 photocatalyst with superior photocatalytic activity for the degradation of methylene blue dye solution - Prakash, K.; Kumar, P. Senthil; Pandiaraj, S.; Saravanakumar, K.; Karuthapandian, S. (Journal of Experimental Nanoscience, 2016)
SnO2 photocatalyst was successfully synthesised by novel chemical route in hydrothermal environment and annealed at two different temperatures viz 550 and 600 degrees C, respectively. The crystal structure, optical properties, surface and bulk morphology have been characterised using various tools like X-ray diffraction (XRD), UV visible spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscope (TEM) and scanning electron microscope (SEM). Cubic, spheres and porous like morphology of SnO2 photocatalyst was successfully confirmed using SEM micrographs and TEM. In addition to this the photocatalytic activity was evaluated towards the degradation of methylene blue dye solution. SnO2 photocatalyst annealed at 600 degrees C exhibits excellent photocatalytic efficiency which may be attributed to the unique morphology, high crystalline nature and charge separation. The photocatalyst efficiency was further tested towards the concentration of dye, catalyst dosage and pH of the dye. The involvement of center dot OH in the photocatalytic reaction was evidenced using trapping experiment by employing different scavengers. The photocatalyst was moderately active, stable upto its fifth usage and stability of the photocatalyst before and after the photocatalytic reaction was also been studied using XRD and SEM.

Controlled synthesis of end-functionalized mannose-6-phosphate glycopolypeptides for lysosome targeting - Das, Soumen; Parekh, Nimisha; Mondal, Basudeb; Sen Gupta, Sayam (ACS Macro Letters, 2016)
The ubiquitous expression of the mannose-6-phosphate receptor on the majority of human cells makes it a valid target in the quest to deliver therapeutics selectively to the lysosome. In this work end-functionalized polyvalent mannose-6-phosphate glycopolypeptides (M6P-GPs) with high molecular weights (up to 22 kDa) have been synthesized via NCA polymerization. These synthetic M6P-GPs were found to display minimal toxicity to cells in vitro and show exceptional selectivity for trafficking into lysosomes in various cell lines. Comparison of the cellular uptake behavior of M6P-GP and the corresponding mannose-GP polymer reveals that incorporation of the phosphate moiety at the 6-position of mannose completely alters its trafficking behavior and becomes exclusively lysosome specific. We also demonstrate that trafficking of M6P-GPs in mammalian cells is likely associated with the CI-MPR receptor pathway.

Convenient synthesis of alpha,alpha `- homo- and alpha,alpha `-hetero-bifunctionalized poly(epsilon-caprolactone)s by ring opening polymerization: the potentially valuable precursors for miktoarm star copolymers - Patil, Sachin S.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Two new ring opening polymerization (ROP) initiators, namely, (3-allyl-2-(allyloxy)phenyl)methanol and (3-allyl-2-(prop-2-yn-1-yloxy)phenyl)methanol each containing two reactive functionalities viz. allyl, allyloxy and allyl, propargyloxy, respectively, were synthesized from 3-allylsalicyaldehyde as a starting material. Well defined -allyl, -allyloxy and -allyl, -propargyloxy bifunctionalized poly(epsilon-caprolactone)s with molecular weights in the range 4200-9500 and 3600-10,900 g/mol and molecular weight distributions in the range 1.16-1.18 and 1.15-1.16, respectively, were synthesized by ROP of epsilon-caprolactone employing these initiators. The presence of -allyl, -allyloxy and -allyl, -propargyloxy functionalities on poly(epsilon-caprolactone)s was confirmed by FT-IR, H-1, C-13 NMR spectroscopy, and MALDI-TOF analysis. The kinetic study of ROP of epsilon-caprolactone with both the initiators revealed the pseudo first order kinetics with respect to epsilon-caprolactone consumption and controlled behavior of polymerization reactions. The usefulness of -allyl, -allyloxy functionalities on poly(epsilon-caprolactone) was demonstrated by performing the thiol-ene reaction with poly(ethylene glycol) thiol to obtain (mPEG)(2)-PCL miktoarm star copolymer. -Allyl, -propargyloxy functionalities on poly(epsilon-caprolactone) were utilized in orthogonal reactions i.e copper catalyzed alkyne-azide click (CuAAC) with azido functionalized poly(N-isopropylacrylamide) followed by thiol-ene reaction with poly(ethylene glycol) thiol to synthesize PCL-PNIPAAm-mPEG miktoarm star terpolymer. The preliminary characterization of A(2)B and ABC miktoarm star copolymers was carried out by H-1 NMR spectroscopy and gel permeation chromatography (GPC). (c) 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2016, 54, 844-860
Keywords: 3-allylsalicyaldehyde; alpha `-allyloxy and alpha-allyl; alpha `-propargyloxy bifunctionalized poly (epsilon-caprolactone)s; alpha-allyl; atom transfer radical polymerization; orthogonal reactions; ring-opening polymerization; star copolymers

Coordination polymers of Fe(III) and Al(III) ions with TCA ligand: distinctive fluorescence, CO2 uptake, redox-activity and oxygen evolution reaction - Dhara, Barun; Sappati, Subrahmanyam; Singh, Santosh K.; Kurungot, Sreekumar; Ghosh, Prasenjit; Ballav, Nirmalya (Dalton Transactions, 2016)
Fe and Al belong to different groups in the periodic table, one from the p-block and the other from the d-block. In spite of their different groups, they have the similarity of exhibiting a stable 3+ oxidation state. Here we have prepared Fe(III) and Al(III) based coordination polymers in the form of metal-organic gels with the 4,4', 4 `'-tricarboxyltriphenylamine (TCA) ligand, namely Fe-TCA and Al-TCA, and evaluated some important physicochemical properties. Specifically, the electrical conductivity, redox-activity, porosity, and electrocatalytic activity (oxygen evolution reaction) of the Fe-TCA system were noted to be remarkably higher than those of the Al-TCA system. As for the photophysical properties, almost complete quenching of the fluorescence originating from TCA was observed in case of the Fe-TCA system, whereas for the Al-TCA system a significant retention of fluorescence with red-shifted emission was observed. Quantum mechanical calculations based on density functional theory (DFT) were performed to unravel the origin of such discriminative behaviour of these coordination polymer systems.

Copolymers comprising monomers with various dipole and quadrupole as active material in organic field effect transistors - Singh, Saumya; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam (Journal of Physical Chemistry C, 2016)
Copolymers of 4,4-difluoro-4-borata-3a-azonia-4a-aza-s-indacene (BODIPY) and diketopyrrolopyrrole (DPP) were synthesized. The BODIPY has a permanent dipole and the DPP has a quadrupole. The dipole and the quadrupole in the monomers are expected to bring the polymers closer and to improve the charge-transport properties. By judicious choice of these monomers, the electron wave function is evenly distributed through the molecules. However, we notice that the torsional angle at the connecting point of BODIPY and DPP is a function of the methyl moieties at the beta,beta' position of the BODIPY. We found that the polymer comprising DPP and BODIPY without methyl moiety at beta,beta' position showed a torsional angle of 27, the lowest among the three polymers studied in this work. The absorption spectrum of the polymer showed transitions because of vibronic coupling indicating linearity along the polymer backbone. The band gap of the polymer was found to be 1.2 eV. The thermally stable polymer showed an ambipolar charge transport of 0.01 cm(2)/(V s).

Correlating Nitrile IR frequencies to local electrostatics quantifies noncovalent interactions of peptides and proteins - Deb, Pranab; Haldar, Tapas; Kashid, Somnath M.; Banerjee, Subhrashis; Chakrabarty, Suman; Bagchi, Sayan (Journal of Physical Chemistry B, 2016)
Noncovalent interactions, in particular the hydrogen bonds and nonspecific long-range electrostatic interactions are fundamental to biomolecular functions. A molecular understanding of the local electrostatic environment, consistently for both specific (hydrogen-bonding) and nonspecific electrostatic (local polarity) interactions, is essential for a detailed understanding of these processes. Vibrational Stark Effect (VSE) has proven to be an extremely useful method to measure the local electric field using infrared spectroscopy of carbonyl and nitrile based probes. The nitrile chemical group would be an ideal choice because of its absorption in an infrared spectral window transparent to biomolecules, ease of site-specific incorporation into proteins, and common occurrence as a substituent in various drug molecules. However, the inability of VSE to describe the dependence of IR frequency on electric field for hydrogen-bonded nitriles to date has severely limited nitrile's utility to probe the noncovalent interactions. In this work, using infrared spectroscopy and atomistic molecular dynamics simulations, we have reported for the first time a linear correlation between nitrile frequencies and electric fields in a wide range of hydrogen-bonding environments that may bridge the existing gap between VSE and H-bonding interactions. We have demonstrated the robustness of this field-frequency correlation for both aromatic nitriles and sulfur-based nitriles in a wide range of molecules of varying size and compactness, including small molecules in complex solvation environments, an amino acid, disordered peptides, and structured proteins. This correlation, when coupled to VSE, can be used to quantify noncovalent interactions, specific or nonspecific, in a consistent manner.

Correlating the role of hydrophilic/hydrophobic nature of Rh(I) and Ru(II) supported organosilica/silica catalysts in organotransformation reactions - Lazar, Anish; George, Shoy C.; Jithesh, P. R.; Vinod, C. P.; Singh, A. P. (Applied Catalysis A-General, 2016)
Highly reactive and hydrophobic triphenyl phosphine based rhodium(I) and ruthenium(II) organometallic complexes over benzene containing periodic mesoporous organosilica (PMOB) have been synthesized. This has been achieved by the immobilization of neat metal complexes like RhCl(PPh3)(3) [Wilkinson catalyst], RuHCl(CO)(PPh3)(3) and RuCl2(PPh3)(3) over aminofunctionalized PMOB to get RhCl(PPh3)(2)-PrNH2PMOB, RuHCl(CO)(PPh3)(2)-PrNH2PMOB and RuCl2(PPh3)(3)-PrNH2PMOB, respectively. The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption analyses, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, SEM, TEM and contact angle measurements. The XRD and N-2 sorption analyses showed excellent textural properties with ordered mesoporous channel structure of all synthesized catalysts. The organic moieties anchored in PMOB were confirmed by C-13 CPMAS NMR and Fr-IR spectroscopy with Si-29 CPMAS NMR spectroscopy providing the information about the degree of functionalization of surface silanol groups with organic moiety. The Rh(I) and Ru(II) complexes supported on MCM-41/SBA-15/PMOE (ethane-PMO) were synthesized, and their catalytic activities in hydrogenation and sulfoxidation reactions were compared with Rh(I) and Ru(II) complexes supported on PMOB. The results show that PMOB based catalysts exhibit higher activities and selectivities than MCM-41/SBA-15/PMOB supported catalysts, neat homogeneous complexes and without catalyst. The better catalytic performance of PMOB based catalyst is attributed to the hydrophobic nature and high surface area of the PMOB support. The recycling studies of anchored catalysts show no major deactivation of the catalyst. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Hydrogenation and sulfoxidation; Hydrophobic; Periodic mesoporous organosilica

Counteranion driven homochiral assembly of a cationic C-3-symmetric gelator through ion-pair assisted hydrogen bond - Maity, Arunava; Gangopadhyay, Monalisa; Basu, Arghya; Aute, Sunil; Babu, Sukumaran Santhosh; Das, Amitava (Journal of the American Chemical Society, 2016)
The helical handedness in achiral self-assemblies is mostly complex due to spontaneous symmetry breaking or kinetically controlled random assembly formation. Here an attempt has been made to address this issue through chiral anion exchange. A new class of cationic achiral C-3-symmetric gelator devoid of any conventional gelation assisting functional units is found to form both right-and left-handed helical structures. A chiral counteranion exchange-assisted approach is successfully introduced to control the chirality sign and thereby to obtain preferred homochiral assemblies. Formation of anion-assisted chiral assembly was confirmed by circular dichroism (CD) spectroscopy, microscopic images, and crystal structure. The X-ray crystal structure reveals the construction of helical assemblies with opposite handedness for (+)- and (-)-chiral anion reformed gelators. The appropriate counteranion driven ion-pair-assisted hydrogen-bonding interactions are found responsible for the helical bias control in this C-3-symmetric gelator.

Crosslinked polymer embedded Cu/Ag for comparative drug adsorption and kinetics evaluation - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (International Journal of Polymeric Materials and Polymeric Biomaterials, 2016)
Two-dimensional crosslinked polymer (2-DCP) was synthesized for evaluation of drug adsorption and kinetics thereof. Further, polymer properties were evaluated and parameters such as contact time and adsorption isotherm were also studied. Herein, contact time demonstrated 83% and 85% of drug loading in an acidic medium for two-dimensional crosslinked polymer embedded copper and silver (2-DCP-Cu/Ag), respectively in 24h. Initial 4h is the exponential drug loading period whereas drug loading was increased gradually after 4h. Salbutamol loading was well-fitted to Langmuir adsorption isotherm, which indicated a monolayer drug adsorption with respect to 2-DCP-Cu/Ag. Pseudo first- and pseudo second-order kinetics was evaluated to perceive the drug adsorption mechanism and equilibrium adsorption capacity. Monolayer drug adsorption with chemisorption mechanism was observed for 2-DCP-Cu/Ag. In addition to this, decomposition temperature of polymer was 440 and 325 degrees C while glass transition temperature of polymer was 280 and 200 degrees C before and after metal modification, respectively. (A=aqueous phase; B=organic phase; C=drug solution; D=drug loaded polymer; E=enlarged drug loaded polymer.) [GRAPHICS] .
Keywords: Adsorption isotherm; adsorption kinetics; crosslink polymer; drug loading; langmuir adsorption isotherm; salbutamol

Crystal engineering of a zwitterionic drug to neutral cocrystals: a general solution for floxacins - Gunnam, Anilkumar; Suresh, Kuthuru; Ganduri, Ramesh; Nangia, Ashwini (Chemical Communications, 2016)
The transformation of zwitterionic Sparfloxacin (SPX) to the neutral form is achieved by cocrystallization. Neutral forms of drugs are important for higher membrane permeability, while zwitterions are more soluble in water. The twin advantages of higher solubility/dissolution rate and good stability of neutral SPX are achieved in a molecular cocrystal compared to its zwitterionic SPX hydrate. The amine-phenol supra-molecular synthon drives cocrystal formation, with the paraben ester acting as a "proton migrator'' for the ionic to neutral transformation.

Crystal structure, computational studies, and stereoselectivity in the synthesis of 2-aryl-thiazolidine-4-carboxylic acids via insitu imine intermediate - Jagtap, Rohidas M.; Rizvi, Masood A.; Dangat, Yuvraj B.; Pardeshi, Satish K. (Journal of Sulfur Chemistry, 2016)
This article presents the synthesis of (2R/2S,4R)-2-aryl-thiazolidine-4-carboxylic acids via nucleophilic addition of L-Cysteine on aromatic aldehydes involving a yield and time-effective room temperature reaction in an aqueous DMSO medium in the presence of NaHCO3 as a base. The synthesized diastereomers were spectroscopically characterized and quantified for diastereomeric excess by liquid chromatography-mass spectrometry analysis. The impact of the type and position of substituent in aromatic aldehydes on reaction time, % yield, H-1 NMR shift at newly formed chiral center [C(2)-H], and diastereomeric excess (de%) have been investigated. A plausible mechanism for stereoselectivity via an in situ imine intermediate is proposed using real-time IR monitoring of the synthetic reaction based on the significant signals at 1597, 1593cm(-1) for imine (C=N) stretching. The imine mechanism for stereoselectivity was further supported by NMR studies of azomethine C-13 NMR signals at 159, 160ppm and by the single crystal structure of hitherto unknown (2S,4R)-3-(tert-butoxycarbonyl)-2-(2-hydroxyphenyl)thiazolidine-4-carbox ylic acid (3a) obtained as a major diastereomer in the synthesis of the butyloxy carbonyl (BOC) derivative of (2R/2S,4R)-2-(2-hydroxyphenyl)thiazolidine-4-carboxylic acid. The significant ortho-OH effect of phenolic hydroxyl group leading to strong hydrogen bondings plays a vital role in the formation of 2S,4R BOC derivative stereoselectively. The frontier molecular orbitals, possible electronic excitations, IR band characterizations, and reactivity parameters of newly reported compound (3a) have been predicted using quantum chemical descriptors from density functional theory. The theoretical exploration of experimental spectra using time-dependent DFT indicated a (-*) transition between HOMO and LUMO in the ultraviolet region.
Keywords: 2-aryl-thiazolidine-4-carboxylic acids; density function theory; frontier molecular orbitals; imine intermediate; X-ray crystal structure

Crystallization kinetics for carbon dioxide gas hydrate in fixed bed and stirred tank reactor - Kumar, Asheesh; Khatri, Dishant; Lee, Ju Dong; Kumar, Rajnish (Korean Journal of Chemical Engineering, 2016)
The phase change from germ nuclei to growth nuclei and subsequent volume transformation in a crystallization process was modeled by Avrami equations. The phase change during the hydrate formation was fitted with the classical Avrami model by utilizing gas uptake data. The idea is to understand the difference in growth behavior of hydrate crystals when in small pores compared to a stirred tank reactor which does not pose any physical restrictions to hydrate growth. The parameters n and k of the Avrami equation were determined explicitly for CO2 hydrate formation.
Keywords: Avrami Equation; CO2 Capture & Sequestration; Fixed Bed; Gas hydrates; kinetics

Cu-Catalyzed iminative hydroolefination of unactivated alkynes en route to 4-imino-tetrahydropyridines and 4-aminopyridines - Kumar, Ravi; Thorat, Shridhar H.; Reddy, Maddi Sridhar (Chemical Communications, 2016)
A general method for synthesizing 4-imino tetrahydropyridine derivatives is achieved, from readily available beta-enaminones and sulfonyl azides, which comprises a sequential copper catalyzed ketenimine formation and its hitherto inaccessible intramolecular hydrovinylation. The products are shown as ready precursors for highly valuable 4-sulfonamidopyridine derivatives via DDQ mediated oxidation.

Cu-catalyzed sequential C-N bond formations: expeditious synthesis of tetracyclic indoloindol-3-ones - Kulkarni, Anand M.; Srinivas, Kolluru; Deshpande, Mukund V.; Ramana, Chepuri V. (Organic Chemistry Frontiers, 2016)
The tetracyclic indoloindol-3-one core has been forged from easily accessible 2,2'-bis-bromochalcones employing a reaction cascade comprising Cu-catalyzed SNAr with azide; nitrene C-H insertion and intramolecular Ullmann reaction with all three C-N bond formations in one-go.

Culture conditions for the production of thermostable lipase by thermomyces lanuginosus - Sreelatha, B.; Vankudoth, Koteswara Rao; Kumar, R. Ranjith; Girisham, Sivadevuni; Reddy, S. M. (Journal of Basic and Applied Sciences, 2016)
In the present investigation lipase production by three strains of thermophilic Thermomyces lanuginosus (GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14) was carried out in submerged fermentation process. Olive oil and triacetin (0.1%) were added to the basal medium, which stimulated the lipase production. The maximum lipase was produced by GSLMBKU-10 and GSLMBKU-13 in yeast extract starch medium supplemented with triacetin (0.1%). The optimum pH was recorded at 6.0, 6.5 and 7.0 by GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14 respectively. T. lanuginosus GSLMBKU-10 strains failed to produce lipase at pH 8.0. The optimum temperature for lipase production was observed at 45 °C by GSLMBKU-14 and GSLMBKU-10, while that for GSLMBKU-13 was at 50 °C. The marginal temperature ranged from 45 °C to 50 °C for both lipase production and vegetative growth by the three strains of T. lanuginosus under study. In conclusion, the GSLMBKU-13 strain was comparatively superior in the production of lipase than the other two strains under investigation.

Cutaneous exposure to clinically-relevant pigeon pea (Cajanus cajan) proteins promote T(H)2-dependent sensitization and IgE-mediated anaphylaxis in Balb/c mice - Gupta, Rinkesh Kumar; Kumar, Sandeep; Gupta, Kriti; Sharma, Akanksha; Roy, Ruchi; Verma, Alok Kumar; Chaudhari, Bhushan P.; Das, Mukul; Ansari, Irfan Ahmad; Dwivedi, Premendra D. (Journal of Immunotoxicology, 2016)
Epicutaneous (EC) sensitization to food allergens may occur when the skin has been lightly damaged. The study here tested whether cutaneous exposure to pigeon pea protein(s) may cause allergic sensitization. BALB/c mice were either orally gavaged or epicutaneously sensitized by repeated application of pigeon pea crude protein extract (CPE) on undamaged areas of skin without any adjuvant; afterwards, both groups were orally challenged with the pigeon pea CPE. Anaphylactic symptoms along with measures of body temperature, MCPT-1, TSLP, pigeon pea-specific IgE and IgG(1), myeloperoxidase (MPO) activity, T(H)2 cytokines, T(H)2 transcription factors (TFs) and filaggrin expression were determined. Mast cell staining, eosinophil levels and histopathological analysis of the skin and intestines were also performed. In the epicutaneously-sensitized mice, elevated levels of specific IgE and IgG(1), as well as of MCPT-1, TSLP, T(H)2 cytokines and TFs, higher anaphylactic scores and histological changes in the skin and intestine were indicative of sensitization ability via both routes in the pigeon pea CPE-treated hosts. Elevated levels of mast cells were observed in both the skin and intestine; increased levels of eosinophils and MPO activity were noted only in the skin. Decreased levels of filaggrin in skin may have played a key role in the skin barrier dysfunction, increasing the chances of sensitization. Therefore, the experimental data support the hypothesis that in addition to oral exposure, skin exposure to food allergens can promote T(H)2-dependent sensitization, IgE-mediated anaphylaxis and intestinal changes after oral challenge. Based on this, an avoidance of cutaneous exposures to allergens might prevent development of food anaphylaxis.

Cysteine-specific fluorescent switch for monitoring oxidative stress and quantification of aminoacylase-1 in blood serum - Anila, H. A.; Ali, Firoj; Kushwaha, Shilpi; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Analytical Chemistry, 2016)

Calculation of the magnetic hyperfine structure constant of alkali metals and alkaline-earth-metal ions using the relativistic coupled-cluster method - Sasmal, Sudip (Physical Review A, 2017)
The Z-vector method in the relativistic coupled-cluster framework is used to calculate the magnetic hyperfine structure constant (A(J)) of alkali metals and singly charged alkaline earth metals in their ground state electronic configuration. The Z-vector results are in very good agreement with the experiment. The A(J) values of Li, Na, K, Rb, Cs, Be+, Mg+, Ca+, and Sr+ obtained in the Z-vector method are compared with the extended coupled-cluster results taken from Phys. Rev. A 91, 022512 (2015). The same basis and cutoff are used for the comparison purpose. The comparison shows that the Z-vector method with the single and double approximation can produce a more precise wave function in the nuclear region than the ECC method.

Calixarene based nanocomposite materials for high performance supercapacitor electrode - Waghmode, Babasaheb J.; Soni, Roby; Patil, Kashinath Rangu; Malkhede, Dipalee D. (New Journal of Chemistry, 2017)
A functionalised calixarene {4-Sulphatocalix [6] arene Hydrate (SC6)} stabilises MoS2/partially reduced graphene oxide (rGO) nanosheet. Such stabilised SC6-rGO/SC6-MoS2 and SC6 doped polyaniline (PANI) together forms a nanocomposite hybrid material for supercapacitor electrode. It was fabricated by an in situ polymerization method. Transmission electron microscopy (TEM) results suggest that PANI nanostructures grow homogeneously onto the surfaces of SC6 functionalised MoS2. Calixarene acts as a dopant for PANI as well as a stabiliser for the 2D nanosheets of rGO/MoS2. The characterisation of composites together with basic components was done by using various techniques namely, solid-state FT-IRspectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The electrochemical performance was analysed by cyclic voltammetry (CV), galvanostatic charge/discharge and electrochemical impedance spectrometry (EIS). It was found that the SC6 functionalised MoS2 and SC6 doped PANI formed a uniform nanocomposite. The synthesised composites show high specific capacitance (691 F/g) and good cycling stability during the charge-discharge process when used as supercapacitor electrodes. The improvement in electrochemical performance of composites is assigned to synergistic effect of SC6 stabilised MoS2 and doped PANI. Our investigation highlighted the importance of use of calixarene in composites for above stated supercapacitor performance. The role of calixarene in the present study opens a way for the application of alike materials in the composite supercapacitors for energy storage applications.

Camptothecin-producing endophytic bacteria from pyrenacantha volubilis hook. (Icacinaceae): a possible role of a plasmid in the production of camptothecin - Soujanya, K. N.; Siva, R.; Kumara, P. Mohana; Srimany, Amitava; Ravikanth, G.; Mulani, F. A.; Aarthy, T.; Thulasiram, H. V.; Santhoshkumar, T. R.; Nataraja, Karaba N.; Shaanker, R. Uma (Phytomedicine, 2017)
Background: Camptothecin (CPT), a quinoline alkaloid, is a potent inhibitor of eukaryotic topoisomerase I. Because of this property, several derivatives of CPT are used as chemotherapeutic agents. CPT is produced by several plant species belonging to the Asterid clade as well as by a number of endophytic fungal associates of these plants. In this study, we report the production of CPT by four bacterial endophytes and show the possible role of a plasmid in the biosynthesis of CPT. Methods: Endophytic bacteria were isolated from leaves, stems and fruits of Pyrenacantha volubilis Hook. (Icacinanceae). The bacterial isolates were purified and analyzed for production of CPT by ESI-MS/MS and NMR analysis. Bacterial identity was established based on the morphology and 16s rRNA sequence analysis. Crude extracts of the bacterial endophytes were evaluated for their cytotoxicity using colon cancer cell lines. The role of plasmid in the production of CPT was studied by purging the plasmid, using acriflavine, as well as reconstituting the bacteria with the plasmid. Results: Four bacterial isolates, Bacillus sp. (KP125955 and KP125956), Bacillus subtilis (KY741853) and Bacillus amyloliquefaciens (KY741854) were found to produce CPT in culture. Both based on ESI-MS/MS and NMR analysis, the identity of CPT was found to be similar to that produced by the host plant. The CPT was biologically active as evident by its cytotoxicity against colon cancer cell line. The production of CPT by the endophyte (Bacillus subtilis, KY741853) attenuated with sub-culture. A likely role of a plasmid in the production of CPT was established. A 5 kbp plasmid was recovered from the bacteria. Bacterial isolate cured of plasmid failed to produce CPT. Conclusion: Our study implies a possible role of a plasmid in the production of CPT by the endophytic bacteria and opens up further work to unravel the exact mechanisms that might be involved.

Can fungi compete with marine sources for chitosan production? - Ghormade, V. (International Journal of Biological Macromolecules, 2017)
Chitosan, a β-1,4-linked glucosamine polymer is formed by deacetylation of chitin. It has a wide range of applications from agriculture to human health care products. Chitosan is commercially produced from shellfish, shrimp waste, crab and lobster processing using strong alkalis at high temperatures for long time periods. The production of chitin and chitosan from fungal sources has gained increased attention in recent years due to potential advantages in terms of homogenous polymer length, high degree of deacetylation and solubility over the current marine source. Zygomycetous fungi such as Absidia coerulea, Benjaminiella poitrasii, Cunninghamella elegans, Gongrenella butleri, Mucor rouxii, Mucor racemosus and Rhizopus oryzae have been studied extensively. Isolation of chitosan are reported from few edible basidiomycetous fungi like Agaricus bisporus, Lentinula edodes and Pleurotus sajor-caju. Other organisms from mycotech industries explored for chitosan production are Aspergillus niger, Penicillium chrysogenum, Saccharomyces cerevisiae and other wine yeasts. Number of aspects such as value addition to the existing applications of fungi, utilization of waste from agriculture sector, and issues and challenges for the production of fungal chitosan to compete with existing sources, metabolic engineering and novel applications have been discussed to adjudge the potential of fungal sources for commercial chitosan production.
Keywords: Cell wall; Chitin/chitosan; Waste Mycelial Biomass; Zygomycetous Fungi

Capillary uptake in macroporous compressible sponges - Chatterjee, Soumyajyoti; Doshi, Pankaj; Kumaraswamy, Guruswamy (Soft Matter, 2017)
The capillarity-driven uptake of liquid in swellable, highly porous sponges is of significant industrial importance. Sponges prepared using polymers and their composites with carbon nanotubes and graphene have been reported, with extraordinary solvent uptake capacities and with the ability to separate oil from water. However, the effect of systematic variation of sponge characteristics on solvent uptake has not been investigated. Here, we report experiments that study capillary uptake in a variety of flexible, centimetre-sized macroporous cylindrical sponges. We used ice-templating to prepare a series of model macroporous sponges in which the porosity, modulus and composition were systematically varied. We investigated two kinds of sponge: (a) those composed purely of cross-linked polymers and (b) those prepared as composites of inorganic particles and polymers. Both kinds of sponge are flexible and exhibit elastic recovery after large compressive deformation. All sponges were characterized thoroughly with respect to their pore microstructure and elastic modulus. When one end of a sponge is plunged into a large reservoir, water rises through capillary action against gravity. We observed a transition from an inertial capillary regime, where the liquid column height rose linearly with time, t, to a viscous capillary regime, where the liquid height rose with time t(0.5). We showed that these results can be rationalized using analyses developed for rigid sponges. We combined differential momentum balance equations for uptake in rigid capillaries with the phenomenological Ergun-Forchheimer relations to account for the effect of the sponge microstructure. This approach works remarkably well in the viscous capillary regime and shows that capillary uptake is governed primarily by the total porosity and pore dimensions of soft sponges.
Keywords: aerogels; Building blocks; Catalyst Supports; Contact-angels; Dynamics; flow; Organic Liquids; Porous-Media; Rise

Carbene or C1 polymerization - De Bruin, B.; Chikkali, S.H. (Metal-catalyzed polymerization: fundamentals to applications, 2017)
As noted in Chapter 2, metal-catalyzed polymerization of carbon-carbon double bond (C=C) containing monomers is most widely known and today we produce roughly 180 million tons of polyolefins every year. 1 In this so-called olefin polymerization or vinyl insertion polymerization method, each monomer delivers two carbon (C2) atoms in each propagation step. Insertion polymerization of monomers delivering only one carbon unit in each chain growth step is named as C1 or carbene polymerization (see Figure 3.1). 2 In the recent past, C1 polymerization techniques are being viewed as a valuable alternative to the classical C2 polymerization methods. Not only this but also C1 polymerization offer distinct advantages over C2 polymerization and thus opens up new avenues for the development of new material with polymer properties that are very difficult to achieve using traditional C2 polymerization methods. In this chapter we will discuss the significance of C1 polymerization and the different methods used for C1 polymerization, will summarize the recent developments, and will highlight the elementary steps involved in it.

Carbonylation of glycerol with urea to glycerol carbonate over supported Zn catalysts - Kondawar, S. E.; Mane, R. B.; Vasishta, A.; More, S. B.; Dhengale, S. D.; Rode, C. V. (Applied Petrochemical Research, 2017)
Glycerol carbonylation with urea is a very feasible option to produce glycerol carbonate with a net result of CO2 fixation through urea synthesis. The prerequisite of an efficient catalyst for this reaction is to possess both acid and basic sites together. Several acidic supports were screened for ZnO catalyst in this work and Zn/MCM-41 was found to exhibit the best activity and almost complete selectivity to glycerol carbonate (GC). Although, non-catalytic glycerol carbonylation resulted in GC formation but glycerol conversion achieved was twice with Zn/MCM-41 as a catalyst. Further to that increase in Zn loading from 2 to 5% resulted in increase in glycerol conversion from 63 to 82%. The prepared catalysts were characterized by XRD, NH3 and CO2-TPD and effects of reaction parameters such as catalyst loading, glycerol to urea mole ratio and temperature on glycerol conversion and GC selectivity in batch mode of operation were also studied. Time on stream activity of 5% Zn/MCM-41 catalyst for continuous carbonylation of glycerol was also studied for ~100 h with an average conversion of ~55% and complete selectivity to GC. This indicated five times lower productivity of GC per h due to lower residence time than that in a batch operation as compared to that of a continuous operation. Activation energy estimated from the Arrhenius plot was found to be 39.82 kJ mol−1 suggesting that the reaction is kinetically controlled. A reaction pathway mediated by acid and basic sites of the Zn/MCM-41 catalyst is also proposed.
Keywords: Acid–base ratio; Continuous process; Glycerol carbonate; Glycerol-urea carbonylation; reaction pathway; Supported Zn; Zn loading

Carboxymethyl cellulose-grafted mesoporous silica hybrid nanogels for enhanced cellular uptake and release of curcumin - Tiwari, Neha; Nawale, Laxman U.; Sarkar, Dhiman; Badiger, Manohar V. (Gels, 2017)
Mesoporous silica nanoparticles (MSNs) with ordered pore structure have beensynthesized and used as carriers for the anticancer drug curcumin. MSNs were functionalizedwith amine groups and further attached with carboxymethyl cellulose (CMC) using 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC) coupling chemistry, which increased the hydrophilicityand biocompatibility of MSNs. The functionalized MSNs (MSN-NH2and MSN-CMC) werecharacterized using Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM),Dynamic Light Scattering (DLS), N2adsorption, X-Ray Diffraction (XRD), Thermo GravimetricAnalysis (TGA) and Fourier Transform Infrared Spectroscopy (FT-IR). Thein vitrorelease of curcuminfrom the –NH2and CMC functionalized MSNs (MSN-cur-NH2and MSN-cur-CMC) was performedin 0.5% aqueous solution of sodium lauryl sulphate (SLS). The effect of CMC functionalization ofMSNs towards cellular uptake was studied in the human breast cancer cell line MDA-MB-231 andwas compared with that of MSN-NH2and free curcumin (cur). Both MSN-NH2and MSN-CMCshowed good biocompatibility with the breast cancer cell line. The MTT assay study revealedthat curcumin-loaded MSN-cur-CMC showed better uptake as compared to curcumin-loadedMSN-cur-NH2. Free curcumin was used as a control and was shown to have much less internalizationas compared to the curcumin-loaded functionalized MSNs due to poor bioavailability. Fluorescencemicroscopy was used to localize the ﬂuorescent drug curcumin inside the cells. The workdemonstrates that CMC-functionalized MSNs can be used as potential carriers for loading and releaseof hydrophobic drugs that otherwise cannot be used effectively in their free form for cancer therapy.

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2017)
Light harvesting donor-acceptor assemblies are indispensable to efficiently tap photons. In an attempt to improve the light harvesting efficiency of an acceptor doped assembly, we design and synthesize a donor-acceptor-donor triad which exhibits an exceptional intramolecular energy transfer with excellent efficiency. Moreover, a facile cascade energy transfer (energy funnelling) is observed in the presence of a series of second acceptors (63-91% efficiency) with tunable emission colours. Self-assembled nanosheets formed by the triad in the presence of acceptors exhibit cascade energy transfer assisted tunable emission. In addition, use of chiral acceptors induces chirality to the triad and results in the formation of chiral nanosheets alongwith cascade energy transfer. Here chiral induction, nanosheet formation and cascade energy transfer in the presence of chiral acceptors are used as tools to probe the intercalation of acceptor molecules in the donor scaffold.

Cascade reductive etherification of bioderived aldehydes over Zr-based catalysts - Shinde, Suhas; Rode, Chandrashekhar (ChemSusChem, 2017)
An efficient one-pot catalytic cascade sequence has been developed for the production of value-added ethers from bioderived aldehydes. Etherification of 5-(hydroxymethyl)furfural with different aliphatic alcohols over acidic Zr-montmorillonite (Zr-Mont) catalyst produced a mixture of 5-(alkoxymethyl)furfural and 2-(dialkoxymethyl)-5-(alkoxymethyl)furan. The latter was selectively converted back into 5-(alkoxymethyl)furfural by treating it with water over the same catalyst. The synthesis of 2,5-bis(alkoxymethyl)furan was achieved through a cascade sequence involving etherification, transfer hydrogenation, and re-etherification over a combination of acidic Zr-Mont and the charge-transfer hydrogenation catalyst [ZrO(OH)(2)]. This catalyst combination was further explored for the cascade conversion of 2-furfuraldehyde into 2-(alkoxymethyl)furan. The scope of this strategy was then extended for the reductive etherification of lignin-derived arylaldehydes to obtain the respective benzyl ethers in >80% yield. Additionally, the mixture of Zr-Mont and ZrO(OH)(2) does not undergo mutual destruction, which was proved by recycling experiments and XRD analysis. Both the catalysts were thoroughly characterized using BET, temperature-programmed desorption of NH3 and CO2, pyridine-FTIR, XRD, inductively coupled plasma optical emission spectroscopy, and X-ray photoelectron spectroscopy techniques.

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2017)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone(A (R))-KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone-KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine-Oxone as an unprecedented catalyst-oxidant combination. [GRAPHICS] .
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

Catalytic branching cascades in diversity oriented synthesis - Bansode, Avinash H.; Chimala, Prathyusha; Patil, Nitin T. (ChemCatChem, 2017)
Diversity oriented synthesis (DOS) aims to generate small molecules with great structural diversity in an efficient manner. Recent years have witnessed significant achievements in the field, which help to validate the usefulness of DOS as a tool for the discovery of novel, biologically interesting small molecules. Catalytic branching cascades have emerged as a promising strategy because of their potential to transform a common type of substrate into diverse and distinct molecular frameworks. The details of the concept are presented herein.

Catalytic conversion of biomass - Dhepe, Paresh; Tomishige, Keiichi; Wu, Kevin C. -W. (Chemcatchem, 2017)

Catalytic enantioselective aza-piancatelli rearrangement - Gade, Amol B.; Patil, Nitin T. (Synlett, 2017)
The design and development of an enantioselective aza-Piancatelli rearrangement reaction are described. In the presence of a chiral phosphoric acid catalyst, furylcarbinols react with anilines to afford highly functionalized cyclopentenones with excellent diastereo-and enantioselectivities. The process was shown to be scalable, and up to 1 gram of starting material could be employed under mild reaction conditions.

Catalytic macroporous biohydrogels made of ferritin-encapsulated gold nanoparticles - Kumari, Sushma; Haring, Marleen; Sen Gupta, Sayam; Diaz, David Diaz (Chempluschem, 2017)
Reported is a modular approach for the incorporation and stabilization of gold nanoparticles inside a three-dimensional macroporous hydrogel made of ferritin. The strategy, which involves the dynamic templating of surfactant H-1 domains, demineralization, and remineralization helps to overcome aggregation and degradation issues usually associated with bare-metal-based nanocatalysts. The catalytic activity of the so-synthesized bionanocomposite hydrogel was demonstrated in both nitroaldol (Henry) and nitroreduction model reactions in aqueous solution at room temperature. An interesting synergistic effect between basic residues of the protein and the gold nanoparticles was found in the nitroaldol reaction when carried out in water in the presence of a phase-transfer catalyst. Furthermore, the reduction of 4-nitrophenol and 4-nitroaniline catalyzed by the nanocomposite scaffold in the presence of NaBH4 proceeded significantly faster than that using other known Au- and Ag-based catalysts under similar conditions.

Catalytic ozonation of clofibric acid over copper-based catalysts: in situ ATR-IR studies - Sable, Shailesh S.; Ghute, P. P.; Fakhrnasova, D.; Mane, R. B.; Rode, Chandrashekhar V.; Medina, F.; Contreras, S. (Applied Catalysis B-Environmental, 2017)
The current study describes the catalytic ozonation of clofibric acid (CFA) under ambient conditions using copper oxide catalysts synthesized by different methods. The objective of this study is to provide novel catalysts and reaction mechanism for the degradation of emerging pharmaceutical compounds in aqueous solution. Among the various Cu catalysts screened in this study, the Cut-Ali oxide catalyst showed an excellent activity and stability in the degradation and mineralization of CFA. In situ attenuated total reflection IR (ATR-IR) spectroscopy was used to examine the interaction of ozone with the active sites of the catalyst in presence of water and to investigate the possible catalytic mechanism. The presence of Lewis acid sites in the Cut-Ali catalyst increased the amount of chemisorbed water enhancing stronger interaction of ozone to form surface activated species, resulting in higher catalytic activity. The results obtained from in-situ ATR-IR study indicate that surface hydroxyl groups and Lewis acid sites are responsible for promoting the generation of hydroxyl radicals (OHS) from aqueous ozone. (C) 2017 Elsevier B.V. All rights reserved.

Cell culture processes for biopharmaceutical manufacturing - Gadgil, Mugdha (Current Science, 2017)
Recombinant proteins manufactured using animal cell culture processes comprise a significant fraction of biopharmaceuticals. With the expiry of patents on this class of therapeutics, there is also a significant interest in manufacture of biosimilar versions of such therapeutics. This article provides a birds-eye view of upstream process development for animal cell culture processes, with a focus on advances pertinent to the development of processes for biosimilars.
Keywords: Biopharmaceutical; Cell line development; CHO; glycosylation; monoclonal antibody

Cerium-based metal-organic framework having inherent oxidase-like activity applicable for colorimetric sensing of biothiols and aerobic oxidation of thiols - Dalapati, Rana; Sakthivel, Balasubramanian; Ghosalya, Manoj K.; Dhakshinamoorthy, Amarajothi; Biswas, Shyam (Crystengcomm, 2017)
A cerium-basedmetal-organic framework (MOF; 1) with a UiO-66 (UiO: University of Oslo) framework topology was synthesized solvothermally by employing 3,4-dimethylthieno[2,3-b] thiophene-2,5-dicarboxylic acid as a ligand. The MOF was thoroughly characterized by X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction, infrared spectroscopy, and thermogravimetric and N-2 sorption analyses. The activated material (1') retained its structural integrity in water, acetic acid and 1 M HCl solution. XPS investigation reveals the presence of both Ce(III) and Ce(IV) ions in 1. Owing to the presence of mixed-valence cerium ions, 1' was able to oxidize the chromogenic peroxidase substrate 3,3', 5,5'-tetramethylbenzidine (TMB) or 2,2'azinobis.3- ethylbenzothizoline-6-sulfonic acid) (AzBTS) in the absence of an external oxidizing agent. Thus, it showed inherent oxidase-like catalytic properties. Inspired by the excellent oxidase-mimicking activity of 1', a protocol was developed for the rapid colorimetric sensing of biothiols in NaAc buffer (0.2 M, pH = 4). The sensing ability of 1' towards cysteine was also demonstrated in human blood plasma. Furthermore, the redox-active cerium ions enabled 1' to exhibit excellent heterogeneous catalytic performance in aerobic oxidation catalysis of thiol compounds. The material is reusable (both as a sensor and as a catalyst), lowcost and highly stable, which renders it a promising candidate for the monitoring of biothiols in immunoassays and medical diagnosis as well as for industrial oxidation catalysis.

CH3NH3PbI3 based solar cell: modified by antisolvent treatment - Nandi, P.; Giri, C.; Bansode, U.; Topwal, D. (AIP Conference Proceedings, 2017)
Solar cells based on new class of organic inorganic hybrid perovskite CH3NH3PbI3 were prepared by Ethyl acetate (EA); antisolvent treatment for the first time. This treatment results in new morphology for CH3NH3PbI3 thin film. FESEM image shows microrod type structures of CH3NH3PbI3 after EA antisolvent treatment. Energy band diagram was constructed using photoluminescence and photoemission studies. A better power conversion efficiency was achieved in EA treated film compare to without EA treated film.
Keywords: CH3NH3PbI3; Perovskite solar cell

Chapter 5: Experimental and computational approaches to study membranes and lipid-protein interactions - Sengupta, Durba; Kumar, G. Aditya; Prasanna, Xavier; Chattopadhyay, A. (Computational biophysics of membrane proteins, 2017)
Biological membranes are complex two-dimensional, non-covalent assemblies of a diverse variety of lipids and proteins. A hallmark of membrane organization is varying degrees of spatiotemporal heterogeneity spanning a wide range. Membrane proteins are implicated in a wide variety of cellular functions, and comprise ∼30% of the human proteome and ∼50% of the current drug targets. Their interactions with membrane lipids are recognized as crucial elements in their function. In this article, we provide an overview of experimental and theoretical approaches to analyze membrane organization, dynamics, and lipid-protein interactions. In this context, we highlight the wide range of time scales that membrane events span, and approaches that are suitable for a given time scale. We discuss representative fluorescence-based approaches (FRET and FRAP) that help to address questions on lipid-protein and protein-cytoskeleton interactions in membranes. In a complimentary fashion, we discuss computational methods, atomistic and coarse-grain, that are required to address a given membrane problem at an appropriate scale. We believe that the synthesis of knowledge gained from experimental and computational approaches will enable us to probe membrane organization, dynamics, and interactions at increasing spatiotemporal resolution, thereby providing a robust model for the membrane in health and disease.

Characterizing clinically relevant natural variants of GPCRs using computational approaches - Sengupta, Durba; Sonar, Krushna; Joshi, Manali (Methods in cell biology, 2017)
G protein-coupled receptors (GPCRs) are an important class of drug targets owing to their physiological role. A large number of clinically relevant single nucleotide polymorphisms (SNPs) have been observed in GPCRs that are linked to disease susceptibility and adverse drug response. It is therefore important to characterize the variants in order to improve GPCR therapeutics. Here, we discuss computational methods coupling molecular dynamics simulations with docking and free energy calculations to characterize the functional differences in GPCR variants. The hallmark of this approach is the explicit incorporation of receptor and membrane dynamics that allows us to analyze short- and long-range effects in the variant receptors. We use the SNPs reported in β2-adrenergic receptor (β2AR) as a test case and highlight the recent successes in analyzing structural and dynamic differences in a series of population variants. The computational approach we discuss here has a twofold benefit: it helps to unravel the molecular mechanisms underlying hypo- or hyperfunctionality of variant receptors as well as prioritizing novel variants that must be experimentally tested.

Chemistry that impacts us (and the scientists behind them) - Kumaraswamy, G. (Resonance, 2017)

Chickpea-fusarium oxysporum interaction transcriptome reveals differential modulation of plant defense strategies - Upasani, Medha L.; Limaye, Bhakti M.; Gurjar, Gayatri S.; Kasibhatla, Sunitha M.; Joshi, Rajendra R.; Kadoo, Narendra Y.; Gupta, Vidya S. (Scientific Reports, 2017)
Fusarium wilt is one of the major biotic stresses reducing chickpea productivity. The use of wilt-resistant cultivars is the most appropriate means to combat the disease and secure productivity. As a step towards understanding the molecular basis of wilt resistance in chickpea, we investigated the transcriptomes of wilt-susceptible and wilt-resistant cultivars under both Fusarium oxysporum f.sp. ciceri (Foc) challenged and unchallenged conditions. Transcriptome profiling using LongSAGE provided a valuable insight into the molecular interactions between chickpea and Foc, which revealed several known as well as novel genes with differential or unique expression patterns in chickpea contributing to lignification, hormonal homeostasis, plant defense signaling, ROS homeostasis, R-gene mediated defense, etc. Similarly, several Foc genes characteristically required for survival and growth of the pathogen were expressed only in the susceptible cultivar with null expression of most of these genes in the resistant cultivar. This study provides a rich resource for functional characterization of the genes involved in resistance mechanism and their use in breeding for sustainable wilt-resistance. Additionally, it provides pathogen targets facilitating the development of novel control strategies.

Chiral discrimination through h-1 nmr and luminescence spectroscopy: dynamic processes and solid strip for chiral recognition - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Rajamohanan, P. R.; Ravindranathan, Sapna; Das, Amitava (Chemistry-A European Journal, 2017)
The appropriate choice of the host molecules with well-defined optical activity (S-H/R-H) helps in the differentiation between two secondary ammonium ion-derivative guest molecules with different optical activities (R-G/S-G) based on the fluorescence resonance energy transfer (FRET)based luminescence responses. Crown ether-based host molecules with opposite chiral configurations (R-H, S-H) have been derived from 1,1'-bi-2-naphthol (BINOL) derivatives that have axially chiral biaryl centers. These chiral crown ethers form host-guest complexes (i.e., [2] pseudoro-taxanes) with chiral secondary ammonium ion derivatives (R-G, S-G). NMR spectroscopic studies show that the complexes are in a dynamic equilibrium in solution. Results of the H-1 NMR and fluorescence spectroscopic studies indicate a head-on orientation of the host and guest in the [2] pseudorotaxanes. The difference in the efficiency in the FRET-based responses between anthracene and the BINOL derivatives allow efficient chiral discrimination of the guests. Isothermal titration calorimetry and NMR investigations reveal that inclusion complexes between hosts and guests of the same chirality (R-H center dot R-G, S-H center dot S-G) are more stable relative to those of opposite chirality (R-H center dot S-G, S-H center dot R-G). However, FRET-based energy-transfer efficiency is higher for R-H center dot S-G and S-H center dot R-G complexes. NMR spectroscopic studies show that the relative orientation of the guest in the host cavity is significantly different when the host binds a guest of the same or opposite chirality; furthermore, the latter is more favorable for FRET, thus enabling discrimination between enantiomers. Interestingly, chiral discrimination of guest ions could also be achieved by using silica surfaces modified with chiral host molecules.

Chitosan intercalated metal organic gel as a green precursor of fe entrenched and fe distributed N-doped mesoporous graphitic carbon for oxygen reduction reaction - Shijina, Kottarathil; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Yamaguchi, Takeo; Anilkumar, Gopinathan M.; Hareesh, U. S.; Sailaja, G. S. (Chemistryselect, 2017)
Herein, we present Metal-Organic Gel intercalated with chitosan, a `green'' precursor for the synthesis of intrinsic N-doped Fe entrenched (CHI-TMA-Fe-CW) and Fe distributed mesoporous graphitic carbon structures (CHI-TMA-Fe-CW-M1) with appreciable Oxygen Reduction Reaction (ORR) activity in alkaline medium. Modulation of the synthetic protocol as a function of reaction kinetics and gelation time while maintaining identical pyrolysis conditions (900 degrees C, flowing N-2 atmosphere) improves the microstructure, surface area and Fe distribution of the graphitic structures (CHI-TMA-Fe-CW-M1). CHI-TMA-Fe-CW has a Fe entrenched graphitic nanocapsule like morphology while Fe distributed mesoporous graphitic carbon sheets, with a specific surface area value of 565 m(2) g(-1) obtained by modulating the synthesis chemistry in CHI-TMA-Fe-CW-M1. The higher percentage of graphitic N in CHI-TMA-Fe-CW-M1 apparent from the XPS data validate that the modified synthetic method favours creation of more graphitic N sites contributing for better catalytic performance. CHI-TMA-Fe-CW-M1 catalyst exhibited comparable electrocatalytic activity with that of the commercially available Pt/C via an efficient four-electron-dominant ORR pathway with a positive onset potential value of 0.925 V vs RHE. Good durability of CHI-TMA-Fe-CW-M1 after 5000 cycles further confirm the prospects of MOG-chitosan and the feasibility to be used as a potential catalyst for ORR.
Keywords: electrocatalyst; fuel cell; Metal-Organic-Gel; oxygen reduction reaction

CHO Cells Adapted to Inorganic Phosphate Limitation Show Higher Growth and Higher Pyruvate Carboxylase Flux in Phosphate Replete Conditions - Maralingannavar, Vishwanathgouda;; Parmar, Dharmeshkumar; Pant, Tejal; Gadgil, Chetan; Panchagnula, Venkateswarlu; Gadgil, Mugdha (Biotechnology progress, 2017)
Inorganic phosphate (P-i) is an essential ion involved in diverse cellular processes including metabolism. Changes in cellular metabolism upon long term adaptation to P-i limitation have been reported in E. coli. Given the essential role of P-i, adaptation to P-i limitation may also result in metabolic changes in animal cells. In this study, we have adapted CHO cells producing recombinant IgG to limiting P-i conditions for 75 days. Not surprisingly, adapted cells showed better survival under P-i limitation. Here, we report the finding that such cells also showed better growth characteristics compared to control in batch culture replete with P-i ( higher peak density and integral viable cell density), accompanied by a lower specific oxygen uptake rate and cytochrome oxidase activity towards the end of exponential phase. Surprisingly, the adapted cells grew to a lower peak density under glucose limitation. This suggests long term P-i limitation may lead to selection for an altered metabolism with higher dependence on glucose availability for biomass assimilation compared to control. Steady state U-C-13 glucose labeling experiments suggest that adapted cells have a higher pyruvate carboxylase flux. Consistent with this observation, supplementation with aspartate abolished the peak density difference whereas supplementation with serine did not abolish the difference. This supports the hypothesis that cell growth in the adapted culture might be higher due to a higher pyruvate carboxylase flux. Decreased fitness under carbon limitation and mutations in the sucABCD operon has been previously reported in E. coli upon long term adaptation to P-i limitation, suggestive of a similarity in cellular response among such diverse species. (C) 2017 American Institute of Chemical Engineers

Cisplatin-induced self-assembly of graphene oxide sheets into spherical nanoparticles for damaging sub-cellular DNA - Nandi, Aditi; Mallick, Abhik; More, Piyush; Sengupta, Poulomi; Ballav, Nirmalya; Basu, Sudipta (Chemical Communications, 2017)
This report describes the hitherto unobserved cisplatin induced self-assembly of 2D-graphene oxide sheets into 3D-spherical nano-scale particles. These nanoparticles can encompass dual DNA damaging drugs simultaneously. A combination of confocal microscopy, gel electrophoresis and flow cytometry studies clearly demonstrated that these novel nanoparticles can internalize into cancer cells by endocytosis, localize into lysosomes, and damage DNA, leading to apoptosis. Cell viability assays indicated that these nanoparticles were more cytotoxic towards cancer cells compared to healthy cells.

Clickable polyurethanes based on s- triazine ring containing aromatic diisocyanate bearing pendent alkyne group: synthesis and postmodification - Garg, Kavita; Chatterjee, Deepshikha; Wadgaonkar, Prakash (Journal of Polymer Science Part A Polymer Chemistry, 2017)
A new s-triazine ring containing aromatic diisocyanate bearing a pendent alkyne group, namely, 2,4-bis(4-isocyanatophenoxy)−6-(prop-2-yn-1-yloxy)−1,3,5-triazine was synthesized and reacted with various diols viz., 1,10-decanediol, tetraethylene glycol and polyethylene glycols in the presence of dibutyltin dilaurate as the catalyst to obtain a series of linear polyurethanes. The selected polyurethanes possessing pendent alkyne groups were postmodified with chemically diverse azides viz., 1-(azidomethyl)benzene, 1-(azidomethyl)pyrene, and methoxy end-caped poly(ethylene glycol) azide via copper-catalysed azide-alkyne Huisgen 1,3-dipolar cycloaddition. FTIR and 1H NMR spectra indicated quantitative click reaction. UV–vis and fluorescence spectroscopic analysis confirmed complete incorporation of pyrenyl groups indicating the formation of fluorescence active polyurethane by postmodification with 1-(azidomethyl)pyrene. TG analysis of polyurethanes indicated two stage weight loss and their thermal stability, as judged by T10 values, was governed by weight percent of urethane linkages. The water contact angle measurements revealed improved wettability with increased content of PEG either in the backbone of polyurethanes or as grafted chains. DLS and TEM studies confirmed that certain polyurethanes possessing PEG segments displayed self-assembly in aqueous solution, which was further supported by pyrene encapsulation studies using UV–vis spectroscopy. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2017, 55, 1008–1020
Keywords: Click chemistry; Diisocynate; Polyethelene Glycol; polyurethanes; Self- Assembly

Click-chemistry-based multicomponent condensation approach for design and synthesis of spirochromene-tethered 1,2,3-triazoles as potential antitubercular agents - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Nawale, Laxman; Bhansali, Sujit; Sarkar, Dhiman (Research on Chemical Intermediates, 2017)

Clues from crystal structures pave the way to access chiral myo-inositol derived versatile synthons: resolution of racemic 4-o-allyl-myo-inositol-1,3,5-orthoesters via corresponding dicamphanates by crystallization - Patil, Nivedita T.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Racemic 4-O-allyl-myo-inositol-1,3,5-orthoesters were resolved as the corresponding diastereomeric dicamphanates by crystallization from alcoholic solvents. Crystals of the two diastereomers of myo-inositol orthoacetate and one diastereomer each of myo-inositol orthoformate and myo-inositol orthobenzoate were obtained in >99% purity, on gram scale. The configuration of all these diastereomers was established by conversion to known chiral myo-inositol derivatives as well as by single crystal structure analysis. It is interesting to note that the procedures for the separation of diastereomeric myo-inositol orthoesters could be evolved due to the knowledge of crystal growth and crystal structures of inositol derivatives of comparable molecular structures. Due to the synthetic versatility of myo-inositol orthoesters, the methods described provide rapid and convenient access to a variety of chiral inositol derivatives with high synthetic potential.

Co-catalytic metal oxide nanoparticles decorated silicon/hematite core shell nanowire arrays as efficient photo electrodes for water splitting - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ChemistrySelect, 2017)
By looking global energy demands, development of highly efficient stable semiconductor photoelectrodes for photoelectrochemical (PEC) water splitting is highly desirable. Herein, we have fabricated co-catalytic nanoparticles decorated Silicon nanowire (SiNWs)/Hematite(Fe2O3) core sell structures as photo anodes and studied the PEC water oxidation properties. As, Fe2O3 possess weak oxidation kinetics, decoration of NiO and Co3O4 nanoparticles on SiNW/Fe2O3 by hydrothermal method, which acts as co-catalysts to improves the water oxidation reactions. It was found that decoration of Co3O4 nanoparticles enhances the photocurrent up to 2.6 times, whereas for NiO nanoparticles improvement is of 1.5 times when compared to the undecorated electrodes. Along with enhancement of photocurrents, it also shows shift of onset potentials. The effect of the co-catalytic nanoparticles on the enhancement of photocurrent and charge transfer resistance at the interface of electrode-electrolyte have been studied by electrochemical impedance spectroscopy. Further, flat band potentials of the photo electrodes have been measured by using Mott-schottky analysis.
Keywords: Co-catalysts; photo anodes; Photoelectrochemical cell; silicon nanowires; water splitting

Colloidal nanocomposite of TiN and N-doped few-layer graphene for plasmonics and electrocatalysis - Shanker, G. Shiva; Markad, Ganesh B.; Jagadeeswararao, Metikoti; Bansode, Umesh; Nag, Angshuman (ACS Energy Letters, 2017)
A combination of high carrier density, high surface area, solution processability, and low cost is desired in a material for electrocatalytic applications, including H-2 evolution and a counter electrode of a solar cell. Also, plasmonic-based applications in biological systems can be derived from such material. In this regard, a colloidal nanocomposite of TiN and N-doped few-layer graphene (TiN NFG) is synthesized from molecular precursors. TiN nano crystals (NCs) provide free electrons for electrical conductivity and plasmonics, whereas NFG is responsible for charge transport, high surface area, and colloidal stability. Colloidal TiN NFG nano composites exhibit a localized surface plasmon resonance band at around 700 nm. Coatings of the nanocomposite form a counter electrode for efficient (8.9%) dye-sensitized solar cells. Furthermore, the nanocomposite acts as an efficient electrocatalyst for hydrogen evolution reaction, exhibiting an overpotential similar to 161 mV at a current density of 10 mA/cm(2).

Colossal photo-conductive gain in low temperature processed TiO2 films and their application in quantum dot solar cells - Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K. (Applied Physics Letters, 2017)
Colloidal quantum dot (QD) solar cells have seen remarkable progress in recent past to reach the certified efficiency of 10.6%. Anatase titanium oxide (TiO2) is a widely studied n-type widow layer for the collection of photogenerated electrons in QD solar cells. Requirement of high temperature (similar to 500 degrees C) processing steps proved to be disadvantageous for its applications in flexible solar cells and roll to roll processing, and it also has adverse commercial implications. Here, we report that solar light exposure to low temperature processed (80 degrees C-150 degrees C) TiO2 and niobium doped TiO2 films leads to unprecedented enhancement in their electron densities and electron mobilities, which enables them to be used as efficient n-type layers in quantum dot solar cells. Such photoinduced high conducting states in these films show gradual decay over hours after the light bias is taken off and can be retrieved under solar illumination. On the contrary, TiO2 films processed at 500 degrees C show marginal photo induced enhancements in their characteristics. In bilayer configuration with PbS QDs, photovoltaic devices based on low temperature processed TiO2 films show improved performance over high temperature processed TiO2 films. The stability of photovoltaic devices also improved in low temperature processed TiO2 films under ambient working conditions. Published by AIP Publishing.

Comparable ionicity of the solutions of aprotic and protic ionic liquids by anion substitution - Jain, Preeti; Kumar, Anil (Journal of Solution Chemistry, 2017)
Temperature dependent molar conductances and fluidities of bisulfate and ethyl sulfate anion-based ionic liquids were measured. The extent of dissociation of the ionic liquids was estimated from the Walden plot in term of ionicity. The ionicity mainly depends on the magnitude of Coulombic forces, altered by the anion’s Lewis basicity. Aqueous solutions of aprotic ionic liquids, in general, possesses ionicity in the range of ≈70–99%. This article reveals that the substitution of the anion by bisulfate and ethylsulfate reduces the ionicity of aqueous solution of these ionic liquids to the range of 10–37%. This is very close to that exhibited by some of the protic ionic liquids and phosphonium based ionic liquids with sweetner anions. The concentration dependent molar conductance of these ionic liquids has been fitted to Mahiuddin and Ismail’s equation. To our surprise, the molar conductances of bisulfate-based aprotic ionic liquids are remarkably high, even though these ionic liquids possess lower ionicity.

Comparative analysis of extractive and pressure swing distillation for separation of THF-water separation - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Computers & Chemical Engineering, 2017)
In the present work, extractive and pressure-swing distillation methods are analyzed in detail through steady state ASPEN Plus simulations to propose the most economic method for separation of equimolar mixture of THF-Water. Various solvents were evaluated and DMSO was identified as the most appropriate solvent, as it gave minimum Total Annual Cost (TAC) for desired purity. In case of pressure swing distillation, various pressure ranges were explored to achieve minimum TAC. Configurations for extractive and pressure swing distillation with heat integration were also worked out. The optimum designs of extractive and pressure swing distillation with and without heat integration were compared on a common basis of feed conditions and purity constraints. Results indicate that TAC of extractive distillation with heat integration is 5.2% less than that of PSD with partial heat integration. (C) 2017 Elsevier Ltd. All rights reserved.

Compositional dependence of electrical conduction in solution grown Zn1-xCrxSe thin films: a correlation - Deshmukh, S. L.; Pingale, P. C.; Chavan, G. T.; Pawar, S. T.; Prakshale, V. M.; Kamble, S. S.; Jadkar, S. R.; Chaure, N. B.; Gopinath, C. S.; Maldar, N. N.; Deshmukh, L. P. (Journal of Materials Science: Materials in Electronics, 2017)
Zinc selenide (ZnSe) has a typical band gap of 2.7 eV suitable for window application and can easily be synthesized using a liquid phase chemical bath deposition. An attempt is made to tune its band gap and other characteristics to cope with a maxima of the solar spectrum by deliberate addition of Cr3+. ZnSe and Zn1-xCrxSe (0 <= x <= 0.35) thin films were obtained under the controlled deposition conditions (temperature = 70 A degrees C, time = 210 min, pH = 10, etc). The compositional analysis showed Zn2+ replacement by Cr3+. The X-ray photoelectron spectroscopy revealed chemical states of the constituents Zn, Cr and Se as 2(+), 3(+) and 2(-) respectively. The electrical conductivity and thermo-power measurements in the 300-550 K temperature range showed semiconducting nature of the material and that the electrical conduction is of the n-type. The electrical conductivity is found to be increased continuously up to x = 0.05 and then decreased for further increase in x. The Hall-probe measurements also confirmed n-type conduction. The average Hall coefficient for pure ZnSe is -1.03 x 10(7) cm(3)/C whereas, it is -4.55 x 10(6) cm(3)/C for a sample with x = 0.35.

Computational intelligence based models for prediction of elemental composition of solid biomass fuels from proximate analysis - Ghugare, S.B.; Tiwary, S.; Tambe, S.S. (International Journal of Systems Assurance Engineering and Management, 2017)
Biomass is a renewable and sustainable source of “green” energy. The elemental composition comprising carbon (C), hydrogen (H) and oxygen (O) as major components, is an important measure of the biomass fuel’s energy content. Its knowledge is also valuable in: (a) computing material balance in a biomass-based process, (b) designing and operating biomass utilizing efficient and clean combustors, gasifiers and boilers, (c) fixing the quantity of oxidants required for biomass combustion/gasification, and (d) determining the volume and composition of the combustion/gasification gases. Obtaining the elemental composition of a biomass fuel via ultimateanalysis is an expensive and time-consuming task. In comparison, proximate analysis that determines fixed carbon, ash, volatile matter and moisture content is a cruder characterization of the fuel and easier to perform. Thus, there exists a need for models possessing high accuracies for predicting the elemental composition of a solid biomass fuel from its proximate analysis constituents. Accordingly, this study utilizes three computational intelligence (CI) formalisms, namely, genetic programming, artificial neural networks and support vector regression, for developing nonlinear models for the prediction of C, H and O fractions of solid biomass fuels. A large database of 830 biomasses has been used in the stated model development. A comparison of the prediction accuracy and generalization performance of the nine CI-based models (three each for C, H and O) with that of the currently available linear models indicates that the CI-based models have consistently and significantly outperformed their linear counterparts. The models developed in this study have proved to be the best models for the prediction of elemental composition of solid biomass fuels from their proximate analyses.

Computational strategies to explore antimalarial thiazine alkaloid lead compounds based on an australian marine sponge plakortis lita - Lilly, Aswathy; Jisha, R. S.; Masand, Vijay H.; Gajbhiye, Jayant M.; Shibi, Indira G. (Journal of biomolecular Structure & Dynamics, 2017)
In this work, an attempt was made to propose new leads based on the natural scaffold Thiaplakortone-A active against malaria. The 2D QSAR studies suggested that three descriptors correlate with the anti-malarial activity with an R2 value of 0.814. Robustness, reliability and predictive power of the model were tested by internal validation, external validation, Y-scrambling and Applicability domain analysis. HQSAR studies were carried out as an additional tool to find the sub-structural fingerprints. The CoMFA and CoMSIA models gave Q2 values of 0.813 and 0.647, and R2ncv values of 0.994 and 0.984, respectively. Using the 2D-QSAR equation, the activity values of the seven modified compounds were calculated and it was found that three molecules showed good anti-malarial activity. Molecular docking of the 42 Thiaplakortone-A derivatives with P. falciparum calcium-dependent protein kinase 1 (PfCDPK1) was carried out to find out protein-ligand interactions. Data mining of the bioassay dataset AID: 504850 using the classifier based on Random Forest (RF) of Weka suggested that all of the eight molecules selected and three out of the seven virtual molecules were anti-malarial active. Both the virtual molecules and drug molecules were docked with CYP3A4, indicating that the virtual molecules could metabolize easily. Toxicity studies using Osiris shows that three molecules showed no toxic characters.

Computational survey of ligand properties on iron(III)-iron(II) redox potential: exploring natural attenuation of nitroaromatic compounds - Rizvi, Masood Ahmad; Mane, Manoj; Khuroo, Mohammad Akbar; Peerzada, Ghulam Mustafa (Monatshefte Fur Chemie, 2017)
This study is a computational investigation of the ligand effect on the redox potential of iron redox couple aimed at screening these systems for novel applications. The influence of common and naturally available organic compounds with diverse ligand characteristics (nature of donor site, chelation, pre-organization, degree of back acceptance) on the redox potential of iron(III)-iron(II) redox couple has been theoretically calculated using an appropriate level of density functional theory (DFT). The DFT calculated redox potentials of iron complexes are explored to supplement, corroborate, and predict the experimental behavior of the studied systems towards environmental reduction of nitroaromatic compounds to corresponding anilines. The comparative avidity of iron complexes with cysteine derivatives for the reduction of nitroaromatic compounds has been theoretically explored and based on structure-activity relationship; new iron complexes with a range of reactivity and enhanced ability towards nitroaromatic reduction have been predicted.
Keywords: Catechol derivatives; computational chemistry; Density functional theory; Iron complexes; Ligand effect on redox potential; Natural attenuation; Nitroaromatic compounds

Concise approach for central core of trigolutes: total synthesis of trigolute B and 3-epi-trigolute B and analogues - Reddy, B. Narendraprasad; Ramana, Chepuri V. (Tetrahedron, 2017)
A concise approach comprising a combination of the Pd- or Ir-catalyzed Tsuji-Trost allylation and olefin dihydrox-ylation/acid catalyzed lactonization has been developed to construct the central spirolactone core of trigolutes with the requisite functional groups. A large number of analogues of trigolute B have been synthesized. Furthermore, the synthesis of both (±)-trigolute B and (±)-3-epi-trigolute B has been accomplished in 4–5 steps from easily accessible building blocks.

Concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol using Co(III)(salen)-catalyzed hydrolytic kinetic resolution of a two-stereocentered anti-azido epoxide - Reddi, Rambabu N.; Prasad, Pragati K.; Kalshetti, Rupali G.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2017)
A concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol, (+)-DAB-1, has been described in good overall yield (18.1%) and with high enantiomeric purity (up to 98% ee) starting from a simple raw material, cis-2-butene-1,4-diol. The Co-catalyzed hydrolytic kinetic resolution of a two-stereocentered racemic azido epoxide followed by asymmetric dihydroxylation of the alkene and 'one pot' reductive cyclisation of the azido diol are key reactions in the synthetic sequence. (C) 2016 Elsevier Ltd. All rights reserved.

Concurrent synthesis of SnO/SnO2 nanocomposites and their enhanced photocatalytic activity - Roy, Animesh; Arbuj, Sudhir; Waghadkar, Yogesh; Shinde, Manish; Umarji, Govind; Rane, Sunit; Patil, Kashinath; Gosavi, Suresh; Chauhan, Ratna (Journal of Solid State Electrochemistry, 2017)
The SnO/SnO2 nanocomposites were synthesized using semisolvothermal reaction technique. These nanocomposites were prepared using different combination of solvents viz., ethanol, water, and ethylene glycol at 180 A degrees C for 24 h. The synthesized nanocomposites were analyzed with various characterization techniques. Structural analysis indicates the formation of tetragonal phase of SnO2 for the sample prepared in ethanol, whereas for other solvent combinations, the mixture of SnO and SnO2 having tetragonal crystal structures were observed. The optical study shows enhanced absorbance in the visible region for all the prepared SnO/SnO2 nanocomposites. The observed band gap was found to be in the range of 3.0 to 3.25 eV. Microstructural determinations confirm the formation of nanostructures having spherical as well as rod-like morphology. The size of nanoparticles in ethanol-mediated solvent was found to be in the range of 5 to 7 nm. Thermogravimetric analysis indicate the weight gain around 1.3 wt% confirming the conversion of SnO to SnO2 material. The photocatalytic activity of synthesized nanocomposites was evaluated by following the aqueous methylene blue (MB) degradation. The sample prepared in ethylene glycol-mediated solvent showed highest photoactivity having apparent rate constant (K-app) 0.62 x 10(-2) min(-1).
Keywords: Dye-degradation; Nanocomposite; Photocatalysis; tin oxide

Conformational and functional transitions and in silico analysis of a serine protease from conidiobolus brefeldianus (MTCC 5185) - Shukla, Ekta; Agrawal, Sanskruthi B.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2017)
This work describes functional and structural transitions of a novel protease isolated from Conidiobolus brefeldianus MTCC 5185 (Cprot), in detail using biophysical and bioinformatics tools. The commercial importance of Cprot in silk and leather industries made it an interesting candidate for structural investigations. Cprot possesses 8.2%alpha-helix, 31.1% beta-sheet and 23.8% turns. The enzyme was found to be active over a wide pH range and up to 55 degrees C. The protease was also stable in organic solvents up to 50% (v/v) concentration of alcohols and DMSO for >24 h and in 2 M guanidine hydrochloride for >12 h. Cprot was also resistant to trypsin, chymotrypsin, proteinase K and fluorinated alcohols (5-10%). The melting temperatures observed for the native Cprot and for the enzyme treated under various stress conditions correlated well with the corresponding structural and functional transitions obtained. The structural information was supported by the homology model of its closest homologue from C. coronatus; revealing its similarity to PA clan of proteases (Proteases of mixed nucleophile, superfamily A), with His-64, Asp-113 and Ser-208 as putative catalytic triad. Three tryptophan residues in Cprot are surrounded by positively charged residues, as evident from solute quenching studies and homology model. (C) 2017 Elsevier B.V. All rights reserved.

Conformational dynamics of intracellular tau protein revealed by cd and saxs - Gorantla, vijay nalini; Alexander, V. Shkumatov; Chinnathambi, Subashchandrabose (Methods in Molecular Biology, 2017)
A native conformation of a protein is essential for its biological role. In certain conditions, some proteins show non-native conformations, leading to aggregation, which in turn may produce severe pathologies. Such physiological conditions are classified as protein misfolding diseases. Alzheimer’s disease (AD) is the most common form of dementia. Extracellular senile plaques formed by Amyloid β and intracellular aggregates formed by microtubule-associated protein Tau (MAPT) are the hallmarks of AD. Physiological role of MAPT is to maintain the integrity and stability of microtubules, however it tends to self-aggregate forming intracellular paired helical filaments (PHFs) during AD. MAPT is also subjected to various post-translational modifications such as phosphorylation, glycosylation, truncation, and acetylation. Being natively unfolded, MAPT is prone to full characterization at atomic level. Small-angle X-ray scattering (SAXS) is often applied in combination with other biophysical methods, like nuclear magnetic resonance (NMR), circular dichroism (CD), fluorescence spectroscopy, analytical ultracentrifugation (AUC), or dynamic light scattering (DLS) to characterize natively unfolded systems. Here we describe the practical aspects of MAPT characterization by SAXS and CD in detail as well as outline the inferred structural and functional implications.

Constructing ultraporous covalent organic fameworks in seconds via an organic terracotta process - Karak, S.; Kandambeth, S.; Biswal, B. P.; Sasmal, H. S.; Kumar, S.; Pachfule, P.; Banerjee, R. (Journal of the American Chemical Society, 2017)
Research on covalent organic frameworks (COFs) has recently gathered significant momentum by the virtue of their predictive design, controllable porosity, and long-range ordering. However, the lack of solvent-free and easy-to-perform synthesis processes appears to be the bottleneck toward their greener fabrication, thereby limiting their possible potential applications. To alleviate such shortcomings, we demonstrate a simple route toward the rapid synthesis of highly crystalline and ultraporous COFs in seconds using a novel salt-mediated crystallization approach. A high degree of synthetic control in interlayer stacking and layer planarity renders an ordered network with a surface area as high as 3000 m(2) g-(1). Further, this approach has been extrapolated for the continuous synthesis of COFs by means of a twin screw extruder and in situ processes of COFs into different shapes mimicking the ancient terracotta process. Finally, the regular COF beads are shown to outperform the leading zeolites in water sorption performance, with notably facile regeneration ability and structural integrity.

Continuous flow telescopic oxidation of alcohols via generation of chlorine and hypochlorite - Sharma, Y.; Moolya, S.; Joshi, Ramesh A.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2017)
A 3-step continuous flow oxidation of alcohols is demonstrated with continuous generation of chlorine as the first step followed by its use for the flow synthesis of high strength sodium hypochlorite. The solution is subsequently used for oxidation of alcohols in the presence of a catalytic amount of the nitroxyl radical “TEMPO”, which inhibits oxidation at the aldehyde stage. Selective oxidations of eight different alcohols were demonstrated. To achieve identical yields, the aromatic alcohols containing electron withdrawing groups needed a longer residence time than aliphatic alcohols.

Control of polymerization reactors - Schurk, F. J; Deshpande, P. B; Leffew, K. W.; Nadkarni, V. M. (CRC Press, 2017)
This reference and text provides an in-depth description of developments in control techniques and their application to polymerization reactors and offers important introductory background information on polymerization reaction engineering.;Discussing modelling, identification, linear, nonlinear and multivariable schemes, Control of Polymerization Reactors: presents all available techniques that can be used to control reactors properly for optimal performance; shows how to manipulate pivotal variables that affect reactor control; examines methods for deriving dynamic process models to improve reactor efficiency; reviews reactor control problems and points out end-use properties; supplies methods for measuring process variables, and ways to estimate variables that can’t be measured; and explains how single-input, single-output (SISO) strategies can be effectively used for control.;Filled with illustrative examples to clarify concepts, including more than 730 figures, tables and equations, Control of Polymerization Reactors is intended for use as a reference for chemical, process development, process design, research and development, control systems, and polymer engineers; and polymer chemists and physicists; as well as a text for upper-level undergraduate and graduate students in polymerization reactor control courses.

Controlling necking in extrusion film casting using polymer nanocomposites - Rokade, Dhammaraj; Azad, Lal B.; Poddar, Suparna; Mishra, Satyendra; Pol, Harshawardhan V.; Shukla, Rishab (Journal of Macromolecular Science Part B-Physics, 2017)
The research described was concerned with the effect of layered-silicate-based organically modified nanoclay fillers on controlling the extent of necking in a polymer melt extrusion film casting (EFC) process. We show that a linear polythylene resin (such as a linear low-density polyethylene-LLDPE) filled with a very low percentage of well-dispersed (or intercalated) nanoclay displays an enhanced resistance to the necking phenomenon. In general, melt-compounded nanoclay-filled LLDPE resin formulations displayed a higher final film width (less necking), thus a lower final film thickness (greater draw down for the same draw ratio), and cooled down faster when compared to the base LLDPE resin. Incorporation of nanoclay filler in the mainly linear chain LLDPE resin led to significant modification of the melt rheological properties that, in turn, affected the melt processability of these formulations. Primarily, the intercalated nanoclay-filled LLDPE formulations displayed the presence of strain-hardening in unaxial extensional rheology. Additionally, the presence of well-dispersed nanoclay in the LLDPE resin led to a display of prominent extrudate swell indicating the presence of melt elasticity in such formulations. The presence of melt elasticity, as shown by shear rheology and strain-hardening, observed by uniaxial extensional rheology, contributed to the LLDPE nanoclay formulations displaying an enhanced resistance to necking for these films. It can be concluded that linear chain polymers susceptible to necking in an EFC process can be made more resistant to such necking by using nanoclay fillers at very low levels of loading.

Convenient new and efficient commercial synthetic route for dasatinib (sprycel®) - Suresh, Garbapu; Nadh, Ratnakaram Venkata; Srinivasu, Navuluri; Yennity, Durgaprasad (Synthetic Communications, 2017)
A new and efficient synthetic route for dual Src/Abl kinase inhibitor Dasatinib (Sprycel®), an anticancer drug, is described. This commercially viable process yields Dasatinib monohydrate free of potential impurities with consistent yield of 68% in route A and 61% in route B with HPLC purity >99.80% over 4 stages.

Convenient route for Au@Ti-SiO2 nanocatalyst synthesis and its application for room temperature CO oxidation - Soni, Yogita; Kumar, Anumol Erumpukuthical Ashok; Nayak, Chandrani; Deepak, Francis Leonard; Vinod, C. P. (Journal of Physical Chemistry C, 2017)
Small gold nanoparticles.of size less than 5 nm encapsulated inside titanium modified silica shell have been reported. Here, a modified sol-gel method, which is a one-step process, produces Au@Ti-SiO2 nanocatalyst with a good control of titanium loading. With a titanium loading of 0.9 and 2.2 wt % in silica, unprecedented low temperature activity (full conversion) is observed for this catalyst for CO oxidation reaction compared to Au@SiO2 catalyst. A combination of optimum sized gold nanoparticles with a large amount of oxygen vacancies created due to Ti incorporation in silica matrix is considered to be the reason for this enhanced catalytic activity. The size of.gold nanoparticles is maintained even after high temperature pretreatments, which show the benefit of encapsulation. The effect of the various pretreatments on the catalytic activity has also been reported.

Copper and silver nanoparticles stabilized by bistriazole-based dendritic amphiphile micelles for 4-nitrophenol reduction - Patil, Naganath G.; Basutkar, Nitin B.; Ambade, Ashootosh V. (New Journal of Chemistry, 2017)
Copper and silver nanoparticles were fabricated in aqueous solution using micellar assemblies of dendritic amphiphiles containing triazole rings. Dendritic amphiphiles displaying a bistriazole unit between a hydrophobic benzyl ether dendron and two oligo(ethylene glycol) (OEG) chains were synthesized using click chemistry. Micelles were characterized by DLS, TEM, CMC determination, and dye encapsulation. Micellar size was dependent on the dendron backbone structure and OEG chain length. Metal nanoparticles were characterized by TEM and UV-Vis spectroscopy. The Cu NPs had a smaller average particle diameter than the Ag NPs. The micelle-stabilized nanoparticles, at a concentration of 7.5 ppm, were shown to efficiently catalyze the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 in aqueous solution without stirring, using up to 1 ppm of substrate. The reaction catalyzed by Cu NPs followed zero order kinetics (k = 3.48 x 10(-3) M s(-1)), while the Ag NP-catalyzed reaction followed pseudo-first order kinetics (k = 1.28 x 10(-3) s(-1)).

Copper Cobalt Sulfide Nanosheets Realizing a Promising Electrocatalytic Oxygen Evolution Reaction - Chauhan, Meenakshi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Catalysis, 2017)
Nanostructured CuCo2S4, a mixed metal thiospinel, is found to be a benchmark electrocatalyst for oxygen evolution reaction (OER) in this study with a low overpotential, a low Tafel slope, a high durability, and a high turnover frequency (TOF) at lower mass loadings. Nanosheets of CuCo2S4 are realized from a hydrothermal synthesis method in which the average thickness of the sheets is found to be in the range of 815 nm. Aggregated nanosheets form a highly open hierarchical structure. When used as an electrocatalyst, CuCo2S4 nanosheets offer an overpotential value of 310 mV at a 10 mA cm(2) current density, which remains consistent for 10000 measured cycles in a 1 M KOH electrolyte. A chronoamperometric study reveals constant oxygen evolution for 12 h at a 10 mV s(-1) scan rate without any degradation of the activity. Furthermore, the calculated mass activity of the CuCo2S4 electrocatalyst is found to be 14.29 A/g and to afford a TOF value of 0.1431 s(-1) at 310 mV at a mass loading of 0.7 mg cm(-2). For comparison, nanostructures of Co3S4 and Cu0.5Co2.5S4 have been synthesized using a similar method followed for CuCo2S4. When compared to the OER activities among these three thiospinels and standard IrO2, CuCo2S4 nanosheets offered the highest OER activities at the same mass loading (0.7 mg/cm(-2)). Extensive X-ray photoelectron spectroscopy and electron paramagnetic resonance analyses for a mechanistic study reveal that introduction of Cu into the Co3S4 lattice enhances the oxygen evolution and kinetics by offering Cu2+ sites for utilitarian adsorption of OH, O, and OOH reactive species and also by offering a highly active high-spin state of octahedral Co3+ for OER catalysis.
Keywords: Bifunctional Electrocatalyst; Catalyst; Cuco2s4; Efficient Electrocatalyst; electrocatalyst; Electronic-structure; Nanoparticles; Nanosheet; oxide; oxygen evolution; performance; Recent Progress; Water oxidation; Water Splitting Hydrogen Evolution

Copper oxide supported on three-dimensional ammonia-doped porous reduced graphene oxide prepared through electrophoretic deposition for non-enzymatic glucose sensing - Maaoui, H.; Singh, S. K.; Teodorescu, F.; Coffinier, Y.; Barras, A.; Chtourou, R.; Kurungot, S.; Szunerits, S.; Boukherroub, R. (Electrochimica Acta, 2017)
The paper reports on the preparation of N-doped porous reduced graphene oxide/copper oxide (ammonia-doped-prGO/CuO) nanocomposite on gold electrodes using electrophoretic deposition (EPD) from an ethanolic suspension of ammonia-doped-prGO and Cu(ClO4)(2) by applying a DC voltage. The ammonia-doped-prGO/CuO nanocomposite film thickness is controlled by varying the deposition time. Morphological analysis using scanning electron microscopy (SEM) showed the formation of a 3 dimensional structure with CuO nanoparticles being homogeneously embedded in the graphene layer. Xray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Raman analysis revealed that the deposited copper was in its oxidized form, mainly CuO. The Au/ammonia-doped-prGO/CuO electrode was successfully applied for non-enzymatic amperometric detection of glucose. Under optimized conditions, the electrode exhibited a sensitivity of 1210 mu mM(-1) cm(-2) with a detection limit of 0.25 p,M (S/N =3) over a wide concentration range (0.25 mu M to 6 mM) at an applied potential of +0.50 V vs. Ag/AgCl. The electrode material displayed good stability, excellent selectivity, and accurate measurement in healthy and diabetic human serum samples.

Corrigendum: Agro-Industrial wastes for production of biosurfactant by bacillus subtilis ANR 88 and its application in synthesis of silver and gold nanoparticles [Front. Microbiol. 8, (492)] DOI: 10.3389/fmicb.2017.00492 - Rane, A.N.; Baikar, V. V.; Ravi Kumar, V.; Deopurkar, R. L. (Frontiers in Microbiology, 2017)

Coumarin-appended stable fluorescent self-complementary quadruple-hydrogen-bonded molecular duplexes - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2017)
In this paper we report a coumarin-conjugated self-assembling system adorned with valuable features such as high duplex stability and a built-in fluorophore, which would augment its application potential. This system forms a highly :stalik molecular duplex in a nonpolar solvent (K-dim > 1.9 X 10(7) M-1 in CDCl3). Due to the fluorescent property of coumarin, these new structural motifs may find potential application in material chemistry and supramolecular chemistry.

Covalent organic frameworks and organic cage structures - Banerjee, Rahul; Champness, Neil R. (CrystEngComm, 2017)

Critical role of select peptides in the loop region of G-rich PNA in the preferred G-quadruplex topology and stability - Bose, Tanaya; Kumar, Vaijayanti A. (Tetrahedron, 2017)
An uncharged PNA 15mer sequence formed unimolecular antiparallel G-quadruplex similar to that observed for DNA-TBA. Replacement of `tt' loop regions by peptides which induce helices or turns were found to have unpresidented effect on the quadruplex topology and stability. This study opens up a completely new strategy of utilizing G-quadruplex formation to display the array of functional groups in the three dimensional space thus creating a possibility of getting closer to the dream of designed peptides with three dimensional structures as observed in catalytic protein folds. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: ESI-MS study; G-quadruplex; Peptide nucleic acid; topology

Cross-coupling reactions of aryldiazonium salts with allylsilanes under merged gold/visible-light photoredox catalysis - Akram, Manjur O.; Mali, Pramod S.; Patil, Nitin T. (Organic Letters, 2017)
A method for the cross-coupling reactions of aryldiazonium salts with trialkylallylsilanes via merged gold/photoredox catalysis is described. The reaction is proposed to proceed through a photoredox-promoted generation of an electrophilic arylgold(III) intermediate that undergoes transmetalation with allyltrimethylsilane to form allylarenes.

Crystallisation-enhanced bulk hole mobility in phenothiazine-based organic semiconductors - Shinde, D. B.; Salunke, Jagadish K.; Candeias, Nuno R.; Tinti, Francesca; Gazzano, Massimo; Wadgaonkar, P. P.; Priimagi, Arri; Camaioni, Nadia; Vivo, Paola (Scientific Reports, 2017)
A series of three novel donor-acceptor systems based on C(3)-malononitrile-substituted phenothiazines was synthesised in good overall yields and their thermal, spectroscopic, and electrochemical properties were characterised. The compounds were prepared through a sequence of Ullmann-coupling, Vilsmeier-Haack formylation and Knoevenagel-condensation, followed by Suzuki-coupling reactions for introduction of aryl substitutents at C(7) position of the phenothiazine. The introduction of a donor unit at the C(7) position exhibited a weak impact on the optical and electrochemical characteristics of the compounds and led to amorphous films with bulk hole mobilities in the typical range reported for phenothiazines, despite the higher charge delocalisation as attested by computational studies. In contrast, highly ordered films were formed when using the C(7)-unsubstituted 3-malononitrile phenothiazine, exhibiting an outstanding mobility of 1 x 10(-3) cm(2) V-1 s(-1), the highest reported for this class of compounds. Computational conformational analysis of the new phenothizanes suggested that free rotation of the substitutents at the C(7) position suppresses the ordering of the system, thereby hampering suitable packing of the new materials needed for high charge carrier mobility.

C(sp(3))-F, C(sp(2))-F and C(sp(3))-H bond activation at silicon(II) centers - Swamy, V. S. V. S. N.; Parvin, Nasrina; Raj, K. Vipin; Sen, Sakya S. (Chemical Communication, 2017)
Silylene [PhC(NtBu)(2)SiN(SiMe3)(2)] (1) cleaves the C(sp(3))-H and C-F bonds of acetophenone and 1,1,1-trifluoroacetophenone, respectively, under mild conditions. The reaction is initiated via a nucleophilic attack from the oxygen to the silicon atom followed by C-F/H bond cleavage. The scope of C-F bond activation has further been extended with C6F6 and C6F5CF3.
Keywords: Boron triple bond; C-F Bond; Fluorinated Building-Block; H Activation; Ketones; N-heterocyclic carbenes; Oxodative Addition; Perfluorinated Arenes; Selective Activation; Transition-Metal Centers

CuCo2O4 nanowall morphology as Li-ion battery anode: Enhancing electrochemical performance through stoichiometry control - Bhardwaj, M.; Suryawanshi, A.; Fernandes, R.; Tonda, S.; Banerjee, A.; Kothari, D.; Ogale, S. (Materials Research Bulletin, 2017)
We have employed template-free synthesis of CuCo2O4 (CCO) system to achieve unique ultrathin porous nanowall type morphology, and evaluated for Li-Ion battery anode application. We observe that under the hydrothermal growth a starting stoichiometric mixture of cationic precursor's leads to a bi-phasic constitution comprising of defect-spinel CCO and a small quantity of CuO. Use of the excess but optimum cobalt in the precursor mix leads to single phase defect-spinel. We have carefully examined the implications of off-stoichiometry for different cases of interest (including the case of Cu-excess) for morphology, microstructure, the physical/electrochemical properties, and the evolution of the Li-ion battery anode under cycling for different active materials loading. In case of optimum Cu excess based CCO renders an impressive performance as Li-ion battery anode with high rate performance, 836 mAh g−1 and 757 mAh g−1 at 1.25C and 2.5C, respectively, and good cycling stability. © 2016 Elsevier Ltd

Cucurbit[7]uril induced formation of fret-enabled unilamellar lipid vesicles - Kushwaha, Shilpi; Maity, Arunava; Gangopadhyay, Monalisa; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Langmuir, 2017)
A unique fluorescence resonance energy transfer (FRET) process is found to be operational in a unilamellar lipid self-assembly in the aqueous phase. A newly synthesized naphthyl based long chain lipid derivative [N-(naphthalene-1-ylmethyl)tetradecane-1-ammonium chloride, 14NA(+)] forms various self-assembled architectures in the aqueous phase. Controlled changes in lipid concentration lead to a transition of the self-assemblies from micelles to vesicles to rods. In the presence of cucurbit[7]uril (CB7), 14NA(+) forms a host-guest [2]pseudorotaxane complex (CB7(sic)14NA(+)) and secondary interactions lead to the formation of a lipid bilayer with hydrophobic pockets situated in between the layers. The change in the structure of 14NA(+) assemblies, interaction with CB7 and formation of supramolecular assemblies of CB7(sic)14NA(+) were examined using light scattering, spectroscopic, and microscopic techniques. Entrapment of a luminescent dye, anthracene within the hydrophobic bilayer of the supramolecular assembly CB7(sic)14NA(+) favors a modified luminescent response due to an efficient FRET process. Further, the FRET process could be controlled by thermal and chemical stimuli that induce transformation of unilamellar vesicles.

Cyclization mechanism of phomopsene synthase: mass spectrometry based analysis of various site-specifically labeled terpenes - Shinde, Sandip S.; Minami, Atsushi; Chen, Zhi; Tokiwano, Tetsuo; Toyomasu, Tomonobu; Kato, Nobuo; Sassa, Takeshi; Oikawa, Hideaki (Journal of Antibiotics, 2017)
Elucidation of the cyclization mechanism catalyzed by terpene synthases is important for the rational engineering of terpene cyclases. We developed a chemoenzymatic method for the synthesis of systematically deuterium-labeled geranylgeranyl diphosphate ( GGPP), starting from site-specifically deuterium-labeled isopentenyl diphosphates (IPPs) using IPP isomerase and three prenyltransferases. We examined the cyclization mechanism of tetracyclic diterpene phomopsene with phomopsene synthase. A detailed EI-MS analysis of phomopsene labeled at various positions allowed us to propose the structures corresponding to the most intense peaks, and thus elucidate a cyclization mechanism involving double 1,2-alkyl shifts and a 1,2-hydride shift via a dolabelladien-15-yl cation. Our study demonstrated that this newly developed method is highly sensitive and provides sufficient information for a reliable assignment of the structures of fragmented ions.

Calixarene intercalated NiCo layered double hydroxide for enhanced oxygen evolution catalysis - Waghmode, Babasaheb J.; Gaikwad, Aarti P.; Rode, V, Chandrashekhar; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (ACS Sustainable Chemistry & Engineering, 2018)
Water splitting provides a promising, sustainable way to resolve problems arising due to depleting fossil fuels. The success needs development of low-cost and high-performance electrode materials. The oxygen evolution reaction (OER) is a crucial reaction in water splitting. The combined Ni and Co oxide developed nanostructures having a small overpotential and fast kinetics of OER. They have drawn considerable attention, because of their theoretically high efficiency, high abundance, low cost, and environmental benignity in comparison with precious metal oxides, such as RuO2 and IrO2. However, the desired efficiency needs the developments of enhanced specific active area and conductivity. In the present communication, we address these issues. Specifically, exfoliation of layer double hydroxide (LDH) is applied to enhance the active surface area. The study reveals that intercalation by calixarene in NiCo LDH affords a multifunctional interlayer to deliver a large active surface area and fast electron transport toward the carbon nano-onion (CNO) support. It favorably lowers the overpotentials in OER (290 mV) and attains Tafel slope of 31 mV/decade. Enhanced conductivity is achieved using CNO as a support for the calixarene intercalated NiCo LDH. These developments offer a synergistic effect in achieving superior electrocatalytic activity for OER. This work gives insight into designing binder-free electrodes in alkaline media with good stability for advanced OER activity.
Keywords: Calixarene; electrocatalyst; Exfoliation; NiCo LDH; Oxygen Evolution Reaction

Carbon fabric based solar steam generation for waste water treatment - Higgins, M. W.; Rahmaan, Shakeel A. R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Jha, Neetu (Solar Energy, 2018)
Decontamination of waste water is one of the most practical techniques to tackle the worldwide clean water shortage. In recent times, solar steam based decontamination of contaminated water has been attested as a potential sustainable strategy to get clean water using renewable resources. Herein, we report the utilization of Carbon fabric and Titanium Nanorods on Carbon Fabric for solar steam based water purification techniques. The performance of Carbon Fabric was tested under different conditions and the results proved that Carbon Fabric has excellent light to heat conversion capabilities in both real and ideal conditions. Owing to the excellent performance of Carbon Fabric, it was used for purification of different types of contaminated water. About 99.9% of salt and 87% of organic contaminants were removed from saline water and organic waste water respectively, using a simple low cost carbon fabric based homemade prototype. We also present the application of Titanium Nanorods on carbon fabric for the efficient removal of dye molecules like Rhodamine B from contaminated water using solar driven interfacial steam generation mechanism.
Keywords: Desalination; Dye degradation; Solar steam; Waste water treatment

Cascade dehydrative amination of glycerol to oxazoline - Pandya, R.; Mane, R.; Rode, C. V. (Catalysis Science & Technology, 2018)
Transformation of biomass into valuable nitrogen-containing compounds is highly desired, yet less explored. Here, we report a simple and efficient method for the direct conversion of bioglycerol to oxazoline involving glycerol dehydration to acetol followed by its amination using an aqueous solution of ammonia. For the two-step strategy a non-noble metal Cu-Zr catalyst was developed, giving a glycerol to acetol conversion of 78% followed by amination separately with 95% selectivity to oxazoline. Moreover, we have demonstrated a single-pot oxazoline synthesis using Ru/C as the most stable catalyst to achieve 95% selectivity to oxazoline without any leaching. XPS studies revealed the co-existence of multivalent Ru species in different percentages depending on the nature and structure of the support. These multivalent species (RuO2 and RuO3) have a synergistic effect on the activation of the carbonyl group, whereas Ru-0 is an active site for ammonia dissociation. NH3-TPD and Py-IR spectroscopy results also suggest that the presence of relatively moderate acid sites and a higher BrOnsted/Lewis acid ratio in the catalyst promote the selective production of oxazoline. The reaction pathway involves first glycerol dehydration to acetol. In the subsequent step, NH3 is dissociatively adsorbed on the catalyst surface and the imine thus formed is condensed with a second molecule of acetol to obtain oxazoline. The studied catalyst could be recycled successfully without any significant loss of catalytic activity.

Cascade synthesis of 5-(Acetoxymethyl) furfural from carbohydrates over Sn-mont catalyst - Shinde, Suhas; Deval, Kashmira; Chikate, Rajeev; Rode, Chandrashekhar (ChemistrySelect, 2018)
The 5-(Acetoxymethyl)furfural (AcMF) is emerged as an important alternative for 5-(hydroxymethyl)furfural (HMF). It is also a starting material for those products which are typically prepared from HMF. The growing importance of AcMF encouraged us to prepare it directly from cheap and abundant carbohydrates. The production AcMF from glucose and glucose-like carbohydrates is an exigent assignment, owing to tough isomerisation of glucose to fructose. The Sn-Mont catalyst having a unique combination of Lewis as well as Bronsted acid sites was employed for direct glucose conversion into AcMF. Lewis acid sites of Sn-Mont facilitate the isomerisation of glucose to fructose. At the same time, dehydrative-esterification of fructose to AcMF is catalyzed by Bronsted acid sites of Sn-Mont. Different concentrations of Sn containing Sn-Mont catalysts were by prepared mixing montmorillonite clay with different molar concentration (e.g. 0.1 M-0.4 M) of aqueous solutions of SnCl4 center dot 5H(2)O. AcMF was produced in as high as 43% yield directly from glucose over Sn-Mont(0.3 M) catalyst owing to its highest acid strength. The efficacy of Sn-Mont(0.3 M) catalyst was also probed for sucrose and fructose that resulted in 53% and 58% yield of AcMF, respectively. The critical properties of all the prepared Sn-Mont catalysts were investigated through XRD, BET surface area, ICP-OES, temperature-programmed desorption of NH3 and pyridine-FTIR and XPS techniques.
Keywords: 5-(Acetoxymethyl)furfural; Bronsted/Lewis acid; carbohydrates; Dehydrative-esterification; Sn-Mont

Cascade synthesis of dihydrobenzofuran via claisen rearrangement of allyl aryl ethers using FeCl 3 /MCM-41 catalyst - Sakate, Sachin S.; Shinde, Suhas H.; Kasar, Gayatri B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Journal of Saudi Chemical Society, 2018)
Dihydrobenzofuran as one of the active ingredients of the naturally occurring motif is synthesized by using in situ generation of ortho allyl phenols. Aryl allyl ethers on reacting with catalytic amounts of non noble metal iron (III) chloride supported on MCM-41 under moderate reaction conditions yield dihydrobenzofuran. First step via Claisen rearrangement gives ortho allyl phenol followed by its in situ cyclization to yield dihydrobenzofuran in very good yields. Both Lewis as well as Brønsted acidity of the catalyst as evidenced by Py-FTIR studies was found to catalyze the cascade synthesis of dihydrobenzofuran. The scope of the present strategy was successfully demonstrated for several substrates with varying electronic effects for the synthesis of corresponding dihydrobenzofuran with high yields in a range of 71-86%.
Keywords: Aryl allyl ether; Claisen rearrangement; Dihydrobenzofuran; Ferric chloride; MCM-41

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using Oxone as an oxidant (vol 43, pg 6875, 2017) - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2018)

Catalytic and efficient synthesis of optically active terminal epoxides and 1,2-diols using a new lanthanum triflate assisted C1-symmetric bimetallic chiral salen cobalt complex - Patel, D.; Thakur, S. S.; Shinde, S. S.; Kumar, P. (Letters in Organic Chemistry, 2018)
The catalytic asymmetric synthesis of terminal epoxides and 1,2-diols via a hydrolytic kinetic resolution of racemic terminal epoxides using a new bimetallic chiral salen CoIII complex incorporated with La(OTf)3 as a catalyst is reported. The new bimetallic chiral salen CoIII complex bearing La(OTf)3 was prepared in a one-pot procedure by activation and bimetallic complex formation from the inactive Jacobsen chiral salen CoII complex (salen = N, N′-bis(3,5-di-tert-butylsalicylidene)-1,2- cyclohexane-diamine). We observed that C1-symmetric chiral bimetallic Co-complex coordinated with La(OTf)3 works as a chiral catalyst and remarkably increased the reactivity and enantioselectivity in the hydrolytic kinetic resolution of terminal epoxides compared to its monometallic analogues. La(OTf)3 plays a crucial role as an achiral Lewis acid in this process, which is supported by the experimental observation presented. To explore the absolute configuration of glycidyl butyrate a vibrational circular dichroism (VCD) spectra was calculated using density functional theory.

Catalytic enantioselective 1,3-alkyl shift in alkyl aryl ethers: efficient synthesis of optically active 3,3 '-diaryloxindoles - Gade, Amol B.; Bagle, Pradip N.; Shinde, Popat S.; Bhardwaj, Vipin; Banerjee, Subhrashis; Chande, Ajit; Patil, Nitin T. (Angewandte Chemie-International Edition, 2018)
Reported is the first organocatalytic asymmetric 1,3-alkyl shift in alkyl aryl ethers for the synthesis of chiral 3,3'-diaryloxindoles using a chiral Bronsted acid catalyst. Preliminary results showed that each enantiomer of the 3,3'-diaryloxindole, and a racemic mixture, showed different antiproliferative activities against HeLa cell lines by using an MTT assay.

CCCTK (Compute Cure for Cancer ToolKit) an open source drug discovery platform for design of novel anti-cancer agents - Karthikeyan, Muthukumarasamy; Vyas, Renu (255th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nexus of Food, Energy, and Water, 2018)

CCCTK: High performance molecular informatics toolkit for the design of anti-cancer molecule - Karthikeyan, Muthukumarasamy (256th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nanoscience, Nanotechnology and Beyond, 2018)

Changing landscapes of industry-academia collaboration - Nair, G.G. (Indian Drugs, 2018)

Characterization of mineral phosphate solubilizing and plant growth promoting bacteria from termite soil of arid region - Chakdar, Hillol; Dastager, Syed G.; Khire, Jayant M.; Rane, Digeshwar; Dharne, Mahesh S. (3 Biotech, 2018)
Five highly efficient phosphate solubilizing bacteria, viz., Pantoea sp. A3, Pantoea sp. A34, Kosakonia sp. A37, Kosakonia sp. B7 and Bacillus sp. AH9 were isolated from termitorial soils of Sanjivani island of southern Maharashtra, India. These isolates were characterized and explored for phosphate solubilization and plant growth promotion. Among these, Bacillus sp. AH9 showed highest phosphate solubilization index (3.5) and solubilization efficiency (250%) on Pikovskaya agar. Interestingly, Pantoea sp. A34 displayed maximum mineral phosphate solubilization (1072.35mg/L) in liquid medium and during this period the pH dropped to 3.13. All five isolates had highest P solubilization at 48h after inoculation. During mineral phosphate solubilization, both gluconic acid and 2-keto gluconic acid were produced by Kosakonia and Bacillus isolates, while only 2-keto gluconic acid was detected in Pantoea isolates. Highest organic acid (39.07 +/- 0.04g/L) production was envisaged in Bacillus sp. AH9, while Pantoea sp. A34 produced the least amount (13.00 +/- 0.01g/L) of organic acid. Seed bacterization with Pantoea sp. A3 and Kosakonia sp. A37 resulted in 37% and 53% increase in root length of tomato seedlings, respectively, while Pantoea sp. A34 and Kosakonia sp. B7 had deleterious effects on root length as well as overall growth of the seedlings. To our knowledge, this is the first report of plant growth promoting potential of microorganisms isolated from termitorial soil of Sanjivani island, which is a drought-prone area. Therefore, such efficient growth promoting P solubilizers can offer an effective solution for sustainable agriculture in arid, dryland farming and drought-prone regions.

Chemical oxidative and solid state synthesis of low molecular weight polymers for organic field effect transistors - Mahale, Rajashree Y.; Dharmapurikar, Satej S.; Chini, Mrinmoy Kumar (Chemical Physics Letters, 2018)
Solution processability of the precursor molecules is a major issue owing to their limited solubility for the synthesis of conjugated polymers. Therefore, we favour the solvent free solid state chemical oxidative polymerization route for the synthesis of diketopyrrolopyrrole (DPP) based donor-acceptor (D-A) type conjugated polymers. D-A type polymer Poly(S-OD-EDOT) which contains DPP coupled with EDOT donor units is synthesized via solid state polymerization method. The polymer is employed as an active layer for organic field-effect transistors to measure charge transport properties. The Polymer shows good hole mobility 3.1 x 10(-2) cm(2) V-1 s(-1), with a on/off ratio of 1.1 x 10(3). (C) 2018 Elsevier B.V. All rights reserved.

Chemo-biological evaluation of antidiabetic activity of M entha arvensis L. and it's role in inhibition of advanced glycation end products - Agawane, Sachin B.; Gupta, Vidya S.; Kulkarni, Mahesh J.; Bhattacharya, Asish K.; Koratkar, Santosh (Journal of Ayurveda and integrative medicine, 2018)
Background: There has been enormous curiosity in the development of alternative plant based medicines to control diabetes, oxidative stress and related disorders. One of the therapeutic approaches is to reduce postprandial release of glucose in the blood. Two key enzymes that are involved in reducing postprandial glucose are α-amylase and α-glucosidase. Mentha arvensis L. has been traditionally used by several tribes as a medicinal plant to treat various disorders. Objective: The present study was undertaken to test M. arvenisis L. for inhibition of postprandial hyperglycemia. Material and method: We performed various in vitro and in vivo tests to evaluate efficacy of M. arvenisis L. for antidiabetic activity (postprandial hyperglycemia). Results: Methanolic extract of M. arvensis L. leaves showed DPPH free radical scavenging activity (more than 78% μg/μl) and high antiglycation potential (more than 90% inhibition of AGE formation). Methanolic extract also showed remarkable inhibitory effects on α-amylase (more than 50% μg/μl) and α-glucosidase (68% μg/μl) and significant inhibition of postprandial hyperglycemia in starch induced diabetic Wistar rats. Conclusion: The non-insulin dependent antidiabetic or inhibition of postprandial hyperglycemic activity of methanolic extract of M. arvensis L. leaves was shown by using in vitro and in vivo approaches in the present study.

Chiral amino-acid-amide based ionic liquids as a stereoselective organocatalyst in asymmetric transfer hydrogenation of acetophenone at room-temperature - Javle, Balasaheb R.; Kinage, Anil K. (Chemistryselect, 2018)
Chiral Ionic Liquids (CILs) of amino acid amide were synthesized and used as novel organo catalyst for Asymmetric Transfer Hydrogenation (ATH) of acetophenone at room temperature. The developed CILs show very high yield and excellent enantio-selectivity in transfer hydrogenation of acetophenone.

Chitosan-based bionanocomposites for biomedical application - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Annamalai, Pratheep K. (Bioinspired Biomimetic and Nanobiomaterials, 2018)
Natural polymers have greatly impacted the advancement of modern medicine. Natural polymer-based biomaterials are biodegradable. A significant advantage of natural polymers is that they can be broken down and removed from the body after they have served their function. A wide range of novel biomaterials from natural polymers has been investigated to meet new challenges in medical science. Chitosan is one of the natural polymers which have been widely used in the biomedical field. Nanotechnology is one of the most popular areas of current research. In the area of nanotechnology, polymer and metal/metal oxide nanoparticle matrix-based nanocomposites have generated a significant amount of attention in the recent literature. These bionanocomposites have wide-ranging applications in drug delivery and tissue engineering. This paper discusses polymer-metal/metal oxide nanoparticle matrix-based nanocomposite biomaterials and their applications in the biomedical field - that is, drug delivery and tissue engineering applications.

Chitosan-thiobarbituric acid: a superadsorbent for mercury - Bhatt, Rahul; Kushwaha, Shilpi; Bojja, Sreedhar; Padmaja, P. (ACS Omega, 2018)
In the present investigation, chitosan (CH) as supramolecularly cross-linked with thiobarbituric acid to form CT. CT was well characterized by UV, scanning electron microscopy-energy-dispersive X-ray analysis, Fourier trans form infrared, NMR, differential scanning calorimetry, thermogravimetric analysis, and X-ray difTraction analyses, and its adsorption potential for elemental mercury (Hg-0), inorganic mercury (Hg2+), and methyl mercury (CH3Hg+) was investigated. Adsorption experiments were conducted to optimize the parameters for removal of the mercury species under study, and the data were analyzed using Langmuir, Freundlich, an Temkin adsorption isotherm models. CT was found to have high adsorption capacities of 1357.69, 2504.86, and 2475.38 rng/g for Hg-0, Hg2+, and CH3Hg+, respectively. The adsorbent CT could be reused up elemental mercury using 0.01 N thiourea, inorganic mercury using 0.01 N perchloric acid, and methyl to three cycles by eluting mercury with 0.2 N NaCl.

Cloning and characterization of trehalase: a conserved glycosidase from oriental midge, Chironomus ramosus - Shukla, Ekta; Thorat, Leena; Bendre, Ameya D.; Jadhav, Santosh; Pal, Jayanta K.; Nath, Bimalendu B.; Gaikwad, Sushama M. (3 Biotech, 2018)
Insect trehalase is a multiferous enzyme, crucial for normal physiological functions as well as under stress conditions. In this report, we present a fundamental study of the trehalase gene segment (1587 bp) from Chironomus ramosus (CrTre) encoding for 529 amino acids, using appropriate bioinformatics tools. C. ramosus, a tropical midge is an emerging animal model to investigate the consequences of environmental stresses. We observed that CrTre belongs to GH family 37 in the CAZy database and possess 57-92% identity to dipteran trehalases. In silico characterization provided information regarding the structural, functional and evolutionary aspects of midge trehalase. In the phylogenetic tree, CrTre clustered with the soluble dipteran trehalases. Moreover, domain functional characterization of the deduced protein sequence by InterProScan (IPR001661), ProSite (PS00927 and PS00928) and Pfam (PF01204) indicated presence of highly conserved signature motifs which are important for the identification of trehalase superfamily. Furthermore, the instability index of CrTre was predicted to be < 40 suggesting its in vivo stability while, the high aliphatic index indicated towards its thermal stability (index value 71-81). The modelled 3D tertiary structure of CrTre depicts a (alpha/alpha)(6) barrel toroidal core. The catalytic domain of the enzyme comprised Glu424 and Asp226 as the putative active site residues. Interestingly, the conserved motifs were observed to be formed by the flexible loopy regions in the tertiary structure. This study revealed essential sequence features of the midge trehalase and offers better insights into the structural aspects of this enzyme which can be correlated with its function.
Keywords: Conserved motifs; Homology modelling; Midges; Secondary structure; trehalose

Close loop separation process for the recovery of Co, Cu, Mn, Fe and Li from spent lithium-ion batteries - Dutta, Deblina; Kumari, Archana; Panda, Rekha; Jha, Soni; Gupta, Divika; Goel, Sudha; Jha, Manis Kumar (Separation and Purification Technology, 2018)
Lithium-ion batteries (LIBs) are essential energy source used in advanced electronic gadgets for getting constant and continuous power supply. Huge amount of spent LIBs are generated after their end use. LIBs contain metals, organics and plastics which require proper treatment before disposal. Keeping in view of stringent environmental regulations, limited natural resources and energy crisis, adopting recycling will not only protect the environment and pacify the gap between demand and supply but also conserve the natural resources. Present paper reports a complete process for the recycling of LIBs to recover metals and materials as value added products fulfilling zero waste concept. Initially, the spent LIBs were crushed and beneficiated by wet scrubbing process to separate cathodic material, plastic and metallic fractions. The cathodic material contained 20% Co and 2.4% Li along with other impurities (Mn, Fe, Cu). The cathodic material obtained from different LIBs were homogenized and put to leaching studies to optimize various process parameters viz. effect of leachant concentration, temperature, time, etc. About 97% Co and 99.99% Li were leached using 2 M H2SO4 and 10% H2O2 at room temperature, in 2 h maintaining pulp density 75 g/L. Kinetics for leaching of Co fitted well with Chemical reaction control dense constant size cylindrical particles model, i.e. 1 - (1 - X)(1/2) = Kct. The leach liquor obtained was further processed to recover Mn and Fe using (NH4)(2)S2O8 as a precipitant whereas 99.99% Cu was extracted using LIX 84 IC at eq. pH 2, O/A ratio 1/1 and mixing time 5 min. Further, from the leach liquor depleted with Mn, Fe and Cu, similar to 98% Co was extracted using 20% Cyanex 272 at pH 4.8 in 10 min maintaining phase ratio (O/A) 1/1 in two stages, leaving Li in the raffinate. From the pure Co solution, value added products as metal and salt were produced using electrowinning/evaporation/precipitation techniques. The TCLP test of leached residue shows the presence of metals within permissible limit and the effluent generated was treated in an effluent treatment plant (ETP) with standard procedure and recycled to the system. The developed clean process is economical as well as environment friendly and has potential to be translated in industry after scale-up studies.

Co9Se8 nanoparticles as high capacity anode material for lithium-ion batteries - Kumar, Pushpendra; Hu, Lung-Hao (Materials Research Express, 2018)
Present investigation deal with the facile synthesis of Co9Se8 nanoparticles (NPs) and their application as the potential anode for lithium-ion battery (LIB). The primary size of the Co9Se8 NPs can be achieved between 10 similar to 25 nm while the secondary cluster size ranging from 150 similar to 200 nm as observed by transmission electron microscope (TEM). The specific capacity of Co9Se8 NPs LIB anode can reach around similar to 610 mAhg(-1) during charging (lithium ion released from Co9Se8 nanoparticles), and -730 mAhg(-1) during discharging (lithium ion intercalated) at an applied current density of similar to 100 mAg(-1). These values are significantly higher than that of the commercial graphite anode (theoretical capacity similar to 372 mAhg(-1)). The irreversibility of Co9Se8 anode (similar to 15%) is also significantly lower than that of most metal oxides and silicon-based anodes (irreversibility ranging between 30 similar to 50% or higher for Si). The reason for superior specific capacity and low irreversibility compared to metal oxides and silicon-based materials could be owing to the stable nano-cluster size which help to reduce the diffusion path and internal resistance to lithium ion.
Keywords: irreversibility; lithium-ion battery; lithium-ion diffusion; Nanoparticles; specific capacity

Cobalt-catalyzed acceptorless dehydrogenative coupling of aminoalcohols with alcohols: direct access to pyrrole, pyridine and pyrazine derivatives - Midya, Siba P.; Landge, Vinod G.; Sahoo, Manoj K.; Rana, Jagannath; Balaraman, Ekambaram (Chemical Communications, 2018)
Here, the first example is reported of a new, molecularly defined SNS-cobalt(II) catalyst for the acceptorless dehydrogenative coupling (ADC) of unprotected amino alcohols with secondary alcohols leading to pyrrole and pyridine derivatives.

Cobalt-doped Ba2In2O5 brownmillerites: an efficient electrocatalyst for oxygen reduction in alkaline medium - Jijil, C. P.; Patil, I. M.; Kakade, B.; Nandini Devi, R. (ACS omega, 2018)
A series of compounds with cobalt doping in the indium site of Ba2In2O5 brownmillerites exhibited excellent oxygen reduction activity under alkaline conditions. Doping (25%) retains the brownmillerite structure with disorder in the O3 site in the two-dimensional alternate layer along the ab plane. Further substitution of cobalt in the indium site leads to the loss of a brownmillerite structure, and the compound attains a perovskite structure. Cobalt-doped samples exhibited far better oxygen reduction reaction (ORR) activity when compared to the parent Ba2In2O5 brownmillerite. Among the series of compounds, BaIn0.25Co0.75O3−δ with the highest Co doping and oxygen vacancies randomly distributed in the lattice exhibited the best ORR activity. BaIn0.25Co0.75O3−δ showed a 40 mV positive shift in the onset potential with better limiting current density and a nearly four-electron-transfer reduction pathway when compared to the parent Ba2In2O5 brownmillerite.

Co-gasification of high ash coal–biomass blends in a fluidized bed gasifier: experimental study and computational intelligence-based modeling - Tiwary, Shishir; Ghugare, Suhas B.; Chavan, Prakash D.; Saha, Sujan; Datta, Sudipta; Sahu, Gajanan; Tambe, Sanjeev S. (Waste and Biomass Valorization, 2018)
Co-gasification (COG) is a clean-coal technology that uses a binary blend of coal and biomass for generating the product gas; it is environment-friendly since it emits lesser quantities of pollutants compared to the coal gasification process. Although coals found in many countries contain high percentages of ash, co-gasification studies involving such coals, and the process modeling thereof, are rare. Accordingly, this study presents results of the co-gasification experiments conducted in a fluidized-bed gasifier (FBG) pilot plant using as a feed the blends of high ash Indian coals with three biomasses, namely, rice husk, press mud, and sawdust. Since the underlying physicochemical phenomena are complex and nonlinear, modeling of the COG process has been performed using three computational intelligence (CI)-based methods namely, genetic programming, artificial neural networks, and support vector regression. Each of these formalisms was employed separately to develop models predicting four COG performance variables, namely, total gas yield, carbon conversion efficiency, heating value of product gas, and cold gas efficiency. All the CI-based models exhibit an excellent prediction accuracy and generalization performance. The co-gasification experiments and their modeling presented here for a pilot-plant FBG can be gainfully utilized in the efficient design and operation of the corresponding commercial scale co-gasifiers utilizing high ash coals.
Keywords: Artificial neural networks; Co-gasification; Computational intelligence; Fluidized bed gasifier; genetic programming; support vector regression

Colloidal Mn2+ doped 2D (n =1) lead bromide perovskites: efficient energy transfer and role of anion in doping mechanism - Haris, Muhammed; Bakthavatsalam, Rangarajan; Kundu, Janardan (ChemistrySelect, 2018)
Mn²⁺ doping directly into APbCl3 type 3D nanocrystals, manifesting host to dopant energy transfer, have been heavily reported for illumination and display applications. However, these doped 3D ABX3 systems have low/modest exciton binding energy. Strongly bound excitons in the doped system can enhance the dopant‐host carrier exchange interactions leading to efficient energy transfer. Reported here is a simple and facile synthesis of colloidal Mn²⁺ doped (Butylammonium/octylammonium)2PbBr4 2D (n=1) perovskites that demonstrate enhanced energy transfer from strongly bound excitons of the host material to the Mn²⁺ dopant ions resulting in intense orange‐yellow emission due to spin forbidden internal transition (⁴T1 → ⁶A1) with the highest quantum yield (Mn²⁺) of 36%. Consistent with experimental evidences presented here, mechanism of this thermally aided doping process in these 2D systems, very likely, involves halide vacancy and its diffusion that precedes the cation exchange (doping) process. Owing to the high quantum yield, stability in ambient atmosphere, simplicity and scalability of the synthetic procedure, Mn²⁺ doped 2D perovskites could be beneficial as color converting phosphor material and can be utilized to further explore their magneto‐optoelectronic properties.

Composite thin film of simultaneously formed carbon and SnO2 QDs for supercapacitance application - Jadhav, Aarti; Patil, Sagar; Patil, Kashinath Rangu; Sathaye, Shivaram Dattatray; Rode, Chandrashekhar Vasant (New Journal of Chemistry, 2018)
Composite material with uniform size and structure is a critical asset that decides its properties like charge transfer, thermal, photoluminescence, mechanical, etc. and consequently the applications. Here for the first time, we report the concept of flame/combustion at liquid-liquid interface to synthesize in situ, thin film formation of composite consisting of two or more quantum dots. Synthesis of thin films of a composite containing C and SnO2 QDs having particle sizes below 3 nm was successfully done. As compared to a single quantum dots system, the formed composite showed significantly improved specific capacitance due to the synergistic effect arising from strong interaction between C and SnO2 QDs. This was confirmed by XPS, UV visible spectroscopy and photoluminescence spectra. Moreover, it was confirmed that even after 1000 charge/discharge cycles, the interaction between C and Sn remained unaltered; indicating significant stability of capacitance. Some of the advantages of this method include one step, eco-friendly process at ambient conditions. The generality of the method was established by synthesizing C-ZnO and C-TiO2 composite thin film. This new approach can be extended to form many other valuable composite thin films for various applications.

Comprehensive metabolic and transcriptomic profiling of various tissues provide insights for saponin biosynthesis in the medicinally important Asparagus racemosus - Srivastava, Prabhakar Lal; Shukla, Anurag; Kalunke, Raviraj M. (Scientific Reports, 2018)
Asparagus racemosus (Shatavari), belongs to the family Asparagaceae and is known as a "curer of hundred diseases" since ancient time. This plant has been exploited as a food supplement to enhance immune system and regarded as a highly valued medicinal plant in Ayurvedic medicine system for the treatment of various ailments such as gastric ulcers, dyspepsia, cardiovascular diseases, neurodegenerative diseases, cancer, as a galactogogue and against several other diseases. In depth metabolic fingerprinting of various parts of the plant led to the identification of 13 monoterpenoids exclusively present in roots. LC-MS profiling led to the identification of a significant number of steroidal saponins (33). However, we have also identified 16 triterpene saponins for the first time in A. racemosus. In order to understand the molecular basis of biosynthesis of major components, transcriptome sequencing from three different tissues (root, leaf and fruit) was carried out. Functional annotation of A. racemosus transcriptome resulted in the identification of 153 transcripts involved in steroidal saponin biosynthesis, 45 transcripts in triterpene saponin biosynthesis, 44 transcripts in monoterpenoid biosynthesis and 79 transcripts in flavonoid biosynthesis. These findings will pave the way for better understanding of the molecular basis of steroidal saponin, triterpene saponin, monoterpenoids and flavonoid biosynthesis in A. racemosus.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule - Shivakumar, K.I.; Goudappagouda.; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2018)
We report a novel set of easily tailorable C-3 symmetric molecules with a pi-extended core and adorned with different thioalkyl groups, exhibiting solvatofluorochromic and amphoteric redox behaviour. The nearly planar core exhibits intermolecular face-to-face pi-stacking, S...S and intramolecular S...O interactions. Current-sensing atomic force microscopy studies revealed a high conductivity of similar to 0.15 mS cm(-1) in the undoped J-aggregate nanofibres of the thiopropyl appended gelator.

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Continuous flow synthesis of micron size silica nanoparticles: parametric study and effect of dosing strategy - Jundale, Rajashri; Bari, Atul; Thara, Chinnu; Kulkarni, Amol (Journal of Flow Chemistry, 2018)
This work for the first time reports continuous flow synthesis of silica nano-particles of size over 1 mu m using a simple tubular reactor. The systematic approach involves the study of effect of various parameters like: ammonia concentration, water concentration, electrolyte concentraton, temperature, solvent, residence time and mode of TEOS injection over a wide range. A combination of ethanol and butanol was used as the medium with relatively lower polarity. Various process parameters were optimized to obtain highly monodispersed particles of size up to 600 nm and high yield (up to 90%). Attempts of reducing the reaction time by increasing temperature or concentrations of any of the reagents resulted in significant polydispersity and even in the formation of random shape agglomerates. At the optimized conditions almost complete conversion of TEOS happenned within 40 min and further growth of particles was achieved by adding TEOS using multipoint injection approach. While multipoint dosing resulted in the formation of very small number of secondary particles, the larger particles continued to grow beyond 800 nm. Further reduction in the polarity of reaction medium was achieved by adding 20% v/v of toluene, which without changing homogeneity of the solution resulted in particles as large as 0.9-1.1 mu m.
Keywords: Flow synthesis; Multipoint injection; silica; TEOS; Tubular reactor

Controlled release nanocomposite microcapsules for agricultural applications - Shanmuganathan, Kadhiravan; Shukla, Parshuram; Jagtap, Siddheshwar; Patil, Vishal; Sapre, Aditya (256th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nanoscience, Nanotechnology and Beyond, 2018)

Controlled surface/interface structure and spin enabled superior properties and biocompatibility of cobalt ferrite nanoparticles - Ansari, Sumayya M.; Sinha, Bhavesh B.; Pai, Kalpana R.; Bhat, Suresh K.; Ma, Yuan-Ron; Sen, Debasis; Kolekar, Yesh D.; Ramana, C., V. (Allied Surface Science, 2018)
High quality, crystalline, well-dispersed, and stable magnetic oxide nanoparticles (NPs) of inverse spinel cobalt ferrite (CoFe2O4; CFO) were prepared by a facile, reproducible, and simple hydrothermal route. The transmission electron microscopy, small-angle scattering and X-ray diffraction analyses demonstrate the structural quality of CFO NPs with a controlled size of similar to 12 nm. Small-angle scattering experiments demonstrate that the pristine CFO NPs have the individual size similar to 8.5 nm and spherical shape. The Raman and infrared spectroscopic measurements further confirm their high chemical quality and cubic symmetry. CFO NPs exhibit a remarkable, maximum coercivity (H-c) value of 18.92 kOe, which is the highest value achieved to date. Surface spins and spins canting along with a weak dipolar interaction accounts for the giant H-c and large effective anisotropy (11.45 x 10(6) erg/cm(3)) of these CFO NPs. The magnetic grain size of NPs reveals that the canted surface spins exist around the magnetic particles. Reorientation of surface spins and interparticle interaction causes the jumping behaviour in M-H hysteresis loops at H = 0. The cell viability of CFO NPs against the cancer (cisplatin resistant ovarian cancer - A2780/CP70) was evaluated to determine their potential application in biomedicine and health science. The mild response of CFO NPs in terms of their anti-proliferative nature against cancer cells and negligible cytotoxicity suggests their human-safe-and-friendly nature which makes them suitable for biomedical/health-related applications. Assessment of toxicity toward human red blood cells (RBC) revealed that hemolysis is less than 5% compared to the positive control confirming the potential applications of CFO NPs targeting human cells and making relevant for adopting them in biomedicine.

Convenient synthesis of the enantiomerically pure (S)-2,4-dihydroxybutyl-4-hydroxybenzoate using hydrolytic kinetic resolution - More, N. A.; Jadhao, N. L.; Garud, D. R.; Gajbhiye, J. M. (Synthetic Communications, 2018)
(S)-2,4-Dihydroxybutyl-4-hydroxybenzoate was prepared in an extremely simple and practical way with high enantiomeric excess (99% ee) using Jacobsen’s Hydrolytic Kinetic Resolution technique as a key step and source of chirality.

Convergent covalent organic framework thin sheets as flexible supercapacitor electrodes - Khayum, Abdul M.; Vijayakumar, Vidyanand; Karak, Suvendu; Kandambeth, Sharath; Bhadra, Mohitosh; Suresh, Karthika; Acharambath, Nikhil; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Material & Interfaces, 2018)
Flexible supercapacitors in modern electronic equipment require light-weight electrodes, which have a high surface area, precisely integrated redox moieties, and mechanically strong flexible free-standing nature. However, the incorporation of the aforementioned properties into a single electrode remains a great task. Herein, we could overcome these challenges by a facile and scalable synthesis of the convergent covalent organic framework (COF) free-standing flexible thin sheets through solid-state molecular baking strategy. Here, redox-active anthraquinone (Dq) and pi-electron-rich anthracene (Da) are judiciously selected as two different linkers in a beta-ketoenamine-linked two-dimensional (2D) COF. As a result of precisely integrated anthraquinone moieties, COF thin sheet exhibits redox activity. Meanwhile, pi-electron-rich anthracene linker assists to improve the mechanical property of the free-standing thin sheet through the enhancement of noncovalent interaction between crystallites. This binder-free strategy offers the togetherness of crystallinity and flexibility in 2D COF thin sheets. Also, the synthesized porous crystalline convergent COF thin sheets are benefited with crack-free uniform surface and light-weight nature. Further, to demonstrate the practical utility of the material as an electrode in energy-storage systems, we fabricated a solid-state symmetrical flexible COF supercapacitor device using a GRAFOIL peeled carbon tape as the current collector.

Copper- and phosphine-free nickel(II)-catalyzed method for C-H bond alkynylation of benzothiazoles and related azoles - Patel, Ulhas N.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2018)
A phosphine-free nickel(II)-catalyzed method for the C(2)-H bond alkynylation of (benzo)thiazoles, (benz)imidazoles, and oxazoles is described. Well-defined and air-stable (Phen)NiCl2 catalyst efficiently catalyzes the coupling of diverse azoles with alkynyl bromides without the use of a copper co-catalyst, and the method tolerates synthetically important functional groups. Preliminary mechanistic studies on this Ni-II-catalyzed alkynylation emphasize the homogeneous nature of the catalyst, and rule out a radical manifold for the reaction. The synthetic utility of this Ni-catalyzed method is demonstrated by further functionalizing the alkynylated benzothiazoles to 3-methyl-2-(alkynyl)benzo[d]thiazolium salts that are known DNA cleaving agents.
Keywords: alkynylation; azoles; C-H activation; heterocycles; Nickel

Correlation of intermolecular acyl transfer reactivity with noncovalent lattice interactions in molecular crystals: toward prediction of reactivity of organic molecules in the solid state - Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Journal of Organic Chemistry, 2018)
Intermolecular acyl transfer reactivity in several molecular Acyl transfer reactivity can be predicted in solution based crystals was studied, and the outcome of the reactivity was analyzed in the light of structural information obtained from the crystals of the reactants. in solid state Minor changes in the molecular structure resulted in significant variations in the noncovalent interactions and packing of molecules in the crystal lattice, which drastically affected the facility of the intermolecular acyl transfer reactivity in these crystals. Analysis of the reactivity vs crystal structure data revealed dependence of the reactivity on electrophile ... nucleophile interactions and C-H center dot center dot center dot pi interactions between the reacting molecules. The presence of these noncovalent interactions augmented the acyl transfer reactivity, while their absence hindered the reactivity of the molecules in the crystal. The validity of these correlations allows the prediction of intermolecular acyl transfer reactivity in crystals and co-crystals of unknown reactivity. This crystal structure-reactivity correlation parallels the molecular structure-reactivity correlation in solution-state reactions, widely accepted as organic functional group transformations, and sets the stage for the development of a similar approach for reactions in the solid state.

Correlation trends in the magnetic hyperfine structure of atoms: a relativistic coupled-cluster case study - Talukdar, Kaushik; Sasmal, Sudip; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2018)
The role of electron correlation in the hyperfine structure of alkali metals and alkaline earth metal monopositive ions in their ground electronic configuration is investigated using the Z-vector method in a relativistic coupled-cluster regime within the singles and doubles approximation. The systematic effects of core-correlating functions, polarization of core electrons, and high-lying virtual functions on core electrons correlation are studied. The study reveals that the core-correlating function plays a significant role in core polarization and thus is very important for precise calculation of the wave function near the nuclear region. The inner-core electrons (1s-2p) require very high virtual energy functions for proper correlation. Therefore, the all-electron correlation treatment and the inclusion of higher-energy virtual functions are the key factors for precise calculation of the hyperfine structure constant of atoms. Our calculated values are in excellent agreement with the available experimental values, which also implies that the wave function produced by the Z-vector method is accurate enough for further calculation of the parity- and time-reversal symmetry-violating properties in atoms and molecules.

Covalent organic frameworks: chemistry beyond the structure - Kandambeth, S.; Dey, K.; Banerjee, R. (Journal of the American Chemical Society, 2018)
Covalent organic frameworks (COFs) represent a new field of rapidly growing chemical research that takes direct inspiration from diverse covalent bonds existing between atoms. The success of linking atoms in two and three dimensions to construct extended framework structures moved the chemistry of COFs beyond the structures to methodologies, highlighting the possibility of prospective applications. Although structure to property relation in COFs has led to fascinating properties, chemical stability, processability and scalability were some of the important challenges that needed to be overcome for their successful implementation. In this Perspective, we take a closer look at the growth of COFs from mere supramolecular structures to potential industrializable materials.

CRC handbook of terpenoids: triterpenoids volume I: acyclic, monocyclic, bicyclic, tricyclic, and tetracyclic terpenoids - Dev, S.; Nagasampagi, B.A. (CRC Press, Inc., 2018)
This Handbook, pinpoints salient features of known information about Terpenoids in a readily accessible and readable format. Terpenoids have singularly enriched organic chemistry by its variety of structural types, by its wealth of“unexpected” reactions, rearrangements and spectral features, and by offering exciting targets for synthesis. Much imaginative experimental work has been invested in exploring their natural pathways. Recent years have revealed an increasingly important biological and ecological role for several of its members.

CRC handbook of terpenoids: triterpenoids: Volume ii: pentacyclic and hexacyclic triterpenoids - Dev, S.; Gupta, A.S. (CRC Press, 2018)
A compilation of all the known information on terpenoids specifically triterpenoids, is presented in these volumes. The most important available information on a particular compound is discussed, such as its isolation/occurence, available spectral data, and leading references on structural determination. Additionally, triterpenoids synthesis, biosynthesis, proven pharmacological properties, and any known applications are explained. A comprehensive general introduction has been included which surveys the development of triterpenoid chemistry from the beginning to the present. Extremely helpful is the selected list of references to books and reviews dealing with various aspects of triterpenoid chemistry

Cross-metathesis of biorenewable dioxalates and diols to film-forming degradable polyoxalates - Rajput, Bhausaheb S.; Ram, Farsa; Menon, Shamal K.; Shanmuganathan, Kadhiravan; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Starting from commonly available sugar derivatives, a single step protocol to access a small family of isohexide-dioxalates (2a-c) has been established. The synthetic competence of 2a-c has been demonstrated by subjecting them to condensation polymerization. Quite surprisingly, the proton NMR of poly(isomannide-co-hexane)oxalate revealed a 1:2 ratio between isomannide-dioxalate (2a) and 1,6-hexanediol (3a) in the polymer backbone. This intriguing reactivity was found to be an outcome of a cross metathesis reaction between 2a and 3a. The cross metathesis products 3a[2-(2-methoxyacetoxy)ethyl 2-(2-hydroxyethoxy)-2-(3-oxydanylidene)acetate] and 2a(3R,6R)-6-hydroxyhexahydrofuro[3,2-b]-furan-3-yl methyl oxalate were isolated in a control experiment. Based on direct and indirect evidence, and control experiments, an alternative polymerization mechanism is proposed. Polymerization conditions were optimized to obtain polyoxalates P1(2a-3a)-P9(2c-3c) with molecular weights in the range of 14,000-68,000 g/mol, and narrow polydispersities. The identity of the polyoxalates was unambiguously established using 1-2D NMR spectroscopy, MALDI-ToF-MS, and GPC measurements. The practical implication of these polymers is demonstrated by preparing transparent, mechanically robust films. The environmental footprint of the selected polyoxalates was investigated by subjecting them to solution and solid-state degradation. The polyoxalates were found to be amenable to degradation. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1584-1592

CSGID solves structures and identifies phenotypes for five enzymes in toxoplasma gondii - Lykins, Joseph D.; Filippova, Ekaterina V; Halavaty, Andrei S.; Minasov, George; Zhou, Ying; Dubrovska, Ievgeniia; Flores, Kristin J.; Shuvalova, Ludmilla A.; Ruan, Jiapeng; El Bissati, Kamal; Dovgin, Sarah; Roberts, Craig W.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Toxoplasma gondii, an Apicomplexan parasite, causes significant morbidity and mortality, including severe disease in immunocompromised hosts and devastating congenital disease, with no effective treatment for the bradyzoite stage. To address this, we used the Tropical Disease Research database, crystallography, molecular modeling, and antisense to identify and characterize a range of potential therapeutic targets for toxoplasmosis. Phosphoglycerate mutase II (PGMII), nucleoside diphosphate kinase (NDK), ribulose phosphate 3-epimerase (RPE), ribose-5-phosphate isomerase (RPI), and ornithine aminotransferase (OAT) were structurally characterized. Crystallography revealed insights into the overall structure, protein oligomeric states and molecular details of active sites important for ligand recognition. Literature and molecular modeling suggested potential inhibitors and druggability. The targets were further studied with vivoPMO to interrupt enzyme synthesis, identifying the targets as potentially important to parasitic replication and, therefore, of therapeutic interest. Targeted vivoPMO resulted in statistically significant perturbation of parasite replication without concomitant host cell toxicity, consistent with a previous CRISPR/Cas9 screen showing PGM, RPE, and RPI contribute to parasite fitness. PGM, RPE, and RPI have the greatest promise for affecting replication in tachyzoites. These targets are shared between other medically important parasites and may have wider therapeutic potential.

CuOx-TiO2 composites: electronically integrated nanocomposites for solar hydrogen generation - Bharad, Pradnya A.; Nikam, Arun, V.; Thomas, Femi; Gopinath, Chinnakonda S. (ChemistrySelect, 2018)
CuOx-TiO2 (CT) composites were prepared by different methods (impregnation, microwave and photodeposition methods) and evaluated for solar water splitting (SWS) with aqueous methanol. CT composites prepared by three different methods were characterized by relevant methods to understand the correlation between synthesis method and activity, and the mechanism of water splitting. A comparison of photocatalytic activity of CT composite materials indicates that the photocatalyst prepared by photodeposition method shows significantly improved activity for hydrogen production from aqueous methanol as well as with water (overall water splitting) under one sun conditions. Cu is present in Cu/Cu+1 form in photodeposition method prepared CT, which is more effective and helpful for solar light absorption as well as charge carrier separation due to the formation of bulk p-n (Cu2O-TiO2) heterojunctions. However, CuO formation seems to decrease the activity with other preparation methods.

Curcumin: pharmaceutical solids as a platform to improve solubility and bioavailability - Suresh, Kuthuru; Nangia, Ashwini (Crystengcomm, 2018)
Curcumin (CUR) is the prime curcuminoid in the Indian dietary spice turmeric, Curcuma longa, a plant of the Zingiberaceae family. CUR has promising and diverse therapeutic benefits, such as antioxidant, anti-inflammatory, antitumor, anti-hyperglycemic, antimalarial, antibacterial, and antiviral activity, including anti-Alzheimer's disease. However, CUR is yet to reach the status of a therapeutic drug candidate mainly because a standard solid dosage of curcumin suffers from poor oral bioavailability (0.05 g mL(-1), less than 1%). The reasons behind its low bioavailability include poor solubility (<8 g mL(-1) in water), low permeability and absorption, and rapid metabolism (short elimination half-life of <2 h). A successful CUR therapy requires an appropriate formulation system that will enhance the bioavailability and offer greater therapeutic efficacy. This review covers a comprehensive description of the CUR pharmaceutical solids, such as polymorphs, cocrystals, eutectics, and coamorphous solid-state forms with aim to determine ways to improve its physicochemical properties, including dissolution rate, solubility, physicochemical stability, mechanical strength, compressibility for tablet formation, and oral bioavailability. The cumulative publications in the past decade have forecast a bright future for development of an oral drug formulation of curcumin.

Curcumin-artemisinin coamorphous solid: Xenograft model preclinical study - Mannava, M. K. Chaitanya; Suresh, Kuthuru; Bommaka, Manish Kumar; Konga, Durga Bhavani; Nangia, Ashwini (Pharmaceutics, 2018)
Curcumin is a natural compound present in Indian spice turmeric. It has diverse pharmacological action but low oral solubility and bioavailability continue to limit its use as a drug. With the aim of improving the bioavailability of Curcumin (CUR), we evaluated Curcumin-Pyrogallol (CUR-PYR) cocrystal and Curcumin-Artemisinin (CUR-ART) coamorphous solid. Both of these solid forms exhibited superior dissolution and pharmacokinetic behavior compared to pure CUR, which is practically insoluble in water. CUR-ART coamorphous solid showed two fold higher bioavailability than CUR-PYR cocrystal (at 200 mg/kg oral dose). Moreover, in simulated gastric and intestinal fluids (SGF and SIF), CUR-ART is stable up to 3 and 12 h, respectively. In addition, CUR-PYR and CUR-ART showed no adverse effects in toxicology studies (10 times higher dose at 2000 mg/kg). CUR-ART showed higher therapeutic effect and inhibited approximately 62% of tumor growth at 100 mg/kg oral dosage of CUR in xenograft models, which is equal to the positive control drug, doxorubicin (2 mg/kg) by i.v. administration.

Cyclohexylation of resorcinol with cyclohexanol catalyzed by tungstophosphoric acid supported zirconia catalysts - Balasubramanian, V. V.; Devassay, B. M.; Halligudi, S. B.; Deepika, R.; Umbarakar, S. B.; Vinu, A. (Journal of Nanoscience and Nanotechnology, 2018)
We demonstrate a highly active and reusable heterogeneous catalyst system, tungstophosphoric acid (TPA) supported on zirconia (ZrO2), for the cyclohexylation of resorcinol by cyclohexanol to produce value added chemicals such as 2-cyclohexyl resorcinol, 4-cyclohexyl resorcinol and 3-Hydroxy cyclohexyl phenyl ether under liquid phase reaction condition. TPA/ZrO2 catalysts prepared with different TPA loadings (5-30 wt.%) by wet impregnation method and calcined in the temperature range of 650-850 degrees C were characterized by Nitrogen sorption analysis, XRD, FTIR, DTG and DTA, and P-31 MAS NMR spectroscopy. Among the catalysts studied, 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C gave the highest conversion of resorcinol (51.2%) with the selectivities for 3-Hydroxy cyclohexyl phenyl ether (53.9%) and 2-cyclohexyl resorcinol and 4-cyclohexyl resorcinol together (46.1%) under optimum reaction conditions. However, the selectivity of the products were controlled by varying the reaction conditions. At higher conversion of resorcinol (78.9%), only C-alkylated products were formed at 200 degrees C with 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C. The combination of TPA and ZrO2 coupled with calcination temperature offered an excellent platform for the conversion of resorcinol into O- or C-alkylated products.
Keywords: 15% TPA/ZrO2; Cyclohexanol; Cyclohexylation; Keggin TPA; Resorcinol

Cyclometallation of a germylene ligand by concerted metalation-deprotonation of a methyl group - Bakthavachalam, K.; Dutta, Sayan; Arivazhagan, C.; Raghavendra, Beesam; Haridas, Anagha; Sen, Sakya S.; Koley, Debasis; Ghosh, Sundargopal (Dalton Transactions, 2018)
The reaction of [CH{(CMe)(2,6-iPr(2)C(6)H(3)N)}(2)]GeCl with LiN(SiMe3)(2) was previously reported, which led to the formation of a hetero-fulvene type germylene, [CH{(CMe)(C?CH2)(2,6-iPr(2)C(6)H(3)N)}(2)]Ge through the deprotonation of the C-H bond from the methyl substituents. In this paper, we attempted the analogous reaction with (Dipp)NCMeCHCOMeGeCl using LiN(SiMe3)(2) which gave rise to a metathesis product, (Dipp)NCMeCHCOMeGeN(SiMe3)(2) (2). However, the reactions of 2 with [M2Cl2(-Cl)(2)((5)-Cp*)(2)] (M = Rh and Ir) resulted in cyclometallated Rh and Ir complexes through the activation of the C-H bond from the germylene ligand. The complexes were characterized by single crystal X-ray analysis, which authenticated the presence of Ge-Rh and Ge-Ir bonds. DFT studies have been performed to understand the mechanism.

Cadmium sulfide nanostructures: influence of morphology on the photocatalytic degradation of erioglaucine and hydrogen generation - Shenoy, Sulakshana; Jang, Eunyong; Park, Tae Joo; Gopinath, Chinnakonda S.; Sridharan, Kishore (Applied Surface Science, 2019)
Size and shape of inorganic materials are known to have great effects on their physical and chemical properties. Here, for the first time we report the visible light driven photocatalytic degradation of erioglaucine - a stable organic dye molecule in the presence of chemically synthesized nanoscale CdS with 1D (nanorods), 2D (nanosheets) and 3D (hierarchical) morphology. Visible light driven photocatalytic degradation efficiency of both 1D and 3D CdS in the removal of erioglaucine are identical. Surprisingly, with 5 min of sonication, the highly crystalline 3D CdS stacked with many thin nanowires containing numerous active surface sites exhibited fourfold enhanced photodegradation efficiency in comparison to 1D and 2D CdS. Scavenger studies revealed that electrons and superoxide radicals are primary reactive species involved in the photodegradation of erioglaucine, while cyclic photodegradation studies revealed the good stability of 3D CdS against photocorrosion. Further, the photocatalytic hydrogen evolution studies also revealed the excellent activity of 3D CdS in comparison to 1D and 2D CdS. Thus, we find that the morphology indeed influences the photocatalytic activity. These results reveal that 3D CdS nanostructures investigated in the present work are efficient photocatalysts that could be fine-tuned for both environmental remediation and hydrogen generation applications.
Keywords: Cadmium sulfide; Erioglaucine; Hydrogen evolution; Nanostructures; Photocatalysis

Can the solvent enhance the rate of chemical reactions through C-H/pi interactions? insights from theory - Jain, Shailja; Vanka, Kumar (Physical Chemistry Chemical Physics, 2019)
The current computational study with density functional theory (DFT) shows that the rate of chemical reactions can be influenced through non-covalent C-H/p interactions between substrates and the solvent. It is shown that intramolecular carbon-carbon interaction and CO2 activation by a low valent silicon complex are both favourably affected by the explicit presence of the solvent toluene, due to C-H/p interactions between toluene and the silicon complex. Furthermore, ab initio molecular dynamics (AIMD) simulations demonstrate that even if the C-H/p interacting solvent molecule is displaced from the complex, another would quickly take its place, thus maintaining the interaction. Hence, the current work shows how non-covalent interactions between solvent and substrate can enhance the rate of the reaction and expands our understanding of the role and influence of the solvent in effecting important chemical transformations.

Carbon derived from soft pyrolysis of a covalent organic framework as a support for small-sized RuO2 showing exceptionally low overpotential for oxygen evolution reaction - Chakraborty, Debanjan; Nandi, Shyamapada; Illathvalappil, Rajith; Mullangi, Dinesh; Maity, Rahul; Singh, Santosh K.; Haldar, Sattwick; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (ACS Omega, 2019)
Electrochemical water splitting is the most energy-efficient technique for producing hydrogen and oxygen, the two valuable gases. However, it is limited by the slow kinetics of the anodic oxygen evolution reaction (OER), which can be improved using catalysts. Covalent organic framework (COF)-derived porous carbon can serve as an excellent catalyst support. Here, we report high electrocatalytic activity of two composites, formed by supporting RuO2 on carbon derived from two COFs with closely related structures. These composites catalyze oxygen evolution from alkaline media with overpotentials as low as 210 and 217 mV at 10 mA/cm(2), respectively. The Tafel slopes of these catalysts (65 and 67 mV/dec) indicate fast kinetics compared to commercial RuO2. The observed activity is the highest among all RuO2-based heterogeneous OER catalysts-a touted benchmark OER catalyst. The high catalytic activity arises from the extremely small-sized (similar to 3-4 nm) RuO2 nanoparticles homogeneously dispersed in a micro-mesoporous (BET = 517 m(2)/g) COF-derived carbon. The porous graphenic carbon favors mass transfer, while its N-rich framework anchors the catalytic nanoparticles, making it highly stable and recyclable. Crucially, the soft pyrolysis of the COF enables the formation of porous carbon and simultaneous growth of small RuO2 particles without aggregation.

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping (vol 53, pg 7072, 2017) - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Correction for `Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping' by Goudappagouda et al., Chem. Commun., 2017, 53, 7072-7075.

Catalytic hydrogenation products of aromatic and aliphatic dicarboxylic acids - Shinde, Sunil; Deshpande, Raj M. (Asian Journal of Chemistry, 2019)
Hydrogenation of aromatic dicarboxylic acids gave 100 % selectivity to respective cyclohexane dicarboxylic acid with 5 % Pd/C catalyst. 5 % Ru/C catalyst was observed to give over hydrogenation products at 493 K and at lower temperature (453 K) the selectivity for cyclohexane dicarboxylic acids was increased. Hydrogenation of phthalic acid with Ru-Sn/Al2O3 catalyst was observed to give phthalide instead of 1,2-benzene dimethanol or 2-hydroxy methyl benzoic acid. Ru-Sn/Al2O3 catalyst selectively hydrogenated the carboxylic group of cyclohexane dicarboxylic acids to give cyclohexane dimethanol. Use of proper catalysts and reaction conditions resulted in desired products.

CFD modelling of almond drying in a tray dryer - Chilka, Amarvir G.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
Drying is important in many food processing applications, and particularly so in the dry fruits industry. This work is focused on developing computational models for simulating the drying of almonds in a tray dryer. It is important to quantitatively understand heat and mass transfer within and around a single almond particle as well as the particle-particle interactions and their implications for dryer design. In this work, we have developed a systematic CFD modelling framework for modelling almond drying in a tray dryer. A single tray filled with almonds (similar to 2 kg) were dried at three set temperatures viz., 55, 65, and 75 degrees C. Air relative humidity at the inlet and outlet locations, and the weight of almonds were measured during drying for each experiment. An additional set of experiments were conducted in which almonds were filled only in the half section of the tray, keeping the other half empty. The same amount of almonds were used, to have multiple layers of almonds in the tray, and the set temperature for the experiment was 75 degrees C. Flow, heat, and mass transfer in the tray dryer were simulated using commercial CFD software Ansys Fluent. The validated computational model was used to simulate various cases including larger and more trays. The developed approach and models will be useful to select the appropriate dryer configuration and optimize its design. The developed models will also be useful to identify suitable operation conditions for the drying of almonds as well as other food products.
Keywords: Almonds; CFD; Drying; scale-up; tray dryer

C-H functionalization of indoles by 3d transition-metal catalysis - Jagtap, Rahul A.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2019)
Over the past decade, the use of 3d transition metal for the regioselective C-H bond functionalization of indoles has significantly increased. Particularly, advances in manganese, iron, cobalt, nickel and copper catalysis have demonstrated the selective C(2)-H and C(3)-H arylation, alkenylation, alkynylation and alkylation to a greater extent. Similarly, the C-O and C-N bond-forming reactions are manifested via direct C-H bond activation by these earth-abundant metals. The emergence of 3d metals in selective functionalization of the biologically relevant indoles and related heteroarenes would make this protocol more attractive for practical applications. Herein, we provide a brief overview of 3d transition metal-catalyzed (mostly Mn, Fe, Co, Ni and Cu) C-H functionalization of indoles and related heteroarenes.
Keywords: 3d transition metal; C-H functionalization; Indole; indoline

Characterization of novel acidic and thermostable phytase secreting Streptomyces sp. (NCIM 5533) for plant growth promoting characteristics - Puppala, K. R.; Bhavsar, K.; Sonalkar, V.; Khire, J. M.; Dharne, M. S. (Biocatalysis and Agricultural Biotechnology, 2019)
Successful agricultural practices in acidic and arid region soils are still challenging worldwide. We investigated Actinomycete strain obtained from soil, which was found to produce extracellular phytase having the optimum pH, temperature of 2.5 and 70 °C, respectively and Plant growth promoting (PGP) attributes. These abilities of the phytase make it novel as compared to other Streptomyces derived phytases. Strain was also evaluated for physiological traits such as salinity, temperature, and pH followed by morphological and molecular identification. The Streptomyces sp. strain (NCIM 5533) displayed additional PGP traits such as indole-3-acetic acid (IAA), ammonia and phosphate solubilization activity. A significant increment in Tomato plant (Solanum lycopersicum) root, shoot and as well as total height in bioassays at laboratory scale and green house level and its ability to colonize roots substantiated its potency as a true plant growth promoting rhizobacteria (PGPR). To our knowledge this is the first report of Streptomyces sp. having the ability to produce acidic and thermostable phytase as well as PGP traits showing enhanced plant growth could have implications in soils having acidic nature and also in arid region.

Characterizing microvoids in regenerated cellulose fibers obtained from viscose and lyocell processes - Sharma, Aakash; Sen, Debasis; Thakre, Shirish; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Regenerated cellulose fibers are among the most widely used bio-derived materials. Currently, there is great interest in transitioning from the traditional viscose process to the more environmentally friendly lyocell process for fiber production. Differences between the characteristics of viscose and lyocell fibers can be attributed to microstructural differences that arise due to differences in the processing techniques. Here, we use small-angle scattering to characterize the microvoids in regenerated cellulose fibers that might govern the onset of mechanical failure in these. In regenerated cellulose fibers, scattering of X-rays or neutrons at small angles is largely dominated by scattering from microvoids. We demonstrate that small angle X-ray scattering (SAXS) over the q range that is typical for most commercial instruments arises from Porod scattering from the microvoid surfaces, viz., the scattered intensity scales as q(-4). Therefore, it is not possible to extrapolate this data to lower q to obtain microvoid dimensions and volume fraction. We combine SAXS with medium-resolution small-angle neutron scattering to characterize the microvoids in regenerated cellulose fibers. Specifically, we compare fibers produced using the viscose process with those from the lyocell process. For both viscose and lyocell fibers, microvoids have a high aspect ratio and are elongated in the fiber direction. Also, the volume fraction occupied by the microvoids is comparable for viscose and lyocell fibers (0.04-0.05%). However, there are differences in the microvoid size: Microvoids are more highly oriented in lyocell fibers and have a larger average length and diameter compared with viscose fibers. This result might have important implications for understanding failure of these fibers.

Charge transfer liquid: a stable donor-acceptor interaction in the solvent-free liquid state - Wakchaure, Vivek Chandrakant; Pillai, Lekshmi, V; Goudappagouda; Ranjeesh, Kayaramkodath Chandran; Chakrabarty, Suman; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Charge-transfer complexes have been an inspiration to develop many functional soft materials. However, most of those studies have focused on solution based assemblies wherein the explicit control of solvents and their polarity are crucial. In this context, we explore an efficient and stable charge transfer liquid using a solvent-free liquid dialkoxynaphthalene donor and a naphthalenediimide acceptor. It has been observed that irrespective of the donor-acceptor ratio, the charge-transfer liquid exhibited an unprecedented stability and retained characteristic features even at increased temperatures. The underlying intermolecular interactions leading to efficient CT have been examined by NMR techniques together with theoretical modelling studies. The concept of charge transfer liquid will be highly beneficial for the development of processable optoelectronically active materials.

Chiral separation of styrene oxides supported by enantiomeric tetrahedral neutral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Ferrara, Joseph D.; Del Campo, Mark; Le Magueres, Pierre; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2019)
The separation of enantiomers is of considerable importance in the preparation of the compounds of biological interests, catalysis, and drug development. Here, we report a novel enantioseparation of styrene epoxides (SOs) resolved in the presence of a pair of enantio-enriched tetrahedral cages. Chiral neutral cages of formula [(Pd3X*)(4)(C6O4Cl2)(6)] ([X*](3-) = RRR-or SSS-[PO(N(*CH(CH3)Ph)(3)](3)) are constructed from Pcl, building units supported by tris(imido)phosphate trianions and chloranilate linkers. These cages exhibit considerable enantioselective separation capabilities toward a series of styrene epoxides via a crystallization inclusion method. A highest enantiomeric excess (ee) value of up to 80% is achieved for the (R)-4-fluorostyrene oxide.

Clathrin-mediated endocytosis regulates a balance between opposing signals to maintain the pluripotent state of embryonic stem cells - Narayana, V, Yadavalli; Gadgil, Chetan; Mote, Ridim D.; Rajan, Raghav; Subramanyam, Deepa (Stem Cell Reports, 2019)
Endocytosis is implicated in the maintenance of embryonic stem cell (ESC) pluripotency, although its exact role and the identity of molecular players remain poorly understood. Here, we show that the clathrin heavy chain (CLTC), involved in clathrin-mediated endocytosis (CME), is vital for maintaining mouse ESC (mESC) pluripotency. Knockdown of Cltc resulted in a loss of pluripotency accompanied by reduced E-cadherin (E-CAD) levels and increased levels of transforming growth factor beta (TGF-beta) and extracellular signal-regulated kinase (ERK) signaling. We demonstrate that both E-CAD and TGF-beta receptor type 1 (TGF-beta R1) are internalized through CME in mESCs. While E-CAD is recycled, TGF-beta R1 is targeted for lysosomal degradation thus maintaining inverse levels of these molecules. Finally, we show that E-CAD interacts with ERK, and that the decreased pluripotency upon CME loss can be rescued by inhibiting TGF-beta R, MEK, and GSK3 beta, or overexpressing E-CAD. Our results demonstrate that CME is critical for balancing signaling outputs to regulate ESC pluripotency, and possibly cell fate choices in early development.

Click chemistry based multicomponent approach in the synthesis of spirochromenocarbazole tethered 1,2,3-triazoles as potential anticancer agents - Chavan, V, Pramod; Desai, V, Uday; Wadgaonkar, Prakash P.; Tapase, Savita R.; Kodam, Kisan M.; Choudhari, Amit; Sarkar, Dhiman (Bioorganic Chemistry, 2019)
A series of spirochromenocarbazole tethered 1,2,3-triazoles were synthesized via click chemistry based one-pot, five component reaction between N-propargyl isatins, malononitrile, 4-hydroxycarbazole, aralkyl halides and sodium azide using cellulose supported CuI nanoparticles (Cell-CuI NPs) as the heterogeneous catalyst. Antiproliferative activity of all the synthesized compounds was investigated against panel of cancer cell lines such as MCF-7, MDA-MB-231, HeLa, PANG-1, A-549, and THP-1. Many of the synthesized compounds exhibited good anti-proliferative activity against breast (MCF-7 and MDA-MB-231) and cervical (HeLa) cancer cells with IC50 values less than 10 mu M. In case of MCF-7 cells, among the nine compounds that showed good anti-proliferative activity, compounds 6f and 6j were found to be highly potent (IC50 , = 2.13 mu M and 4.80 mu M, respectively). In case of MDA-MB-231, three compounds (6k, 6j and 6s) showed antiproliferative activity amongst which 6k was the most potent one (IC50 = 3.78 mu M). On the other hand, in cervical cancer HeLa cells, compounds 6b, 6g, 6s and 6u showed excellent antiproliferative activity (IC50 = 4.05, 3.54, 3.83, 3.35 mu M, respectively). All the compounds were found to be nontoxic to the human umbilical vein endothelial cells (HUVECs). AO and EtBr staining and fluorescence microscopy studies of the active compounds (IC50 < 5 mu M) suggested that these compounds induce cell death by apoptosis.
Keywords: 1; 2; 3-Triazolylspirochromenocarbazole; Anticancer; Apoptotic assay; Click chemistry; Cytotoxicity; heterogeneous catalysis; Multicomponent synthesis

Clopidogrel eluting electrospun polyurethane/polyethylene glycol thromboresistant, hemocompatible nanofibrous scaffolds - Shitole, Ajinkya A.; Giram, Prabhanjan S.; Raut, Piyush W.; Rade, Priyanka P.; Khandwekar, Anand P.; Sharma, Neeti; Garnaik, Baijayantimala (Journal of Biomaterials Applications, 2019)
Biomaterials used as blood-contacting material must be hemocompatible and exhibit lower thrombotic potential while maintaining hemostasis and angiogenesis. With the aim of developing thromboresistant, hemocompatible nanofibrous scaffolds, polyurethane/polyethylene glycol scaffolds incorporated with 1, 5, and 10 wt% Clopidogrel were fabricated and evaluated for their physiochemical properties, biocompatibility, hemocompatibility, and antithrombotic potential. The results of physicochemical characterization revealed the fabrication of nanometer-sized scaffolds with smooth surfaces. The incorporation of both polyethylene glycol and Clopidogrel to polyurethane enhanced the hydrophilicity and water uptake potential of polyurethane/polyethylene glycol/Clopidogrel scaffolds. The dynamic mechanical analysis revealed the enhancement in mechanical strength of the polyurethane/polyethylene glycol scaffolds on incorporation of Clopidogrel. The polyurethane/polyethylene glycol/Clopidogrel scaffolds showed a tri-phasic drug release pattern. The results of hemocompatibility assessment demonstrated the excellent blood compatibility of the polyurethane/polyethylene glycol/Clopidogrel scaffolds, with the developed scaffolds exhibiting lower hemolysis, increased albumin and plasma protein adsorption while reduction in fibrinogen adsorption. Further, the platelet adhesion was highly suppressed and significant increase in coagulation period was observed for Clopidogrel incorporated scaffolds. The results of cell adhesion and cell viability substantiate the biocompatibility of the developed nanofibrous scaffolds with the HUVEC cell viability on polyurethane/polyethylene glycol, polyurethane/polyethylene glycol/Clopidogrel-1, 5, and 10% at day 7 found to be 12.35, 13.36, 14.85, and 4.18% higher as compared to polyurethane scaffolds, and the NIH/3T3 cell viability found to be 35.27, 70.82, 36.60, and 7.95% higher as compared to polyurethane scaffolds, respectively. Altogether the results of the study advocate the incorporation of Clopidogrel to the polyurethane/polyethylene glycol blend in order to fabricate scaffolds with appropriate antithrombotic property, hemocompatibility, and cell proliferation capacity and thus, might be successfully used as antithrombotic material for biomedical application.
Keywords: adhesion; cardiovascular; coagulation; electrospinning; Hemocompatible; platelet

Co amorphous valsartan nifedipine system: Preparation, characterization, in vitro and in vivo evaluation - Lodagekar, Anurag; Chavan, Rahul B.; Mannava, M. K. Chaitanya; Yadav, Balvant; Chella, Naveen; Nangia, Ashwini K.; Shastri, Nalini R. (European Journal of Pharmaceutical Sciences, 2019)
Co amorphous systems are supersaturated drug delivery systems which offer a basic platform for delivery of multicomponent adducts (combination of more than one active pharmaceutical ingredient (API)) and/or as a fixed dose combination therapy, in addition to their potential to improve the apparent solubility, dissolution rate and ultimately bioavailability of poorly water soluble APIs. In the present work, a new drug-drug co amorphous system namely valsartan-nifedipine was prepared by quench cooling technique. Prepared co amorphous system was characterized for its solid state behavior with the help of Fourier Transform Infrared spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and Powder X Ray Diffractometry (PXRD). The optimized co amorphous system was stable for 1 month when exposed to accelerated stability condition (40 +/- 2 degrees C and 75 +/- 5% RH). The improved stability of amorphous nifedipine in co amorphous system was attributed to improved miscibility and intra and intermolecular non-covalent interactions mainly due to presence of hydrogen bonding between valsartan and nifedipine which was studied by FTIR analysis. Co amorphous systems were evaluated by mainly in vitro dissolution and in vivo benefit. In vitro dissolution study showed nearly 5.66 folds and 1.61 folds improvement which was translated to 3.63 and 2.19 times enhancement in vivo C-max for nifedipine and valsartan respectively.

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity (vol 15, pg 12 - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2019)

Cocrystals, salts, and supramolecular gels of nonsteroidal anti inflammatory drug niflumic acid - Mittapalli, Sudhir; Mannava, M. K. Chaitanya; Sahoo, Rasmita; Nangia, Ashwini (Crystal Growth & Design, 2019)
Niflumic acid (NFA) is a nonsteroidal anti-inflammatory drug (NSAID) classified under the BCS (Biopharmaceutical Classification System) Class II category of poor aqueous solubility and high permeability. In an attempt to improve the physicochemical properties of NFA, particularly solubility and dissolution rate by cocrystallization and salt formation, cocrystals of NFA were prepared with caprolactam (CPR, 1:1) and 2-hydroxy pyridine (2HP, 1:1) as well as salts with piperazine (PIP, 1:0.5), benzenesulfonic acid (BSA, 1:1), benzyl amine (BZA, 1:1 and 2:2), and tyramine (TYA, 1:1). The new solid forms were characterized by powder X-ray diffraction, infrared spectroscopy, and differential scanning calorimetry and confirmed by single crystal X-ray diffraction. In the cocrystals NFA CPR and NFA-2HP, the cyclic amide of the coformer forms a dimer synthon through N-H center dot center dot center dot O hydrogen bonds and such dimers extend through O-H center dot center dot center dot O hydrogen bonds. In piperazine, benzyl amine, and tyramine salts, proton transfer occurs from the NFA to the basic nitrogen of the coformer, and in NFA BSA salt, the proton is transferred from benzenesulfonic acid to the pyridine nitrogen of NFA. In addition to the above salts and cocrystals, supramolecular gels of NFA-PIP and NFA-BZA salts are reported, which were obtained from nitrobenzene, methyl salicylate, menthol, and mesitylene solvents. These gels were studied by rheology. Solubility and dissolution rate of the novel solid forms (NFA CPR, NFA PIP, NFA BSA, and NFA TYA) in 20% EtOH water showed the best behavior for NFA-TYA salt with improvement of 42-and 54-times in solubility and dissolution rate compared to the reference drug. The remaining solids such as NFA-PIP, NFA-BSA salts, and NFA-CPR cocrystal exhibited improvement of 39-, 18-, 1.4-times in solubility and 7.8-, 10-, 2-times for dissolution rate.

Cold thermal response of an amyloid oligomer differs from typical globular protein cold denaturation - Menon, Sneha; Sengupta, Neelanjana (Journal of Physical Chemistry Letters, 2019)
In contrast with the general behavior of folded proteins, the cold thermal response of amyloid assemblies is difficult to elicit with simple models. We exploit exhaustive simulations to evaluate the thermal response of a barrel-shaped model amyloid oligomer, with a distinct hydrophobic core akin to that of folded proteins. Cumulative thermal data over the range of 210-483 K indicate a sharp inflection and rise in structural stability as the temperature is decreased below the melting temperature of the water model. This is not commensurate with the equilibrium free energy profile obtained with core packing as the order parameter. However, energetic analyses and the size of their fluctuations indicate the crucial role of hydration in mediating structural transitions, beyond the expected temperature-dependent hydrophobic effect. Structural ordering of the hydration layer over bulk water is maximized at the transition and vanishes at high temperatures. This is a first direct demonstration of the microscopic influence of hydration water on the low-temperature response of an amyloid assembly close to the cryo-regime.

Comparative study of a class of mean field theories of the glass transition - Saha, Indranil; Nandi, Manoj Kumar; Dasgupta, Chandan; Bhattacharyya, Sarika Maitra (Journal of Statistical Mechanics-Theory and Experiment, 2019)
In a recently developed microscopic mean field theory, we have shown that the dynamics of a system, when described only in terms of its pair structure, can predict the correct dynamical transition temperature. Further, the theory predicted the difference in dynamics of two systems (the Lennard-Jones and the Weeks-Chandler-Andersen) despite them having quite similar structures. This is in contrast to the Schweizer-Saltzman (SS) formalism which predicted the dynamics of these two systems to be similar. The two theories although similar in spirit have certain differences. Here we present a comparative study of these two formalism to find the origin of the difference in their predictive power. We show that not only the dynamics in the potential energy surface, as described by our earlier study, but also that in the free energy surface, like in the SS theory, can predict the correct dynamical transition temperature. Even an approximate one component version of our theory, similar to the system used in the SS theory, can predict the transition temperature reasonably well. Interestingly, we show here that despite the above mentioned shortcomings the SS theory can actually predict the correct transition temperatures. Thus microscopic mean field theories of this class which express dynamics in terms of the pair structure of the liquid while being unable to predict the actual dynamics of the system are successful in predicting the correct dynamical transition temperature.
Keywords: aging; etc); glasses (colloidal; glassy dynamics; mode coupling theory; Polymer; slow relaxation

Comparative study of anomalous size dependence of charged and neutral solute diffusion in water - Acharya, Sayantan; Nandi, Ujjwal K.; Bhattacharyya, Sarika Maitra (Journal of Physical Chemistry B, 2019)
We present a comparative study of size dependence of diffusion for charged and neutral solutes in water. Although both show nonmonotonicity of the size dependence of diffusion, their nature and origin are quite different. For neutral solutes, the peak position and the value of diffusion at the maximum are both independent of the solute water interaction. Interestingly, for charged solutes, with an increase in solute water interaction strength, the peak position shifts to lower solute sizes and with an increase in charge, it shifts to higher solute sizes. The diffusion value at the peak reduces with an increase in both solute water interaction and solute charge. We show that all these features observed for charged solutes can be understood in terms of the interplay between ionic and nonionic interactions which is definitely absent for neutral solutes. Some of the earlier studies addressing the nonmonotonicity in diffusion did suggest the interplay between the two interactions to be the cause. However, this is the first time we show that such an interplay gives rise to the nonmonotonicity in the potential energy which is a prerequisite for obtaining the nonmonotonicity in the diffusion. Such nonmonotonicity in the potential energy is absent for neutral solutes.

Comparison of different water models for melting point calculation of methane hydrate using molecular dynamics simulations - Choudhary, Nilesh; Chakrabarty, Suman; Roy, Sudip; Kumar, Rajnish (Chemical Physics, 2019)
Molecular dynamics simulation is a powerful tool to understand the gas hydrate nucleation, growth, and dissociation at molecular level. Prerequisite of super-cooling during gas hydrate formation and a certain degree of super-healing during melting shows significant hysteresis in the transition between solid and liquid state due to large nucleation barrier. Different water models quantitatively differ in their prediction of thermodynamic and kinetic properties of bulk water, including phase behaviour. The present work carries out a systematic investigation of the effect of the chosen water model on the phase behaviour, in particular, the decomposition of methane hydrate. Void-induced melting has been used to predict the melting point of methane hydrate using TIP4P/Ice, TIP4P/2005, TIP4P, and SPC/E water models. This method avoids the need for a predetermined interface for melting point calculations and thus may have its importance in identifying dissociation kinetics of bulk hydrate.
Keywords: decomposition; Gas hydrates; Void-induced melting; Water models

Comprehensive analytical model for polarization curve of a PEM fuel cell and experimental validation - Thosar, Aniket U.; Agarwal, Harshal; Govarthan, S.; Lele, Ashish K. (Chemical Engineering Science, 2019)
The kinetics of cathodic oxygen reduction reaction (ORR) in a proton exchange membrane fuel cell (PEMFC) is significantly modulated by the resistances for transport of reactants to the catalytic sites offered by different components of the fuel cell. This modulation governs the polarization curve of the PEMFC. Consequently, the various operating, geometric and material parameters of the fuel cell dictate the polarization curve. The effects of these parameters on the polarization curve over the entire range of current density, from zero to limiting current, can be predicted using detailed numerical simulations, which are however expensive. Analytical models, although simple can capture the essential details of physico-chemical processes occurring inside a PEMFC and are significantly inexpensive. In this article, we derive an analytical equation of the polarization curve which is valid over the entire range of current density. Specifically, the representative situation of a humidified low temperature PEMFC is considered wherein oxygen transport resistance in the cathode catalyst layer (CCL) is encountered at lower current density than proton transport resistance in the CCL. A novel experimental methodology is illustrated to confirm that this is indeed the case. Next, we elucidate a procedure to determine in-situ oxygen diffusion coefficients in the various domains of an operational PEMFC. Finally, it is shown that the analytical polarization curve predicted using these parameters is in excellent agreement with the experimental and numerically simulated polarization curves over the entire range of current density. The significance of this work is that the analytical model relates the performance of a PEMFC to all operating and geometric parameters as well as the average transport and kinetic properties of the materials used in its different components, without the need for computationally expensive numerical simulations. The model can therefore provide useful insights for enhancing the performance of PEMFC in different regimes of current density as well as for diagnostic purposes. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Fuel cell equation; Modelling; PEMFC; Polarization curve

Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule (vol 54, pg 212, 2018) - Shivakumar, Kilingaru I.; Goudappagouda; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2019)
Correction for `Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule' by Kilingaru I. Shivakumar et al., Chem. Commun., 2018, 54, 212-215.

Constraints-based analysis identifies NAD(+) recycling through metabolic reprogramming in antibiotic resistant Chromobacterium violaceum - Banerjee, Deepanwita; Raghunathan, Anu (PLoS One, 2019)
In the post genomic era, high throughput data augment stoichiometric flux balance models to compute accurate metabolic flux states, growth and energy phenotypes. Investigating altered metabolism in the context of evolved resistant genotypes potentially provide simple strategies to overcome drug resistance and induce susceptibility to existing antibiotics. A genome-scale metabolic model (GSMM) for Chromobacterium violaceum, an opportunistic human pathogen, was reconstructed using legacy data. Experimental constraints were used to represent antibiotic susceptible and resistant populations. Model predictions were validated using growth and respiration data successfully. Differential flux distribution and metabolic reprogramming were identified as a response to antibiotics, chloramphenicol and streptomycin. Streptomycin resistant populations (StrpR) redirected tricarboxylic acid (TCA) cycle flux through the glyoxylate shunt. Chloramphenicol resistant populations (ChlR) resorted to overflow metabolism producing acetate and formate. This switch to fermentative metabolism is potentially through excess reducing equivalents and increased NADH/NAD ratios. Reduced proton gradients and changed Proton Motive Force (PMF) induced by antibiotics were also predicted and verified experimentally using flow cytometry based membrane potential measurements. Pareto analysis of NADH and ATP maintenance showed the decoupling of electron transfer and ATP synthesis in StrpR. Redox homeostasis and NAD(+) cycling through rewiring metabolic flux was implicated in re-sensitizing antibiotic resistant C. violaceum. These approaches can be used to probe metabolic vulnerabilities of resistant pathogens. On the verge of a post-antibiotic era, we foresee a critical need for systems level understanding of pathogens and host interaction to extend shelf life of antibiotics and strategize novel therapies.

Continuous flow solvent free organic synthesis involving solids (reactants/products) using a screw reactor - Sharma, Brijesh M.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Green Chemistry, 2019)
Here we report for the first-time various organic transformations such as aldol condensation, oxidation, nucleophilic substitutions, protection, acylations and coupling reactions using a mechanochemical approach at a controlled temperature using a single synthesis platform. Almost minimal solvents or solvent-free conditions are used, making it a very efficient and clean synthesis of various products. A jacketed screw reactor when operated at different temperatures (0 degrees C to 160 degrees C) and over a range of rotation speeds for changing the residence time (15 s-300 s) helped to achieve maximum conversion. This approach is also extended to the synthesis using substrates having different substitutions, heterocycles and steric hindrance.

Conversion of curved assemblies into two dimensional sheets - Deshmukh, Gunvant; Krishnamoorthy, Kothandam (Nanoscale, 2019)
The design and preparation of organic two dimensional (O2D) sheets and their conversion to curved nanostructures is in its infancy. To convert a flat structure into a curved structure, the molecule must have multiple interaction possibilities and an in-built twist. The conjugated small molecule iso-Indigo (i-Indigo) comprises two phenyl rings that are twisted (the dihedral angle is 15 degrees) at the junction. The i-Indigo has been connected with moieties that impart hydrogen bonding and van der Waals interactions. Due to the presence of the cloud in i-Indigo, - interactions are also present in the molecule. While all three interactions are in operation, rings and toroids are formed. Upon addition of hydrogen bonding competing solvents, the rings and toroids unravel to form O2D sheets. Control molecules that don't have hydrogen bonding moieties and - interactions form random assemblies. Please note that the rings, toroids and O2D sheets are formed in a single solvent by simple dissolution, unlike previous approaches that involve multiple steps and solvents.

A copper(ii)-coordination polymer based on a sulfonic-carboxylic ligand exhibits high water-facilitated proton conductivity - Tayade, Sakharam B.; Illathvalappil, Rajith; Lapalikar, Vaidehi; Markad, Datta; Kurungot, Sreekumar; Pujari, Bhatchandra; Kumbhar, Avinash S. (Dalton Transactions, 2019)
Proton conduction ability has been investigated in a new Cu(ii) based coordination polymer (CP), {[Cu-2(sba)(2)(bpg)(2)(H2O)(3)]center dot 5H(2)O}(n) (1), synthesized using the combination of 4-sulfobenzoic acid (4-Hsba) and bipyridine-glycoluril (BPG) ligands. Single crystal X-ray structure determination revealed that 1 features 1D porous channels encapsulating a continuous array of water molecules. Proton conductivity measurements reveal a high conductivity value of 0.94 x 10(-2) S cm(-1) at 80 degrees C and 95% RH. The activation energy (E-a) of 0.64 eV demonstrates that the solvate water, coordinated water and hydrophilic groups in the channels promote the mobility of protons in the framework. Water sorption measurements exhibited hysterical behaviour with a high uptake value of 379.07 cm(3) g(-1). Time-dependent measurements revealed that the proton conductivity is retained even after 12 h of measurements. The proton conduction mechanism was validated by ab initio electronic structure calculations using the Nudged Elastic Band (NEB) method with molecular dynamics (MD) simulation studies. The theoretical activation energy is calculated to be 0.54 eV which is in accordance with the experimental value.

Core-composite mediated separation of diverse nanoparticles to purity - Bhatt, Chandra S.; Nagaraj, Bharathkumar; Ghosh, Deepanjan; Ramasamy, Sureshkumar; Thapa, Ranjit; Marpu, Sreekar B.; Suresh, Anil K. (Soft Matter, 2019)
A generalized method for sorting nanoparticles based on their cores does not exist; it is an immediate necessity, and an approach incorporating cost-effectiveness and biocompatibility is in demand. Therefore, an efficient method for the separation of various mixed core-compositions or dissimilar metallic nanoparticles to their pure forms at the nano-bio interface was developed. Various simple core-combinations of monodispersed nanoparticles with dual cores, including silver plus gold, iron oxide plus gold and platinum plus gold, to the complex three-set core-combinations of platinum plus gold plus silver and platinum plus iron plus gold were sorted using step-gradient centrifugation in a sucrose suspension. Viscosity mediated differential terminal velocities of the nanoparticles permitted diversified dragging at different gradients allowing separation. Stability, purity and properties of the nanoparticles during separation were evaluated based on visual confirmation and by employing advanced instrumentations. Moreover, theoretical studies validated our experimental observations, revealing the roles of various parameters, such as the viscosity of sucrose, the density of the particles and the velocity and duration of centrifugation, involved during the separation process. This remarkably rapid, cost-efficient and sustainable strategy can be adapted to separate other cores of nanoparticles for various biomedical research purposes, primarily to understand nanoparticle induced toxicity and particle fate and transformations in natural biotic environments.

Core-size dispersity dominates the self-assembly of polymer grafted nanoparticles in solution - Bachhar, Nirmalya; Kurnaraswamy, Guruswamy; Kumar, Sanat K. (Macromolecules, 2019)
In polymer-grafted nanoparticles (PGN), covalent tethering of apolar polymer chains to a polar inorganic nanoparticle core induces the formation of self-assembled aggregates. Since the nature of these aggregates determines bulk mechanical and transport properties, it is of importance to understand the factors that determine the underlying assembly processes. In the literature, the solution assembly of PGNs has been understood in analogy to small-molecule amphiphiles. However, in any experimental realization, PGNs are invariably characterized by additional structural complexity, such as the distributions in the inorganic core size and in the grafted chains (both in their length and grafting density). These strongly influence the assembly of amphiphilic PGNs. We have previously demonstrated that dispersity in core size qualitatively affects the structure of PGN aggregates, and Jayaraman et al. demonstrated the effect of grafted chain-length dispersity. The combined effects of dispersity in the size of the core and grafted chains have not been explored previously. Here, we develop a model that builds on the work of Daoud and Cotton to explore a wide parameter space of PGN with dispersity simultaneously in core size and grafted chain length. We demonstrate that dispersity in core size is the dominant factor affecting the self-assembled solution structure of PGN aggregates. Our work suggests the importance of focusing on synthetic strategies for control of core-size dispersity to control aggregate structure in PGN.

Covalent organic frameworks: chemistry beyond the structure - Kandambeth, Sharath; Dey, Kaushik; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Covalent organic frameworks (COFs) represent a new field of rapidly growing chemical research that takes direct inspiration from diverse covalent bonds existing between atoms. The success of linking atoms in two and three dimensions to construct extended framework structures moved the chemistry of COFs beyond the structures to methodologies, highlighting the possibility of prospective applications. Although structure to property relation in COFs has led to fascinating properties, chemical stability, processability and scalability were some of the important challenges that needed to be overcome for their successful implementation. In this Perspective, we take a closer look at the growth of COFs from mere supramolecular structures to potential industrializable materials.

Covalent self-assembly in two dimensions: connecting covalent organic framework nanospheres into crystalline and porous thin films - Sasmal, Himadri Sekhar; Halder, Arjun; Kunjattu, Shebeeb; Dey, Kaushik; Nadol, Athulya; Ajithkumar, Thalasseril G.; Bedadur, Prachiti Ravindra; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Insolubility of covalent organic frameworks (COFs) in organic solvents is one of the major obstacles for the potential application of these extended networks such as drug delivery, sensing, optoelectronics, and semiconductor device fabrication. The present work proposes a unique way to make uniform, solution-processable, crystalline, and porous COF nanospheres directly from the homogeneous solution of amine and aldehyde via spatial and temporal control of the nucleation and growth. This strategy of direct nucleation simultaneously showcases the caliber to tune the size of the COF nanospheres from 25 to 570 nm. We have also demonstrated the concept of mesoscale covalent self-assembly of those solution-processable COF nanospheres in the liquid-liquid interface (DCM-water bilayer) for the very first time, transmuting them into self-standing COF thin films with long-range ordered arrangements in two dimensions. The crystalline and porous (with TpAzo showing highest S-BET of 1932 m(2) g(-1)) free-standing COF thin films could be fabricated in a wide range of thicknesses from as low as 21 nm to as high as 630 nm. Both beta-ketoenamine (TpAzo, TpDPP) and imine (TpOMeAzo, TpOMeDPP) linked COF thin films have been synthesized via mesoscale covalent self-assembly of the solution-processable COF nanospheres illustrating the generality of this eloquent methodology. Further, the solution processability has been tested and utilized to cast COF thin films uniformly in the inner and outer surface of an alumina hollow fiber membrane. The COF thin film-alumina hollow fiber membrane composites have showcased promising selective molecular separation of He and O-2, He and CO2, and He and N-2.

cRGD functionalized nanocarriers for targeted delivery of bioactives - Gajbhiye, Kavita Rai; Gajbhiye, Virendra; Siddiqui, Imtiaz A.; Gajbhiye, Jayant M. (Journal of Drug Targeting, 2019)
The integrins αvβ3 play a very imperative role in angiogenesis and are overexpressed in endothelial cells of the tumor. Recent years have witnessed huge exploration in the field of αvβ3 integrin-mediated bioactive targeting for treatment of cancer. In these studies, the cRGD peptide has been employed extensively owing to their binding capacity to the αvβ3 integrin. Principally, RGD-based approaches comprise of antagonist molecules of the RGD sequence, drug-RGD conjugates, and most importantly tethering of the nanocarrier surface with the RGD peptide as targeting ligand. Targeting tumor vasculature or cells via cRGD conjugated nanocarriers have emerged as a promising technique for delivering chemotherapeutic drugs and imaging agents for cancer theranostics. In this review, primary emphasis has been given on the application of cRGD-anchored nanocarriers for targeted delivery of drugs, imaging agents, etc. for tumor therapy.
Keywords: alpha(v)beta(3) integrin receptors; cancer; cRGD; nanocarriers; targeting

Critical role of processing on the mechanical properties of cross-linked highly loaded nanocomposites - Suresh, Karthika; Chowdhury, Arindam; Kumar, Sanat K.; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Polymer nanocomposites are frequently not at equilibrium-therefore, the structure and properties critically depend on the protocol followed in their preparation. Here, we demonstrate that the elastic-brittle transition in highly loaded ice-templated polymer nanocomposites is sensitively determined by the conformation of polymer chains during nanocomposite preparation. Macroporous polymer nanocomposites are synthesized using two preparation pathways, both exhibiting minor modifications of the ice-templating method wherein an aqueous dispersion of nanoparticles, polymers, and cross-linkers is frozen. In one method, the matrix polymer is cross-linked in the presence of ice, whereas in the other method, the ice is removed by freeze-drying before the polymer is cross-linked. Although all measurable structural metrics are practically identical for the two composites, they exhibit qualitatively different mechanical properties. Nanocomposites cross-linked in the presence of ice show exceptional resilience, recovering elastically from large compression for very high nanoparticle loadings-in some instances, above 90% by weight. Here, the critical particle loading for the elastic- brittle transition is dependent on the molecular weight of the polymer. In comparison, samples cross-linked after freeze-drying appear structurally identical but turn brittle at much lower particle loadings (about 60% by weight), independent of the matrix polymer molecular weight. We rationalize these differences in terms of the conformational state of the polymer during cross- linking. In the former case, polymer chains are in good solvent during nanocomposite preparation, while after lyophilization, they are in a poor solvent. The large spatial extent of well-solvated chains and chain-chain overlap during cross-linking results in the formation of intermolecular cross-links, and we obtain elastic nanocomposites even at high nanoparticle loadings. In contrast, for chains in collapsed conformations in a bad solvent, chain connectivity during cross-linking is achieved only for much lower particle loadings. Our results reiterate that the sensitivity of polymer conformations to different processing methods can result in large differences in properties, even though their consequences on structural characteristics are effectively indistinguishable.

Crystal engineering: an outlook for the future - Nangia, Ashwini K.; Desiraju, Gautam R. (Angewandte Chemie-International Edition, 2019)
Crystal Engineering has traditionally dealt with molecular crystals. It is the understanding of intermolecular interactions in the context of crystal packing and in the utilization of such understanding in the design of new solids with desired physical and chemical properties. We outline here five areas which come under the umbrella of Crystal Engineering and where we feel that a proper planning of research efforts could lead to higher dividends for science together with greater returns for humankind. We touch on themes and domains where science funding and translation efforts could be directed in the current climate of a society that increasingly expects applications and utility products from science and technology. The five topics are: 1)pharmaceutical solids; 2)industrial solid state reactions; 3)mechanical properties with practical applications; 4)MOFs and COFs framework solids; 5)new materials for solar energy harvesting and advanced polymers.
Keywords: crystal engineering; metal-organic frameworks; pharmaceutical solids; solar energy; solid-state reactions

Crystal engineering for intramolecular pi-pi stacking: effect of sequential substitution of f on molecular geometry in conformationally flexible sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Kumar, Deepak; Kotmale, Amol; Gonnade, Rajesh G.; Stuerzer, Tobias (Crystal Growth & Design, 2019)
A small library of ten sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of chronological positioning of the F-atom on the intramolecular pi-stacking assembly. The sequential positioning of F atoms was carried out on one of the aromatic rings that is linked to the sulfonamide moiety directly while the other aromatic ring (phenyl or pyridine) is linked by an ethyl spacer with the sulfonamide moiety. The ethyl spacer is provided to achieve the required flexibility so that both aromatic rings can bend to acquire syn conformation facilitated pi-stacking between electron-deficient and electron-rich aromatic rings. The idea was to study the interplay between hydrogen bonding and pi-stacking synthons in the conformationally flexible sulfonamide derivatives. The solid-state conformation of all the derivatives was investigated using the single-crystal X-ray diffraction technique. Crystal structure analysis revealed that the syn conformation was achieved only in trifluoro and pentafluoro sulfonamide derivatives with benzene substitution while in all other derivatives the molecules take either midway or anti conformations. None of the sulfonamide molecules with a pyridine moiety showed syn conformation. It could be because of the involvement of the pyridine N-atom in the hydrogen bonding dimeric synthon. The molecular conformation study in solution state using 2D NOESY and HOESY NMR experiments also substantiated syn conformation in a pentafluoro sulfonamide molecule with benzene substitution. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed higher stability for the syn conformation over midway and anti orientations.

Crystalline acylhydrazone photoswitches with multiple mechanical responses - Gupta, Poonam; Panda, Tamas; Allu, Suryanarayana; Borah, Silpisikha; Baishya, Anamika; Gunnam, Anilkumar; Nangia, Ashwini; Naumov, Pance; Nath, Naba K. (Crystal Growth & Design, 2019)
The advancement of our understanding of stimuli responsive molecular crystals has led to the realization that they hold great yet unexplored potential as adaptive materials. Although molecular crystals that exhibit a single mechanical response to a single input stimulus are now abundant, crystals that are capable of response to multiple stimuli are rather scarce. Here we report two photoswitchable acylhydrazone derivatives, Ac-1 and Ac-2, which respond to light as well as to mechanical force. Upon application of localized mechanical stress, the anhydrous (Ac-1a) and monohydrate (Ac-1h) crystals of Ac-1 undergo plastic shearing deformation and bending, whereas monohydrate crystals of Ac-2 undergo elastic deformation. When they are exposed to UV light, crystals of Ac-1h and Ac-2 undergo photoinduced bending; on the other hand, crystals of Ac-1a and thicker crystals of Ac-2 exhibit photosalient effect (light-induced leaping). It is demonstrated that the synergistic action of multiple stimuli (UV light and force) elicits enhanced mechanical response, and this strategy could be employed in the future to increase the efficacy of single crystal actuators.

Crystalline LaCoO3 perovskite as a novel catalyst for glycerol transesterification - Phadtare, Deepshree; Kondawar, Sharda; Athawale, Anjali; Rode, Chandrashekhar (Molecular Catalysis, 2019)
LaCoO3 perovskite was synthesized using sol-gel method by nitrate and acetate precursors of La and Co with varying molar ratios of La and Co (1:1, 1:2 and 2:1). This was found to be an unique strategy to obtain highly crystalline LaCoO3 perovskite material without using any chelating agent. The variation of precursors was found to influence their crystallinity however, variation in molar ratio in the range of 0.5-2, did not affect the formation of perovskite framework. The formation of pure perovskite phase (around or > 80%) could be achieved by combination of acetate and nitrate precursors while, the combination of acetate- acetate or nitrate- nitrate precursors resulted in low phase purity for the perovskite due to the formation of secondary phases like La2O3 and Co3O4. Very interestingly, such combination of perovskite and pure oxide phases contributed to enhancement of basic sites which catalyzed the glycerol transestrifiaction with DMC (dimethyl carbonate) to GC (glycerol carbonate) and GD (glycidol). Among all the catalysts studied, NAP-2 showed highest efficiency in terms of 98% glycerol conversion and 77% GC and 22% GD selectivities. The highlight of this work is that first step glycerol transesterification with DMC required basic sites of either metal oxide or perovskite but for cascade reaction involving decarboxylation required both metal oxide as well as LaCoO3 perovskite phase.

Cubic palladium nanorattles with solid octahedron gold core for catalysis and alkaline membrane fuel cell applications - Singh, Prem; Sonika; Gangadharan, Pranav K.; Khan, Ziyauddin; Kurungot, Sreekumar; Jaiswal, Amit (ChemCatChem, 2019)
Herein, we report the synthesis of palladium nanorattles (Au-Pd NRTs) comprising of a gold octahedral core caged within a thin porous cubic palladium shell. The introduction of core-shell and porous architecture was realized by combining seed mediated and galvanic replacement reaction techniques. Next, we examined the catalytic efficiency of the nanocatalyst in comparison with solid palladium nanocube (Pd-NC) of similar size for the degradation of p-nitrophenol and organic dyes. The rate constant of Au-Pd NRTs was found nearly 12 times higher than the Pd-NCs. Further, we exploited our catalyst for electrochemical oxygen reduction reaction (ORR) and observed its high intrinsic ORR activity. Compared with commercialized Pt/C, the Au-Pd NRT displayed nearly comparable onset and half-wave potential values and excellent durability upon potential cycling. The system level validation in a single-cell mode of alkaline exchange membrane fuel cell also confirms the efficiency of the present catalyst to serve as a potential cathode catalyst for realistic device applications.
Keywords: alkaline exchange membrane fuel cell; electrocatalysis; nanorattles; ORR; Pd nanoparticle

Cu/Cu2O nanoparticles supported on a phenol-pyridyl COF as a heterogeneous catalyst for the synthesis of unsymmetrical diynes via glaser-hay coupling - Chakraborty, Debanjan; Nandi, Shyamapada; Mullangi, Dinesh; Haldar, Sattwick; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (ACS Applied Materials & Interfaces, 2019)
Covalent organic frameworks (COFs) are a new class of porous crystalline polymers with a modular construct that favors fiinctionalization. COF pores can be used to grow nanoparticles (nPs) with dramatic size reduction, stabilize them as dispersions, and provide excellent nP access. Embedding substrate binding sites in COFs can generate host-guest synergy, leading to enhanced catalytic activity. In this report, Cu/Cu2O nPs (2-3 nm) are grown on a COF, which is built by linking a phenolic trialdehyde and a triamine through Schiff bonds. Their micropores restrict the nP to exceptionally small sizes (similar to 2-3 nm), and the pore walls decorated with strategically positioned hydrogen-bonding phenolic groups anchor the substrates via hydrogen-bonding, whereas the basic pyridyl sites serve as cationic species to stabilize the [CuclusterCl2](2-) type reactive intermediates. This composite catalyst shows high activity for Glaser-Hay heterocoupling reactions, an essential 1,3-diyne yielding reaction with widespread applicability in organic synthesis and material science. Despite their broad successes in homocoupled products, preparation of unsymmetrical 1,3-diynes is challenging due to poor selectivity. Here, our COF-based Cu catalyst shows elevated selectivity toward heterocoupling product(s) (Cu nP loading 0.0992 mol %; turn over frequency: similar to 4S-50; turn over number: similar to 17S-190). The reversible redox activity at the Cu centers has been demonstrated by carrying out X-ray photoelectron spectroscopy on the frozen reactions, whereas the crucial interactions between the substrates and the binding sites in their optimized configurations have been modeled using density functional theory methods. This report emphasizes the utility of COFs in developing a heterogeneous catalyst for a truly challenging organic heterocoupling reaction.
Keywords: Copper nanoparticles; Covalent organic framework; Glaser-Hay heterocoupling; heterogeneous catalysis; unsymmetrical diynes

Cyanuric-chloride-mediated synthesis of 2-Aryl-3-tert-butoxycarbonyl-thiazolidine-4-carboxylic acid anilides: mechanistic, X-ray crystal structures and cytotoxicity studies - Jagtap, Rohidas M.; Shaikh, Samir R.; Gonnade, Rajesh G.; Raheem, Shabnam; Rizvi, Masood A.; Pardeshi, Satish K. (ChemistrySelect, 2019)
The `2R,4R'-2-aryl thiazolidine-4-carboxylic acid anilides (ATCAAs) were synthesized using cyanuric chloride (CC) as a clean and substoichiometric acid-amine coupling agent under optimized reaction conditions. The diesterphenol intermediate based mechanism is proposed and supported by spectral characterization of the intermediate. The single crystal X-ray structures of acid substrate (2R,4R)-3-(tert-butoxycarbonyl)-2-(2-methoxyphenyl)thiazolidine-4-carbox ylic acid (3 a) and anilides (R)-tert-butyl 4-(2-fluorophenylcarbamoyl)thiazolidine-3-carboxylate (4 b), (2R,4R)-tert-butyl 2-(2,6-dichlorophenyl)-4-(m-tolylcarbamoyl)thiazolidine-3-carboxylate (6 b) confirmed the formation of chiral anilides. The synthesized library of anilides [(R)-tert-butyl 4-Aryl thiazolidine-3-carboxylate and (2R,4R)-tert-butyl 2-Aryl-4-Aryl thiazolidine-3-carboxylate] 4 a-6 f was screened for their in vitro anti cancer, neuronal and neuroprotective studies. The anilides 4 b, 4 g, 5 d, 5 h, 6 c and 6 f (where the aryl=2-fluorophenylcarbamoyl, 4-chlorophenylcarbamoyl, 2-methoxyphenyl, 2,5-dichlorophenylcarbamoyl, 2,6-dichlorophenyl, 4-chlorophenylcarbamoyl respectively)were found to be less cytotoxic towards N2 A, SHSY-5Y neuronal cell lines in their differentiated and undifferentiated forms, and also exhibited dose dependant anti-inflammatory properties for a possible identification towards neurodegenerative and inflammatory disorders.
Keywords: Acid-amine coupling; Cyanuric chloride; Cytotoxicity; Mechanistic investigations; Single crystal x-ray structure

Cyclic tetrapeptides from nature and design: a review of synthetic methodologies, structure, and function - Sarojini, Vijayalekshmi; Cameron, Alan J.; Varnava, Kyriakos G.; Denny, William A.; Sanjayan, Gangadhar (Chemical Reviews, 2019)
Small cyclic peptides possess a wide range of biological properties and unique structures that make them attractive to scientists working in a range of areas from medicinal to materials chemistry. However, cyclic tetrapeptides (CTPs), which are important members of this family, are notoriously difficult to synthesize. Various synthetic methodologies have been developed that enable access to natural product CTPs and their rationally designed synthetic analogues having novel molecular structures. These methodologies include the use of reversible protecting groups such as pseudoprolines that restrict conformational freedom, ring contraction strategies, on-resin cyclization approaches, and optimization of coupling reagents and reaction conditions such as temperature and dilution factors. Several fundamental studies have documented the impacts of amino acid configurations, N-alkylation, and steric bulk on both synthetic success and ensuing conformations. Carefully executed retrosynthetic ring dissection and the unique structural features of the linear precursor sequences that result from the ring dissection are crucial for the success of the cyclization step. Other factors that influence the outcome of the cyclization step include reaction temperature, solvent, reagents used as well as dilution levels. The purpose of this review is to highlight the current state of affairs on naturally occurring and rationally designed cyclic tetrapeptides, including strategies investigated for their syntheses in the literature, the conformations adopted by these molecules, and specific examples of their function. Using selected examples from the literature, an in-depth discussion of the synthetic techniques and reaction parameters applied for the successful syntheses of 12-, 13-, and 14-membered natural product CTPs and their novel analogues are presented, with particular focus on the cyclization step. Selected examples of the three-dimensional structures of cyclic tetrapeptides studied by NMR, and X-ray crystallography are also included.

C‐F bond activation by saturated NHC: mesoionic compound formation and its unprecedented adduct with B(C6F5)3 - Pait, M.; Kundu, G.; Tothadi, S.; Karak, S.; Jain, S.; Vanka, K.; Sen, S. S. (Angewandte Chemie - International Edition, 2019)
The reaction of SIPr, [1,3‐bis(2,6‐diisopropylphenyl)‐imidazolin‐2‐ylidene] (1), with C6F6 led to the formation of an unprecedented mesoionic compound (2). The formation of 2 is made accessible by deprotonation of the SIPr backbone with simultaneous elimination of HF. The C−F bond para to the imidazolium ring in 2 is only of 1.258(4) Å, which is the one of the shortest structurally authenticated C−F bonds known to date. The liberation of HF during the reaction is unequivocally proved by the addition of one more equivalent of SIPr, which leads to the imidazolium salt with the HF2− anion. To functionalize 2, the latter reacted with B(C6F5)3 to give an unusual donor–acceptor compound, where the fluoride atom from the C6F5 moiety coordinates to B(C6F5)3 and the carbanion moiety remains unaffected. Such coordination susceptibility of the fluoride atom of a nonmetallic system to a main‐group Lewis acid (Fnon‐metal→BR3) is quite unprecedented.
Keywords: C-F activation; carbanions; N-heterocyclic carbenes; structure elucidation; Ylides

Can half-a-monolayer of pt simulate activity like that of bulk pt? solar hydrogen activity demonstration with quasi-artificial leaf device - Bajpai, Himanshu; Patra, Kshirodra Kumar; Ranjan, Ravi; Nalajala, Naresh; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2020)
Pt is the best cocatalyst for hydrogen production. It is also well-known that the surface atomic layer is critical for catalysis. To minimize the Pt content as cocatalyst, herein we report on half-a-monolayer of Pt (0.5 theta(Pt)) decorated on earth-abundant Ni-Cu cocatalyst, which is integrated with a quasiartificial leaf (QuAL) device (TiO2/ZnS/CdS) and demonstrated for efficient solar hydrogen production. For the QuAL, TiO2 is sensitized with ZnS and CdS quantum dots by the SILAR method. The 0.5 theta(Pt)-decorated Ni-Cu shows an onset potential of 0.05 V vs reversible hydrogen electrode for the hydrogen evolution reaction, which is almost similar to that of commercial Pt/C. Photoactivity of the present QuAL device with either bulk Pt or 0.5 theta(Pt)-coated Ni-Cu cocatalyst is, surprisingly, equal. Our findings underscore that a fraction of a monolayer of Pt can enhance the activity of the cocatalyst, and it is worth exploring further for the high activity associated with atomic Pt and other noble metals.
Keywords: artificial leaf; nickel-copper; Photocatalysis; platinum; Solar hydrogen

Carbon allotropes: metal-complex chemistry, properties and applications - Sharma, Geeta (MRS Bulletin, 2020)

Carbon quantum dots functionalized agarose gel matrix for in solution detection of nonylphenol - Singh, S.; Nigam, P.; Pednekar, A.; Mukherjee, S.; Mishra, A. (Environmental Technology, 2020)
Nonylphenol, an endocrine disrupter, is widely released to the aquatic environment, which is accumulative and extremely toxic to aquatic organisms. Here, we report a simple and cost-effective large-scale green synthesis of water-soluble highly fluorescent carbon quantum dots (CQDs) from marine biowaste (offshore washed algae) which gets quenched strongly in the presence of nonylphenol. These CQDs were around 20-40 nm in size and exhibit fluorescence constantly at 360 nm. The XRD profile depicted the interlayer spacing in the particle as 0.284 nm with a humped peak around 14 degrees showing the amorphous nature of the CQDs. FTIR spectra showed the stretching vibration of the hydroxyl groups (OH), asymmetric and symmetric stretching vibrations of the carboxylate anions (COO-). The fluorescence quantum yield of the CQDs is up to 68% and nonyl phenol detection limit is less than 0.1 µM. Furthermore, the CQDs were found to be stable at a wide pH range which makes it a suitable nonylphenol sensor for a variety of environmental samples. We functionalized these CQDs on an agarose gel matrix to develop a convenient sensor for the rapid detection of nonylphenol.
Keywords: Carbon quantum dots; endocrine disrupter; marine algae; nonylphenol; pollutant

Carbon supported size-controlled ru catalysts for selective levulinic acid hydrogenation into γ-valerolactone - Simakova, Irina L.; Demidova, Yuliya S.; Simonov, Mikhail N.; Niphadkar, Prashant S.; Bokade, Vijay V.; Devi, Nandini; Dhepe, Paresh L.; Murzin, Dmitry Yu (Journal of Siberian Federal University-Chemistry, 2020)
Liquid phase levulinic acid hydrogenation into γ-valerolactone in 1,4-dioxane as a solvent (165°C, 20 bar) was studied over a range of Ru monometallic catalysts using mesoporous carbon material Sibunit as a support. In addition to the catalyst prepared by impregnation with RuCl3∙nH2O (0.1 M) followed by reduction in H2, size-controlled Ru(NPs)/Sibunit catalysts were synthesized by immobilization of polyvinylpyrrolidone (PVP) stabilized Ru nanoparticles (NPs) (dRu=2.4 nm). Сarbon supported colloidal Ru NPs were not studied earlier in levulinic acid hydrogenation. Activity of colloidal Ru(NPs)/Sibunit catalysts was found to be lower than that of impregnated Ru/Sibunit which could be attributed to hampering effect of PVP. However, colloidal Ru(NPs)/Sibunit purified by thermal treatment in air (180°C) followed by reduction in H2 (400°C) exhibited the same activity as impregnated one yielding 93% γ-valerolactone at 100% levulinic acid conversion. Applicability of supported PVP-assisted colloidal Ru NPs in hydrogenation of levulinic acid illustrates a potential to prepare more efficient catalysts for this reaction with a desired particle size. The catalysts were characterized by TEM, XRF, and N2 physisorption to compare their physical chemical properties.

Cascade dehydrative amination of glycerol to oxazoline (vol 8, pg 2954, 2018) - Pandya, R.; Mane, R.; Rode, C. V. (Catalysis Science & Technology, 2020)
Correction for `Cascade dehydrative amination of glycerol to oxazoline' by R. Pandyaet al.,Catal. Sci. Technol., 2018,8, 2954-2965, DOI: ;10.1039/C8CY00185E.

Catalyst-free regioselective [3+2] cycloadditions of alpha,beta-unsaturated N-arylnitrones with alkenes to access functionalized isoxazolidines: a DFT study - Ghosh, Arnab; Mane, Manoj V.; Rode, Haridas B.; Patil, Siddappa A.; Sridhar, Balasubramanian; Dateer, Ramesh B. (Chemistry-An Asian Journal, 2020)
The catalyst-free regioselective [3+2]-cycloaddition of alpha,beta-unsaturated N-arylnitrones with alkenes are developed. The series of synthetically important functionalized isoxazolidines are prepared in good to excellent yields by step economic pathway under ligand and transition-metal-free conditions. The regioselective cycloaddition pathway supported by control experiment and computational study.
Keywords: DFT study; isoxazolidines; metal and ligand free; nitrone cycloaddition; Regioselective

Catalytic biomass valorization - status and perspectives - Sudarsanam, Putla (Biomass Conversion and Biorefinery, 2020)

Catalytic conversion of HMF into ethyl levulinate - a biofuel over hierarchical zeolites - Chithra, P. A.; Darbha, Srinivas (Catalysis Communications, 2020)
Catalytic conversion of 5-hydroxymethyl-2-furfuraldehyde (HMF, a biomass-derived platform chemical) into ethyl levulinate (EL) is an attractive approach for producing renewable transport fuels for mitigating global warming. We report here the application of hierarchical zeolites (DZSM-5 and MZSM-5 synthesized by desilication and mesoporous templating approaches, respectively) as solid acid catalysts for this transformation. Hierarchical structure of these zeolites was confirmed by X-ray diffraction, nitrogen-physisorption and electron microscopy, and acidity was determined by temperature-programmed desorption of ammonia. HMF conversion of 94.2% with EL selectivity of 90.8% was achieved over the MZSM-5 catalyst. Acidity, pore size and surface properties affected the catalytic activity.
Keywords: 5-Hydroxymethyl-2-furfuraldehyde (HMF); Biofuel; ethyl levulinate; Hierarchical zeolite; ZSM-5

Catalytic hydrogenation of cinnamic acid and salicylic acid - Shinde, Sunil; Deshpande, Raj M. (Asian Journal of Chemistry, 2020)
Hydrogenation of cinnamic acid and salicylic acid was carried out using 5 %Ru/C, 5 % Pd/C and Ru-Sn/Al2O3 catalyst at 493 K and 6.89 MPa of hydrogen partial pressure. Ru-Sn/Al2O3 catalyst was found to be active for hydrogenation -COOH group to give cinnamyl alcohol. The selectivity to cinnamyl alcohol was low (15 %) as absolute inhibition of C=C bond hydrogenation in cinnamic acid is challenging. 5 %Pd/C catalyst was found to hydrogenate C=C bond and aromatic ring in cinnamic acid. 5 %Ru/C catalyst was found to be least selective catalyst as it hydrogenated C=C bond, aromatic ring and -COOH group in cinnamic acid. Hydrogenation of salicylic acid is not possible at 493 K as decarboxylation of salicylic acid occurs.

Catalytic reductive deoxygenation of esters to ethers driven by hydrosilane activation through non-covalent interactions with a fluorinated borate salt - Rysak, Vincent; Dixit, Ruchi; Trivelli, Xavier; Merle, Nicolas; Agbossou-Niedercorn, Francine; Vanka, Kumar; Michon, Christophe (Catalysis Science & Technology, 2020)
We report the catalytic and transition metal-free reductive deoxygenation of esters to ethers through the use of a hydrosilane and a fluorinated borate BArF salt as a catalyst. Experimental and theoretical studies support the role of noncovalent interactions between the fluorinated catalyst, the hydrosilane and the ester substrate in the reaction mechanism.

CD44, a predominant protein in methylglyoxal-induced secretome of muscle cells, is elevated in diabetic plasma - Bai, Shakuntala; Chaurasiya, Arvindkumar H.; Banarjee, Reema; Walke, Prachi B.; Rashid, Faraz; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2020)
Methylglyoxal (MG), a glycolytic intermediate and reactive dicarbonyl, is responsible for exacerbation of insulin resistance and diabetic complication. In this study, NIG-induced secretome of rat muscle cells was identified and relatively quantified by SWATH-MS. A total of 643 proteins were identified in MG induced' secretome, of which 82 proteins were upregulated and 99 proteins were downregulated by more than 1.3-fold in SWATH analysis. Further, secretory proteins from the dassical secretory pathway and nonclassical secretory pathway were identified using SignalP and SecretomeP, respectively. A total of 180 proteins were identified with SignalP, and 113 proteins were identified with SecretomeP. The differentially expressed proteins were functionallyannotated by KEGG pathway analysis using Cytoscape soft ware with plugin clusterMaker. The differentially expressed proteins were'sfound to he involved m various pathways like extracellular matrix (ECM) receptor interaction, leukocyte transendothelial migration, fluid shear tress and atherosclerosis, complement and coagulation cascades, and lysosomal pathway. Since the MG levels are high in diabetic conditions, the presence of MG-induced isecreted proteins was inspected `by profiling human plasma of healthy and diabetic subjects (n = 10 each). CD44, a predominant MG -induced secreted protein, was found to be elevated in the diabetic plasma and to have a role in the development of insulin resistance.

Chapter 18 - Advances in agrochemical remediation using nanoparticles - Abin Sebastian; Ashwini Nangia; Majeti Narasimha Vara Prasad (Agrochemicals Detection, Treatment and Remediation, 2020)
Agrochemical pollution is a serious threat to environmental safety. Exposure to agrochemicals had deleterious health effects such as nervous system damage and cancer. Biological magnification of persistent agrochemicals also occurred. Hence, remediation approaches for agrochemical pollution must be a holistic approach, including environment and crop produces. The advent of nanotechnology helped to formulate highly efficient methods for the remediation of agrochemicals. High reactive surface area and very small packing space requirements made usage of nanoparticles as a popular agent in agrochemical remediation. Growing interests in surface-engineered nanoparticles promise complete removal of agrochemicals from the environment. Nanosorbents immobilized agrochemicals in the soil and helped microbial degradation of these compounds. However, many of the agrochemicals are persistent, and hence complete removal of these residues practice via photocatalysis. Photocatalytic degradation of persistent agrochemicals using bimetallic nanocomposites widely adopted. Large-scale environmental remediation of agrochemicals in soil, water, and agriculture products achieved via nanoparticles-based agrochemical cleaning systems such as thin-film fixed-bed reactors and nano-phytoremediation.
Keywords: agrochemical cleaning systems; nanosorbents; Pesticides; Photocatalysis; surface engineering

Chapter 9. continuous flow synthesis of nanomaterials - Kulkarni, Amol A.; Jundale, Rajashri B. (Flow Chemistry, 2020)
Continuous flow synthesis of nanoparticles is now a well-accepted and reliable synthesis approach that gives consistent product properties. This chapter aims to do a critical analysis of the recent work in some of the relevant areas and gives specific recommendations where flow synthesis of nanomaterials can be realized as a reliable manufacturing process. The chapter also highlights the typical engineering issues that one needs to consider while transforming a batch synthesis protocol into continuous mode and its scale-up.

Chapter 9 - CRISPR-Cas9 for therapy: the challenges and ways to overcome them - Sundaram Acharya; Souvik Maiti; Debojyoti Chakraborty (Genome Engineering via CRISPR-Cas9 System, 2020)
Clustered regularly interspaced short palindromic repeat/CRISPR-associated (CRISPR Cas) is a component of the prokaryotic adaptive immune system which has been repurposed for genome editing in recent years. The precision, simplicity and flexibility of this system have opened up a broad range of biological applications covering basic research to biotechnology and medicine. Additionally, the multiplexing capabilities of CRISPR offers a promising approach for modeling or correcting common polygenic disorders along with its monogenic and infectious counterparts. Although CRISPR is not completely precise and questions remain regarding its specificity and modes of delivery, the robustness and wide applicability of this genome editing tool has opened up numerous ways to address these issues. In this chapter, we will discuss about initial progress toward CRISPR therapeutics, existing delivery modalities, the challenges before CRISPR editing before it becomes a therapeutic possibility and the ongoing efforts toward developing a perfect CRISPR system for bench to bedside application.
Keywords: CRISPR therapeutics; CRISPR-Cas9; iPSC

Characterisation of hyper tolerant Bacillus firmus L-148 for arsenic oxidation - Bagade, Aditi; Nandre, Vinod; Paul, Dhiraj; Patil, Yugendra; Sharma, Nisha; Giri, Ashok; Kodam, Kisan (Environmental Pollution, 2020)
Groundwater arsenic pollution causes millions of deaths worldwide. Long term natural and anthropogenic activities have increased arsenic levels in groundwater causing higher threats of arsenic exposure. Arsenic hyper-tolerant Firmicute Bacillus firmus L-148 was isolated from arsenic limiting Lonar lake soil, which tolerated more than 3 M arsenic and could oxidize 75 mM arsenite [As(III)] in 14 days. It oxidized As(III) in presence of heavy metals and had unusual pH optima at 9.2. B. firmus L-148 was studied at the biochemical, protein, genomic and transcript level for understanding its arsenic oxidizing machinery. The proteomic and transcript analysis exhibited the presence of ars and aio operon and supported the inducible nature of ars operon. Robust, hyper-tolerant, fast As(III) oxidizing, least nutrient requiring and multi-metal resistance qualities of the strain were used in microcosm studies for bioremediation. Artificial groundwater mimicking microcosm with 75 mM As(III) was developed. Modulation of carbon source, iron and multi metals affected growth and As(III) oxidation rate. The As(III) oxidation was recorded to be 77% in 15 days in presence of sodium acetate and Fe ions. This microcosm study can be explored for bioremediation of arsenic contaminated water and followed by precipitation using other methods. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Arsenic hyper-tolerance; Lonar lake; Microcosm studies; Multi-metal resistance; Next generation sequencing

Characterization of multidrug resistance in Vibriospecies isolated from marine invertebrates from Andaman Sea - Kumari, Prabla; Poddar, Abhijit; Das, Subrata K. (3 Biotech, 2020)
This study describes the abundance of multidrug-resistantVibriosassociated with marine invertebrate hosts from the Andaman Sea, India. Thirty-eightVibriostrains were isolated from surface mucus layers of coralPorites,Goniastrea, Pocillopora, Fungia, and eggs of spiny lobster (Panulirus penicillatus). Phenotypically, the majority of strains exhibited growth at a wide range of temperatures, salt tolerance, and diverse nutritional requirements. All the strains had more than 97% 16S rRNA sequence similarity with type species of the genusVibriowhereVibrio fortis, andVibrio alginolyticuswere predominant. Multilocus Sequence Analysis (MLSA) using eight housekeeping genes namelyftsZ,gapA,gyrB,mreB,pyrH,recA,rpoA,andtopAdistributed the strains into 6 reported clades i.e.,Harveyi, Ponticus, Nereis, Orientalis, Splendidus,andMediterraneiwhere nearly half of the total strains represented the cladeHarveyi, followed by the cladeSplendidus.Likewise, the PFGE profile indicated genomic heterogeneity among the strains resulting in their distribution in five major clusters. Resistance to different antimicrobials was tested following the disc diffusion method where all strains were found susceptible to chloramphenicol (30 mu g) and resistant to streptomycin (10 mu g), vancomycin (30 mu g), sulfamethoxazole-trimethoprim (25 mu g). Moreover, the resistant phenotype to other antimicrobials confirmed the abundance of multidrug resistance strains in this marine environment.
Keywords: Drug-resistant; Genetic diversity; marine invertebrate; Multilocus sequence analysis; Vibrio

Chemoselective ring closure of 4-(3-Methyl-2-oxo-2,5-dihydro-1H-pyrrol-1-yl)butanal leading to pandalizine A - Yadav, Mahesh B.; Pandhade, Kailas R.; Argade, Narshinha P. (ACS Omega, 2020)
Starting from methylmaleic anhydride, a facile total synthesis of pandalizine A alkaloid is described via the regioselective reduction of methylmaleimide and acid-catalyzed enolization of 4-(3-methyl-2-oxo-2,5-dihydro-1H-pyrrol-1-yl)butanal followed by chemoselective intramolecular dehydrative cyclization as the key steps. It is noteworthy that the analogous model system with an additional beta-methyl group followed an alternative chemoselective intermolecular aldol condensation pathway.

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid (vol 55, pg 6423, 2014) - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2020)

Co (9) S (8) nanoparticle-supported nitrogen-doped carbon as a robust catalyst for oxygen reduction reaction in both acidic and alkaline conditions - Illathvalappil, Rajith; Kurungot, Sreekumar (ChemElectroChem, 2020)
The present work illustrates the synthesis of an efficient and durable catalyst for electrochemical oxygen reduction reaction (ORR) which is active both in the alkaline and acidic conditions by dispersing few-layer graphitic carbon coated Co(9)S(8)nanoparticles on the nitrogen-doped carbon (NVC-G) support (Co9S8/NVC-G). The size of the Co(9)S(8)nanoparticles is nearly 7-8 nm and the particles are found to be dispersed homogeneously on the NVC-G support. The few-layer graphitic carbon formed on the surface of Co(9)S(8)nanoparticles is assisting to accomplish their small size and it also prevents agglomeration of the nanoparticles. The ORR activity of the obtained material was analyzed in both 0.1 M KOH and 0.5 M H(2)SO(4)solutions. Co9S8/NVC-G displays nearly 70 mV overpotential compared to thestate-of-the-artPt/C in 0.1 M KOH solution. The half-wave potential (E-1/2) difference of the present system is nearly 75 mV with the commercial Pt/C. Co9S8/NVC-G displays promising ORR activity in the acidic conditions as well with nearly 140 mV overpotential compared to its Pt/C counterpart. The system shows about 170 mV lowerE(1/2)value with Pt/C. The system shows good stability both in acidic and basic conditions compared to the Pt/C system. Finally, testing of a single cell of a polymer electrolyte membrane fuel cell (PEMFC) was performed by employing Co9S8/NVC-G as the cathode catalyst and Nafion-212 as the proton exchange membrane. The system displays a maximum power density of 245 mW cm(-2)in H-2-O(2)and 115 mW cm(-2)in H-2-air feeding conditions.
Keywords: cobalt sulfide; fuel cells; Nanoparticles; nitrogen-doped carbon; oxygen reduction reaction

CO2 hydrogenation to formate by palladium nanoparticles supported on N-incorporated periodic mesoporous organosilica - Betsy, K. J.; Lazar, Anish; Pavithran, Anjuna; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2020)
Development of a heterogeneous catalyst capable of selective transformation of CO2 to valuable products still remains a challenge. In this article, we account for the surfactant-directed synthesis of a new framework-incorporated nitrogen-containing periodic mesoporous organosilica nanosphere (NPMO). A thoroughly characterized N-incorporated hybrid PMO was utilized as a platform for stabilizing well-dispersed and easily accessible Pd nanoparticles (Pd-NPMO) without using any stabilizing agents or expensive dendrimers. Further, this bifunctional hybrid catalyst has been demonstrated to heterogeneously catalyze aqueous phase CO2 hydrogenation (CO2/H-2 ratio 1:3) for the direct synthesis of formate under 4 MPa pressure and at 100 degrees C. To validate the superior performance of the Pd-NPMO catalyst, we compared the activity with Pd-SBA-15 catalysts, and the results showed a 10-fold increase in turnover frequency of 108 h(-1) using Pd on NPMO which envisaged the crucial role of nitrogen sites in this catalyst to boost the CO2 valorization to formate.
Keywords: CO2 hydrogenation; Formic acid synthesis; Hybrid silica; Pd nanoparticles; PMO

Cobalt-based metal complexes prevent repeat tau aggregation and nontoxic to neuronal cells - Gorantla, V. Nalini; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease (AD) is a fatal neurodegenerative disorder with an alarming increase in the death rate every year. AD is characterised by an aberrant accumulation of proteins in the form of aggregates. The axonal microtubule-associated protein Tau and arnyloid-beta undergo structural transition to beta-sheet rich structure and form aggregates in neuronal soma as well as in the extracellular region. The loss of Tau from microtubules leads to the disintegration of axon and causing neuronal degeneration. This led to the development of effective drugs against AD, to prevent Tau aggregation. Here, we synthesized and screen metal-based complexes to prevent Tau protein aggregation. ThS fluorescence and TEM suggested the role of synthetic cobalt complexes in inhibiting Tau aggregation. CD spectroscopy showed that these complexes prevented conformational changes in Tau to beta-sheet. CBMCs were not toxic at lower concentrations and formed non-toxic Tau species. L1 and L2 prevented membrane leakage: whereas, higher concentrations of L3 caused membrane leakage as observed by LDH release assay. The overall results indicate the synthetic cobalt complexes to be a promising molecule against AD. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cobalt-based metals; Tau Aggregation; Tau inhibition; Tau toxicity

Co@CoAl-layered double hydroxide/nitrogen-doped graphene composite catalyst for Al-H2O-based batteries: simultaneous hydrogen production and electricity generation - Nadeema, Ayasha; Pandurang Kharabe, Geeta; Prakash Biswal, Dibya; Kurungot, Sreekumar (ChemElectroChem, 2020)
Currently, the low energy efficiency of water electrolysis has compelled research toward the development of novel and energy-effective strategies for low-cost H-2 generation. In this context, we report a new concept of simultaneous H-2 and electricity generation by separating out the exothermic self-sustained Al-H2O reaction via electrochemistry. In addition, to catalyze the cathodic water reduction reaction, a single-pot and environmentally benign synthesis method is adopted. It results in the design of an electrocatalyst composed of Co@CoAl-layered double hydroxide core-shell nanospheres anchored over in situ generated N-doped graphene. Toward the water reduction reaction, the designed catalyst shows a negative voltage shift of mere around 113 mV with respect to the commercial Pt/C catalyst to reach the benchmark 10 mA cm(-2), with excellent stability of approximately 86 % voltage retention after 12 h of continuous operation. The catalytic superiority of our material is evident when taken for battery-level testing; the fabricated device was able to deliver an average output voltage of around 0.95 V at a discharge current density of 5 mA cm(-2) along with H-2 liberation, which was also detected and quantified through gas chromatography.
Keywords: Al-H2O fuel cells; chronopotentiometry; core-shell structures; hydrogen evolution reaction; layered double hydroxides

Co-gasification of high ash coal–biomass blends in a fluidized bed gasifier: - Tiwary, Shishir; Ghugare, Suhas B.; Chavan, Prakash D.; Saha, Sujan; Datta, Sudipta; Sahu, Gajanan; Tambe, Sanjeev S. (Waste and Biomass Valorization, 2020)
Co-gasification (COG) is a clean-coal technology that uses a binary blend of coal and biomass for generating the product gas; it is environment-friendly since it emits lesser quantities of pollutants compared to the coal gasification process. Although coals found in many countries contain high percentages of ash, co-gasification studies involving such coals, and the process modeling thereof, are rare. Accordingly, this study presents results of the co-gasification experiments conducted in a fluidized-bed gasifier (FBG) pilot plant using as a feed the blends of high ash Indian coals with three biomasses, namely, rice husk, press mud, and sawdust. Since the underlying physicochemical phenomena are complex and nonlinear, modeling of the COG process has been performed using three computational intelligence (CI)-based methods namely, genetic programming, artificial neural networks, and support vector regression. Each of these formalisms was employed separately to develop models predicting four COG performance variables, namely, total gas yield, carbon conversion efficiency, heating value of product gas, and cold gas efficiency. All the CI-based models exhibit an excellent prediction accuracy and generalization performance. The co-gasification experiments and their modeling presented here for a pilot-plant FBG can be gainfully utilized in the efficient design and operation of the corresponding commercial scale co-gasifiers utilizing high ash coals.

Combinatorial approach through in vitro regeneration and phytochemical profiling of ceropegia media (huber) ans.: a potential way forward in the conservation of an endangered medicinal plant from the western ghats in India - Pandey, Meena; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Punekar, Sachin A.; Giri, Ashok P. (Journal of Plant Growth Regulation, 2020)
Ceropegia mediais an endemic and endangered plant as its propagation through seeds is unreliable due to low germination, slow growth and seedling decay under natural conditions. Also, tubers of this plant are edible serving as carbohydrate source with medicinal values leading to severe population decline in the natural habitat. To provide a sustainable solution, an efficient in vitro propagation protocol along with phytochemical profiling was developed forC. media. Callus cultures were induced from seedling and wild leaf tissues using the most effective Murashige and Skoog's (MS) medium with 2,4-dichlorophenoxyacetic acid (2,4-D; 2 mu M) and sucrose (3%). Somatic embryos were acquired on MS medium with 1 mu M 6-Benzylaminopurine (BAP) and 1 mu M 2,4-D. Conversion into plantlets was attained only from tissue culture-derived seedling leaf (TCDSL) explant. Further, in vitro tuberization was achieved from TCDSL callus with BAP and Naphthalene acetic acid (NAA). AgNO(3)as an elicitor had a positive effect on both fresh and dry weights of callus. Successful acclimatization (58%) was attained after two months resulting in normal phenotype in pots. Further, metabolite profiles of ten different tissues from wild and in vitro plants were compared. Total 82 compounds comprising alkaloids, fatty acids, fatty acid ester, steroids, terpenes and hydrocarbons were identified. Overall, results suggested enhanced production of selected metabolites with in vitro propagation and AgNO3, alleviating the problem of unavailability of planting materials. Thus, the current study might offer potential ways for the conservation of such RED enlisted species asC. media. [GRAHICS]
Keywords: Ceropegia media; GC-MS; Microtuberization; Secondary metabolites; Silver nitrate; somatic embryogenesis

Comparative proteomics unravels the differences in salt stress response of own-rooted and 110R-grafted thompson seedless grapevines - Patil, Sucheta; Shinde, Manisha; Prashant, Ramya; Kadoo, Narendra; Upadhyay, Anuradha; Gupta, Vidya (Journal of Proteome Research, 2020)
Thompson Seedless, a commonly grown table grape variety, is sensitive to salinity when grown on its own roots, and therefore, it is frequently grafted onto salinity-tolerant wild grapevine rootstocks. Rising soil salinity is a growing concern in irrigated agricultural systems. The accumulation of salts near the root zone severely hampers plant growth, leading to a decrease in the productive lifespan of grapevine and causing heavy yield losses to the farmer. In the present study, we investigated the differences in response to salinity between own-rooted Thompson Seedless (TSOR) and 110R-grafted Thompson Seedless (TS110R) grapevines, wherein 110R is reported to be a salt-tolerant rootstock. The grapevines were subjected to salt stress by treating them with a 150 mM NaCl solution. The stress-induced changes in protein abundance were investigated using a label-free shotgun proteomics approach at three time points viz. 6 h, 48 h, and 7 days of salt treatment. A total of 2793 proteins were identified, of which 246 were differentially abundant at various time-points in TSOR and TS110R vines. The abundance of proteins involved in several biological processes such as photosynthesis, amino acid metabolism, translation, chlorophyll biosynthesis, and generation of precursor metabolites was significantly affected by salt stress in both the vines but at different stages of stress. The results revealed that TSOR vines responded fervently to salt stress, while TS110R vines adopted a preventive approach. The findings of this study add to the knowledge of salinity response in woody and grafted plants and hence open the scope for further studies on salt stress-specific differences induced by grafting.
Keywords: 110R rootstock; gene ontology; grafting; label-free proteomics; salt stress; Vitis vinifera

Comprehensive metagenomic insights into a unique mass gathering and bathing event reveals transient influence on a riverine ecosystem - Yadav, Rakeshkumar; Rajput, Vinay; Gohil, Kushal; Khairnar, Krishna; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
The religious mass gathering and bathing can pose a multitude of significant public health challenges and lead to severe alterations in the river microbial ecology. The Pandharpur Wari is an annual pilgrimage of Maharashtra, India, where millions of devotees carry the footprints of the saint-poets and pay their obeisance to Lord Vitthal on the 11th day of moon's waxing phase (Ashadi Ekadashi). As a part of the ritual, the engrossed devotees, walk over 250 km, take a first holy dip in a sacred river Indrayani at Alandi and secondly in Bhima River at Pandharpur. The MinION-based shotgun metagenomic approach was employed to examine the impact of spiritual mass bathing on environmental changes (concerning the river microbial community structure and functions); and public health aspects (in terms of changes in the pathogenic potential and antibiotic resistance). The analysis of bathing and post-bathing samples of both the rivers revealed alterations in the alpha and beta diversity, indicating significant spatiotemporal variations in the overall microbial structure and function. Furthermore, the analysis revealed up to 80% of differences in the abundance of virulence genes between the bathing and post bathing samples. We observed parallel increase of priority skin and enteric pathogens (ranging from 11% to 80%) such as Acinetobacter baumannii, Staphylococcus aureus, Streptococcus pyogenes, Mycobacterium tuberculosis, and Pseudomonas aeruginosa during the bathing event. Moreover, we observed a significant increase in the antibiotic resistance in the bathing samples of Bhima and Indrayani rivers respectively. Altogether, this is the first comprehensive metagenomic study unravelling the influence of religious mass-bathing on the riverine ecosystem.
Keywords: Antibiotic resistance; Mass bathing; MinION sequencing; Priority pathogens; Virulence genes

Concise enantioselective synthesis of (R)-(+)-goniothalamin oxide, a trypanocidal active agent via L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde - Kumar, B. Senthil; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
A short and straight-forward enantioselective synthesis of (R)-(+)-goniothalamin oxide 2 has been achieved with an overall yield of 39% and 99% ee. The synthetic approach involves L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde followed by Lewis acid-mediated diastereoselective allylation of epoxy aldehyde as the key chiral-inducing steps.
Keywords: Allylation; asymmetric epoxidation; Esterification; Grubbs' catalyst; L-prolinol catalyst; Ring closing metathesis

Conjunctive photoluminescence enhancement through plasmonic and photonic band-gap pathways in a chiral self-assembled system - Baral, Marlin; Krishna Prasad, S.; Bhat, Sachin A.; Nayak, Rashmi A.; Yelamaggad, C. V. (ChemPhotoChem, 2020)
We describe two parallel pathways for enhancing the intrinsic photoluminescence of an organic emitter dispersed in a liquid crystal (LC) medium. The pathways have independent origins: (i) Metal enhanced fluorescence (MEF) incorporating gold nanoparticles having an organic shell of pro-mesogenic cholesterol esters; and (ii) Matching the photonic band gap (PBG) due to the helical structure in a self-assembled chiral system with the excitation wavelength. This unprecedented combination of both pathways achieves a level of photoluminescence exceeding the sum of the contribution from the individual methods. This conjunctive protocol results in an overall enhancement by a factor of 37 between the emitter dispersed in a non-chiral LC and that appealing to both MEF and PBG pathways. Circular polarized luminescence measurements also show that this protocol helps in effective discrimination of chiral light achieving a large dissymmetry factor whose magnitude (+0.33) is comparable to the highest recorded to date. Electric field switching between two states is also shown to result in appreciable fluorescence modulation. Being generic in nature the protocol employed can be adapted to a variety of situations with the large magnitude as well the modulation level suitable for applications such as biosensors, various analyte detection, and other photonic devices.
Keywords: chirality; circularly polarized luminescence; liquid crystals; photonic band-gap; plasmonics

Connecting microscopic structures, mesoscale assemblies, and macroscopic architectures in 3D-printed hierarchical porous covalent organic framework foams - Mohammed, Abdul Khayum; Usgaonkar, Saurabh; Kanheerampockil, Fayis; Karak, Suvendu; Halder, Arjun; Tharkar, Minakshi; Addicoat, Matthew; Ajithkumar, Thalasseril G.; Banerjee, Rahul (Journal of the American Chemical Society, 2020)
The induction of macro and mesopores into two-dimensional porous covalent organic frameworks (COFs) could enhance the exposure of the intrinsic micropores toward the pollutant environment, thereby, improving the performance. However, the challenge is to build a continuous hierarchically porous macro-architecture of crystalline organic materials in the bulk scale. In this regard, we have strategized a novel synthetic method to create hierarchically porous COF foams consisting of ordered micropores (2-2.2 nm) and disordered meso and macropores (50 nm to 200 mu m) as well as ordered macropores (1.5 mm to 2 cm). Herein, graphene oxide was used for creating disordered macro and mesopores in COF-GO foams. Considering the rheological features of the precursor hydrogel, we could integrate crystalline and porous COF-GO foams into self-supported three-dimensional (3D)-printed objects with the desired shapes and sizes. Therefore, we have engineered the 3D macro-architecture of COF-GO foams into complex geometries keeping their structural order and continuous porosity intact over a range of more than a million (10(-9) m to 10(-3) m). The interconnected 3D openings in these COF-GO foams further enhance the rapid and efficient uptake of organic and inorganic pollutants from water (>95% removal within 30 s). The abundant distribution of interconnected macroporous volume (55%) throughout the COF-GO foam matrix enhances the flow of water (1.13 x 10(-3) m.s(-1)) which results in efficient mass transport and adsorption.

Construction of unique SCF3-containing building blocks via allylic alkylation of Morita-Baylis-Hillman adducts - Halder, Priyanka; Pol, Mahesh D.; Ahire, Milind M.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2020)
Lewis base-catalyzed allylic alkylation of Morita-Baylis-Hillman adducts with alpha-SCF3 ketones has been demonstrated. The developed strategy provides efficient access to a series of highly functionalized scaffolds featuring trifluoromethanesufinyl motif on a stereogenic carbon.

Continuous Flow Synthesis of Nanomaterials - Kulkarni, Amol A.; Jundale, R. B. (Continuous Flow Synthesis of Nanomaterials, 2020)

Continuous interfacial centrifugal separation and recovery of silver nanoparticles - Deshpande, Jaydeep B.; Navale, Govinda R.; Dharne, Mahesh S.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2020)
Continuous-flow separation and recovery of silver nanoparticles (AgNPs) using an annular centrifugal extractor (ACE) is demonstrated. Separation was achieved at the liquid-liquid interface based on the balance between centrifugal force and the solubility of the capping agent. A mathematical model is presented to understand the mechanism in greater detail. The separation of poly(vinylpyrrolidone) (PVP)-coated AgNPs in an ACE using a strong immiscible solvent was performed. The material accumulated at the interface was separated periodically without discontinuing the operation. The method is also suitable for separation of large particles or 1D/2D nanostructures even employing a single annular centrifugal extractor. Stable AgNPs were selected for a detailed antimicrobial activity study.
Keywords: Annular centrifugal extractor; Antimicrobial activity; Continuous-flow separation; Liquid-liquid interface; silver nanoparticles

Continuous time random walk concepts applied to extended mode coupling theory: a study of the Stokes? Einstein breakdown - Nandi, Manoj Kumar; Bhattacharyya, Sarika Maitra (Journal of Physics-Condensed Matter, 2020)
In an attempt to extend the mode coupling theory (MCT) to lower temperatures, some years back an Unified theory was proposed which within the MCT framework incorporated the activated dynamics via the random first order transition theory (RFOT). The theory successfully showed that there is hopping induced diffusive dynamics and the modified MCT coupled to the activated motion continues till low temperatures. Here we show that the theory although successful in describing other properties of supercooled liquids is unable to capture the Stokes?Einstein breakdown. We then show using continuous time random work (CTRW) formalism that the Unified theory is equivalent to a CTRW dynamics in presence of two waiting time distributions. It is known from earlier work on CTRW that in such cases the total dynamics is dominated by the fast motion. This explains the failure of the Unified theory in predicting the SE breakdown as both the structural relaxation and the diffusion process are described by the comparatively fast MCT like dynamics. The study also predicts that other forms of extended MCT with Markovian hopping kernel will face a similar issue. We next modify the Unified theory by applying the concept of renewal theory, usually used in CTRW models where the distribution has a long tail. According to this theory the first jump given by the persistent time is slower than the subsequent jumps given by the exchange time. We first show that for systems with two waiting time distributions even when both the distributions are exponential the persistent time is larger than the exchange time. We also identify the persistent time with the slower activated process. The extended Unified theory can now explain the SE breakdown. In this extended theory at low temperatures the structural relaxation is described by the activated dynamics whereas the diffusion is primarily determined by the MCT like dynamics leading to a decoupling between them. We also calculate a dynamic lengthscale from the wavenumber dependence of the relaxation time. We find that this dynamic length scale grows faster than the static length scale.
Keywords: continuous time random walk; mode coupling theory; Stokes?Einstein breakdown

Controlled synthesis of two-dimensional (2-D) ultra-thin bismuth selenide (Bi2Se3) nanosheets by bottom-up solution-phase chemistry and its electrical transport properties for thermoelectric application - Bin Masood, Khalid; Kumar, Pushpendra; Giri, Rajiv; Singh, Jai (FlatChem, 2020)
Bismuth Selenide and associated compounds inheriting stacked layered structure represent a unique class of materials where bulks are insulating with conducting surfaces, best known as thermoelectric materials. The bottom-up solution-based approach is a convenient alternative producing ultrathin high quality two-dimensional Bi2Se3 nanosheets. The present investigation deals with glycol mediated synthesis of highly crystalline ultrathin Bi2Se3 nanosheets. The as-synthesized Bi2Se3 nanosheets exhibit a rhombohedral crystal structure with a substantial surface-to-volume ratio that can possess several potential applications. Besides, the ultrathin Bi2Se3 nanosheets produced herein, found to be n-type with robust spatial confinement of charge carriers advantageous for thermoelectric applications, delivering a high-power factor of 1.55 mu W/cmK(2) at 150 degrees C. The method demonstrates the generic feature of the solution phase technique for the synthesis of highly crystalline nanosheets allowing mass production of identical ultra-thin nanosheets that can be easily integrated into devices for several promising applications, including spintronics, energy storage, and topological quantum computation.
Keywords: Rhombohedral structure; Sheet-like structure; Thermoelectric nanomaterials; transmission electron microscopy; XPS Spectra

Controlling and stabilization of Ru nanoparticles by tuning the nitrogen content of the support for enhanced H-2 production through aqueous-phase reforming of glycerol - Gogoi, Pranjal; Kanna, Narsimharao; Begum, Pakiza; Deka, Ramesh C.; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (ACS Catalysis, 2020)
The stable activity of catalysts is an important issue in catalysis, particularly aqueous-phase reforming (APR) of renewable oxygenates, of biomass origin, to get H-2. Sintering of metal nanoparticles on supports affects catalyst stability. To alleviate this problem, a series of highly stable Ru-supported catalysts with controlled metal nanoparticle sizes have been prepared via the easy incipient wetness impregnation method. These catalysts were used for APR of glycerol to produce H-2. Nitrogen-doped mesoporous carbons (NMCs) were utlized as supports and found to have a strong influence on the catalytic performance of the catalysts. Incorporation of nitrogen in the carbon framework significantly enhanced the catalytic activity compared to Ru catalysts on nitrogen-free supports. Notably, the catalyst (5 wt % Ru-NMC-3) with optimal N content (10.9 wt %) demonstrated improved stability and H-2 selectivity, which are better than those of many state-of-the-art catalysts. Nitrogen in the carbon framework has a dual relationship with the activity of the catalyst: (i) it creates basic environment over the catalysts support and (ii) it acts as an anchoring site for metal nanoparticles. Anchoring of metal nanoparticles has helped to curb their sintering, thus leading to better stability of the catalysts under APR reaction conditions. Various characterization techniques were employed to understand the nature of active catalytic sites responsible for higher H-2 production while minimizing CO formation. In situ CO-FTIR studies showed that the higher catalytic activity of 5 wt % Ru-NMC-3 catalyst was attributed to the enhanced WGS activity over this catalyst. Density functional theory calculations were performed to understand the stabilization of metal nanoparticles by different types of N present on the support and provide insights into the prefered sites of glycerol adsorption on the NMC support. Since S wt % Ru-NMC-3 was the relatively best catalyst, it was selected for the preparation of bimetallic catalysts. Accordingly, addition of Pt to this system helped to increase the stability of the catalyst. This bimetallic catalyst may, therefore, find application for wide use in APR of biomass oxygenates.
Keywords: aqueous-phase reforming; Glycerol; H-2 production; Ru/NMC catalyst; synergistic effect

Cooperative acid-base sites of solid Ba-Zr mixed oxide catalyst for efficient isomerization of glucose to fructose in aqueous medium - Shaikh, Samrin S.; Patil, Chetana R.; Kondawar, Sharda E.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
Efficient and highly selective isomerization of glucose to fructose was achieved by using the inexpensive Ba-Zr mixed metal oxide catalyst. Catalyst was prepared by varying Ba-Zr ratios using co-precipitation method. Various phases formed, planes exposed, morphology, elemental composition and particle size, basic site density and strength, oxidation state of elements were well studied by using various characterization techniques. The XRD analysis clearly indicates the presence of Ba+2 and Zr+4 in the form of BaO, ZrO2 and BaZrO3 phases. The SEM and HR-TEM images indicate that, Ba-Zr (2 : 1) catalyst prepared showed uniform morphology with spherical and rod-shaped particles ranging from 300 to 600 nm. Under the optimized reaction conditions Ba-Zr (2 : 1) catalyst exhibited excellent results in terms of 57 % of glucose conversion with 89 % selective formation of glucose. The presence of both acidic as well as basic sites play vital roles in activating the substrate molecules to selectively yield fructose. Ba-Zr (2 : 1) catalyst showed excellent recyclability performance up to four recycles.
Keywords: Co-precipitation; fructose; glucose; isomerization; mixed metal oxide

Copper-catalyzed direct arylation of indoles and related (hetero)arenes: a ligandless and solvent-free approach - Pandey, Dilip K.; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2020)
A ligandless and solvent-free copper-catalyzed method for the regioselective C-H bond arylation of indoles and related heteroarenes is reported. The use of CuCl efficiently catalyzes the direct coupling of diverse heteroarenes with aryl iodides via chelation-assistance. This reaction could tolerate sensitive and structurally diverse functionalities, including halides, ethers, thioethers, amines, indolyl, pyrrolyl and carbazolyl groups. The directing group, 2-pyridinyl can be smoothly removed to generate C-2 arylated free-NH indoles, and the arylated indoles can further be functionalized into Tryptamine derivatives. Preliminary mechanistic study revealed a radical pathway for the arylation reaction.
Keywords: Arylation; C-H activation; Chelation-assistance; Copper; Indole; Solvent-free

Correlation between multifunctional properties of lead free Iron doped BCT perovskite ceramics - Redhu, Preeti; Punia, Rajesh; Hooda, Ashima; Malik, B. P.; Sharma, Geeta; Sharma, Preeti (Ceramics International, 2020)
Present study investigates the effect of Fe doping on structural, microstructural, dielectric, ferroelectric, piezoelectric and magnetic properties of Barium calcium titanate (BCT) ceramics synthesized by solid state reaction route. The polycrystalline tetragonal structure of prepared ceramics was confirmed from XRD study. Analysis done using Rietveld refinement reveals reduction in lattice parameters as well as unit cell volume on substitution of Fe3+ ions in BCT lattice. Occurrence of four distinct Raman bands viz. 297 cm(-1) -302 cm(-1), 473 cm(-1)-475 cm(-1), 516 cm(-1) -524 cm(-1) and 729 cm(-1) -733 cm(-1) in Raman spectroscopic studies confirms the tetragonal phase of prepared ceramic compositions which are in accordance with XRD study. The Scanning Electron Microscopy analysis revealed polyhedral shaped grains whose average grain size decreased with increase in Fe content (x) in BCT ceramics. A diffused frequency independent phase transition was observed in temperature dependent dielectric measurements. Dielectric properties improved significantly, with shifting of transition temperature, T c close to room temperature with Fe doping. These studiessuggest applications of these ceramics in the development of environment friendly dielectric materials meeting X7R MLCCs specifications. The ferroelectric and piezoelectric properties of these ceramic compositions were found to decrease with increase in Fe concentration. Feeble room temperature ferromagnetism was observed for composition x = 0.020.
Keywords: BCT; dielectric response; Fe doping; ferroelectric properties; Lead free ceramics; Magnetic measurements

Critical organic modifier aliphatic tail length for the formation of poly(methyl methacrylate)-montmorillonite nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2020)
In this article, we report the influence of organic modifier structure (alkyl chain length C8-C20, single vs ditallow) and thereby, the effect of hydrophobicity on the structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay hybrids. Melt processed PMMA-clay hybrids were characterized using wide-angle X-ray diffraction, transmission electron microscopy, and differential scanning calorimetry. The organoclays having an alkyl chain length of more than 12 CH2 groups resulted in the formation of nanocomposites. The glass transition temperature (T-g) of PMMA increased in the presence of clay. The mean-field lattice model was used to predict the free energy for nanocomposite formation, which showed a reasonable match with the experimental results and provided a general guideline for the proper selection of polymer and organoclay (ie, organic modifier) to obtain nanocomposite. Tensile modulus showed maximum improvement of 58% for the nanocomposites compared to 9% improvement for the composites. Tensile modulus increased with increases in the alkyl chain length of the organic modifier and clay loading. The level of improvement for the tensile properties of nanocomposites prepared from primary and secondary ammonium-modified clay is the same as that obtained with the commercial organoclays.
Keywords: hybrid; mechanical properties; Montmorillonite; Nanocomposites; organoclay; poly(methyl methacrylate)

Crystal structure of a 1:1 co-crystal of the anti-cancer drug gefitinib with azelaic acid - George, Christy P.; Sangtani, Ekta; Gonnade, Rajesh G. (Acta Crystallographica Section E: Crystallographic Communications, 2020)
In the title co-crystal, C22H24ClFN4O3·C9H16O4, gefitinib (GTB; systematic name: quinazolin-4-amine) co-crystallizes with azelaic acid (AA; systematic name: nona-nedioic acid). The co-crystal has the monoclinic P21/n centrosymmetric space group, containing one mol-ecule each of GTB and AA in the asymmetric unit. A structure overlay of the GTB mol-ecule in the co-crystal with that of its most stable polymorph revealed a significant difference in the conformation of the morpholine moiety. The significant deviation in the conformation of one of the acidic groups of azelaic acid from its usual linear chain structure could be due to the encapsulation of one acidic group in the pocket formed between the two pincers of GTB namely, the morpholine and phenyl moieties. Both GTB and AA mol-ecules form N-H⋯O, O-H⋯N, C-H⋯O hydrogen bonds with C-H⋯F close contacts along with off-stacked aromatic π-π inter-actions between the GTB mol-ecules.

Crystal-to-crystal synthesis of helically ordered polymers of trehalose by topochemical polymerization - Hema, Kuntrapakam; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2020)
The synthesis of crystalline helical polymers of trehalose via topochemical azide-alkyne cycloaddition (TAAC) of a trehalose-based monomer is presented. An unsymmetrical trehalose derivative having azide and alkyne crystallizes in two different forms having almost similar packing. Upon heating, both the crystals undergo TAAC reaction to form crystalline polymers. Powder X-ray diffraction (PXRD) studies revealed that the monomers in both the crystals polymerize in a crystal-to-crystal fashion; circular dichroism (CD) studies of the product crystals revealed that the formed polymer is helically ordered. This solvent-free, catalyst-free polymerization method that eliminates the tedious purification of the polymeric product exemplifies the advantage of topochemical polymerization reaction over traditional solution-phase polymerization.
Keywords: Click reaction; helical polymers; polysaccharide; topochemical reactions; trehalose

Cu-Ni bimetal integrated TiO2 thin film for enhanced solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Saikia, Pranjal; Gopinath, Chinnakonda S. (Solar RRL, 2020)
A series of non-noble Cu-Ni bimetallic catalysts is prepared with different molar proportions of metals. Of these bimetallic catalysts, 1 wt% is subsequently integrated with titania P25. The catalysts are evaluated for solar hydrogen generation under 1 sun condition in both the powder and thin film forms. All the photocatalysts in the thin film exhibit an 8-24 times higher hydrogen yield (HY) compared with the corresponding particulate counterpart. The highest HY (41.7 mmol h(-1) g(-1)) is demonstrated for the photocatalyst Cu-Ni/TiO2 (CNT; 1:1 = Cu:Ni) in the thin film form, which is 24 times higher than that with its powder counterpart (1.75 mmol h(-1) g(-1)) and exceeds the performance of other Cu-Ni/TiO2 compositions. This enhanced activity in the thin film can be ascribed to improved absorption of visible light and an effective separation of photogenerated charge carriers at the interface of Cu-Ni/TiO2 leading to better charge carrier utilization.
Keywords: bimetals; energy conversion; Hydrogen; Photocatalysis; solar energy

Cyanosilylation by compounds with main-group elements: an odyssey - Pahar, Sanjukta; Kundu, Gargi; Sen, Sakya S. (ACS Omega, 2020)
The past few decades have seen remarkable headways in the structural and reaction chemistry of compounds with heavier main-group elements. In recent years, there is an ongoing effort to derive catalytic chemistry involving main-group compounds, driven by their lower costs and higher terrestrial abundances. Here, a survey on the state-of-the-art in the development of cyanosilylation methodology by compounds with heavier main-group elements has been given. Once dominated by transition metals, the field has matured to embrace the majority of the main-group elements including aluminum, silicon, and calcium. Of particular focus will be how the mechanism of cyanosilylation involving compounds with main-group elements differs from those of transition metals.

C (1)-Symmetric diphosphorus ligands in metal-catalyzed asymmetric hydrogenation to prepare chiral compounds - Sen, Anirban; Chikkali, Samir H. (Organic & Biomolecular Chemistry, 2021)
Asymmetric hydrogenation has remained an important and challenging research area in industry as well as academia due to its high atom economy and ability to induce chirality. Among several types of ligands, chiral bidentate phosphine ligands have played a pivotal role in developing asymmetric hydrogenation. Although C-2-symmetric chiral bidentate phosphine ligands have dominated the field, it has been found that several C-1-symmetric ligands are equally effective and, in many cases, have outperformed their C-2-symmetric counterparts. This review evaluates the possibility of the use of C-1-symmetric diphosphorus ligands in asymmetric hydrogenation to produce chiral compounds. The recent strategies and advances in the application of C-1-symmetric diphosphorus ligands in the metal-catalyzed asymmetric hydrogenation of a variety of C=C bonds have been summarized. The potential of diphosphorus ligands in asymmetric hydrogenation to produce pharmaceutical intermediates, bioactive molecules, drug molecules, agrochemicals, and fragrances is discussed. Although asymmetric hydrogenation appears to be a problem that has been resolved, a deep dive into the recent literature reveals that there are several challenges that are yet to be addressed. The current asymmetric hydrogenation methods mostly employ precious metals, which are depleting at a fast pace. Therefore, scientific interventions to perform asymmetric hydrogenation using base metals or earth-abundant metals that can compete with established precious metals hold significant potential.

Can we identify the salt-cocrystal continuum state using XPS? - Tothadi, Srinu; Shaikh, Tabrez Rafique; Gupta, Sharad; Dandela, Rambabu; Vinod, Chathakudath P.; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
X-ray photoelectron spectroscopy (XPS) is used to understand the nature of acid-base crystalline solids, to know whether the product is a salt (proton transfer, O-center dot center dot center dot H-N+) or a cocrystal (neutral adduct, O-H center dot center dot center dot N). The present study was carried out to explore if intermediate states of proton transfer from COOH to nitrogen (the proton resides between hydrogen bonded to O and N, O center dot center dot center dot H center dot center dot center dot N, quasi state) can be differentiated from a salt (complete proton transfer, N+-H center dot center dot center dot center dot O-) and cocrystal (no proton transfer, O-H center dot center dot center dot N) using N 1s XPS spectroscopy. The intermediate states of proton transfer arise when the pK(a) difference between the acid and the conjugate base is between -1 and 4, -1 < Delta pK(a) < 4, a situation common with COOH and pyridine functional groups present in drug molecules and pharmaceutically acceptable coformers. Complexes of pyridine N bases with aromatic COOH molecules in nine salts/cocrystals were cocrystallized, and their N 1s core binding energies in XPS spectra were measured. The proton state was analyzed by single-crystal X-ray diffraction for confirmation. Three new complexes were crystallized and analyzed by XPS spectra (without knowledge of their X-ray structures), to assess the predictive ability of XPS spectra in differentiating salt-cocrystal intermediate states against the extremities. The XPS results were subsequently confirmed by single-crystal X-ray data. Complexes of 3,5-dinitrobenzoic acid and isonicotinamide in 1:1 and 1:2 ratios exist as a salt and a salt-cocrystal continuum, respectively, as shown by the N 1s core binding energies. The proton states of the crystalline solids by XPS are in good agreement with the corresponding crystal structures. Other complexes, such as those of 3,5-dinitrobenzoic acid with 1,2-bis(4-pyridyl)ethylene, exhibit a salt-cocrystal continuum, maleic acids with 1,2-bis(4-pyridyl)ethylene and acridine are salts, 2-hydroxybenzoic acid and acridine is a salt, and the complex of 3,5-dinitrobenzoic acid and 3-hydroxypyridine is a salt and salt-cocrystal continuum, while fumaric acids with 1,2-bis(4-pyridyl)ethylene and acridine are cocrystals. Furthermore, three new acidbase complexes of 3,5-dinitrobenzoic acid with phenazine, 4-hydroxypyridine, and 4-cyanopyridine were studied initially by XPS and then confirmed by X-ray diffraction. In summary, since the N 1s binding energies cluster in a narrow range as cocrystals (398.7-398.9 eV) and salts (400.1-401.1 eV), it is clearly possible to differentiate between cocrystals and salts, but the saltcocrystal continuum values in XPS spectra are clustered in an intermediate range of cocrystals and salts but overlap with those of cocrystal or salt binding energies.

Carbazole substituted amidinato silylene: synthesis, bonding, and coordination behavior with coinage metals - Ghosh, Moushakhi; Tothadi, Srinu; Khan, Shabana (Organometallics, 2021)
In this work, the synthesis and characterization of a new carbazole substituted amidinatosilylene (1) and its coinage metal complexes 3-8 are being reported. Before the complexation reactions, we prepared [PhC(N+Bu)(2)Si(Cbz)-> Co(CO)Cp] complex (2) to estimate the sigma-donating strength of the newly synthesized silylene 1. Further, several commonly available coinage metal salts were utilized for the complexation reactions with 1, which afforded complexes 3-8. The solid-state structures of 1-8 have been validated by single-crystal X-ray diffraction studies, NMR spectroscopy, and mass spectroscopy. DFT studies were also performed to understand the bonding scenario of 1 and 3-7. Of note, 1 consists of a HOMO on its carbazolide moiety, and the HOMO-1 features the silylene character. We also compared the HOMO-LUMO gap of 1 with other amidinato silylenes having different N-substitutions.

Catalytic applications of hydrotalcite and related materials in multi -component reactions: concepts, challenges and future scope - Burange, Anand S.; Gopinath, Chinnakonda S. (Sustainable Chemistry and Pharmacy, 2021)
Hydrotalcites (HTs) are the potential substitute to conventional base catalysts. HTs are useful in efficient syntheses of various heterocycles, such as chromenes, pyrans, pyrazoles, triazoles, using multi-component reactions. This review focuses on the chemistry of HTs and particularly hydrotalcites and related materials in the synthesis of heterocycles. The effects of preparation method and, physico-chemical parameters, such as calcination, molar ratio of metals, role of intercalated ions, surface area, on the catalytic activities are discussed. Along with technical aspects, this review also unlocks various untouched areas in developing sustainable catalyst for syntheses of heterocycles, drugs, etc. for the future.
Keywords: green chemistry; green synthesis; heterocycles; heterogeneous catalysis; hydrotalcite; Metal Oxide

Caveolin induced membrane curvature and lipid clustering: two sides of the same coin? - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (Faraday Discussions, 2021)
Caveolin-1 (cav-1) is a multi-domain membrane protein that is a key player in cell signaling, endocytosis and mechanoprotection. It is the principle component of cholesterol-rich caveolar domains and has been reported to induce membrane curvature. The molecular mechanisms underlying the interactions of cav-1 with complex membranes, leading to modulation of membrane topology and the formation of cholesterol-rich domains, remain elusive. In this study, we aim to understand the effect of lipid composition by analyzing the interactions of cav-1 with complex membrane bilayers comprised of about sixty lipid types. We have performed a series of coarse-grain molecular dynamics simulations using the Martini force-field with a cav-1 protein construct (residue 82-136) that includes the membrane binding domains and a palmitoyl tail. We observe that cav-1 induces curvature in this complex membrane, though it is restricted to a nanometer length scale. Concurrently, we observe a clustering of cholesterol, sphingolipids and other lipid molecules leading to the formation of nanodomains. Direct microsecond timescale interactions are observed for specific lipids such as cholesterol, phosphatidylserine and phosphatidylethanolamine lipid types. The results indicate that there is an interplay between membrane topology and lipid species. Our work is a step toward understanding how lipid composition and organization regulate the formation of caveolae, in the context of endocytosis and cell signaling.

Caveolin mediated curvature and clustering: from simple to complex membrane - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (Biophysical Journal, 2021)

Characterization of a novel nanocomposite film based on functionalized chitosan-Pt-Fe3O4 hybrid nanoparticles - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Sahi, Shivendra V.; Sharma, Nilesh (Nanomaterials, 2021)
The development of organic-inorganic hybrids or nanocomposite films is increasingly becoming attractive in light of their emerging applications. This research focuses on the formation of a unique nanocomposite film with enhanced elasticity suitable for many biomedical applications. The physical property measurement system and transmission electron microscopy were used to analyze Pt-Fe3O4 hybrid nanoparticles. These nanohybrids exhibited magnetic effects. They were further exploited to prepare the nanocomposite films in conjunction with a chitosan-g-glycolic acid organic fraction. The nanocomposite films were then examined using standard techniques: thermogravimetric analysis, X-ray diffraction, Fourier transform infrared spectroscopy, and atomic force microscopy. Tensile strength testing demonstrated a significantly greater elastic strength of these nanocomposite films than pure chitosan films. The water absorption behavior of the nanocomposites was evaluated by measuring swelling degree. These nanocomposites were observed to have substantially improved physical properties. Such novel nanocomposites can be extended to various biomedical applications, which include drug delivery and tissue engineering.
Keywords: Chitosan; nanocomposite films; Pt-Fe3O4 hybrid nanoparticles; tensile strength testing; Thermogravimetric analysis

Chemistry, anti-diabetic activity and structural analysis of substituted dihydropyrimidine analogues - Bairagi, Keshab M.; Younis, Nancy Safwat; Emeka, Promise Madu; Venugopala, Katharigatta N.; Alwassil, I, Osama; Khalil, Hany Ezzat; Sangtani, Ekta; Gonnade, Rajesh G.; Mohanlall, Viresh; Nayak, Susanta K. (Journal of Molecular Structure, 2021)
In an effort to identify an anti-diabetic agent, a series of methyl/ethyl 4-(hydroxyphenyl)-6-methyl-2-oxo/thioxo-1,2,3,4 tetrahydropyrimidine-5-carboxylate analogues (4a-h) have been synthesized, purified, and characterized by using Fourier-Transform Infrared Spectroscopy (FT-IR) and NMR (H-1 and C-13). The synthesized compounds were screened for anti-hyperglycemic activity using Streptozotocin (STZ) induced diabetic rat model. The anti-hyperglycemic activity of dihydropyrimidine (DHPM) compound is mainly analyzed with the variation of substituents present on the phenyl ring and urea/thiourea group on pharmacophoric features. Further, the crystal structure and supramolecular characteristics of two compounds 4c and 4f were analyzed through a single-crystal X-ray method and the Hirshfeld Surface Analysis, which shows hydrogen bonding through N-H center dot center dot center dot O and N-H center dot center dot center dot S interactions with the formation of ring motif in the crystal structure. It is interesting to note that among the title compounds, the 4a, 4e, 4f, and 4g significantly displayed a better hypoglycemic effect in vivo rat model study. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dihydropyrimidine (DHPM); Hypoglycemia; Streptozotocin (STZ); Type-2 diabetes mellitus (T2DM)

Chronic systemic exposure to IL6 leads to deregulation of glycolysis and fat accumulation in the zebrafish liver - Singh, Manoj K.; Jayarajan, Rijith; Varshney, Swati; Upadrasta, Sindhuri; Singh, Archana; Yadav, Rajni; Scaria, Vinod; Sengupta, Shantanu; Shanmugam, Dhanasekaran; Shalimar; Sivasubbu, Sridhar; Gandotra, Sheetal; et al. (Biochimica ET Biophysica Acta-Molecular and Cell Biology of Lipids, 2021)
Inflammation is a constant in Non-Alcoholic Fatty Liver Disease (NAFLD), although their relationship is unclear. In a transgenic zebrafish system with chronic systemic overexpression of human IL6 (IL6-OE) we show that inflammation can cause intra-hepatic accumulation of triglycerides. Transcriptomics and proteomics analysis of the IL6-OE liver revealed a deregulation of glycolysis/gluconeogenesis pathway, especially a striking down regulation of the glycolytic enzyme aldolase b. Metabolomics analysis by mass spectrometry showed accumulation of hexose monophosphates and their derivatives, which can act as precursors for triglyceride synthesis. Our results suggest that IL6-driven repression of glycolysis/gluconeogenesis, specifically aldolase b, may be a novel mechanism for fatty liver. This mechanism may be relevant for NAFLD in lean individuals, an emerging class of NAFLD prevalent more in Asian Indian populations.
Keywords: Aldolase b; DHAP; Inflammation; Interleukin 6; Lean NAFLD; Non-alcoholic fatty liver

Cloning and expression of antibody fragment (Fab) I: effect of expression construct and induction strategies on light and heavy chain gene expression - Mehta, Deepa; Chirmade, Tejas; Tungekar, Aatir A.; Gani, Kayanat; Bhambure, Rahul (Biochemical Engineering Journal, 2021)
Dual promoter expression constructs offer time and cost-effective alternatives to produce multi-domain proteins like antibody fragments. This investigation is focused on understanding the effect of expression construct (dual promoter vs. co-transformation strategy), codon optimization, and induction strategies on yield and expression stoichiometry of LC and HC genes of antibody fragment at shake-flask and bioreactor scale. rHu biosimilar Ranibizumab was selected as a model protein for the study. Expression stoichiometry of HC and LC gene at mRNA level was studied using RTqPCR, whereas protein expression level was studied quantitatively using RP-HPLC and SDS-PAGE analysis. In the case of dual promoter expression construct, it was observed that LC gene cloned in the MCS1 of the duet vectors has > 2-fold expression than the HC gene, cloned in the MCS2. Transcript abundance profile of the HC and LC genes determined at different time intervals post-induction shows a difference in the gene expression at the transcriptional level. Comparative analysis of dual promoter and co-transformation strategy shows better stoichiometry in co-transformation (1:1.3), whereas higher protein yield in a dual expression system (>2.4 fold). The use of lactose and galactose as inducers show higher Fab yield of 2.30 +/- 0.03 g/L and 2.81 +/- 0.06 g/L with expression stoichiometry of 1:1.9 and 1:2 (HC: LC) respectively than IPTG-based induction with a protein yield of 1.40 +/- 0.02 g/L.
Keywords: Dual promoter vector; Expression stoichiometry; High cell density fermentation; rHu biosimilar Ranibizumab; Transcript abundance

Cobalt recovery from spent Li-ion batteries using lactic acid as dissolution agent - G. Santhosh; G.P. Nayaka (Cleaner Engineering and Technology, 2021)
The eﬀective recovery of cobalt from spent cathode materials is a critical issue and becomes a necessary assignment for the waste treatment of spent lithium-ion batteries (LIBs) in concern with waste to wealth. The dissolution process encompasses an organic acid leaching followed by recovery of pure Co oxalate. The use of lactic acid effectively improves the leaching of spent LiCoO2 materials with ascorbic acid. The leaching efficiencies of 99% for Li and 98% for Co were achieved under the optimal condition of 0.5 mol/L lactic acid and 0.02 mol/L ascorbic acid, solid/liquid ratio of 2 g/L, leaching time of 360 min and temperature of 90 °C. Based on the kinetic analysis, the enhancement leaching process is mainly on the concentration of dissolution reagent. Compared to other organic acids used previously, lactic acid showed better dissolution behavior.
Keywords: Cathode recycling; Kinetic analysis; Lactic acid; Spent Li-ion batteries

Co-decorated tellurium nanotubes for energy storage applications - Bhol, Prangya; Swain, Swarnalata; Jena, Satyaranjan; Bhatte, Kushal; Rout, Chandra Sekhar; Saxena, Manav; Jadhav, Arvind H.; Samal, Akshaya K. (ACS Applied Nano Materials, 2021)
This paper explicitly discusses the synthesis of Co-decorated Te nanotubes (NTs) using Te NTs as the sacrificial template and the evaluation of their electrochemical performance. First, one-dimensional (1D) Te NTs were synthesized and characterized by spectroscopic and microscopic tools such as UV-visible spectroscopy, X-ray diffraction spectroscopy, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, high-resolution transmission electron microscopy, and energy-dispersive X-ray spectroscopy analyses. The as-prepared hexagonal Te NTs (h-Te NTs) possess diameters of about 35 +/- 5 nm and lengths of about 500 +/- 50 nm and were used for the synthesis of Co-decorated Te NTs. The 1D nanostructure with excellent conductivity enables the material to show excellent electrochemical performance. The asymmetric assembly of the CoTe-2//AC electrode material displayed a high specific capacitance of 147 F g(-1) (specific capacity, 162 C g(-1) at a current density of 2 A g(-1) in 4 M KOH electrolyte. In addition to that, the assembly of CoTe-2//AC achieved an excellent energy density of 51.1 W h kg(-1) at a power density of 2294 W kg(-1) and confirmed the as-synthesized Co-decorated Te NTs to be an excellent electrode material.
Keywords: cobalt; nanotubes; pseudocapacitors; surfactant; Tellurium; template

Colchicine induces tetraploids in in vitro cultures of digitalis lanata Ehrh.: enhanced production of biomass and cardiac glycosides - Bhusare, B. P.; John, C. K.; Bhatt, V. P.; Nikam, T. D. (Industrial Crops and Products, 2021)
This study describes a promising method for tetraploidy induction in the in vitro grown diploid shoots of the cardiotonic herb Digitalis lanata by colchicine treatment to obtain a higher content of the cardiac glycosides' digoxin and digitoxin. The best frequency of tetraploids (33 %) induction was observed with 0.5 % colchicine treatment for 8 h. The content of digoxin and digitoxin in the tetraploids increased by 1.61-fold and 1.73-fold over the control diploids respectively. The higher cardiotonic glycoside production in the tetraploid plants of D. lanata have the potential to satisfy the increasing demand of superior plant material for pharmaceutical industries.
Keywords: Cardiac glycosides; Colchicine induced polyploidy; Digitalis lanata; Digitoxin; Digoxin

Cold active lipases: biocatalytic tools for greener technology - Mhetras, Nutan; Mapare, Vidhyashri; Gokhale, Digambar (Applied Biochemistry and Biotechnology, 2021)
Lipases are enzymes that catalyze the ester bond hydrolysis in triglycerides with the release of fatty acids, mono- and diglycerides, and glycerol. The microbial lipases account for \$400 million market size in 2017 and it is expected to reach \$590 million by 2023. Many biotechnological processes are expedited at high temperatures and hence much research is dealt with thermostable enzymes. Cold active lipases are now gaining importance in the detergent, synthesis of chiral intermediates and frail/fragile compounds, and food and pharmaceutical industries. In addition, they consume less energy since they are active at low temperatures. These cold active lipases have not been commercially exploited so far compared to mesophilic and thermophilc lipases. Cold active lipases are distributed in microbes found at low temperatures. Only a few microbes were studied for the production of these enzymes. These cold-adapted enzymes show increased flexibility of their structures in response to freezing effect of the cold habitats. This review presents an update on cold-active lipases from microbial sources along with some structural features justifying high enzyme activity at low temperature. In addition, recent achievements on their use in various industries will also be discussed.
Keywords: Cold active lipases; Frail compounds; Psychrophilic microbes; Synthesis of chiral molecules

Colloidal assembly by directional ice templating - Biswas, Bipul; Misra, Mayank; Bisht, Anil Singh; Kumar, Sanat K.; Kumaraswamy, Guruswamy (Soft Matter, 2021)
We investigate directional ice templating of dilute aqueous colloidal particle dispersions and examine the nature of the assemblies that result. We coat micron-size polystyrene colloids with cross-linkable polymer (polyethyleneimine, PEI), add cross-linker, and subject this dispersion to unidirectional freezing. We work at sufficiently low colloid concentrations, such that the particles do not percolate on freezing. When the aqueous dispersion freezes, ice crystals force polymer-coated particles and cross-linker into close proximity. This results in the formation of cross-linked clusters of particles at ice crystal boundaries. We vary the particle volume fraction from phi similar to 2.5 x 10(-3) to phi similar to 5.0 x 10(-2) and observe that there is a transition from isolated single particles to increasingly large sized clusters. Most of the clusters formed under these conditions are either linear, two-particle wide chains, or sheet-like aggregates. The probability (P-n) of clusters containing n particles (n > 2) obeys a power law P-n similar to n(-eta), where eta strongly depends on the particle concentration in the dispersion, varying from 2.10 (for phi similar to 5.0 x 10(-2)) to 3.03 (for phi similar to 2.5 x 10(-3)). This change in eta is qualitatively different from the case of isotropic freezing, where eta is particle concentration-independent and depends only on the ice nucleation density. To understand the differences between isotropic and directional ice templating, we performed lattice simulations of a highly simplified model, where ice crystals grow at a constant rate to force clustering. We ignore hydrodynamic interactions and ice growth instabilities. Despite ignoring these experimental details, the simulations capture the experimental results, nearly quantitatively. As the ice crystals grow and the space available to the colloids ``closes up'' so that the particles cluster to form aggregates, crystallization protocol-induced differences in the geometry of these ``closed up'' spaces determine the scaling behaviour of P-n.

Combating multi-drug resistant malaria parasite by inhibiting falcipain-2 and heme-polymerization: Artemisinin-peptidyl vinyl phosphonate hybrid molecules as new antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Rana, Kalpeshkumar C.; Datta, Gaurav; Asad, Mohd; Sundararaman, Srividhya; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (European Journal of Medicinal Chemistry, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Artemisinin-based combination therapies (ACTs) have been able to reduce the clinical and pathological malaria cases in endemic areas around the globe. However, recent reports have shown a progressive decline in malaria parasite clearance in South-east Asia after ACT treatment, thus envisaging a need for new artemisinin (ART) derivatives and combinations. To address the emergence of drug resistance to current antimalarials, here we report the synthesis of artemisinin-peptidyl vinyl phosphonate hybrid molecules that show superior efficacy than artemisinin alone against chloroquine-resistant as well as multidrug-resistant Plasmodium falciparum strains with EC<span style="box-sizing: inherit; font-size: 12px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">50<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> in pico-molar ranges. Further, the compounds effectively inhibited the survival of ring-stage parasite for laboratory-adapted artemisinin-resistant parasite lines as compared to artemisinin. These hybrid molecules showed complete parasite clearance in vivo using P. berghei mouse malaria model in comparison to artemisinin alone. Studies on the mode of action of hybrid molecules suggested that these artemisinin-peptidyl vinyl phosphonate hybrid molecules possessed dual activities: inhibited falcipain-2 (FP-2) activity, a P. falciparum cysteine protease involved in hemoglobin degradation, and also blocked the hemozoin formation in the food-vacuole, a step earlier shown to be blocked by artemisinin. Since these hybrid molecules blocked multiple steps of a pathway and showed synergistic efficacies, we believe that these lead compounds can be developed as effective antimalarials to prevent the spread of resistance to current antimalarials.

Comparative studies of the influence of particle size on various pretreatments of rice husk by assessment of chemical and structural components and wastewater characteristics of liquid fraction - Shahabazuddin, Mohmmad; Banuvalli, Bhavana Karibasappa; Mulik, Nagesh; Pande, Ashwini; Bokade, Vijay; Mudliar, Sandeep Narayan (Biomass Conversion and Biorefinery, 2021)
The dilute acid (DA), steam explosion (SE), and a 2-step: steam explosion followed by alkali (SEA) were evaluated for pretreatment of rice husk. The maximum hemicellulose and lignin removal via degradation and dissolution was observed for SEA pretreatment, enabling higher cellulose enrichment (up to 44% w/w) and recovery (up to 78%). The hemicellulose solubilization was >90% for all the pretreatments, while maximum lignin removal (up to 62%) was observed for SEA pretreatment. The particle size in the range of 0.3-0.6 mm enabled higher pretreatment efficiencies in terms of cellulose enrichment. The liquid fraction obtained after DA pretreatment indicated higher COD values (20800-24440 mg/L) as compared to SEA (7800-11400 mg/L) due to lower cellulose recoveries in DAP (54-68%). SEM analysis of the biomass indicated disrupted regions with multiple pores. FTIR analysis revealed cleavage of lignin side chains, and XRD analysis confirmed the increase in cellulose crystallinity post-pretreatment.
Keywords: Lignocellulosic crop residues; Liquid-waste characterization; Particle size; Rice husk biomass; Steam explosion pretreatment

Comparison of glycoprofiles of rituximab versions licensed for sale in India and an analytical approach for quality assessment - Kaur, Tejinder; Shukla, Bhupendra Nath; Yadav, Vinay Kumar; Kulkarni, Mahesh J.; Rao, Alka (Journal of Proteomics, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Glycosylation affects clinical efficacy and safety; therefore, is a critical quality attribute of therapeutic monoclonal antibodies. Glycans are often labile and complex in patterns, giving rise to macro- and micro-heterogeneity. Recombinant production, diverse geographical locations, associated transportation and storage conditions further compound the problem. Two-way studies comparing glycoprofile of the originator and its given biosimilar are aplenty. However, the extent of analytical variation and similarity in glycoprofile across all approved versions of a drug is hardly explored. Using UHPLC and mass spectrometry, we compared the glycoprofiles of eight rituximab drug samples licensed for sale in India. While the types of glycans were found identical, the abundance of some glycans varied significantly within the tested population. The quality range of glycosylation parameters of the tested sample population differed significantly from the previously established values for US/EU licensed rituximab. As the mean abundance of the 90% of identified glycans falls within ±3SD, the extent of mutual variations amongst tested lots is less significant compared to the extreme deviation from previously established QR limits. Thus, we propose this approach as an orthogonal method to capture glycan variations in licensed versions of mAbs for quality surveillance and in cases where originator samples' are limiting. SIGNIFICANCE: As fluctuation in glycosylation may be of clinical significance, we identify that a one-to-one comparison with originator alone is insufficient in sensing the extent of variations in glycosylation parameters in licensed biosimilars of a given therapeutic mAb. Here we propose that future biosimilarity analysis may include an orthogonal approach of generating an additional combined QR range representing variations across the originator and its biosimilars. The glycosylation profiles of eight rituximab drug samples of different make obtained from the point of sale in India were found identical amongst the tested rituximab versions. However, the QR limits corresponding to important glycosylation parameters differed significantly across all tested samples from the previously established QR limits of US- and EU-licensed rituximab in statistical terms. Such an approach may be useful in defining the true range of glycan variations in licensed versions of therapeutic mAbs.

Comprehensive review on catalytic O-alkylation of phenol and hydroquinone - Bhongale, Priyanka; Joshi, Sunil; Mali, Nilesh (Catalysis Reviews-Science and Engineering, 2021)
The alkylation process involves two competitive paths of O- and C-alkylation and achieving better selectivity for desired products is a very challenging problem. The development of new process for synthesis of O-methylated products of phenol and dihydric phenols is a subject of high industrial and academic interest. Alkyl phenyl ethers, especially anisole and 4-methoxyphenol, have captivated significant interest due to their increasing applications in pharmaceutical industries. The main emphasis of the present review is to explore the recent development in two catalytic O-alkylation processes. The first process is O-methylation of phenol into anisole and another is selective mono O-methylation of hydroquinone into 4-methoxyphenol. The present article covers O-alkylation methods with methanol and dimethyl carbonate as alkylating agent over various acidic and basic catalytic systems. The catalyst systems analyzed involves Bronsted and Lewis acidic and basic ionic liquids, conventional acids, metal oxides, solid acid and basic catalysts, hydrotalcites, various zeolites and heteropolyacids. The mechanistic behavior of alkylation reactions in presence of different catalytic system is reviewed critically which is important to design new and/or modified catalyst in order to maximize the yield of desired product. Additionally, an influence of reaction parameters, role of catalyst and their active sites on product distribution is described. The review paper gives useful insight for researchers in the field of catalysis and reaction engineering of alkylation reactions. Understandings of the reaction pathways will help in developing reliable kinetic models necessary for process scale-up to industrial scale reactor system.
Keywords: Dimethyl carbonate; Hydroquinone; Methanol; O-alkylation; phenol

Comprehensive tutorial on the pulsed laser deposition technique and developments in the fabrication of low dimensional systems and nanostructures - Masood, Khalid Bin; Kumar, Pushpendra; Malik, Mushtaq Ahmad; Singh, Jai (Emergent Materials, 2021)
Pulsed laser deposition (PLD) is a simple and extremely versatile technique to grow thin films and nanomaterials of a wide variety of materials. PLD allows the deposition of profoundly different materials, including high-temperature superconductors, oxides, nitrides, carbides, semiconductors, metals, and even polymers or fullerenes with high deposition rates. Growing thin films using PLD is now being used around the world for prototyping thin films of many inorganic materials and even in device fabrication protocols. This article covers the detailed development, versatility, and reliability of the ultraviolet (UV) excimer laser. It is envisioned that this review article is of interest for both the materials and chemical scientists engaged in more fundamental aspects of pulsed laser ablation and deposition. The present article highlights the historical developments of PLD technique, complete mechanism of thin film fabrication, optimization of the quality of thin films and the fabrication of thin films of the materials like ZnO, Graphene, MoS2, and WS2 which are being explored for various potential applications.

Computational insights into the role of external and local electric fields in macrocyclic chemical and biological systems - Mukherjee, Anagh; Ghule, Siddharth; Vanka, Kumar (ChemPhysChem, 2021)
The investigation of the role of the electric field in systems of widespread interest employing computational techniques is an emerging area of research. The outcome of applying an oriented external electric field (OEEF) on the geometric and electronic properties of the chemically unique pi-conjugated cyclic carbon ring compounds has been explored with density functional theory (DFT). Distinct changes in the structural and electronic features of such ring compounds are observed upon the application of OEEFs. Importantly, the calculations indicate that a mixed aliphatic-aromatic conjugated ring converts from a singlet to a triplet after the application of an OEEF, suggesting potential applications in optoelectronics for such molecules, without the need for photochemically induced change in the spin state. Furthermore, the influence of built-in local electric fields (LEFs) present in naturally occurring macrocyclic systems such as valinomycin has also been explored. Static and ab initio molecular dynamics (AIMD) calculations indicate that LEFs are the primary driving factor in determining the energetically favoured position of counter anions such as chloride (Cl-) in the potassium (K+) and sodium (Na+) coordinated valinomycin macrocycle structures: they exist inside the cage in the case of K+ sequestration by valinomycin and outside for Na+. This divergence has been proposed to be the determining factor for the selectivity of the valinomycin macrocycle for binding a K+ cation over Na+.
Keywords: counter anions; Density functional calculations; electric field; ion selectivity; macrocyclic systems

Concise/catalytic approach for the construction of the C14-C28 fragment of eribulin - Senapati, Sibadatta; Ramana, V, Chepuri (Organic & Biomolecular Chemistry, 2021)
A simple approach for the synthesis of the C14-C28 fragment of eribulin has been developed by employing a one-pot gold-catalyzed alkynol cyclization/Kishi reduction to construct the 1,5-cis-tetrahydropyran unit and a cross-metathesis/Sharpless asymmetric dihydroxylation-cycloetherification to install the 1,4-trans-tetrahydrofuran ring. Use of easily accessible building blocks, ease of operation and catalytic transformations as key reactions for the construction of THF/THP units highlight the current approach.

Conductive interface promoted bifunctional oxygen reduction/evolution activity in an ultra-low precious metal based hybrid catalyst (vol 57, pg 1951, 2021) - Sarkar, Shreya; Varghese, Merin; Vinod, C. P.; Peter, Sebastian C. (Chemical Communications, 2021)

Conductive interface promoted bifunctional oxygen reduction/evolution activity in an ultra-low precious metal based hybrid catalyst - Sarkar, Shreya; Varghese, Merin; Vinod, C. P.; Peter, Sebastian C. (Chemical Communications, 2021)
Ultra low PtPd alloy deposited on Ni12P5 nanostructures (PtPd/Ni12P5) exhibited enhanced ORR activity (onset: 1.003 V and E-1/2:0.95 V) on par with commercial Pt/C and superior OER activity with 81% reduction of the precious metal compared to the commercial catalyst.

Conformational plasticity and dynamic interactions of the N-terminal domain of the chemokine receptor CXCR1 - Kharche, Shalmali; Joshi, Manali; Chattopadhyay, Amitabha; Sengupta, Durba (Plos Computational Biology, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The dynamic interactions between G protein-coupled receptors (GPCRs) and their cognate protein partners are central to several cell signaling pathways. For example, the association of CXC chemokine receptor 1 (CXCR1) with its cognate chemokine, interleukin-8 (IL8 or CXCL8) initiates pathways leading to neutrophil-mediated immune responses. The N-terminal domain of chemokine receptors confers ligand selectivity, but unfortunately the conformational dynamics of this intrinsically disordered region remains unresolved. In this work, we have explored the interaction of CXCR1 with IL8 by microsecond time scale coarse-grain simulations, complemented by atomistic models and NMR chemical shift predictions. We show that the conformational plasticity of the apo-receptor N-terminal domain is restricted upon ligand binding, driving it to an open C-shaped conformation. Importantly, we corroborated the dynamic complex sampled in our simulations against chemical shift perturbations reported by previous NMR studies and show that the trends are similar. Our results indicate that chemical shift perturbation is often not a reporter of residue contacts in such dynamic associations. We believe our results represent a step forward in devising a strategy to understand intrinsically disordered regions in GPCRs and how they acquire functionally important conformational ensembles in dynamic protein-protein interfaces.

Connecting real glasses to mean-field models - Nandi, Ujjwal Kumar; Kob, Walter; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2021)
We propose a novel model for a glass-forming liquid, which allows us to switch in a continuous manner from a standard three-dimensional liquid to a fully connected mean-field model. This is achieved by introducing k additional particle-particle interactions, which thus augments the effective number of neighbors of each particle. Our computer simulations of this system show that the structure of the liquid does not change with the introduction of these pseudo-neighbors and by means of analytical calculations, and we determine the structural properties related to these additional neighbors. We show that the relaxation dynamics of the system slows down very quickly with the increase in k and that the onset and the mode-coupling temperatures increase. The systems with high values of k follow the mode-coupling theory power law behavior for a larger temperature range compared to the ones with lower values of k. The dynamic susceptibility indicates that the dynamic heterogeneity decreases with the increase in k, whereas the non-Gaussian parameter is independent of it. Thus, we conclude that with the increase in the number of pseudo-neighbors, the system becomes more mean-field-like. By comparing our results with previous studies on mean-field-like systems, we come to the conclusion that the details of how the mean-field limit is approached are important since they can lead to different dynamical behavior in this limit.

Conserved RNA binding activity of phosphatidyl inositol 5-phosphate 4-kinase (PIP4K2A) - Behari, Jatin; Borkar, Pranita; Vindu, Arya; Dandewad, Vishal; Upadrasta, Sindhuri; Shanmugam, Dhanasekaran; Seshadri, Vasudevan (Frontiers in Molecular Biosciences, 2021)
Plasmodium falciparum is a causative agent for malaria and has a complex life cycle in human and mosquito hosts. During its life cycle, the malarial parasite Plasmodium goes through different asexual and sexual stages, in humans and mosquitoes. Expression of stage-specific proteins is important for successful completion of its life cycle and requires tight gene regulation. In the case of Plasmodium, due to relative paucity of the transcription factors, it is postulated that posttranscriptional regulation plays an important role in stage-specific gene expression. Translation repression of specific set of mRNA has been reported in gametocyte stages of the parasite. A conserved element present in the 3 ` UTR of some of these transcripts was identified. Phosphatidylinositol 5-phosphate 4-kinase (PIP4K2A) was identified as the protein that associates with these RNA. We now show that the RNA binding activity of PIP4K2A is independent of its kinase activity. We also observe that PIP4K2A is imported into the parasite from the host on Plasmodium berghei and Toxoplasma gondii. The RNA binding activity of PIP4K2A seems to be conserved across species from Drosophila and C. elegans to humans, suggesting that the RNA binding activity of PIP4K may be important, and there may be host transcripts that may be regulated by PIP4K2A. These results identify a novel RNA binding role for PIP4K2A that may not only play a role in Plasmodium propagation but may also function in regulating gene expression in multicellular organisms.
Keywords: malaria; posttranscriptional gene regulation; RNA-protein interaction; translation regulation

Construction of beta-cyclodextrin linked glycidyl methacrylate polymers for stereoselective separation of chiral drug - Wale, Apparav; Mulani, Khudbudin; Deshpande, Supriya; Rajan, C. R.; Ponrathnam, Surendra (Journal of Polymer Research, 2021)
In this present study, a series of cross-linked porous polymers based on Glycidyl Methacrylate (GMA) were synthesized by suspension polymerization using cyclohexanol and hexanol as pore generating solvents. beta-cyclodextrin (beta-CD) was covalently bonded to the polymers by using Hexamethylene Diisocyanate (HMDI) and Sebacoyl Chloride (SC) as spacer arms. The effects of matrix properties such as pore volume, type of crosslinker, and spacer on the loading of beta-cyclodextrin were investigated. The stereoselective binding of enantiomers of the anti-depressant drug citalopram was studied using beta-cyclodextrin loaded polymers under batch adsorption mode. The capacity factor and selectivity of isomers were investigated also. This study reveals that these beta-cyclodextrin bonded Glycidyl Methacrylate (GMA) polymers are potentially suitable for chromatographic separation of citalopram.
Keywords: beta-cyclodextrin; Citalopram; Glycidyl Methacrylate (GMA) beads; HPLC etc; Stereoslelctivity

Construction of IrO2@Mn3O4 core-shell heterostructured nanocomposites for high performance symmetric supercapacitor device - Beknalkar, S. A.; Teli, A. M.; Harale, N. S.; Shin, J. C.; Patil, P. S. (Journal of Alloys and Compounds, 2021)
In the present work, we have designed and synthesized nanocomposite of IrO2@Mn3O4 with two-step simple and scalable chemical routes. In this route, nanofibers of IrO2 were synthesized by a single nozzle electrospinning technique onto which Mn3O4 was overlaid by a simple SILAR route. The ratio of Mn3O4 and IrO2 was varied by varying the SILAR cycles onto electrospun IrO2 thin film as 20, 40, 60, and 80 cycles. The structural, morphological, and energy storage performance of IrO2@Mn3O4 composite elec-trodes were investigated. A 2 V kinetic potential with a rectangular-shaped cyclic voltammogram was observed for the IrO2@Mn3O4 electrodes. Moreover, the specific capacitance of 1027 F/g at 1 mA/cm(2) was observed for the optimized electrode which is superior as compared with other electrodes. The opti-mized electrode showed better current and voltage than the individual compounds which might be due to the synergic effect of IrO2 and Mn3O4. Finally, a PVA-LiClO4 gel electrolyte-based solid-state IrO2@ Mn3O4//IrO2@Mn3O4 symmetric device was fabricated. The symmetric device possessed an energy density of 81 Wh/kg with a power delivery of 714 W/kg which was capable to light up a green LED. Hence, the 2D transition metal oxides laminated on 1D metal oxides with high conductivity can be promising electrodes for future research. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: And nanoflakes; Charge storage kinetics; Electrochemical properties; electrospinning; IrO2@Mn3O4 nanocomposite; nanofibers; SILAR

Construction of two-component chemically reactive supramolecular assemblies-acyl migration reactions in cocrystals of napthalene-2,3-diol and its diesters - Bahadur, Vir; Gonnade, Rajesh G.; Tamboli, I. Majid; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (ChemPlusChem, 2021)
Reactions in solids are of contemporary interest due to applications in pharmaceutical industries to environmental sustainability. Although several reactive crystals that support chemical reactions have been identified and characterized, the same cannot be said about reactive cocrystals. Earlier we correlated the facile acyl group transfer reactions in crystals with supramolecular parameters obtained from the crystal structures. The structure-reactivity correlation revealed the requirement of proper juxtaposition of electrophile (C=O) and the nucleophile (OH) with distance (similar to 3.2 angstrom) and angle (similar to 90 degrees) along the chain structure. The current article describes the preparation of cocrystals that are capable of supporting intermolecular acyl group transfer reactions in a group of structurally similar molecules. The cocrystals of naphthalene 2,3-diol and its corresponding diesters showed a facile solid state acyl transfer reaction, which has been well correlated with their crystal structures.
Keywords: Acylation; domino reactions; intermolecular interactions; reaction in cocrystal; solid-state reactions; X-ray diffraction

Continuous citrate-capped gold nanoparticle synthesis in a two-phase flow reactor - Damilos, Spyridon; Alissandratos, Ioannis; Panariello, Luca; Radhakrishnan, Anand N. P.; Cao, Enhong; Wu, Gaowei; Besenhard, Maximilian O.; Kulkarni, Amol A.; Makatsoris, Charalampos; Gavriilidis, Asterios (Journal of Flow Chemistry, 2021)
A continuous manufacturing platform was developed for the synthesis of aqueous colloidal 10-20 nm gold nanoparticles (Au NPs) in a flow reactor using chloroauric acid, sodium citrate and citric acid at 95 degrees C and 2.3 bar(a) pressure. The use of a twophase flow system - using heptane as the continuous phase - prevented fouling on the reactor walls, while improving the residence time distribution. Continuous syntheses for up to 2 h demonstrated its potential application for continuous manufacturing, while live quality control was established using online UV-Vis photospectrometry that monitored the particle size and process yield. The synthesis was stable and reproducible over time for gold precursor concentration above 0.23 mM (after mixing), resulting in average particle size between 12 and 15 nm. A hydrophobic membrane separator provided successful separation of the aqueous and organic phases and collection of colloidal Au NPs in flow. Process yield increased at higher inlet flow rates (from 70% to almost 100 %), due to lower residence time of the colloidal solution in the separator resulting in less fouling in the PTFE membrane. This study addresses the challenges for the translation of the synthesis from batch to flow and provides tools for the development of a continuous manufacturing platform for gold nanoparticles.
Keywords: Continuous manufacturing; Nanomaterials; Online analysis; phase separation; segmented flow

Controlled di-lithiation enabled synthesis of phosphine-sulfonamide ligands and implications in ethylene oligomerization - Mote, Nilesh R.; Gaikwad, Shahaji R.; Khopade, V, Kishor; Gonnade, Rajesh G.; Chikkali, Samir H. (Dalton Transactions, 2021)
Catalyst design for ethylene oligomerization has attracted significant interest. Herein, we report the synthesis of phosphine-sulfonamide-derived palladium complexes and examine their performance in ethylene oligomerization. Arresting a dilithiation intermediate of N-(2-bromophenyl)-4-methylbenzenesulfonamide (1) at -84 degrees C selectively produced N-(2-(bis(2-methoxyphenyl)phosphanyl)phenyl)-4-methylbenzenesulfonamide (L1A). However, the same reaction at -41 degrees C delivered a different ligand; 2-(bis(2-methoxyphenyl)phosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2A). The generality of our strategy has been demonstrated by preparing N-(2-(diphenylphosphanyl)phenyl)-4-methylbenzenesulfonamide (L1B) and 2-(diphenylphosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2B). Subsequently, L1A and L1B were treated with a palladium precursor to yield 5-membered complexes C1 and C2, respectively. In contrast, L2A upon treatment with palladium produced a 6-membered metal complex C3. Thus, a small library of 7 palladium complexes (C1-C7) were synthesized by varying the donor moiety (pyridine, DMSO, and acetonitrile). The identity of palladium complexes was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. The performance of the complexes C1-C7 was investigated in ethylene oligomerization and almost all of them were found to be active. The resultant ethylene oligomers were characterized using H-1 and C-13 NMR, MALDI-ToF-MS, and GPC. Detailed screening of reaction parameters revealed 100 degrees C and 40 bars ethylene to be optimal conditions. Complex C5 outperformed other complexes and produced ethylene oligomers with a molecular weight of 1000-1900 g mol(-1).

Controlling draw resonance during extrusion film casting of nanoclay filled linear low-density polyethylene: an experimental study and numerical linear stability analysis - Rokade, Dhammaraj; Chougale, Sanket; Patil, Prashant; Bhattacharjee, Tanushree; Gawande, Dnyaneshwar; Pol, Harshawardhan; Dhadwal, Renu (Journal of Plastic Film & Sheeting, 2021)
Commercially important extrusion film casting (EFC) processes for manufacturing plastic films or sheets are hampered by several instabilities that severely limits their productivity. In this research we focussed on one important instability: the draw resonance that occurs during the EFC process mainly under extensional flow conditions. Draw resonance is the sustained periodic oscillations in the film dimensions, notably film width and thickness, when the process operates beyond a critical draw ratio (CDR). In this research our goal was to reduce this draw resonance instability by incorporating well dispersed nanoclay fillers in a base polymeric resin (such as a linear low density polyethylene - LLDPE) to determine how these nanocomposite (NC) formulations can prevent or reduce the draw resonance defect. EFC experiments were conducted on the base resin and on the NC formulations under non-isothermal conditions to determine the onset of the draw resonance experimentally. Conventional linear stability analysis was performed to determine the onset of the draw resonance defect numerically. Numerical predictions for the onset of draw resonance were in qualitative agreement with our experimental data. Our results showed that incorporating appropriate nanoclay concentrations in a base polymeric resin indeed enhanced the EFC process stability for those polymer formulations and thus can have important economic implications for processors.
Keywords: Draw resonance; extensional strain hardening; Extrusion; Film; hydrodynamic interactions; Nanoclay; Nanocomposites; Polyethylene; Rheology; stability

Convenient and mild protocol for preparation of α –trimethylsilyloxyphosphonates using sulfamic acid and their oxidation to α – ketophosphonates in the presence of N-bromosuccinimide - Mitragotri, Satish; Kulkarni, Makarand; Desai, Uday; Wadagaonkar, Prakash (Arkivoc, 2021)
A convenient and mild protocol was developed for the trimethylsilylation of α-hydroxyphosphonates using hexamethyldisilazane as the silylating agent in the presence of sulfamic acid (SA) as a heterogeneous solid acid catalyst in dichloromethane as the reaction medium. The utility of SA as the catalyst for deprotection of α-trimethylsilyloxyphosphonates to parent α-hydroxyphosphonates by making a switch to a protic solvent such as methanol was also demonstrated. Furthermore, the oxidation of α–trimethylsilyloxyphosphonates to corresponding α–ketophosphonates was achieved in excellent yields employing N-bromosuccinimide in the presence of catalytic quantity of AIBN.

Convenient semihydrogenation of azoarenes to hydrazoarenes using H-2 - Sahoo, Manoj K.; Sivakumar, Ganesan; Jadhav, Sanjay; Shaikh, Samrin; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2021)
The high atom-economical and eco-benign nature of hydrogenation reactions make them much more superior to conventional reduction and transfer hydrogenation. Herein, a convenient and highly selective hydrogenation reaction of azoarenes using molecular hydrogen to access diverse hydrazoarenes is reported. The present catalytic method is general and operationally simple, and it operates under exceedingly mild conditions (room temperature and 1 atm of hydrogen pressure). The reusability of catalysts used in this method is also successfully demonstrated.

Copolymers of bipyridinium and metal (Zn & Ni) porphyrin derivatives; theoretical insights and electrochemical activity towards CO2 - Kochrekar, Sachin; Kalekar, Ajit; Mehta, Shweta; Damlin, Pia; Salomaki, Mikko; Granroth, Sari; Meltola, Niko; Joshi, Kavita; Kvarnstrom, Carita (RSC Advances, 2021)
This study reports the electropolymerization of novel keto functionalized octaethyl metal porphyrins (Zn2+ and Ni2+) in the presence of 4,4 `-bipyridine (4,4 `-bpy) as a bridging nucleophile. The polymer films were characterized by electrochemical, spectroscopic (UV-Vis, XPS, FT-IR and Raman spectroscopy) and imaging (AFM and SEM) techniques. The absorption and electronic spectra confirm the presence of both porphyrin and 4,4 `-bipyridine units in the film. The surface morphology reveals homogeneous film deposition with average roughness values of approx. 8 nm. The theoretical studies performed offered insights into the interplay of different metal centres (Zn2+ and Ni2+) and the keto functionality of the porphyrin unit in the formation of copolymer films. The electrochemical interaction of polymer films with CO2 suggests a reversible trap and release of CO2 with low energy barriers for both the polymers.

Cotton fabric decorated with manganese oxide nanorods as a supercapacitive flexible electrode for wearable electronics - Samuel, Edmund; Joshi, Bhavana; Kim, Yongil; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
We present the fabrication (using a hydrothermal process) and the properties of wearable fabrics decorated with ultrathin manganese oxide (MnO2) nanorods for supercapacitor applications. The superior mechanical durability of the supercapacitor was confirmed by cyclic voltammetry (CV) curves, which showed little change during 1000 bending cycles. The pseudocapacitive properties of the ultrathin MnO2 nanorods were confirmed by recording the CV curves at various scan rates. The galvanostatic charge-discharge curves at various specific currents confirmed the pseudocapacitance of MnO2. The ultrathin MnO2 nanorods exhibited a superior capacitance of 508 F.g(-1) and an energy density of 35.3 Wh.kg(-1). The MnO2 electrode with optimal properties demonstrated stable long-term cycling performance with 90% retention after 10,000 galvanostatic cycles.
Keywords: Cotton fabric; Manganese oxide; Ultrafine nanostructures; Wearable supercapacitors

Crack-free conjugated PbS quantum dot-hole transport layers for solar cells - Sharma, Ashish; Dambhare, V. Neha; Bera, Jayanta; Sahu, Satyajit; Rath, Arup K. (ACS Applied Nano Materials, 2021)
Colloidal quantum dots (QDs) benefit from solution-phase processing and band-gap tuning for their application in solar cell development. Today's QD solar cells rely on solid-state ligand exchange (SLE) to replace bulky oleic acid (OA) ligands with small 1,2-ethanedithiol (EDT) ligands to develop a conducting hole transport layer (HTL). High volume contraction in EDT conjugated QD films, however, leads to crack and porosity in the HTL, which is a major cause of concern for the device reproducibility and large-area solar cell development. We show that partial removal of the OA ligands in the solution phase reduces the volume contraction in solid films, thereby allowing the growth of crack-free QD films in the SLE process. The cleaning of QDs by repeated precipitation and redispersion using a protic methanol (MeOH) solvent helps with partial removal of the OA ligands, but it is detrimental to the electronic properties of QDs. We develop a one-step solution-phase partial ligand-exchange process using ammonium salts, which enable partial replacement of the OA ligands and passivation of the QD surface. Introduction of the facile partial ligand-exchange process eliminates the need for tedious and wasteful multiple cleaning steps with MeOH, while improving the photophysical properties of QDs. The advancement in QD processing helps to build crack-free, smooth, and conjugated QD films for their deployment as HTLs in solar cell development. Partial ligand exchange with NH4SCN leads to a 1.5 times increase in p doping and mobility over multiple MeOH-cleaned PbS QD films. HTLs developed using NH4SCN QDs show an improved photovoltaic performance to attain a 10.5% power conversion efficiency. Improvement in the depletion width and hole collection efficiency leads to a superior photovoltaic performance, as confirmed from experimental studies and one-dimensional solar cell capacitance simulation.
Keywords: Efficiency; ligand; polydispersity; quantum dot; solar cells; thin film

Crystal structure analysis of highly efficient chiral resolution of (RS)-arginine-fumaric acid cocrystal under preferential enrichment conditions - Manoj, Kochunnoonny; Takahashi, Hiroki; Iwama, Sekai; Gonnade, G. Rajesh; Tsue, Hirohito; Tamura, Rui (Journal of Molecular Structure, 2021)
Two new hydrate cocrystals, (RS)-arginine-fumaric acid-H2O ( 2 ) and (S)-arginine-2 fumaric acid-H2O ( 3 ), were obtained by the slow evaporation of the saturated aqueous ethanol solution of a 1:1 mixture of S-enriched arginine (33% ee) and fumaric acid or (S)-arginine and fumaric acid, respectively. Cocrystals 2 and 3 possess an isostructural molecular organization containing homochiral 1D chains of arginine sim-ilar to that of the anhydrous cocrystal of (RS)-arginine-fumaric acid ( 1 ). The latter showed an efficient ``preferential enrichment (PE)'', a unique spontaneous enantiomeric resolution phenomenon by simple recrystallization from the highly supersaturated solution. The formation of unstable cocrystals 2 and 3 seems to have played a crucial role in the enrichment of arginine in the mother liquor under PE crystal-lization conditions. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Arginine; cocrystals; crystal structure; Enantiomeric resolution; preferential enrichment

CsPbBr3/Cs4PbBr6 perovskite@COF nanocomposites for visible-light-driven photocatalytic applications in water - Kour, Prachi; Mukherjee, Shatabdi Porel (Journal of Materials Chemistry A, 2021)
For the first time, we have synthesized all-inorganic CsPbBr3/Cs4PbBr6 perovskite@COF nanocomposites under atmospheric conditions and tuned the crystal structures of the perovskite as well. The nanocomposite is reasonably stable and maintains its crystalline properties even when dipped into water for 60 minutes. The perovskite@COF nanocomposite shows efficient visible-light-driven photocatalytic performance to degrade Methyl orange (10 mL; 20-100 ppm). The rate of photodegradation was about 0.245 min(-1) with high catalytic activity and recyclability for three to six cycles.

CuO as a reactive and reusable reagent for the hydrogenation of nitroarenes - Rajendran, K.; Pandurangan, N.; Vinod, C. P.; Khan, Tuhin S.; Gupta, Shelaka; Haider, M. Ali; Jagadeesan, D. (Applied Catalysis B-Environmental, 2021)
{Copper oxide (CuO) is used as a reusable solid reagent for hydrogenation of nitroarenes to aminoarenes. The use of CuO resulted in 100 % conversion of 2.9 mmol of nitrobenzene to aniline in 45 s at room temperature using hydrazine hydrate as the reducing agent. During the reaction, CuO is converted to inactive metallic Cu which can be regenerated to active CuO by thermal oxidation. DFT simulations indicated facile formation of oxygen vacancies (EO
Keywords: Copper vacancy; CuO; Hydrogenation; Nitroarene reduction; Oxygen defects; Reactive solids

Curious case of aqueous warfarin: structural isomers or distinct excited states? - Sakpal, Sushil S.; Ghosh, Deborin; Manae, Meghna A.; Hazra, Anirban; Bagchi, Sayan (Journal of Physical Chemistry B, 2021)
Warfarin is a potent anti-coagulant drug and is on the World Health Organization's List of Essential Medicines. Additionally, it displays fluorescence enhancement upon binding to human serum albumin, making warfarin a prototype fluorescent probe in biology. Despite its biological significance, the current structural assignment of warfarin in aqueous solution is based on indirect evidence in organic solvents. Warfarin is known to exist in different isomeric forms-open-chain, hemiketal, and anionic forms-based on the solvent and pH. Moreover, warfarin displays a dual absorption feature in several solvents, which has been employed to study the ring-chain isomerism between its open-chain and hemiketal isomers. In this study, our pH-dependent experiments on warfarin and structurally constrained warfarin derivatives in aqueous solution demonstrate that the structural assignment of warfarin solely on the basis of its absorption spectrum is erroneous. Using a combination of steady-state and time-resolved spectroscopic experiments, along with quantum chemical calculations, we assign the observed dual absorption to two distinct pi ->pi* transitions in the 4-hydroxycoumarin moiety of warfarin. Furthermore, we unambiguously identify the isomeric form of warfarin that binds to human serum albumin in aqueous buffer.

Cardol: Cashew nut shell liquid (CNSL) - derived starting material for the preparation of partially bio-based epoxy resins - Ketan Makwana; Amol B. Ichake; Vinayak Valodkar; G. Padmanaban; Manohar V. Badiger; Prakash P. Wadgaonkar (European Polymer Journal, 2022)
Cardol is one of the interesting constituents of cashew nut shell liquid (CNSL) - a by-product of cashew processing industry- and it amounts to 15–20% by weight in natural CNSL. Chemically, cardol is a 15-carbon chain-substituted resorcinol wherein the side chain predominately contains mixture of one, two and three double bonds. Cardol on reaction with epichlorohydrin in the presence of sodium hydroxide afforded diglycidyl ether of cardol (DGEC). DGEC is a viscous free-flowing liquid (bulk viscosity 70 cP at 25 °C) and thus offers advantages in terms of ease of processing. DGEC and various compositions of DGEC with commercially available diglycidyl ether of bisphenol A (DGEBA) were cured with two amine hardeners, namely, isophorone diamine (IPDA) and diethylene triamine (DETA). The effects of different ratios of amine/epoxy (nah/ne) on cure characteristics were studied. The epoxy thermosets were characterized by DSC, TGA, DMA and tensile testing. DSC analysis showed glass transition temperature (Tg) values in the range 63–155 °C for IPDA-cured thermosets, while DETA-cured thermosets exhibited Tg values in the range 45–145 °C. Td5% values, determined by TG analysis of epoxy thermosets, were in the range 347–359 °C indicating their reasonably good thermal stability. Dynamic mechanical analysis showed storage modulus (E’) in the range 0.75–2.54 GPa and 0.51–2.24 GPa for IPDA-cured and DETA-cured thermosets, respectively. The E’ value of epoxy thermosets was found to decrease with increase in molar proportion of DGEC in the formulations with DGEBA while elongation at break was found to increase from 3.1% to 9.7% and 2.8% to 5.1% for IPDA- and DETA-cured systems, respectively. SEM images of cryogenically fractured surfaces of cured thermosets based on studied compositions of DGEBA and DGEC did not indicate any phase separation implying homogeneous mixing of both the epoxy resins.
Keywords: bio-based; Cardol; cashew nut shell liquid (CNSL); Epoxy resins; Storage modulus

Case report: a fatal case of babesiosis in a splenectomized male patient from Western India - Godbole, Ravi; Gaur, Avantika; Nayar, Priyanka; Kiruthiga, Kala; D'Costa, Pradeep; Manchanda, Rumma; Khilari, Ajinkya; Shanmugam, Dhanasekaran; Muglikar, Kalpana D.; Kundu, Krishnendu (American Journal of Tropical Medicine and Hygiene, 2022)
Human babesiosis is a rare disease, caused by Babesia species and commonly transmitted by tick bite. Although human babesiosis is known to be asymptomatic in immunocompetent hosts, clinical cases of severe babesiosis have been reported from splenectomized or immunocompromised individuals. To our knowledge, only one case of human babesiosis in India has been previously reported. Here, we report a case of severe babesiosis with high parasitemia (similar to 70%) in a 30-year-old asplenic farmer. The patient presented with fever, yellowish discoloration of skin, oliguria, and anemia; he eventually developed multiorgan failure syndrome and died. Peripheral blood films were prepared and used to confirm the presence of piroplasms by microscopy. Total DNA isolated from blood was used for 18S ribosomal RNA gene fragment amplification by polymerase chain reaction, which was subjected to Sanger sequencing. Although 18S sequence indicated that the Babesia species infecting the patient was similar to that of other Babesia species originating from wild mammals, species identification could not be done. Phylogenetic analysis revealed that the patientderived pathogen is distinct because it forms a separate clade in the cladogram.

Catalytic activity of CuFe2O4 spinel oxide for liquid-phase oxidation of cinnamyl alcohol - Dange, Rutvija M.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
CuFe2O4 spinel oxide catalyst was synthesized by sol-gel and co-precipitation methods for liquid phase oxidation of Cinnamyl alcohol (CnOH) to Cinnamaldehydes (CnHO) using tert-Butyl hydroperoxide (TBHP) as oxidising agent. Spinel oxide catalyst was characterized by different techniques such as X-ray diffraction (XRD), N-2 adsorption-desorption, BET surface area, and X-ray photoelectron spectroscopy (XPS) to understand the structural, physical properties and oxidation state of the catalyst. The result shows that catalyst prepared by sol-gel method was found higher surface area and smaller crystalline size than co-precipitation method. XPS data confirm the formation of Cu2+ in the spinel which helps to improve the catalytic activity of oxidation. This reaction follows radical mechanism, and exhibited 76.7 % of CnOH conversion and 68.4 % of CnHO, and 24.8 % benzaldehyde (benzald) selectivity using TBHP at 60 degrees C. Kinetic data reveal that 41.2 kJ/mol of activation energy for the reaction. The higher activity of spinel oxide catalyst could be due synergetic effect of spinel (88 %) and oxides (12 %) formed in the catalyst, which helps to provide the oxygen during reaction. The contribution of Cu2+ is higher in sol-gel than co-precipitation, which may provide the better reactivity of catalyst. This work helps to select the effective and cost-effective catalyst for the oxidation of CnOH.
Keywords: Catalysts; Cinnamaldehyde; Cinnamyl Alcohol; Cupper; iron; oxide; spinel

Catalytic conversion of sucrose to 1,2-propanediol over alumina-supported Ni-Mo bimetallic catalysts - Sreekantan, Sreejith; Kirali, Arun Arunima Balachandran; Marimuthu, Banu (Sustainable Energy & Fuels, 2022)
Ni-Mo supported on gamma-Al2O3 catalysts were synthesized to test its catalytic activity towards sucrose to 1,2-propanediol (1,2-PDO) conversion. The catalyst system was characterized using various physicochemical methods, including XRD, BET, py-FTIR, XPS, FE-SEM, HR-TEM and ICP. The metal combination of 8%Ni-20%Mo/gamma-Al2O3 is found to be effective in producing a good yield of 1,2-propanediol (similar to 74%) under mild reaction conditions of 180 degrees C, 40 bar H-2 pressure and a run time of 4.5 h in a batch reaction. The activity of the active catalyst over various substrates such as cellulose, glucose, fructose and real-source biomass has also been investigated. XPS analysis of the active catalyst confirms the various oxidation states of the metals Ni and Mo in the active catalyst. The py-IR results show that the optimum Lewis to Bronsted acidic site ratio is responsible for the selective conversion of sucrose to 1,2-PDO. The presence of interparticle mesopores on gamma-Al2O3 helps in the high conversion of sucrose. Furthermore, the catalyst has been found reusable for four consecutive runs without any structural or morphological changes.

CdS cubane type clusters encapsulated by rolling of single layer reduced graphene oxide sheets for enhanced mechanical energy harvesting - Kumar, Praveen; Ram, Farsa; Shanmuganathan, Kadhiravan; Luwang, Meitram Niraj (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Composites with Single Layer Graphene Oxide (SLGO) sheets are extremely difficult to achieve, irrespective of the current advancements in graphene composites research. The difficulties in exfoliating the graphite oxide (GO) was associated with a strong interaction among the edge sides of the adjacent layers. This in-turn barricades the foreign intruders to interact with the basal plane, thereby restraining one to form composites with SLGO sheets. In this work, we had successfully exfoliated GO through a spacer [Cd(OAc)(2) + polyethylene glycol (PEG)] to result in nano-engineered CdS cubane-type clusters in rolled up SLGO to form graphene oxide complex compound (GOCC), resembling carbon nanotubes (CNTs). The CdS cubane-type clusters were found to interacting with the carbon skeleton of rolled reduced SLGO sheet through a Manogate' structures, which was supported by density functional theory (DFT) calculations. Our theoretical study reveals that the obtained complex compound (GOCC) is thermodynamically more favourable than its ancestor materials (CdS cubane and empty CNT). Flexible piezoelectric nanogenerators (PENGs) fabricated from GOCC and thermoplastic polyurethane (TPU) resulted in output voltage (V-oc) of 4.5 V and output current of 0.4 mu A at applied force of 13 N. The nanoengineering helps to achieve superior mechanical energy harvesting performance for GOCC compared to pristine CdS, which demonstrate the potential of nanogate structures to enhance the intrinsic properties of materials.
Keywords: Graphene oxide complex compound; Nanogate structure; New material; Novel procedure; Piezoelectric nanogenerator; SLGO

CdSe quantum dot-based nanocomposites for ultralow-power memristors - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Shankar, Uday; Rath, Arup Kumar; Sahu, Satyajit (ACS Applied Nano Materials, 2022)
The explosion in digital communication with the huge amount of data and the internet of things (IoT) led to the increasing demand for data storage technology with faster operation speed, high-density stacking, nonvolatility, and low power consumption for saving energy. Metal chalcogenide-based quantum dots (QDs) show excellent nonvolatile resistive memory behavior owing to their tunable electronic states and control in trap states by passivating the surface with different ligands. Here, we synthesized high-quality colloidal monodispersed CdSe QDs by the hot injection method. The CdSe QDs were blended with an organic polymer, poly(4-vinylpyridine) (PVP), to fabricate an Al\textbackslashCdSe-PVP\textbackslashAl device. Our device shows excellent bipolar nonvolatile resistive random access memory (RRAM) switching behavior with a high current ON/OFF ratio (I-ON/OFF) of 6.1 x 10(4), and it consumes ultralow power. The charge trapping and detrapping in the potential well formed by the CdSe QD and PVP combination result in resistive switching. This CdSe-PVP-based resistive random access memory (RRAM) device with a high I-ON/OFF, ultrafast switching speed, high endurance, low operating voltage, and long retention period can be used as a high-performance and ultralow-power memristive device.
Keywords: memory switching; memristor; metal chalcogenides; nonvolatile; quantum dots

Ce promoted Cu/?-Al2O3 catalysts for the enhanced selectivity of 1,2-pro-panediol from catalytic hydrogenolysis of glucose - Kirali, Arun Arunima Balachandran; Sreekantan, Sreejith; Marimuthu, Banu (Catalysis Communications, 2022)
Ce promoted Cu/gamma-Al2O3 catalysts were prepared with varying amounts of Cu (x = 0-10 wt%) and Ce (y = 0-15 wt%). The prepared catalysts were characterized and tested for the conversion of aqueous glucose (5 wt%) to 1,2propanediol in a batch reactor. 10%Ce-8%Cu/gamma-Al2O3 & nbsp;showed the complete conversion of glucose with 62.7% selectivity of 1,2-propanediol and total glycols (1,2-propanediol, ethylene glycol & 1,2-butanediol) of 81% at milder reaction conditions. Cu facilitated the hydrogenation activity and Ce loading optimize the acid/base sites of Cu/gamma-Al2O3 which obtain high selectivity of 1, 2-propanediol. Catalyst reusability is reported.
Keywords: 2-Propanediol; 1; Cu-Ce catalyst; ethylene glycol; Gamma alumina; Glucose hydrogenolysis

Characterization of axial dispersion in a vertical helical coil for gas-liquid-liquid flow at low Reynolds numbers - Khan, Muzammil; Joshi, Sunil; Ranade, Vivek (Reaction Chemistry & Engineering, 2022)
Gas-liquid-liquid (GLL) slug flow reactors offer several advantages like higher interfacial area, excellent mass transfer, and lower backmixing. Mesoscale (diameter similar to a few mm) helical coiled reactors operating in a slug flow regime can be used as GLL reactors even for reactions with long residence times. The long residence time invariably leads to low Reynolds number flows, which makes the backmixing or axial dispersion an important parameter influencing reactor performance. In this work, we have characterized the residence time distribution (RTD) and axial dispersion for single, gas-liquid, liquid-liquid, and gas-liquid-liquid flows through a vertical helical coil. Slow flows with low Reynolds numbers (<100) were considered. RTD measurements were carried out with a step input and the outlet concentration was tracked by measuring light absorbance using a spectrophotometer. The applicability of the axial dispersion model was examined and verified for the studied systems. The axial dispersion was quantified in terms of dispersion coefficients. A significant reduction in the axial dispersion was observed by virtue of multiphase operation, in the order single > gas-liquid > liquid-liquid > gas-liquid-liquid flow. This characterization of backmixing for multiphase flows in curved geometries will be helpful in the optimization of slow reactions in flow and also for processes like nanoparticle synthesis, crystallization, etc.

Characterized constituents of insect herbivore oral secretions and their influence on the regulation of plant defenses - Kallure, Gopal S.; Kumari, Archana; Shinde, Balkrishna A.; Giri, Ashok P. (Phytochemistry, 2022)
For more than 350 million years, there have been ongoing dynamic interactions between plants and insects. In several cases, insects cause-specific feeding damage with ensuing herbivore-associated molecular patterns that invoke characteristic defense responses. During feeding on plant tissue, insects release oral secretions (OSs) containing a repertoire of molecules affecting plant defense (effectors). Some of these OS components might elicit a defense response to combat insect attacks (elicitors), while some might curb the plant defenses (suppressors). Few reports suggest that the synthesis and function of OS components might depend on the host plant and associated microorganisms. We review these intricate plant-insect interactions, during which there is a continuous exchange of molecules between plants and feeding insects along with the associated microorganisms. We further provide a list of commonly identified inducible plant produced defensive molecules released upon insect attack as well as in response to OS treatments of the plants. Thus, we describe how plants specialized and defense-related metabolism is modulated at innumerable phases by OS during plant-insect interactions. A molecular understanding of these complex interactions will provide a means to design eco-friendly crop protection strategies.
Keywords: Effector; Elicitor; Herbivore insects; Oral secretion; Plant defense; Suppressor

Choline-amino acid-derived bio-ionic liquids for solubility enhancement of zafirlukast - Gaikwad, Namrata; Kudal, Swapna; Avachat, Amelia M. (AAPS Pharmscitech, 2022)
This study investigated the application of bio-ionic liquids (ILs) prepared from choline as cation and amino acid as anion for solubility enhancement of poorly water-soluble drug, Zafirlukast (ZFL). Herein, the solubility of ZFL in water and mixtures of water and ILs was assessed using UV spectroscopy at two temperature points 25 degrees C and 37 degrees C with increasing concentrations of IL. ZFL solubility was found to improve linearly with increasing concentration of [Ch][Pro] in water, representing 35- to 37-fold improvement in ZFL solubility at maximum concentration of [Ch][Pro] (1% w/v) compared to when only pure water was present. Also, the effect of IL on ZFL solubility was analyzed using NMR, DSC, and TGA. These results clearly suggest that ZFL solubility was increased by forming hydrogen bonds with selected [Ch][Pro] IL. Toxicity study of ILs was tested against gram-positive and gram-negative bacteria. Since IL solvent was found to increase the solubility of ZFL, this may serve as ``functional excipient solvent'' for solubility enhancement in its commercialized formulations.
Keywords: Amino acids; choline chloride; Ionic liquid; solubility; zafirlukast

cis-aziridine synthon based synthetic investigation for tamiflu employing horner-wadsworth-emmons reaction - Chavan, Subhash P.; Kawale, Sanket A.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2022)
Synthetic investigations to achieve a novel intermediate of Tamiflu by using cis-aziridine as a chiral building block, which is readily synthesized from (D)-mannitol as a renewable starting material, has been presented. The present approach utilizes the intramolecular Horner-Wadsworth-Emmons reaction as the key step for the synthesis of Tamiflu. On the other hand, diene containing allylic aziridine framework is found to be inefficient to furnish the six-membered core skeleton of Tamiflu through ring-closing metathesis reaction.
Keywords: Aziridine; cyclization; HWE reaction; Metathesis; Tamiflu

C-O hydrogenolysis of C3-C4 polyols selectively to terminal diols over Pt/W/SBA-15 catalysts - Bhowmik, Susmita; Enjamuri, Nagasuresh; Marimuthu, Banu; Darbha, Srinivas (Catalysts, 2022)
Pt/W/SBA-15 catalysts (with Pt-loading = 0.5-4 wt% and W-loading = 1 wt%) prepared by the sequential impregnation method were evaluated for selective C-O cleavage of erythritol and glycerol in an aqueous medium. The Pt and W particles dispersed on SBA-15 approached close proximity at higher Pt loadings and afforded synergistic enhancement in C-O hydrogenolysis activity/selectivity. 1,4-Butanediol yields of 30.9% (at 190 degrees C, 50 bar H-2 and 24 h) and 1,3-propanediol yields of 34.4% (at 190 degrees C, 50 bar H-2 and 12 h of reaction) were obtained over these catalysts. Pt nanoparticles (facilitating dissociative H-2 adsorption and spillover) and W (present as acidic oligomeric WOx species; activating and coordinating the polyol via 1 degrees-OH group) worked in tandem for the selective hydrogenolysis of polyols yielding terminal diols of industrial demand.
Keywords: diol; Erythritol; Glycerol; Hydrodeoxygenation; Pt; SBA-15; W

Cobalt-immobilized carbon-based nano-catalyst for Csingle bondN cross coupling reaction - Bankar, Shubham R.; Kirdant, Swapnali P.; Jadhav, Vrushali H. (Results in Chemistry, 2022)
<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/cross-coupling-reaction" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about cross coupling reaction from ScienceDirect's AI-generated Topic Pages">cross coupling reaction is very important in synthesis of pharmaceuticals, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/occurrence-in-nature" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about natural products from ScienceDirect's AI-generated Topic Pages">natural products, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/agrochemical" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about agrochemicals from ScienceDirect's AI-generated Topic Pages">agrochemicals, fine chemicals and functional materials. Traditionally, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/palladium" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about palladium from ScienceDirect's AI-generated Topic Pages">palladium or copper metals are used for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling reaction. As palladium is expensive, we developed cobalt immobilized carbon-based nano-catalyst Co@CC for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling. In this work, we synthesized non-noble metal-based Co@CC nano-catalyst by <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/carbonization" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about carbonization from ScienceDirect's AI-generated Topic Pages">carbonization of glucose, it’s functionalization followed by immobilization of cobalt on the surface of the catalyst. The catalyst was well characterized. The C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N cross coupling reaction of various aryl <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/halide" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about halides from ScienceDirect's AI-generated Topic Pages">halides & amines using Co@CC nano-catalyst was optimized for solvent, reaction temperature & catalyst <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/concentration-condition" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about concentration conditions from ScienceDirect's AI-generated Topic Pages">concentration conditions. The catalyst showed high catalytic activity for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling of various aryl halides & amines to form aryl amines in good to excellent yield up to 91 % in <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/sulfolane" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about sulfolane from ScienceDirect's AI-generated Topic Pages">sulfolane as a solvent at 150 °C. The catalyst showed recyclability up to 5 times. The method developed for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling reaction was noble metal free, ligand free, recyclable, sustainable, economical & environmentally friendly.

Colloidal MoS2 quantum dots for high-performance low power resistive memory devices with excellent temperature stability - Bera, Jayanta; Betal, Atanu; Sharma, Ashish; Rath, Arup Kumar; Sahu, Satyajit (Applied Physics Letters, 2022)
Conventional memory technologies are facing enormous problems with downscaling, and are hence unable to fulfill the requirement of big data storage generated by a huge explosion of digital information. A resistive random access memory device (RRAM) is one of the most emerging technologies for next-generation computing data storage owing to its high-density stacking, ultrafast switching speed, high non-volatility, multilevel data storage, low power consumption, and simple device structure. In this work, colloidal MoS2 quantum dots (QDs) embedded in an insulating matrix of poly-(4vinylpyridine) (PVP) were used as an active layer to fabricate a RRAM device. The MoS2 QDs-PVP based RRAM device reveals an excellent nonvolatile resistive switching (RS) behavior with a maximum current on-off ratio (I-ON/I-OFF) of 10(5). High endurance, long retention time, and successive ``write-read-erase-read'' cycles indicate high-performance RRAM characteristics. The ultimate power consumption by this RRAM device is considerably low for energy saving. In addition, the MoS2 QDs-PVP based device shows RS behavior even at 130 degrees C. High I-ON/I-OFF, low operating power, high endurance, long retention time, and excellent stability with temperatures reveal that the MoS2 QDs-PVP based device can be a promising candidate for high-performance low power RRAM devices that can be operated at relatively higher temperatures. Published under an exclusive license by AIP Publishing.

Combinatorial therapy using RNAi and curcumin nano-architectures regresses tumors in breast and colon cancer models - Kumar, Aviral; Singam, Amarnath; Swaminathan, Guruprasadh; Killi, Naresh; Tangudu, Naveen Kumar; Jose, Jedy; Gundloori, Rathna V. N.; Kumar, Lekha Dinesh (Nanoscale, 2022)
Cancer is a debilitating disease and one of the leading causes of death in the world. In spite of the current clinical management being dependent on applying robust pathological variables and well-defined therapeutic strategies, there is an imminent need for novel and targeted therapies with least side effects. RNA interference (RNAi) has gained attention due to its precise potential for targeting multiple genes involved in cancer progression. Nanoparticles with their enhanced permeability and retention (EPR) effect have been found to overcome the limitations of RNAi-based therapies. With their high transportation capacity, nanocarriers can target RNAi molecules to tumor tissues and protect them from enzymatic degradation. Accumulating evidence has shown that tyrosine kinase Ephb4 is overexpressed in various cancers. Therefore, we report here the development and pre-clinical validation of curcumin-chitosan-loaded: eudragit-coated nanocomposites conjugated with Ephb4 shRNA as a feasible bio-drug to suppress breast and colon cancers. The proposed bio-drug is non-toxic and bio-compatible with a higher uptake efficiency and through our experimental results we have demonstrated the effective site-specific delivery of this biodrug and the successfull silencing of their respective target genes in vivo in autochthonous knockout models of breast and colon cancer. While mammary tumors showed a considerable decrease in size, oral administration of the biodrug conjugate to Apc knockout colon models prolonged the animal survival period by six months. Hence, this study has provided empirical proof that the combinatorial approach involving RNA interference and nanotechnology is a promising alliance for next-generation cancer therapeutics.

Comparative analysis and structural modeling of elaeis oleifera FAD2, a fatty acid desaturase involved in unsaturated fatty acid composition of american oil palm - Ben Ayed, Rayda; Chirmade, Tejas; Hanana, Mohsen; Khamassi, Khalil; Ercisli, Sezai; Choudhary, Ravish; Kadoo, Narendra; Karunakaran, Rohini (Biology-Basel, 2022)
Simple Summary Palm oil has become the world's most important vegetable oil in terms of production quantity, and its overall demand is exponentially growing with the global population. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing palm oil quality. In this study, we focused on FAD2, a fatty acid desaturase enzyme involved in the desaturation and conversion of oleic acid to linoleic acid in Elaeis oleifera, identified through in silico annotation analysis. Our phylogenetic and comparative studies revealed two SNP markers, SNP278 and SNP851, significantly correlated with the oleic/linoleic acid contents. Our study provides fundamental insights into the mechanism of fatty acids synthesis in oil palm and could support the application of molecular biology techniques to enhance the enzymatic activity and substrate affinity of EoFAD2. American oil palm (Elaeis oleifera) is an important source of dietary oil that could fulfill the increasing worldwide demand for cooking oil. Therefore, improving its production is crucial and could be realized through breeding and genetic engineering approaches aiming to obtain high-yielding varieties with improved oil content and quality. The fatty acid composition and particularly the oleic/linoleic acid ratio are major factors influencing oil quality. Our work focused on a fatty acid desaturase (FAD) enzyme involved in the desaturation and conversion of oleic acid to linoleic acid. Following the in silico identification and annotation of Elaeis oleifera FAD2, its molecular and structural features characterization was performed to better understand the mechanistic bases of its enzymatic activity. EoFAD2 is 1173 nucleotides long and encodes a protein of 390 amino acids that shares similarities with other FADs. Interestingly, the phylogenetic study showed three distinguished groups where EoFAD2 clustered among monocotyledonous taxa. EoFAD2 is a membrane-bound protein with five transmembrane domains presumably located in the endoplasmic reticulum. The homodimer organization model of EoFAD2 enzyme and substrates and respective substrate-binding residues were predicted and described. Moreover, the comparison between 24 FAD2 sequences from different species generated two interesting single-nucleotide polymorphisms (SNPs) associated with the oleic/linoleic acid contents.
Keywords: FAD2; Fatty acids; in silico annotation; linoleic acid ratio; oil palm; oleic; SNP; structural modeling

Comparative investigation on the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose - Manikandan, Marimuthu; Arjunan, Ayyappan; Prabu, Marimuthu; Raja, Thirumalaiswamy; Sangeetha, Palanivelu (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Hydrotalcites (HT) have a broad spectrum of applications as prosperous heterogeneous catalysts for diverse chemical transformations. The catalytic activity of HT-based materials can be tailored by introducing siliceous material into the internal or external framework. The surface modification of the HT framework with silica mesostructures leads to the formation of versatile Lewis base, Bronsted base and redox catalytic active sites. This work presents the comparative evaluation of the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose using 1-butanol as a solvent. The composites with different external morphology were prepared by a modified template-assisted hydrothermal method, using different HT to SBA-15 proportions. The textural and morphological characterization results conferred the efficiency of the employed post-synthetic intercalation strategy to achieve the successful formation of HT/SBA-15 and SBA-15/HT composites. With optimal HT loading and surface basicity, the HTS-3 composite demonstrated the highest catalytic performance, resulting in good glucose conversions (54 %) with improved selectivity (>83 %). The observed high reactivity could be mainly attributed to the extensive dispersion of HT particles on the SBA-15 component, which contributes to a significant increase in textural properties and surface basicity. Furthermore, special attention is devoted to addressing such reactivity phenomena as active site selectivity, catalyst multifunctionality and multisite reactivity commonly encountered in mesoporous catalysis.
Keywords: composites; glucose; hydrotalcite; isomerization; SBA-15

Comparative study of polycaprolactone electrospun fibers and casting films enriched with carbon and nitrogen sources and their potential use in water bioremediation - Alejandra Pompa-Monroy, Daniella; Leticia Iglesias, Ana; Gulam Dastager, Syed; Namdeo Thorat, Meghana; Olivas-Sarabia, Amelia; Valdez-Castro, Ricardo; Angelica Hurtado-Ayala, Lilia; Manuel Cornejo-Bravo, Jose; Lizeth Perez-Gonzalez, Graciela; Jesus Villarreal-Gomez, Luis (Membranes, 2022)
Augmenting bacterial growth is of great interest to the biotechnological industry. Hence, the effect of poly (caprolactone) fibrous scaffolds to promote the growth of different bacterial strains of biological and industrial interest was evaluated. Furthermore, different types of carbon (glucose, fructose, lactose and galactose) and nitrogen sources (yeast extract, glycine, peptone and urea) were added to the scaffold to determinate their influence in bacterial growth. Bacterial growth was observed by scanning electron microscopy; thermal characteristics were also evaluated; bacterial cell growth was measured by ultraviolet-visible spectrophotometry at 600-nm. Fibers produced have an average diameter between 313 to 766 nm, with 44% superficial porosity of the scaffolds, a glass transition around similar to 64 degrees C and a critical temperature of similar to 338 degrees C. The fibrous scaffold increased the cell growth of Escherichia coli by 23% at 72 h, while Pseudomonas aeruginosa and Staphylococcus aureus increased by 36% and 95% respectively at 48 h, when compared to the normal growth of their respective bacterial cultures. However, no significant difference in bacterial growth between the scaffolds and the casted films could be observed. Cell growth depended on a combination of several factors: type of bacteria, carbon or nitrogen sources, casted films or 3D scaffolds. Microscopy showed traces of a biofilm formation around 3 h in culture of P. aeruginosa. Water bioremediation studies showed that P. aeruginosa on poly (caprolactone)/Glucose fibers was effective in removing 87% of chromium in 8 h.
Keywords: bacterial growth; carbon source; electrospinning; nitrogen source; poly (caprolactone)

Comparison of hydrodynamic characteristics of Tulsion and Siran immobilised beads in a fluidised bed bioreactor - Kashid, Shweta; Joshi, Kalpana; Nene, Sanjay (Biocatalysis and Agricultural Biotechnology, 2022)
<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">The fluidised bed reactors are successfully utilised in various bioprocesses to produce <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/high-value-products" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about high value products from ScienceDirect's AI-generated Topic Pages">high value products using <a class="topic-link" href="https://www.sciencedirect.com/topics/immunology-and-microbiology/immobilized-cell" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about immobilised cells from ScienceDirect's AI-generated Topic Pages">immobilised cells and enzymes. The present work aims at evaluating hydrodynamic characteristics of a three phase fluidised bed <a class="topic-link" href="https://www.sciencedirect.com/topics/immunology-and-microbiology/bioreactor" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about bioreactor from ScienceDirect's AI-generated Topic Pages">bioreactor using Tulsion® A-1X MP, Tulsion® ADS-400 and Tulsion® ADS-800, <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/polystyrene" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about polystyrene from ScienceDirect's AI-generated Topic Pages">polystyrene and polyacrylic based three types of free and <a class="topic-link" href="https://www.sciencedirect.com/topics/immunology-and-microbiology/immobilized-cell" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about immobilised cells from ScienceDirect's AI-generated Topic Pages">immobilised cells solid carriers viz. and comparing their performance with Siran® SIKUG41 glass beads. The hydrodynamic parameters such as particle density (cells and beads), drag coefficient, minimum and maximum <a class="topic-link" href="https://www.sciencedirect.com/topics/immunology-and-microbiology/fluidization" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about fluidisation from ScienceDirect's AI-generated Topic Pages">fluidisation velocity, particle settling velocity were estimated and compared in water and biological media (E2 and MSM) having varying rheological properties. The relationships between drag coefficient (C<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif;">D<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">)–Reynolds numbers (N<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif;">Re<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">), superficial liquid velocity (U<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif;">f<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">)–void fraction(ε), expansion index(n)–N<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif;">Re<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;"> were obtained.

Competing intra- vs intermolecular nitrene transfer in the [Au]-catalysed reaction of 2-alkynylphenylazides - Dhote, Pawan S.; Ramana, V. Chepuri (Advanced Synthesis & Catalysis, 2022)
The possibility of interrupting the gold-catalysed intramolecular cyclization of 2-alkynylphenylazide derivatives, employing known nitrene transfer reagents such as anthranil and its isomer 1,2-benzisoxazole, has been attempted in search of developing simple tools for product diversification. With 1,2-benzisoxazoles, the intermolecular nitrene transfer leading to quinazoline is competitive with intramolecular azidoalkyne cyclization resulting in spiro indol-3-ylidene derivatives. However, in case of the reaction in the presence of anthranil, both intra- and intermolecular nitrene transfer processes result in the same product indol-3-ylidene.
Keywords: 2-Benzisoxazole; Anthranil and 1; Gold catalysis; Nitrene Transfer; Quinazoline

Composition and surface morphology invariant high on-off ratio from an organic memristor - Betal, Atanu; Bera, Jayanta; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Electronic Materials, 2022)
Material composition plays a crucial role in the device performance; thus, nonvolatile memory devices from a small molecule named 5-mercapto-1-methyl tetrazole (MMT) in an insulating polymer matrix of poly(4-vinyl pyridine) (PVP) were fabricated. The composition of the active material in the device was varied to observe its influence on the device's electronic properties. The device with a more or less weight ratio of MMT has a much smoother surface morphology, whereas when the contributions of MMT and PVP were equal, the average surface roughness increased. However, the maximum on-off current ratio for all the devices is 10(5), suggesting that the MMT molecule does not show any change in its characteristic properties when surrounded by an insulating material. When the device was fabricated without the polymer matrix, the surface morphology of the device completely changed as it was filled with large holes. These holes provide short-circuited pathways for the current by forming the direct metal contact between the top and bottom electrodes. The carrier transport through these devices follows various conduction mechanisms. Some of the dominating conduction mechanisms are direct tunneling and trap-free and trap-assisted space-charge-limited conduction.
Keywords: Nonvolatile memory; Polymer; small molecule; space-charge; tunneling

Computational insights into hydroboration with acyclic alpha-Borylamido-germylene and stannylene catalysts: Cooperative dual catalysis the key to system efficiency - Banerjee, Subhrashis; Vanka, Kumar (Polyhedron, 2022)
The chemistry of low valent main group compounds has grown as an alternative to the chemistry of less abundant and less green transition metal complexes. It has been found that low valent compounds such as carbenes, silylenes, stannylenes and germylenes are efficient for activating small molecules and for catalysis. However, the reaction mechanism and the factors that affect the rate of reaction are not completely understood. In this computational investigation with density functional theory (DFT), we investigate and demonstrate the efficiency of a new mechanism for the hydroboration of aldehydes by germylenes and stannylenes, in the presence of the common hydroborating agent, pinacolborane, HBpin. This mechanism involves an HBpin molecule as an additional catalyst that cooperates with the germylene or stannylene catalyst to efficiently carry out the hydroboration. This mechanism is first demonstrated to work for experimentally reported systems, and then shown to be efficient for newly proposed germylene and stannylene systems. These new systems are alpha-Borylamido-germylene ((2,6-iPr(2)C(6)H(3)NBCy(2))(2)Ge(II)) and alpha-Borylamido-stannylene((2,6-iPr(2)C(6)H(3)NBCy(2))(2)Sn(II)). These new insights will help researchers look into low valent germylene and stannylene chemistry from a new perspective.
Keywords: Catalysis of hydroboration; computational chemistry; Germylenes and stannylenes; Main group chemistry; New mechanism

Concerted effect of Ni-in and S-out on ReS2 nanostructures towards high-efficiency oxygen evolution reaction - Das, Tapas K.; Ping, Tapan; Mohapatra, Manoj; Anwar, Shahid; Gopinath, Chinnakonda S.; Jena, Bikash Kumar (Chemical Communications, 2022)
Herein, a one-step hydrothermal reaction is developed to synthesize a Ni-doped ReS2 nanostructure with sulphur defects. The material exhibited excellent OER activity with a current density of 10 mA cm(-2) at an overpotential of 270 mV, a low Tafel slope of 31 mV dec(-1), and good long-term durability of 10 h in 1 M KOH. It shows high faradaic efficiency of 96%, benefiting from the rapid charge transfer caused by the concerted effect of Ni-in and S-out on the ReS2 nanostructure.

Concise total synthesis of (+)-lanceolactone a: revision of absolute stereochemistry - Borade, Balasaheb R.; Kontham, Ravindar (Journal of Organic Chemistry, 2022)
A chiral-pool protecting-group-free five-step total synthesis of tetranorsesquiterpenoide (+)-lanceolactone A and all of its four stereoisomers using (S)-(+)-, and (R)-(-)-linalool (coriandrol) as building blocks is disclosed. The key steps involved in this synthetic route are regioselective ozonolysis, Au(I)-catalyzed cycloisomerization-induced construction of furan from alleneone, and dye-sensitized photo-oxidation (through O-1(2) ; singlet oxygen) of hydroxyalkyl-tethered furan to access oxaspirolactone. After a thorough evaluation of electronic circular dichroism (ECD) and optical rotation data of all possible stereoisomers, the absolute configuration of natural lanceolactone A at the C4 and C7 positions has been assigned as (+)-(4S,7S), which is an enantiomer to the initially proposed structure (+)-(4R,7R). Further, these investigations led us to extend Feringa and Gawronski's CD correlation method to [5,5]- and [6,5]-oxaspirolactones.

Concurrent polyvalent interaction and electrocatalysis to improve lithium-sulfur battery performance - Kumar, Subramani; Krishnamoorthy, Kothandam (Batteries & Supercaps, 2022)
Batteries with improved efficiency are desired. Li-S batteries are attractive due to their high specific capacity and energy density. However, sluggish sulfur redox reaction and polysulfide dissolution are significant challenges in Li-S batteries. In this work, we report graphene with doped layer to electrocatalyze the sluggish sulfur redox reaction. The doped layer comprises heteroatoms such as either N or N and S. The doped layer also comprises cations of Ni. We have chosen a ``doped layer on graphene'' over ``doped graphene'' to avoid defects in the basal plane of graphene. We found the doped layer comprising graphene (DLC-G) to electrocatalyze the polysulfide redox reaction. However, the interaction between the doped layer and polysulfide is still weak, hence the dissolution is not suppressed. To circumvent the polysulfide dissolution, graphene with cationic layer was prepared. We found that cations in the layer electrostatically attract the polysulfides due to the polyvalent interaction. Thus, the dissolution is suppressed. While using this material in the Li-S batteries, the specific capacity, energy density and power density were found to be 1345 mAh g(-1), 782 Wh kg(-1) and 4437 W kg(-1), respectively.
Keywords: electrocatalysis; graphene; lithium-sulfur battery; mechanical exfoliation; polyvalent interaction

Co-Ni layered double hydroxide for the electrocatalytic oxidation of organic molecules: an approach to lowering the overall cell voltage for the water splitting process - Shilpa, Nagaraju; Pandikassala, Ajmal; Krishnaraj, Perayil; Walko, Priyanka S.; Devi, R. Nandini; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2022)
Electrocatalytic oxidation of simple organic molecules oilers a promising strategy to combat the sluggish kinetics of the water oxidation reaction (WOR). The low potential requirement, inhibition of the crossover of gases, and formation of value-added products at the anode are benefits of the electrocatalytic oxidation of organic molecules. Herein, we developed cobalt-nickel-based layered double hydroxide (LDH) as a robust material for the electrocatalytic oxidation of alcohols and urea at the anode, replacing the WOR. A facile synthesis protocol to form LDHs with different ratios of Co and Ni is adapted. It demonstrates that the reactants could be efficiently oxidized to concomitant chemical products at the anode. The half-cell study shows an onset potential of 1.30 V for benzyl alcohol oxidation reaction (BAOR), 1.36 V for glycerol oxidation reaction (GOR), 1.33 V for ethanol oxidation reaction (EOR), and 1.32 V for urea oxidation reaction (UOR) compared with 1.53 V for WOR. Notably, the hybrid electrolyzer in a full-cell configuration significantly reduces the overall cell voltage at a 20 mA cm(-2) current density by similar to 15% while coupling with the BAOR, EOR, and GOR and similar to 12% with the UOR as the anodic half-cell reaction. Furthermore, the efficiency of hydrogen generation remains unhampered with the types of oxidation reactions (alcohols and urea) occurring at the anode. This work demonstrates the prospects of lowering the overall cell voltage in the case of a water electrolyzer by integrating the hydrogen evolution reaction with suitable organic molecule oxidation.
Keywords: electrocatalytic oxidation; energy conversion; imidazole mediated; Layered compounds; water splitting

Construction of tetrahydrobenzo[f]quinoline scaffolds via polar [4+2]-Cycloaddition reaction with arynes as dienophiles - Pandya, Virat G.; Mhaske, Santosh B. (Tetrahedron Letters, 2022)
A transition-metal-free route has been developed for the direct synthesis of biologically significant tetrahydrobenzo[f]quinoline scaffolds. The reaction features polar [4 + 2] Diels-Alder cycloaddition reaction of arynes with a well-designed diene N-Boc protected vinyl tetrahydropyridine, followed by the isomerisation of the double bond leading to the formation of tetrahydrobenzo[f]quinoline scaffolds in good to moderate yields.
Keywords: Aryne; Diels-Alder; Diene; Tetrahydrobenzo[ f ]quinoline

Controlled exchange bias behavior of manganese nanoparticles - Tiwari, Garima; Vinod, C. Prabhakaran; Jagirdar, Balaji R. (Journal of Magnetism and Magnetic Materials, 2022)
Mn(0) colloids were synthesized by solvated metal atom dispersion approach utilizing hexadecylamine, toluene, and THF as coordinating ligands. Mn-toluene and Mn-THF nanoparticles were found to be highly pyrophoric in nature and demand careful handling whereas, Mn-HDA nanoparticles undergo slow oxidation. TEM micrographs revealed formation of nanoparticles between 3 and 6 nm. Magnetic studies of these three samples displayed shift in the field-cooled M-H hysteresis loop which has been attributed to exchange bias behavior. The exchange bias field, HE measured at 5 K varies with change in coordinating ligands around the Mn center which are 1217 Oe, 4408 Oe and, 6350 Oe for Mn-HDA, Mn-toluene and Mn-THF nanoparticles, respectively. The large exchange bias field has been attributed to the presence of uncompensated antiferromagnetic surface spins and the exchange interactions at the nanoparticle surface due to surface oxidation.
Keywords: Antiferromagnetism; exchange bias; Ferromagnetism; Manganese nanoparticles; Uncompensated spins

Controlled modulation of the structure and luminescence properties of zero-dimensional manganese halide hybrids through structure-directing metal-ion (Cd2+ and Zn2+) centers - Das, Deep Kumar; Bakthavatsalam, Rangarajan; Anilkumar, Vishnu; Mali, Bhupendra P.; Ahmed, Md Soif; Raavi, Sai Santosh Kumar; Pallepogu, Raghavaiah; Kundu, Janardan (Inorganic Chemistry, 2022)
Zero-dimensional (0D) metal halide hybrids with high exciton binding energy are excellent materials for lighting applications. Controlling/modulating the structure of the con-stituent metal halide units allows tunability of their photo-luminescence properties. 0D manganese halide hybrids are currently attracting research efforts in lighting applications due to their eco-friendly and strong emission. However, structural transformation-induced tunability of their photophysical propertieshas rarely been reported. Herein, we demonstrate a rationalsynthetic strategy to modulate the structure and luminescenceproperties of 0D Mn(II) halide hybrids utilizing the structure-directing d10metal ions (Cd2+/Zn2+). 0D metal halide hybrids ofCd2+/Zn2+, which act as hosts with tunable structures, accept Mn2+ions as substitutional dopants. This structural flexibility of thehost d10metal ions is realized by optimizing the metal-to-ligand ratio (Cd/AEPip). This reaction parameter allows structuraltransformation from an octahedral (AEPipCdMnBrOh) to a tetrahedral (AEPipCdMnBrTd) 0D Mn halide hybrid with tunableluminescence (orange -> green) with high photoluminescence quantum yield. Interestingly, when Zn2+is utilized, a tetrahedralAEPipZnMnBr structure forms exclusively with strong green emission. Optical and single-crystal X-ray diffraction structural analysisof the host and the doped system supports our experimental data and confirms the structure-directing role played by Cd2+/Zn2+centers. This work demonstrates a rational strategy to modulate the structure/luminescence properties of 0D Mn(II) halide hybrids, which can further be implemented for other 0D metal halide hybrids

Conventional and microwave-assisted organic synthesis of novel antimycobacterial agents bearing furan and pyridine hybrids - Desai, Nisheeth C.; Bhatt, Kandarp; Jadeja, Dharmpalsinh J.; Mehta, Harsh K.; Khedkar, Vijay M.; Sarkar, Dhiman (Drug Development Research, 2022)
Drug resistance in tuberculosis poses a serious threat to humanity because currently available antitubercular drugs are ineffective against Mycobacterium tuberculosis (M. tuberculosis). As a result, the approval of Bedaquiline and Delamanid for the treatment of drug-resistant tuberculosis was accelerated. Still, there is an urgent need to search for new antitubercular drugs with novel mechanisms of action (MoA). Due to this, we have designed a synthetic strategy by utilizing microwave-assisted organic synthesis. We have compared our method with the conventional procedure, and the data show that our procedure is more effective in the preparation of title compounds. A unique series of 1-(2-(furan-2-yl)-5-(pyridin-4-yl)-1,3,4-oxadiazol-3(2H)-yl)-3-(aryl)-pr op-2-en-1-ones (5a-o) was synthesized utilizing conventional and microwave-assisted techniques. Synthetic compounds were investigated for antitubercular activity against Mycobacterium TB H37Ra and Mycobacterium bovis (M. bovis). Compound 5b was reported to be the most effective against M. tuberculosis H37Ra (97.69 percent inhibition at 30 mu g/ml) and M. bovis (97.09 percent inhibition at 30 mu g/ml). An in silico binding affinity study of mycobacterial enoyl-acyl carrier protein reductase (InhA) reveals the binding mechanism and thermodynamic interactions that determine these molecule's binding affinity. Compound 5b had a high glide score of -8.991 and low glide energy of -49.893 kcal/mol.
Keywords: Antitubercular activity; microwave-assisted organic synthesis; Molecular docking

Coordination flexibility aided CO2-specific gating in an iron isonicotinate MOF - Singh, Himan Dev; Nandi, Shyamapada; Chakraborty, Debanjan; Singh, Kirandeep; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Chemistry-an Asian Journal, 2022)
Coordination flexibility assisted porosity has been introduced into an Iron-isonicotinate metal-organic framework (MOF), (Fe(4-PyC)(2) . (OH). The framework showed CO2-specific gate opening behavior, which gets tuned as a function of temperature and pressure. The MOF ` s physisorptive porosity towards CO2, CH4, and N-2 was investigated; it adsorbed only CO2 via a gate opening phenomenon. The isonicotinate, representing a borderline soft base, is bound to the hard Fe3+ centre through monodentate carboxylate and pyridyl nitrogen. This moderately weak binding enables isonicotinate to spin like a spindle under the CO2 pressure opening the gate for a sharp increase in CO2 uptake at 333 mmHg (At 298 K, the CO2 uptake increases from 0.70 to 1.57 mmol/g). We investigated the MOF ` s potential for CO2/N-2 and CO2/CH4 gas separation aided by this gating. IAST model reveals that the CO2/N-2 selectivity jumps from 325 to 3131 when the gate opens, while the CO2/CH4 selectivity increases three times. Interestingly, this Fe-isonicotinate MOF did not follow the trend set by our earlier reported Hard-Soft Gate Control (established for isostructural M2+-isonicotinate MOFs (M=Mg, Mn)). However, we account for this discrepancy using the different oxidation state of metals confirmed by X-ray photoelectron spectroscopy and magnetism.
Keywords: CO2 capture; flexible MOF; gating; Isonicotinic

Copper(II) import and reduction are dependent on His-Met clusters in the extracellular amino terminus of human copper transporter-1 - Kar, Sumanta; Sen, Samarpita; Maji, Saptarshi; Saraf, Deepashri; Ruturaj; Paul, Rupam; Dutt, Sohini; Mondal, Basudeb; Rodriguez-Boulan, Enrique; Schreiner, Ryan; Sengupta, Durba; Gupta, Arnab (Journal of Biological Chemistry, 2022)
Copper(I) is an essential metal for all life forms. Though Cu(II) is the most abundant and stable state, its reduction to Cu(I) via an unclear mechanism is prerequisite for its bioutilization. In eukaryotes, the copper transporter-1(CTR1) is the primary high-affinity copper importer, although its mechanism and role in Cu(II) reduction remain uncharacterized. Here we show that extracellular amino-terminus of human CTR1 contains two methionine-histidine clusters and neighboring aspartates that distinctly bind Cu(I) and Cu(II) preceding its import. We determined that hCTR1 localizes at the basolateral membrane of polarized MDCK-II cells and that its endocytosis to Common-Recycling-Endosomes is regulated by reduction of Cu(II) to Cu(I) and subsequent Cu(I) coordination by the methionine cluster. We demonstrate the transient binding of both Cu(II) and Cu(I) during the reduction process is facilitated by aspartates that also act as another crucial determinant of hCTR1 endocytosis. Mutating the first Methionine cluster ((7)Met-Gly-Met(9)) and Asp(13)( )abrogated copper uptake and endocytosis upon copper treatment. This phenotype could be reverted by treating the cells with reduced and nonreoxidizable Cu(I). We show that histidine clusters, on other hand, bind Cu(II) and are crucial for hCTR1 functioning at limiting copper. Finally, we show that two N-terminal His-Met-Asp clusters exhibit functional complementarity, as the second cluster is sufficient to preserve copper-induced CTR1 endocytosis upon complete deletion of the first cluster. We propose a novel and detailed mechanism by which the two His-Met-Asp residues of hCTR1 amino-terminus not only bind copper, but also maintain its reduced state, crucial for intracellular uptake.

Covalent organic framework with electrodeposited copper nanoparticles - a desirable catalyst for the Ullmann coupling reaction - Chandran, Chandana; Singh, Himan Dev; Leo, Liya S.; Shekhar, Pragalbh; Rase, Deepak; Chakraborty, Debanjan; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Journal of Materials Chemistry A, 2022)
A covalent organic framework is a porous covalently-linked polymeric assembly built from molecular lego blocks, the monomers. A COF's high surface area, ordered pores, and intrinsic low density makes it a perfect heterogeneous catalyst component. Dispersing catalytic metal nanoparticles into the porous COF matrix in a `capping-agent-free' manner can aid the maximal utilization of the active sites. To generate single-site catalysts, metals have been anchored to dense supports, or metal ions have been coordinated to the porous organic framework. The latter has superior atom efficiency and a substrate diffusion advantage. Stably nestling neutral metallic clusters into open-framework supports with no specifically strong binding groups requires a different approach. If infused from extremely dilute electrolytes, metal clusters can be nanoconfined into electrically activated COFs. At low-loadings, it can resemble a single-site catalyst with high atom efficiency. Herein, we report the larger scale synthesis of IISERP-COF15 and electrochemical loading of copper nanoparticles into its pores at loadings as low as 3.34 wt%. We employed classical Ullmann reactions to adjudge its activity. Typical turnover numbers for the catalysts reported in the literature are approximately 50-100. A Cu@COF shows high activity with a very low catalyst loading of 0.25 mol% (TON around similar to 300-350 vs. 4 for neat CuCl2 center dot 2H(2)O (homogeneous catalyst) and turnover frequency (similar to 15-17 h(-1))). We recycled it for up to 3 cycles. Furthermore, we report a multi-fold Ullmann reaction producing an unreported hexaaldehyde to demonstrate the latitude of the catalyst. Our work points to the potential of a dilutely loaded metal@COF as a mimic of the single-site catalyst for synthesizing valuable C-O linked molecules. Our findings from computational modeling shed light on the role of the COF as an active nanoporous support for Ullmann C-O coupling.

COVID-19 associated mucormycosis: evolving technologies for early and rapid diagnosis - Samson, Rachel; Dharne, Mahesh (3 Biotech, 2022)
The post-coronavirus disease (COVID-19) mucormycosis is a deadly addition to the pandemic spectrum. Although it's a rare, aggressive, and opportunistic disease, the associated morbidity and mortality are significant. The complex interplay of factors aggravating CAM is uncontrolled diabetes, irrational and excessive use of antibiotics, steroids, and an impaired immune system. Recently, India has been witnessing a rapid surge in the cases of coronavirus disease-associated mucormycosis (CAM), since the second wave of COVID-19. The devastating and lethal implications of CAM had now become a matter of global attention. A delayed diagnosis is often associated with a poor prognosis. Therefore, the rapid and early diagnosis of infection would be life-saving. Prevention and effective management of mucormycosis depend upon its early and accurate diagnosis followed by a multimodal therapeutic approach. The current review summarizes an array of detection methods and highlights certain evolving technologies for early and rapid diagnosis of CAM. Furthermore, several potential management strategies have also been discussed, which would aid in tackling the neglected yet fatal crisis of mucormycosis associated with COVID-19.
Keywords: Biosensors; COVID-19; Diagnostics; Mucormycosis; Probiotics

Crystalline xylitol production from corncob biomass with oral toxicity analysis - Ahuja, Vishal; Dasgupta, Diptarka; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; More, Snehal; Gupta, Piyush; Behera, Babita; Bhaskar, Thallada (Industrial Crops and Products, 2022)
Xylitol, a five-carbon sugar alcohol, has a steady global market and finds application as a natural sugar substitute in various food and confectionery products. Biocatalytic xylitol production, although touted as a greener alternative to conventional chemical catalysis, suffers from certain challenges, the primary being high cost of production. This study demonstrates a process for food-grade xylitol production from corncob biomass with energy reduction through two major process modifications. A non-conventional fermentation strategy was adopted whereby adjusting aeration without agitation, xylitol with high yield (0.86 +/- 0.015 g/g), and productivity (0.74 gL(-1)h(-1)) could be produced by a GRAS Pichia caribbica MTCC 5703 strain. Xylitol was recovered from the broth in the form of crystals using a combination of membrane-based filtration and crystallization. The crystals demonstrated similar to 98 % purity when quantified with H-1 NMR. Oral toxicity analysis of the crystals demonstrated no adverse effect in female Winstar rats (at a loading of 2000 mg/kg body weight of animals). Overall process statistics showed that 0.584 kg of food-grade xylitol crystals could be produced from 3.5 kg of corncob biomass. The two-process modifications during fermentation and xylitol recovery enabled an energy saving of similar to 20.842 kW/kg of crystals, providing tremendous advantages for biorefinery-based large-scale xylitol production from corncob biomass.
Keywords: Biomass; Fermentation; Oral toxicity analysis; Wastewater treatment; xylitol

Cyclic peptide engineered from phytocystatin inhibitory hairpin loop as an effective modulator of falcipains and potent antimalarial - Mishra, Manasi; Singh, Vigyasa; Tellis, Meenakshi B.; Joshi, Rakesh S.; Pandey, Kailash C.; Singh, Shailja (Journal of Biomolecular Structure & Dynamics, 2022)
Cystatins are classical competitive inhibitors of C1 family cysteine proteases (papain family). Phytocystatin superfamily shares high sequence homology and typical tertiary structure with conserved glutamine-valine-glycine (Q-X-V-X-G) loop blocking the active site of C1 proteases. Here, we develop a cysteine-bounded cyclic peptide (CYS-cIHL) and linear peptide (CYS-IHL), using the conserved inhibitory hairpin loop amino acid sequence. Using an in silico approach based on modeling, protein-peptide docking, molecular dynamics simulations and calculation of free energy of binding, we designed and validated inhibitory peptides against falcipain-2 (FP-2) and -3 (FP-3), cysteine proteases from the malarial parasite Plasmodium falciparum. Falcipains are critical hemoglobinases of P. falciparum that are validated targets for the development of antimalarial therapies. CYS-cIHL was able to bind with micromolar affinity to FP-2 and modulate its binding with its substrate, hemoglobin in in vitro and in vivo assays. CYS-cIHL could effectively block parasite growth and displayed antimalarial activity in culture assays with no cytotoxicity towards human cells. These results indicated that cyclization can substantially increase the peptide affinity to the target. Furthermore, this can be applied as an effective strategy for engineering peptide inhibitory potency against proteases.
Keywords: Cyclic peptide; falcipain inhibitors; falciparum; P; Phytocystatin; protein interaction mimics; protein&#8211

Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT): a 3D sandwiched frameworks with efficient hydrogen production - Kumar, Praveen; Bajpai, Himanshu; Luwang, Meitram Niraj (Journal of Catalysis, 2023)
For over a decade, the structure, reactivity, and mechanism of graphene based photocatalysts have been of great interest for hydrogen (H2) generation. Several studies have been done on the edge side groups (ESGs) of graphene oxide (GO), but the basal plane groups (BPGs)-epoxide and hydroxide have acquired far less attention. This is because the GO layers are strongly held with van der waals forces as well as H-bonding which prevents the foreign body from entering inside the layers. To overcome these problems, this study presents the successful synthesis and application of four coordinated sandwiched (FCS) Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT) in rGO-CdS composite (A 3D sandwiched frame-work). Additionally, experimental outcomes have been further supported using density functional theory (DFT), which suggest that CdOTOT is more stable than its precursors as well as thermodynamically favourable. The CdOTOT shows high H2 production activity -67.5 mmol/g or 13.5 mmol/g/h in presence of 1 % Pt cocatalyst and sacrificial reagents (Na2S/Na2SO3). It is around 33 times higher than pristine CdS, and stable up to around 15 hrs without adding any cocatalyst. This mesmerising outcome is over with reported various CdS-rGO based photocatalysts. The higher activity was further explained through the proposed mechanism and observed low electronic work function of CdOTOT. This innovative and extend-able (with other metals) approach provides a revolutionary impact on numerous cutting-edge research applications like photocatalysis, water splitting, solar cell, etc.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: 2]; 3D sandwiched frameworks; Basal Plane Groups (BPGs); Cadmium (II) Organo Tetrakis-[1; hydrogen production; Oxathiin (CdOTOT)

Can Li atoms anchored on boron- and nitrogen-doped graphene catalyze dinitrogen molecules to ammonia? a DFT study - Verma, Tushar Singh; Samal, Pragnya Paramita; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (ChemPhysChem, 2023)
The most successful electrochemical conversion of ammonia from dinitrogen molecule reported to date is through a Li mediated mechanism. In the framework of the above fact and that Li anchored graphene is an experimentally feasible system, the present work is a computational experiment to identify the potential of Li anchored graphene as a catalyst for N-2 to NH3 conversion as a function of (a) minimum number of Li atoms needed for anchoring on graphene sheets and (b) the role of chemical modification of graphene surfaces. The studies bring forth an understanding that Li anchored graphene sheets are potential catalysts for ammonia conversion with preferential adsorption of N-2 through end-on configuration on Li atoms anchored on doped and pristine graphene surfaces. This mode of adsorption being characteristic of Nitrogen Reduction Reaction (NRR) through enzymatic pathway, examination of the same followed by analysis of electronic properties demonstrates that tri-Li atoms (Tri Atom Catalysts, TACs) are more efficient as catalysts for NRR as compared to two Li atoms (Di Atom Catalysts, DACs). Either way, the rate determining step was found to be *NH2 ->*NH3 step (mixed pathway) with Delta G(max)=1.02 eV and *NH2-*NH3 ->*NH2 step (enzymatic pathway) with Delta G(max)=1.11 eV for 1B doped TAC and DAC on graphene sheet, respectively. Consequently, this work identifies the viability of Li anchored graphene based 2-D sheets as hetero-atom catalyst for NRR.
Keywords: computational chemistry; Graphene Sheet; heterogeneous catalysis; Li Nanoparticles; Nitrogen Reduction Reaction

Can metal cations electrocatalyze sulfur redox reaction and suppress polysulfide shuttle? - Kumar, Subramani; Swain, Gitanjali; Krishnamoorthy, Kothandam (Batteries & Supercaps, 2023)
In lithium-sulfur (Li-S) batteries, sulfur undergoes various changes. It switches between cyclic structure and linear structure. The charge on the sulfur varies between a neutral state and a negative charge-bearing state. Due to these changes, the sulfur/polysulfide dissolves in the battery electrolyte. Furthermore, the kinetics of the sulfur redox reaction is sluggish. Therefore, a material that can suppress sulfur/polysulfide dissolution and electrocatalyze sulfur redox reaction is needed. We hypothesize that the polysulfide dissolution can be suppressed if the host exhibits polyvalent electrostatic attraction. Polysulfide is a negative charge-bearing molecule; hence the host must comprise multiple positive charges. Nickel cations with other heteroatoms have been explored as a host in Li-S batteries. The heteroatoms impart additional interactions. The easier way to circumvent the effect of heteroatoms is the addition of metal salts. However, metal salts can either exhibit monovalent or divalent attraction with polysulfides. Those interactions are weak and we must have polyvalent interaction. Towards this objective, we have designed and synthesized a material that comprises multiple divalent cations that is also devoid of heteroatoms. The Li-S batteries fabricated using the metal cation immobilized graphene showed a maximum specific capacity of 1022 mAh/g at 0.1 C rate. Among the metal cations, nickel cations showed better performance than cobalt cations. Thus, we demonstrate that metal cations immobilized on Graphene can efficiently electrocatalyze the sluggish sulfur redox reaction and suppress the polysulfide dissolution.
Keywords: electrocatalysis; graphene; lithium-sulfur batteries; metal cations; polysulfides

Carbohydrate recognition using metal-ligand assemblies - Ahamed, Rafiq; Venkatesh, Jayashree; Srithar, Rakshantha; Gaikwad, Sudhakar; Pramanik, Susnata (Organic & Biomolecular Chemistry, 2023)
Carbohydrate-binding proteins, known as lectins, play a wide range of vital roles in cellular and pathological processes. Mimicking lectins to achieve specific molecular recognition of carbohydrates in organic and aqueous media using artificial receptors is challenging due to the synthetic hurdles of receptors and structural similarities between sugars. Carbohydrate recognition using non-covalent interactions remains a vast topic. This review summarises the recognition of carbohydrates using metal-ligand assemblies, including metallosupramolecules, macrocycles, and cages. It also highlights the challenges and future directions in the field.

Carbon black and chitin nanofibers for green tyres: preparation and property evaluation - Mathew, Mariya; Dominic, C. D. Midhun; Neenu, K. V.; Begum, P. M. Sabura; Dileep, P.; Kumar, T. G. Ajith; Sabu, Akshay Alax; Nagane, Dhiraj; Parameswaranpillai, Jyotishkumar; Badawi, Michael (Carbohydrate Polymers, 2023)
This research highlights the synergistic use of carbon black (CB) and chitin nanofibers (CHNFs) for developing green tyres for the first time. The CHNFs (12-30 nm) were prepared from chitin powder with the help of steam explosion and mild oxalic acid hydrolysis. The CHNFs were uniformly dispersed in natural rubber (NR) latex, dried, and mixed with CB in a two-roll mill to form NR/CB/CHNF composites. The NR/CB/CHNF composite at 1 phr CHNF loading exhibited tensile and tear strengths that were about 47 and 160 % greater than the NR-Neat, respectively. The dynamic mechanical analysis showed that the loss tangent (tan delta) at 60 degrees C was 50 % lower for the NR/CB/CHNF 1.0 composite than for the NR/CB50 composite. The study succeeded in developing a new green tyre tread formulation that would be helpful for attaining sustainability and a circular economy.
Keywords: carbon black; Chitin nanofibers; Green Tyre; natural rubber latex

Carbon encapsulated NiCo2S4 nanoparticles with enhanced surface mediated charge storage for superior ultracapacitor electrodes - Chaturvedi, Vikash; Pawar, Meenakshi; Thripuranthaka, M.; Shivade, Rajkiran; Shelke, Manjusha V. V. (Chemistry-An Asian Journal, 2023)
Three different compositions of NiCo2S4 (NCS) materials were prepared using three solvents, named NCS HTDI (hydrothermal in DI water), NCS STEG (solvothermal in ethylene glycol), and a novel carbon-encapsulated NCS STFA (solvothermal in formamide). The structural and morphological properties of the prepared NCS HTDI, NCS STEG, and NCS HTDI materials were analyzed using various physical characterization techniques. As prepared, NCS materials were tested as an electrode for supercapacitor (SC) application using a 3-electrode system in a basic electrolyte (3 M KOH). NCS HTDI exhibits a specific capacitance of 2536 F g(-1), NCS STEG shows 1355 F g(-1), and NCS STFA shows 1178 F g(-1) at an input current density of 1 A g(-1). The SBN-PSC material is utilized as a counter electrode in the NCS STFA || SBN-PSC-based asymmetric SC device. The device exhibits exceptionally superior electrochemical performance with a specific capacitance of 172 F g(-1) at 10 A g(-1) input current density and 97% capacity retention after 5000 cycles in a voltage window of 1.6 V. The results confirm the superiority of NCS STFA||SBN-PSC deviceas an excellent high-energy and high-power SC.
Keywords: Asymmetric supercapacitor device; NiCo2S4; pseudocapacitor; Surface charge storage

Catalyst-assisted selective vinylation and methylallylation of a quaternary carbon center using tert-butyl acetate - Mohanta, Nirmala; Samal, Pragnya Paramita; Pandey, Akanksha M.; Mondal, Shankhajit; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Journal of Organic Chemistry, 2023)
The In-(OTf)(3)-catalyzed & alpha;-vinylationof varioushydroxy-functionalized quaternary carbon centers using in situ generatedisobutylene from tert-butyl acetate is presentedas a novel synthetic methodology. Moreover, tert-butylacetate is a nonflammable feed stock and is a readily available sourcefor the in situ production of vinyl substituents, as demonstratedby the vinylation reaction with quaternary hydroxy/methoxy compounds.Moreover, an excellent selectivity for methylallylation over vinylationwas obtained with Ni-(OTf)(2) as a catalyst. In the case ofperoxyoxindole, methylallyl-functionalized 1,4-benzoxazin-3-one derivativeswere formed through the sequential rearrangement of peroxyoxindolefollowed by the nucleophilic attack by isobutylene. The detailed mechanismfor this reaction and rationalization for the selectivity are providedusing kinetics and density functional theory studies.

C-H functionalization of pyridines - Maity, Susmita; Bera, Asish; Bhattacharjya, Ayantika; Maity, Pradip (Organic & Biomolecular Chemistry, 2023)
Pyridine and its reduced form (piperidine) are the most common nitrogen heterocycles in FDA-approved drugs. Additionally, their presence in alkaloids, ligands for transition metals, catalysts, and organic materials with various properties makes them among the most important structural cores. Despite its importance, direct and selective functionalization of pyridine remains scarce due to its electron-poor nature and nitrogen coordination power. Instead, functionalized pyridine rings were primarily constructed from suitably substituted acyclic precursors. The focus on sustainable chemistry with minimum waste generation encourages chemists to develop direct C-H functionalization. This review summarizes different approaches to tackle the reactivity and regio- and stereoselectivity aspects for direct pyridine C-H functionalization.

Challenges and emerging strategies for next generation liposomal based drug delivery: an account of the breast cancer conundrum - Moudgil, Aliesha; Salve, Rajesh; Gajbhiye, Virendra; Chaudhari, Bhushan P. (Chemistry and Physics of Lipids, 2023)
The global cancer burden is witnessing an upsurge with breast cancer surpassing other cancers worldwide. Furthermore, an escalation in the breast cancer caseload is also expected in the coming years. The conventional therapeutic regimens practiced routinely are associated with many drawbacks to which nanotechnological in-terventions offer a great advantage. But how eminent could liposomes and their advantages be in superseding these existing therapeutic modalities? A solution is reflected in this review that draws attention to a decade-long journey embarked upon by researchers in this wake. This text is a comprehensive discussion of liposomes, the front runners of the drug delivery systems, and their active and passive targeting approaches for breast cancer management. Active targeting has been studied over the decade by many receptors overexpressed on the breast cancer cells and passive targeting with many drug combinations. The results converge on the fact that the actively targeted formulations exhibit a superior efficacy over their non-targeted counterparts and the all lipo-somal formulations are efficacious over the free drugs. This undoubtedly underlines the dominion of liposomal formulations over conventional chemotherapy. These investigations have led to the development of different liposomal formulations with active and passive targeting capacities that could be explored in depth. Acknowl-edging and getting a deeper insight into the liposomal evolution through time also unveiled many imperfections and unchartered territories that can be explored to deliver dexterous liposomal formulations against breast cancer and more in the clinical trial pipeline.
Keywords: Breast cancer; Liposomal metamorphosis; Receptor-ligand dynamics; Targeted Drug Delivery

Charge trapped CdS quantum dot embedded polymer matrix for a high speed and low power memristor - Betal, Atanu; Bera, Jayanta; Sharma, Ashish; Rath, Arup K. K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2023)
The data storage requirement in the digital world is increasing day by day with the advancement of the internet of things. In this respect, nonvolatile resistive random-access memory is an option that provides high density and low power data storage capabilities. In this work, zero-dimensional colloidal CdS quantum dots and a polymer composite at an appropriate ratio were used to fabricate a memristive device. Comparison with a pristine CdS quantum dot-based device reveals that a surrounding matrix around the quantum dots is needed for observing memristive behavior. The quantum dots embedded in the polymer matrix device showed extremely stable electrical switching behavior that can be operated for more than 300 cycles and 60 000 seconds. Moreover, the device needs extremely low power to operate at a very high speed. The smooth surface morphology dictates a charge trapping mechanism for the switching phenomenon; however, an interplay between different charge transport mechanisms leads to the fast switching and high on-off ratio of the device.

Chemical bridge-mediated heterojunction electron transport layers enable efficient and stable perovskite solar cells - Patil, Pramila; Maibam, Ashakiran; Sangale, Sushil S.; Mann, Dilpreet Singh; Lee, Hyun-Jung; Krishnamurty, Sailaja; Kwon, Sung-Nam; Na, Seok-In (ACS Applied Materials and Interfaces, 2023)
Perovskite solar cells (PSCs) emerged as potential photovoltaicenergy-generating devices developing in recent years because of theirexcellent photovoltaic properties and ease of processing. However,PSCs are still reporting efficiencies much lower than their theoreticallimits owing to various losses caused by the charge transport layerand the perovskite. In this regard, herein, an interface engineeringstrategy using functional molecules and chemical bridges was appliedto reduce the loss of the heterojunction electron transport layer.As a functional interface layer, ethylenediaminetetraacetic acid (EDTA)was introduced between PCBM and the ZnO layer, and as a result, EDTAsimultaneously formed chemical bonds with PCBM and ZnO to serve asa chemical bridge connecting the two. DFT and chemical analyses revealedthat EDTA can act as a chemical bridge between PCBM and ZnO, passivatedefect sites, and improve charge transfer. Optoelectrical analysisproved that EDTA chemical bridge-mediated charge transfer (CBM-CT)provides more efficient interfacial charge transport by reducing trap-assistedrecombination losses at ETL interfaces, thereby improving device performance.The PSC with EDTA chemical bridge-mediated heterojunction ETL exhibiteda high PCE of 21.21%, almost no hysteresis, and excellent stabilityto both air and light.
Keywords: charge transfer; chemical bridge; electron transport layer; ethylenediaminetetraacetic acid; Perovskite solar cells; trap-assisted recombination

Chemically modified graphene sheets as potential sensors for organophosphate compounds(pesticide): A DFT study - Shivankar, Bhavana R.; Singh, Chandrodai Pratap; Krishnamurty, Sailaja (Applied Surface Science, 2023)
Owing to the extensive use of pesticides in agriculture and the threat posed to the environment and humankind, attention is drawn toward the need for its remediation from various sources, in particular from water. The adsorption characteristics of hydrophobic graphene and its BN doped counterparts are evaluated using DFT methodology, to assess their sensing potential towards notable pesticide molecules (Organophosphate pesticides (OPs) such as chlorpyriphos, parathion, methyl-parathion, and fenitrothion). To accomplish this, various elec-tronic properties such as band structure, DOS, Bader charge analysis, and CDD have been calculated. Interest-ingly, exothermic interactions (-0.1 eV to-2 eV) have been noted for all the OPs with NB doped single vacancy defect induced graphene surfaces. With an exception of FTN, all the other OPs showed significant changes in the electronic properties of surfaces as apparent from the change in band gap and nature of the band from indirect to direct. The appreciable adsorption energy, higher charge transfer, and notable variation in the band gap are the decisive factors behind the strong interaction exhibited by NB doped surfaces especially dg-(NB-2)2 (except FTN). These findings demonstrate the suitability of NB doped single vacancy defect induced graphene sheets for the detection of the studied OPs.
Keywords: Adsorption; BN doped graphene surfaces; Charge density difference; Density functional theory; Organophosphate pesticides

Chemodivergent coupling of azoarenes with benzyl alcohols via a borrowing hydrogen strategy using a well-defined nickel catalyst - Bansal, Sadhna; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2023)
Chemodivergent (de)hydrogenative coupling of azoarenes with benzyl alcohols is achieved via the N=N bond activation using an inexpensive and well-defined (6-OH-bpy)NiCl2 catalyst. This protocol highlights the construction of C-N bonds via a borrowing hydrogen strategy that offers substituted imines and amines. A range of azo compounds couple with various substituted benzyl alcohols in a tandem hydrogenation/dehydrogenation process. The nickel catalyst along with the K2CO3 or (KOBu)-Bu-t base governed the selectivity in imine and amine formation. A preliminary mechanistic study establishes the crucial role of metal-ligand cooperation (MLC) comprising the distinct radical pathways.

Chromatography assisted in-vitro refolding and purification of recombinant peptibody: recombinant romiplostim a case study - Rana, Sunil; Ughade, Santosh; Kumthekar, Rupali; Bhambure, Rahul (International Journal of Biological Macromolecules, 2023)
In-vitro protein refolding is one of the key rate-limiting unit operations in manufacturing of fusion proteins such as peptibodies expressed using E. coli. Dilution-assisted refolding is the most commonly used industrial practice to achieve the soluble, native functional form of the recombinant protein from the inclusion bodies. This study is focused on developing a chromatography-assisted in-vitro refolding platform to produce the biologically active, native form of recombinant peptibody. Recombinant Romiplostim was selected as a model protein for the study. A plug flow tubular reactor was connected in series with capture step affinity chromatography to achieve simultaneous in-vitro refolding and capture step purification of recombinant Romiplostim. Effect of various critical process parameters like fold dilution, temperature, residence time, and Cysteine: DTT ratio was studied using a central composite based design of experiment strategy to achieve a maximum refolding yield of selected peptibody. Under optimum refolding conditions, the maximum refolding yield of 57.0 & PLUSMN; 1.5 % and a purity of over 79.73 & PLUSMN; 3.4 % were achieved at 25-fold dilution, 15 degrees C temperature, 6 h residence time with 6 mM and 10 mM of cysteine and DTT, respectively. The formation of native peptibody structure was examined using various orthogonal analytical tools to study the protein's primary, secondary, and tertiary structure. The amino acid sequence for the disulfide-linked peptide was mapped using collision-induced dissociation (CID) to confirm the formation of interchain disulfide bonds between Cys7-Cys7 and Cys10-Cys10 similarly for intra-chain disulfide bonds between Cys42-Cys102, and Cys148-Cys206. The developed protocol here is a valuable tool to identify high-yield scalable refolding conditions for multi-domain proteins involving inter-domain disulfide bonds.
Keywords: CE-SDS; Disulfide bonds; In-vitro refolding; Peptibody; Romiplostim

CO2 electrolysis towards large scale operation: rational catalyst and electrolyte design for efficient flow-cell - Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (Chemical Communications, 2023)
The electrochemical CO2 reduction reaction (CO2RR) to renewable fuels/chemicals is a potential approach towards addressing the carbon neutral economy. To date, a comprehensive analysis of key performance indicators, such as an intrinsic property of catalyst, reaction environment and technological advancement in the flow cell, is limited. In this study, we discuss how the design of catalyst material, electrolyte and engineering gas diffusion electrode (GDE) could affect the CO2RR in a gas-fed flow cell. Significant emphasis is given to scale-up requirements, such as promising catalysts with a partial current density of >= 100 mA cm(-2) and high faradaic efficiency. Additional experimental hurdles and their potential solutions, as well as the best available protocols for data acquisition for catalyst activity evaluation, are listed. We believe this manuscript provides some insights into the making of catalysts and electrolytes in a rational manner along with the engineering of GDEs towards CO2RR.

Co3O4 for sustainable CO2 reduction and possible fine-tuning towards selective CO production - Ranjan, Ravi; Tekawadia, Jyoti; Jain, Ruchi; Mhamane, Nitin B.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2023)
Two main challenges involved in heterogeneous catalytic CO2 reduction are: (a) decreasing the consumption of H2 to the minimum required level with possibly the maximum CO2 conversion, and (b) concurrently enhancing the selectivity of the desired CO, at the cost of methane. Towards meeting these two challenges, Co3O4 spinel has been identified as a potential catalyst and it exhibits predominant CO selectivity > 673 K at atmospheric pressure. CO2 conversion begins > 523 K, with 100% CO selectivity observed > 673 K with CO2:H2 = 3:2. Current work shows a sustainable catalytic CO2 conversion to 100% CO selectivity with Co3O4-Nanocube (NC). Critically, CO selectivity and yield is observed to increase at the cost of methane with smaller amount of H2. 1:1 and 3:2 CO2:H2 ratio exhibits 88-100% CO selectivity with 24-32.5% CO2 conversion between 623 and 823 K. Irrespective of the input CO2:H2, ratio of CO2:H2 uptake changes from around 1:3 at 523 K to 1:1-1.5 at 823 K with concurrent production of significant methane to predominant CO, respectively. Surface electronic state changes was explored by near ambient pressure photoelectron spectroscopy, and the results suggests that Co3O4 is the active phase that promotes CO2 reduction selectively to CO. Broadening observed with the vibrational feature of the CO2 molecules at high temperature underscores the heterogeneous character of the catalyst surface, under operating conditions, due to changing electron density. By optimizing the gas hourly space velocity (GHSV), H2-lean CO2:H2 ratio, and the reaction temperature/pressure, 100% CO selectivity could be broadened to a range of operating conditions.
Keywords: Carbon neutral economy; heterogeneous catalysis; RWGS; SDG; Surface Science

Cobalt-manganese modified theophrastite phase of nickel hydroxide nanoflower arrays on nickel foam as a self-standing bifunctional electrode for overall water electrolysis - Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Barik, Sidharth; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2023)
Designing and developing self-supported electrodes for water electrolysis is attractive as compared to conventional catalyst-coated electrodes. Herein, a (Co0.3Mn0.1Ni0.6)(OH)(2)/NF nanocomposite is prepared by anchoring (Co0.3Mn0.1Ni0.6)(OH)(2)via simple one-pot hydrothermal synthesis on nickel foam. The presence of Mn induces the external electronic structure of Co(OH)(2), and this also improves the electrochemically active surface area (ECSA). These favor better accessibility of active sites and increased intrinsic activity for the OER and HER. (Co0.3Mn0.1Ni0.6)(OH)(2)/NF has shown promising electrochemical activity toward the OER and HER in a 1 M KOH electrolyte, with an overpotential of 270 mV for the OER and 163 mV for the HER to deliver 10 mA cm(-2) current density. The overall water splitting was performed by employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as both the cathode and anode by displaying a voltage of 1.62 V at 10 mA cm(-2), which is comparable to that extracted from a similar system based on the state-of-the-art Pt/C@NF cathode and RuO2@NF anode (1.60 V at 10 mA cm(-2)) standard electrode pair. Interestingly, at high current densities, the (Co0.3Mn0.1Ni0.6)(OH)(2)/NF//(Co0.3Mn0.1Ni0.6)(OH)(2)/NF system displayed better overall water splitting performance (1.78 V at 100 mA cm(-2)) compared to its Pt/C@NF//RuO2@NF (1.89 V at 100 mA cm(-2)) counterpart while displaying a stable output during the evolution period that lasted for 24 h. The amounts of H-2 and O-2 produced are estimated to be 701.2 and 358.6 mmol, respectively, at a time interval of 1 h; these amounts correspond to an similar to 1 : 2 ratio of O-2 and H-2, respectively. This study confirms the capability for employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as a bi-functional and self-standing electrode for the realistic demonstrations of overall water splitting applications.

Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.

Cocrystallization of multi-kinase inhibitor pazopanib with fenamic acids: improving dissolution and inhibiting cell migration - Rai, Sunil K.; Gunnam, Anilkumar; Roy, Debopriya; Rajput, Raveena; Kulkarni, Kiran; Nangia, Ashwini K. (CrystEngComm, 2023)
A multi-kinase inhibitor, pazopanib (PAZ) is cocrystallized with cyclooxygenase (COX) inhibitor fenamic acids to investigate the dissolution rate and inhibition of cell migration in VEGF-triggered HUVEC cells to test the efficacy of stoichiometric drug-drug combinations. Crystallization experiments at the sub-milligram level in an acetonitrile-methanol mixture yielded two drug-drug salt forms of PAZ with flufenamic acid (FFA) and niflumic acid (NFA) as PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named as form I) and PAZ+center dot NFA-. Structures of the crystal forms were characterized by single crystal X-ray diffraction (SC-XRD) method. Crystal structures revealed that the presence of a 2-aminopyrimidine group in PAZ is a strong partner for the carboxyl group in all solid forms, forming an acidMIDLINE HORIZONTAL ELLIPSISpyrimidine heterosynthon with COX inhibitor fenamic acids. To perform dissolution experiments and cell line analysis, the scale-up of both salt forms were done in the acetonitrile-methanol mixture through crystallization, which showed a polymorphic transformation in the case of PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named form II). The thermodynamic stability of PAZ+center dot FFA-center dot ACN (form II) and PAZ+center dot NFA- were analysed using slurry experiment under ambient conditions in pH 1.2 (0.1 N HCl) buffer medium and the residual solid phase was characterized by powder XRD, which showed that PAZ+center dot FFA-center dot ACN (form II) was a metastable solid form while PAZ+center dot NFA- was a stable solid form. The dissolution experiments at gastric pH 1.2 showed that the rate of dissolution of PAZ+center dot FFA-center dot ACN was 10 times higher than PAZ+center dot NFA-. The cell migration assay suggested that PAZ+center dot FFA-center dot ACN inhibited similar to 25% and PAZ+center dot NFA- inhibited similar to 20% migration of HUVEC cells compared to PAZ alone. These investigations suggested that the drug-drug salts PAZ+center dot FFA- and PAZ+center dot NFA- would be potential combo drug candidates for clinical trials. Multi-drug crystalline salts of pazopanib with fenamic acids exhibit enhanced dissolution and 20% higher inhibition in the migration of HUVEC cells compared to the reference drug.

Cofilin-membrane interactions: electrostatic effects in phosphoinositide lipid binding - Prakash, Shikha; Krishna, Anjali; Sengupta, Durba (ChemPhysChem, 2023)
The actin cytoskeleton interacts with the cell membrane primarily through the indirect interactions of actin-binding proteins such as cofilin-1. The molecular mechanisms underlying the specific interactions of cofilin-1 with membrane lipids are still unclear. Here, we performed coarse-grain molecular dynamics simulations of cofilin-1 with complex lipid bilayers to analyze the specificity of protein-lipid interactions. We observed the maximal interactions with phosphoinositide (PIP) lipids, especially PIP2 and PIP3 lipids. A good match was observed between the residues predicted to interact and previous experimental studies. The clustering of PIP lipids around the membrane bound protein leads to an overall lipid demixing and gives rise to persistent membrane curvature. Further, through a series of control simulations, we observe that both electrostatics and geometry are critical for specificity of lipid binding. Our current study is a step towards understanding the physico-chemical basis of cofilin-PIP lipid interactions.
Keywords: complex membrane; lipid clustering; Martini coarse-grain simulations; Molecular dynamics simulations; Protein-lipid interactions

COF-supported zirconium oxyhydroxide as a versatile heterogeneous catalyst for Knoevenagel condensation and nerve agent hydrolysis - Shekhar, Pragalbh; Devulapalli, Venkata Swaroopa Datta; Reji, Reshma; Singh, Himan Dev; Jose, Aleena; Singh, Piyush; Torris, Arun; Vinod, Chatakudath P.; Tokarz III, John A.; Mahle, John J.; Peterson, Gregory W.; Borguet, Eric; et al. (iScience, 2023)
A composite of catalytic Lewis acidic zirconium oxyhydroxides (8 wt %) and a covalent organic framework (COF) was synthesized. X-ray diffraction and infrared (IR) spectroscopy reveal that COF's structure is pre-served after loading with zirconium oxyhydroxides. Electron microscopy confirms a homogeneous distri-bution of nano-to sub-micron-sized zirconium clusters in the COF. 3D X-ray tomography captures the micron-sized channels connecting the well-dispersed zirconium clusters on the COF. The crystalline ZrOx(OH)(y)@COF's nanostructure was model-optimized via simulated annealing methods. Using 0.8 mol % of the catalyst yielded a turnover number of 100-120 and a turnover frequency of 160-360 h(-1) for Knoevenagel condensation in aqueous medium. Additionally, 2.2 mol % of catalyst catalyzes the hy-drolysis of dimethyl nitrophenyl phosphate, a simulant of nerve agent Soman, with a conversion rate of 37% in 180 min. The hydrolytic detoxification of the live agent Soman is also achieved. Our study unveils COF-stabilized ZrOx(OH)(y) as a new class of zirconium-based Lewis + Bronsted-acid catalysts.

Comparative evaluation of advanced oxidation processes (AOPs) for reducing SARS-CoV-2 viral load from campus sewage water - Pramanik, Rinka; Bodawar, Narendra; Brahme, Aashay; Kamble, Sanjay; Dharne, Mahesh (Journal of Environmental Chemical Engineering, 2023)
Presence of SARS-CoV-2 in wastewater is a major concern as the wastewater meets rivers and other water bodies and is used by the population for various purposes. Hence it is very important to treat sewage water in an efficient manner in order to reduce the public health risk. In the present work, various advanced oxidation processes (AOPs) have been evaluated for disinfection of SARS-CoV-2 from sewage water collected from STP inlet of academic institutional residential. The sewage water was subjected to ten AOPs, which include Ozone (O3), Hydrodynamic cavitation (HC), Ultraviolet radiation (UV), and their hybrid combinations like HC/O3, HC/O3/ H2O2, HC/H2O2, O3/UV, UV/H2O2, UV/H2O2/O3, and O3/H2O2 to reduce SARS-CoV-2 viral load. Further, AOP treated sewage water was subjected to total nucleic acid isolation followed by RT-qPCR for viral load estimation. The sewage water treatment techniques were evaluated based on their viral concentration-reducing efficiency. It was found that ozone and ozone-coupled hybrid AOPs showed the most promising result with more than 98 % SARS-CoV-2 viral load reducing efficiency from sewage water. Interestingly, the best six AOPs used in this study significantly reduced both the SARS-CoV-2 and PMMoV (faecal indicator) viral load and improved water quality in terms of increasing DO and decreasing TOC.
Keywords: AOPs and hybrid AOPs; Hydrodynamic cavitation; Ozonation; PMMoV; SARS-CoV-2; Sewage water treatment

Comparison of the solid-state and submerged fermentation derived secretomes of hyper-cellulolytic Penicillium janthinellum NCIM 1366 reveals the changes responsible for differences in hydrolytic performance - Sankar, Meena; Mathew, Reshma M.; Puthiyamadam, Anoop; Sreeja-Raju, Athiraraj; Christopher, Meera; Gokhale, Digambar Vitthal; Sukumaran, Rajeev K. (Bioresource Technology, 2023)
better hydrolytic performance along with a higher initial rate of reaction. Secretome analyses of the SSF and SmF enzymes using LC/MS-MS, indicated that while the type of proteins secreted were similar in both modes, the abundance of specific beta glucosidases, lytic polysaccharide monooxygenases and hemicellulolytic enzymes were very high in SSF resulting in efficient initiation, low accumulation of cellobiose and high initial reaction rates. Key enzymes that catalyse lignocellulose breakdown under SSF and SmF are therefore different and the fungus may be speculated to have regulation mechanisms that aid differential expression under different culti
Keywords: Cellulase; Solid -state fermentation

On the competition between six-membered and five-membered NHC towards alane centered ring expansion - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Ravindranathan, Sapna; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The combination of 6-SIDipp center dot AlH3 (1) and 5-IDipp resulted in the ring expansion of 6-NHC, while the five-membered NHC remained unchanged, which was subsequently explained by DFT studies. Besides, the substitution chemistry of 1 was also studied with TMSOTf and I-2, which gave rise to the substitution of a hydride by triflate or iodide ligands.

Composites of HKUST-1@nanocellulose for gas-separation and dye-sorption applications - Muhamed, Shamna; Sunny, Blesson; Kunjattu, Shebeeb H.; Alagarsamy, Thirumurugan (CHEMISTRY-A EUROPEAN JOURNAL, 2023)
In this study, composites of HKUST-1 MOF with nanocellulose, HKUST-1@NCs, have been prepared and explored for CO2/N-2 gas-separation and dye-sorption based applications. Our biopolymer-MOF composites are prepared via a copper ion pre-seeding method, in which, the HKUST-1 crystallites are grown in situ on the Cu-seeded and carboxylate anchored NC fibers for a better interfacial integration between the MOF and the polymer matrices. Static gas sorption studies show the capability of one of our HKUST-1@NC composites to reach similar to 300 % enhancement in the CO2/N-2 sorption selectivity compared to the corresponding MOF alone - blank reference sample prepared at similar conditions. The same composite, C100, in the bulk powder form, shows a remarkable IAST sorption selectivity of 298 (CO2/N-2) at 298 K and 1 bar for the CO2/N-2 (15/85, v/v) gas mixture. The relative position of the C100, in the bound plot visualizations of the CO2/N-2 separation trade-off factors indicate a significant potential. The HKUST-1@NC composites have also been processed along with a polymeric cellulose acetate (CA) matrix as HKUST-1@NC@CA films to study them as free-standing mixed-matrix membranes. The CO2/N-2 sorption selectivity, at 298 K and 1 bar is 600 for one such membrane, C-120@CA, as bulk sample studied by the static gas sorption. The composite, C120, exhibits a good uptake with an enhancement of 11 % for alizarin and 70 % for Congo red in comparison to the uptakes of the corresponding blank reference HKUST-1 sample, B120.
Keywords: CO2 separation; dye sorption; MOFs; nanocellulose composites; sustainable polymers

Comprehensive analysis of physiological and metabolomic responses to drought reveals specific modulation of acquired tolerance mechanisms in rice - Doddaraju, Pushpa; Dharmappa, Prathibha M.; Thiagarayaselvam, Aarthy; Vijayaraghavareddy, Preethi; Bheemanahalli, Raju; Basavaraddi, Priyanka A.; Malagondanahalli, Mohan Kumar V.; Kambalimath, Sumanth; Thulasiram, Hirekodathakallu V.; Sreeman, Sheshshayee M. (Physiologia Plantarum, 2023)
Mild stresses induce ``acquired tolerance traits'' (ATTs) that provide tolerance when stress becomes severe. Here, we identified the genetic variability in ATTs among a panel of rice germplasm accessions and demonstrated their relevance in protecting growth and productivity under water-limited conditions. Diverse approaches, including physiological screens, association mapping and metabolomics, were adopted and revealed 43 significant marker-trait associations. Nontargeted metabolomic profiling of contrasting genotypes revealed 26 ``tolerance-related-induced'' primary and secondary metabolites in the tolerant genotypes (AC-39000 and AC-39020) compared to the susceptible one (BPT-5204) under water-limited condition. Metabolites that help maintain cellular functions, especially Calvin cycle processes, significantly accumulated more in tolerant genotypes, which resulted in superior photosynthetic capacity and hence water use efficiency. Upregulation of the glutathione cycle intermediates explains the ROS homeostasis among the tolerant genotypes, maintaining spikelet fertility, and grain yield under stress. Bioinformatic dissection of a major effect quantitative trait locus on chromosome 8 revealed genes controlling metabolic pathways leading to the production of osmolites and antioxidants, such as GABA and raffinose. The study also led to the identification of specific trait donor genotypes that can be effectively used in translational crop improvement activities.

Comprehensive molecular and clinical investigation of approved Anti-HCV drugs repurposing against SARS-CoV-2 infection: a glaring gap between benchside and bedside medicine - Bansode, Sneha; Singh, Pawan Kumar; Tellis, Meenakshi; Chugh, Anita; Deshmukh, Narendra; Gupta, Mahesh; Verma, Savita; Giri, Ashok; Kulkarni, Mahesh; Joshi, Rakesh; Chaudhary, Dhruva (Vaccines, 2023)
The limited availability of effective treatment against SARS-CoV-2 infection is a major challenge in managing COVID-19. This scenario has augmented the need for repurposing anti-virals for COVID-19 mitigation. In this report, the anti-SARS-CoV-2 potential of anti-HCV drugs such as daclatasvir (DCV) or ledipasvir (LDP) in combination with sofosbuvir (SOF) was evaluated. The binding mode and higher affinity of these molecules with RNA-dependent-RNA-polymerase of SARS-CoV-2 were apparent by computational analysis. In vitro anti-SARS-CoV-2 activity depicted that SOF/DCV and SOF/LDP combination has IC50 of 1.8 and 2.0 mu M, respectively, comparable to remdesivir, an approved drug for COVID-19. Furthermore, the clinical trial was conducted in 183 mild COVID-19 patients for 14 days to check the efficacy and safety of SOF/DCV and SOF/LDP compared to standard of care (SOC) in a parallel-group, hybrid, individually randomized, controlled clinical study. The primary outcomes of the study suggested no significant difference in negativity after 3, 7 and 14 days in both treatments. None of the patients displayed any worsening in the disease severity, and no mortality was observed in the study. Although, the post hoc exploratory analysis indicated significant normalization of the pulse rate showed in SOF/DCV and SOF/LDP treatment vs. SOC. The current study highlights the limitations of bench side models in predicting the clinical efficacy of drugs that are planned for repurposing.
Keywords: antiviral; COVID-19; daclatasvir; ledipasvir; SARS-CoV-2; sofosbuvir

Computational insights into the iron-catalyze d magnesium-me diate d hydroformylation of alkynes - Sharma, Himanshu; Tewari, Tanuja; Chikkali, Samir H.; Vanka, Kumar (Journal of Organometallic Chemistry, 2023)
Iron is one of the most abundant transition metals in the earth's crust. It has attracted a lot of attention due to its low toxicity, bio-compatibility, and high natural abundance. Iron-catalyzed hydroamination, hydroalkoxylation, hydrocarboxylation, hydrosilylation, hydroboration, hydrophosphination, hydromagnesiation, and carbonylation reactions have therefore been developed over the past decades. However, despite many experimental and theoretical studies, a complete mechanistic understanding of iron-catalyzed hydrofunctionalisation at the molecular level has not yet been achieved. In this work, through density functional theory (DFT) calculations, we have shown the most feasible path for the hydroformylation of alkynes for an experimentally studied system. We have looked at the iron salt as a precatalyst without any external donor ligand, and the calculations revealed that hydrometalation followed by beta-hydride elimination was favorable over the direct migration of the beta-hydrogen to carbon. Furthermore, our calculations show that the solvent plays an important role in the hydromagnesiation reaction. Furthermore, we have employed an explicit solvent model, where the attachment of one molecule of solvent to the iron center was seen to stabilize the transition states significantly.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Computational study; Ethylene Assisted Catalysis; EtMgBr Assistance; Explicit Role of Solvent; Hydroformylation; Iron Catalyst

Concise approach for the synthesis of the tetracyclic framework of Lycibarbarines A and B - Shet, Manoj N.; Nechooli, Hemanth K.; Ramana, Chepuri V. (Tetrahedron Letters, 2023)
A simple approach for the construction of the tetracyclic spiroketal skeleton of Lycibarbarine A and B has been described. Employing a solvent free condition for epoxide opening with tetrahydroquinoline as a key reaction to couple both the fragments, an oxidation followed by TBAF-mediated silyl deprotection spiroketalization establishes the complete tetracyclic core present in these natural products. (c) 2023 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool approach; D -Glyceraldehyde; Tetracyclic spiroketal; Total synthesis

Construction of the quinobenzoxazine core via gold-catalyzed dual annulation of azide-tethered alkynones with anthranils - Halnor, Swapnil V. V.; Dhote, Pawan S. S.; Ramana, Chepuri V. V. (Organic & Biomolecular Chemistry, 2023)
A new catalytic method for the construction of the quinobenzoxazine core has been developed employing the gold-catalyzed cyclization of o-azidoacetylenic ketones in the presence of anthranils. The overall process comprises of a gold-catalyzed 6-endo-dig cyclisation of o-azidoacetylenic ketone leading to a alpha-imino gold carbene and subsequent carbene transfer to anthranil leading to the 3-aryl-imino-quinoline-4-one intermediate, which undergoes 6 pi-electrocyclization and aromatization to form the central quinobenzoxazine core. This transformation provides a new approach to a diverse array of quinobenzoxazine structures, in addition to being scalable and having mild reaction conditions.

Continuous hydrogenation of cinnamaldehyde: gas-liquid-liquid-solid helical coil reactor - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2023)
The advantages and challenges of using the gas-liquid-liquid-solid(GLLS) hydrogenation system are discussed in this work using the caseof selective hydrogenation of cinnamaldehyde to cinnamyl alcohol (animportant ingredient in the perfume and flavoring industry). The fourphases in this system include gas (hydrogen)-liquid (organic, reactant+ solvent)-liquid (aqueous KOH)-solid (5% Pt/C catalyst). The additionof second liquid phase, i.e., aqueous KOH significantly increasesselectivity toward cinnamyl alcohol compared to the conventional three-phasehydrogenation. The four-phase GLLS reactions were carried out andoptimized in a continuous helical coil reactor. The role of key aspectssuch as gas solubility, kinetics, flow hydrodynamics, axial dispersion,and mass transfer on the performance of a continuous GLLS reactoris presented and discussed in this work. The presented results anddiscussion will be useful for addressing conflicting demands likelong residence time, low axial dispersion, and high mass transfer.The experimental studies and results of the developed mathematicalmodel indicate that the continuous GLLS helical coil reactor outperformsthe batch operation. The production rates (kg day(-1)) of cinnamyl alcohol achieved in continuous operation were at leastdouble in comparison to batch operation, with 32% less consumptionof precious catalyst (per kg of product). The presented results will open up new opportunities for enhancing selectivity and overall performanceof hydrogenations via introducing a second immiscible liquid phaseand designing continuous tubular reactors for the same.

Controlled reduction of isocyanates to formamides using monomeric magnesium - Kumar, Rohit; Sharma, Vishal; Banerjee, Subhrashis; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2023)
This work describes a transition metal-free methodology involving an efficient and controlled reduction of isocyanates to only formamide derivatives using pinacolborane (HBpin) as the hydrogenating agent and a bis(phosphino)carbazole ligand stabilized magnesium methyl complex (1) as the catalyst. A large number of substrates undergo selective hydroboration and give exclusively N-boryl formamides.

Controlled synthesis of thermosensitive tunable porous film of (pNIPAM)-b-(PCL) copolymer for sustain drug delivery - Amgoth, Chander; Patra, Sukanya; Wasnik, Kirti; Maity, Pradip; Paik, Pradip (Journal of Applied Polymer Science, 2023)
There have been reports on different types of porous polymer films for various applications. The designing of such porous films with uniform properties is a challenging task. In this work, tunable porous thin films of poly(N-isopropylacrylamide) (pNIPAM) and polycaprolactone (PCL), that is, (pNIPAM)-b-(PCL) has been fabricated and its sustained drug delivery applications have been reported. First, the (pNIPAM)-b-(PCL) has been synthesized through the addition polymerization of pNIPAM and PCL. Then the synthesized (pNIPAM)-b(PCL) has been used to design porous thin film with varying temperatures without using any external template, below and above the lower critical solution temperatures (LCST) of pNIPAM. Pore size in (pNIPAM)-b-(PCL) films has been tuned by varying the temperature from similar to 10 to 40 degrees C. Then the developed thermosensitive porous film has been taken and seeded with the K562 (chronic myeloid leukemia blood cancer) and HepG2 (hepatocarcinoma) cells and the skin cancer cells (B16-F10) killing efficiency of anticancer drug (e.g., doxorubicin hydrochloride, DOX) loaded (pNIPAM)-b-(PCL) film has been studied. It is found that the DOX-loaded (pNIPAM)-b-(PCL) can efficiently kill the skin cancer cells. The porous polymer thin film reported in this work can be a versatile platform for the loading of drugs and it can be used for the various therapeutic applications.
Keywords: Biomaterials; Biomedical Applications; drug delivery systems; films; nanostructured polymers

Conversion of benzyl phenyl ether to monoaromatics in high-temperature aqueous ethanol solution under high-pressure carbon dioxide conditions - Taniguchi, Kenkichi; Kusumawati, Etty N.; Nanao, Hidetaka; Rode, Chandrashekhar V.; Sato, Osamu; Yamaguchi, Aritomo; Shirai, Masayuki (New Journal of Chemistry, 2023)
Solvolysis of benzyl phenyl ether (BPE), which is a model compound of lignin ether linkage, was studied in an aqueous ethanol solution, which can be obtained from bioethanol, under high-pressure carbon dioxide conditions. A batch study revealed that BPE solvolysis to monoaromatics (benzyl ethyl ether (BEE), benzyl alcohol (BA), and phenol (Ph)) proceeded in aqueous ethanol solution over 523 K and the addition of high-pressure carbon dioxide enhanced the initial solvolysis rate and suppressed the side reaction (hydrogenolysis to toluene (TL)). The ethanol molar fraction (ethanol-water volume ratio) is the key factor for the solvolysis reaction, and the highest monoaromatic yield of 72.9% (BEE 10.7%, BA 19.3%, Ph 37.9%, and TL 5.1%) was obtained in aqueous ethanol solution (2 cm(3) : 1 cm(3) = water:ethanol) at 598 K for 3 h under a pressure of 18 MPa of carbon dioxide. The solvolysis reaction proceeded continuously to produce monoaromatics with a flow system. A monoaromatic yield of 76.7% (BEE 8.6%, BA 19.7%, Ph 39.6%, and TL 8.9%) was obtained, and the formation rates were 2.7 x 10(-4) mmol min(-1) for BEE, 6.2 x 10(-4) mmol min(-1) for BA, and 12.4 x 10(-4) mmol min(-1) for Ph at 598 K under flowing water (26 mmol min(-1)), ethanol solution (4.1 mmol min(-1)), carbon dioxide (1.2 mmol min(-1)), and BPE (15.6 x 10(-4) mmol min(-1)) under a total pressure of 40 MPa.

Covalent organic framework cladding on peptide-amphiphile-based biomimetic catalysts - Kumar Mahato, Ashok; Pal, Sumit; Dey, Kaushik; Reja, Antara; Paul, Satyadip; Shelke, Ankita; Ajithkumar, Thalasseril G.; Das, Dibyendu; Banerjee, Rahul (Journal of the American Chemical Society, 2023)
Peptide-based biomimetic catalysts are promising materialsforefficient catalytic activity in various biochemical transformations.However, their lack of operational stability and fragile nature innon-aqueous media limit their practical applications. In this study,we have developed a cladding technique to stabilize biomimetic catalystswithin porous covalent organic framework (COF) scaffolds. This methodologyallows for the homogeneous distribution of peptide nanotubes insidethe COF (TpAzo and TpDPP) backbone, creating strong noncovalent interactionsthat prevent leaching. We synthesized two different peptide-amphiphiles,C10FFVK and C10FFVR, with lysine (K) and arginine(R) at the C-termini, respectively, which formed nanotubular morphologies.The C10FFVK peptide-amphiphile nanotubes exhibit enzyme-likebehavior and efficiently catalyze C-C bond cleavage in a buffermedium (pH 7.5). We produced nanotubular structures of TpAzo-C10FFVK and TpDPP-C10FFVK through COF claddingby using interfacial crystallization (IC). The peptide nanotubes encasedin the COF catalyze C-C bond cleavage in a buffer medium aswell as in different organic solvents (such as acetonitrile, acetone,and dichloromethane). The TpAzo-C10FFVK catalyst,being heterogeneous, is easily recoverable, enabling the reactionto be performed for multiple cycles. Additionally, the synthesis ofTpAzo-C10FFVK thin films facilitates catalysis inflow. As control, we synthesized another peptide-amphiphile, C10FFVR, which also forms tubular assemblies. By depositingTpAzo COF crystallites on C10FFVR nanotubes through IC,we produced TpAzo-C10FFVR nanotubular structuresthat expectedly did not show catalysis, suggesting the critical roleof the lysines in the TpAzo-C10FFVK.

Covalent organic framework thin-film photodetectors from solution-processable porous nanospheres - Bag, Saikat; Sasmal, Himadri Sekhar; Chaudhary, Sonu Pratap; Dey, Kaushik; Blaette, Dominic; Guntermann, Roman; Zhang, Yingying; Poloz, Miroslav; Kuc, Agnieszka; Shelke, Ankita; Vijayaraghavan, Ratheesh K.; Ajithkumar, Thalasseril G.; et al. (Journal of the American Chemical Society, 2023)
The synthesis of homogeneous covalent organic framework (COF) thin films on a desired substrate with decent crystallinity, porosity, and uniform thickness has great potential for optoelectronic applications. We have used a solution-processable sphere transmutation process to synthesize 300 +/- 20 nm uniform COF thin films on a 2 x 2 cm2 TiO2-coated fluorine-doped tin oxide (FTO) surface. This process controls the nucleation of COF crystallites and molecular morphology that helps the nanospheres to arrange periodically to form homogeneous COF thin films. We have synthesized four COF thin films (TpDPP, TpEtBt, TpTab, and TpTta) with different functional backbones. In a close agreement between the experiment and density functional theory, the TpEtBr COF film showed the lowest optical band gap (2.26 eV) and highest excited-state lifetime (8.52 ns) among all four COF films. Hence, the TpEtBr COF film can participate in efficient charge generation and separation. We constructed optoelectronic devices having a glass/FTO/TiO2/COF-film/Au architecture, which serves as a model system to study the optoelectronic charge transport properties of COF thin films under dark and illuminated conditions. Visible light with a calibrated intensity of 100 mW cm-2 was used for the excitation of COF thin films. All of the COF thin films exhibit significant photocurrent after illumination with visible light in comparison to the dark. Hence, all of the COF films behave as good photoactive substrates with minimal pinhole defects. The fabricated out-of-plane photodetector device based on the TpEtBr COF thin film exhibits high photocurrent density (2.65 +/- 0.24 mA cm-2 at 0.5 V) and hole mobility (8.15 +/- 0.64 x10-3 cm2 V-1 S-1) compared to other as synthesized films, indicating the best photoactive characteristics.

Covalently interconnected layers in g-C3N4: toward high mechanical stability, catalytic efficiency and sustainability - Roy, Raj Sekhar; Mondal, Sanjit; Mishra, Samita; Banoo, Maqsuma; Sahoo, Lipipuspa; Kumar, Amit; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Applied Catalysis B: Environmental, 2023)
The grim prospects for the industrial utilization of g-C3N4 nanosheets arise from multi-step processing resulting in low material yields and poor visible light response due to quantum confinement. Herein, we introduce a strategy for linking the adjacent layers of g-C3N4 covalently to realize a high surface area without excess mass loss in a one-step process by introducing diethylene glycol as a precursor that produces-(CH2)2-O-(CH2)2-linkers in-situ. Their presence increases interlayer spacing and introduces surface curvatures, discouraging the stacking of a larger number of layers to produce nanosheets with-3 times higher surface area. Interestingly, unlike other layered materials, the linkers also provide extraordinary mechanical stability against exfoliating forces. In addition, the process instills sub-bandgap states and a considerable visible light response at 500 nm to slow down the picosecond exciton recombination dynamics, resulting in-5 times enhancement in H2 generation efficiency from photocatalytic water-splitting over the bulk sample.
Keywords: Layer-linkers; Sustainable synthesis; Transient absorption spectroscopy; water-splitting

Chemodialysis of organic acids using ABPBI-based hollow fiber membranes - Gawas, Saroj; Alladi, Lavanya; Kharul, Ulhas K. (Journal of Membrane Science, 2024)
Organic acids are a class of essential commodity chemicals used in various industries. Their production methods are shifting from conventional chemicals to fermentation, driven by green process strategies, environmental regulations, cost feasibility, etc. Separating formed acid from the fermentation broth is a primary technological barrier. Conventional methods are complex and impose environmental issues. A promising approach, `Chemodialysis,' capable of transforming the techno-economical feasibility of acid recovery scenario by reducing the number of steps, needs further investigation. This work evaluates scalable hollow fiber membranes based on poly(2,5-benzimidazole) (ABPBI) for chemically assisted dialysis, viz., Chemodialysis. Sorption analyses of commercially significant organic acids (acetic, lactic, and glycolic acid) and nonacidic solutes (NaCl and glucose) were performed using conventional flat sheet samples to assess their role in governing permeation characteristics. The transport properties of acids in the presence of NaCl and glucose as co-solutes were analyzed using hollow fiber membranes. The high selectivity of acid over nonacidic solutes ranges from 400-22,400, coupled with high acid permeability, enhances the applicability of Chemodialysis for the separation of acids using hollow fiber membranes. The fluxes of acids (acetic, glycolic, and lactic) through dense, similar to 100 mu m thick, scalable hollow fiber membranes ranging from 10.9 to 13.12 g/m(2)h are highly appreciable.
Keywords: 5-benzimidazole); Acid separation; Chemodialysis; Hollow fiber membranes; Organic acids; Poly(2